2-Stage and 3-stage restorative proctocolectomy with ileal pouch-anal anastomosis for ulcerative colitis show comparable short- and long-term outcomes - Brunner, Maximilian; Brandl, Martin; Denz, Axel; Krautz, Christian; Weber, Georg; Grützmann, Robert; Weber, Klaus (Scientific Reports, 2024)
Restorative proctocolectomy with ileal pouch-anal anastomosis (IPAA) represents the standard treatment for therapy-refractory, malignant or complicated ulcerative colitis (UC) and can be performed as a 2-stage or 3-stage procedure. This study aimed to compare the short- and long-term outcomes after 2- and 3-stage IPAA in patients with UC in our department. A retrospective analysis of 176 patients with UC who received 2- or 3-stage restorative proctocolectomy with IPAA at our institution from 2001 to 2021 was performed. Outcomes for short-term (morbidity, longer hospital stay, readmission) and long-term (pouch failure and quality of life) parameters were compared between the 2- and 3-stage procedure. Regarding short-term outcomes for all patients, in-hospital morbidity and readmission rates after any surgical stage were observed in 69% and 24%, respectively. Morbidity and readmission did not differ significantly between the 2- and 3-stage procedure in uni- and multivariate analysis. Median length of hospital stay for all stages was 17 days. The 3-stage procedure was identified as an independent factor for longer hospital stay (OR 3.8 (CI 1.3-10.8), p = 0.014). Pouch failure and failure of improved quality of life during long-term follow-up occurred both in 10% of patients, with no significant differences between the 2- and 3-stage procedure in uni- and multivariate analysis. Our data suggest that both the 2- and 3-stage proctocolectomy with IPAA demonstrate favourable and comparable postoperative short- and long-term outcomes, with a high rate of improved quality of life in patients with UC.
CRIS-Team Scopus Importer:2024-10-11
Keywords: Ileal pouch-anal anastomosis; Outcome; Pouch failure; Proctocolectomy; Ulcerative colitis

Absolute quantification of DcR3 and GDF15 from human serum by LC-ESI MS - Lancrajan, Ioana Maria; Schneider-Stock, Regine; Naschberger, Elisabeth; Schellerer, Vera; Stürzl, Michael; Enz, Ralf (Journal of Cellular and Molecular Medicine, 2015)
Biomarkers are widely used in clinical diagnosis, prognosis and therapy monitoring. Here, we developed a protocol for the efficient and selective enrichment of small and low concentrated biomarkers from human serum, involving a 95% effective depletion of high-abundant serum proteins by partial denaturation and enrichment of low-abundant biomarkers by size exclusion chromatography. The recovery of low-abundance biomarkers was above 97%. Using this protocol, we quantified the tumour markers DcR3 and growth/differentiation factor (GDF)15 from 100 ?l human serum by isotope dilution mass spectrometry, using (15) N metabolically labelled and concatamerized fingerprint peptides for the both proteins. Analysis of three different fingerprint peptides for each protein by liquid chromatography electrospray ionization mass spectrometry resulted in comparable concentrations in three healthy human serum samples (DcR3: 27.23 ± 2.49 fmol/ml; GDF15: 98.11 ± 0.49 fmol/ml). In contrast, serum levels were significantly elevated in tumour patients for DcR3 (116.94 ± 57.37 fmol/ml) and GDF15 (164.44 ± 79.31 fmol/ml). Obtained data were in good agreement with ELISA and qPCR measurements, as well as with literature data. In summary, our protocol allows the reliable quantification of biomarkers, shows a higher resolution at low biomarker concentrations than antibody-based strategies, and offers the possibility of multiplexing. Our proof-of-principle studies in patient sera encourage the future analysis of the prognostic value of DcR3 and GDF15 for colon cancer patients in larger patient cohorts.
EVALuna2:4708

A contemporary assessment of total neoadjuvant therapy (TNT) protocols for locally advanced rectal cancer: adoption and expert perspectives at German Cancer Society (DKG)-certified colorectal cancer centers - Langheinrich, Melanie; Paasch, Christoph; Mantke, René; Weber, Klaus; Benz, Stefan; Kersting, Stephan (Journal of Cancer Research and Clinical Oncology, 2023)
Purpose: The treatment paradigm for locally advanced rectal cancer (LARC) is shifting toward the total neoadjuvant therapy (TNT) concept, which administered systemic chemotherapy in the neoadjuvant setting, either before or after chemoradiotherapy (CRT) or short-course radiotherapy (SCRT). First results have shown higher pathologic complete response (pCR) rates and a favorable impact on disease-free survival (DFS). Our study aimed to evaluate the current clinical practice and expert opinion regarding TNT for locally advanced rectal cancer across DKG (German Cancer Society)-certified colorectal cancer centers. Methods: A comprehensive online questionnaire, constituted of 14 TNT-focused queries targeting patients with locally advanced rectal cancer, was conducted among DKG-certified colorectal cancer centers registered within the database of the Addz (Arbeitsgemeinschaft Deutscher Darmzentren) between December 2022 and January 2023. Results: A significant majority (68%) indicated that they treated between 0 and 10 patients using a TNT protocol. Only a third (36%) of these centers participated in patient enrollment for a TNT study. Despite this, 84% of centers reported treating patients in a manner analogous to a TNT study, with the RAPIDO regimen being the most prevalent approach, employed by 60% of the respondents. The decision to adopt a TNT approach was primarily influenced by factors, such as the lower third of the rectum (93% of centers), cT4 stage (86% of centers), and a positive circumferential resection margin (80% of centers). Regarding concerns, 65% of the survey respondents expressed no reservations about the TNT concept, while 35% had concerns. In particular, there appears to be disagreement and uncertainty in regard to a clinical complete response and the “Watch and Wait” approach. While some centers adopt the watch-and-wait approach (42%), others only utilize it when extirpation is otherwise necessary (39%), and a portion still proceeds with surgery as initially planned (19%). The survey also addressed unmet needs, which were elaborated in the free-text responses. Overall, there was high interest in participating in planned observational studies. Conclusions: This study presents an overview of current clinical practice and unmet needs within DKG-certified German colorectal cancer centers. It is noteworthy that total neoadjuvant therapy (TNT) is predominantly performed outside of clinical trials. Moreover, across the centers, there is significant heterogeneity in handling clinical complete response and adopting the “watch and wait” approach. Further research is needed to establish standardization in the care of locally advanced rectal cancer.
CRIS-Team Scopus Importer:2023-07-21
Keywords: DKG-certified colorectal cancer centers; Locally advanced rectal cancer; Rectal cancer; TNT; Total neoadjuvant therapy

Activation of liver X receptors inhibits experimental fibrosis by interfering with interleukin-6 release from macrophages - Beyer, Christian; Huang, Jingang; Beer, Juergen; Zhang, Yun; Palumbo-Zerr, Katrin; Zerr, Pawel; Distler, Alfiya; Dees, Clara; Maier, Christiane; Munoz, Louis; Krönke, Gerhard; Uderhardt, Stefan; et al. (Annals of the Rheumatic Diseases, 2015)
To investigate the role of liver X receptors (LXRs) in experimental skin fibrosis and evaluate their potential as novel antifibrotic targets.We studied the role of LXRs in bleomycin-induced skin fibrosis, in the model of sclerodermatous graft-versus-host disease (sclGvHD) and in tight skin-1 (Tsk-1) mice, reflecting different subtypes of fibrotic disease. We examined both LXR isoforms using LXR?-, LXR?- and LXR-?/?-double-knockout mice. Finally, we investigated the effects of LXRs on fibroblasts and macrophages to establish the antifibrotic mode of action of LXRs.LXR activation by the agonist T0901317 had antifibrotic effects in bleomycin-induced skin fibrosis, in the sclGvHD model and in Tsk-1 mice. The antifibrotic activity of LXRs was particularly prominent in the inflammation-driven bleomycin and sclGvHD models. LXR?-, LXR?- and LXR?/?-double-knockout mice showed a similar response to bleomycin as wildtype animals. Low levels of the LXR target gene ABCA-1 in the skin of bleomycin-challenged and control mice suggested a low baseline activation of the antifibrotic LXR signalling, which, however, could be specifically activated by T0901317. Fibroblasts were not the direct target cells of LXRs agonists, but LXR activation inhibited fibrosis by interfering with infiltration of macrophages and their release of the pro-fibrotic interleukin-6.We identified LXRs as novel targets for antifibrotic therapies, a yet unknown aspect of these nuclear receptors. Our data suggest that LXR activation might be particularly effective in patients with inflammatory disease subtypes. Activation of LXRs interfered with the release of interleukin-6 from macrophages and, thus, inhibited fibroblast activation and collagen release.
EVALuna2:12871

Activation of matrix-metalloproteinase-2 and membrane-type-1-matrix-metalloproteinase in endothelial cells and induction of vascular permeability in vivo by human immunodeficiency virus-1 Tat protein and basic fibroblast growth factor. - Tosch, Elena; Barillari, Giovanni; Sgadari, Cecilia; Bacigalupo, Ilaria; Cereseto, Anna; Carlei, Davide; Palladino, Clelia; Zietz, Christian; Leone, Patrizia; Stürzl, Michael; Buttò, Stefano; Cafaro, Aurelio; et al. (Molecular Biology of the Cell, 2001)
Previous studies indicated that the Tat protein of human immunodeficiency virus type-1 (HIV-1) is a progression factor for Kaposi's sarcoma (KS). Specifically, extracellular Tat cooperates with basic fibroblast growth factor (bFGF) in promoting KS and endothelial cell growth and locomotion and in inducing KS-like lesions in vivo. Here we show that Tat and bFGF combined increase matrix-metalloproteinase-2 (MMP-2) secretion and activation in endothelial cells in an additive/synergistic manner. These effects are due to the activation of the membrane-type-1-matrix-metalloproteinase and to the induction of the membrane-bound tissue inhibitor of metalloproteinase-2 (TIMP-2) by Tat and bFGF combined, but also to Tat-mediated inhibition of both basal or bFGF-induced TIMP-1 and -2 secretion. Consistent with this, Tat and bFGF promote vascular permeability and edema in vivo that are blocked by a synthetic MMP inhibitor. Finally, high MMP-2 expression is detected in acquired immunodeficiency virus syndrome (AIDS)-KS lesions, and increased levels of MMP-2 are found in plasma from patients with AIDS-KS compared with HIV-uninfected individuals with classic KS, indicating that these mechanisms are operative in AIDS-KS. This suggests a novel pathway by which Tat can increase KS aggressiveness or induce vasculopathy in the setting of HIV-1 infection.

Activation of NF-κB by the Kaposi's sarcoma-associated herpesvirus K15 protein involves recruitment of the NF-κB-inducing kinase, IκB kinases, and phosphorylation of p65. - Havemeier, Anika; Gramolelli, Silvia; Pietrek, Marcel; Jochmann, Ramona; Stürzl, Michael; Schulz, Thomas F. (Journal of Virology, 2014)
Kaposi's sarcoma herpesvirus (KSHV) (or human herpesvirus 8) is the cause of Kaposi's sarcoma, primary effusion lymphoma (PEL), and the plasma cell variant of multicentric Castleman's disease (MCD). The transmembrane K15 protein, encoded by KSHV, has been shown to activate NF-κB and the mitogen-activated protein kinases (MAPKs) c-jun-N-terminal kinase (JNK) and extracellular signal-regulated kinase (Erk) as well as phospholipase C gamma (PLCγ) and to contribute to KSHV-induced angiogenesis. Here we investigate how the K15 protein activates the NF-κB pathway. We show that activation of NF-κB involves the recruitment of NF-κB-inducing kinase (NIK) and IKK α/β to result in the phosphorylation of p65/RelA on Ser536. A K15 mutant devoid in NIK/IKK recruitment fails to activate NF-κB but remains proficient in the stimulation of both NFAT- and AP1-dependent promoters, showing that the structural integrity of the mutant K15 protein has not been altered dramatically. Direct recruitment of NIK represents a novel way for a viral protein to activate and manipulate the NF-κB pathway. KSHV K15 is a viral protein involved in the activation of proinflammatory and angiogenic pathways. Previous studies reported that K15 can activate the NF-κB pathway. Here we show the molecular mechanism underlying the activation of this signaling pathway by K15, which involves direct recruitment of the NF-κB-inducing kinase NIK to K15 as well as NIK-mediated NF-κB p65 phosphorylation on Ser536. K15 is the first viral protein shown to activate NF-κB through direct recruitment of NIK. These results indicate a new mechanism whereby a viral protein can manipulate the NF-κB pathway. UNLABELLED IMPORTANCE
EVALuna2:15180

Acyltransferase skinny hedgehog regulates TGFβ-dependent fibroblast activation in SSc - Liang, Ruifang; Kagwiria, Rosebeth; Zehender, Ariella; Dees, Clara; Bergmann, Christina; Krasowska, Dorota; Michalska-Jakubus, Małgorzata; Kreuter, Alexander; Kraner, Max; Schett, Georg; Distler, Jörg; Ramming, Andreas (Annals of the Rheumatic Diseases, 2019)
Objectives: Systemic sclerosis (SSc) is characterised by aberrant hedgehog signalling in fibrotic tissues. The hedgehog acyltransferase (HHAT) skinny hedgehog catalyses the attachment of palmitate onto sonic hedgehog (SHH). Palmitoylation of SHH is required for multimerisation of SHH proteins, which is thought to promote long-range, endocrine hedgehog signalling. The aim of this study was to evaluate the role of HHAT in the pathogenesis of SSc. Methods: Expression of HHAT was analysed by real-time polymerase chain reaction(RT-PCR), immunofluorescence and histomorphometry. The effects of HHAT knockdown were analysed by reporter assays, target gene studies and quantification of collagen release and myofibroblast differentiation in cultured human fibroblasts and in two mouse models. Results: The expression of HHAT was upregulated in dermal fibroblasts of patients with SSc in a transforming growth factor-β (TGFβ)/SMAD-dependent manner. Knockdown of HHAT reduced TGFβ-induced hedgehog signalling as well as myofibroblast differentiation and collagen release in human dermal fibroblasts. Knockdown of HHAT in the skin of mice ameliorated bleomycin-induced and topoisomerase-induced skin fibrosis. Conclusion: HHAT is regulated in SSc in a TGFβ-dependent manner and in turn stimulates TGFβ-induced long-range hedgehog signalling to promote fibroblast activation and tissue fibrosis. Targeting of HHAT might be a novel approach to more selectively interfere with the profibrotic effects of long-range hedgehog signalling.
CRIS-Team Scopus Importer:2019-06-21
Keywords: dermal fibrosis; hedgehog signaling; skinny hedgehog; systemic sclerosis; TGFβ

A European snapshot of psychosocial characteristics and patients’ perspectives of faecal incontinence—do they correlate with current scoring systems? - Creamer, Felicity; Orlando, Alessandra; Brunner, Maximilian; Buntzen, Steen; Dennis, Alexander; Gómez-Fernández, Laura; Handtrack, Claudia; Hanly, Ann; Matzel, Klaus E.; Duyos, Arantxa Muñoz; Meurette, Guillaume; O’Connell, P. Ronan; et al. (International Journal of Colorectal Disease, 2021)
Purpose: To compare the current clinical scoring systems used to quantify the severity of symptoms of faecal incontinence (FI) to patients’ subjective scoring of parameters of psychosocial well-being. Methods: Patients referred to six European centres for investigation or treatment of symptoms of FI between June 2017 and September 2019 completed a questionnaire that captured patient demographics, incontinence symptoms using St. Mark’s Incontinence score (SMIS) and ICIQ-B, psychological well-being (HADS, Hospital Anxiety and Depression Scale), and social interaction (a three-item loneliness scale). Results: Three hundred eighteen patients completed questionnaires (62 men, mean age 58.7). Sixty percent of the respondents were aged under 65. Median SMIS was 15 (11–18), ICIQ-B bowel pattern was 8 (6–11) and bowel control was 17 (13–22), similar across all demographic groups; however, younger patients were more likely to experience symptoms of depression and anxiety (HADS score > 10, 65.2% of patients age < 65 vs 54.9% of those ages > = 65, p = 0.03) with lower quality of life (ICIQ-B QoL, median score 19 (14–23)) vs age > = 65 (16 (11–21) (p < 0.005)). On loneliness score 25.5% reported often feeling isolated from others. One of the most significant concerns by patients was the fear and embarrassment related to unpredictable episodes of incontinence. Conclusion: The SMIS remains a useful tool for quantifying incontinence symptoms but may underestimate the psychosocial morbidity associated with unpredictable episodes of incontinence. Interventions aimed at decreasing anxiety and to address feelings of disgust may be helpful for a significant number of patients requiring treatment for FI.
CRIS-Team Scopus Importer:2021-01-22
Keywords: Anxiety; Faecal incontinence; Psychosocial; Score

Alpha interferon inhibits human herpesvirus 8 (HHV-8) reactivation in primary effusion lymphoma cells and reduces HHV-8 load in cultured peripheral blood mononuclear cells. - Monini, Paolo; Carlini, Francesca; Stürzl, Michael; Rimessi, Paola; Superti, Fabiana; Franco, Marina; Melucci-Vigo, Gianna; Cafaro, Aurelio; Goletti, Delia; Sgadari, Cecilia; Buttò, Stefano; Leone, Patrizia; et al. (Journal of Virology, 1999)
Infection by human herpesvirus 8 (HHV-8) is associated with the development of Kaposi's sarcoma (KS). Since regression of KS can be achieved by treatment of the patients with alpha interferon (IFN-alpha), we analyzed the effects of IFN-alpha or anti-IFN-alpha antibodies (Ab) on HHV-8 latently infected primary effusion lymphoma-derived cell lines (BCBL-1 and BC-1) and on peripheral blood mononuclear cells (PBMC) from patients with all forms of KS and from at-risk subjects. IFN-alpha inhibited in a dose-dependent manner the amplification of HHV-8 DNA in BCBL-1 cells induced to lytic infection with tetradecanoyl phorbol acetate (TPA). This effect was associated with the inhibition of the expression of HHV-8 nut-1 and kaposin genes that are induced early and several hours, respectively, after TPA treatment. In addition, IFN-alpha inhibited virus production and/or release from BCBL-1 cells. Inhibition of nut-1 and kaposin genes by IFN-alpha was also observed in BC-1 cells induced with n-butyrate. Conversely, the addition of anti-IFN-alpha Ab to TPA-induced BCBL-1 cells resulted in a larger number of mature enveloped particles and in a more extensive cytopathic effect due to the neutralization of the endogenous IFN produced by these cells. IFN was also produced by cultured PBMC from HHV-8-infected individuals, and this was associated with a loss of viral DNA during culture. However, the addition of anti-IFN-alpha Ab or anti-type I IFN receptor Ab promoted the maintenance of HHV-8 DNA in these cells that was associated with the detection of the latency-associated kaposin RNA. Finally, the addition of IFN-alpha reduced the HHV-8 load in PBMC. Thus, IFN-alpha appears to have inhibitory effects on HHV-8 persistent infection of PBMC. These results suggest that, in addition to inhibiting the expression of angiogenic factors that are key to KS development, IFN-alpha may induce KS regression by reducing the HHV-8 load and/or inhibiting virus reactivation.

Altered Diversity and Composition of the Microbiome in Patients with Primary Untreated Colorectal Cancer - Langheinrich, Melanie; Wirtz, Stefan; Weber, Klaus; Grützmann, Robert; Kersting, Stephan (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-03-20

A microfluidic-based PDAC organoid system reveals the impact of hypoxia in response to treatment - Geyer, Marlene; Schreyer, Daniel; Gaul, Lisa Marie; Pfeffer, Sina; Pilarsky, Christian; Queiroz, Karla (Cell Death Discovery, 2023)
Pancreatic Ductal Adenocarcinoma (PDAC) is estimated to become the second leading cause of cancer-related deaths by 2030 with mortality rates of up to 93%. Standard of care chemotherapeutic treatment only prolongs the survival of patients for a short timeframe. Therefore, it is important to understand events driving treatment failure in PDAC as well as identify potential more effective treatment opportunities. PDAC is characterized by a high-density stroma, high interstitial pressure and very low oxygen tension. The aim of this study was to establish a PDAC platform that supported the understanding of treatment response of PDAC organoids in mono-, and co-culture with pancreatic stellate cells (PSCs) under hypoxic and normoxic conditions. Cultures were exposed to Gemcitabine in combination with molecules targeting relevant molecular programs that could explain treatment specific responses under different oxygen pressure conditions. Two groups of treatment responses were identified, showing either a better effect in monoculture or co-culture. Moreover, treatment response also differed between normoxia and hypoxia. Modulation of response to Gemcitabine was also observed in presence of a Hypoxia-inducible factor (HIF) prolyl hydroxylase (PHD) inhibitor and HIF inhibitors. Altogether this highlights the importance of adjusting experimental conditions to include relevant oxygen levels in drug response studies in PDAC.
CRIS-Team Scopus Importer:2023-02-03

AMIGO2 characterizes cancer-associated fibroblasts in metastatic colon cancer and induces the release of paracrine active tumorigenic secretomes - Yong, Yong-song; Demmler, Richard; Zohud, Bisan; Fang, Qi; Zhang, Tong; Zhou, Yonghua; Petter, Katja; Flierl, Christian; Gass, Tobias; Geppert, Carol-Immanuel; Merkel, Susanne; Schellerer, Vera; et al. (Journal of Pathology, 2024)
Secretomes of cancer-associated fibroblasts (CAFs) in colorectal cancer (CRC) contribute to malignancy. Detailed knowledge is available on the components and functions of CAF secretomes. Little is known about the regulation of CAF secretomes. Here, we searched for receptor-like membrane-bound molecules in CAFs, which may regulate the production and release of tumor-activating secretomes. The adhesion molecule with Ig-like domain 2 (AMIGO2) was significantly upregulated in cultivated CAFs compared to normal tissue-associated fibroblasts (NAFs), and this was confirmed in patient-derived tissues. AMIGO2 expression was low or absent in healthy colon, significantly increased in fibroblasts of primary CRC, and highest in the stromal tissues of CRC-derived liver metastases. AMIGO2 expression in CAFs correlated with a higher T-category, increased lymph node metastasis, progressed tumor stages and was associated with reduced survival in different cohorts of CRC patients. Interestingly, AMIGO2 expression was induced by transforming growth factor-β and higher in female patients, who exhibit a more aggressive disease course. In functional studies, conditioned media of NAFs with experimentally induced AMIGO2 overexpression enhanced proliferation and migration of different CRC tumor cells, while siRNA-mediated inhibition of AMIGO2 in CAFs attenuated these effects. Accordingly, therapeutic inhibition of the receptor-like AMIGO2 protein in CRC CAFs could prevent tumorigenic secretomes in CRC. © 2024 The Author(s). The Journal of Pathology published by John Wiley & Sons Ltd on behalf of The Pathological Society of Great Britain and Ireland.
CRIS-Team Scopus Importer:2024-11-22
Keywords: cancer-associated fibroblasts; colorectal cancer; secretion; secretomes; tumor microenvironment

Ampullary Cancers Harbor ELF3 Tumor Suppressor Gene Mutations and Exhibit Frequent WNT Dysregulation - Gingras, Marie-Claude; Covington, Kyle R.; Chang, David K.; Donehower, Lawrence A.; Gill, Anthony J.; Ittmann, Michael M.; Creighton, Chad J.; Johns, Amber L.; Shinbrot, Eve; Dewal, Ninad; Fisher, William E.; Pilarsky, Christian; et al. (Cell Reports, 2016)
The ampulla of Vater is a complex cellular environment from which adenocarcinomas arise to form a group of histopathologically heterogenous tumors. To evaluate the molecular features of these tumors, 98 ampullary adenocarcinomas were evaluated and compared to 44 distal bile duct and 18 duodenal adenocarcinomas. Genomic analyses revealed mutations in the WNT signaling pathway among half of the patients and in all three adenocarcinomas irrespective of their origin and histological morphology. These tumors were characterized by a high frequency of inactivating mutations of ELF3, a high rate of microsatellite instability, and common focal deletions and amplifications, suggesting common attributes in the molecular pathogenesis are at play in these tumors. The high frequency of WNT pathway activating mutation, coupled with small-molecule inhibitors of ?-catenin in clinical trials, suggests future treatment decisions for these patients may be guided by genomic analysis.
EVALuna2:15250

Analysis of DNA Hypermethylation in Pancreatic Cancer Using Methylation-Specific PCR and Bisulfite Sequencing - Liu, Bin; Pilarsky, Christian (Methods in Molecular Biology, 2018)
Pancreatic ductal adenocarcinoma (PDAC) is an aggressive tumor and the fourth common cause of cancer death in the Western world. The lack of effective therapeutic strategies is attributed to the late diagnosis of this disease. Methylation markers could improve early detection and help in the surveillance of PDAC after treatment. Analysis of hypermethylation in the tumor tissue and tumor-derived exosomes might help to identify new therapeutic strategies and aid in the understanding of the pathophysiological changes occurring in pancreatic cancer. There are several methods for the detection of methylation events. Whereas methylation-specific PCR (MSP-PCR) is the method of choice, the cost reductions in DNA sequencing enables researchers to add bisulfite sequencing (BSS) to their repertoire if a small number of genes will be tested in a larger set of patients' samples. During the last years, several techniques to isolate and analyze DNA methylation have been proposed, but DNA modification using sodium bisulfite is still the gold standard.
CRIS-Team WoS Importer:2019-02-27

Analysis of GPRC6A variants in different pancreatitis etiologies - Kaune, Tom; Ruffert, Claudia; Hesselbarth, Nico; Damm, Marko; Krug, Sebastian; Cardinal von Widdern, Julian; Masson, Emmanuelle; Chen, Jian Min; Rebours, Vinciane; Buscail, Louis; Férec, Claude; Grützmann, Robert; et al. (Pancreatology, 2020)
Background: The G-protein-coupled receptor Class C Group 6 Member A (GPRC6A) is activated by multiple ligands and is important for the regulation of calcium homeostasis. Extracellular calcium is capable to increase NLRP3 inflammasome activity of the innate immune system and deletion of this proinflammatory pathway mitigated pancreatitis severity in vivo. As such this pathway and the GPRC6A receptor is a reasonable candidate gene for pancreatitis. Here we investigated the prevalence of sequence variants in the GPRC6A locus in different pancreatitis aetiologies. Methods: We selected 6 tagging SNPs with the SNPinfo LD TAG SNP Selection tool and the functional relevant SNP rs6907580 for genotyping. Cohorts from Germany, further European countries and China with up to 1,124 patients and 1,999 controls were screened for single SNPs with melting curve analysis. Results: We identified an association of rs1606365(G) with alcoholic chronic pancreatitis in a German (odds ratio (OR) 0.76, 95% confidence interval (CI) 0.65–0.89, p = 8 × 10−5) and a Chinese cohort (OR 0.78, 95% CI 0.64–0.96, p = 0.02). However, this association was not replicated in a combined cohort of European patients (OR 1.18, 95% CI 0.99–1.41, p = 0.07). Finally, no association was found with acute and non-alcoholic chronic pancreatitis. Conclusions: Our results support a potential role of calcium sensing receptors and inflammasome activation in alcoholic chronic pancreatitis development. As the functional consequence of the associated variant is unclear, further investigations might elucidate the relevant mechanisms.
CRIS-Team Scopus Importer:2020-09-04
Keywords: Calcium; G-Protein coupled receptor; Genetics; Inflammation; Pancreatitis

Analysis of Intraoperative Frozen Pancreatic Resection Margin and Prediction of Postoperative Pancreatic Fistula Risk During Pancreatoduodenectomy - Brunner, Maximilian; Kovacevic, Jasna; Krautz, Christian; Merkel, Susanne; Hartmann, Arndt; Grützmann, Robert; Haller, Florian; Weber, Georg (Journal of the American College of Surgeons, 2022)
BACKGROUND: Pancreatic duct diameter and pancreatic texture are important predictive factors for a postoperative pancreatic fistula (POPF) and are assessed intraoperatively by the surgeon. However, surgical evaluation is arbitrary and difficult to objectify, especially in minimally invasive approaches in pancreatic surgery. STUDY DESIGN: We conducted a retrospective analysis of 275 patients that underwent pancreatoduodenectomy from 2012 to 2019 at our institution. Pancreatic duct diameter and pancreatic fibrosis were assessed by histopathologic examination of the pancreatic resection margin using intraoperative frozen sections and correlated with the occurrence of POPF and clinically relevant POPF (CR-POPF). RESULTS: The POPF and CR-POPF rates were 27% and 19%, respectively. Univariate analysis indicated that the indication for surgery, the surgically determined pancreatic duct diameter, and pancreatic texture, as well as the histopathologically determined pancreatic duct diameter and pancreatic fibrosis were significant predictive factors for POPF and CR-POPF. A multivariate analysis revealed histopathologically determined pancreatic duct diameter and pancreatic fibrosis as independent risk factors for POPF (OR [odds ratio] 2.3 [1.1 to 4.5], p = 0.022 and OR 2.4 [1.1 to 5.1], p = 0.023, respectively) and CR-POPF (OR 2.2 [1.1 to 4.8], p = 0.037 and OR 2.6 [1.1 to 6.1], p = 0.036). CONCLUSIONS: Histopathologically determined pancreatic duct diameter and pancreatic fibrosis are quantitatively measurable independent risk factors for POPF and CR-POPF. An intraoperative objective histopathologic evaluation of these parameters using frozen sections could support the surgical assessment of the pancreatic duct diameter and the pancreatic texture.
CRIS-Team Scopus Importer:2022-04-29

Analysis of the interferon-γ-induced secretome of intestinal endothelial cells: putative impact on epithelial barrier dysfunction in IBD - Naschberger, Elisabeth; Flierl, Christian; Huang, Jinghao; Erkert, Lena; Gámez Belmonte, Maria de los Reyes; Gonzalez Acera, Miguel; Bober, Magdalena; Mehnert, Martin; Becker, Christoph; Schellerer, Vera S.; Britzen-Laurent, Nathalie; Stürzl, Michael (Frontiers in Cell and Developmental Biology, 2023)
The development of inflammatory bowel diseases (IBD) involves the breakdown of two barriers: the epithelial barrier and the gut-vascular barrier (GVB). The destabilization of each barrier can promote initiation and progression of the disease. Interestingly, first evidence is available that both barriers are communicating through secreted factors that may accordingly serve as targets for therapeutic modulation of barrier functions. Interferon (IFN)-γ is among the major pathogenesis factors in IBD and can severely impair both barriers. In order to identify factors transmitting signals from the GVB to the epithelial cell barrier, we analyzed the secretome of IFN-γ-treated human intestinal endothelial cells (HIEC). To this goal, HIEC were isolated in high purity from normal colon tissues. HIEC were either untreated or stimulated with IFN-γ (10 U/mL). After 48 h, conditioned media (CM) were harvested and subjected to comparative hyper reaction monitoring mass spectrometry (HRM™ MS). In total, 1,084 human proteins were detected in the HIEC-CM. Among these, 43 proteins were present in significantly different concentrations between the CM of IFN-γ- and control-stimulated HIEC. Several of these proteins were also differentially expressed in various murine colitis models as compared to healthy animals supporting the relevance of these proteins secreted by inflammatory activated HIEC in the inter-barrier communication in IBD. The angiocrine pathogenic impact of these differentially secreted HIEC proteins on the epithelial cell barrier and their perspectives as targets to treat IBD by modulation of trans-barrier communication is discussed in detail.
CRIS-Team Scopus Importer:2023-09-08
Keywords: angiocrine; barrier; cytokines; endothelial; IBD-inflammatory bowel disease; interferon; paracrine; secretion

Angiocrine Regulation of Epithelial Barrier Integrity in Inflammatory Bowel Disease - Stürzl, Michael; Kunz, Meik; Krug, Susanne M.; Naschberger, Elisabeth (Frontiers in Medicine, 2021)
Inflammatory bowel disease describes chronic inflammatory disorders. The incidence of the disease is rising. A major step in disease development is the breakdown of the epithelial cell barrier. Numerous blood vessels are directly located underneath this barrier. Diseased tissues are heavily vascularized and blood vessels significantly contribute to disease progression. The gut-vascular barrier (GVB) is an additional barrier controlling the entry of substances into the portal circulation and to the liver after passing the first epithelial barrier. The presence of the GVB rises the question, whether the vascular and endothelial barriers may communicate bi-directionally in the regulation of selective barrier permeability. Communication from epithelial to endothelial cells is well-accepted. In contrast, little is known on the respective backwards communication. Only recently, perfusion-independent angiocrine functions of endothelial cells were recognized in a way that endothelial cells release specific soluble factors that may directly act on the epithelial barrier. This review discusses the putative involvement of angiocrine inter-barrier communication in the pathogenesis of IBD.
CRIS-Team Scopus Importer:2021-08-27
Keywords: angiocrine; angiogenesis; barrier; endothelial; epithelial; inflammation; inflammatory bowel disease

Angiostatic immune reaction in colorectal carcinoma: Impact on survival and perspectives for antiangiogenic therapy - Naschberger, Elisabeth; Croner, Roland S.; Merkel, Susanne; Dimmler, Arno; Tripal, Philipp; Amann, Kerstin Ute; Kremmer, Elisabeth; Brueckl, Wolfgang M.; Papadopoulos, Thomas; Hohenadl, Christine; Hohenberger, Werner; Stürzl, Michael (International Journal of Cancer, 2008)
Angiogenesis and inflammation are the 2 major stroma reactions in colorectal carcinoma (CRC). Guanylate binding protein-1 (GBP-1) is a key mediator of angiostatic effects of inflammation. Therefore, we hypothesized that GBP-1 may be a biomarker of intrinsic angiostasis associated with an improved outcome in CRC patients. GBP-1 was strongly expressed in endothelial cells and immune cells in the desmoplastic stroma of 32% of CRC as determined by immunohistochemical investigation of 388 sporadic CRC. Cancer-related 5-year survival was highly significant (p < 0.001) increased (16.2%) in patients with GBP-1-positive CRC. Multivariate analysis showed that GBP-1 is an independent prognostic factor indicating a reduction of the relative risk of cancer-related death by the half (p = 0.032). A comparative transcriptome analysis (22,215 probe sets) of GBP-1-positive (n = 12) and -negative (n = 12) tumors showed that particularly IFN-γ-induced genes including the major antiangiogenic chemokines CXCL9, CXCL10 and CXCL11 were coexpressed with GBP-1. Altogether our findings indicated that GBP-1 may be a novel biomarker and an active component of a Th-1-like angiostatic immune reaction in CRC. This reaction may affect patient's response to antiangiogenic therapy and the identification of such tumors may provide a novel criterion for patient selection. Moreover, the induction of a Th-1-like angiostatic immune reaction may be a promising approach for the clinical treatment of CRC. © 2008 Wiley-Liss, Inc.
Created from Fastlane, Scopus look-up
Keywords: Angiogenesis; Colorectal carcinoma; Guanylate binding protein-1; Inflammation; Interferon-γ

An m5C methylation regulator-associated signature predicts prognosis and therapy response in pancreatic cancer - Yun, Duo; Yang, Zhirong; Zhang, Shuman; Yang, Hai; Liu, Dongxue; Grützmann, Robert; Pilarsky, Christian; Britzen-Laurent, Nathalie (Frontiers in Cell and Developmental Biology, 2022)
Pancreatic ductal adenocarcinoma (PDAC) is the most aggressive digestive malignancy due to frequent late-stage diagnosis, rapid progression and resistance to therapy. With increasing PDAC incidence worldwide, there is an urgent need for new prognostic biomarkers and therapy targets. Recently, RNA methylation has emerged as a new tumorigenic mechanism in different cancers. 5-methylcytosine (m5C) is one of the most frequent RNA modifications and occurs on a variety of RNA species including mRNA, thereby regulating gene expression. Here we investigated the prognostic role of m5C-regulator-associated transcriptional signature in PDAC. We evaluated m5C-regulator status and expression in 239 PDAC samples from publicly available datasets. We used unsupervised consensus clustering analyses to classify PDACs based on m5C-regulator expression. From the resulting signature of differentially expressed genes (DEGs), we selected prognosis-relevant DEGs to stratify patients and build a scoring signature (m5C-score) through LASSO and multivariate Cox regression analyses. The m5C-score represented a highly significant independent prognostic marker. A high m5C-score correlated with poor prognosis in different PDAC cohorts, and was associated with the squamous/basal subtype as well as activated cancer-related pathways including Ras, MAPK and PI3K pathways. Furthermore, the m5C-score correlated with sensitivity to pathway-specific inhibitors of PARP, EGFR, AKT, HER2 and mTOR. Tumors with high m5C-score were characterized by overall immune exclusion, low CD8(+) T-cell infiltration, and higher PD-L1 expression. Overall, the m5C-score represented a robust predictor of prognosis and therapy response in PDAC, which was associated with unfavorable molecular subtypes and immune microenvironment.
CRIS-Team WoS Importer:2022-09-16

A Novel Anti-Cancer Therapy: CRISPR/Cas9 Gene Editing - Chen, Xin-Zhu; Guo, Rong; Zhao, Cong; Xu, Jing; Song, Hang; Yu, Hua; Pilarsky, Christian; Nainu, Firzan; Li, Jing-Quan; Zhou, Xin-Ke; Zhang, Jian-Ye (Frontiers in Pharmacology, 2022)
Cancer becomes one of the main causes of human deaths in the world due to the high incidence and mortality rate and produces serious economic burdens. With more and more attention is paid on cancer, its therapies are getting more of a concern. Previous research has shown that the occurrence, progression, and treatment prognosis of malignant tumors are closely related to genetic and gene mutation. CRISPR/Cas9 has emerged as a powerful method for making changes to the genome, which has extensively been applied in various cell lines. Establishing the cell and animal models by CRISPR/Cas9 laid the foundation for the clinical trials which possibly treated the tumor. CRISPR-Cas9-mediated genome editing technology brings a great promise for inhibiting migration, invasion, and even treatment of tumor. However, the potential off-target effect limits its clinical application, and the effective ethical review is necessary. The article reviews the molecular mechanisms of CRISPR/Cas9 and discusses the research and the limitation related to cancer clinical trials.
CRIS-Team WoS Importer:2022-08-12

A novel approach to 3-D Endoscopy in Minimally Invasive Surgery - Krüger, Sophie; Penne, Jochen; Hornegger, Joachim; Hohenberger, Werner; Horbach, Thomas (Abstractband curac 2006, 2006)

A novel chip-based parallel transfection assay to evaluate paracrine cell interactions - Kühn, Elisabeth; Naschberger, Elisabeth; Konrad, Andreas; Croner, Roland S.; Britzen-Laurent, Nathalie; Jochmann, Ramona; Münstedt, Helmut; Stürzl, Michael (Lab on A Chip, 2012)
Created from Fastlane, Scopus look-up

Antibiotic treatment after appendectomy for acute complicated appendicitis to prevent intrabdominal abscess and wound infections - Laverde, Bruno Leonardo Bancke; Maak, Matthias; Langheinrich, Melanie; Kersting, Stephan; Denz, Axel; Krautz, Christian; Weber, Georg; Grützmann, Robert; Brunner, Maximilian (Langenbecks Archives of Surgery, 2024)
Introduction: The purpose of this analysis was to investigate the most appropriate duration of postoperative antibiotic treatment to minimize the incidence of intraabdominal abscesses and wound infections in patients with complicated appendicitis. Materials and methods: In this retrospective study, which included 396 adult patients who underwent appendectomy for complicated appendicitis between January 2010 and December 2020 at the University Hospital Erlangen, patients were classified into two groups based on the duration of their postoperative antibiotic intake: ≤ 3 postoperative days (group 1) vs. ≥ 4 postoperative days (group 2). The incidence of postoperative intraabdominal abscesses and wound infections were compared between the groups. Additionally, multivariate risk factor analysis for the occurrence of intraabdominal abscesses and wound infections was performed. Results: The two groups contained 226 and 170 patients, respectively. The incidence of postoperative intraabdominal abscesses (2% vs. 3%, p = 0.507) and wound infections (3% vs. 6%, p = 0.080) did not differ significantly between the groups. Multivariate analysis revealed that an additional cecum resection (OR 5.5 (95% CI 1.4–21.5), p = 0.014) was an independent risk factor for intraabdominal abscesses. A higher BMI (OR 5.9 (95% CI 1.2–29.2), p = 0.030) and conversion to an open procedure (OR 5.2 (95% CI 1.4–20.0), p = 0.016) were identified as independent risk factors for wound infections. Conclusion: The duration of postoperative antibiotic therapy does not appear to influence the incidence of postoperative intraabdominal abscesses and wound infections. Therefore, short-term postoperative antibiotic treatment should be preferred.
CRIS-Team Scopus Importer:2024-06-21
Keywords: Appendectomy; Complicated appendicitis; Intraabdominal abscess; Postoperative antibiotic therapy; Wound infection

Anti-DNA-IgM Favors the Detection of NET-Associated Extracellular DNA - Wang, Han; Stehr, Antonia; Singh, Jeeshan; Zlatar, Leticija; Hartmann, Arndt; Evert, Katja; Naschberger, Elisabeth; Von Stillfried, Saskia; Boor, Peter; Munoz, Luis Enrique; Knopf, Jasmin; Stürzl, Michael; et al. (International Journal of Molecular Sciences, 2023)
During inflammatory responses, neutrophils enter the sites of attack where they execute various defense mechanisms. They (I) phagocytose microorganisms, (II) degranulate to release cytokines, (III) recruit various immune cells by cell-type specific chemokines, (IV) secrete anti-microbials including lactoferrin, lysozyme, defensins and reactive oxygen species, and (V) release DNA as neutrophil extracellular traps (NETs). The latter originates from mitochondria as well as from decondensed nuclei. This is easily detected in cultured cells by staining of DNA with specific dyes. However, in tissues sections the very high fluorescence signals emitted from the condensed nuclear DNA hamper the detection of the widespread, extranuclear DNA of the NETs. In contrast, when we employ anti-DNA-IgM antibodies, they are unable to penetrate deep into the tightly packed DNA of the nucleus, and we observe a robust signal for the extended DNA patches of the NETs. To validate anti-DNA-IgM, we additionally stained the sections for the NET-markers histone H2B, myeloperoxidase, citrullinated histone H3, and neutrophil elastase. Altogether, we have described a fast one-step procedure for the detection of NETs in tissue sections, which provides new perspectives to characterize neutrophil-associated immune reactions in disease.
CRIS-Team Scopus Importer:2023-03-10
Keywords: anti-DNA-IgM; extracellular DNA; NETs

Antioxidative, anti-androgenic, and inhibitory activities of ethanolic extract of Annona muricata leaf on sex hormones-induced benign prostate hyperplasia through in vivo and in silico studies - Ebenyi, Lilian N.; Chigozie, Victor U.; Destiny, Demian; Anyanwu, Chidinma (Natural Product Research, 2024)
Benign prostate hyperplasia (BPH) remains one of the major age-related urological problems in the world. Annona muricata (soursop) leaf has been reported to exhibit antiproliferative, antioxidant, and anti-inflammatory activities, among others, in the literature. Here, we aimed to unravel the antioxidative, antiandrogenic, and inhibitory activities of the ethanol extract of Annona muricata leaf (EEAML) on sex hormones-induced benign prostate hyperplasia (BPH) through in vivo and in silico studies. Thirty-six male rats were segmented into six groups of six animals each, the control group received water, and the BPH group and the remaining four groups were parentally infused with testosterone (T) and oestradiol (E2) (0.08 and 0.04 mg/Kgbwt) once daily for 28 days to induce BPH. After that, the control and BPH groups received water and normal saline, while the remaining four groups received finasteride (FIN) (0.1 mg/kgbwt) and EEAML (200, 400, and 800 mg/kgbwt) for another 28 days before sacrifice, and serum was collected for biochemical analysis. Additionally, the active ingredients of EEAML were identified using a Gas Chromatography Flame Ionisation Detector (GC-FID) followed by molecular docking (MD) against the human androgen receptor (hAR) target, and ADMET analysis of selected EEAML compounds was carried out. EEAML (200, 400, and 800 mg/kgbwt) restored the T and E2-induced depletion of reduced glutathione level, superoxide dismutase and catalase activities, and elevation of malondialdehyde, prostate-specific antigen, testosterone, and dihydrotestosterone levels in the serum of BPH rats. GC-FID analysis of EEAML showed the presence of 21 compounds from which 15 compounds were subjected to MD revealing that flavone, followed by ribalinidine, flavonone, anthocyanin, and naringenin displayed desirable binding affinities against the hAR target. ADMET analysis of these top-five EEAML compounds revealed that they were excellent oral bioavailable drug candidates with predicted minimal toxicities. In conclusion, EEAML exhibited antioxidative, antiandrogenic, and inhibitory activities owing to its phytoconstituents, which in turn could serve as drug templates for much better efficacy.
CRIS-Team Scopus Importer:2024-10-25
Keywords: Annona muricata; anti-androgenic; antioxidative; benign prostate hyperplasia (BPH); ethanol extract of Annona muricata leaf (EEAML)

Anti-TNF-refractory colitis after checkpoint inhibitor therapy: Possible role of CMV-mediated immunopathogenesis - Lankes, Katharina; Hundorfean, Gheorghe; Harrer, Thomas; Pommer, Ansgar J.; Agaimy, Abbas; Angelovska, Irena; Tajmir-Riahi, Azadeh; Göhl, Jonas; Schuler, Gerold; Neurath, Markus; Hohenberger, Werner; Heinzerling, Lucie (OncoImmunology, 2016)
Immune-related adverse events (irAEs) induced by checkpoint inhibitors are well known. Since fatal outcomes have been reported early detection and adequate management are crucial. In particular, colitis is frequently observed and can result in intestinal perforation. This is the first report of an autoimmune colitis that was treated according to algorithms but became resistant due to a CMV reactivation. The 32-y-old male patient with metastatic melanoma treated within an anti-PD-1/ipilimumab combination study developed severe immune-mediated colitis (CTCAE grade 3) with up to 18 watery stools per day starting 2 weeks after treatment initiation. After improving upon therapy with immunosuppressive treatment (high dose steroids and infliximab) combined with parenteral nutrition diarrhea again exacerbated. Additionally, the patient had asymptomatic grade 3 CTCAE amylase and lipase elevation. Colitis was monitored by weekly endoscopies and colon biopsies were analyzed histologically with CMV staining, multi-epitope ligand cartography (MELC) and qRT-PCR for inflammatory genes. In the course, CMV reactivation was detected in the colon and treated with antiviral medication in parallel to a reduction of corticosteroids. Subsequently, symptoms improved. The patient showed a complete response for 2 y now including regression of bone metastases. CMV reactivation under checkpoint inhibitor therapy in combination with immunosuppressive treatment for autoimmune side effects has to be considered in these patients and if present treated. Potentially, CMV reactivation is underdiagnosed. Treatment algorithms should include CMV diagnostics.
EVALuna2:2063

A Possible Distinct Molecular Subtype (Quintuple-Wildtype) of Metastatic Colorectal Cancer in First-Line Anti-EGFR Therapy with Cetuximab Plus FOLFIRI - Palliative Precision Therapy and a Multidisciplinary Treatment Approach: Interim Analysis of the IVOPAK II Trial with Early Results - Wein, Axel; Stöhr, Robert; Kersting, Stephan; Siebler, Jürgen; Merkel, Susanne; Busse, Daniel; Wolff, Kerstin; Ostermeier, Nicola; Neufert, Clemens; Vitali, Francesco; Eckstein, Markus; Roth, Jan-Peter; et al. (Oncology, 2021)
Objective: The study aimed to prospectively evaluate a new molecular biomarker panel (KRAS, NRAS, BRAF, PIK3CA, and ERBB2) for palliative first-line treatment of colorectal cancer (CRC), including a multidisciplinary treatment approach. The rate of secondary metastasis resections was assessed. Patients and Methods: A total of 40 patients with definitively nonresectable metastatic CRC were enrolled from 10 centers before the interim analysis (June 2019) of the IVOPAK II trial (Interdisciplinary Care with Quality Control in Palliative Treatment of Colorectal Cancer). After determination of 5 molecular biomarkers in the tumor (KRAS, exons 2-4; NRAS, exons 2-4; BRAF V600E; PIK3CA; and ERBB2), patients in the IVOPAK II study received FOLFIRI plus cetuximab for all-RAS/quintuple-wildtype disease and FOLFIRI plus bevacizumab in the case of RAS mutations. The current article presents the early description of the clinical outcome of the interim analysis of IVOPAK II comparing the all-RAS/quintuple-wildtype and RAS-mutations populations, including a multidisciplinary-treated case report of a quintuple-wildtype patient. Results: The quintuple-wildtype population treated with FOLFIRI plus cetuximab in first-line exhibited a significantly higher response rate and enhanced early tumor shrinkage in the interim analysis than the RAS-mutations population, as well as a high rate of secondary metastatic resections. Conclusion: Initial results of this new biomarker panel (quintuple-wildtype) are promising for anti-EGFR therapy with cetuximab plus doublet chemotherapy (FOLFIRI) in first-line treatment of metastatic CRC. These results warrant confirmation with higher case numbers in the IVOPAK II trial.
CRIS-Team WoS Importer:2021-11-05

A possible role for interferon-alpha and activated natural killer cells in remission of AIDS-related Kaposi's sarcoma: in vitro studies. - Reiter, Z; Ozés, O N; Blatt, L M; Stürzl, Michael; Taylor, M W (Journal of Acquired Immune Deficiency Syndromes, 1992)
The effect of consensus interferon-alpha on the growth of AIDS-related Kaposi's sarcoma-derived cells was studied. Interferon caused a low but significant in vitro inhibition of cell growth. Whereas Kaposi's sarcoma cells were resistant to the cytotoxic effect of natural killer (NK) cells, treatment of NK cells with either interferon or interleukin-2 activated the cell-mediated cytotoxic response. Pretreatment of the Kaposi's sarcoma cells with interferon reduced their sensitivity to interferon-primed natural killer cell or lymphokine (interleukin-2)-activated killer (LAK) cell cytotoxicity. The resistance of Kaposi's sarcoma cells to NK cell-mediated cytotoxicity did not reside in conjugate formation but was due to an inability of Kaposi's sarcoma cells to induce NK cytotoxic factor. Although interferon reduces the sensitivity of Kaposi's sarcoma cells to interferon-primed NK cell and LAK cell activities, the level of natural killing susceptibility remained significantly higher than the poor sensitivity of Kaposi's sarcoma cells to unprimed NK cell activity. Thus, the potential antitumor effect of interferon against Kaposi's sarcoma cells could be mediated both directly (antiproliferative) and/or indirectly by activation of NK cells.

Application of machine learning algorithms for multiparametric MRI-based evaluation of murine colitis - Ellmann, Stephan; Langer, Victoria; Britzen-Laurent, Nathalie; Hildner, Kai; Huber, Carina; Tripal, Philipp; Seyler, Lisa; Waldner, Maximilian; Uder, Michael; Stürzl, Michael; Bäuerle, Tobias (PLoS ONE, 2018)
Magnetic resonance imaging (MRI) allows non-invasive evaluation of inflammatory bowel disease (IBD) by assessing pathologically altered gut. Besides morphological changes, relaxation times and diffusion capacity of involved bowel segments can be obtained by MRI. The aim of this study was to assess the use of multiparametric MRI in the diagnosis of experimentally induced colitis in mice, and evaluate the diagnostic benefit of parameter combinations using machine learning. This study relied on colitis induction by Dextran Sodium Sulfate (DSS) and investigated the colon of mice in vivo as well as ex vivo. Receiver Operating Characteristics were used to calculate sensitivity, specificity, positive- and negative-predictive values (PPV and NPV) of these single values in detecting DSS-treatment as a reference condition. A Model Averaged Neural Network (avNNet) was trained on the multiparametric combination of the measured values, and its predictive capacity was compared to those of the single parameters using exact binomial tests. Within the in vivo subgroup (n = 19), the avNNet featured a sensitivity of 91.3% (95% CI: 86.6-96.0%), specificity of 92.3% (95% CI: 85.1-99.6%), PPV of 96.9% (94.0-99.9%) and NPV of 80.0% (95% CI: 69.9-90.1%), significantly outperforming all single parameters in at least 2 accuracy measures (p < 0.003) and performing significantly worse compared to none of the single values. Within the ex vivo subgroup (n = 30), the avNNet featured a sensitivity of 87.4% (95% CI: 82.6-92.2%), specificity of 82.9% (95% CI: 76.1-89.7%), PPV of 88.9% (84.3-93.5%) and NPV of 80.8% (95% CI: 73.8-87.9%), significantly outperforming all single parameters in at least 2 accuracy measures (p < 0.015), exceeded by none of the single parameters. In experimental mouse colitis, multiparametric MRI and the combination of several single measured values to an avNNet can significantly increase diagnostic accuracy compared to the single parameters alone. This pilot study will provide new avenues for the development of an MR-derived colitis score for optimized diagnosis and surveillance of inflammatory bowel disease.
EVALuna2:35135

Application of microfluidic chips in anticancer drug screening - Fan, Xin Yue; Deng, Zhuo Fen; Yan, Yan Yan; E Orel, Valerii; Shypko, Andrii; B Orel, Valerii; Ivanova, Donika; Pilarsky, Christian; Tang, Jing; Chen, Zhe Sheng; Zhang, Jian Ye (Bosnian Journal of Basic Medical Sciences, 2022)
With the continuous development of drug screening technology, new screening methodologies and technologies are constantly emerging, driving drug screening into rapid, efficient and high-throughput development. Microfluidics is a rising star in the development of innovative approaches in drug discovery. In this article, we summarize the recent years' progress of microfluidic chip technology in drug screening, including the developmental history, structural design, and applications in different aspects of microfluidic chips on drug screening. Herein, the existing microfluidic chip screening platforms are summarized from four aspects: chip structure design, sample injection and drive system, cell culture technology on a chip, and efficient remote detection technology. Furthermore, this review discusses the application and developmental prospects of using microfluidic chips in drug screening, particularly in screening natural product anticancer drugs based on chemical properties, pharmacological effects, and drug cytotoxicity.
CRIS-Team Scopus Importer:2022-06-17

A proposed system for standardized terminology in minimally invasive surgery – a video vignette - Zawadzki, M.; Gómez Ruiz, M.; Tou, S.; Jeffels, A.; Matzel, Klaus (Colorectal Disease, 2020)
CRIS-Team Scopus Importer:2020-09-25

A role for MALT1 activity in Kaposi's sarcoma-associated herpes virus latency and growth of primary effusion lymphoma - Bonsignore, L.; Passelli, K.; Pelzer, C.; Perroud, M.; Konrad, A.; Thurau, Mathias; Stürzl, Michael; Dai, L.; Trillo-Tinoco, Jimena; Del Valle, L.; Qin, Z.; Thome, Margot (Leukemia, 2017)
Primary effusion lymphoma (PEL) is an incurable malignancy that develops in immunodeficient patients as a consequence of latent infection of B-cells with Kaposi's sarcoma-associated herpes virus (KSHV). Malignant growth of KSHV-infected B cells requires the activity of the transcription factor nuclear factor (NF)-?B, which controls maintenance of viral latency and suppression of the viral lytic program. Here we show that the KSHV proteins K13 and K15 promote NF-?B activation via the protease mucosa-associated lymphoid tissue lymphoma translocation protein-1 (MALT1), a key driver of NF-?B activation in lymphocytes. Inhibition of the MALT1 protease activity induced a switch from the latent to the lytic stage of viral infection, and led to reduced growth and survival of PEL cell lines in vitro and in a xenograft model. These results demonstrate a key role for the proteolytic activity of MALT1 in PEL, and provide a rationale for the pharmacological targeting of MALT1 in PEL therapy.
EVALuna2:15308

Association of Plane of Total Mesorectal Excision With Prognosis of Rectal Cancer: Secondary Analysis of the CAO/ARO/AIO-04 Phase 3 Randomized Clinical Trial - Kitz, Julia; Fokas, Emmanouil; Beissbarth, Tim; Stroebel, Philipp; Wittekind, Christian; Hartmann, Arndt; Rueschoff, Josef; Papadopoulos, Thomas; Roesler, Elisabeth; Ortloff-Kittredge, Peter; Kania, Ulrich; Schlitt, Hans; et al. (JAMA Surgery, 2018)
Importance: Previous retrospective studies have shown that surgical quality affects local control in rectal cancer.. Objective: In this secondary end point analysis, we evaluated the prognostic effect of the total mesorectal excision (TME) plane in the CAO/ARO/AIO-04 phase 3 randomized clinical trial. Design, Setting, and Participants: The CAO/ARO/AIO-04 trial enrolled 1236 patients with cT3-4 and/or node-positive rectal adenocarcinoma from 88 centers in Germany between July 25, 2006, and February 26, 2010. Interventions: Patients were randomized to receive treatment with standard fluorouracil-based preoperative chemoradiotherapy (CRT) alone (control arm) or oxaliplatin (experimental arm) followed by TME and adjuvant chemotherapy. Main Outcomes and Measures: The TME quality (mesorectal, intramesorectal, and muscularis propria plane) was prospectively assessed in 1152 operation specimens. An assessment was performed independently by pathologists and surgeons. The results were correlated with clinicopathologic data and the clinical outcome was tested, including multivariable analysis with the Cox regression model. Results: Of 1152 German Caucasian participants, 332 (28.8) were women and the mean age was 63 years. The plane of TME was mesorectal in 930 patients (80.7%), intramesorectal in 169 (14.7%), and muscularis propria in 53 (4.6%). In a univariable analysis, the TME plane was significantly associated with 3-year disease-free survival (mesorectal vs intramesorectal vs muscularis propria, 95% CI, 73.1-78.8 vs 61.6-76.0 vs 55.6-81.3, respectively; P = .01), cumulative incidence of local and distant recurrences (mesorectal vs intramesorectal vs muscularis propria, 95% CI, 2.0-4.5 vs 1.2-8.1 vs 2.5-20.5, respectively; P < .001; and mesorectal vs intramesorectal vs muscularis propria, 95% CI, 17.0-22.4 vs 18.3-32.0 vs 14.2-39.0, respectively; P = .03, respectively), and overall survival (mesorectal vs intramesorectal vs muscularis propria, 95% CI, 88.3-92.3 vs 79.7-91.0 vs 81.6-98.7, respectively; P = .02). In contrast to the pathologist-based evaluation, the assessment of TME plane by the operating surgeon failed to demonstrate prognostic significance for any of these clinical end points. In a multivariable analysis, the plane of surgery (mesorectal vs muscularis propria TME) constituted an independent factor for local recurrence (P = .002). Conclusions and Relevance: This phase 3 randomized clinical trial confirms the long-term clinical effect of TME plane quality on local recurrence, as initially reported in the MRC CR07 study. The data highlight the key role of pathologists and surgeons in the multidisciplinary management of rectal cancer. Trial Registration: ClinicalTrials.gov Identifier: NCT00349076.
EVALuna2:34814

A survey among physicians in surgery and anesthesiology departments after the first surge of SARS-CoV-2 infections in Germany Preparing for further challenges ahead - Grishina, Anna; Link, Fabian; Arend, Arne; Kleemann, Florentine; Tober-Lau, Pinkus; Andree, Dominik; Muenn, Friederike; Gruendl, Magdalena; Quante, Markus; Lederhuber, Hans; Albertsmeier, Markus; Struller, Florian; et al. (Wiener Klinische Wochenschrift, 2022)
Background The SARS-CoV-2 pandemic has extensively challenged healthcare systems all over the world. Many elective operations were postponed or cancelled, changing priorities and workflows in surgery departments. Aims The primary aim of this cross-sectional study was to assess the workload and psychosocial burden of surgeons and anesthesiologists, working in German hospitals during the first wave of SARS-CoV-2 infections in 2020. Methods Quantitative online survey on the workplace situation including psychosocial and work-related stress factors among resident and board-certified surgeons and anesthesiologists. Physicians in German hospitals across all levels of healthcare were contacted via departments, professional associations and social media posts. Results Among 154 total study participants, 54% of respondents stated a lack of personal protective equipment in their own wards and 56% reported increased staff shortages since the onset of the pandemic. While routine practice was reported as fully resumed in 71% of surgery departments at the time of the survey, work-related dissatisfaction among responding surgeons and anesthesiologists increased from 24% before the pandemic to 36% after the first wave of infections. As a countermeasure, 94% of participants deemed the establishment of action plans to increase pandemic preparedness and strengthening German public health systems a useful measure to respond to current challenges. Conclusion The aftermath of the first wave of SARS-CoV-2 infections in Germany has left the surgical staff strained, despite temporarily decreased workloads. Overall, a critical review of the altered conditions is indispensable to identify and promote effective solutions and prudent action plans required to address imminent challenges.
CRIS-Team WoS Importer:2022-01-28

A systems biology approach to identify the combination effects of human herpesvirus 8 genes on NF-κB activation - Konrad, Andreas; Wies, Effi; Thurau, Mathias; Marquardt, Gaby; Naschberger, Elisabeth; Hentschel, Sonja; Jochmann, Ramona; Schulz, Thomas F.; Erfle, Holger; Brors, Benedikt; Lausen, Berthold; Neipel, Frank; et al. (Journal of Virology, 2009)
Human herpesvirus 8 (HHV-8) is the etiologic agent of Kaposi's sarcoma and primary effusion lymphoma. Activation of the cellular transcription factor nuclear factor-kappa B (NF-κB) is essential for latent persistence of HHV-8, survival of HHV-8-infected cells, and disease progression. We used reverse-transfected cell microarrays (RTCM) as an unbiased systems biology approach to systematically analyze the effects of HHV-8 genes on the NF-κB signaling pathway. All HHV-8 genes individually (n = 86) and, additionally, all K and latent genes in pairwise combinations (n = 231) were investigated. Statistical analyses of more than 14,000 transfections identified ORF75 as a novel and confirmed K13 as a known HHV-8 activator of NF-κB. K13 and ORF75 showed cooperative NF-κB activation. Small interfering RNA-mediated knockdown of ORF75 expression demonstrated that this gene contributes significantly to NF-κB activation in HHV-8-infected cells. Furthermore, our approach confirmed K10.5 as an NF-κB inhibitor and newly identified K1 as an inhibitor of both K13- and ORF75-mediated NF-κB activation. All results obtained with RTCM were confirmed with classical transfection experiments. Our work describes the first successful application of RTCM for the systematic analysis of pathofunctions of genes of an infectious agent. With this approach, ORF75 and K1 were identified as novel HHV-8 regulatory molecules on the NF-κB signal transduction pathway. The genes identified may be involved in fine-tuning of the balance between latency and lytic replication, since this depends critically on the state of NF-κB activity. Copyright © 2009, American Society for Microbiology.
Created from Fastlane, Scopus look-up

ATF2 loss promotes tumor invasion in colorectal cancer cells via upregulation of cancer driver TROP2 - Hübner, Kerstin; Erlenbach-Wünsch, Katharina; Prochazka, Jan; Sheraj, Ilir; Hampel, Chuanpit; Mrazkova, Blanka; Michalcikova, Tereza; Tureckova, Jolana; Iatsiuk, Veronika; Weissmann, Anne; Ferrazzi, Fulvia; Kunze, Philipp; et al. (Cellular and Molecular Life Sciences, 2022)
In cancer, the activating transcription factor 2 (ATF2) has pleiotropic functions in cellular responses to growth stimuli, damage, or inflammation. Due to only limited studies, the significance of ATF2 in colorectal cancer (CRC) is not well understood. We report that low ATF2 levels correlated with worse prognosis and tumor aggressiveness in CRC patients. NanoString gene expression and ChIP analysis confirmed trophoblast cell surface antigen 2 (TROP2) as a novel inhibitory ATF2 target gene. This inverse correlation was further observed in primary human tumor tissues. Immunostainings revealed that high intratumoral heterogeneity for ATF2 and TROP2 expression was sustained also in liver metastasis. Mechanistically, our in vitro data of CRISPR/Cas9-generated ATF2 knockout (KO) clones revealed that high TROP2 levels were critical for cell de-adhesion and increased cell migration without triggering EMT. TROP2 was enriched in filopodia and displaced Paxillin from adherens junctions. In vivo imaging, micro-computer tomography, and immunostainings verified that an ATF2(KO)/TROP2(high) status triggered tumor invasiveness in in vivo mouse and chicken xenograft models. In silico analysis provided direct support that ATF2(low)/TROP2(high) expression status defined high-risk CRC patients. Finally, our data demonstrate that ATF2 acts as a tumor suppressor by inhibiting the cancer driver TROP2. Therapeutic TROP2 targeting might prevent particularly the first steps in metastasis, i.e., the de-adhesion and invasion of colon cancer cells.
CRIS-Team WoS Importer:2022-07-29

Automated Lesion Detection in Endoscopic Imagery for Small Animal Models - Eixelberger, Thomas; Fang, Qi; Zohud, Bisan; Hackner, Ralf; Jackstadt, Rene; Stürzl, Michael; Naschberger, Elisabeth; Wittenberg, Thomas (Bildverarbeitung für die Medizin 2024. BVM 2024, 2024)
Murine animal models are routinely used in research of gastrointestinal diseases, for example to analyze colorectal cancer or chronic inflammatory bowel diseases. By using suitable (miniaturized) endoscopy systems, it is possible to examine the large intestine of mice with respect to inflammatory, vascular or neoplastic changes without the need to sacrifice the animals. This enables the acquisition of high-resolution colonoscopy image sequences that can be used for the visual examination of tumors, the assessment of inflammation or the vasculature. Since the human resources for analyzing a multitude of videos, are limited, an automated evaluation of such image data is desirable. Video recordings (n = 49) of mice with and without colorectal cancer (CRC) were employed for this purpose and scored by clinical experts. The videos contained mice with tumors in 33 cases and 16 are pathologically normal. For the automatic detection of neoplastic changes (e.g. polyps), a deep neural network based on the YOLOv7- tiny architecture was applied. This network was previously trained on >36,000 human colon images with neoplasias visible in all frames. On test data with human images, the precision of the network is Prec = 0.92, and Rec = 0.90. The network was applied to the mouse data without any changes. To avoid falsepositive detections a color-based method was added to differentiate between stool residues and polyps. With the framework for the detection of neoplastic changes and classification of stool residues, we achieve results of Prec = 0.90, Rec = 0.98, F1 score = 0.94.Without the detection of stool residues, the values were dropping to Prec = 0.65 and Rec = 0.98, as 19 occurrences of stool are incorrectly classified as tumors. Our network trained on human data for neoplasia detection is able to accurately detect tumors in the murine colon. An additional module for the separation of stool residues is essential to avoid integration of wrongly positive cases.
CRIS-Team Scopus Importer:2024-03-29

Autonomously vascularized cellular constructs in tissue engeneering: opening a new perspective for biomedical science - Polykandriotis, Elias; Arkudas, Andreas; Horch, Raymund E.; Stürzl, Michael; Kneser, Ulrich (Journal of cellular and molecular medicine, 2007)
In tissue engineering cell cultures play a crucial role besides the matrix materials for the end of substituting lost tissue functions. The cell itself is situated at the cross-roads leading to different orders of scale, from molecule to organism and different levels of function, from biochemistry to macrophysiology. Extensive in vitro investigations have dissected a vast amount of cellular phenomena and the role of a number of bioactive substances has been elucidated in the past. Further, recombinant DNA technologies allow modulation of the expression profiles of virtually all kinds of cells. However, issues of vascularization in vivo limit transferability of these observations and restrict upscaling into clinical applications. Novel in vivo models of vascularization have evolved inspired from reconstructive microsurgical concepts and they encompass axial neovascularization by means of vascular induction. This work represents a brief description of latest developments and potential applications of neovascularization and angiogenesis in tissue engineering.
UnivIS-Import:2015-04-14:Pub.2007.med.packli.pchw2.autono

Autonomously vascularized cellular constructs in tissue engineering: opening a new perspective for biomedical science. - Polykandriotis, Elias; Arkudas, Andreas; Horch, Raymund E.; Stürzl, Michael; Kneser, Ulrich (Journal of Cellular and Molecular Medicine, 2007)
In tissue engineering cell cultures play a crucial role besides the matrix materials for the end of substituting lost tissue functions. The cell itself is situated at the cross-roads leading to different orders of scale, from molecule to organism and different levels of function, from biochemistry to macrophysiology. Extensive in vitro investigations have dissected a vast amount of cellular phenomena and the role of a number of bioactive substances has been elucidated in the past. Further, recombinant DNA technologies allow modulation of the expression profiles of virtually all kinds of cells. However, issues of vascularization in vivo limit transferability of these observations and restrict upscaling into clinical applications. Novel in vivo models of vascularization have evolved inspired from reconstructive microsurgical concepts and they encompass axial neovascularization by means of vascular induction. This work represents a brief description of latest developments and potential applications of neovascularization and angiogenesis in tissue engineering.

Avoidance of complications in oncological surgery of the pelvic region : Combined oncosurgical and plastic reconstruction measures - Beier, Justus; Croner, R. S.; Lang, Werner; Arkudas, Andreas; Schmitz, Marweh; Göhl, Jonas; Hohenberger, Werner; Horch, Raymund E. (Chirurg, 2015)
Prevention of perioperative and postoperative complications resulting from surgical oncology in the pelvic region remains a major interdisciplinary challenge. With modern interdisciplinary concepts joining forces of various surgical specialties, tumor resection can be sufficiently carried out with wide margins and the patients benefit from reduced morbidity even in complex situations. As an example chronic fistulation and secretion from the presacral cavity and sinus may result as potential sequelae from intra-abdominal and intrapelvic tumor resection, especially when neoadjuvant multimodal therapies have been applied. This can be prevented by simultaneous transplantation of for example transpelvic vertical rectus abdominis myocutaneous (VRAM) flap transfer, while extensive perineal skin and soft tissue defects may also be simultaneously reconstructed. In cases of malignant soft tissue tumors in the pelvic region a staged surgical procedure can be performed with a period of time between tumor resection and reconstruction. Thus, a histological R0 status can be secured prior to plastic reconstruction surgery in order to increase oncological safety. In cases of postresectional exposition of e. g. pelvic or femoral vessels or intrapelvic and intra-abdominal organs simultaneous flap procedure is mandatory.The reconstructive armamentarium of the plastic surgeon should contain not only pedicled but also free microsurgical flaps so that no compromise in terms of the extent of the oncological resection has to be accepted. At the same time perioperative and postoperative complications may be avoided and the patient quality of life can be preserved even in more complex cases.
EVALuna2:15195

Axial prevascularization of porous matrices using an arteriovenous loop promotes survival and differentiation of transplanted autologous osteoblasts. - Arkudas, Andreas; Beier, Justus P.; Heidner, Kristina; Tjiawi, Jimmy; Polykandriotis, Elias; Srour, Safwan; Stürzl, Michael; Horch, Raymund E.; Kneser, Ulrich (Tissue Engineering -Larchmont, 2007)
Generation of axially vascularized bioartificial bone might be performed using matrix neovascularization in connection with osteoblast injection. We sought to evaluate whether prevascularization of porous hard matrices using an arteriovenous (AV) loop promotes survival of transplanted osteoblasts. A processed bovine cancellous bone matrix was inserted into the AV loop. Six weeks later, 5 x 10(6) carboxyfluorescein diacetate-stained osteoblasts were injected into the matrix (group A, n = 34). Osteoblast-seeded matrices without prevascularization were implanted subcutaneously as controls (group B, n = 32). Specimens were subjected to histologic, morphometric, and molecular-biological analysis after 1, 4, 8, and 16 weeks. Upon cell injection, matrices were completely vascularized. An intense foreign body reaction was observed in matrices from both groups. Group A was significantly superior to group B in terms of osteoblast survival at any time point. Expression of bone-specific genes was detected in the AV loop group but not in the subcutaneous control. Bone formation was only detectable in 1 long-term animal of group A. This study demonstrates for the first time that axial prevascularization increases the survival of implanted osteoblasts in porous matrices. Matrices with optimized biocompatibility might eventually facilitate generation of axially vascularized bone tissue after injection of osteogenic cells in the AV loop model.

Azidothymidine Sensitizes Primary Effusion Lymphoma Cells to Kaposi Sarcoma-Associated Herpesvirus-Specific CD4+ T Cell Control and Inhibits vIRF3 Function - Williamson, Samantha J.; Nicol, Samantha M.; Stürzl, Michael; Sabbah, Shereen; Hislop, Andrew D. (PLoS Pathogens, 2016)
Kaposi sarcoma-associated herpesvirus (KSHV) is linked with the development of Kaposi sarcoma and the B lymphocyte disorders primary effusion lymphoma (PEL) and multi-centric Castleman disease. T cell immunity limits KSHV infection and disease, however the virus employs multiple mechanisms to inhibit efficient control by these effectors. Thus KSHV-specific CD4+ T cells poorly recognize most PEL cells and even where they can, they are unable to kill them. To make KSHV-infected cells more sensitive to T cell control we treated PEL cells with the thymidine analogue azidothymidine (AZT), which sensitizes PEL lines to Fas-ligand and TRAIL challenge; effector mechanisms which T cells use. PELs co-cultured with KSHV-specific CD4+ T cells in the absence of AZT showed no control of PEL outgrowth. However in the presence of AZT PEL outgrowth was controlled in an MHC-restricted manner. To investigate how AZT sensitizes PELs to immune control we first examined BJAB cells transduced with individual KSHV-latent genes for their ability to resist apoptosis mediated by stimuli delivered through Fas and TRAIL receptors. This showed that in addition to the previously described vFLIP protein, expression of vIRF3 also inhibited apoptosis delivered by these stimuli. Importantly vIRF3 mediated protection from these apoptotic stimuli was inhibited in the presence of AZT as was a second vIRF3 associated phenotype, the downregulation of surface MHC class II. Although both vFLIP and vIRF3 are expressed in PELs, we propose that inhibiting vIRF3 function with AZT may be sufficient to restore T cell control of these tumor cells.
EVALuna2:15266

Beta-6-Integrin serves as a novel tumor marker and therapeutic target for colorectal carcinoma - Bengs, Susan; Becker, Eugenia; Spalinger, Marianne R.; Raselli, Tina; Kasper, Stephanie; Lang, Silvia; Atrott, Kirstin; Mamie, Celine; Britzen-Laurent, Nathalie; Von Boehmer, Lotta; Knuth, Alexander; Tuomisto, Anne; et al. (2017)
EVALuna2:35840

Better Therapy for Pancreatic Cancer through More Radical Surgery? Bessere Therapie des Pankreaskarzinoms durch radikalere Chirurgie? - Brunner, Maximilian; Krautz, Christian; Grützmann, Robert; Weber, Georg (Zentralblatt für Chirurgie, 2022)
Despite advances in the treatment of pancreatic cancer, the survival of affected patients remains limited. A more radical surgical therapy could help to improve the prognosis, in particular by reducing the local recurrence rate, which is around 45% in patients with resected pancreatic cancer. In addition, patients with oligometastatic pancreatic cancer could also benefit from a more radical indication for surgery.Based on an analysis of the literature, important principles of pancreatic cancer surgery were examined.Even if even more radical surgical approaches such as an "extended" lymphadenectomy or a standard complete pancreatectomy do not bring any survival advantage, complete resection of the tumour (R0), a thorough locoregional lymphadenectomy and an adequate radical dissection in the area of the peripancreatic vessels including periarterial nerve plexuses should be the standard of pancreatic carcinoma resections. Whenever necessary to achieve an R0 resection, resections of the pancreas have to be extended, as well as additional venous vascular resections and multivisceral resections had to be performed. Simultaneous arterial vascular resections as part of pancreatic resections as well as surgical resections in oligometastatic patients should, however, be reserved for selected patients. These aspects of the surgical technique in pancreatic carcinoma mentioned above must not be neglected from the point of view of an "existing limited prognosis". On the contrary, they form the absolutely necessary basis in order to achieve good survival results in combination with system therapy. However, it may always be necessary to adapt these standards according to the age, comorbidities and wishes of the patient.
CRIS-Team Scopus Importer:2022-04-15

Big but weak: how many pathogenic genes does human herpesvirus-8 need to cause Kaposi's sarcoma? (Review). - Stürzl, Michael; Ensoli, Barbara (International Journal of Oncology, 1999)
Human herpesvirus-8 (HHV-8) is implicated in the pathogenesis of Kaposi's sarcoma (KS). In the last two years several HHV-8 gene products were heralded to 'cause KS' without any evidence that the respective gene is expressed in the tumor cells of KS lesions. In this framework it is of interest that almost 10% of the genes encoded by HHV-8 have been suggested to promote KS development due to either mitogenic, anti-apoptotic, chemoattractive, angiogenic or transforming activities. The rapidly growing number of HHV-8-encoded genes with 'KS causing' activities raises the question of why HHV-8 may need so many genes to trigger growth of KS that appears to be more closely related to a hyperplasia than to a real sarcoma. In this review an overview of the current knowledge of HHV-8 gene expressions in KS lesions in vivo is presented.

Biological roles of RNA m5C modification and its implications in Cancer immunotherapy - Song, Hang; Zhang, Jianye; Liu, Bin; Xu, Jing; Cai, Biao; Yang, Hai; Straube, Julia; Yu, Xiyong; Ma, Teng (Biomarker Research, 2022)
Epigenetics including DNA and RNA modifications have always been the hotspot field of life sciences in the post-genome era. Since the first mapping of N6-methyladenosine (m6A) and the discovery of its widespread presence in mRNA, there are at least 160-170 RNA modifications have been discovered. These methylations occur in different RNA types, and their distribution is species-specific. 5-methylcytosine (m5C) has been found in mRNA, rRNA and tRNA of representative organisms from all kinds of species. As reversible epigenetic modifications, m5C modifications of RNA affect the fate of the modified RNA molecules and play important roles in various biological processes including RNA stability control, protein synthesis, and transcriptional regulation. Furthermore, accumulative evidence also implicates the role of RNA m5C in tumorigenesis. Here, we review the latest progresses in the biological roles of m5C modifications and how it is regulated by corresponding “writers”, “readers” and “erasers” proteins, as well as the potential molecular mechanism in tumorigenesis and cancer immunotherapy.
CRIS-Team Scopus Importer:2022-04-15
Keywords: 5-methylcytosine (m; cancer immunotherapy; Epigenetics; Non-coding RNAs; RNA methylation modification

Biology of Kaposi's sarcoma. - Ensoli, Barbara; Sgadari, Cecilia; Barillari, Giovanni; Sirianni, Maria Caterina; Stürzl, Michael; Monini, Paolo (European Journal of Cancer, 2001)
Kaposi's sarcoma (KS) is an angioproliferative disease occurring in several different clinical-epidemiological forms that, however, share the same histological traits and are all associated with infection by the human herpesvirus 8 (HHV8). KS initiates in a context of immune dysregulation characterised by CD8+ T cell activation and the production of Th1-type cytokines that induce a generalised activation of endothelial cells leading to adhesion and tissue extravasation of lympho-monocytes, spindle cell formation and angiogenesis. These phenomena are triggered or enhanced by infection with HHV8 that, in turn, is reactivated by the same cytokines. Productively-infected circulating cells are recruited into 'activated' tissue sites where HHV8 finds an optimal environment for establishing a persistent, latent infection of KS spindle cells (KSC). HHV8 dissemination is favoured by virus escape mechanisms and immune dysregulation, and leads to immune responses that are not effective against the virus but, paradoxically, exacerbates the reactive process. Although early KS is a reactive process of polyclonal nature that can regress, in time it can progress in to a true sarcoma. The progression of KS appears to be due to the deregulated expression of oncogenes and oncosuppressor genes, to the long-lasting expression of the HHV8 latency genes and, for AIDS-KS, is promoted by the proliferative and angiogenic effects of the HIV-1 Tat protein.
Keywords: KS; Spindle cells; Inflammatory cytokines; Angiogenic factors; AIDS; HIV-1 Tat; HHV8; Angiogenesis; bcl-2; Immune evasion

Blood Vessel-Targeted Therapy in Colorectal Cancer: Current Strategies and Future Perspectives - Jacobsen, Anne; Siebler, Jürgen; Grützmann, Robert; Stürzl, Michael; Naschberger, Elisabeth (Cancers, 2024)
The vasculature is a key player and regulatory component in the multicellular microenvironment of solid tumors and, consequently, a therapeutic target. In colorectal carcinoma (CRC), antiangiogenic treatment was approved almost 20 years ago, but there are still no valid predictors of response. In addition, treatment resistance has become a problem. Vascular heterogeneity and plasticity due to species-, organ-, and milieu-dependent phenotypic and functional differences of blood vascular cells reduced the hope of being able to apply a standard approach of antiangiogenic therapy to all patients. In addition, the pathological vasculature in CRC is characterized by heterogeneous perfusion, impaired barrier function, immunosuppressive endothelial cell anergy, and metabolic competition-induced microenvironmental stress. Only recently, angiocrine proteins have been identified that are specifically released from vascular cells and can regulate tumor initiation and progression in an autocrine and paracrine manner. In this review, we summarize the history and current strategies for applying antiangiogenic treatment and discuss the associated challenges and opportunities, including normalizing the tumor vasculature, modulating milieu-dependent vascular heterogeneity, and targeting functions of angiocrine proteins. These new strategies could open perspectives for future vascular-targeted and patient-tailored therapy selection in CRC.
CRIS-Team Scopus Importer:2024-03-22
Keywords: aflibercept; angiocrine; antiangiogenic treatment; bevacizumab; cancer; colorectal cancer; endothelial cells; fruquintinib; ramucirumab; regorafenib; tumor microenvironment; vascular heterogeneity; vasculature

Branch duct intraductal papillary mucinous neoplasm - contra resection - Brunner, Michaela; Kersting, S.; Grützmann, Robert; Weber, Georg (Chirurg, 2017)
Due to improvements in imaging modalities the diagnosis of branch duct intraductal papillary mucinous neoplasms (BD-IPMN) has been significantly increased in recent years. A BD-IPMN is frequently diagnosed as an incidental finding in asymptomatic patients. The optimal management of BD-IPMN is the subject of controversial discussions. Numerous studies have shown that an individualized therapeutic strategy with a follow-up observation of most BD-IPMNs is feasible and safe, considering age, comorbidities and patient preference. An accurate evaluation of BD-IPMN with a detailed anamnesis, high-resolution imaging techniques and endoscopic ultrasound is necessary. Symptomatic patients as well as patients with so-called high-risk stigmata should undergo resection. Asymptomatic patients with so-called worrisome features can either undergo surveillance or surgical resection, taking age and comorbidities into account. For BD-IPMN patients without high-risk stigmata and worrisome features and showing no symptoms, surveillance of the pancreatic lesion is the preferred approach. The high prevalence of BD-IPMN, limitations in differential diagnostics, an overestimation of the risk of malignancy due to an overrepresentation of symptomatic and suspected BD-IPMN in resected cohorts, an overestimated role of BD-IPMN as precursor lesions for pancreatic carcinoma and evidence of the safety of follow-up surveillance, underline the enormous importance of surveillance. Based on this and considering the background of a notable mortality and morbidity of pancreatic surgery, aggressive management with prophylactic surgical resection is not justified for all BD-IPMN, in particular for low-risk lesions.
EVALuna2:15288

Cancer is associated with alterations in the three-dimensional organization of the genome - Li, Lifei; Barth, Nicolai; Pilarsky, Christian; Taher, Leila (Cancers, 2019)
The human genome is organized into topologically associating domains (TADs), which represent contiguous regions with a higher frequency of intra-interactions as opposed to inter-interactions. TADs contribute to gene expression regulation by restricting the interactions between their regulatory elements, and TAD disruption has been associated with cancer. Here, we provide a proof of principle that mutations within TADs can be used to predict the survival of cancer patients. Specifically, we constructed a set of 1467 consensus TADs representing the three-dimensional organization of the human genome and used Cox regression analysis to identify a total of 35 prognostic TADs in different cancer types. Interestingly, only 46% of the 35 prognostic TADs comprised genes with known clinical relevance. Moreover, in the vast majority of such cases, the prognostic value of the TAD was not directly related to the presence/absence of mutations in the gene(s), emphasizing the importance of regulatory mutations. In addition, we found that 34% of the prognostic TADs show strong structural perturbations in the cancer genome, consistent with the widespread, global epigenetic dysregulation often observed in cancer patients. In summary, this study elucidates the mechanisms through which non-coding variants may influence cancer progression and opens new avenues for personalized medicine.
CRIS-Team Scopus Importer:2019-12-10
Keywords: Biomarkers; Cancer; Copy number variants (CNVs); LASSO cox regression analysis; The cancer genome atlas (TCGA); Topologically associating domains (TADs)

Can clinicopathological parameters predict for lymph node metastases in ypT0-2 rectal carcinoma? Results of the CAO/ARO/AIO-94 and CAO/ARO/AIO-04 phase 3 trials - Von Den Gruen, Jens Mueller; Hartmann, Arndt; Fietkau, Rainer; Ghadimi, Michael; Liersch, Torsten; Hohenberger, Werner; Weitz, Jurgen; Sauer, Rolf; Wittekind, Christian; Stroebel, Philipp; Roedel, Claus; Fokas, Emmanouil (Radiotherapy and Oncology, 2018)
BACKGROUND: The advent of less radical surgical approaches has generated concern about leaving locoregional lymph node metastases (LNM) unresected that could lead to adverse outcome. We examined the prognostic role of clinicopathological factors for ypN-positivity in patients with ypT0-2 rectal carcinoma treated within the CAO/ARO/AIO-94 and CAO/ARO/AIO-04 randomized phase 3 trials. METHODS: The correlation of clinicopathological factors with ypN-status (ypN0 vs ypN1/2) was examined in n = 776 patients with ypT0-2 rectal carcinoma after preoperative CRT and total mesorectal excision surgery using Pearson's Chi-squared test for categorical variables and Kruskal-Wallis' test for continuous variables. Multivariable analysis was performed using binary logistic regression to identify independent prognosticators for ypN-positivity. RESULTS: Residual LNM (ypN+) were found in 6%, 20.8% and 21.4% of patients with ypT0, ypT1 and ypT2 carcinomas, respectively. Independent prognosticators for LNM were advanced ypT category (p = 0.002) and lymphatic invasion (p = 0.020). In a separate multivariable analysis performed upon exclusion of ypT-category due to multicollinearity with residual tumor diameter (RTD), lymphatic invasion (p = 0.015) and RTD ≥10 mm (p = 0.005) demonstrated strong correlation with LNM. CONCLUSION: Advanced ypT-stage, lymphatic invasion and RTD ≥10 mm were prognostic factors for LNM in patients ypT0-2 rectal carcinoma treated with CRT and surgery within both phase 3 trials. The high incidence of LNM in the ypT1-2 group needs to be taken into consideration in the context of oncological safety and indicate that LE should be advocated with great caution in this patient subgroup. The prognostic pathological factor identified here could help guide decision of LE vs TME after standard CRT.
EVALuna2:34854

CD71 expressing circulating neutrophils serve as a novel prognostic biomarker for metastatic spread and reduced outcome in pancreatic ductal adenocarcinoma patients - Hansen, Frederik; Mittelstädt, Anke; Clausen, Finn-Niklas; Knoedler, Samuel; Knoedler, Leonard; Klöckner, Sebastian; Kuchenreuther, Isabelle; Mazurie de Keroualin, Johanne; Arnold, Lisa-Sophie; Anthuber, Anna; Jacobsen, Anne; Merkel, Susanne; et al. (Scientific Reports, 2024)
Pancreatic ductal adenocarcinoma (PDAC) is one of the most lethal malignancies, presenting a persisting global health burden. Neutrophils have a double-edged role in tumor progression exhibiting both pro-tumor and anti-tumor functions. CD71, also known as transferrin receptor 1, performs a critical role in cellular iron uptake and is highly expressed on proliferating cells, and especially on activated immune cells. CD71 is known to be elevated in various types of solid cancers and is associated with poor prognosis, however, the expression of CD71 on neutrophils in PDAC and its potential clinical impact is still unknown. Therefore, we analyzed CD71 on circulating neutrophils in PDAC and clinical control patients and found a significant increased expression in PDAC patients. High expression of CD71 on neutrophils in PDAC patients was associated with reduced outcome compared to low expression. CD71 on neutrophils correlated positively with the levels of proinflammatory cytokines IL-6, IFN-γ, and growth factor ligands CD40-L, and BAFF in plasma of PDAC patients. Finally, we have demonstrated that high expression of CD71 on neutrophils was also associated with an increased expression of CD39 and CD25 on circulating T-cells. Based on our findings, we hypothesize that CD71 on neutrophils is associated with tumor progression in PDAC. Further studies are required to investigate the distinct functionality of CD71 expressing neutrophils and their potential clinical application.
CRIS-Team Scopus Importer:2024-09-20
Keywords: CD71; Metastatic spread; Neutrophils; Pancreatic ductal adenocarcinoma; Prognostic biomarker; Transferrin receptor 1

CDK7 inhibition augments response to multidrug chemotherapy in pancreatic cancer - Zeng, Siyuan; Lan, Bin; Ren, Xiaofan; Zhang, Shuman; Schreyer, Daniel; Eckstein, Markus; Yang, Hai; Britzen-Laurent, Nathalie; Dahl, Andreas; Mukhopadhyay, Debabrata; Chang, David; Kutschick, Isabella; et al. (Journal of Experimental & Clinical Cancer Research, 2022)
Background: Pancreatic ductal adenocarcinoma (PDAC) is an aggressive cancer with a dismal prognosis. Although combined treatment with gemcitabine and albumin-bound paclitaxel has improved the prognosis of PDAC, both intrinsic and acquired chemoresistance remain as severe hurtles towards improved prognosis. Thus, new therapeutic targets and innovative strategies are urgently needed. Methods: In this study, we used the KPC mouse model-derived PDAC cell line TB32047 to perform kinome-wide CRISPR-Cas9 loss-of-function screening. Next-generation sequencing and MAGeCK-VISPR analysis were performed to identify candidate genes. We then conducted cell viability, clonogenic, and apoptosis assays and evaluated the synergistic therapeutic effects of cyclin-dependent kinase 7 (CDK7) depletion or inhibition with gemcitabine (GEM) and paclitaxel (PTX) in a murine orthotopic pancreatic cancer model. For mechanistic studies, we performed genome enrichment analysis (GSEA) and Western blotting to identify and verify the pathways that render PDAC sensitive to GEM/PTX therapy. Results: We identified several cell cycle checkpoint kinases and DNA damage-related kinases as targets for overcoming chemoresistance. Among them, CDK7 ranked highly in both screenings. We demonstrated that both gene knockout and pharmacological inhibition of CDK7 by THZ1 result in cell cycle arrest, apoptosis induction, and DNA damage at least predominantly through the STAT3-MCL1-CHK1 axis. Furthermore, THZ1 synergized with GEM and PTX in vitro and in vivo, resulting in enhanced antitumor effects. Conclusions: Our findings support the application of CRISPR-Cas9 screening in identifying novel therapeutic targets and suggest new strategies for overcoming chemoresistance in pancreatic cancer.
CRIS-Team Scopus Importer:2022-08-19
Keywords: CDK7; CRISPR-Cas9; FOLFIRINOX; Gemcitabine; Paclitaxel; THZ1

Cell death inhibition by KSHV - Murtadak, Vinay; Becker, Christoph; Stürzl, Michael (Aging-Us, 2015)
EVALuna2:1975

Cellular and molecular features of HIV-associated Kaposi's sarcoma. - Roth, Willi Kurt; Brandstetter, Heinz; Stürzl, Michael (Aids, 1992)

Centrosomal protein TRIM43 restricts herpesvirus infection by regulating nuclear lamina integrity - Full, Florian; Van Gent, Michiel; Sparrer, Konstantin M. J.; Chiang, Cindy; Zurenski, Matthew A.; Scherer, Myriam; Brockmeyer, Norbert H.; Heinzerling, Lucie; Stürzl, Michael; Korn, Klaus; Stamminger, Thomas; Enßer, Armin; et al. (Nature Microbiology, 2019)
Tripartite motif (TRIM) proteins mediate antiviral host defences by either directly targeting viral components or modulating innate immune responses. Here we identify a mechanism of antiviral restriction in which a TRIM E3 ligase controls viral replication by regulating the structure of host cell centrosomes and thereby nuclear lamina integrity. Through RNAi screening we identified several TRIM proteins, including TRIM43, that control the reactivation of Kaposi's sarcoma-associated herpesvirus. TRIM43 was distinguished by its ability to restrict a broad range of herpesviruses and its profound upregulation during herpesvirus infection as part of a germline-specific transcriptional program mediated by the transcription factor DUX4. TRIM43 ubiquitinates the centrosomal protein pericentrin, thereby targeting it for proteasomal degradation, which subsequently leads to alterations of the nuclear lamina that repress active viral chromatin states. Our study identifies a role of the TRIM43-pericentrin-lamin axis in intrinsic immunity, which may be targeted for therapeutic intervention against herpesviral infections.
EVALuna2:35255

Changing paradigm of sacral neuromodulation and external anal sphincter repair for faecal incontinence in specialist centres - Ong, Kelly; Bordeianou, L.; Brunner, Maximilian; Buntzen, S.; Collie, M. H. S.; Hanly, A.; Hunt, C. W.; Matzel, Klaus; O'Connell, P. R.; Rydningen, M.; Savitt, L.; Totaro, A.; et al. (Colorectal Disease, 2020)
Aim: The aim of this study was to determine whether the paradigm of surgical intervention for faecal incontinence (FI) has changed between 2000 and 2013. Method: This was a multi-centre retrospective study of patients who had undergone either sacral neuromodulation (SNM) or delayed sphincter repair or sphincteroplasty (SR) as a primary surgical intervention for FI in five centres in Europe and one in the United States. The flow of patients according to the intervention, sustainability of the treatment at a minimum follow-up of 5 years, complications and requirement for further interventions were recorded. Results: A total of 461 patients (median age 56 years, range 24–90 years, 41 men) had either SNM or SR as an index operation during the study period [SNM 284 (61.6%), SR 177 (38.4%)]. Among SNM patients, there were 169 revisional operations (change of battery and/or lead, re-siting or removal). At the time of last follow-up 203 patients (71.4%) continued to use SNM. Among SR patients, 30 (16.9%) had complications, most notably wound infection (22, 12.4%). During follow-up 32 patients (18.1%) crossed over to SNM. Comparing two 4-year periods (2000–2003 and 2007–2010), the proportion of patients operated on who had a circumferential sphincter defect of less than 90° was 48 (68%) and 45 (46%), respectively (P = 0.03), while those who had SNM as the primary intervention increased from 29% to 89% (P < 0.05). Conclusion: The paradigm of surgical intervention for FI has changed with increasing use of SNM.
CRIS-Team Scopus Importer:2020-10-02
Keywords: faecal incontinence; sacral nerve stimulation; sacral neuromodulation; sphincter repair; sphincteroplasty

Chemoradiotherapy plus induction or consolidation chemotherapy as total neoadjuvant therapy for locally advanced rectal cancer: Final results of the CAO/ARO/AIO-12 randomized phase 2 trial - Fokas, E.; Schlenska-Lange, A.; Polat, B.; Klautke, G.; Grabenbauer, G.; Fietkau, Rainer; Kuhnt, T.; Staib, L.; Brunner, T.; Grosu, A. -L.; Kirste, S.; Jacobasch, L.; et al. (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Chemoradiotherapy plus induction or consolidation chemotherapy as total neoadjuvant therapy for locally advanced rectal cancer: Pooled analysis of the CAO/ARO/AIO-12 and the OPRA randomized phase 2 trials - Fokas, Emmanouil; Williams, Hannah; Diefenhardt, Markus; Lin, Sabrina; Qin, Li Xuan; Piso, Pompiliu; Dapper, Hendrik; Germer, Christoph Thomas; Grützmann, Robert; Tim Friede, J.; Joshua Smith, J.; Saltz, Leonard B.; et al. (European Journal of Cancer, 2024)
Background: Total neoadjuvant therapy (TNT) has been used for patients with locally advanced rectal cancer. The optimal sequence of chemoradiotherapy (CRT) and chemotherapy (CT) is a matter of debate. Methods: We performed a pooled analysis of the CAO/ARO/AIO-12 and OPRA multicenter, randomized phase 2 trials to identify patient subsets that could benefit from one TNT sequence over the other regarding disease-free survival (DFS). Patients with stage II/III rectal cancer were randomized to CRT (50.4–54 Gy) with either induction (INCT-CRT) or consolidation CT (CRT-CNCT) with fluorouracil, leucovorin, oxaliplatin (CAO/ARO/AIO-12 and OPRA) or capecitabine and oxaliplatin (OPRA) followed by mandatory total mesorectal excision (TME) (CAO/ARO/AIO-12) or selective watch-and-wait surveillance (OPRA). 311 and 324 patients were recruited from June 15, 2015 to January 31, 2018; and from April 12, 2014 to March 30, 2020 in the two trials, respectively. Pretreatment clinical and tumor characteristics included were age, sex, ECOG, cT-category, cN-category, clinical UICC stage, location from anal verge, and tumor grade. Findings: In total, 628 eligible patients were included in the pooled analysis (CAO/ARO/AIO-12, n = 304; OPRA, n = 324). Of those, 313 were randomly assigned to the INCT-CRT group, and 315 to the CRT-CNCT group. Median follow-up was 43 months (IQR, 35–49) months in the CAO/ARO/AIO-12 trial and 61,2 months (IQR, 42–68,4) in the OPRA trial. Pooled analysis of baseline clinical and tumor characteristics did not identify any subgroups of patients that would benefit by the one TNT sequence over the other with regard to DFS. Interpretation: To our knowledge, this is the first pooled analysis of two randomized trials after direct head-to-head comparison of both TNT sequences. Both trials reported higher rates of complete response with CRT-CNCT, and this should be considered the preferred TNT sequence if organ preservation is a priority.
CRIS-Team Scopus Importer:2024-09-13
Keywords: Oncological guidelines; Pooled analysis; Randomized trials; Rectal cancer; Sequence; Total neoadjuvant treatment

Chemoradiotherapy Plus Induction or Consolidation Chemotherapy as Total Neoadjuvant Therapy for Patients With Locally Advanced Rectal Cancer Long-term Results of the CAO/ARO/AIO-12 Randomized Clinical Trial - Fokas, Emmanouil; Schlenska-Lange, Anke; Polat, Buelent; Klautke, Gunther; Grabenbauer, Gerhard G.; Fietkau, Rainer; Kuhnt, Thomas; Staib, Ludger; Brunner, Thomas; Grosu, Anca-Ligia; Kirste, Simon; Jacobasch, Lutz; et al. (JAMA Oncology, 2021)
IMPORTANCE Total neoadjuvant therapy has been increasingly adopted for multimodal rectal cancer treatment. The optimal sequence of chemoradiotherapy (CRT) and chemotherapy needs to be established.
CRIS-Team WoS Importer:2021-12-10

Chemoradiotherapy plus induction versus consolidation chemotherapy as total neoadjuvant therapy for locally advanced rectal cancer: results of the German CAO/ARO/AIO-12 multicentre, open-label, randomised, phase 2 trial - Fokas, E.; Allgaeuer, M.; Polat, B.; Klautke, G.; Grabenbauer, G.; Fietkau, Rainer; Kuhnt, T.; Staib, L.; Brunner, T.; Grosu, A-L; Schmiegel, W.; Jacobasch, L.; et al. (STRAHLENTHERAPIE UND ONKOLOGIE, 2019)
CRIS-Team WoS Importer:2019-06-07

Chemoradiotherapy with and without deep regional hyperthermia for squamous cell carcinoma of the anus - Ott, Oliver J.; Schmidt, Manfred; Semrau, Sabine; Strnad, Vratislav; Matzel, Klaus E.; Schneider, Ignaz Hans Friedrich; Raptis, Dimitrios; Uter, Wolfgang; Grützmann, Robert; Fietkau, Rainer (Strahlentherapie und Onkologie, 2018)
PURPOSE: To compare results after chemoradiotherapy with and without deep regional hyperthermia in patients with anal cancer. METHODS: Between 2000 and 2015, a total of 112 consecutive patients with UICC stage I-IV anal cancer received chemoradiotherapy with 5‑fluororuracil and mitomycin C (CRT). In case of insufficient tumor response 4-6 weeks after chemoradiotherapy, patients received an interstitial pulsed-dose-rate brachytherapy boost. Additionally, 50/112 patients received hyperthermia treatments (HCRT). RESULTS: Median follow-up was 41 (2-165) months. After 5 years follow-up, overall (95.8 vs. 74.5%, P = 0.045), disease-free (89.1 vs. 70.4%, P = 0.027), local recurrence-free (97.7 vs. 78.7%, P = 0.006), and colostomy-free survival rates (87.7 vs. 69.0%, P = 0.016) were better for the HCRT group. Disease-specific, regional failure-free, and distant metastasis-free survival rates showed no significant differences. The adjusted hazard ratios for death were 0.25 (95% CI, 0.07 to 0.92; P = 0.036) and for local recurrence 0.14 (95% CI, 0.02 to 1.09; P = 0.06), respectively. Grades 3-4 early toxicities were comparable with the exception of hematotoxicity, which was higher in the HCRT group (66 vs. 43%, P = 0.032). Incidences of late side effects were similar with the exception of a higher telangiectasia rate in the HCRT group (38.0 vs. 16.1%, P = 0.009). CONCLUSION: Additional regional hyperthermia improved overall survival, local control, and colostomy rates. Its potential beneficial role has to be confirmed in a prospective randomized setting. Therefore, the HyCAN trial has already been established by our group and is currently recruiting patients (Clinicaltrials.gov identifier: NCT02369939).
EVALuna2:36451

Chemoradiotherapy with and without deep regional hyperthermia for squamous cell carcinoma of the anus - Ott, O. J.; Schmidt, M.; Semrau, S.; Strnad, Vratislav; Matzel, K. E.; Schneider, I.; Raptis, D.; Uter, Wolfgang; Grützmann, Robert; Fietkau, Rainer (STRAHLENTHERAPIE UND ONKOLOGIE, 2019)
CRIS-Team WoS Importer:2019-06-07

Chemoresistance in Pancreatic Cancer - Zeng, Siyuan; Pöttler, Marina; Lan, Bin; Grützmann, Robert; Pilarsky, Christian; Yang, Hai (International Journal of Molecular Sciences, 2019)
Pancreatic ductal adenocarcinoma (PDAC), generally known as pancreatic cancer (PC), ranks the fourth leading cause of cancer-related deaths in the western world. While the incidence of pancreatic cancer is displaying a rising tendency every year, the mortality rate has not decreased significantly because of late diagnosis, early metastasis, and limited reaction to chemotherapy or radiotherapy. Adjuvant chemotherapy after surgical resection is typically the preferred option to treat early pancreatic cancer. Although 5-fluorouracil/leucovorin with irinotecan and oxaliplatin (FOLFIRINOX) and gemcitabine/nab-paclitaxel can profoundly improve the prognosis of advanced pancreatic cancer, the development of chemoresistance still leads to poor clinical outcomes. Chemoresistance is multifactorial as a result of the interaction among pancreatic cancer cells, cancer stem cells, and the tumor microenvironment. Nevertheless, more pancreatic cancer patients will benefit from precision treatment and targeted drugs. Therefore, we outline new perspectives for enhancing the efficacy of gemcitabine after reviewing the related factors of gemcitabine metabolism, mechanism of action, and chemoresistance.
CRIS-Team Scopus Importer:2019-09-20
Keywords: chemoresistance; FOLFIRINOX; gemcitabine; pancreatic cancer; PDAC

Chemo-RT plus induction or consolidation chemotherapy for rectal cancer: a randomised phase 2 trial - Fokas, E.; Allgaeuer, M.; Polat, B.; Klautke, G.; Grabenbauer, G.; Fietkau, Rainer; Kuhnt, T.; Staib, L.; Brunner, T.; Grosu, A. L.; Schmiegel, W.; Jacobasch, L.; et al. (RADIOTHERAPY AND ONCOLOGY, 2019)
CRIS-Team WoS Importer:2019-06-18

Chronic intestinal inflammation in mice expressing viral Flip in epithelial cells - Ruder, Barbara; Murtadak, Vinay; Stürzl, Michael; Wirtz, Stefan; Distler, Ute; Tenzer, Stefan; Mahapatro, Mousumi; Greten, Florian R.; Hu, Yinling; Neurath, Markus; Cesarman, Ethel; Ballon, Gianna; et al. (Mucosal Immunology, 2018)
Viruses are present in the intestinal microflora and are currently discussed as a potential causative mechanism for the development of inflammatory bowel disease. A number of viruses, such as Human Herpesvirus-8, express homologs to cellular FLIPs, which are major contributors for the regulation of epithelial cell death. In this study we analyzed the consequences of constitutive expression of HHV8-viral FLIP in intestinal epithelial cells (IECs) in mice. Surprisingly, expression of vFlip disrupts tissue homeostasis and induces severe intestinal inflammation. Moreover vFlipIEC-tg mice showed reduced Paneth cell numbers, associated with excessive necrotic cell death. On a molecular level vFlip expression altered classical and alternative NFκB activation. Blocking of alternative NFκB signaling by deletion of Ikka in vivo largely protected mice from inflammation and Paneth cell loss induced by vFLIP. Collectively, our data provide functional evidence that expression of a single viral protein in IECs can be sufficient to disrupt epithelial homeostasis and to initiate chronic intestinal inflammation.
EVALuna2:35131

Cinematic Rendering in Anatomy: A Crossover Study Comparing a Novel 3D Reconstruction Technique to Conventional Computed Tomography - Binder, Johannes; Scholz, Michael; Ellmann, Stephan; Uder, Michael; Grützmann, Robert; Krautz, Christian; Weber, Georg (Anatomical Sciences Education, 2020)
Integration of medical imaging into preclinical anatomy courses is already underway in many medical schools. However, interpretation of two-dimensional grayscale images is difficult and conventional volume rendering techniques provide only images of limited quality. In this regard, a more photorealistic visualization provided by Cinematic Rendering (CR) may be more suitable for anatomical education. A randomized, two-period crossover study was conducted from July to December 2018, at the University Hospital of Erlangen, Germany to compare CR and conventional computed tomography (CT) imaging for speed and comprehension of anatomy. Sixteen students were randomized into two assessment sequences. During each assessment period, participants had to answer 15 anatomy-related questions that were divided into three categories: parenchymal, musculoskeletal, and vascular anatomy. After a washout period of 14 days, assessments were crossed over to the respective second reconstruction technique. The mean interperiod differences for the time to answer differed significantly between the CR-CT sequence (-204.21 +/- 156.0 seconds) and the CT-CR sequence (243.33 +/- 113.83 seconds;P < 0.001). Overall time reduction by CR was 65.56%. Cinematic Rendering visualization of musculoskeletal and vascular anatomy was higher rated compared to CT visualization (P P = 0.003), whereas CT visualization of parenchymal anatomy received a higher scoring than CR visualization (P < 0.001). No carryover effects were observed. A questionnaire revealed that students consider CR to be beneficial for medical education. These results suggest that CR has a potential to enhance knowledge acquisition and transfer from medical imaging data in medical education.
CRIS-Team WoS Importer:2020-07-17

Circulating Monocytes Serve as Novel Prognostic Biomarker in Pancreatic Ductal Adenocarcinoma Patients - Hansen, Frederik; David, Paul; Akram, Marina; Knoedler, Samuel; Mittelstädt, Anke; Merkel, Susanne; Podolska, Malgorzata; Swierzy, Izabela; Roßdeutsch, Lotta; Klösch, Bettina; Kouhestani, Dina; Anthuber, Anna; et al. (Cancers, 2023)
Pancreatic ductal adenocarcinoma (PDAC) ranks among the most fatal cancer diseases, widely accepted to have the most dismal prognoses. Although immunotherapy has broadly revolutionized cancer treatment, its value in PDAC appears to be relatively low. Exhibiting protumoral effects, monocytes have recently been proposed as potential targets of such immunotherapeutic regimens. However, to date, the body of evidence on monocytes’ role in PDAC is scarce. Therefore, we analyzed monocytes in the peripheral blood of 58 PDAC patients prior to surgery and compared them to healthy individuals. PDAC patients showed increased levels of monocytes when compared to healthy controls In addition, patients with perineural infiltration demonstrated a higher percentage of monocytes compared to non-infiltrating tumors and PDAC G3 was associated with higher monocyte levels than PDAC G2. Patients with monocyte levels > 5% were found to have an 8.9-fold increased risk for a G3 and perineural infiltrated PDAC resulting in poorer survival compared to patients with <5% monocyte levels. Furthermore, PDAC patients showed increased expressions of CD86 and CD11c and decreased expressions of PD-L1 on monocytes compared to healthy individuals. Finally, levels of monocytes correlated positively with concentrations of IL-6 and TNF-α in plasma of PDAC patients. Based on our findings, we propose monocytes as a novel prognostic biomarker. Large-scale studies are needed to further decipher the role of monocytes in PDAC and investigate their potential as therapeutic targets.
CRIS-Team Scopus Importer:2023-02-03
Keywords: grading; liquid biopsy; monocytes; pancreatic ductal adenocarcinoma; perineural invasion; prognostic biomarker

Clearance of human herpesvirus 8 from blood and regression of leukopenia-associated aggressive classic Kaposi's sarcoma during interferon-alpha therapy: a case report. - Monini, Paolo; Sirianni, Maria Caterina; Franco, Marina; Vincenzi, Laura; Topino, Simone; Goletti, Delia; Leone, Patrizia; Leone, Pasqualina; Chiozzini, Chiara; Nicastri, Emanuele; Andreoni, Massimo; Borduagni, Osvaldo; et al. (Clinical Infectious Diseases, 2001)
A human immunodeficiency virus-negative woman with severe classic Kaposi's sarcoma, idiopathic leukopenia, and massive spread of human herpesvirus 8 (HHV-8) in circulating cells showed stable disease remission in response to systemic interferon-alpha treatment that was accompanied by increased CD3(+) and CD4(+) T cell numbers and complete clearance of HHV-8 from the circulation. These results suggest a direct relationship between HHV-8 clearance from blood and regression of Kaposi's sarcoma and are consistent with the in vitro inhibitory effects of interferon-alpha on HHV-8 infection.

Clinical outcome after total neoadjuvant treatment (CAO/ARO/AIO-12) versus intensified neoadjuvant and adjuvant treatment (CAO/ARO/AIO 04) a comparison between two multicenter randomized phase II/III trials - Diefenhardt, Markus; Fleischmann, Maximillian; Martin, Daniel; Hofheinz, Ralf-Dieter; Piso, Pompiliu; Germer, Christoph-Thomas; Hambsch, Peter; Grützmann, Robert; Kirste, Simon; Schlenska-Lange, Anke; Ghadimi, Michael; Roedel, Claus; et al. (Radiotherapy and Oncology, 2023)
Background: Total neoadjuvant therapy (TNT) can enhance local tumor regression, but its survival bene-fits compared to intensified chemoradiotherapy (CRT) followed by adjuvant chemotherapy (CT) remain unclear.Methods: This is a secondary comparison between 607 patients treated with intensified 5-FU/Oxaliplatin neoadjuvant CRT and adjuvant CT within the experimental arm of the CAO/ARO/AIO-04 phase III trial, and 306 patients treated with TNT within the CAO/ARO/AIO-12 phase II trial. Comparison between clinical-pathological characteristics, surgical quality, and post-surgical complications were analyzed using the Pearson's Chi-squared or Mann-Whitney U test. Oncological outcome was examined with log-rank, Gray's test, and multivariate cox regression. In addition, further subgroup analyses and propensity score matching were performed to optimize the balance of baseline covariates.Findings: Patients treated with CRT followed by consolidation CT had a significantly higher rate of patho-logical complete remission (pCR) compared to patients treated within the experimental arm of the CAO/ ARO/AIO-04 trial (25.3 % vs 17.3 %, P = 0.04). Post-surgical complications were less common in the CAO/ ARO/AIO-12 trial. After a median follow-up of 46 months, clinical outcome did not differ significantly in the overall cohort, in any subgroup or after propensity score matching. In multivariate analysis, disease-free survival (DFS) was similar between the experimental arm of the CAO/ARO/AIO-04 trial and treat-ments arms of the CAO/ARO/AIO-12 trial (vs arm A: HR 0.92 [95 % CI 0.62-1.37], P = 0.69; vs arm B: HR 1.06 [95 % CI 0.72-1.58], P = 0.76).Interpretation: Notwithstanding the limitations of intertrial comparison, TNT did not improve long term oncological outcome in our study compared to the intensified neoadjuvant CRT and adjuvant CT treat-ment in the CAO/ARO/AIO-04 trial. Improved response rates after TNT offers an attractive option to explore organ preservation in selective patients with locally advanced rectal cancer.(c) 2022 Elsevier B.V. All rights reserved. Radiotherapy and Oncology 179 (2023) 109455
CRIS-Team WoS Importer:2023-03-03

Clinical Performance of the Consensus Immunoscore in Colon Cancer in the Asian Population from the Multicenter International SITC Study - Mlecnik, Bernhard; Torigoe, Toshihiko; Bindea, Gabriela; Popivanova, Boryana; Xu, Mingli; Fujita, Tomonobu; Hazama, Shoichi; Suzuki, Nobuaki; Nagano, Hiroaki; Okuno, Kiyotaka; Hirohashi, Yoshihiko; Furuhata, Tomohisa; et al. (Cancers, 2022)
BACKGROUND: In this study, we evaluated the prognostic value of Immunoscore in patients with stage I–III colon cancer (CC) in the Asian population. These patients were originally included in an international study led by the Society for Immunotherapy of Cancer (SITC) on 2681 patients with AJCC/UICC-TNM stages I–III CC. METHODS: CD3+ and cytotoxic CD8+ T-lymphocyte densities were quantified in the tumor and invasive margin by digital pathology. The association of Immunoscore with prognosis was evaluated for time to recurrence (TTR), disease-free survival (DFS), and overall survival (OS). RESULTS: Immunoscore stratified Asian patients (n = 423) into different risk categories and was not impacted by age. Recurrence-free rates at 3 years were 78.5%, 85.2%, and 98.3% for a Low, Intermediate, and High Immunoscore, respectively (HR[Low-vs-High] = 7.26 (95% CI 1.75−30.19); p = 0.0064). A High Immunoscore showed a significant association with prolonged TTR, OS, and DFS (p < 0.05). In Cox multivariable analysis stratified by center, Immunoscore association with TTR was independent (HR[Low-vs-Int+High] = 2.22 (95% CI 1.10–4.55) p = 0.0269) of the patient’s gender, T-stage, N-stage, sidedness, and MSI status. A significant association of a High Immunoscore with prolonged TTR was also found among MSS (HR[Low-vs-Int+High] = 4.58 (95% CI 2.27−9.23); p ≤ 0.0001), stage II (HR[Low-vs-Int+High] = 2.72 (95% CI 1.35−5.51); p = 0.0052), low-risk stage-II (HR[Low-vs-Int+High] = 2.62 (95% CI 1.21−5.68); p = 0.0146), and high-risk stage II patients (HR[Low-vs-Int+High] = 3.11 (95% CI 1.39−6.91); p = 0.0055). CONCLUSION: A High Immunoscore is significantly associated with the prolonged survival of CC patients within the Asian population.
CRIS-Team Scopus Importer:2022-10-07
Keywords: Asian; classification; colon cancer; immune response; Immunoscore; MSI; prognostic markers; risk stratification; T cell; tumor microenvironment

c-Met and PD-L1 on Circulating Exosomes as Diagnostic and Prognostic Markers for Pancreatic Cancer - Lux, Alexander; Kahlert, Christoph; Grützmann, Robert; Pilarsky, Christian (International Journal of Molecular Sciences, 2019)
Exosomes are membrane vesicles which offer potential as blood derived biomarkers for malign tumors in clinical practice. Pancreatic cancer is counted among cancer diseases with the highest mortality. The present work seeks to assess whether pancreatic carcinomas release exosomes which express c-Met (proto-oncogene mesenchymal-epithelial transition factor) and PD-L1 (programmed cell death 1 ligand 1), and whether the detection of such expression in serum has diagnostic or prognostic meaning for the affected patients. Exosome isolation was performed on culture media of one benign pancreatic cell line and ten pancreatic carcinoma cell lines as well as on serum samples from 55 patients with pancreatic ductal adenocarcinoma (PDAC), 26 patients with chronic pancreatitis and 10 patients with benign serous cyst adenoma of the pancreas. Exosomes were bound to latex beads and stained with antibodies against c-Met or PD-L1. Analysis of fluorescence intensity was performed by flow cytometry. In terms of c-Met, the mean fluorescence intensity of PDAC-patients was significantly higher than the fluorescence intensity of the comparative patients with benign disease (p < 0.001). A diagnostic test based on c-Met resulted in a sensitivity of 70%, a specificity of 85% and a diagnostic odds ratio of 13:2. The specificity of the test can be further improved by combining it with the established tumor marker carbohydrate antigen 19-9 (CA 19-9). In addition, c-Met-positive patients showed a significantly shorter postoperative survival time (9.5 vs. 21.7 months, p < 0.001). In terms of PD-L1, no significant difference between fluorescence intensity of PDAC-patients and comparative patients was detectable. However, PD-L1-positive PDAC-patients also showed a significantly shorter postoperative survival time (7.8 vs. 17.2 months, p = 0.043). Thus, both markers can be considered as negative prognostic factors.
CRIS-Team Scopus Importer:2019-07-30
Keywords: c-Met; chronic pancreatitis; exosomes; pancreatic cancer; PD-L1; PDAC; serous cyst adenoma

Cocultivation of Mesenchymal Stem Cells and Endothelial Progenitor Cells Reveals Antiapoptotic and Proangiogenic Effects - Steiner, Dominik; Köhn, Katrin; Beier, Justus; Stürzl, Michael; Horch, Raymund E.; Arkudas, Andreas (Cells Tissues Organs, 2017)
Integrating bioartificial tissues into the host vasculature is a prerequisite for tissue engineering applications. Endothelial progenitor cells (EPCs) display a high angiogenic potential and a low donor-site morbidity, making them ideal for tissue engineering applications. In our study we used a murine EPC cell line (T17b) and rat mesenchymal stem cells (MSCs) for cocultivation experiments. MSCs were cocultured with increasing T17b EPC amounts. Furthermore, MSCs in monoculture were treated with conditioned medium (CM) from T17b EPCs and T17b EPCs were treated with CM from MSCs. Proliferation and apoptosis were quantified with a bromodeoxyuridine ELISA and a DNA fragmentation ELISA, respectively. Osteogenic differentiation was detected with an alkaline phosphatase assay and bone morphogenetic protein-2 ELISA. The production of proangiogenic molecules was measured with a matrix metalloproteinase-3 and vascular endothelial growth factor ELISA as well as nitric oxide assay. We could show that T17b EPCs stimulated MSC proliferation but not vice versa. On the other hand, MSCs promoted the cell survival of EPCs. The growth-inducing and antiapoptotic effects were dependent on heterotypic cell contacts and paracrine mediators. Moreover, proangiogenic growth factors were found in the coculture. Collectively, our results indicate that the coapplication of MSCs and T17b EPCs provides new perspectives for tissue engineering applications.
EVALuna2:15306

Collateral effects of the SARS-CoV-2 pandemic on oncologic surgery in Bavaria - Dienemann, Thomas; Brennfleck, Frank; Dejaco, Alexander; Grützmann, Robert; Binder, Johannes; Krautz, Christian; Stoess, Christian; Jaeger, Carsten; Friess, Helmut; Schlitt, Hans Juergen; Brunner, Stefan M. (BMC Surgery, 2021)
Background: The ongoing SARS-COV-2 pandemic has severe implications for people and healthcare systems everywhere. In Germany, worry about the consequences of the pandemic led to the deferral of non-emergency surgeries. Tumor surgery accounts for a large volume in the field of visceral surgery and cannot be considered purely elective. It is not known how the SARS-COV-2 pandemic has changed the surgical volume in tumor patients. Methods: Retrospective analysis of the amount of oncological surgeries in three academic visceral surgery departments in Bavaria, Germany, in 2020. Procedures were split into subgroups: Upper Gastrointestinal (Upper GI), Colorectal, Hepato-Pancreato-Biliary (HPB), Peritoneal and Endocrine. Procedures in 2020 were compared to a reference period from January 1st, 2017 to December 31st 2019. Surgical volume was graphically merged with SARS-COV-2 incidence and the number of occupied ICU beds. Results: Surgical volume decreased by 7.6% from an average of 924 oncologic surgeries from 2017 to 2019 to 854 in 2020. The decline was temporally associated with the incidence of infections and ICU capacity. Surgical volume did not uniformly increase to pre-pandemic levels in the months following the first pandemic wave with lower SARS-COV-2 incidence and varied according to local incidence levels. The decline was most pronounced in colorectal surgery where procedures declined on average by 26% following the beginning of the pandemic situation. Conclusion: The comparison with pre-pandemic years showed a decline in oncologic surgeries in 2020, which could have an impact on lost life years in non-COVID-19 patients. This decline was very different in subgroups which could not be solely explained by the pandemic.
CRIS-Team Scopus Importer:2021-12-17
Keywords: COVID-19; Oncologic surgery; Oncology; Patient care; SARS-CoV-2

Colon Cancer Microbiome Landscaping: Differences in Right- and Left-Sided Colon Cancer and a Tumor Microbiome-Ileal Microbiome Association - Kneis, Barbara; Wirtz, Stefan; Weber, Klaus; Denz, Axel; Gittler, Matthias; Geppert, Carol-Immanuel; Brunner, Maximilian; Krautz, Christian; Siebenhuener, Alexander Reinhard; Schierwagen, Robert; Tyc, Olaf; Agaimy, Abbas; et al. (International Journal of Molecular Sciences, 2023)
In the current era of precision oncology, it is widely acknowledged that CRC is a heterogeneous disease entity. Tumor location (right- or left-sided colon cancer or rectal cancer) is a crucial factor in determining disease progression as well as prognosis and influences disease management. In the last decade, numerous works have reported that the microbiome is an important element of CRC carcinogenesis, progression and therapy response. Owing to the heterogeneous nature of microbiomes, the findings of these studies were inconsistent. The majority of the studies combined colon cancer (CC) and rectal cancer (RC) samples as CRC for analysis. Furthermore, the small intestine, as the major site for immune surveillance in the gut, is understudied compared to the colon. Thus, the CRC heterogeneity puzzle is far from being solved, and more research is necessary for prospective trials that separately investigate CC and RC. Our prospective study aimed to map the colon cancer landscape using 16S rRNA amplicon sequencing in biopsy samples from the terminal ileum, healthy colon tissue, healthy rectal tissue and tumor tissue as well as in preoperative and postoperative stool samples of 41 patients. While fecal samples provide a good approximation of the average gut microbiome composition, mucosal biopsies allow for detecting subtle variations in local microbial communities. In particular, the small bowel microbiome has remained poorly characterized, mainly because of sampling difficulties. Our analysis revealed the following: (i) right- and left-sided colon cancers harbor distinct and diverse microbiomes, (ii) the tumor microbiome leads to a more consistent cancer-defined microbiome between locations and reveals a tumor microbiome-ileal microbiome association, (iii) the stool only partly reflects the microbiome landscape in patients with CC, and (iv) mechanical bowel preparation and perioperative antibiotics together with surgery result in major changes in the stool microbiome, characterized by a significant increase in the abundance of potentially pathogenic bacteria, such as Enterococcus. Collectively, our results provide new and valuable insights into the complex microbiome landscape in patients with colon cancer.
CRIS-Team Scopus Importer:2023-03-10
Keywords: colon cancer; gut microbiome; left-sided colon cancer; microbiome; right-sided colon cancer; tumor microbiome

Colorectal cancer in Crohn’s colitis is associated with advanced tumor invasion and a poorer survival compared with ulcerative colitis: a retrospective dual-center study - Vetter, Leonie E.; Merkel, Susanne; Bénard, Alan; Krautz, Christian; Brunner, Maximilian; Mittelstädt, Anke; Schlegel, Nicolas; Wiegering, Armin; Germer, Christoph Thomas; Weber, Klaus; Grützmann, Robert; Weber, Georg (International Journal of Colorectal Disease, 2020)
Purpose: Colorectal cancer is a well-recognized complication of inflammatory bowel diseases (IBD), such as ulcerative colitis (UC) and Crohn’s colitis (CC). In this study, we assess the clinico-pathological features and outcomes of patients with colorectal cancer from UC in comparison with CC. Methods: Data of all patients with colitis-associated cancer (CAC) who underwent surgery at Erlangen or Würzburg University Clinic between 1995 and 2015 were selected. Clinical, histopathological, and survival data were analyzed retrospectively. Results: Of all 88 patients with CAC, 20 patients had Crohn’s colitis and 68 patients had ulcerative colitis. We observed a young median age at tumor diagnosis (49.5 years UC; 45.5 years CC, p = 0.208) in both diseases and a long median disease duration before CAC (19 years UC; 18 years CC; p = 0.840). Patients with CC suffered more often from rectal cancer (14 (70.0%) in CC; 23 (33.8%) in UC; p = 0.005) and advanced tumor stages (8 (47.0%) pT4 in CC; 14 (25.0%) pT4/ypT4 in UC; p = 0.008). Five-year overall survival rate was 39.3% for CC and 67.1% for UC (p = 0.009 for difference between the groups). Survival did not differ significantly between UC and CC in the multivariate analysis after correction for UICC tumor stage. Conclusion: CAC in CC showed advanced tumor stages associated with reduced survival compared with CAC in UC. This may be explained by less intense surveillance in patients with CC leading to delayed cancer diagnosis.
CRIS-Team Scopus Importer:2020-09-25
Keywords: Colorectal cancer; Crohn’s colitis; Ulcerative colitis

Comment on: Complete mesocolic excision for right colonic cancer: prospective multicentre study - Bertelsen, Claus Anders; Bianchi, Paolo Pietro; Croner, Roland; Kleif, Jakob; Matzel, Klaus; Merkel, Susanne; Miskovic, Danilo; Gomez Ruiz, Marcos; Stearns, Adam T.; Storli, Kristian Eeg (British Journal of Surgery, 2023)
CRIS-Team WoS Importer:2023-04-14

Common variants in glyoxalase I do not inease chronic pancreatitis risk - Kaune, Tom; Hollenbach, Marcus; Keil, Bettina; Chen, Jian Min; Masson, Emmanuelle; Becker, Carla; Damm, Marko; Ruffert, Claudia; Grützmann, Robert; Hoffmeister, Albrecht; Te Morsche, Rene H.M.; Cavestro, Giulia Martina; et al. (PLoS ONE, 2019)
Introduction Chronic pancreatitis (CP) may be caused by oxidative stress. An important source of reactive oxygen species (ROS) is the methylglyoxal-derived formation of advanced glycation endproducts (AGE). Methylglyoxal is detoxified by Glyoxalase I (GLO1). A reduction in GLO1 activity results in increased ROS. Single nucleotide polymorphisms (SNPs) of GLO1 have been linked to various inflammatory diseases. Here, we analyzed whether common GLO1 variants are associated with alcoholic (ACP) and non-alcoholic CP (NACP). Methods Using melting curve analysis, we genotyped a screening cohort of 223 ACP, 218 NACP patients, and 328 controls for 11 tagging SNPs defined by the SNPinfo LD TAG SNP Selection tool and the functionally relevant variant rs4746. For selected variants the cohorts were extended to up to 1,441 patient samples. Results In the ACP cohort, comparison of genotypes for rs1937780 between patients and controls displayed an ambiguous result in the screening cohort (p = 0.08). However, in the extended cohort of 1,441 patients no statistically significant association was found for the comparison of genotypes (p = 0.11), nor in logistic regression analysis (p = 0.214, OR 1.072, 95% CI 0.961-1.196). In the NACP screening cohort SNPs rs937662, rs1699012, and rs4746 displayed an ambiguous result when patients were compared to controls in the recessive or dominant model (p = 0.08, 0.08, and 0.07, respectively). Again, these associations were not confirmed in the extended cohorts (rs937662, dominant model: P = 0.07, logistic regression: P = 0.07, OR 1.207, 95% CI 0.985-1.480) or in the replication cohorts for rs4746 (Germany, p = 0.42, OR 1.080, 95% CI 0.673-1.124; France, p = 0.19, OR 0.90, 95% CI 0.76-1.06; China, p = 0.24, OR 1.18, 95% CI 0.90-1.54) and rs1699012 (Germany, Munich; p = 0.279, OR 0.903, 95% CI 0.750-1.087). Conclusions Common GLO1 variants do not increase chronic pancreatitis risk.
CRIS-Team Scopus Importer:2019-11-08

Composition of TWIST1 dimers regulates fibroblast activation and tissue fibrosis - Palumbo-Zerr, Katrin; Soare, Alina; Zerr, Pawel; Liebl, Andrea; Mancuso, Rossella; Tomcik, Michal; Sumova, Barbora; Dees, Clara; Chen, Chih-Wei; Wohlfahrt, Thomas; Mallano, Tatjana; Distler, Alfiya; et al. (Annals of the Rheumatic Diseases, 2017)
TWIST1 is a member of the class B of basic helix-loop-helix transcription factors that regulates cell lineage determination and differentiation and has been implicated in epithelial-to-mesenchymal transition. Here, we aimed to investigate the role of TWIST1 for the activation of resident fibroblasts in systemic sclerosis (SSc).The expression of Twist1 in fibroblasts was modulated by forced overexpression or siRNA-mediated knockdown. Interaction of Twist1, E12 and inhibitor Of differentiation (Id) was analysed by co-immunoprecipitation. The role of Twist1 in vivo was evaluated using inducible, conditional knockout mice with either ubiquitous or fibroblast-specific depletion of Twist1. Mice were either challenged with bleomycin or overexpressing a constitutively active transforming growth factor (TGF)? receptor I.The expression of TWIST1 was increased in fibroblasts in fibrotic human and murine skin in a TGF?/SMAD3-dependent manner. TWIST1 in turn enhanced TGF?-induced fibroblast activation in a p38-dependent manner. The stimulatory effects of TWIST1 on resident fibroblasts were mediated by TWIST1 homodimers. TGF? promotes the formation of TWIST1 homodimers by upregulation of TWIST1 and by induction of inhibitor of DNA-binding proteins, which have high affinity for E12/E47 and compete against TWIST1 for E12/E47 binding. Mice with selective depletion of Twist1 in fibroblasts are protected from experimental skin fibrosis in different murine models to a comparable degree as mice with ubiquitous depletion of Twist1.Our data identify TWIST1 as a central pro-fibrotic factor in SSc, which facilitates fibroblast activation by amplifying TGF? signalling. Targeting of TWIST1 may thus be a novel approach to normalise aberrant TGF? signalling in SSc.
EVALuna2:13273

Comprehensive screening for mutations associated with colorectal cancer in unselected cases reveals penetrant and nonpenetrant mutations - Kraus, Cornelia; Rau, Tilman; Lux, Philipp; Erlenbach-Wuensch, Katharina; Loehr, Sabine; Krumbiegel, Mandy; Thiel, Christian; Stoehr, Robert; Agaimy, Abbas; Croner, Roland S.; Stürzl, Michael; Hohenberger, Werner; et al. (International Journal of Cancer, 2015)
Germline mutation testing in patients with colorectal cancer (CRC) is offered only to a subset of patients with a clinical presentation or tumor histology suggestive of familial CRC syndromes, probably underestimating familial CRC predisposition. The aim of our study was to determine whether unbiased screening of newly diagnosed CRC cases with next generation sequencing (NGS) increases the overall detection rate of germline mutations. We analyzed 152 consecutive CRC patients for germline mutations in 18 CRC-associated genes using NGS. All patients were also evaluated for Bethesda criteria and all tumors were investigated for microsatellite instability, immunohistochemistry for mismatch repair proteins and the BRAF*V600E somatic mutation. NGS based sequencing identified 27 variants in 9 genes in 23 out of 152 patients studied (18%). Three of them were already reported as pathogenic and 12 were class 3 germline variants with an uncertain prediction of pathogenicity. Only 1 of these patients fulfilled Bethesda criteria and had a microsatellite instable tumor and an MLH1 germline mutation. The others would have been missed with current approaches: 2 with a MSH6 premature termination mutation and 12 uncertain, potentially pathogenic class 3 variants in APC, MLH1, MSH2, MSH6, MSH3 and MLH3. The higher NGS mutation detection rate compared with current testing strategies based on clinicopathological criteria is probably due to the large genetic heterogeneity and overlapping clinical presentation of the various CRC syndromes. It can also identify apparently nonpenetrant germline mutations complicating the clinical management of the patients and their families.
EVALuna2:6598

CONKO-005: Adjuvant Chemotherapy With Gemcitabine Plus Erlotinib Versus Gemcitabine Alone in Patients After R0 Resection of Pancreatic Cancer: A Multicenter Randomized Phase III Trial - Sinn, Marianne; Bahra, Marcus; Liersch, Torsten; Gellert, Klaus; Messmann, Helmut; Bechstein, Wolf; Waldschmidt, Dirk; Jacobasch, Lutz; Wilhelm, Martin; Rau, Bettina M.; Grützmann, Robert; Weinmann, Arndt; et al. (Journal of Clinical Oncology, 2017)
Purpose Gemcitabine is standard of care in the adjuvant treatment of resectable pancreatic ductal adenocarcinoma (PDAC). The epidermal growth factor receptor tyrosine kinase inhibitor erlotinib in combination with gemcitabine has shown efficacy in the treatment of advanced PDAC and was considered to improve survival in patients with primarily resectable PDAC after R0 resection. Patients and Methods In an open-label, multicenter trial, patients were randomly assigned to one of two study arms: gemcitabine 1,000 mg/m2 days 1, 8, 15, every 4 weeks plus erlotinib 100 mg once per day (GemErlo) or gemcitabine (Gem) alone for six cycles. The primary end point of the study was to improve disease-free survival (DFS) from 14 to 18 months by adding erlotinib to gemcitabine. Results In all, 436 patients were randomly assigned at 57 study centers between April 2008 and July 2013. A total of 361 instances (83%) of disease recurrence were observed after a median follow-up of 54 months. Median treatment duration was 22 weeks in both arms. There was no difference in median DFS (GemErlo 11.4 months; Gem 11.4 months) or median overall survival (GemErlo 24.5 months; Gem 26.5 months). There was a trend toward long-term survival in favor of GemErlo (estimated survival after 1, 2, and 5 years for GemErlo was 77%, 53%, and 25% v 79%, 54%, and 20% for Gem, respectively). The occurrence or the grade of rash was not associated with a better survival in the GemErlo arm. Conclusion To the best of our knowledge, CONKO-005 is the first study to investigate the combination of chemotherapy and a targeted therapy in the adjuvant treatment of PDAC. GemErlo for 24 weeks did not improve DFS or overall survival over Gem.
EVALuna2:15299

Consensus in determining the resectability of locally progressed pancreatic ductal adenocarcinoma - results of the Conko-007 multicenter trial - Wittel, U. A.; Lubgan, Dorota; Ghadimi, M.; Belyaev, O.; Uhl, W.; Bechstein, W. O.; Grützmann, Robert; Hohenberger, Werner; Schmid, Andrea; Jacobasch, L.; Croner, R. S.; Reinacher-Schick, A.; et al. (BMC Cancer, 2019)
BACKGROUND: One critical step in the therapy of patients with localized pancreatic cancer is the determination of local resectability. The decision between primary surgery versus upfront local or systemic cancer therapy seems especially to differ between pancreatic cancer centers. In our cohort study, we analyzed the independent judgement of resectability of five experienced high volume pancreatic surgeons in 200 consecutive patients with borderline resectable or locally advanced pancreatic cancer. METHODS: Pretherapeutic CT or MRI scans of 200 consecutive patients with borderline resectable or locally advanced pancreatic cancer were evaluated by 5 independent pancreatic surgeons. Resectability and the degree of abutment of the tumor to the venous and arterial structures adjacent to the pancreas were reported. Interrater reliability and dispersion indices were compared. RESULTS: One hundred ninety-four CT scans and 6 MRI scans were evaluated and all parameters were evaluated by all surgeons in 133 (66.5%) cases. Low agreement was observed for tumor infiltration of venous structures (κ = 0.265 and κ = 0.285) while good agreement was achieved for the abutment of the tumor to arterial structures (interrater reliability celiac trunk κ = 0.708 P < 0.001). In patients with vascular tumor contact indicating locally advanced disease, surgeons highly agreed on unresectability, but in patients with vascular tumor abutment consistent with borderline resectable disease, the judgement of resectability was less uniform (dispersion index locally advanced vs. borderline resectable p < 0.05). CONCLUSION: Excellent agreement between surgeons exists in determining the presence of arterial abutment and locally advanced pancreatic cancer. The determination of resectability in borderline resectable patients is influenced by additional subjective factors. TRIAL REGISTRATION: EudraCT:2009-014476-21 (2013-02-22) and NCT01827553 (2013-04-09).
CRIS-Team Scopus Importer:2019-10-29
Keywords: Borderline resectable; Determination of resectability; Locally advanced; Pancreatic cancer; Prospective randomized multicenter trial

Context Matters—Why We Need to Change From a One Size Fits all Approach to Made-to-Measure Therapies for Individual Patients With Pancreatic Cancer - Sankarasubramanian, Sushmitha; Pfohl, Ulrike; Regenbrecht, Christian R. A.; Reinhard, Christoph; Wedeken, Lena (Frontiers in Cell and Developmental Biology, 2021)
Pancreatic cancer is one of the deadliest cancers and remains a major unsolved health problem. While pancreatic ductal adenocarcinoma (PDAC) is associated with driver mutations in only four major genes (KRAS, TP53, SMAD4, and CDKN2A), every tumor differs in its molecular landscape, histology, and prognosis. It is crucial to understand and consider these differences to be able to tailor treatment regimens specific to the vulnerabilities of the individual tumor to enhance patient outcome. This review focuses on the heterogeneity of pancreatic tumor cells and how in addition to genetic alterations, the subsequent dysregulation of multiple signaling cascades at various levels, epigenetic and metabolic factors contribute to the oncogenesis of PDAC and compensate for each other in driving cancer progression if one is tackled by a therapeutic approach. This implicates that besides the need for new combinatorial therapies for PDAC, a personalized approach for treating this highly complex cancer is required. A strategy that combines both a target-based and phenotypic approach to identify an effective treatment, like Reverse Clinical Engineering® using patient-derived organoids, is discussed as a promising way forward in the field of personalized medicine to tackle this deadly disease.
CRIS-Team Scopus Importer:2021-12-03
Keywords: 3D cell culture models; combined targeted and phenotypic approach; KRAS; pancreatic ductal adenocarcinoma (PDAC); patient-derived tumor organoids; personalized medicine; reverse clinical engineering; tumor heterogeneity

Continuous or interrupted suture technique for hepaticojejunostomy? A national survey - Brunner, Maximilian; Stockheim, Jessica; Krautz, Christian; Raptis, Dimitrios; Kersting, Stephan; Grützmann, Robert; Weber, Georg (BMC Surgery, 2018)
BACKGROUND: Hepaticojejunostomy is commonly used in hepato-bilio-pancreatic surgery and a crucial step in many surgical procedures, including pancreaticoduodenectomy. The most frequently used techniques are the interrupted suture and the continuous suture technique. Currently, there is no data available in regard to the utilization of these techniques. METHODS: In total, 102 hospitals in Germany were invited between September and November 2017 to participate in this survey. Using a paper-based questionnaire, data were collected on surgical technique and complication rates of hepaticojejunostomies. RESULTS: A total of 77 of the 102 addressed hospitals (76%) participated in the survey. On average, each hospital performed 71 hepaticojejunostomies per year - most often in the context of pancreaticoduodenectomy (71%). 24 (31%) hospitals exclusively use an interrupted suture technique, 7 (9%) hospitals solely a continuous suture technique, 3 (4%) hospitals perform a combination of continuous and interrupted suture technique and 43 (56%) hospitals decide on one of both techniques depending on intraoperative findings. According to the participants in this survey, the continuous suture technique is significantly faster than the interrupted suture technique in hepaticojejunostomy (p = 0,015). There were no significant differences in the overall complication rate (p = 0,902) and insufficiency rate (p = 1,000). CONCLUSIONS: In Germany, there is a heterogeneity in the technique used to create a hepaticojejunostomy. As our survey suggests that the use of continuous suture technique may offer an advantage in time without jeopardizing patient outcomes, the different techniques should be compared in a randomized controlled study.
EVALuna2:210706

Continuous or interrupted suture technique for hepaticojejunostomy during pancreatoduodenectomy (HEKTIK trial): study protocol of a randomized controlled multicenter trial - Brunner, Maximilian; Golcher, Henriette; Krautz, Christian; Kersting, Stephan; Grützmann, Robert; Weber, Georg (Trials, 2022)
Background: Hepaticojejunostomy is commonly performed in hepato-bilio-pancreatic surgery, particularly during pancreaticoduodenectomy. The purpose of this study is to evaluate the safety and efficiency of two commonly applied suture techniques (the interrupted versus the continuous suture technique) in patients undergoing a hepaticojejunostomy during pancreatoduodenectomy.
CRIS-Team WoS Importer:2022-06-24

Contribution of Blood Vessel Activation, Remodeling and Barrier Function to Inflammatory Bowel Diseases - Britzen-Laurent, Nathalie; Weidinger, Carl; Stürzl, Michael (International Journal of Molecular Sciences, 2023)
Inflammatory bowel diseases (IBDs) consist of a group of chronic inflammatory disorders with a complex etiology, which represent a clinical challenge due to their often therapy-refractory nature. In IBD, inflammation of the intestinal mucosa is characterized by strong and sustained leukocyte infiltration, resulting in the loss of epithelial barrier function and subsequent tissue destruction. This is accompanied by the activation and the massive remodeling of mucosal micro-vessels. The role of the gut vasculature in the induction and perpetuation of mucosal inflammation is receiving increasing recognition. While the vascular barrier is considered to offer protection against bacterial translocation and sepsis after the breakdown of the epithelial barrier, endothelium activation and angiogenesis are thought to promote inflammation. The present review examines the respective pathological contributions of the different phenotypical changes observed in the microvascular endothelium during IBD, and provides an overview of potential vessel-specific targeted therapy options for the treatment of IBD.
CRIS-Team Scopus Importer:2023-04-07
Keywords: angiogenesis; gut vascular barrier; inflammatory bowel diseases (IBDs); vasculature; vessel permeability

Correction: The sarcoma ring trial: a case-based analysis of inter-center agreement across 21 German-speaking sarcoma centers (Journal of Cancer Research and Clinical Oncology, (2025), 151, 1, (30), 10.1007/s00432-024-06063-z) - Roohani, Siyer; Handtke, Jolina; Hummedah, Kamal; Albertsmeier, Markus; Andreou, Dimosthenis; Apostolidis, Leonidas; Augustin, Marinela; Bauer, Sebastian; Billner, Moritz; Bösch, Florian; Deinzer, Christoph K.W.; Deventer, Niklas; et al. (Journal of Cancer Research and Clinical Oncology, 2025)
In this article, the author’s name Armin Tuchscherer was incorrectly written as Armin Tuscherer. The original article has been corrected.
CRIS-Team Scopus Importer:2025-05-02

Correction to: Outcomes After Distal Pancreatectomy with Celiac Axis Resection for Pancreatic Cancer: A Pan-European Retrospective Cohort Study - Klompmaker, Sjors; Van Hilst, Jony; Gerritsen, Sarah L.; Adham, Mustapha; Albiol Quer, M. Teresa; Bassi, Claudio; Berrevoet, Frederik; Boggi, Ugo; Busch, Olivier R.; Cesaretti, Manuela; Dalla Valle, Raffaele; Darnis, Benjamin; et al. (Annals of Surgical Oncology, 2018)
In the original article, the institutional author the E-AHPBA DP-CAR study group was misspelled. It is correct as reflected here. The original article has also been corrected.
EVALuna2:202846

CRISPR Cas9 in Pancreatic Cancer Research - Yang, Hai; Bailey, Peter; Pilarsky, Christian (Frontiers in Cell and Developmental Biology, 2019)
Pancreatic cancer is now becoming a common cause of cancer death with no significant change in patient survival over the last 10 years. The main treatment options for pancreatic cancer patients are surgery, radiation therapy and chemotherapy, but there is now considerable effort to develop new and effective treatments. In recent years, CRISPR/Cas9 technology has emerged as a powerful gene editing tool with promise, not only as an important research methodology, but also as a new and effective method for targeted therapy. In this review, we summarize current advances in CRISPR/Cas9 technology and its application to pancreatic cancer research, and importantly as a means of selectively targeting key drivers of pancreatic cancer.
CRIS-Team Scopus Importer:2019-11-15
Keywords: CRISPR/Cas9; gene editing; knock out and knock in; library screening; pancreatic cancer

CRISPR/Cas9-mediated knock-out of krasG12D mutated pancreatic cancer cell lines - Lentsch, Eva; Li, Lifei; Pfeffer, Sina; Ekici, Arif Bülent; Taher, Leila; Pilarsky, Christian; Grützmann, Robert (International Journal of Molecular Sciences, 2019)
In 90% of pancreatic ductal adenocarcinoma cases, genetic alteration of the proto-oncogene Kras has occurred, leading to uncontrolled proliferation of cancerous cells. Targeting Kras has proven to be difficult and the battle against pancreatic cancer is ongoing. A promising approach to combat cancer was the discovery of the clustered regularly interspaced short palindromic repeat (CRISPR)/CRISPR-associated (Cas) system, which can be used to genetically modify cells. To assess the potential of a CRISPR/CRISPR-associated protein 9 (Cas9) method to eliminate Kras mutations in cells, we aimed to knock-out the c.35G>A (p.G12D) Kras mutation. Therefore, three cell lines with a heterozygous Kras mutation (the human cell lines SUIT-2 and Panc-1 and the cell line TB32047 from a KPC mouse model) were used. After transfection, puromycin selection and single-cell cloning, proteins from two negative controls and five to seven clones were isolated to verify the knock-out and to analyze changes in key signal transduction proteins. Western blots showed a specific knock-out in the KrasG12D protein, but wildtype Kras was expressed by all of the cells. Signal transduction analysis (for Erk, Akt, Stat3, AMPKα, and c-myc) revealed expression levels similar to the wildtype. The results described herein indicate that knocking-out the KrasG12D mutation by CRISPR/Cas9 is possible. Additionally, under regular growth conditions, the knock-out clones resembled wildtype cells.
CRIS-Team Scopus Importer:2019-11-26
Keywords: CRISPR/Cas9 system; G12D; Kras; Panc-1; Suit-2; TB32047

CRISPR-Cas9 Screen Identifies DYRK1A as a Target for Radiotherapy Sensitization in Pancreatic Cancer - Lan, Bin; Zeng, Siyuan; Zhang, Shuman; Ren, Xiaofan; Xing, Yuming; Kutschick, Isabella; Pfeffer, Sina; Frey, Benjamin; Britzen-Laurent, Nathalie; Grützmann, Robert; Cordes, Nils; Pilarsky, Christian (Cancers, 2022)
Although radiation therapy has recently made great advances in cancer treatment, the majority of patients diagnosed with pancreatic cancer (PC) cannot achieve satisfactory outcomes due to intrinsic and acquired radioresistance. Identifying the molecular mechanisms that impair the efficacy of radiotherapy and targeting these pathways are essential to improve the radiation response of PC patients. Our goal is to identify sensitive targets for pancreatic cancer radiotherapy (RT) using the kinome-wide CRISPR-Cas9 loss-of-function screen and enhance the therapeutic effect through the development and application of targeted inhibitors combined with radiotherapy. We transduced pancreatic cancer cells with a protein kinase library; 2D and 3D library cells were irradiated daily with a single dose of up to 2 Gy for 4 weeks for a total of 40 Gy using an X-ray generator. Sufficient DNA was collected for next-generation deep sequencing to identify candidate genes. In this study, we identified several cell cycle checkpoint kinases and DNA damage related kinases in 2D-and 3D-cultivated cells, including DYRK1A, whose loss of function sensitizes cells to radiotherapy. Additionally, we demonstrated that the harmine-targeted suppression of DYRK1A used in conjunction with radiotherapy increases DNA double-strand breaks (DSBs) and impairs homologous repair (HR), resulting in more cancer cell death. Our results support the use of CRISPR-Cas9 screening to identify new therapeutic targets, develop radiosensitizers, and provide novel strategies for overcoming the tolerance of pancreatic cancer to radiotherapy.
CRIS-Team Scopus Importer:2022-01-14
Keywords: CRISPR-Cas9; DNA damage repair; DNA double-strand break; DYRK1A; Harmine; Pancreatic cancer; Radioresistance; Radiotherapy

Cu-releasing bioactive glass/polycaprolactone coating on Mg with antibacterial and anticorrosive properties for bone tissue engineering - Yang, Yuyun; Zheng, Kai; Liang, Ruifang; Mainka, Astrid; Taccardi, Nicola; Roether, Judith; Detsch, Rainer; Goldmann, Wolfgang; Virtanen, Sannakaisa; Boccaccini, Aldo R. (Biomedical Materials, 2017)
Copper (Cu)-containing bioactive glass nanoparticles (Cu-BGNs) were introduced in polycaprolactone (PCL) coating systems to improve the bioactivity, antibacterial property, and corrosion resistance of vulnerable magnesium matrices under physiological conditions. The influence of different amounts of Cu-BGNs in PCL coatings was thoroughly investigated determining the wettability, electrochemical properties, and antibacterial effects against Staphylococcus carnosus and Escherichia coli, as well as their cyto-compatibility. Cu-BGNs were observed randomly scattered in PCL coatings. Increasing concentration of Cu-BGNs resulted in slightly decreasing water contact angle, and reducing anti-corrosion properties of the Cu-BGNs composite coatings. Yet higher Cu-BGNs content in coatings led to more calcium phosphate formation on the surface after 7 days of immersion in DMEM, which was confirmed by FTIR and XPS. The growth of S. carnosus and E. coli was inhibited by Cu2+ ion released from Cu-BGN coatings. In addition, both direct and indirect cyto-compatibility experiments showed that the viability and proliferation of MG-63 cells on Cu-BGN coatings were highly increased compared to pure magnesium; however, an additional increase of Cu-BGNs concentration showed a slight decrease of cell proliferation and cell activity. In summary, Cu-BGN/PCL composite coatings impart magnesium-based biomaterials antibacterial and anticorrosive properties for clinical applications.
EVALuna2:13499

Current Clinical Strategies of Pancreatic Cancer Treatment and Open Molecular Questions - Brunner, Maximilian; Wu, Zhiyuan; Krautz, Christian; Pilarsky, Christian; Grützmann, Robert; Weber, Georg (International Journal of Molecular Sciences, 2019)
Pancreatic cancer is one of the most lethal malignancies and is associated with a poor prognosis. Surgery is considered the only potential curative treatment for pancreatic cancer, followed by adjuvant chemotherapy, but surgery is reserved for the minority of patients with non-metastatic resectable tumors. In the future, neoadjuvant treatment strategies based on molecular testing of tumor biopsies may increase the amount of patients becoming eligible for surgery. In the context of non-metastatic disease, patients with resectable or borderline resectable pancreatic carcinoma might benefit from neoadjuvant chemo- or chemoradiotherapy followed by surgeryPatients with locally advanced or (oligo-/poly-)metastatic tumors presenting significant response to (neoadjuvant) chemotherapy should undergo surgery if R0 resection seems to be achievable. New immunotherapeutic strategies to induce potent immune response to the tumors and investigation in molecular mechanisms driving tumorigenesis of pancreatic cancer may provide novel therapeutic opportunities in patients with pancreatic carcinoma and help patient selection for optimal treatment.
CRIS-Team Scopus Importer:2019-10-01
Keywords: chemoradiation; chemotherapy; immunotherapy; molecular mechanism; pancreatic cancer; surgery; therapeutic targets; treatment options

Cylindric Abdominoperineal Rectum Exstirpation with Partial Vulvar and Vaginal Resection as well as Perineal and Vaginal Defect Reconstruction by a Vertical Rectus Abdominis Myocutaneous (VRAM) Flap - Krautz, Christian; Weber, Klaus; Croner, Roland; Denz, Axel; Maak, Matthias; Horch, Raymund E.; Grützmann, Robert (Zentralblatt für Chirurgie, 2017)
Introduction Patients with low rectal cancer or anal cancer undergoing abdominoperineal excision (APE) benefit from extended surgery and the subsequent avoidance of surgical "waisting" at the level of the puborectalis muscle. The method of cylindrical APE was introduced by T. Holm and led to a reduction of intraoperative perforations and involvement of circumferential resection margins, and subsequently reduced the risk of local recurrence. The use of myocutaneous flaps reduces perineal wound complications, which occur in up to 60% of patients with primary closure of perineal defects, especially following neoadjuvant radiochemotherapy. Flaps obliterate pelvic dead space, recruit well-vascularised tissue into irradiated regions, facilitate wound closure and allow for vaginal and perineal reconstructions. This video shows the technique of extended cylindrical APE with partial vulvar and vaginal resection and subsequent reconstruction of the posterior vaginal wall and the pelvic floor defect by a vertical rectus abdominis myocutaneous (VRAM) flap. Indication Locally advanced anal cancer with infiltration and fistula to the posterior vaginal wall without metastatic spread following neoadjuvant radiochemotherapy. Procedure Extended cylindric APE with partial vulvar and vaginal resection, construction of a descending colostomy with parastomal intraperitoneal onlay mesh augmentation, pelvic reconstruction with a VRAM flap and inlay mesh augmentation of the anterior rectus sheath. Conclusion From the oncological point of view, extralevator APE is superior to standard surgery. The use of myocutaneous flaps improves postoperative wound healing and quality of life.
EVALuna2:15291

Cytochemical and molecular properties of simian virus 40 transformed Kaposi's sarcoma-derived cells: evidence for the secretion of a member of the fibroblast growth factor family. - Werner, Sabine; Hofschneider, Peter Hans; Stürzl, Michael; Dick, Irene; Roth, Willi Kurt (Journal of Cellular Physiology, 1989)
Contact-inhibited Kaposi's sarcoma-derived cells (KS cells) were transfected with Simian Virus 40 (SV40) DNA. Transformed cells (SV-KSC) were selected for their capacity to form foci on monolayers of the low-malignant KS cells. Isolated SV-KSC foci were found to contain integrated SV40 DNA sequences and to express SV40 large T-antigen. Several differentiation properties of KS cells are retained in the SV40 transformants, e.g., expression of vimentin and the endothelial cell marker BMA 120. In contrast to the maternal KS cells, SV-KSC are capable of growing in platelet-derived growth factor (PDGF)-depleted platelet-poor-plasma serum (PPPS) and in soft agar. However, they are not tumorigenic in nude mice. Expression of the oncogenes c-myc, c-N-ras, c-Ha-ras, and p53 is significantly elevated in SV-KSC, whereas c-fos and c-erb B expression is comparable to that of KS cells and fibroblasts. Conditioned medium from SV-KSC can substitute for PDGF when PDGF-dependent, nontransformed KS cells are grown in PPPS. Biochemical analysis of the SV-KSC supernatant and PDGF A and B mRNA expression analysis provide evidence that the mitogenic activity is not due to a PDGF-like growth factor. On the other hand, there is evidence to indicate that the SV-KSC mitogen is a member of the fibroblast growth factor family. SV-KSC represent an interesting model system for the study of different degrees of malignancy of cultured mesenchymal cells and especially provide an important source for the isolation of a potent growth factor for KS cells and other mesenchymal cells in vitro.

Cytokine-induced guanylate binding protein 1 (GBP1) release from human ovarian cancer cells - Carbotti, Grazia; Petretto, Andrea; Naschberger, Elisabeth; Stürzl, Michael; Martini, Stefania; Mingari, Maria Cristina; Filaci, Gilberto; Ferrini, Silvano; Fabbi, Marina (Cancers, 2020)
We showed that IL-27 shares several effects with IFN-γ in human cancer cells. To identify novel extracellular mediators, potentially involved in epithelial ovarian cancer (EOC) biology, we analyzed the effect of IL-27 or IFN-γ on the secretome of cultured EOC cells by mass-spectrometry (nano-UHPLC-MS/MS). IL-27 and IFN-γ modulate the release of a limited fraction of proteins among those induced in the whole cell. We focused our attention on GBP1, a guanylate-binding protein and GTPase, which mediates several biological activities of IFNs. Cytokine treatment induced GBP1, 2, and 5 expressions in EOC cells, but only GBP1 was secreted. ELISA and immunoblotting showed that cytokine-stimulated EOC cells release full-length GBP1 in vitro, through non-classical pathways, not involving microvesicles. Importantly, full-length GBP1 accumulates in the ascites of most EOC patients and ex-vivo EOC cells show constitutive tyrosine-phosphorylated STAT1/3 proteins and GBP1 expression, supporting a role for Signal Transducer And Activator Of Transcription (STAT)-activating cytokines in vivo. High GBP1 gene expression correlates with better overall survival in the TCGA (The Cancer Genome Atlas) dataset of EOC. In addition, GBP1 transfection partially reduced EOC cell viability in an MTT assay. Our data show for the first time that cytokine-stimulated tumor cells release soluble GBP1 in vitro and in vivo and suggest that GBP1 may have anti-tumor effects in EOC.
CRIS-Team Scopus Importer:2020-02-28
Keywords: Guanylate binding protein 1; Interferon-γ; Interleukin-27; Microenvironment; Ovarian cancer; Secretome

Cytokine-mediated growth promotion of Kaposi's sarcoma and primary effusion lymphoma. - Ensoli, Barbara; Stürzl, Michael; Monini, Paolo (Seminars in Cancer Biology, 2000)
Kaposi's sarcoma (KS) is an angioproliferative disease particularly frequent and aggressive in patients with AIDS but occurring also in post-transplant patients or in immunocompetent individuals of certain geographic areas. At least in its early stages, KS behaves as a reactive hyperplastic process mediated by inflammatory cytokines and angiogenic factors triggered or exacerbated by human herpesvirus-8 (HHV-8) infection. The HIV Tat protein appears to be responsible for the highly aggressive nature of AIDS-KS. Over time, however, KS may evolve into a true sarcoma in association with the expression of oncogenes and/or HHV-8 latency genes endowed with growth and anti-apoptotic properties. HHV-8 infection is also associated with primary effusion lymphoma (PEL), a rare tumor that similarly develops more frequently in the setting of HIV infection. HHV-8 latency genes are likely to contribute to the neoplastic phenotype of PEL cells, whose growth in vivo may require cytokines and factors from the host, or encoded by the virus.

Cytokine profile of HIV-positive Kaposi's sarcoma derived cells in vitro. - Brockmeyer, Norbert H.; Willers, C P; Anders, S; Mertins, L; Rockstroh, Jürgen; Stürzl, Michael (European Journal of Medical Research, 1999)
Kaposi's sarcoma (KS) is the most frequent neoplastic complication observed in HIV-infected patients. Cutaneous KS is the most common manifestation but visceral and lymph node involvement may occur. HIV-infection does not only lead to a decrease of certain cell types (CD4 T-lymphocytes), but also modifies the function of non-infected cells such as B-lymphocytes and NK-cells by upregulating cytokine release of IL-1, IL-6, GM-CSF, IFN-gamma and TNF-alpha. These multifunctional mediators show both autocrine and paracrine proliferative effects on normal endothelial cells and AIDS-related KS-cells. Using ELISA-, RIA- and IRMA-techniques we analysed the influence of seven cytokines (IL-1beta, IL-6, TNF-alpha, GM-CSF, IFN-alpha, IFN-beta, IFN-gamma) and the soluble IL-2 receptor (sIL-2R) on the growth of eight different KS-derived cell lines compared with eight fibroblast cell lines, established from skin biopsies of HIV-positive individuals. Furthermore, we analysed the dose-dependent effect of the above mentioned cytokines on KS-derived cells in vitro. The KS-derived cell culture medium demonstrated significantly higher concentrations than the fibroblast cell lines in view of the following cytokines: sIL-2R, IL-1beta, IL-6, TNF-alpha, GM-CSF, IFN-gamma (p<0.05). The most pronounced differences between KS-cells and fibroblasts were observed for IL-1beta and IFN-gamma. The antiproliferative effect of IFN-beta and IFN-gamma began at a concentration of 20 and 50 IU/ml, respectively, whereas for IFN-alpha an antiproliferative effect was observed at a concentration of 100 U/ml. Furthermore we observed a proliferative effect in low concentrations (2-5 IU/ml) of IFN-gamma in our in vitro model

Cytosolic 5 '-nucleotidase 1A is overexpressed in pancreatic cancer and mediates gemcitabine resistance by reducing intracellular gemcitabine metabolites - Patzak, Melanie S.; Kari, Vijayalakshmi; Patil, Shilpa; Hamdan, Feda H.; Goetze, Robert G.; Brunner, Marius; Gaedcke, Jochen; Kitz, Julia; Jodrell, Duncan; Richards, Frances M.; Pilarsky, Christian; Grützmann, Robert; et al. (EBioMedicine, 2019)
Background: Cytosolic 5'-nucleotidase 1A (NT5C1A) dephosphorylates non-cyclic nucleoside monophosphates to produce nucleosides and inorganic phosphates. Here, we investigate NT5C1A expression in pancreatic ductal adenocarcinoma (PDAC) and its impact on gemcitabine metabolism and therapeutic efficacy.
CRIS-Team WoS Importer:2019-03-22

Cytotoxic effect of Efavirenz in BxPC-3 pancreatic cancer cells is based on oxidative stress and is synergistic with ionizing radiation - Hecht, Markus; Harrer, Thomas; Koeber, Verena; Sarpong, Eric Opoku; Moser, Fabian; Fiebig, Nora; Schwegler, Manuela; Stürzl, Michael; Fietkau, Rainer; Distel, Luitpold (Oncology Letters, 2018)
The non-nucleoside reverse transcriptase inhibitor (NNRTI) Efavirenz is frequently used in human immunodeficiency virus treatment, but also efficient against cancer in mouse models. Its radiosensitizing effect makes it a promising drug for combination with radiotherapy. The efficacy of Efavirenz combined with irradiation was assessed with immunostaining of DNA-damage markers and colony formation assays in BxPC-3 pancreatic cancer cells. Gene expression and protein phosphorylation of the Efavirenz-sensitive BxPC-3 cells was compared to the resistant primary fibroblasts SBL-5. Oxidative stress, mitochondrial damage and cell death were studied with live-cell microscopy and flow cytometry. Combined Efavirenz and radiation significantly increased the number of γH2AX and phospho-ataxia telangiectasia mutated foci. Efavirenz and ionizing radiation had a synergistic effect using the clonogenic survival assay. Efavirenz selectively induced cell death in the BxPC-3 cells. The differing gene expression of cell cycle and apoptotic regulator genes in both cell cultures after Efavirenz treatment match with this selective effect against cancer cells. In the phosphoprotein array, an early phosphorylation of extracellular signal-related kinase 1/2 and p38 mitogen-activated protein kinase was notably detected in the cancer cells. The phosphorylation of AKT decreased in the cancer cells whereas it increased in the fibroblasts. Oxidative stress and mitochondrial membrane depolarization appeared in the cancer cells immediately after Efavirenz treatment, but not in the fibroblasts. Efavirenz has an anti-cancer effect against pancreatic cancer mainly by the induction of oxidative stress. The antitumor potential of Efavirenz and radiotherapy are additive.
EVALuna2:36443

Deep learning improves pancreatic cancer diagnosis using rna-based variants - Al-Fatlawi, Ali; Malekian, Negin; García, Sebastián; Henschel, Andreas; Kim, Ilwook; Dahl, Andreas; Jahnke, Beatrix; Bailey, Peter; Bolz, Sarah Naomi; Poetsch, Anna R.; Mahler, Sandra; Grützmann, Robert; et al. (Cancers, 2021)
For optimal pancreatic cancer treatment, early and accurate diagnosis is vital. Blood-derived biomarkers and genetic predispositions can contribute to early diagnosis, but they often have limited accuracy or applicability. Here, we seek to exploit the synergy between them by combining the biomarker CA19-9 with RNA-based variants. We use deep sequencing and deep learning to improve differentiating pancreatic cancer and chronic pancreatitis. We obtained samples of nucleated cells found in peripheral blood from 268 patients suffering from resectable, non-resectable pancreatic cancer, and chronic pancreatitis. We sequenced RNA with high coverage and obtained millions of variants. The high-quality variants served as input together with CA19-9 values to deep learning models. Our model achieved an area under the curve (AUC) of 96% in differentiating resectable cancer from pancreatitis using a test cohort. Moreover, we identified variants to estimate survival in resectable cancer. We show that the blood transcriptome harbours variants, which can substantially improve noninvasive clinical diagnosis.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Chronic pancreatitis; Deep learning; Pancreatic cancer; Transcriptome-wide association study

Defining early recurrence in patients with resected primary colorectal carcinoma and its respective risk factors - Wiesmüller, Felix; Schuetz, Rolf; Langheinrich, Melanie; Brunner, Maximilian; Grützmann, Robert; Merkel, Susanne; Krautz, Christian; Weber, Georg (International Journal of Colorectal Disease, 2021)
Purpose: There is no evidence-based definition of early recurrence following resection of colorectal cancer. The purpose of this study is to define a point that discriminates between early and late recurrence in patients who have undergone colorectal cancer resection with curative intent and to analyze associated risk factors. Methods: A retrospective single-center cohort study was performed at a university hospital recognized as a comprehensive cancer center, specializing in colorectal cancer surgery. Patient data were retrieved from a prospectively maintained institutional database. Included patients underwent resection for primary, non-metastatic colorectal carcinomas with curative intent between 1995 and 2010. Aims of the study were (1) to define the optimal cut-off point of recurrence-free survival based on overall survival using a minimum p value approach and (2) to identify patterns of initial recurrence and putative risk factors for early recurrence using regression models. Results: Recurrence was diagnosed in 412 of 1893 patients. Statistical analysis suggested that a recurrence-free survival of 16 months could be used to distinguish between early and late recurrence based on overall survival (p < 0.001). Independent risk factors for early recurrence included advanced pT categories (pT3,4/ypT3,4) and positive lymph node status (pN+/ypN+). Early recurrence was independent of site of recurrence and was associated with worse prognosis. Conclusions: Recurrence of colorectal carcinoma within 16 months after primary treatment should be labeled as “early.” Tumor categories pT3,4/ypT3,4 and positive lymph node status pN+/ypN+ are predictive of early recurrence.
CRIS-Team Scopus Importer:2021-02-05
Keywords: Cancer recurrence; Colorectal cancer; Colorectal carcinoma; Follow-up; Hemicolectomy; Low anterior resection; Recurrence group

Deletion of Kaposi's sarcoma-associated herpesvirus FLICE inhibitory protein, vFLIP, from the viral genome compromises the activation of STAT1-responsive cellular genes and spindle cell formation in endothelial cells. - Stürzl, Michael; et al. (Journal of Virology, 2011)
Kaposi's sarcoma herpesvirus (KSHV) Fas-associated death domain (FADD)-like interleukin-1 beta-converting enzyme (FLICE)-inhibitory protein, vFLIP, has antiapoptotic properties, is a potent activator of the NF-κB pathway, and induces the formation of endothelial spindle cells, the hallmark of Kaposi's sarcoma, when overexpressed in primary endothelial cells. We used a reverse genetics approach to study several functions of KSHV vFLIP in the context of the whole viral genome. Deletion of the gene encoding vFLIP from a KSHV genome cloned in a bacterial artificial chromosome (BAC) reduced the ability of the virus to persist and induce spindle cell formation in primary human umbilical vein endothelial cells (HUVECs). Only a few, mainly interferon (IFN)-responsive, genes were expressed in wild-type KSHV (KSHV-wt)-infected endothelial cells at levels higher than those in KSHV-ΔFLIP-infected endothelial cells, in contrast to the plethora of cellular genes induced by overexpressed vFLIP. In keeping with this observation, vFLIP induces the phosphorylation of STAT1 and STAT2 in an NF-κB-dependent manner in endothelial cells. vFLIP-dependent phosphorylation of STAT1 and STAT2 could be demonstrated after endothelial cells were infected with KSHV-wt, KSHV-ΔFLIP, and a KSHV-vFLIP revertant virus. These findings document the impact of KSHV vFLIP on the transcriptome of primary endothelial cells during viral persistence and highlight the role of vFLIP in the activation of STAT1/STAT2 and STAT-responsive cellular genes by KSHV.

Detection of COPB2 as a KRAS synthetic lethal partner through integration of functional genomics screens - Christodoulou, Eleni G.; Yang, Hai; Lademann, Franziska; Pilarsky, Christian; Beyer, Andreas; Schroeder, Michael (Oncotarget, 2017)
Mutated KRAS plays an important role in many cancers. Although targeting KRAS directly is difficult, indirect inactivation via synthetic lethal partners (SLPs) is promising. Yet to date, there are no SLPs from high-throughput RNAi screening, which are supported by multiple screens. Here, we address this problem by aggregating and ranking data over three independent high-throughput screens. We integrate rankings by minimizing the displacement and by considering established methods such as RIGER and RSA.Our meta analysis reveals COPB2 as a potential SLP of KRAS with good support from all three screens. COPB2 is a coatomer subunit and its knock down has already been linked to disabled autophagy and reduced tumor growth. We confirm COPB2 as SLP in knock down experiments on pancreas and colorectal cancer cell lines.Overall, consistent integration of high throughput data can generate candidate synthetic lethal partners, which individual screens do not uncover. Concretely, we reveal and confirm that COPB2 is a synthetic lethal partner of KRAS and hence a promising cancer target. Ligands inhibiting COPB2 may, therefore, be promising new cancer drugs.
EVALuna2:15311

Development and Validation of a Multivariable Prediction Model Based on Blood Plasma and Serum Metabolomics for the Diagnosis of Chronic Pancreatitis - Beyer, G.; Adam, M. G.; Christiansen, N.; Kamlage, B.; Pilarsky, Christian; Distler, M.; Falbusch, T.; Chromik, A.; Klein, F.; Bahra, M.; Uhl, W.; Grützmann, Robert; et al. (PANCREAS, 2020)
CRIS-Team WoS Importer:2021-02-19

Development and validation of a prognostic model to predict the prognosis of patients who underwent chemotherapy and resection of pancreatic adenocarcinoma: a large international population-based cohort study - Huang, Lei; Balavarca, Yesilda; Van Der Geest, Lydia; Lemmens, Valery; Van Eycken, Liesbet; De Schutter, Harlinde; Johannesen, Tom B.; Zadnik, Vesna; Primic-Zakelj, Maja; Magi, Margit; Grützmann, Robert; Besselink, Marc G.; et al. (BMC Medicine, 2019)
BackgroundPancreatic cancer (PaC) remains extremely lethal worldwide even after resection. PaC resection rates are low, making prognostic studies in resected PaC difficult. This large international population-based study aimed at exploring factors associated with survival in patients with resected TNM stage I-II PaC receiving chemotherapy and at developing and internationally validating a survival-predicting model.MethodsData of stage I-II PaC patients resected and receiving chemotherapy in 2003-2014 were obtained from the national cancer registries of Belgium, the Netherlands, Slovenia, and Norway, and the US Surveillance, Epidemiology, and End Results (SEER)-18 Program. Multivariable Cox proportional hazards models were constructed to investigate the associations of patient and tumor characteristics with overall survival, and analysis was performed in each country respectively without pooling. Prognostic factors remaining after backward selection in SEER-18 were used to build a nomogram, which was subjected to bootstrap internal validation and external validation using the European datasets.ResultsA total of 11,837 resected PaC patients were analyzed, with median survival time of 18-23months and 3-year survival rates of 21-31%. In the main analysis, patient age, tumor T stage, N stage, and differentiation were associated with survival across most countries, with country-specific association patterns and strengths. However, tumor location was mostly not significantly associated with survival. Resection margin, hospital type, tumor size, positive and harvested lymph node number, lymph node ratio, and comorbidity number were associated with survival in certain countries where the information was available. A median survival time- and 1-, 2-, 3-, and 5-year survival probability-predictive nomogram incorporating the backward-selected variables in the main analysis was established. It fits each European national cohort similarly well. Calibration curves showed very good agreement between nomogram-prediction and actual observation. The concordance index of the nomogram (0.60) was significantly higher than that of the T and N stage-based model (0.56) for predicting survival.ConclusionsIn these large international population-based cohorts, patients with resected PaC receiving chemotherapy have distinct characteristics independently associated with survival, with country-specific patterns and strengths. A robust benchmark population-based survival-predicting model is established and internationally validated. Like previous models predicting survival in resected PaC, our nomogram performs modestly.
CRIS-Team WoS Importer:2019-04-04

Development of a Class Prediction Model to Discriminate Pancreatic Ductal Adenocarcinoma from Pancreatic Neuroendocrine Tumor by MALDI Mass Spectrometry Imaging - Casadonte, Rita; Kriegsmann, Mark; Perren, Aurel; Baretton, Gustavo; Deininger, Soeren-Oliver; Kriegsmann, Katharina; Welsch, Thilo; Pilarsky, Christian; Kriegsmann, Joerg (Proteomics Clinical Applications, 2019)
Purpose To define proteomic differences between pancreatic ductal adenocarcinoma (pDAC) and pancreatic neuroendocrine tumor (pNET) by matrix-assisted laser desorption/ionization mass spectrometry imaging (MALDI MSI). Experimental design Ninety-three pDAC and 126 pNET individual tissues are assembled in tissue microarrays and analyzed by MALDI MSI. The cohort is separated in a training (52 pDAC and 83 pNET) and validation set (41 pDAC and 43 pNET). Subsequently, a linear discriminant analysis (LDA) model based on 46 peptide ions is performed on the training set and evaluated on the validation cohort. Additionally, two liver metastases and a whole slide of pDAC are analyzed by the same LDA algorithm. Results Classification of pDAC and pNET by the LDA model is correct in 95% (39/41) and 100% (43/43) of patients in the validation cohort, respectively. The two liver metastases and the whole slide of pDAC are also correctly classified in agreement with the histopathological diagnosis. Conclusion and clinical relevance: In the present study, a large dataset of pDAC and pNET by MALDI MSI is investigated, a class prediction model that allowed separation of both entities with high accuracy is developed, and differential peptide peaks with potential diagnostic, prognostic, and predictive values are highlighted.
CRIS-Team WoS Importer:2019-02-27

Differential Effects of Ontamalimab Versus Vedolizumab on Immune Cell Trafficking in Intestinal Inflammation and Inflammatory Bowel Disease - Schulze, Lisa; Becker, Emily; Dedden, Mark; Liu, Lijuan; Van Passen, Chiara; Mohamed Abdou, Mariam; Müller, Tanja; Wiendl, Maximilian; Ullrich, Karen; Atreya, Imke; Leppkes, Moritz; Ekici, Arif Bülent; et al. (Journal of Crohns & Colitis, 2023)
Background and Aims: The anti-MAdCAM-1 antibody ontamalimab demonstrated efficacy in a phase II trial in ulcerative colitis and results of early terminated phase III trials are pending, but its precise mechanisms of action are still unclear. Thus, we explored the mechanisms of action of ontamalimab and compared it to the anti-α4β7 antibody vedolizumab. Methods: We studied MAdCAM-1 expression with RNA sequencing and immunohistochemistry. The mechanisms of action of ontamalimab were assessed with fluorescence microscopy, dynamic adhesion and rolling assays. We performed in vivo cell trafficking studies in mice and compared ontamalimab and vedolizumab surrogate [-s] antibodies in experimental models of colitis and wound healing. We analysed immune cell infiltration under anti-MAdCAM-1 and anti-α4β7 treatment by single-cell transcriptomics and studied compensatory trafficking pathways. Results: MAdCAM-1 expression was increased in active inflammatory bowel disease. Binding of ontamalimab to MAdCAM-1 induced the internalization of the complex. Functionally, ontamalimab blocked T cell adhesion similar to vedolizumab, but also inhibited L-selectin-dependent rolling of innate and adaptive immune cells. Despite conserved mechanisms in mice, the impact of ontamalimab-s and vedolizumab-s on experimental colitis and wound healing was similar. Single-cell RNA sequencing demonstrated enrichment of ontamalimab-s-treated lamina propria cells in specific clusters, and in vitro experiments indicated that redundant adhesion pathways are active in these cells. Conclusions: Ontamalimab has unique and broader mechanisms of action compared to vedolizumab. However, this seems to be compensated for by redundant cell trafficking circuits and leads to similar preclinical efficacy of anti-α4β7 and anti-MAdCAM-1 treatment. These results will be important for the interpretation of pending phase III data.
CRIS-Team Scopus Importer:2023-12-15

Diffuse Neuromatosis of Intrahepatic and Extrahepatic Bile Ducts as a Rare Cause of Jaundice - Vassos, Nikolaos; Perrakis, Aristotelis; Schmid, Axel; Croner, Roland S.; Grützmann, Robert; Agaimy, Abbas (Visceral Medicine, 2020)
Background: Neuroma of the biliary tree is extremely rare with no more than 100 cases reported so far. They mostly present with obstructive jaundice and have been commonly described after surgery or abdominal trauma. Although involvement of the extrahepatic bile duct is far more common, occurrence in the intrahepatic ducts has not so far been reported. Case Report: We describe 3 cases of diffuse biliary tree neuroma affecting 3 females aged 53-68 years. None had a history of neurofibromatosis type1. All presented with progressive obstructive jaundice with no evidence of gallstones. A history of previous surgery was noted in 2 patients. Initial impression on clinical and imaging examination was highly suspicious for bile duct carcinoma in 2 patients. Histology showed diffuse neuromatous proliferation replacing and thickening the bile duct walls. The third patient had concurrent neuroma and recurrent cholangiocarcinoma causing great clinical confusion as initial biopsy showed only benign neuroma, but CA 19-9 was steadily increasing, necessitating a second biopsy which then confirmed recurrent carcinoma. Conclusion: This uncommon cause of long-distance bile duct stenosis and progressive jaundice should be included in the differential diagnosis of bile duct neoplasms, in particular when there is a previous surgical history in this abdominal region.
CRIS-Team Scopus Importer:2020-12-18
Keywords: Bile duct neuroma; Bile duct stenosis; Cholangiocarcinoma; Jaundice; Neuromatosis

Dipeptidyl-Peptidase-4 (DPP4) Positive Fibroblast Subpopulation Promotes Fibrosis and Are a Molecular Target for Treatment of Fibrosis - Soare, Alina; Rauber, Simon; Wohlfahrt, Thomas; Dees, Clara; Liang, Ruifang; Zhang, Yun; Chen, Chih-Wei; Distler, Oliver; Mihai, Carina; Schett, Georg; Distler, Jörg; Ramming, Andreas (2016)
EVALuna2:35065

Discrimination of pancreato-biliary cancer and pancreatitis patients by non-invasive liquid biopsy - Hartwig, Christina; Müller, Jan; Klett, Hagen; Kouhestani, Dina; Mittelstädt, Anke; Anthuber, Anna; David, Paul; Brunner, Maximilian; Jacobsen, Anne; Glanz, Karolina; Swierzy, Izabela; Roßdeutsch, Lotta; et al. (Molecular Cancer, 2024)
Background: Current diagnostics for the detection of pancreato-biliary cancers (PBCs) need to be optimized. We therefore propose that methylated cell-free DNA (cfDNA) derived from non-invasive liquid biopsies serves as a novel biomarker with the ability to discriminate pancreato-biliary cancers from non-cancer pancreatitis patients. Methods: Differentially methylated regions (DMRs) from plasma cfDNA between PBCs, pancreatitis and clinical control samples conditions were identified by next-generation sequencing after enrichment using methyl-binding domains and database searches to generate a discriminatory panel for a hybridization and capture assay with subsequent targeted high throughput sequencing. Results: The hybridization and capture panel, covering around 74 kb in total, was applied to sequence a cohort of 25 PBCs, 25 pancreatitis patients, 25 clinical controls, and seven cases of Intraductal Papillary Mucinous Neoplasia (IPMN). An unbiased machine learning approach identified the 50 most discriminatory methylation markers for the discrimination of PBC from pancreatitis and controls resulting in an AUROC of 0.85 and 0.88 for a training (n = 45) and a validation (n = 37) data set, respectively. The panel was also able to distinguish high grade from low grade IPMN samples. Conclusions: We present a proof of concept for a methylation biomarker panel with better performance and improved discriminatory power than the current clinical marker CA19-9 for the discrimination of pancreato-biliary cancers from non-cancerous pancreatitis patients and clinical controls. This workflow might be used in future diagnostics for the detection of precancerous lesions, e.g. the identification of high grade IPMNs vs. low grade IPMNs.
CRIS-Team Scopus Importer:2024-02-16
Keywords: cfDNA; cfMBD-Seq; DMRs; Hybridization and capture; IPMN; Methylation; Next-generation sequencing; Non-invasive diagnostics; Pancreatitis; Pancreato-biliary cancer

Distant metastases in colorectal carcinoma: A proposal for a new M1 subclassification - Merkel, Susanne; Weber, K.; Croner, R. S.; Golcher, H.; Göhl, Jonas; Agaimy, Abbas; Semrau, S.; Wein, Axel; Hohenberger, Werner; Wittekind, C.; Siebler, Jürgen (Ejso, 2016)
In 2010, the seventh Tumour-Node-Metastasis (TNM) cancer staging system of the International Union for Cancer Control (UICC) and the American Joint Committee of Cancer (AJCC) introduced a subdivision of M1 in the TNM classification of colorectal carcinomas. For the eighth TNM edition which will be released in the autumn of 2016 and will become effective in January 2017 new proposals are appreciated. The aim of our study was to define a new and better proposal for M1 subclassification.In a total of 814 patients with stage IV colorectal carcinoma treated between 1995 and 2013 prognostic factors were analysed in univariate and multivariate analyses.Advanced age, treatment in the earlier period 1995-2003, involvement of multiple metastatic sites, and non-curative resection were found to be independent prognostic factors. In patients with only one metastatic site, survival was good in patients with liver or lung metastasis, moderate in patients with metastasis of the peritoneum or non-regional lymph nodes and poor in patients with other rarely metastatic involved organs. The new proposal defines M1a, Metastasis confined to one organ: liver or lung (2-year survival 51.6%); M1b, Metastasis confined to one organ: peritoneum or non-regional lymph nodes, or Metastasis confined to liver plus lung (2-year survival 39.4%); and M1c, Metastasis confined to one organ: all other sites, or Metastasis in more than one organ, except liver plus lung (2-year survival 21.6%).The new proposal can identify three prognostic groups in stage IV colorectal carcinomas with significant differences in survival.
EVALuna2:2060

Distinct mircobiomes in right- and left-sided colon cancer - Langheinrich, Melanie C.; Wirtz, Stefan; Kneis, Barbara; Weber, Klaus; Brunner, Maximilian; Krautz, Christian; Trebicka, Jonel; Agaimy, Abbas; Grützmann, Robert; Kersting, Stephan (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-12-16

Diverging effects of premature birth and bronchopulmonary dysplasia on exercise capacity and physical activity - A case control study - Ruf, Katharina; Thomas, Wolfgang; Brunner, Maximilian; Speer, Christian P.; Hebestreit, Helge (Respiratory Research, 2019)
Background: Extreme prematurity has been associated with exercise intolerance and reduced physical activity. We hypothesized that children with bronchopulmonary dysplasia (BPD) would be especially affected based on long-term lung function impairments. Therefore, the objective of this study was to compare exercise capacity and habitual physical activity between children born very and extremely preterm with and without BPD and term-born children. Methods: Twenty-two school-aged children (aged 8 to 12 years) born with a gestational age < 32 weeks and a birthweight < 1500 g (9 with moderate or severe BPD (=BPD), 13 without BPD (=No-BPD)) and 15 healthy term-born children (=CONTROL) were included in the study. Physical activity was measured by accelerometry, lung function by spirometry and exercise capacity by an incremental cardiopulmonary exercise test. Results: Peak oxygen uptake was reduced in the BPD-group (83 ± 11%predicted) compared to the No-BPD group (91 ± 8%predicted) and the CONTROL group (94 ± 9%predicted). In a general linear model, variance of peak oxygen uptake was significantly explained by BPD status and height but not by prematurity (p < 0.001). Compared to CONTROL, all children born preterm spent significantly more time in sedentary behaviour (BPD 478 ± 50 min, No-BPD 450 ± 52 min, CONTROL 398 ± 56 min, p < 0.05) and less time in moderate-to-vigorous-physical activity (BPD 13 ± 8 min, No-BPD 16 ± 8 min, CONTROL 33 ± 16 min, p < 0.001). Prematurity but not BPD contributed significantly to explained variance in a general linear model of sedentary behaviour and likewise moderate-to-vigorous-physical activity (p < 0.05 and p < 0.001 respectively). Conclusion: In our cohort, BPD but not prematurity was associated with a reduced exercise capacity at school-age. However, prematurity regardless of BPD was related to less engagement in physical activity and more time spent in sedentary behaviour. Thus, our findings suggest diverging effects of prematurity and BPD on exercise capacity and physical activity.
CRIS-Team Scopus Importer:2019-12-03
Keywords: Bronchopulmonary dysplasia; Exercise capacity; Exercise testing; Physical activity; Preterm birth; Sedentary behaviour

DNA demethylation and tri-methylation of H3K4 at the TACSTD2 promoter are complementary players for TROP2 regulation in colorectal cancer cells - Gehring, Annemarie; Hübner, Kerstin; Rani, H.; Erlenbach-Wünsch, Katharina; Merkel, Susanne; Mahadevan, Vijayalakshmi; Grützmann, Robert; Hartmann, Arndt; Schneider-Stock, Regine (Scientific Reports, 2024)
TROP2 is a powerful cancer driver in colorectal cancer cells. Divergent epigenetic regulation mechanisms for the corresponding TACSTD2 gene exist such as miRNAs or DNA methylation. However, the role of TACSTD2 promoter hypermethylation in colorectal cancer has not been investigated yet. In this study, TROP2 expression strongly correlated with promoter methylation in different colorectal tumor cell lines. Treatment with 5-Azacytidine, a DNMT1 inhibitor, led to demethylation of the TACSTD2 promoter accompanied by an increase in TROP2 protein expression. TROP2 expression correlated with promoter methylation in vivo in human colon tumor tissue, thereby verifying promoter methylation as an important factor in the regulation of TROP2 expression in colorectal cancer. When performing a ChIP-Seq analysis in HCT116 and HT29 cells, we found that TACSTD2 promoter demethylation was accompanied by tri-methylation of H3K4. In silico analysis of GSE156613 data set confirmed that a higher binding of histone mark H3K4me3 around the TACSTD2 promoter was found in TACSTD2 high expressing tumors of colon cancer patients compared to the corresponding adjacent tumor tissue. Moreover, the link between TROP2 and the H3K4me3 code was even evident in tumors showing high intratumoral heterogeneity for TROP2 staining. Our data provide novel evidence for promoter demethylation and simultaneous gains of the active histone mark H3K4me3 across CpG-rich sequences, both being complementary mechanisms in the transcriptional regulation of TACSTD2 in colon cancer. The functional consequences of TROP2 loss in colorectal cancer needs to be further investigated.
CRIS-Team Scopus Importer:2024-02-16

DNA stool test for colorectal cancer: hypermethylation of the secreted frizzled-related protein-1 gene. - Zhang, Wei; Bauer, Michael; Croner, Roland S.; Pelz, Jörg Otto Wilhelm; Lodygin, Dimitri; Hermeking, Heiko; Stürzl, Michael; Hohenberger, Werner; Matzel, Klaus (Diseases of the colon & rectum, 2007)
To investigate a potential mode of noninvasive screening for colorectal cancer, we evaluated the hypermethylation of the secreted frizzled-related protein-1 gene promoter in human stool DNA. In stool samples from 36 patients with colorectal neoplasia (7 adenoma, 29 colorectal cancer) and 17 healthy control subjects, isolated DNA was treated with sodium bisulfite and analyzed by methylation-specific polymerase chain reaction with primers specific for methylated or unmethylated promoter sequences of the secreted frizzled-related protein-1 gene. Hypermethylation of the secreted frizzled-related protein-1 promoter was present in the stool DNA of patients with adenoma and colorectal cancer. A sensitivity of 89 percent and specificity of 86 percent were achieved in the detection of colorectal neoplasia. The difference in hypermethylation status of the secreted frizzled-related protein-1 promoter between the patients with colorectal neoplasia and the control group was statistically highly significant (P < 0.001). Adenoma and early tumor Stage I (International Union Against Cancer) displayed both unmethylated and methylated secreted frizzled-related protein-1 promoter sequences, whereas advanced tumor stages showed only methylated secreted frizzled-related protein-1 (P = 0.05). The results indicate that this DNA stool test of hypermethylation of the secreted frizzled-related protein-1 promoter is a sensitive and specific method. It has the potential of a clinically useful test for the early detection of colorectal cancer. PURPOSE METHODS RESULTS CONCLUSIONS
Keywords: DNA methylation; Colorectal cancer; Secreted frizzled-related protein; Stool DNA test; Epigenetic marker; Cancer screening

Donor Site Morbidity of Patients Receiving Vertical Rectus Abdominis Myocutaneous Flap for Perineal, Vaginal or Inguinal Reconstruction - Schellerer, Vera; Bartholomé, Lenka; Langheinrich, Melanie; Grützmann, Robert; Horch, Raymund E.; Merkel, Susanne; Weber, Klaus (World Journal of Surgery, 2020)
Background: Management of donor site closure after harvesting a vertical rectus abdominis myocutaneous (VRAM) flap is discussed heterogeneously in the literature. We aim to analyze the postoperative complications of the donor site depending on the closure technique. Methods: During a 12-year period (2003–2015), 192 patients in our department received transpelvic VRAM flap reconstruction. Prospectively collected data were analyzed retrospectively. Results: 182 patients received a VRAM flap reconstruction for malignant, 10 patients for benign disease. The median age of patients was 62 years. 117 patients (61%) received a reconstruction of donor site by Vypro® mesh, 46 patients (24%) by Vicryl® mesh, 23 patients (12%) by direct closure and 6 patients (3%) by combination of different meshes. 32 patients (17%) developed in total 34 postoperative complications at the donor site. 22 complications (11%) were treated conservatively, 12 (6%) surgically. 17 patients (9%) developed incisional hernia during follow-up, with highest incidence in the Vicryl® group (n = 8; 17%) and lowest in the Vypro® group (n = 7; 6%). Postoperative parastomal hernias were found in 30 patients (16%) including three patients with simultaneous hernia around an urostomy and a colostomy. The highest incidence of parastomal hernia was found in patients receiving primary closure of the donor site (n = 6; 26%), the lowest incidence in the Vypro® group (n = 16; 14%). Conclusion: The use of Vypro® mesh for donor site closure appears to be associated with a low postoperative incidence of complications and can therefore be recommended as a preferred technique.
CRIS-Team Scopus Importer:2020-10-09

Do surgical skills affect outcomes? - Tou, Samson; Gomez Ruiz, M.; Gallagher, A. G.; Eardley, N. J.; Matzel, Klaus (Colorectal Disease, 2020)
CRIS-Team WoS Importer:2020-09-25

DYNAMIC CHANGES IN O-GLCNACYLATION REGULATE OSTEOCLAST DIFFERENTIATION AND BONE LOSS IN ARTHRITIS - Chen, Chih-Wei; Li, Y. N.; Trinh, Minh Thuong; Honglin, Z.; Matei, Alexandru-Emil; Ding, Xiao; Tran Manh, Cuong; Xu, Xiaohan; Liebel, C.; Liang, Ruifang; Huang, M. C.; Lin, N. Y.; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2021)
CRIS-Team WoS Importer:2021-10-01

Dynamic changes in O-GlcNAcylation regulate osteoclast differentiation and bone loss via nucleoporin 153 - Li, Yi-Nan; Chen, Chih-Wei; Trinh, Minh Thuong; Zhu, Honglin; Matei, Alexandru-Emil; Györfi, Andrea-Hermina; Kuwert, Frederic; Hubel, Philipp; Ding, Xiao; Tran Manh, Cuong; Xu, Xiaohan; Liebel, Christoph; et al. (Bone Research, 2022)
Bone mass is maintained by the balance between osteoclast-induced bone resorption and osteoblast-triggered bone formation. In inflammatory arthritis such as rheumatoid arthritis (RA), however, increased osteoclast differentiation and activity skew this balance resulting in progressive bone loss. O-GlcNAcylation is a posttranslational modification with attachment of a single O-linked β-D-N-acetylglucosamine (O-GlcNAc) residue to serine or threonine residues of target proteins. Although O-GlcNAcylation is one of the most common protein modifications, its role in bone homeostasis has not been systematically investigated. We demonstrate that dynamic changes in O-GlcNAcylation are required for osteoclastogenesis. Increased O-GlcNAcylation promotes osteoclast differentiation during the early stages, whereas its downregulation is required for osteoclast maturation. At the molecular level, O-GlcNAcylation affects several pathways including oxidative phosphorylation and cell-cell fusion. TNFα fosters the dynamic regulation of O-GlcNAcylation to promote osteoclastogenesis in inflammatory arthritis. Targeted pharmaceutical or genetic inhibition of O-GlcNAc transferase (OGT) or O-GlcNAcase (OGA) arrests osteoclast differentiation during early stages of differentiation and during later maturation, respectively, and ameliorates bone loss in experimental arthritis. Knockdown of NUP153, an O-GlcNAcylation target, has similar effects as OGT inhibition and inhibits osteoclastogenesis. These findings highlight an important role of O-GlcNAcylation in osteoclastogenesis and may offer the potential to therapeutically interfere with pathologic bone resorption.
CRIS-Team Scopus Importer:2022-08-05

EBV latent membrane protein-1 protects B cells from apoptosis by inhibition of BAX - Naschberger, Elisabeth; Stürzl, Michael; et al. (Blood, 2005)
Latent membrane protein 1 (LMP-1) of Epstein-Barr virus (EBV) promotes tumorigenesis by inhibiting apoptosis. We show that an important antiapoptotic activity of LMP-1 is the inhibition of Bcl2-associated protein X (Bax), a potent proapoptotic protein. BAX expression was regulated by LMP-1 activation of nuclear factor κB (NF-κB) via the C-terminal activation region 1 (CTAR-1) and CTAR-2. Interestingly, p65/p50 inhibited, whereas p50/p50 increased, BAX promoter activity as demonstrated by overexpression and selective inhibition of these NF-κB isoforms. Electrophoretic mobility shift analysis revealed that LMP-1 activates 2 of the 3 NF-κB binding sites (κB1-κB3) in the BAX promoter. LMP-1 induced binding of the NF-κB heterodimer p65/p50 to the κB2 site and of the p50/p50 homodimer to the κB3 site. Promoter mutation analysis revealed that the κB2 site is necessary for inhibition of BAX promoter activity and the κB3 site, for its activation. However, the activation of the BAX promoter by LMP-1 was observed only in the presence of specific inhibitors of p65/p50. In all other cases, LMP-1 inhibited BAX promoter activity. Most importantly, the antiapoptotic activity of LMP-1 was considerably decreased in cells deficient for BAX. These results indicate that the inhibition of Bax may be an important antiapoptotic activity of LMP-1. © 2005 by The American Society of Hematology.
Created from Fastlane, Scopus look-up

Effective local control of advanced soft tissue sarcoma with neoadjuvant chemoradiotherapy and surgery: A single institutional experience - Stubbe, Franziska; Agaimy, Abbas; Ott, O.; Lettmaier, S.; Vassos, N.; Croner, R.; Hohenberger, Werner; Fietkau, Rainer; Semrau, S. (Cancer Radiotherapie, 2016)
There is a sound theoretical basis but little clinical evidence substantiating the benefits of concurrent chemoradiotherapy with two-drug chemotherapy for locally advanced soft tissue sarcomas. Our five-year data on the feasibility and effectiveness of neoadjuvant chemoradiotherapy with systemically effective doses of adriamycin and ifosfamide combined is presented here.Between 2000 and 2011, 53 patients with UICC (2010) stage I (n=1, 1.9%), II (n=12, 22.7%) or III (n=40, 75.5%) nonmetastatic soft tissue sarcoma received neoadjuvant chemoradiotherapy with ifosfamide (1.5g/m(2)/day, d1-5, q28) and doxorubicin (50mg/m(2)/day, d3, q28) plus concurrent radiotherapy with a target dose of 50-64Gy (median 60Gy). The treatment of 34 patients (64.2%) was combined with hyperthermia.At five years, the local control rate was 89.9% (±5.7%), distant metastasis-free survival 66.6% (±7.6%), and survival 83.3% (±6%). The R0 resection rate was 81.1%. Radiotherapy was completed as planned in all patients and chemotherapy in 42/53 (70.2%). Grades III (n=21, 29.6%) and IV (n=18, 34%) leukopenia was the main acute adverse event. All acute and chronic non-hematologic toxicities were moderate.Neoadjuvant chemoradiotherapy for soft tissue sarcoma is associated with good feasibility, manageable acute and late toxicities, and high local efficacy.
EVALuna2:6741

Effect of Circular Stapler Diameter on Anastomotic Leakage Rate and Stenosis After Open Total Gastrectomy With Esophagojejunostomy: A Substantive Retrospective Propensity Score Matched Series. - Mittelstädt, Anke; Reitberger, Helena; Fleischmann, Julia; Elshafei, Moustafa; Brunner, Maximilian; Anthuber, Anna; Krautz, Christian; Lucio, Marianna; Merkel, Susanne; Grützmann, Robert; Weber, Georg (Annals of Surgery Open, 2022)
BACKGROUND: Anastomotic leakage (AL) and stenosis (AS) are two of the most severe postoperative complications after total gastrectomy with esophagojejunostomy. The stapler diameter can be chosen by the surgeon. Therefore, this study aims to assess the correlation between the stapler size as main independent variable as well as other different risk factors and AL and AS. METHODS: We conducted a retrospective analysis of data from 356 patients who underwent open total gastrectomy between 2000 and 2018, mostly due to gastric cancer (96.9%). After propensity score matching the outcome parameters AL and AS were compared between the two stapler size groups. We also assessed different risk factors for AL and AS in cancer patients using multivariate analysis. RESULTS: Small circular stapler diameter (21/25 mm; n = 147 vs 28/29/31 mm; n = 209) was identified as a significant risk factor for the occurrence of AL (10% vs 4% for smaller vs larger staplers; P = 0.042). In multivariate analysis for the occurrence of AL an ASA score ≥ 3 could be identified as a risk factor (OR 2.85; 95% CI = 1.13-7.15; P = 0.026). Additionally, smaller stapler size could be identified as a risk factor for AS (OR small 1.00, OR large 0.24; 95% CI: 0.06-0.97; P = 0.045). AL was associated with lower survival (18.1 vs 38.16 months; P = 0.0119). CONCLUSION: The application of a larger circular stapler for esophagojejunostomy in open total gastrectomy shows significantly lower rates of AL and stenosis. Therefore, the largest possible stapler diameter should be applied.
EVALuna2:547490

Effect of Hospital Volume on In-hospital Morbidity and Mortality Following Pancreatic Surgery in Germany - Krautz, Christian; Nimptsch, Ulrike; Mansky, Thomas; Grützmann, Robert; Weber, Georg (Annals of Surgery, 2017)
We aimed to determine the effect of hospital volume on in-hospital mortality, and failure to rescue following major pancreatic resections using hospital discharge data of every inpatient case in Germany.Several studies have found strong volume-outcome relationships in pancreatic surgery, with high mortality in low-volume facilities. However, their datasets were only based on portions of national populations. In addition, these studies did not assess the effect of hospital volume according to other crucial variables such as medical indications, postoperative complications, and failure to rescue.We studied all inpatient cases of major pancreatic surgery (n = 60,858) in Germany from 2009 to 2014, using national hospital discharge data. We evaluated the association between hospital volume and in-hospital mortality following major pancreatic resections by using multivariate regression methods. In addition, we analyzed rates of major complications and failure to rescue across hospital volume quintiles.Risk-adjusted in-hospital mortality varied widely across hospital volume quintiles, from 6.5% (95% CI 6.0-7.0) in very high volume hospitals to 11.5% (95% CI 10.9-12.1) in very low volume hospitals (OR 0.47, 95% CI 0.41-0.54). Rates of postoperative interventions necessary for complications and failure to rescue were lower in higher volume hospitals [eg, mortality following septic complications in very high volume hospitals: 24.2% (95% CI 22.4-26.1) vs. very low volume hospitals: 36.8% (34.9-38.7)]. Moreover, we estimated that centralization of surgical care to the minimum volume and mortality risk of the medium volume quintile could prevent at least 94 deaths per year.In Germany, patients who are undergoing major pancreatic resections have improved outcomes if they are admitted to higher volume hospitals. As current health policies failed to centralize pancreatic surgery procedures in Germany, new strategies to initiate a sufficient centralization process in the field of pancreatic surgery are needed.
EVALuna2:15282

Effect of the COVID-19 pandemic on surgery for indeterminate thyroid nodules (THYCOVID): a retrospective, international, multicentre, cross-sectional study - Medas, Fabio; Dobrinja, Chiara; Al-Suhaimi, Ebtesam Abdullah; Altmeier, Julia; Anajar, Said; Arikan, Akif Enes; Azaryan, Irina; Bains, Lovenish; Basili, Giancarlo; Bolukbasi, Hakan; Bononi, Marco; Borumandi, Farzad; et al. (Lancet Diabetes and Endocrinology, 2023)
BACKGROUND: Since its outbreak in early 2020, the COVID-19 pandemic has diverted resources from non-urgent and elective procedures, leading to diagnosis and treatment delays, with an increased number of neoplasms at advanced stages worldwide. The aims of this study were to quantify the reduction in surgical activity for indeterminate thyroid nodules during the COVID-19 pandemic; and to evaluate whether delays in surgery led to an increased occurrence of aggressive tumours. METHODS: In this retrospective, international, cross-sectional study, centres were invited to participate in June 22, 2022; each centre joining the study was asked to provide data from medical records on all surgical thyroidectomies consecutively performed from Jan 1, 2019, to Dec 31, 2021. Patients with indeterminate thyroid nodules were divided into three groups according to when they underwent surgery: from Jan 1, 2019, to Feb 29, 2020 (global prepandemic phase), from March 1, 2020, to May 31, 2021 (pandemic escalation phase), and from June 1 to Dec 31, 2021 (pandemic decrease phase). The main outcomes were, for each phase, the number of surgeries for indeterminate thyroid nodules, and in patients with a postoperative diagnosis of thyroid cancers, the occurrence of tumours larger than 10 mm, extrathyroidal extension, lymph node metastases, vascular invasion, distant metastases, and tumours at high risk of structural disease recurrence. Univariate analysis was used to compare the probability of aggressive thyroid features between the first and third study phases. The study was registered on ClinicalTrials.gov, NCT05178186. FINDINGS: Data from 157 centres (n=49 countries) on 87 467 patients who underwent surgery for benign and malignant thyroid disease were collected, of whom 22 974 patients (18 052 [78·6%] female patients and 4922 [21·4%] male patients) received surgery for indeterminate thyroid nodules. We observed a significant reduction in surgery for indeterminate thyroid nodules during the pandemic escalation phase (median monthly surgeries per centre, 1·4 [IQR 0·6-3·4]) compared with the prepandemic phase (2·0 [0·9-3·7]; p<0·0001) and pandemic decrease phase (2·3 [1·0-5·0]; p<0·0001). Compared with the prepandemic phase, in the pandemic decrease phase we observed an increased occurrence of thyroid tumours larger than 10 mm (2554 [69·0%] of 3704 vs 1515 [71·5%] of 2119; OR 1·1 [95% CI 1·0-1·3]; p=0·042), lymph node metastases (343 [9·3%] vs 264 [12·5%]; OR 1·4 [1·2-1·7]; p=0·0001), and tumours at high risk of structural disease recurrence (203 [5·7%] of 3584 vs 155 [7·7%] of 2006; OR 1·4 [1·1-1·7]; p=0·0039). INTERPRETATION: Our study suggests that the reduction in surgical activity for indeterminate thyroid nodules during the COVID-19 pandemic period could have led to an increased occurrence of aggressive thyroid tumours. However, other compelling hypotheses, including increased selection of patients with aggressive malignancies during this period, should be considered. We suggest that surgery for indeterminate thyroid nodules should no longer be postponed even in future instances of pandemic escalation.None.
CRIS-Team Scopus Importer:2023-06-30

Effects of Adjuvant Exercise and Nutrition Therapy on Muscle Fibre Biomechanics in Gastrointestinal Cancer Patients - Haug, Michael; Schwappacher, Raphaela; Pollmann, Charlotte; Ritter, Paul; Michael, Mena; Herrmann, Hans Joachim; Grützmann, Robert; Mittelstädt, Anke; Neurath, Markus; Zopf, Yurdagül; Friedrich, Oliver (Cancers, 2024)
Patients with aggressive cancer, e.g., gastrointestinal cancer, are prone (≥50% chance) to developing cancer cachexia (CC). Little is known about the effects of CC on the biomechanical function of muscle. A promising prevention strategy was found in the form of a multi-modal therapy combining mild resistance exercise (e.g., whole-body electro-myostimulation, WB-EMS) and a protein-rich diet. In a previous study of ours, this was effective in counteracting the loss of muscle mass, yet a systematic and comprehensive assessment of active and passive single muscle fibre functions was so far absent. This pilot study investigated the biomechanical function of single muscle fibres (rectus abdominis) from the biopsies of conventionally treated (pre-)cachectic cancer ((pre-)CC) patients (m = 9), those receiving the multi-modal therapy comprising WB-EMS training and protein-rich nutrition (m = 3), and a control group (m = 5). Our findings not only align with previous findings showing the absolute force loss in CC that is accelerated by atrophy but also speak in favour of a different, potentially energy- and Ca2+-homeostasis-related effect that compromises muscle contraction (F 0.9 mN vs. F 0.6 mN in control patients). However, myofibrillar Ca2+ sensitivity and the quality of contraction were unaltered (pCa50: 5.6–5.8). Single fibres from the (pre-)CC patients receiving WB-EMS training and protein supplementation were significantly more compliant (p < 0.001 at ≥130% of resting length L0). Those fibres displayed a similar softness to the ones from the control patients (axial compliance 15 m/N at ≥130% L0), while single fibres from the patients with (developing) cachexia were significantly stiffer (axial compliance 7 m/N, p < 0.001 at ≥130% L0). Adjuvant multi-modal therapy (WB-EMS training and nutritional support) contributes to maintaining the axial compliance of single fibres and potentially improves the quality of life for patients at risk of developing CC.
CRIS-Team Scopus Importer:2024-05-03
Keywords: cancer cachexia; multi-modal therapy; protein-rich diet; resistance training; single fibres; skeletal muscle

Endothelial CCR2 signaling induced by colon carcinoma cells enables extravasation via the JAK2-Stat5 and p38MAPK pathway. - Wolf, Monika Julia; Hoos, Alexandra; Bauer, Judith; Boettcher, Steffen; Knust, Markus; Weber, Achim; Simonavicius, Nicole; Schneider, Christoph; Lang, Matthias; Stürzl, Michael; Croner, Roland S.; Konrad, Andreas; et al. (Cancer Cell, 2012)
Increased expression of the chemokine CCL2 in tumor cells correlates with enhanced metastasis, poor prognosis, and recruitment of CCR2(+)Ly6C(hi) monocytes. However, the mechanisms driving tumor cell extravasation through the endothelium remain elusive. Here, we describe CCL2 upregulation in metastatic UICC stage IV colon carcinomas and demonstrate that tumor cell-derived CCL2 activates the CCR2(+) endothelium to increase vascular permeability in vivo. CCR2 deficiency prevents colon carcinoma extravasation and metastasis. Of note, CCR2 expression on radio-resistant cells or endothelial CCR2 expression restores extravasation and metastasis in Ccr2(-/-) mice. Reduction of CCR2 expression on myeloid cells decreases but does not prevent metastasis. CCL2-induced vascular permeability and metastasis is dependent on JAK2-Stat5 and p38MAPK signaling. Our study identifies potential targets for treating CCL2-dependent metastasis.

Endothelial cells of human colorectal cancer and healthy colon reveal phenotypic differences in culture - Stürzl, Michael; Naschberger, Elisabeth; et al. (Laboratory Investigation, 2007)
Antiangiogenic drugs have been used successfully for the treatment of colorectal cancer (CRC). Viable tumor endothelial cells (TEC) and normal endothelial cells (NEC) of uninvolved colon tissue of the same patient have not been available to optimize treatment strategies in vitro. Therefore, our target was to establish a protocol for the isolation of TEC and NEC. These cells were isolated with very high purity via magnetic cell sorting of tissue samples obtained from CRC and healthy colon of eight patients. TEC and NEC expressed CD31, CD105, VE-cadherin, VCAM-1, ICAM-1 and E-selectin, formed capillaries in basal membrane extract and were able to take up acetylated low-density lipoprotein. They were negative for podoplanin, CD45, CD68 and cytokeratin-20 indicating blood vessel endothelial lineage. Intense staining of von Willebrand factor (vWF) was observed in five of eight NEC cultures, whereas vWF was absent or only slightly expressed in all TEC cultures in vitro. Low intracellular concentration of vWF was also detected in TEC and NEC at the tissue level. This demonstrated that differences exhibited by TEC and NEC in vivo are stably perpetuated in culture. The isolated cultures may provide a useful in vitro model to elucidate epigenetic effects on angiogenesis in cancer and to optimize antiangiogenic therapy. © 2007 USCAP, Inc All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: Angiogenesis; Colorectal cancer; Endothelial cells; Von Willebrand factor

Endothelial progenitor cells are integrated in newly formed capillaries and alter adjacent fibrovascular tissue after subcutaneous implantation in a fibrin matrix - Bleiziffer, Oliver; Hammon, Matthias; Naschberger, Elisabeth; Lipnik, Karoline; Arkudas, Andreas; Rath, Subha; Pryymachuk, Galyna; Beier, Justus; Stürzl, Michael; Horch, Raymund E.; Kneser, Ulrich (Journal of Cellular and Molecular Medicine, 2011)
Vascularization of bioartificial matrices is crucial for successful tissue engineering. Endothelial progenitor cells (EPC) have shown vascularization potential in ischemic conditions and may also support blood vessel formation in tissue-engineered matrices. The aim of our study was to investigate the impact of a well-characterized murine embryonal EPC line (T17b-EPC) on vascularization and fibrovascular granulation tissue formation after suspension in a fibrine matrix followed by subcutaneous implantation in a separation chamber in rats. EPC were fluorescently labelled in vitro prior to implantation. After 3, 7 or 14 days, animals were killed followed by explantation and histological analysis of the constructs. Before the end of the experiment, Bandeirea Simplicifolia lectin was intravenously injected to mark the vascular ingrowth into the implanted constructs. The transplanted cells were histologically detected at all time-points and located almost exclusively within the fibrin matrix at day 3 but the number of cells in the clot continuously decreased over day 7 to day 14. Conversely, cells were detected within the newly formed granulation tissue in increasing numbers from day 3 over day 7 to day 14. Transplanted cells were also found in the intermuscular septa. Cell viability was confirmed by use of an EPC clone expressing β-galactosidase. Fluorescence microscopy demonstrated integration of the transplanted cells in newly formed blood vessels within the fibrovascular granulation tissue adjacent to the fibrin clot. Presence of cells in the fibrin clot lead to thicker granulation tissue and an increased blood vessel diameter compared to cell-free controls. Organ standard controls showed presence of the transplanted cells in spleens at day 14 after transplantation. In summary, EPC exhibited biological activity after subcutaneous implantation in a fibrin matrix by migration from the fibrin clot into the granulation tissue and along intermuscular septae, undergoing differentiation into mature endothelial cells and integration into newly formed blood vessels and altering fibrovascular granulation tissue development. EPC may hold promise to modulate blood vessel formation in bioartificial matrices. © 2011 Foundation for Cellular and Molecular Medicine/Blackwell Publishing Ltd.
Created from Fastlane, Scopus look-up
Keywords: Angiogenesis; Endothelial progenitor cells; Fibrin matrix; Tissue engineering

Engineering of vascularized transplantable bone tissues: induction of axial vascularization in an osteoconductive matrix using an arteriovenous loop. - Kneser, Ulrich; Polykandriotis, Elias; Ohnolz, Jan; Heidner, Kristina; Grabinger, Lucia; Euler, Simon; Amann, Kerstin Ute; Heß, Andreas; Brune, Kay; Greil, Peter; Stürzl, Michael; Horch, Raymund E. (Tissue Engineering -Larchmont, 2006)
This study demonstrates for the first time successful vascularization of solid porous matrices by means of an AV loop. Injection of osteogenic cells into axially prevascularized matrices may eventually create functional bioartificial bone tissues for reconstruction of large defects. Vascularization remains an obstacle to engineering of larger volume bone tissues. Our aim was to induce axial vascularization in a processed bovine cancellous bone (PBCB) matrix using an arteriovenous (AV) loop (artery, vein graft, and vein). Custom-made PBCB discs (9 x 5 mm) were implanted into rats. In group A (n = 19), the matrices were inserted into microsurgically constructed AV loops between the femoral vessels using a vein graft from the contralateral side. In group B (n = 19), there was no vascular carrier. The matrices were encased in isolation chambers. After 2, 4, and 8 weeks, the animals were perfused with India ink via the abdominal aorta. Matrices were explanted and subjected to histological and morphometric analysis. Results were compared with intravital dynamic micro & magnetic resonance imaging and scanning electron microscopy images of vascular corrosion replicas. In group A, significant vascularization of the matrix had occurred by the 8th week. At this time, vascular remodeling with organization into vessels of different sizes was evident. Blood vessels originated from all 3 zones of the AV loop. Group A was significantly superior to group B in terms of vascular density and vascularization kinetics. DISCUSSION INTRODUCTION METHODS RESULTS

Engineering Therapeutic Regulatory T Cells to Overexpress G Protein-Coupled Receptor 15 Improves Functional Fitness for In Vivo Gut Homing - Müller, Tanja; Liu, Lijuan; Wiesinger, Manuel; Atreya, Imke; Atreya, Raja; Bacher, Petra; Becker, Christoph; Bojarski, Christian; Britzen-Laurent, Nathalie; Bosch-Voskens, Caroline; Chang, Hyun Dong; Diefenbach, Andreas; et al. (Gastroenterology, 2025)
CRIS-Team Scopus Importer:2025-01-31

EPIGENETIC REGULATION OF FRA2 BY JMJD3 REGULATES FIBROBLAST ACTIVATION IN SYSTEMIC SCLEROSIS - Bergmann, C.; Brandt, Adrian; Dees, Clara; Wohlfahrt, T.; Zhang, Y.; Chen, Chih-Wei; Mallano, T.; Liang, Ruifang; Kagwiria, R.; Kam, P. -S.; Bozec, Aline; Abraham, D.; et al. (2017)
EVALuna2:35037

Epithelial OPA1 links mitochondrial fusion to inflammatory bowel disease - Bao, Lili; Yu, Yidong; Gonzalez Acera, Miguel; Patankar, Jay; Gießl, Andreas; Sturm, Gregor; Kühl, Anja A.; Atreya, Raja; Erkert, Lena; Gamez-Belmonte, Reyes; Krug, Susanne M.; Schmid, Benjamin; et al. (Science Translational Medicine, 2025)
Dysregulation at the intestinal epithelial barrier is a driver of inflammatory bowel disease (IBD). However, the molecular mechanisms of barrier failure are not well understood. Here, we demonstrate dysregulated mitochondrial fusion in intestinal epithelial cells (IECs) of patients with IBD and show that impaired fusion is sufficient to drive chronic intestinal inflammation. We found reduced expression of mitochondrial fusion–related genes, such as the dynamin-related guanosine triphosphatase (GTPase) optic atrophy 1 (OPA1), and fragmented mitochondrial networks in crypt IECs of patients with IBD. Mice with Opa1 deficiency in the gut epithelium (Opa1i∆IEC) spontaneously developed chronic intestinal inflammation with mucosal ulcerations and immune cell infiltration. Intestinal inflammation in Opa1i∆IEC mice was driven by microbial translocation and associated with epithelial progenitor cell death and gut barrier dysfunction. Opa1-deficient epithelial cells and human organoids exposed to a pharmacological OPA1 inhibitor showed disruption of the mitochondrial network with mitochondrial fragmentation and changes in mitochondrial size, ultrastructure, and function, resembling changes observed in patient samples. Pharmacological inhibition of the GTPase dynamin-1–like protein in organoids derived from Opa1i∆IEC mice partially reverted this phenotype. Together, our data demonstrate a role for epithelial OPA1 in regulating intestinal immune homeostasis and epithelial barrier function. Our data provide a mechanistic explanation for the observed mitochondrial dysfunction in IBD and identify mitochondrial fusion as a potential therapeutic target in this disease.
CRIS-Team Scopus Importer:2025-01-31

Epithelial presenilin-1 drives colorectal tumour growth by controlling EGFR-COX2 signalling - Gámez Belmonte, Maria de los Reyes; Mahapatro, Mousumi; Erkert, Lena; Gonzalez Acera, Miguel; Naschberger, Elisabeth; Yu, Yuqiang; Tena-Garitaonaindia, Mireia; Patankar, Jay; Wagner, Yara; Podstawa, Eva; Schoedel, Lena; Bubeck, Marvin; et al. (Gut, 2022)
Objective Psen1 was previously characterised as a crucial factor in the pathogenesis of neurodegeneration in patients with Alzheimer's disease. Little, if any, is known about its function in the gut. Here, we uncovered an unexpected functional role of Psen1 in gut epithelial cells during intestinal tumourigenesis. Design Human colorectal cancer (CRC) and control samples were investigated for PSEN1 and proteins of the gamma-secretase complex. Tumour formation was analysed in the AOM-DSS and Apc (min/+) mouse models using newly generated epithelial-specific Psen1 deficient mice. Psen1 deficient human CRC cells were studied in a xenograft tumour model. Tumour-derived organoids were analysed for growth and RNA-Seq was performed to identify Psen1-regulated pathways. Tumouroids were generated to study EGFR activation and evaluation of the influence of prostanoids. Results PSEN1 is expressed in the intestinal epithelium and its level is increased in human CRC. Psen1-deficient mice developed only small tumours and human cancer cell lines deficient in Psen1 had a reduced tumourigenicity. Tumouroids derived from Psen1-deficient Apc (min/+) mice exhibited stunted growth and reduced cell proliferation. On a molecular level, PSEN1 potentiated tumour cell proliferation via enhanced EGFR signalling and COX-2 production. Exogenous administration of PGE(2) reversed the slow growth of PSEN1 deficient tumour cells via PGE(2) receptor 4 (EP4) receptor signalling. Conclusions Psen1 drives tumour development by increasing EGFR signalling via NOTCH1 processing, and by activating the COX-2-PGE(2) pathway. PSEN1 inhibition could be a useful strategy in treatment of CRC.
CRIS-Team WoS Importer:2022-11-04
Keywords: colorectal cancer; colorectal adenomas; arachidonic and metabolism

ESCP President's report - Matzel, Klaus (Colorectal Disease, 2022)
CRIS-Team WoS Importer:2022-09-23

European expert consensus on a structured approach to training robotic-assisted low anterior resection using performance metrics - Tou, Samson; Gomez Ruiz, M.; Gallagher, A. G.; Matzel, Klaus (Colorectal Disease, 2020)
Aim: The aim was to develop and operationally define ‘performance metrics’ that characterize a reference approach to robotic-assisted low anterior resection (RA-LAR) and to obtain face and content validity through a consensus meeting. Method: Three senior colorectal surgeons with robotic experience and a senior behavioural scientist formed the Metrics Group. We used published guidelines, training materials, manufacturers’ instructions and unedited videos of RA-LAR to deconstruct the operation into defined, measurable components – performance metrics (i.e. procedure phases, steps, errors and critical errors). The performance metrics were then subjected to detailed critique by 18 expert colorectal surgeons in a modified Delphi process. Results: Performance metrics for RA-LAR had 15 procedure phases, 128 steps, 89 errors and 117 critical errors in women, 88 errors and 118 critical errors in men. After the modified Delphi process the final performance metrics consisted of 14 procedure phases, 129 steps, 88 errors and 115 critical errors in women, 87 errors and 116 critical errors in men. After discussion by the Delphi panel, all procedure phases received unanimous consensus apart from phase I (patient positioning and preparation, 83%) and phase IV (docking, 94%). Conclusion: A robotic rectal operation can be broken down into procedure phases, steps, with errors and critical errors, known as performance metrics. The face and content of these metrics have been validated by a large group of expert robotic colorectal surgeons from Europe. We consider the metrics essential for the development of a structured training curriculum and standardized procedural assessment for RA-LAR.
CRIS-Team Scopus Importer:2020-09-04
Keywords: colorectal surgery; low anterior resection; metrics; proficiency-based progression; robotic surgery; training

Evaluating predictive modeling algorithms to assess patient eligibility for clinical trials from routine data - Köpcke, Felix; Lubgan, Dorota; Fietkau, Rainer; Scholler, Axel; Nau, Carla; Stürzl, Michael; Croner, Roland S.; Prokosch, Hans-Ulrich; Toddenroth, Dennis (BMC Medical Informatics and Decision Making, 2013)
Background: The necessity to translate eligibility criteria from free text into decision rules that are compatible with data from the electronic health record (EHR) constitutes the main challenge when developing and deploying clinical trial recruitment support systems. Recruitment decisions based on case-based reasoning, i.e. using past cases rather than explicit rules, could dispense with the need for translating eligibility criteria and could also be implemented largely independently from the terminology of the EHR's database. We evaluated the feasibility of predictive modeling to assess the eligibility of patients for clinical trials and report on a prototype's performance for different system configurations. Methods. The prototype worked by using existing basic patient data of manually assessed eligible and ineligible patients to induce prediction models. Performance was measured retrospectively for three clinical trials by plotting receiver operating characteristic curves and comparing the area under the curve (ROC-AUC) for different prediction algorithms, different sizes of the learning set and different numbers and aggregation levels of the patient attributes. Results: Random forests were generally among the best performing models with a maximum ROC-AUC of 0.81 (CI: 0.72-0.88) for trial A, 0.96 (CI: 0.95-0.97) for trial B and 0.99 (CI: 0.98-0.99) for trial C. The full potential of this algorithm was reached after learning from approximately 200 manually screened patients (eligible and ineligible). Neither block- nor category-level aggregation of diagnosis and procedure codes influenced the algorithms' performance substantially. Conclusions: Our results indicate that predictive modeling is a feasible approach to support patient recruitment into clinical trials. Its major advantages over the commonly applied rule-based systems are its independency from the concrete representation of eligibility criteria and EHR data and its potential for automation. © 2013 Köpcke et al.; licensee BioMed Central Ltd.
UnivIS-Import:2015-04-14:Pub.2013.tech.IMMD.infome.evalua_3

Evaluation of response using FDG-PET/CT and diffusion weighted MRI after radiochemotherapy of pancreatic cancer: a non-randomized, monocentric phase II clinical trial—PaCa-DD-041 (Eudra-CT 2009-011968-11) - Zimmermann, Carolin; Distler, Marius; Jentsch, Christina; Blum, Sophia; Folprecht, Gunnar; Zöphel, Klaus; Polster, Heike; Troost, Esther G.C.; Abolmaali, Nasreddin; Weitz, Jürgen; Baumann, Michael; Saeger, Hans Detlev; et al. (Strahlentherapie und Onkologie, 2020)
Background: Pancreatic cancer is a devastating disease with a 5-year survival rate of 20–25%. As approximately only 20% of patients diagnosed with pancreatic cancer are initially staged as resectable, it is necessary to evaluate new therapeutic approaches. Hence, neoadjuvant (radio)chemotherapy is a promising therapeutic option, especially in patients with a borderline resectable tumor. The aim of this non-randomized, monocentric, prospective, phase II clinical study was to assess the prognostic value of functional imaging techniques, i.e., [18F]2-fluoro-2-deoxy-d-glucose positron emission tomography/computed tomography (FDG-PET/CT) and diffusion weighted magnetic resonance imaging (DW-MRI), prior to and during neoadjuvant radiochemotherapy. Methods: Patients with histologically proven resectable, borderline resectable or unresectable non-metastatic pancreatic adenocarcinoma received induction chemotherapy followed by neoadjuvant radiochemotherapy. Patients underwent FDG-PET/CT and DW-MRI including T1- and T2-weighted sequences prior to and after neoadjuvant chemotherapy as well as following induction radiochemotherapy. The primary endpoint was the evaluation of the response as quantified by the standardized uptake value (SUV) measured with FDG-PET. Response to treatment was evaluated by FDG-PET and DW-MRI during and after the neoadjuvant course. Morphologic staging was performed using contrast-enhanced CT and contrast-enhanced MRI to decide inclusion of patients and resectability after neoadjuvant therapy. In those patients undergoing subsequent surgery, imaging findings were correlated with those of the pathologic resection specimen. Results: A total of 25 patients were enrolled in the study. The response rate measured by FDG-PET was 85% with a statistically significant decrease of the maximal SUV (SUVmax) during therapy (p < 0.001). Using the mean apparent diffusion coefficient (ADC), response was not detectable with DW-MRI. After neoadjuvant treatment 16 patients underwent surgery. In 12 (48%) patients tumor resection could be performed. The median overall survival of all patients was 25 months (range: 7–38 months). Conclusion: Based on these limited patient numbers, it was possible to show that this trial design is feasible and that the neoadjuvant therapy regime was well tolerated. FDG-PET/CT may be a reliable method to evaluate response to the combined therapy. In contrast, when evaluating the response using mean ADC, DW-MRI did not show conclusive results.
CRIS-Team Scopus Importer:2020-07-17
Keywords: Downstaging; Imaging; Neoadjuvant radio-/chemotherapy; Pancreas cancer; Pancreatic adenocarcinoma; PDAC; Surgery

Evidence for PTGER4, PSCA, and MBOAT7 as risk genes for gastric cancer on the genome and transcriptome level - Heinrichs, Sophie K. M.; Hess, Timo; Becker, Jessica; Hamann, Lutz; Vashist, Yogesh K.; Butterbach, Katja; Schmidt, Thomas; Alakus, Hakan; Krasniuk, Iurii; Hoeblinger, Aksana; Lingohr, Philipp; Ludwig, Monika; et al. (Cancer Medicine, 2018)
Genetic associations between variants on chromosome 5p13 and 8q24 and gastric cancer (GC) have been previously reported in the Asian population. We aimed to replicate these findings and to characterize the associations at the genome and transcriptome level. We performed a fine-mapping association study in 1926 GC patients and 2012 controls of European descent using high dense SNP marker sets on both chromosomal regions. Next, we performed expression quantitative trait locus (eQTL) analyses using gastric transcriptome data from 143 individuals focusing on the GC associated variants. On chromosome 5p13 the strongest association was observed at rs6872282 (P = 2.53 × 10 ) and on chromosome 8q24 at rs2585176 (P = 1.09 × 10 ). On chromosome 5p13 we found cis-eQTL effects with an upregulation of PTGER4 expression in GC risk allele carrier (P = 9.27 × 10 ). On chromosome 8q24 we observed cis-eQTL effects with an upregulation of PSCA expression in GC risk allele carrier (P = 2.17 × 10 ). In addition, we found trans-eQTL effects for the same variants on 8q24 with a downregulation of MBOAT7 expression in GC risk allele carrier (P = 3.11 × 10 ). In summary, we confirmed and refined the previously reported GC associations at both chromosomal regions. Our data point to shared etiological factors between Asians and Europeans. Furthermore, our data imply an upregulated expression of PTGER4 and PSCA as well as a downregulated expression of MBOAT7 in gastric tissue as risk-conferring GC pathomechanisms.
EVALuna2:91838

Exosomal ROR1 in peritoneal fluid identifies peritoneal disseminated PDAC and is associated with poor survival - Mittelstädt, Anke; Anthuber, Anna; David, Paul; Podolska, Malgorzata; Benard, Alan; Brunner, Maximilian; Krautz, Christian; Jacobsen, Anne; Denz, Axel; Weber, Klaus; Merkel, Susanne; Hackner, Danilo; et al. (Frontiers in Immunology, 2024)
Background: Pancreatic ductal adenocarcinoma (PDAC) is one of the deadliest forms of cancer and peritoneal dissemination is one major cause for this poor prognosis. Exosomes have emerged as promising biomarkers for gastrointestinal cancers and can be found in all kinds of bodily fluids, also in peritoneal fluid (PF). This is a unique sample due to its closeness to gastrointestinal malignancies. The receptor tyrosine kinase-like orphan receptor 1 (ROR1) has been identified as a potential biomarker in human cancers and represents a promising target for an immunotherapy approach, which could be considered for future treatment strategies. Here we prospectively analyzed the exosomal surface protein ROR1 (exo-ROR1) in PF in localized PDAC patients (PER-) on the one hand and peritoneal disseminated tumor stages (PER+) on the other hand followed by the correlation of exo-ROR1 with clinical-pathological parameters. Methods: Exosomes were isolated from PF and plasma samples of non-cancerous (NC) (n = 15), chronic pancreatitis (CP) (n = 4), localized PDAC (PER-) (n = 18) and peritoneal disseminated PDAC (PER+) (n = 9) patients and the surface protein ROR1 was detected via FACS analysis. Additionally, soluble ROR1 in PF was analyzed. ROR1 expression in tissue was investigated using western blots (WB), qPCR, and immunohistochemistry (IHC). Exosome isolation was proven by Nano Tracking Analysis (NTA), WB, Transmission electron microscopy (TEM), and BCA protein assay. The results were correlated with clinical data and survival analysis was performed. Results: PDAC (PER+) patients have the highest exo-ROR1 values in PF and can be discriminated from NC (p <0.0001), PDAC (PER-) (p <0.0001), and CP (p = 0.0112). PDAC (PER-) can be discriminated from NC (p = 0.0003). In plasma, exo-ROR1 is not able to distinguish between the groups. While there is no expression of ROR1 in the exocrine pancreatic tissue, PDAC and peritoneal metastasis show expression of ROR1. High exo-ROR1 expression in PF is associated with lower overall survival (p = 0.0482). Conclusion: With exo-ROR1 in PF we found a promising diagnostic and prognostic biomarker possibly discriminating between NC, PDAC (PER-) and PDAC (PER+) and might shed light on future diagnostic and therapeutic concepts in PDAC.
CRIS-Team Scopus Importer:2024-06-14
Keywords: biomarker; exosomes; PDAC; peritoneal carcinomatosis; peritoneal fluid; peritoneal lavage; ROR1; targeted therapy

Expert consensus on a train-the-trainer curriculum for robotic colorectal surgery - Gómez Ruiz, M.; Alfieri, S.; Becker, T.; Bergmann, M.; Boggi, U.; Collins, J.; Figueiredo, N.; Gögenur, I.; Matzel, Klaus; Miskovic, D.; Parvaiz, A.; Pratschke, J.; et al. (Colorectal Disease, 2019)
Aim: Robotic techniques are being increasingly used in colorectal surgery. There is, however, a lack of training opportunities and structured training programmes. Robotic surgery has specific problems and challenges for trainers and trainees. Ergonomics, specific skills and user–machine interfaces are different from those in traditional laparoscopic surgery. The aim of this study was to establish expert consensus on the requirements for a robotic train-the-trainer curriculum amongst robotic surgeons and trainers. Method: This is a modified Delphi-type study involving 14 experts in robotic surgery teaching. A reiterating 19-item questionnaire was sent out to the same group and agreement levels analysed. A consensus of 0.8 or higher was considered to be high-level agreement. Results: Response rates were 93–100% and most items reached high levels of agreement within three rounds. Specific requirements for a robotic faculty development curriculum included maximizing dual-console teaching, theatre team training, nontechnical skills training, patient safety, user–machine interface training and telementoring. Conclusion: A clear need for the development of a train-the-trainer curriculum has been identified. Further research is needed to assess feasibility, effectiveness and clinical impact of a robotic train-the-trainer curriculum.
CRIS-Team Scopus Importer:2019-06-04
Keywords: Delphi; Robotic surgery; trainer; training

Exploring the Causal Relationship between Ibuprofen Use and Osteoarthritis Risk: A Mendelian Randomization Study - Jian, Yongzhi; Lyu, Yanmin; Hashemolhosseini, Said (Biology, 2024)
This study explored the potential causal relationship between ibuprofen (IBU) use and the risk of developing osteoarthritis, a prevalent joint disorder characterized by pain and stiffness. We conducted a two-sample MR analysis using four distinct OA GWAS datasets as outcomes and single-nucleotide polymorphisms (SNPs) associated with IBU metabolism as exposures. The inverse variance weighted (IVW) and weighted median methods were utilized to assess the causal association by meta-analysis, while pleiotropy and heterogeneity were evaluated using MR–Egger regression and Cochran’s Q statistics. The MR analysis provided strong evidence for a causal association between IBU use and an increased risk of OA. A meta-analysis of the IVW and weighted median results across all datasets demonstrated an OR = 1.116 (95% CI = 1.063–1.170) and an OR = 1.110 (95% CI = 1.041–1.184). The consistency of the results obtained from different methods enhanced the reliability of the findings. Low pleiotropy and minimal heterogeneity were observed, further validating the results. The study supports a causal link between IBU use and an increased risk of OA, suggesting that IBU may accelerate the progression of OA while relieving symptoms. These findings highlight the importance of cautious use of IBU in clinical practice, especially considering its potential impact on long-term joint health.
CRIS-Team Scopus Importer:2024-10-04
Keywords: causal inference; GWAS; ibuprofen; Mendelian randomization; osteoarthritis

Expression and localization of axin 2 in colorectal carcinoma and its clinical implication - Schaal, Ute; Grenz, Sandra; Merkel, Susanne; Rau, Tilman; Hadjihannas, Michel; Kremmer, Elisabeth; Chudasama, Priya; Croner, Roland S.; Behrens, Jürgen; Stürzl, Michael; Naschberger, Elisabeth (International Journal of Colorectal Disease, 2013)
Purpose: Aberrant activation of the Wnt/β-catenin pathway plays a major role in the development of colorectal carcinoma (CRC). Axin 2 is a key protein of this pathway and is upregulated in CRC. Here, we investigated RNA- and protein expression of axin 2 in CRC tissues at the single cell level. Moreover, the association of axin 2 with prognosis and survival was investigated in a large cohort of CRC patients (n = 280). Methods: Localization and expression of axin 2 and β-catenin was investigated using in situ hybridization and immunohistochemical staining. The quantitative expression levels of axin 2 were determined using RT-qPCR. The association of axin 2 expression with prognosis and survival of the patients was determined by statistical analysis (logrank test, Kaplan-Meier). Results: Our results confirmed the upregulation of axin 2 in CRC and showed that it is broadly expressed in the cytoplasm of the tumor epithelial cells both, in the tumor center and at the invasion front. Axin 2 was rarely expressed by tumor stromal cells and only weakly by normal colonic epithelial cells. Staining of β-catenin and axin 2 in consecutive CRC tissue sections revealed that nuclear translocation of β-catenin in the tumor front was not associated with changes in the cytoplasmic localization of axin 2. Axin 2 did not show any association with proven prognostic factors or survival of the CRC patients. Conclusion: The generally increased expression of axin 2 in all tumor stages as compared to normal tissue suggests an initiating pathogenic function in the development of CRC. © 2013 Springer-Verlag Berlin Heidelberg.
Created from Fastlane, Scopus look-up
Keywords: β-Catenin; Axin 2; Colorectal carcinoma; Wnt/β-catenin signaling

Expression and role of the immune checkpoint regulator PD-L1 in the tumor-stroma interplay of pancreatic ductal adenocarcinoma - Daunke, Tina; Beckinger, Silje; Rahn, Sascha; Krüger, Sandra; Heckl, Steffen; Schäfer, Heiner; Wesch, Daniela; Pilarsky, Christian; Eckstein, Markus; Hartmann, Arndt; Röcken, Christoph; Wandmacher, Anna Maxi; et al. (Frontiers in Immunology, 2023)
Introduction: Immune checkpoint inhibitors (ICI), e.g., targeting programmed cell death protein 1-ligand 1 (PD-L1) or its receptor PD-1, have markedly improved the therapy of many cancers but so far failed in pancreatic ductal adenocarcinoma (PDAC). Macrophages represent one of the most abundant immune cell populations within the tumor microenvironment (TME) of PDAC being able to either support or restrain tumor progression depending on their phenotype. To better understand treatment failure of PD-L1/PD-1 inhibitors in PDAC, this study examined PD-L1 expression in the context of a dynamic TME in PDAC with a particular focus on the impact of macrophages. Methods: Formalin-fixed and paraffin embedded tissue samples of primary PDAC tissues and corresponding liver metastases were used for immunohistochemical analyses. Serial sections were stained with antibodies detecting Pan-Cytokeratin, CD68, CD163, CD8, and PD-L1.To investigate whether the PD-1/PD-L1 axis and macrophages contribute to immune escape of PDAC cells, a stroma enriched 3D spheroid coculture model was established in vitro, using different PDAC cell lines and macrophages subtypes as well as CD8+ T cells. Functional and flow cytometry analyses were conducted to characterize cell populations. Results: Immunohistochemical analyses revealed that PD-L1 is mainly expressed by stroma cells, including macrophages and not PDAC cells in primary PDAC tissues and corresponding liver metastases. Notably, high local abundance of macrophages and strong PD-L1 staining were commonly found at invasion fronts of tumoral lesions between CD8+ T cells and tumor cells. In order to investigate whether PD-L1 expressing macrophages impact the response of PDAC cells to treatment with PD-L1/PD-1 inhibitors, we developed a spheroid model comprising two different PDAC cell lines and different ratios of in vitro differentiated primary M1- or M2-like polarized macrophages. In line with our in situ findings, high PD-L1 expression was observed in macrophages rather than PDAC cells, which was further increased by the presence of PDAC cells. The effector phenotype of co-cultured CD8+ T cells exemplified by expression of activation markers and release of effector molecules was rather enhanced by PDAC macrophage spheroids, particularly with M1-like macrophages compared to mono-culture spheroids. However, this was not associated with enhanced PDAC cell death. ICI treatment with either Durvalumab or Pembrolizumab alone or in combination with Gemcitabine hardly affected the effector phenotype of CD8+ T cells along with PDAC cell death. Thus, despite strong PD-L1 expression in macrophages, ICI treatment did not result in an enhanced activation and cytotoxic phenotype of CD8+ T cells. Conclusion: Overall, our study revealed novel insights into the interplay of PDAC cells and macrophages in the presence of ICI.
CRIS-Team Scopus Importer:2023-08-25
Keywords: 3D co-culture; immune checkpoint inhibitor; immune evasion; macrophages; pancreatic cancer; tumor microenvironment

Expression of adhesion molecules, platelet-activating factor, and chemokines by Kaposi's sarcoma cells. - Sciacca, Francesca L; Stürzl, Michael; Bussolino, Federico; Sironi, Manuela; Brandstetter, Hans; Zietz, C; Zhou, D; Matteucci, C; Peri, G; Sozzani, Silvano (Journal of Immunology, 1994)
The present study was designed to investigate whether cells cultured from Kaposi's sarcoma (KS), a vascular tumor with a prominent leukocyte infiltration, express molecules important for the recruitment and activation of leukocytes. KS cells expressed intercellular adhesion molecule-1, which was augmented by exposure to IL-1 beta or TNF-alpha. Unlike endothelial cells, resting or cytokine-activated KS cells did not express appreciable levels of intercellular adhesion molecule-2, vascular cell adhesion molecule-1, and E-selectin on their surface. Weak expression of vascular cell adhesion molecule-1 mRNA was detectable by Northern blot analysis and, most clearly, by PCR analysis. Upon exposure to inflammatory cytokines, KS cells produced the attractant/activating lipid platelet-activating factor. KS cells expressed appreciable levels of the chemotactic cytokines, monocyte chemotactic protein-1 (MCP-1) and IL-8, as determined by Northern blot analysis, immunoassay, or bioassay. Chemokine production was augmented by IL-1 beta or TNF-alpha. MCP-1 expression was also detected in KS lesions by in situ hybridization. The set of molecules identified in the present study is probably important in determining the prominent leukocyte infiltration observed in KS. Tumor-associated leukocytes may amplify autocrine/paracrine circuits that sustain KS proliferation and contribute to recruitment of host vascular cells.

Expression of calcitonin receptor-like receptor in human vascular tumours. - Hagner, Stefanie; Stahl, Ulrich; Grimm, T.; Stürzl, Michael; Lang, R. E. (Journal of Clinical Pathology, 2006)
Background: Vascular tumours such as Kaposi’s sarcoma and capillary haemangioma are characterised by abnormal vascularisation and proliferation of endothelial cells or neoplastic cells. Adrenomedullin, a potent vasodilative peptide, and its receptor, calcitonin receptor-like receptor (CRLR), play an important part in angiogenesis. Aim: To establish whether this system also plays a part in vascular diseases, showing abnormal proliferation such as vascular tumours. Methods: CRLR expression was investigated in several specimens of Kaposi’s sarcoma and other vascular tumours, using immunohistochemical analysis with a previously described CRLR-specific polyclonal antibody and reverse transcriptase-polymerase chain reaction. Results: Intense and specific CRLR-immunoreactive staining of neoplastic cells was observed in all specimens, which was of greater intensity than similar staining of adjacent normal endothelium. Conclusions: CRLR is expressed in vascular tumours and, with adrenomedullin, may have a role in neoplastic vascular growth.

Expression of K13/v-FLIP gene of human herpesvirus 8 and apoptosis in Kaposi's sarcoma spindle cells. - Stürzl, Michael; Hohenadl, Christine; Zietz, Christian; Castanos-Velez, Esmeralda; Wunderlich, Anneliese; Ascherl, Gudrun; Biberfeld, Peter; Monini, Paolo; Browning, Philip J.; Ensoli, Barbara (Journal of the National Cancer Institute, 1999)
Human herpesvirus 8 (HHV8) infection is associated with all forms of Kaposi's sarcoma (KS). The HHV8 genome locus ORFK13-72-73 (ORF = open reading frame) encodes proteins that may be important in HHV8-mediated pathogenesis, i.e., the latency-associated nuclear antigen (encoded by ORF73), viral-cyc-D (v-cyc-D), a viral homologue of cellular cyclin D (encoded by ORF72), and viral-FLIP (v-FLIP), a homologue of the cellular FLICE (Fas-associated death domain-like interleukin 1 beta-converting enzyme) inhibitory protein (encoded by ORFK13; is an inhibitor of apoptosis [programmed cell death]). Through differential splicing events, this locus expresses individual RNA transcripts that encode all three proteins (tricistronic transcripts) or just two of them (v-FLIP and v-cyc-D; bicistronic transcripts). We examined expression of these transcripts in KS tissues. We collected tissues from patients with KS of different stages. By use of an optimized in situ hybridization procedure, we examined different ORFK13-72-73 locus transcripts in HHV8-infected cells in skin lesions and in one adjacent lymph node. Apoptosis in KS lesions was determined by use of an in situ assay. Our results indicate the following: 1) Transcripts from the ORFK13-72-73 locus appear to be spliced differentially in latently infected KS cells in skin lesions and in HHV8-infected cells in lymph nodes; specifically, ORFK13-ORF72 bicistronic transcripts were expressed abundantly in KS cells, whereas ORFK13-ORF72-ORF73 tricistronic transcripts were detected only in lymph node cells. 2) Sequences encoding the antiapoptotic protein v-FLIP are expressed at very low levels in early KS lesions, but expression increases dramatically in late-stage lesions. 3) The increase in expression of v-FLIP-encoding transcripts is associated with a reduction in apoptosis in KS lesions. These data suggest that functional v-FLIP is produced in vivo and that antiapoptotic mechanisms may be involved in the rapid growth of KS lesions, where only a few cells undergoing mitosis are generally observed. BACKGROUND METHODS RESULTS AND CONCLUSIONS IMPLICATIONS

Expression of platelet-derived growth factor and its receptor in AIDS-related Kaposi sarcoma in vivo suggests paracrine and autocrine mechanisms of tumor maintenance. - Stürzl, Michael; Roth, W K; Brockmeyer, Norbert H.; Zietz, C; Speiser, B; Hofschneider, Peter Hans (Proceedings of the National Academy of Sciences of the United States of America, 1992)
As previously described, proliferation of Kaposi sarcoma (KS)-derived cells in vitro is dependent on the presence of platelet-derived growth factor (PDGF). To test the hypothesis that PDGF may also be a major growth factor for KS cells in vivo, we performed in situ hybridization and immunohistochemical staining for PDGF and PDGF receptors in tissue sections of AIDS-related KS. The data suggest that KS consists of two types of tumor cells. (i) The main population are spindle-shaped cells with elongated nuclei (KS-s cells). They reveal a strong expression of PDGF beta receptors but do not express the PDGF-A and PDGF-B isoforms. (ii) A minor population of KS cells express PDGF beta receptor as well as PDGF-A and PDGF-B (KS-p cells). These cells are often grouped in whorls and surrounding vascular slits. They reveal spherical nuclei with evenly distributed chromatin and inconspicuous nucleoli. PDGF alpha receptor is not expressed in either form of KS cells. The results suggest that the isoforms of PDGF and the PDGF beta receptor are differentially expressed in two different cell types in KS and that PDGF isoforms may contribute to the pathogenesis of KS.

Factors influencing downstaging after neoadjuvant long-course chemoradiotherapy in rectal carcinoma - Kohl, Valerie; Weber, Klaus; Brunner, Maximilian; Geppert, Carol-Immanuel; Fietkau, Rainer; Grützmann, Robert; Semrau, Sabine; Merkel, Susanne (International Journal of Colorectal Disease, 2022)
Purpose This single-centre cohort study was designed to identify factors that can predict primary tumour downstaging by neoadjuvant chemoradiotherapy (nCRT) in rectal carcinoma. Methods Prospectively collected data from 555 patients with clinical T category (cT) cT3-4 rectal carcinoma treated between 1995 and 2019 were retrospectively analysed. All patients received long-term neoadjuvant chemoradiotherapy followed by surgery with curative intent at the Department of Surgery, University Hospital Erlangen, Germany. Patient-, tumour- and treatment-related factors with a potential impact on the downstaging of rectal carcinoma to pathological T category (pT) ≤ ypT2 and ypT0 were analysed in univariate and multivariate logistic regression analyses. The prognosis of patients with and without downstaging of the primary tumour was compared. Results A total of 288 (51.9%) patients showed downstaging to ≤ ypT2. Eighty-six (15.5%) patients achieved clinical complete regression (ypT0). In the multivariate logistic regression analysis, the factors cT category, BMI, ECOG score, CEA, histological type, extension in the rectum and year of the start of treatment were found to be independent factors for predicting downstaging to ≤ ypT2 after neoadjuvant chemoradiotherapy. The year of treatment initiation also remained an independent significant predictor for pathological complete regression. The prognosis was superior in patients with downstaging to ≤ ypT2 in terms of locoregional and distant recurrence as well as disease-free and overall survival. Conclusion Factors predicting downstaging after long-term nCRT could be identified. This may be helpful for counselling patients and selecting the optimal treatment for patients with advanced rectal carcinoma.
CRIS-Team WoS Importer:2022-05-27
Keywords: Rectal carcinoma; Neoadjuvant chemoradiotherapy; Downstaging; Tumour regression; Prediction of pathological response; Prognostic factors

Fibrin gel-immobilized VEGF and bFGF efficiently stimulate angiogenesis in the AV loop model. - Arkudas, Andreas; Tjiawi, Jimmy; Bleiziffer, Oliver; Grabinger, Lucia; Polykandriotis, Elias; Beier, Justus P.; Stürzl, Michael; Horch, Raymund E.; Kneser, Ulrich (Molecular Medicine, 2007)
The modulation of angiogenic processes in matrices is of great interest in tissue engineering. We assessed the angiogenic effects of fibrin-immobilized VEGF and bFGF in an arteriovenous loop (AVL) model in 22 AVLs created between the femoral artery and vein in rats. The loops were placed in isolation chambers and were embedded in 500 microL fibrin gel (FG) (group A) or in 500 microL FG loaded with 0.1 ng/microL VEGF and 0.1 ng/microL bFGF (group B). After two and four weeks specimens were explanted and investigated using histological, morphometrical, and ultramorphological [scanning electron microscope (SEM) of vascular corrosion replicas] techniques. In both groups, the AVL induced formation of densely vascularized connective tissue with differentiated and functional vessels inside the fibrin matrix. VEGF and bFGF induced significantly higher absolute and relative vascular density and a faster resorption of the fibrin matrix. SEM analysis in both groups revealed characteristics of an immature vascular bed, with a higher vascular density in group B. VEGF and bFGF efficiently stimulated sprouting of blood vessels in the AVL model. The implantation of vascular carriers into given growth factor-loaded matrix volumes may eventually allow efficient generation of axially vascularized, tissue-engineered composites.
Keywords: Vascular Endothelial Growth Factor (VEGF); Fibrin Matrix; Arteriovenous Loop (AVL); Vascular Carrier; High Vascular Density

Filamin A Is a Potential Driver of Breast Cancer Metastasis via Regulation of MMP-1 - Zhou, Jie; Wu, Lvying; Xu, Pengyan; Li, Yue; Ji, Zhiliang; Kang, Xinmei (Frontiers in Oncology, 2022)
Recurrent metastasis is a major fatal cause of breast cancer. Regretfully, the driving force and the molecular beneath have not been fully illustrated yet. In this study, a cohort of breast cancer patients with locoregional metastasis was recruited. For them, we collected the matched samples of the primary tumor and metastatic tumor, and then we determined the mutation profiles with whole-exome sequencing (WES). On basis of the profiles, we identified a list of deleterious variants in eight susceptible genes. Of them, filamin A (FLNA) was considered a potential driver gene of metastasis, and its low expression could enhance 5 years’ relapse survival rate by 15%. To prove the finding, we constructed a stable FLNA knockout tumor cell line, which manifested that the cell abilities of proliferation, migration, and invasion were significantly weakened in response to the gene knockout. Subsequently, xenograft mouse experiments further proved that FLNA knockout could inhibit local or distal metastasis. Putting all the results together, we consolidated that FLNA could be a potential driver gene to metastasis of breast cancer, in particular triple-negative breast cancer. Additional experiments also suggested that FLNA might intervene in metastasis via the regulation of MMP-1 expression. In summary, this study demonstrates that FLNA may play as a positive regulator in cancer proliferation and recurrence. It provides new insight into breast cancer metastasis and suggests a potential new therapeutic target for breast cancer therapy.
CRIS-Team Scopus Importer:2022-04-15
Keywords: breast cancer; EMT; FLNA; metastasis; MMP-1

Final Analysis of DeCOG-SLT Trial: No Survival Benefit for Complete Lymph Node Dissection in Patients With Melanoma With Positive Sentinel Node - Leiter, Ulrike; Stadler, Rudolf; Mauch, Cornelia; Hohenberger, Werner; Brockmeyer, Norbert H.; Sunderkötter, Cord; Kaatz, Martin; Schatton, Kerstin; Lehmann, Percy; Vogt, Thomas; Ulrich, Jens; Herbst, Rudolf; et al. (Journal of Clinical Oncology, 2019)
PURPOSE: We have previously reported on the 3-year results of the phase III German Dermatologic Cooperative Oncology Group trial (DeCOG; ClinicalTrials.gov identifier: NCT02434107) comparing distant metastasis-free survival (DMFS), recurrence-free survival (RFS), and overall survival (OS) in patients with positive sentinel lymph-node biopsy who were randomly assigned to complete lymph node dissection (CLND) or observation. Here, we report the final analysis with 72 months of median follow up. PATIENTS AND METHODS: The multicenter randomized phase III trial included patients with cutaneous melanoma of the trunk and extremities who were randomly assigned (1:1) to undergo CLND or observation. DMFS was analyzed as the primary end point, and RFS, OS, and recurrences in the regional lymph node basin were secondary end points. The analysis was by intention to treat. Disease and survival information were collected quarterly. RESULTS: From January 2006 to December 2014, 5,547 patients were screened to identify 1,256 with metastases in the sentinel lymph node (SLN). Of these, 483 (39%) were included: 241 in the observation arm and 242 in the CLND arm. In the final analysis, median follow up was 72 months (interquartile range, 67-77 months). No significant treatment-related difference was seen in the 5-year DMFS between the observation and CLND arms (67.6% v 64.9%, respectively; hazard ratio [HR], 1.08; P = .87). The 5-year RFS and OS also showed no difference (HR, 1.01 and 0.99, respectively). Grade 3 and 4 adverse effects occurred in 32 patients (13%) in the CLND arm; lymphedema (n = 20) and delayed wound healing (n = 5) were most common and no serious adverse events were reported. CONCLUSION: The final results of the German Dermatologic Cooperative Oncology Group trial with a median follow up of 72 months showed higher event rates, but similar HRs compared with those at the 3-year analysis. These results confirm that immediate CLND in SLN-positive patients is not superior to observation in terms of DMFS, RFS, or OS and support not recommending CLND in patients with SLN metastasis.
CRIS-Team Scopus Importer:2019-11-15

Gamma interferon-induced guanylate binding protein 1 is a novel actin cytoskeleton remodeling factor - Ostler, Nicole; Britzen-Laurent, Nathalie; Liebl, Andrea; Naschberger, Elisabeth; Lochnit, Guenter; Ostler, Markus; Forster, Florian; Kunzelmann, Peter; Ince, Semra; Supper, Verena; Praefcke, Gerrit J. K.; Schubert, Dirk W.; et al. (Molecular and Cellular Biology, 2014)
Gamma interferon (IFN-?) regulates immune defenses against viruses, intracellular pathogens, and tumors by modulating cell proliferation, migration, invasion, and vesicle trafficking processes. The large GTPase guanylate binding protein 1 (GBP-1) is among the cellular proteins that is the most abundantly induced by IFN-? and mediates its cell biologic effects. As yet, the molecular mechanisms of action of GBP-1 remain unknown. Applying an interaction proteomics approach, we identified actin as a strong and specific binding partner of GBP-1. Furthermore, GBP-1 colocalized with actin at the subcellular level and was both necessary and sufficient for the extensive remodeling of the fibrous actin structure observed in IFN-?-exposed cells. These effects were dependent on the oligomerization and the GTPase activity of GBP-1. Purified GBP-1 and actin bound to each other, and this interaction was sufficient to impair the formation of actin filaments in vitro, as demonstrated by atomic force microscopy, dynamic light scattering, and fluorescence-monitored polymerization. Cosedimentation and band shift analyses demonstrated that GBP-1 binds robustly to globular actin and slightly to filamentous actin. This indicated that GBP-1 may induce actin remodeling via globular actin sequestering and/or filament capping. These results establish GBP-1 as a novel member within the family of actin-remodeling proteins specifically mediating IFN-?-dependent defense strategies.
EVALuna2:15143

Gastric cancer patients less than 50 years of age exhibit significant downregulation of E-cadherin and CDX2 compared to older reference populations - Schildberg, Claus Wilhelm; Abba, Mohammed; Merkel, Susanne; Agaimy, Abbas; Dimmler, Arno; Schlabrakowski, Anne; Croner, Roland; Leupold, Joerg Hendrik; Hohenberger, Werner; Allgayer, Heike (Advances in Medical Sciences, 2014)
There is an increasing need to identify molecular markers, which can be used to prognosticate patient populations in gastric cancer. Whereas a significant number have been identified, very few have been characterized in the context of their ability to discriminate between young and old age groups in which a survival difference clearly exists.In this study, using immunohistochemistry, we evaluated three markers with proven involvement in gastric cancer. The p53 tumor suppressor, the cell adhesion glycoprotein epithelial cadherin (CDH1) and the caudal-related homeobox transcription factor (CDX2) all of these have important roles in the aetiopathogenesis and/or progression of gastric cancer.After adjustments for TNM stage, tumor grade, histopathological characteristics (Lauren classification), we found significant differences in the expression of these proteins, particularly E-cadherin and CDX2 between young and elderly patients. However, these differences did not amount to a significant difference in survival.This study demonstrates that the protein expression of p53, CDH1 and CDX2 significantly discriminates young patients with gastric cancer who have a better prognostic outlook from older patients, but this difference in expression does not contribute to a survival benefit.
EVALuna2:6583

Gastrointestinal schwannomas: a rare but important differential diagnosis of mesenchymal tumors of gastrointestinal tract - Mekras, Alexandros; Krenn, Veit; Perrakis, Aristotelis; Croner, Roland S.; Kalles, Vasileios; Atamer, Cem; Grützmann, Robert; Vassos, Nikolaos (BMC Surgery, 2018)
BACKGROUND: Schwannomas of gastrointestinal tract are rare, mostly benign and notably different neoplasms from conventional schwannomas that arise in soft tissue or the central nervous system. These tumors are of clinical importance since they should always be considered in the differential diagnosis of submucosal lesions of gastrointestinal tract. METHODS: Seven patients with a pathologically proven gastrointestinal schwannoma were identified in our series of mesenchymal tumors and reviewed retrospectively. Clinicopathological and immunohistochemical parameters along with the follow-up results were analysed. RESULTS: The series included two males and five females, with a mean age 69 years (range, 39-81). Most patients were asymptomatic on presentation, except for two patients with abdominal pain. In the other cases (n = 5), the tumor was an incidental finding during other medical, imaging or surgical procedures. The tumors were located in the stomach (n = 4) and in the small intestine (n = 3) with an average size of 29 mm (range, 12-70). A preoperative diagnosis was achieved only in one case with a CT-guided core biopsy. Otherwise the clinical, intraoperative, endoscopic or radiological findings were unspecific. Patients with gastric tumor underwent either laparoscopic (n = 2) or open (n = 2) gastric wedge resection of the tumor; in the cases of intestinal tumor (n = 3) a segmentectomy was performed. Pathological examination revealed solid homogenous tumors, which were highly cellular and composed of spindle cells with positive staining for S100 protein, and confirmed the diagnosis of schwannoma. All tumors were negative for c-Kit, smooth muscle actin, desmin and DOG-1 and showed very low proliferation index. There were negative resection margins and no malignant variants were recognized. At an average follow-up of 60 months (range, 24-185) all patients were free of disease with no signs of recurrence or metastases and acceptable gastrointestinal function. CONCLUSIONS: Schwannomas are rare, slow-growing and mostly asymptomatic gastrointestinal mesenchymal tumors. They are difficult to be diagnosed preoperatively as endoscopic and radiological findings are nonspecific but histological and immunohistochemical features are of paramount importance to differentiate between benign and malignant schwannomas, or other spindle cell sarcomas. The treatment of choice is complete surgical excision without a conclusive preoperative diagnosis, and the long-term outcome is excellent as these lesions are mostly benign.
EVALuna2:210708

GATA4 and GATA6 loss-of-expression is associated with extinction of the classical programme and poor outcome in pancreatic ductal adenocarcinoma - De Andres, Monica P.; Jackson, Richard J.; Felipe, Irene; Zagorac, Sladjana; Pilarsky, Christian; Schlitter, Anna Melissa; Martinez De Villareal, Jaime; Jang, Gun Ho; Costello, Eithne; Gallinger, Steve; Ghaneh, Paula; Greenhalf, William; et al. (Gut, 2022)
Objective GATA6 is a key regulator of the classical phenotype in pancreatic ductal adenocarcinoma (PDAC). Low GATA6 expression associates with poor patient outcome. GATA4 is the second most expressed GATA factor in the pancreas. We assessed whether, and how, GATA4 contributes to PDAC phenotype and analysed the association of expression with outcome and response to chemotherapy. Design We analysed PDAC transcriptomic data, stratifying cases according to GATA4 and GATA6 expression and identified differentially expressed genes and pathways. The genome-wide distribution of GATA4 was assessed, as well as the effects of GATA4 knockdown. A multicentre tissue microarray study to assess GATA4 and GATA6 expression in samples (n=745) from patients with resectable was performed. GATA4 and GATA6 levels were dichotomised into high/low categorical variables; association with outcome was assessed using univariable and multivariable Cox regression models. Results GATA4 messenger RNA is enriched in classical, compared with basal-like tumours. We classified samples in 4 groups as high/low for GATA4 and GATA6. Reduced expression of GATA4 had a minor transcriptional impact but low expression of GATA4 enhanced the effects of GATA6 low expression. GATA4 and GATA6 display a partially overlapping genome-wide distribution, mainly at promoters. Reduced expression of both proteins in tumours was associated with the worst patient survival. GATA4 and GATA6 expression significantly decreased in metastases and negatively correlated with basal markers. Conclusions GATA4 and GATA6 cooperate to maintain the classical phenotype. Our findings provide compelling rationale to assess their expression as biomarkers of poor prognosis and therapeutic response.
CRIS-Team WoS Importer:2022-09-30

GBP-1 acts as a tumor suppressor in colorectal cancer cells - Britzen-Laurent, Nathalie; Lipnik, Karoline; Ocker, Matthias; Naschberger, Elisabeth; Schellerer, Vera; Croner, Roland S.; Vieth, Michael; Waldner, Maximilian; Steinberg, Pablo; Hohenadl, Christine; Stürzl, Michael (Carcinogenesis, 2013)
The human guanylate-binding protein 1 (GBP-1) is among the proteins the most highly induced by interferon-γ (IFN-γ) in every cell type investigated as yet. In vivo, GBP-1 expression is associated with the presence of inflammation and has been observed in autoimmune diseases, inflammatory bowel diseases (IBD) and cancer. In colorectal carcinoma (CRC), the expression of GBP-1 in the desmoplastic stroma has been previously reported to correlate with the presence of an IFN-γ-dominated T helper type 1 (Th1) micromilieu and with an increased cancer-related 5-year survival. In the present study, the analysis of GBP-1 expression in a series of 185 CRCs by immunohistochemistry confirmed that GBP-1 is expressed in stroma cells of CRCs and revealed a significantly less frequent expression in tumor cells, which was contradictory with the broad inducibility of GBP-1. Furthermore, three of six CRC cell lines treated with IFN-γ were unable to express GBP-1 indicating that colorectal tumor cells tend to downregulate GBP-1. On the contrary, non-transformed colon epithelial cells strongly expressed GBP-1 in vitro in presence of IFN-γ and in vivo in inflammatory bowel diseases. Reconstitution of GBP-1 expression in a negative CRC cell line inhibited cell proliferation, migration and invasion. Using RNA interference, we showed that GBP-1 mediates the antitumorigenic effects of IFN-γ in CRC cells. In addition, GBP-1 was able to inhibit tumor growth in vivo. Altogether, these results suggested that GBP-1 acts directly as a tumor suppressor in CRC and the loss of GBP-1 expression might indicate tumor evasion from the IFN-γ-dominated Th1 immune response. © The Author 2012. Published by Oxford University Press. All rights reserved.
Created from Fastlane, Scopus look-up

Gene expression analysis of ischaemia and reperfusion in human microsurgical free muscle tissue transfer. - Dragu, Adrian; Schnuerer, Stefan; Surmann-Schmitt, Cordula; von der Mark, Klaus; Stürzl, Michael; Unglaub, Frank; Wolf, Maya B.; Leffler, Mareike; Beier, Justus; Kneser, Ulrich; Horch, Raymund E. (Journal of Cellular and Molecular Medicine, 2011)
The aim of this study was to analyse various gene expression profiles of muscle tissue during normoxia, ischaemia and after reperfusion in human muscle free flaps, to gain an understanding of the occurring regulatory, inflammatory and apoptotic processes on a cellular and molecular basis. Eleven Caucasian patients with soft tissue defects needing coverage with microsurgical free muscle flaps were included in this study. In all patients, the muscle samples were taken from free myocutaneous flaps. The first sample was taken before induction of ischaemia in normoxia (I), another one after ischaemia (II), and the last one was taken after reperfusion (III). The samples were analysed using DNA-microarray, real-time-quantitative-PCR and immunohistochemistry. DNA-microarray analysis detected multiple, differentially regulated genes when comparing the different groups (I-III) with statistical significance. Comparing ischaemia (II) versus normoxia (I) educed 13 genes and comparing reperfusion (III) versus ischaemia (II) educed 19 genes. The comparison of reperfusion (III) versus normoxia (I) yielded 100 differentially regulated genes. Real-time-quantitative-PCR confirmed the results of the DNA-microarrays for a subset of four genes (CASP8, IL8, PLAUR and S100A8). This study shows that ischaemia and reperfusion induces alterations on the gene expression level in human muscle free flaps. Data may suggest that the four genes CASP8, IL8, PLAUR and S100A8 are of great importance in this context. We could not confirm the DNA-microarry and real-time-quantitative-PCR results on the protein level. Finally, these findings correspond with the surgeon's clinical experience that the accepted times of ischaemia, generally up to 90 min., are not sufficient to induce pathophysiological processes, which can ultimately lead to flap loss. When inflammatory and apoptotic proteins are expressed at high levels, flap damage might occur and flap loss is likely. The sole expression on mRNA level might explain why flap loss is unlikely.

Gene Expression in Solitary Fibrous Tumors (SFTs) Correlates with Anatomic Localization and NAB2-STAT6 Gene Fusion Variants - Bieg, Matthias; Moskalev, Evgeny; Will, Rainer; Hebele, Simone; Schwarzbach, Matthias; Schmeck, Sanja; Hohenberger, Peter; Jakob, Jens; Kasper, Bernd; Gaiser, Timo; Ströbel, Philip; Wardelmann, Eva; et al. (American Journal of Pathology, 2021)
Solitary fibrous tumors (SFTs) harbor recurrent NAB2-STAT6 gene fusions, promoting constitutional up-regulation of oncogenic early growth response 1 (EGR1)-dependent gene expression. SFTs with the most common canonical NAB2 exon 4–STAT6 exon 2 fusion variant are often located in the thorax (pleuropulmonary) and are less cellular with abundant collagen. In contrast, SFTs with NAB2 exon 6–STAT6 exon 16/17 fusion variants typically display a cellular round to ovoid cell morphology and are often located in the deep soft tissue of the retroperitoneum and intra-abdominal pelvic region or in the meninges. Here, we employed next-generation sequencing–based gene expression profiling to identify significant differences in gene expression associated with anatomic localization and NAB2-STAT6 gene fusion variants. SFTs with the NAB2 exon 4–STAT6 exon 2 fusion variant showed a transcriptional signature enriched for genes involved in DNA binding, gene transcription, and nuclear localization, whereas SFTs with the NAB2 exon 6–STAT6 exon 16/17 fusion variants were enriched for genes involved in tyrosine kinase signaling, cell proliferation, and cytoplasmic localization. Specific transcription factor binding motifs were enriched among differentially expressed genes in SFTs with different fusion variants, implicating co–transcription factors in the modification of chimeric NGFI-A binding protein 2 (NAB2)-STAT6–dependent deregulation of EGR1-dependent gene expression. In summary, this study establishes a potential molecular biologic basis for clinicopathologic differences in SFTs with distinct NAB2-STAT6 gene fusion variants.
CRIS-Team Scopus Importer:2021-04-02

Genome-wide association study identifies inversion in the CTRB1-CTRB2 locus to modify risk for alcoholic and non-alcoholic chronic pancreatitis - Rosendahl, Jonas; Kirsten, Holger; Hegyi, Eszter; Kovacs, Peter; Weiss, Frank Ulrich; Laumen, Helmut; Lichtner, Peter; Ruffert, Claudia; Chen, Jian-Min; Masson, Emmanuelle; Beer, Sebastian; Zimmer, Constantin; et al. (Gut, 2017)
Alcohol-related pancreatitis is associated with a disproportionately large number of hospitalisations among GI disorders. Despite its clinical importance, genetic susceptibility to alcoholic chronic pancreatitis (CP) is poorly characterised. To identify risk genes for alcoholic CP and to evaluate their relevance in non-alcoholic CP, we performed a genome-wide association study and functional characterisation of a new pancreatitis locus.1959 European alcoholic CP patients and population-based controls from the KORA, LIFE and INCIPE studies (n=4708) as well as chronic alcoholics from the GESGA consortium (n=1332) were screened with Illumina technology. For replication, three European cohorts comprising 1650 patients with non-alcoholic CP and 6695 controls originating from the same countries were used.We replicated previously reported risk loci CLDN2-MORC4, CTRC, PRSS1-PRSS2 and SPINK1 in alcoholic CP patients. We identified CTRB1-CTRB2 (chymotrypsin B1 and B2) as a new risk locus with lead single-nucleotide polymorphism (SNP) rs8055167 (OR 1.35, 95% CI 1.23 to 1.6). We found that a 16.6 kb inversion in the CTRB1-CTRB2 locus was in linkage disequilibrium with the CP-associated SNPs and was best tagged by rs8048956. The association was replicated in three independent European non-alcoholic CP cohorts of 1650 patients and 6695 controls (OR 1.62, 95% CI 1.42 to 1.86). The inversion changes the expression ratio of the CTRB1 and CTRB2 isoforms and thereby affects protective trypsinogen degradation and ultimately pancreatitis risk.An inversion in the CTRB1-CTRB2 locus modifies risk for alcoholic and non-alcoholic CP indicating that common pathomechanisms are involved in these inflammatory disorders.
EVALuna2:4780

Genome-Wide CRISPR Screening Identifies DCK and CCNL1 as Genes That Contribute to Gemcitabine Resistance in Pancreatic Cancer - Yang, Hai; Liu, Bin; Liu, Dongxue; Yang, Zhirong; Zhang, Shuman; Xu, Pengyan; Xing, Yuming; Kutschick, Isabella; Pfeffer, Sina; Britzen-Laurent, Nathalie; Grützmann, Robert; Pilarsky, Christian (Cancers, 2022)
Pancreatic cancer is one of the most lethal cancers. Due to the difficulty of early diagnosis, most patients are diagnosed with metastasis or advanced-stage cancer, limiting the possibility of surgical treatment. Therefore, chemotherapy is applied to improve patient outcomes, and gemcitabine has been the primary chemotherapy drug for pancreatic cancer for over a decade. However, drug resistance poses a significant challenge to the efficacy of chemotherapy. The CRISPR/Cas9 (clustered regularly interspaced short palindromic repeats/CRISPR-associated protein 9) gene-editing system is a powerful tool, and researchers have developed CRISPR/Cas9 library screening as a means to identify the genes associated with specific phenotype changes. We performed genomewide CRISPR/Cas9 knockout screening in the mouse pancreatic cancer cell line TB32047 with gemcitabine treatment and identified deoxycytidine kinase (DCK) and cyclin L1 (CCNL1) as the top hits. We knocked out DCK and CCNL1 in the TB32047 and PANC1 cell lines and confirmed that the loss of DCK or CCNL1 enhanced gemcitabine resistance in pancreatic cells. Many researchers have addressed the mechanism of DCK-related gemcitabine resistance; however, no study has focused on CCNL1 and gemcitabine resistance. Therefore, we explored the mechanism of CCNL1-related gemcitabine resistance and found that the loss of CCNL1 activates the ERK/AKT/STAT3 survival pathway, causing cell resistance to gemcitabine treatment.
CRIS-Team Scopus Importer:2022-07-15
Keywords: CCNL1; CRISPR-Cas9; DCK; gemcitabine resistance; library screening; pancreatic cancer

Genomic analyses identify molecular subtypes of pancreatic cancer - Bailey, Peter; Chang, David K.; Nones, Katia; Johns, Amber L.; Patch, Ann-Marie; Gingras, Marie-Claude; Miller, David K.; Christ, Angelika N.; Bruxner, Tim J. C.; Quinn, Michael C.; Nourse, Craig; Murtaugh, L. Charles; et al. (Nature, 2016)
Integrated genomic analysis of 456 pancreatic ductal adenocarcinomas identified 32 recurrently mutated genes that aggregate into 10 pathways: KRAS, TGF-?, WNT, NOTCH, ROBO/SLIT signalling, G1/S transition, SWI-SNF, chromatin modification, DNA repair and RNA processing. Expression analysis defined 4 subtypes: (1) squamous; (2) pancreatic progenitor; (3) immunogenic; and (4) aberrantly differentiated endocrine exocrine (ADEX) that correlate with histopathological characteristics. Squamous tumours are enriched for TP53 and KDM6A mutations, upregulation of the TP63?N transcriptional network, hypermethylation of pancreatic endodermal cell-fate determining genes and have a poor prognosis. Pancreatic progenitor tumours preferentially express genes involved in early pancreatic development (FOXA2/3, PDX1 and MNX1). ADEX tumours displayed upregulation of genes that regulate networks involved in KRAS activation, exocrine (NR5A2 and RBPJL), and endocrine differentiation (NEUROD1 and NKX2-2). Immunogenic tumours contained upregulated immune networks including pathways involved in acquired immune suppression. These data infer differences in the molecular evolution of pancreatic cancer subtypes and identify opportunities for therapeutic development.
EVALuna2:15255

Gleiche Langzeitergebnisse der laparoskopischen Resektion nach neoadjuvanter Radiochemotherapie beim lokal fortgeschrittenen Rektumkarzinom wie durch konventionelle offene Chirurgie - Hohenberger, Werner (Strahlentherapie und Onkologie, 2015)
EVALuna2:15197

Guanylate-binding protein 1 expression from embryonal endothelial progenitor cells reduces blood vessel density and cellular apoptosis in an axially vascularised tissue-engineered construct - Bleiziffer, Oliver; Hammon, Matthias; Arkudas, Andreas; Taeger, Christian; Beier, Justus; Amann, Kerstin Ute; Naschberger, Elisabeth; Stürzl, Michael; Horch, Raymund E.; Kneser, Ulrich (BMC Biotechnology, 2012)
Background: Guanylate binding protein-1 (GBP-1) is a large GTPase which is actively secreted by endothelial cells. It is a marker and intracellular inhibitor of endothelial cell proliferation, migration, and invasion. We previously demonstrated that stable expression of GBP-1 in murine endothelial progenitor cells (EPC) induces their premature differentiation and decreases their migration capacity in vitro and in vivo. The goal of the present study was to assess the antiangiogenic capacity of EPC expressing GBP-1 (GBP-1-EPC) and their impact on blood vessel formation in an axially vascularized 3-D bioartificial construct in vivo.Results: Functional in vitro testing demonstrated a significant increase in VEGF secretion by GBP-1-EPC after induction of cell differentiation. Undifferentiated GBP-1-EPC, however, did not secrete increased levels of VEGF compared to undifferentiated control EPC expressing an empty vector (EV-EPC). In our In vivo experiments, we generated axially vascularized tissue-engineered 3-D constructs. The new vascular network arises from an arterio-venous loop (AVL) embedded in a fibrin matrix inside a separation chamber. Total surface area of the construct as calculated from cross sections was larger after transplantation of GBP-1-EPC compared to control EV-EPC. This indicated reduced formation of fibrovascular tissue and less resorption of fibrin matrix compared to constructs containing EV-EPC. Most notably, the ratio of blood vessel surface area over total construct surface area in construct cross sections was significantly reduced in the presence of GBP-1-EPC. This indicates a significant reduction of blood vessel density and thereby inhibition of blood vessel formation from the AVL constructs caused by GBP-1. In addition, GBP-1 expressed from EPC significantly reduced cell apoptosis compared to GBP-1-negative controls.Conclusion: Transgenic EPC expressing the proinflammatory antiangiogenic GTPase GBP-1 can reduce blood vessel density and inhibit apoptosis in a developing bioartificial vascular network and may become a new powerful tool to manipulate angiogenetic processes in tissue engineering and other pathological conditions such as tumour angiogenesis. © 2012 Bleiziffer et al.; licensee BioMed Central Ltd.
Created from Fastlane, Scopus look-up
Keywords: Angiogenesis; Endothelial progenitor cells; Guanylate-binding protein 1; In vivo tissue engineering

Guanylate-binding protein-1 expression is selectively induced by inflammatory cytokines and is an activation marker of endothelial cells during inflammatory diseases - Naschberger, Elisabeth; Stürzl, Michael; et al. (American Journal of Pathology, 2002)
During angiogenesis and inflammatory processes, endothelial cells acquire different activation phenotypes, whose identification may help in understanding the complex network of angiogenic and inflammatory interactions in vivo. To this goal we investigated the expression of the human guanylate-binding protein (GBP)-1 that is highly induced by inflammatory cytokines (ICs) and, therefore, may characterize IC-activated cells. Using a new rat monoclonal antibody raised against GBP-1, we show that GBP-1 is a cytoplasmic protein and that its expression in endothelial cells is selectively induced by interferon-γ, interleukin-1α, interleukin-1β, or tumor necrosis factor-α, but not by other cytokines, chemokines, or growth factors. Moreover, we found that GBP-1 expression is highly associated with vascular endothelial cells as confirmed by the simultaneous detection of GBP-1 and the endothelial cell-associated marker CD31 in a broad range of human tissues. Notably, GBP-1 expression was undetectable in the skin, but it was highly induced in vessels of skin diseases with a high-inflammatory component including psoriasis, adverse drug reactions, and Kaposi's sarcoma. These results indicate that GBP-1 is a novel cellular activation marker that characterizes the IC-activated phenotype of endothelial cells.
Created from Fastlane, Scopus look-up

Guanylate binding protein-1 inhibits spreading and migration of endothelial cells through induction of integrin α4 expression - Weinlaender, Kristina; Naschberger, Elisabeth; Lehmann, Michael H.; Tripal, Philipp; Paster, Wolfgang; Stockinger, Hannes; Hohenadl, Christine; Stürzl, Michael (The FASEB Journal, 2008)
Human guanylate binding protein-1 (GBP-1) is a large GTPase that is induced by inflammatory cytokines and acts antiangiogenically through the inhibition of endothelial cell proliferation and migration. In this study, we detected that GBP-1-expressing cells show a significantly reduced spreading and migration on fibronectin matrices. Investigating possible mechanisms of these effects, we found that integrin α4 (ITGA4) was consistently up-regulated at both the RNA and protein level in GBP-1-expressing cell cultures. Inhibition of cell spreading and migration by GBP-1 was dependent on the binding of ITGA4 to fibronectin. The inflammatory cytokines IL-1β and TNF-α induced ITGA4 expression in HUVECs and inhibited spreading and migration. Knockdown of GBP-1 by shRNA abrogated inflammatory cytokine induced ITGA4 expression and restored spreading and migration capabilities of the cells. These results show that inhibition of endothelial cell spreading and migration by inflammatory cytokines is mediated by GBP-1 through induction of ITGA4 expression. Endothelial cell migration is a key process during angiogenesis. Therefore, ITGA4 may be a novel molecular target to modulate angiogenesis in human disease. © FASEB.
Created from Fastlane, Scopus look-up
Keywords: Angiogenesis; Inflammation; Integrins; Large GTPase

Guanylate binding protein 1-mediated interaction of T cell antigen receptor signaling with the cytoskeleton - Forster, Florian; Paster, Wolfgang; Supper, Verena; Schatzlmaier, Philipp; Sunzenauer, Stefan; Ostler, Nicole; Saliba, Anna; Eckerstorfer, Paul; Britzen-Laurent, Nathalie; Schuetz, Gerhard; Schmid, Johannes A.; Zlabinger, Gerhard J.; et al. (Journal of Immunology, 2014)
GTPases act as important switches in many signaling events in cells. Although small and heterotrimeric G proteins are subjects of intensive studies, little is known about the large IFN-inducible GTPases. In this article, we show that the IFN-?-inducible guanylate binding protein 1 (GBP-1) is a regulator of T cell activation. Silencing of GBP-1 leads to enhanced activation of early T cell Ag receptor/CD3 signaling molecules, including Lck, that is translated to higher IL-2 production. Mass spectrometry analyses showed that regulatory cytoskeletal proteins, like plastin-2 that bundles actin fibers and spectrin ?-chain, brain 1 that links the plasma membrane to the actin cytoskeleton, are binding partners of GBP-1. The spectrin cytoskeleton influences cell spreading and surface expression of TCR/CD3 and the leukocyte phosphatase CD45. We found higher cell spreading and enhanced surface expression of TCR/CD3 and CD45 in GBP-1 silenced T cells that explain their enhanced TCR/CD3 signaling. We conclude that GBP-1 is a downstream processor of IFN-? via which T cells regulate cytoskeleton-dependent cell functions.
EVALuna2:15147

HHV-8 and multistep tumorigenesis. - Ensoli, Barbara; Stürzl, Michael (Trends in Microbiology, 1999)
Human herpesvirus 8 [HHV-8 or Kaposi’s sarcoma-associated herpesvirus (KSHV)] is associated with pleural effusion lymphoma (PEL), multicentric Castleman’s disease (MCD) and Kaposi’s sarcoma (KS) 1. These diseases are rare, but HHV-8 can infect more than 50% of the general population, depending on the geographical area. This indicates that additional factors are required for HHV-8 pathogenicity 1. This is not surprising, as the concept of multistep tumorigenesis is now generally accepted and it does not rule out an etiologic role for HHV-8 in tumor development.
Keywords: Virology; Microbiology; Cell biology; Kaposi's sarcoma; Human herpesvirus-8; Cytokine; Angiogenesis; Pleural effusion lymphomas; Multicentric Castelman's disease

HiatoGast 1: An exploring, semiblinded trial establishing a new endoscopical categorisation of axial hiatal hernias - Eckhardt, Daniel; Engel, Matthias; Golcher, Henriette; Krautz, Christian; Grützmann, Robert; Elshafei, Moustafa (BMJ Global Health, 2019)
Introduction Axial hiatal hernias are a common incidental finding in endoscopical examinations, but reflux symptoms do not necessarily correspond to the presence of hiatal hernias. Diagnosing a reflux disease is difficult due to a leak of existing distinct criteria, especially in order to evaluate a surgical indication. Also a preoperative measurement of the hernia is necessary to choose between surgical options. Methods and analysis We planned a semiblinded trial including a questionnaire and an oesophagogastroduodenoscopy afterwards. While the endoscopy is done, the hiatus oesophagi should be measured in inversion technique under maximum insufflation including length, width and herniated volume. A sample of 210 participants until December 2020 is determined to evaluate the primary endpoint: we look forward to evaluate the anatomical parameters of reflux and non-reflux participants. Ethics and Dissemination The study has been approved by the local ethics committee on 12th February 2019, the data will bei published after closure of inclusion. Trial registration number German Clinical Trials Register (DRKS00016863).
CRIS-Team Scopus Importer:2019-07-02
Keywords: endoscopical technique; gastroscopy; hiatal hernia; reflux

High throughput screening of gene functions in mammalian cells using reversely transfected cell arrays: review and protocol. - Stürzl, Michael; Konrad, Andreas; Sander, Gaby; Wies, Effi; Neipel, Frank; Naschberger, Elisabeth; Reipschlaeger, Simone; Gonin-Laurent, Nathalie; Horch, Raymund E.; Kneser, Ulrich; Hohenberger, Werner; Erfle, Holger; et al. (Combinatorial Chemistry & High Throughput Screening, 2008)
Reversely transfected cell microarrays (RTCM) have been introduced as a method for parallel high throughput analysis of gene functions in mammalian cells. Hundreds to thousands of different recombinant DNA or RNA molecules can be transfected into different cell clusters at the same time on a single glass slide with this method. This allows either the simultaneous overexpression or–by using the recently developed RNA interference (RNAi) techniques–knockdown of a huge number of target genes. A growing number of sophisticated detection systems have been established to determine quantitatively the effects of the transfected molecules on the cell phenotype. Several different cell types have been successfully used for this procedure. This review summarizes the presently available knowledge on this technique and provides a laboratory protocol.

HIV-1 Tat increases the adhesion of monocytes and T-cells to the endothelium in vitro and in vivo: implications for AIDS-associated vasculopathy. - Matzen, Kathrin; Dirkx, Anita E.M; Egbrink, Mirjam G.Aoude; Speth, Cornelia; Götte, Matthias; Ascherl, Gudrun; Grimm, Thomas; Griffioen, Arjan W; Stürzl, Michael (Virus Research, 2004)
HIV-1-infected patients exhibit severe damages of the aortic endothelium, develop angioproliferative lesions such as Kaposi's sarcoma (KS), and have an increased risk of cardiovascular diseases and atherosclerosis. An increased adhesion of leukocytes to the endothelium is a common pathogenic parameter of AIDS-associated vascular diseases. Here we show that the HIV-1 Tat protein, a regulatory protein of HIV-1 released by infected cells, and TNF-alpha, a cytokine increased in sera and tissues of HIV-1-infected patients, activate synergistically the adhesion of leukocytes to endothelial cells both in vitro and in vivo. This effect is selectively mediated by HIV-1 Tat, since HIV-1 Nef, another HIV-1 regulatory protein, and the HIV-1 envelope protein gp41, had no effect. In vitro adhesion assays with PBMC and quantitative cell type analysis of adherent cells by FACS demonstrated that HIV-1 Tat selectively activates the adhesion of T-cells and monocytes but not of B-cells. Intravital microscopic studies in mice confirmed the synergistic activity of HIV-1 Tat and TNF-alpha on leukocyte adhesion to the endothelium in vivo. These data indicate that HIV-1 Tat in cooperation with TNF-alpha may contribute to the vascular damage and cardiovascular diseases observed in AIDS patients but also to the prominent extravasation of T-cells and monocytes which is a key process in the formation and progression of KS lesions.

HNF4A and GATA6 Loss Reveals Therapeutically Actionable Subtypes in Pancreatic Cancer - Brunton, Holly; Caligiuri, Giuseppina; Cunningham, Richard; Upstill-Goddard, Rosie; Bailey, Ulla Maja; Garner, Ian M.; Nourse, Craig; Dreyer, Stephan; Jones, Marc; Moran-Jones, Kim; Wright, Derek W.; Paulus-Hock, Viola; et al. (Cell Reports, 2020)
Pancreatic ductal adenocarcinoma (PDAC) can be divided into transcriptomic subtypes with two broad lineages referred to as classical (pancreatic) and squamous. We find that these two subtypes are driven by distinct metabolic phenotypes. Loss of genes that drive endodermal lineage specification, HNF4A and GATA6, switch metabolic profiles from classical (pancreatic) to predominantly squamous, with glycogen synthase kinase 3 beta (GSK3β) a key regulator of glycolysis. Pharmacological inhibition of GSK3β results in selective sensitivity in the squamous subtype; however, a subset of these squamous patient-derived cell lines (PDCLs) acquires rapid drug tolerance. Using chromatin accessibility maps, we demonstrate that the squamous subtype can be further classified using chromatin accessibility to predict responsiveness and tolerance to GSK3β inhibitors. Our findings demonstrate that distinct patterns of chromatin accessibility can be used to identify patient subgroups that are indistinguishable by gene expression profiles, highlighting the utility of chromatin-based biomarkers for patient selection in the treatment of PDAC. Brunton et al. demonstrate that differential chromatin accessibility can predict responsiveness and tolerance to GSK3β inhibitors in the squamous subtype of PDAC. This study provides an important proof of concept that chromatin accessibility can be used to identify additional PDAC subgroups with potential therapeutic utility.
CRIS-Team Scopus Importer:2020-05-19
Keywords: chromatin landscapes; GATA6; GSK3B; HNF4A; intronic and distal promoters; metabolic targeting; PDAC subtypes; therapeutic tolerance

Human glycoprotein-2 expressed in Brunner glands – A putative autoimmune target and link between Crohn's and coeliac disease - Roggenbuck, Dirk; Goihl, Alexander; Sowa, Mandy; Lopens, Steffi; Rödiger, Stefan; Schierack, Peter; Conrad, Karsten; Sommer, Ulrich; Jöhrens, Korinna; Grützmann, Robert; Reinhold, Dirk; Laass, Martin W. (Clinical Immunology, 2023)
Glycoprotein 2 (GP2) is an autoantigen in Crohn's (CD) and coeliac disease (CeD). We assessed GP2-isoform (GP21–4)-expression in intestinal biopsies of paediatric patients with CD, CeD, ulcerative colitis (UC), and healthy children (HC). Transcription of GP21–4 was elevated in proximal small intestine in CeD and CD patients (only GP22/4) compared to jejunum (CeD/CD) and large bowel (CD). CeD patients demonstrated higher duodenal GP22/4-mRNA levels compared to HC/UC patients whereas CD patients showed higher GP24-mRNA levels compared to UC patients. Duodenal synthesis of only small GP2 isoforms (GP23/4) was demonstrated in epithelial cells in patients/HC and in Brunner glands (also large isoforms) with a more frequent apical location in CD/CeD patients. All four GP2 isoforms interacted with gliadin and phosphopeptidomannan. Gliadin digestion improved binding to GP2 isoforms. GP21–4 binding to CeD/CD-related antigens, elevated duodenal GP21–4-mRNA transcription, and GP2-protein secretion in Brunner glands of CeD/CD patients suggest an autoimmune CeD/CD link.
CRIS-Team Scopus Importer:2023-02-24
Keywords: Celiac disease; Crohn's disease; Zymogen granule membrane glycoprotein GP2

Human guanylate binding protein-1 (hGBP-1) characterizes and establishes a non-angiogenic endothelial cell activation phenotype in inflammatory diseases - Naschberger, Elisabeth; Stürzl, Michael; et al. (Advances in Enzyme Regulation, 2005)
Blood vessel activation in inflammatory diseases is triggered by a myriad of different factors that partially reveal opposite activities on endothelial cells (EC). For example, inflammatory cytokines (IC) inhibit EC proliferation and induce cell adhesiveness for leukocytes. In contrast, angiogenic growth factors (AGF) activate EC proliferation and inhibit cell adhesiveness for leukocytes. In consequence, IC and AGF may induce two different activation phenotypes in EC that appear in a temporally and/or spatially coordinated manner in inflammatory tissues. Human guanylate binding protein-1 (hGBP-1) is a member of the large GTPase protein family. New results demonstrate that hGBP-1 is a specific marker of IC-activated EC that allows to differentiate the IC- and AGF-activated phenotype of EC at the single cell level, both in vitro and in vivo. In addition, hGBP-1 is the key mediator of the inhibitory effects of IC on EC proliferation and invasiveness. Both the expression pattern of hGBP-1 and its activity in EC supported the hypothesis that IC- and AGF-activation induce distinct adversely related phenotypes in EC. In future, hGBP-1 may be used as a marker to monitor the IC-induced phenotype of EC in inflammation and may also be exploited as a target to modulate EC activity in inflammatory diseases and tumor angiogenesis. © 2005 Elsevier Ltd. All rights reserved.
Created from Fastlane, Scopus look-up

Human guanylate binding protein-1 is a secreted GTPase present in increased concentrations in the cerebrospinal fluid of patients with bacterial meningitis - Naschberger, Elisabeth; Stürzl, Michael; et al. (American Journal of Pathology, 2006)
Created from Fastlane, Scopus look-up

Human herpesvirus-8 and Kaposi's sarcoma: relationship with the multistep concept of tumorigenesis. - Stürzl, Michael; Zietz, Christian; Monini, Paolo; Ensoli, Barbara (Advances in Cancer Research, 2001)
Kaposi's sarcoma (KS) develops through discrete inflammatory-angiogenic stages of polyclonal nature (early-stage lesions) to monomorphic nodules of spindle-shaped cells that can be clonal (late-stage lesions) and resemble true sarcomas. Molecular and epidemiological studies indicate that development of KS is tightly associated with infection by the human herpesvirus-8 (HHV-8). However, only individuals with specific conditions of immunodysregulation develop KS. In these individuals the systemic and tissue increase of Th-1-type cytokines (IC) reactivate HHV-8 infection, leading to increased viral load, antibody titers, and an expanded cell tropism that precedes the clinical appearance of KS. Recruitment of the virus into tissues by infected monocytes and other cell types is facilitated by the endothelial cell activation due to IC. In clinical lesions, HHV-8 infection increases with lesion stage and in late-stage lesions most of the spindle cells are latently infected, whereas only few lyrically infected cells are present, suggesting that latent genes may have a role in the transformation of the early inflammatory-hyperplastic lesion into a real sarcoma. The development of tumors, however, is regulated through a multistep process based on the acquisition by cells of several different capabilities leading to malignant growth. Here we review the available data on the expression of HHV-8-encoded genes in primary KS lesions and, in view of their biological activity, analyze their potential function in different steps of tumorigenesis. By this pragmatic approach interesting insights into potential key functions of HHV-8-encoded genes are found and steps of potential cooperativity with other viral factors (HIV-1-Tat) in the pathogenesis of KS are identified.

Human herpesvirus-8 (HHV-8) gene expression in Kaposi's sarcoma (KS) primary lesions: an in situ hybridization study. - Stürzl, Michael; Wunderlich, A; Ascherl, Gudrun; Hohenadl, C; Monini, Paolo; Zietz, Christian; Browning, Philip J.; Neipel, Frank; Biberfeld, Peter; Ensoli, Barbara (Leukemia, 1999)

Hypermutation In Pancreatic Cancer - Humphris, Jeremy L.; Patch, Ann-Marie; Nones, Katia; Bailey, Peter J.; Johns, Amber L.; Mckay, Skye; Chang, David K.; Miller, David K.; Pajic, Marina; Kassahn, Karin S.; Quinn, Michael C. J.; Bruxner, Timothy J. C.; et al. (Gastroenterology, 2017)
Pancreatic cancer is molecularly diverse, with few effective therapies. Increased mutation burden and defective DNA repair are associated with response to immune checkpoint inhibitors in several other cancer types. We interrogated 385 pancreatic cancer genomes to define hypermutation and its causes. Mutational signatures inferring defects in DNA repair were enriched in those with the highest mutation burdens. Mismatch repair deficiency was identified in 1% of tumors harboring different mechanisms of somatic inactivation of MLH1 and MSH2. Defining mutation load in individual pancreatic cancers and the optimal assay for patient selection may inform clinical trial design for immunotherapy in pancreatic cancer.
EVALuna2:15259

Hypoxia generates a more invasive phenotype of tumour cells: An in vivo experimental setup based on the chorioallantoic membrane - Demir, Resit; Naschberger, Elisabeth; Demir, Ilknur; Melling, Nathaniel; Dimmler, Arno; Papadopoulus, Thomas; Stürzl, Michael; Klein, Peter; Hohenberger, Werner (Pathology & Oncology Research, 2009)
Of all processes involved in carcinogenesis, local invasion and the formation of metastases are the clinically most relevant but the scientifically least well understood at their molecular level. Recent experimental progress has identified that tumour hypoxia not only induces tumour angiogenesis, but also modulates the expression of several genes that have been implicated in tumour invasion and metastasis. Here we developed an in vivo model to understand a number of molecular pathways and cellular mechanisms for tumour invasion in hypoxia. For this purpose fertilized chicken eggs were incubated for 10 days in normoxic conditions. Subsequently colon carcinoma cells (SW-480) were placed on the chorioallantoic membrane. During the following 6 days the eggs were incubated either in normoxic conditions or in stepwise decreasing hypoxic conditions. SW-480 colon carcinoma cells did not invade the epithelial layer in normoxic conditions. In contrast an invasion through the epithelial layer in to the mesoderm was already seen after 3 days when incubated in hypoxic conditions. The chorioallantoic membrane assay described in this paper allows investigating tumour invasion and its cellular mechanisms under defined hypoxic conditions. © 2008 Arányi Lajos Foundation.
Created from Fastlane, Scopus look-up
Keywords: Chorioallantoic membrane; Hypoxia; Tumor progression; Tumour invasion

Identification and validation of a multivariable prediction model based on blood plasma and serum metabolomics for the distinction of chronic pancreatitis subjects from non-pancreas disease control subjects - Adam, M. Gordian; Beyer, Georg; Christiansen, Nicole; Kamlage, Beate; Pilarsky, Christian; Distler, Marius; Fahlbusch, Tim; Chromik, Ansgar; Klein, Fritz; Bahra, Marcus; Uhl, Waldemar; Grützmann, Robert; et al. (Gut, 2021)
Objective Chronic pancreatitis (CP) is a fibroinflammatory syndrome leading to organ dysfunction, chronic pain, an increased risk for pancreatic cancer and considerable morbidity. Due to a lack of specific biomarkers, diagnosis is based on symptoms and specific but insensitive imaging features, preventing an early diagnosis and appropriate management. Design We conducted a type 3 study for multivariable prediction for individual prognosis according to the TRIPOD guidelines. A signature to distinguish CP from controls (n=160) was identified using gas chromatography-mass spectrometry and liquid chromatography-tandem mass spectrometry on ethylenediaminetetraacetic acid (EDTA)-plasma and validated in independent cohorts. Results A Naive Bayes algorithm identified eight metabolites of six ontology classes. After algorithm training and computation of optimal cut-offs, classification according to the metabolic signature detected CP with an area under the curve (AUC) of 0.85 ((95% CI 0.79 to 0.91). External validation in two independent cohorts (total n=502) resulted in similar accuracy for detection of CP compared with non-pancreatic controls in EDTA-plasma (AUC 0.85 (95% CI 0.81 to 0.89)) and serum (AUC 0.87 (95% CI 0.81 to 0.95)). Conclusions This is the first study that identifies and independently validates a metabolomic signature in plasma and serum for the diagnosis of CP in large, prospective cohorts. The results could provide the basis for the development of the first routine laboratory test for CP.
CRIS-Team WoS Importer:2021-11-05

Identification of Genes Associated with Liver Metastasis in Pancreatic Cancer Reveals PCSK6 as a Crucial Mediator - He, Hang; Zhang, Shuman; Yang, Hai; Xu, Pengyan; Kutschick, Isabella; Pfeffer, Sina; Britzen-Laurent, Nathalie; Grützmann, Robert; Fu, Deliang; Pilarsky, Christian (Cancers, 2023)
Liver metastasis occurs frequently in patients with pancreatic cancer. We analyzed the molecular profiling in liver metastatic lesions aiming to uncover novel genes responsible for tumor progression. Bioinformatics analysis was applied to identify genes directing liver metastasis. CRISPR/Cas9 technology was used to knock out the candidate gene. Proliferation assays, colony formation assays, cell cycle analysis, migration assays, wound healing assays, Immunofluorescence analysis, and the tumor xenograft model of intrasplenic injection were adopted to evaluate the effects of PCSK6 inactivation on cell growth, migration and liver metastasis. GSEA and Western blot were used to investigate the corresponding signaling pathway. PCSK6 was one of the obtained liver-metastasis-related genes in pancreatic cancer. PCSK6 inactivation inhibited cell growth and cell migration, due to G0/G1 cell cycle arrest and the remodeling of cell–cell junctions or the cell skeleton, respectively. PCSK6 inactivation led to fewer counts and lower outgrowth rates of liver metastatic niches in vivo. The Raf-MEK1/2-ERK1/2 axis was repressed by PCSK6 inactivation. Accordingly, we found PCSK6 inactivation could inhibit cell growth, cell migration, and liver metastasis, and explored the role of the Raf-MEK1/2-ERK1/2 axis in PCSK6 inactivation. PCSK6-targeted therapy might represent a novel approach for combatting liver metastasis in pancreatic cancer.
CRIS-Team Scopus Importer:2023-01-20
Keywords: CRISPR/Cas9; ERK; liver metastasis; PCSK6

Identification of interleukin-1 and platelet-derived growth factor-B as major mitogens for the spindle cells of Kaposi's sarcoma: a combined in vitro and in vivo analysis. - Stürzl, Michael; Brandstetter, H; Zietz, Christian; Eisenburg, B; Raivich, G; Gearing, D P; Brockmeyer, Norbert H.; Hofschneider, Peter Hans (Oncogene, 1995)
By means of a combined in vitro and in vivo analysis we provide evidence that IL-1 beta and PDGF-B, but not OSM (oncostatin M) or IL-6, are major mitogens for the spindle cells of Kaposi's sarcoma (KS) in vivo. PDGF-B and IL-1 beta stimulated proliferation of cultivated KS spindle cells in vitro. Analysis of gene expression in vivo revealed that both factors as well as the PDGF beta-receptor are present in KS lesions. By contrast, IL-6 had no effect and OSM inhibited proliferation of cultivated KS spindle cells. Again, the effect of these factors on cultivated KS spindle cells in vitro was reflected by the gene expression observed in KS lesions in vivo. Neither the expression of IL-6 receptor nor of OSM could be detected in KS lesions by in situ hybridization. Moreover, in situ hybridization revealed an identical pattern of gene expression in cultivated KS spindle cells and KS spindle cells in vivo with respect to the above-mentioned cytokines [PDGF-B, IL-1 beta, IL-1 alpha, IL-6, OSM] and their receptors [PDGF beta-receptor, gp130, IL-6 receptor, leukemia inhibitory factor (LIF) receptor]. This further supported the suitability of cultivated KS spindle cells as an in vitro model in order to determine which cytokines may activate proliferation of KS spindle cells in vivo.

Identification of Predictive Markers for Response to Neoadjuvant Chemoradiation in Rectal Carcinomas by Proteomic Isotope Coded Protein Label (ICPL) Analysis - Croner, Roland S.; Sevim, Muezeyyen; Metodiev, Metodi V.; Jo, Peter; Ghadimi, Michael; Schellerer, Vera; Brunner, Michaela; Geppert, Carol-Immanuel; Rau, Tilman; Stürzl, Michael; Naschberger, Elisabeth; Matzel, Klaus E.; et al. (International Journal of Molecular Sciences, 2016)
Neoadjuvant chemoradiation (nCRT) is an established procedure in stage union internationale contre le cancer (UICC) II/III rectal carcinomas. Around 53% of the tumours present with good tumor regression after nCRT, and 8%-15% are complete responders. Reliable selection markers would allow the identification of poor or non-responders prior to therapy. Tumor biopsies were harvested from 20 patients with rectal carcinomas, and stored in liquid nitrogen prior to therapy after obtaining patients' informed consent (Erlangen-No.3784). Patients received standardized nCRT with 5-Fluoruracil (nCRT I) or 5-Fluoruracil ± Oxaliplatin (nCRT II) according to the CAO/ARO/AIO-04 protocol. After surgery, regression grading (Dworak) of the tumors was performed during histopathological examination of the specimens. Tumors were classified as poor (Dworak 1 + 2) or good (Dworak 3 + 4) responders. Laser capture microdissection (LCM) for tumor enrichment was performed on preoperative biopsies. Differences in expressed proteins between poor and good responders to nCRT I and II were identified by proteomic analysis (Isotope Coded Protein Label, ICPL(TM)) and selected markers were validated by immunohistochemistry. Tumors of 10 patients were classified as histopathologically poor (Dworak 1 or 2) and the other 10 tumor samples as histopathologically good (Dworak 3 or 4) responders to nCRT after surgery. Sufficient material in good quality was harvested for ICPL analysis by LCM from all biopsies. We identified 140 differentially regulated proteins regarding the selection criteria and the response to nCRT. Fourteen of these proteins were synchronously up-regulated at least 1.5-fold after nCRT I or nCRT II (e.g., FLNB, TKT, PKM2, SERINB1, IGHG2). Thirty-five proteins showed a complete reciprocal regulation (up or down) after nCRT I or nCRT II and the rest was regulated either according to nCRT I or II. The protein expression of regulated proteins such as PLEC1, TKT, HADHA and TAGLN was validated successfully by immunohistochemistry. ICPL is a valid method to identify differentially expressed proteins in rectal carcinoma tissue between poor vs. good responders to nCRT. The identified protein markers may act as selection criteria for nCRT in the future, but our preliminary findings must be reproduced and validated in a prospective cohort.
EVALuna2:6749

IFN-γ and TNF-α-induced GBP-1 inhibits epithelial cell proliferation through suppression of β-catenin/TCF signaling - Capaldo, C. T.; Beeman, N.; Hilgarth, R. S.; Nava, Porfirio; Louis, N. A.; Naschberger, Elisabeth; Stürzl, Michael; Parkos, C. A.; Nusrat, A. (Mucosal Immunology, 2012)
Proinflammatory cytokines induce guanylate-binding protein 1 (GBP-1) protein expression in intestinal epithelial tissues. GBP-1 has been described as influencing a number of cellular processes important for epithelial homeostasis, including cell proliferation. However, many questions remain as to the role of GBP-1 in intestinal mucosal homeostasis. We therefore sought to investigate the function of proinflammatory cytokine-induced GBP-1 during intestinal epithelial cell proliferation. Through the use of complementary GBP-1 overexpression and small interfering RNA-mediated knockdown studies, we now show that GBP-1 acts to inhibit pro-mitogenic β-catenin/T cell factor (TCF) signaling. Interestingly, proinflammatory cytokine-induced GBP-1 was found to be a potent suppressor of β-catenin protein levels and β-catenin serine 552 phosphorylation. Neither glycogen synthase kinase 3β nor proteasomal inhibition alleviated GBP-1-mediated suppression of cell proliferation or β-catenin/TCF signaling, indicating a non-canonical mechanism of β-catenin inhibition. Together, these data show that cytokine-induced GBP-1 retards cell proliferation by forming a negative feedback loop that suppresses β-catenin/TCF signaling. © 2012 Society for Mucosal Immunology.
Created from Fastlane, Scopus look-up

IFN-γ-driven intratumoral microenvironment exhibits superior prognostic effect compared with an IFN-α-driven microenvironment in patients with colon carcinoma - Grenz, Sandra; Naschberger, Elisabeth; Merkel, Susanne; Britzen-Laurent, Nathalie; Schaal, Ute; Konrad, Andreas; Aigner, Michael; Rau, Tilman; Hartmann, Arndt; Croner, Roland S.; Hohenberger, Werner; Stürzl, Michael (American Journal of Pathology, 2013)
Interferon (IFN)-α and IFN-γ are cytokines with potent immunomodulating and anti-tumor activities. It is unknown which of the two IFNs may be more potent in the regulation of an anti-tumorigenic response in colorectal carcinoma or whether both cytokines cooperate. We, therefore, established human myxovirus resistance protein A and human guanylate-binding protein-1 as markers for the differential detection of IFN-α- and IFN-γ-driven tumor micromilieus, respectively. In vitro studies with different cultures of tumor cells from colorectal carcinoma and stroma cells showed that the expression of myxovirus resistance protein A was exclusively induced by IFN-α, whereas guanylate-binding protein-1 was strongly induced by IFN-γ and only weakly by IFN-α. This expression pattern was used to distinguish cell activation caused by the two cytokines in a clinical cohort of patients with colon carcinoma (n = 378). Patients with primary tumors expressing only guanylate-binding protein-1 exhibited the highest cancer-specific 5-year survival (94.0%, P = 0.006) compared with those expressing both factors (90.3%, P = 0.006), myxovirus resistance protein A alone (83.5%, P = 0.096), or none (72.8%). Our study describes a successful proof-of-principle approach that complex cytokine interaction networks can be dissected in human tissues and demonstrates that an IFN-γ-driven tumor microenvironment exhibits a superior prognostic effect compared with an IFN-α-driven tumor microenvironment in colon carcinoma. © 2013 American Society for Investigative Pathology.
Created from Fastlane, Scopus look-up

IFN-γ drives inflammatory bowel disease pathogenesis through VE-cadherin-directed vascular barrier disruption - Langer, Victoria; Vivi, Eugenia; Regensburger, Daniela; Winkler, Thomas; Waldner, Maximilian; Rath, Timo; Schmid, Benjamin; Skottke, Lisa; Lee, Somin; Jeon, Noo Li; Wohlfahrt, Thomas; Kramer, Viktoria; et al. (Journal of Clinical Investigation, 2019)
Inflammatory bowel disease (IBD) is a chronic inflammatory disorder with rising incidence. Diseased tissues are heavily vascularized. Surprisingly, the pathogenic impact of the vasculature in IBD and the underlying regulatory mechanisms remain largely unknown. IFN-γ is a major cytokine in IBD pathogenesis, but in the context of the disease, it is almost exclusively its immune-modulatory and epithelial cell-directed functions that have been considered. Recent studies by our group demonstrated that IFN-γ also exerts potent effects on blood vessels. Based on these considerations, we analyzed the vessel-directed pathogenic functions of IFN-γ and found that it drives IBD pathogenesis through vascular barrier disruption. Specifically, we show that inhibition of the IFN-γ response in vessels by endothelial-specific knockout of IFN-γ receptor 2 ameliorates experimentally induced colitis in mice. IFN-γ acts pathogenic by causing a breakdown of the vascular barrier through disruption of the adherens junction protein VE-cadherin. Notably, intestinal vascular barrier dysfunction was also confirmed in human IBD patients, supporting the clinical relevance of our findings. Treatment with imatinib restored VE-cadherin/adherens junctions, inhibited vascular permeability, and significantly reduced colonic inflammation in experimental colitis. Our findings inaugurate the pathogenic impact of IFN-γ-mediated intestinal vessel activation in IBD and open new avenues for vascular-directed treatment of this disease.

IFN-γ-response mediator GBP-1 represses human cell proliferation by inhibiting the Hippo signaling transcription factor TEAD - Unterer, Bea; Wiesmann, Veit; Gunasekaran, Mekala; Sticht, Heinrich; Tenkerian, Clara; Behrens, Jürgen; Leone, Marina; Engel, Felix; Britzen-Laurent, Nathalie; Naschberger, Elisabeth; Wittenberg, Thomas; Stürzl, Michael (Biochemical Journal, 2018)
Interferon-gamma (IFN-γ) is a pleiotropic cytokine that exerts important functions in inflammation, infectious diseases, and cancer. The large GTPase human guanylate-binding protein 1 (GBP-1) is among the most strongly IFN-γ-induced cellular proteins. Previously, it has been shown that GBP-1 mediates manifold cellular responses to IFN-γ including the inhibition of proliferation, spreading, migration, and invasion and through this exerts anti-tumorigenic activity. However, the mechanisms of GBP-1 anti-tumorigenic activities remain poorly understood. Here, we elucidated the molecular mechanism of the human GBP-1-mediated suppression of proliferation by demonstrating for the first time a cross-talk between the anti-tumorigenic IFN-γ and Hippo pathways. The α9-helix of GBP-1 was found to be sufficient to inhibit proliferation. Protein-binding and molecular modeling studies revealed that the α9-helix binds to the DNA-binding domain of the Hippo signaling transcription factor TEA domain protein (TEAD) mediated by the 376VDHLFQK382 sequence at the N-terminus of the GBP-1-α9-helix. Mutation of this sequence resulted in abrogation of both TEAD interaction and suppression of proliferation. Further on, the interaction caused inhibition of TEAD transcriptional activity associated with the down-regulation of TEAD-target genes. In agreement with these results, IFN-γ treatment of the cells also impaired TEAD activity, and this effect was abrogated by siRNA-mediated inhibition of GBP-1 expression. Altogether, this demonstrated that the α9-helix is the proliferation inhibitory domain of GBP-1, which acts independent of the GTPase activity through the inhibition of the Hippo transcription factor TEAD in mediating the anti-proliferative cell response to IFN-γ.
EVALuna2:34818

IL-23 is centrally involved in mediating molecular resistance to anti-TNF therapy in Crohn's disease patients - Schmitt, H.; Billmeier, Ulrike; Dieterich, Walburga; Rath, T.; Sonnewald, Sophia; Reid, Stephen; Hirschmann, S.; Hildner, Kai; Waldner, Maximilian; Mudter, J.; Hartmann, Arndt; Grützmann, Robert; et al. (2018)
EVALuna2:34077

IL-3: key orchestrator of inflammation - Podolska, Malgorzata; Grützmann, Robert; Pilarsky, Christian; Benard, Alan (Frontiers in Immunology, 2024)
Interleukin (IL)-3 has long been known for its hematopoietic properties. However, recent evidence has expanded our understanding of IL-3 function by identifying IL-3 as a critical orchestrator of inflammation in a wide array of diseases. Depending on the type of disease, the course of inflammation, the cell or the tissue involved, IL-3 promotes either pathologic inflammation or its resolution. Here, we describe the cell-specific functions of IL-3 and summarize its role in diseases. We discuss the current treatments targeting IL-3 or its receptor, and highlight the potential and the limitations of targeting IL-3 in clinics.
CRIS-Team Scopus Importer:2024-07-12
Keywords: cancer; CD123; infection; inflammation; interleukin-3

IL-3 orchestrates ulcerative colitis pathogenesis by controlling the development and the recruitment of splenic reservoir neutrophils - Benard, Alan; Mittelstädt, Anke; Klösch, Bettina; Glanz, Karolina; Müller, Jan; Schoen, Janina; Nüse, Björn; Brunner, Maximilian; Naschberger, Elisabeth; Stürzl, Michael; Mattner, Jochen; Munoz, Luis Enrique; et al. (Cell Reports, 2023)
Inflammatory bowel diseases (IBDs) are a global health issue with an increasing incidence. Although the pathogenesis of IBDs has been investigated intensively, the etiology of IBDs remains enigmatic. Here, we report that interleukin-3 (Il-3)-deficient mice are more susceptible and exhibit increased intestinal inflammation during the early stage of experimental colitis. IL-3 is locally expressed in the colon by cells harboring a mesenchymal stem cell phenotype and protects by promoting the early recruitment of splenic neutrophils with high microbicidal capability into the colon. Mechanistically, IL-3-dependent neutrophil recruitment involves CCL5+ PD-1high LAG-3high T cells, STAT5, and CCL20 and is sustained by extramedullary splenic hematopoiesis. During acute colitis, Il-3−/− show, however, increased resistance to the disease as well as reduced intestinal inflammation. Altogether, this study deepens our understanding of IBD pathogenesis, identifies IL-3 as an orchestrator of intestinal inflammation, and reveals the spleen as an emergency reservoir for neutrophils during colonic inflammation.
CRIS-Team Scopus Importer:2023-06-23
Keywords: CCL5; colitis; CP: Immunology; interleukin-3; neutrophils; spleen

IL-3 protects from colitis by recruiting splenic reservoir neutrophils - Benard, A.; Kloesch, B.; Kutschick, I.; Grützmann, Robert; Weber, Georg (EUROPEAN JOURNAL OF IMMUNOLOGY, 2019)
CRIS-Team WoS Importer:2019-11-05

Impact of age on the efficacy of oxaliplatin in the preoperative chemoradiotherapy and adjuvant chemotherapy of rectal cancer: a post hoc analysis of the CAO/ARO/AIO-04 phase III trial - Hofheinz, R. -D.; Arnold, D.; Fokas, E.; Kaufmann, M.; Hothorn, T.; Folprecht, G.; Fietkau, Rainer; Hohenberger, Werner; Ghadimi, M.; Liersch, T.; Grabenbauer, G. G.; Sauer, Rolf; et al. (Annals of Oncology, 2018)
Background: The German rectal cancer trial CAO/ARO/AIO-04 has shown a significant benefit in 3-year disease-free survival (DFS) of adding oxaliplatin to a standard preoperative 5-fluorouracil (5-FU)-based chemoradiotherapy (CRT) and adjuvant chemotherapy in patients with locally advanced rectal cancer. The use of oxaliplatin as adjuvant treatment in elderly patients with colon cancer is controversial. We therefore investigated the impact of age on clinical outcome in the CAO/ARO/AIO-04 phase III trial. Patients and methods: We carried out a post hoc analysis of the CAO/ARO/AIO-04 phase III trial evaluating primary and secondary end points according to age. Patient and tumor characteristics, NCI CTC adverse events grades 3-4 (version 3.0), dose intensities as well as survival and recurrence data were analyzed in three specified age groups (<60, 60-70, and ≥70 years). The influence of age as a continuous variable on DFS was modeled using a subpopulation treatment effect pattern plot (STEPP) analysis. Results: A total of 1232 patients were assessable. With the exception of Eastern Cooperative Oncology Group status (P < 0.001), no differences in patient and tumor characteristics were noticed between age groups. Likewise, toxicity pattern, dose intensities of CRT and surgical results were similar in all age groups. After a median follow-up of 50 months, in patients aged <60 years a significant benefit of adding oxaliplatin to 5-FU-based CRT and adjuvant chemotherapy was observed for local (P = 0.013) and systemic recurrences (P = 0.023), DFS (P = 0.011), and even overall survival (OS; P = 0.044). The STEPP analysis revealed improved hazard ratios for DFS in patients aged 40-70 years compared with elderly patients treated with oxaliplatin. Conclusion: The addition of oxaliplatin significantly improved DFS and OS in younger patients aged <60 years with advanced rectal cancer. Patients aged ≥70 years had no benefit. Clinical Trials Number: NCT00349076.
EVALuna2:36460

Impact of Aspirin Intake on Postoperative Survival after Primary Pancreatic Resection of Pancreatic Ductal Adenocarcinoma—A Single-Center Evaluation - Hackner, Danilo; Hobbs, Mirianna; Merkel, Susanne; Krautz, Christian; Weber, Georg; Grützmann, Robert; Brunner, Maximilian (Biomedicines, 2023)
(1) Background: The intake of aspirin (ASS) has been demonstrated to have a relevant impact on the pathogenesis, incidence and outcome in different solid gastrointestinal tumors. However, data on the effect of ASS on the short-term outcome and the long-term survival in patients with pancreatic carcinoma are still limited. (2) Methods: A total of 213 patients who underwent primary resection of PDAC at the University Hospital of Erlangen from January 2000 to December 2018 were included in this retrospective single-center study in total. Patients were stratified according to the aspirin intake into three groups: continuous aspirin intake (cASS), perioperatively interrupted aspirin intake (iASS) and no aspirin intake (no ASS) at the timepoint of surgery. The postoperative outcome as well as long-term survival were compared between the groups. (3) Results: There were no differences regarding postoperative morbidity (iASS: 54% vs. cASS: 53% vs. no ASS: 64%, p = 0.448) and in-hospital mortality (iASS: 4% vs. cASS: 10% vs. no ASS: 3%, p = 0.198) between the groups. The overall survival (OS) and disease-free survival (DFS) did not differ in the groups when comparing the ASS-intake status (OS: iASS 17.8 months vs. cASS 19.6 months vs. no ASS 21.6 months, p = 0.489; DFS: iASS 14.0 months vs. cASS 18.3 months vs. no ASS 14.7 months, p = 0.957). Multivariate analysis revealed that age (hazard ratio (HR) 2.2, p < 0.001), lymph node-positive status (HR 2.0, p < 0.001), R status 1 or 2 (HR 2.8, p < 0.001) and differentiation with a grading of 3 (HR 1.7, p = 0.005) were significant independent prognostic factors regarding the OS. Moreover, age (HR 1.5, p = 0.040), lymph node-positive status (HR 1.8, p = 0.002) and high-grade (G3) carcinomas (HR 1.5, p = 0.037) could be identified as independent prognostic parameters for DFS. (4) Conclusions: In patients undergoing primary surgery for curative resection of pancreatic carcinoma, the perioperative intake of ASS had no significant impact on postoperative outcome, overall and disease-free survival.
CRIS-Team Scopus Importer:2023-06-09
Keywords: aspirin intake; disease-free survival; overall survival; pancreatic ductal adenocarcinoma; pancreatic resection

Impact of CRISPR/Cas9-Mediated CD73 Knockout in Pancreatic Cancer - Zhang, Jinping; Zhang, Shuman; Dörflein, Isabella; Ren, Xiaofan; Pfeffer, Sina; Britzen-Laurent, Nathalie; Grützmann, Robert; Duan, Xianglong; Pilarsky, Christian (Cancers, 2023)
Pancreatic cancer is among the cancers with the highest mortality rates. Most of the patients are found to have advanced cancer, losing the chance of surgical treatment, and there is an urgent need to find new treatment methods. Targeted therapy for specific genes that play a key role in cancer is now an important means to improve the survival rate of patients. We determined that CD73 is highly expressed in pancreatic cancer by flow cytometry and qRT-PCR assays combined with bioinformatics techniques. Application of CRISPR/Cas9 technology to knockout CD73 in human and murine cell lines, respectively, revealed that CD73 inactivation inhibited cell growth and migration and induced G1 cell cycle arrest. We also found that CD73 deletion inhibited the ERK/STAT3 pathway and activated the E-cadherin pathway. In addition, a CRISPR/Cas9 protein kinase library screen was performed and identified Pbk, Fastk, Cdk19, Adck5, Trim28, and Pfkp as possible genes regulating CD73.
CRIS-Team Scopus Importer:2023-10-20
Keywords: CD73; CRISPR/Cas9; deep sequencing; pancreatic cancer

Impact of Patient Age on Postoperative Short-Term and Long-Term Outcome after Pancreatic Resection of Pancreatic Ductal Adenocarcinoma - Hackner, Danilo; Hobbs, Mirianna; Merkel, Susanne; Siepmann, Timo; Krautz, Christian; Weber, Georg; Grützmann, Robert; Brunner, Maximilian (Cancers, 2022)
Simple Summary Pancreatic ductal adenocarcinoma (PDAC) is frequently seen in elderly patients. The aim of our retrospective study was to evaluate the impact of age on postoperative short-term and long-term outcomes in patients undergoing curative pancreatic resection for PDAC. Our data confirm that pancreatic resections can be performed with equal short-term outcomes even in older age. However, patient age significantly influenced the overall and disease-free survival of patients with PDAC undergoing primary resection in curative intent. Therefore, the choice of the optimal therapy concept for each patient should be individualized taking into account the patient's age. (1) Purpose: to evaluate the impact of age on postoperative short-term and long-term outcomes in patients undergoing curative pancreatic resection for PDAC. (2) Methods: This retrospective single-center study comprised 213 patients who had undergone primary resection of PDAC from January 2000 to December 2018 at the University Hospital of Erlangen, Germany. Patients were stratified according the age into two groups: younger (<= 70 years) and older (>70 years) patients. Postoperative outcome and long-term survival were compared between the groups. (3) Results: There were no significant differences regarding inhospital morbidity (58% vs. 67%, p = 0.255) or inhospital mortality (2% vs. 7%, p = 0.073) between the two groups. The median overall survival (OS) and disease-free survival (DFS) were significantly shorter in elderly patients (OS: 29.2 vs. 17.1 months, p < 0.001, respectively; DFS: 14.9 vs. 10.4 months, p = 0.034). Multivariate analysis revealed that age was a significant independent prognostic predictor for OS and DFS (HR 2.23, 95% CI 1.58-3.15; p < 0.001 for OS and HR 1.62, 95% CI 1.17-2.24; p = 0.004 for DFS). (4) Conclusion: patient age significantly influenced overall and disease-free survival in patients with PDAC undergoing primary resection in curative intent.
CRIS-Team WoS Importer:2022-09-09

Impact of resection margin status on survival in advanced N stage pancreatic cancer – a multi-institutional analysis - Teske, Christian; Stimpel, Richard; Distler, Marius; Merkel, Susanne; Grützmann, Robert; Bolm, Louisa; Wellner, Ulrich; Keck, Tobias; Aust, Daniela; Weitz, Juergen; Welsch, Thilo (Langenbecks Archives of Surgery, 2021)
Background: The present study aimed to examine the impact of microscopically tumour-infiltrated resection margins (R1) in pancreatic ductal adenocarcinoma (PDAC) patients with advanced lymphonodular metastasis (pN1–pN2) on overall survival (OS). Methods: This retrospective, multi-institutional analysis included patients undergoing surgical resection for PDAC at three tertiary university centres between 2005 and 2018. Subcohorts of patients with lymph node status pN0–N2 were stratified according to the histopathological resection status using Kaplan-Meier survival analysis. Results: The OS of the entire cohort (n = 620) correlated inversely with the pN status (26 [pN0], 18 [pN1], 11.8 [pN2] months, P < 0.001) and R status (21.7 [R0], 12.5 [R1] months, P < 0.001). However, there was no statistically significant OS difference between R0 versus R1 in cases with advanced lymphonodular metastases: 19.6 months (95% CI: 17.4–20.9) versus 13.6 months (95% CI: 10.7–18.0) for pN1 stage and 13.7 months (95% CI: 10.7–18.9) versus 10.1 months (95% CI: 7.9–19.1) for pN2, respectively. Accordingly, N stage–dependent Cox regression analysis revealed that R status was a prognostic factor in pN0 cases only. Furthermore, there was no significant survival disadvantage for patients with R0 resection but circumferential resection margin invasion (≤ 1 mm; CRM+; 10.7 months) versus CRM-negative (13.7 months) cases in pN2 stages (P = 0.5). Conclusions: An R1 resection is not associated with worse OS in pN2 cases. If there is evidence of advanced lymph node metastasis and a re-resection due to an R1 situation (e.g. at venous or arterial vessels) may substantially increase the perioperative risk, margin clearance in order to reach local control might be avoided with respect to the OS.
CRIS-Team Scopus Importer:2021-03-26
Keywords: Lymph node; Pancreatectomy; PDAC; Resection status; Survival

Impact of selective anti-BMP9 treatment on tumor cells and tumor angiogenesis - Brand, Verena; Lehmann, Christian; Umkehrer, Christian; Bissinger, Stefan; Thier, Martina; De Wouters, Mariana; Raemsch, Romi; Jucknischke, Ute; Haas, Alexander; Breuer, Sebastian; Birzele, Fabian; Racek, Tomas; et al. (Molecular Oncology, 2016)
The role of bone morphogenic protein 9 (BMP9) signaling in angiogenesis has been controversial, with a number of studies showing that it acts either as a pro-angiogenic or, conversely, as an anti-angiogenic factor in a context-dependent manner. Notably, BMP9 was also reported to function in both pro- or anti-tumorigenic roles during tumor progression. It has therefore remained unclear, whether selective BMP9 inhibition is a useful target for antibody therapy of cancer. To shed light on these questions, we characterized BMP9 expression in plasma of patients with different cancer indications and found elevated levels of pro-domains and precursor BMP9 with a strong response in renal cell carcinoma (RCC). These studies prompted us to evaluate the potential of selective anti-BMP9 cancer therapy in RCC. We generated a novel monoclonal therapeutic antibody candidate, mAb BMP9-0093, that selectively targets all different BMP9 variants but does not bind to the closest homolog BMP10. In vitro, mAb BMP9-0093 treatment inhibited signaling, endothelin-1 (ET-1) production and spreading of endothelial cells and restored BMP9-induced decrease in pericyte migration and attachment. Furthermore, BMP9-mediated epithelial-mesenchymal transition of renal cell carcinoma cells was reversed by mAb BMP9-0093 treatment in vitro. In vivo, mAb BMP9-0093 showed significant anti-tumor activity that was associated with an increase in apoptosis as well as a decrease in tumor cell proliferation and ET-1 release. Furthermore, mAb BMP9-0093 induced mural cell coverage of endothelial cells, which was corroborated by a reduction in vascular permeability, demonstrated by a diminished penetration of omalizumab-Alexa 647 into tumor tissue. Our findings provide new evidence for a better understanding of BMP9 contribution in tumor progression and angiogenesis that may result in the development of effective targeted therapeutic interventions.
EVALuna2:15267

Impact of Structured Postoperative Surveillance on Survival in Patients with Resected Pancreatic Adenocarcinoma - Jacobsen, Anne; Flessa, Maarten; Abels, Anna-Lena; Czubayko, Franziska; Mittelstädt, Anke; Krautz, Christian; Weber, Georg; Grützmann, Robert; Brunner, Maximilian (Cancers, 2025)
Background: This study aimed to investigate whether structured surveillance after resection of PDAC has an impact on survival. Methods: 206 patients who underwent PDAC resection at the University Hospital Erlangen between 2005 and 2020 and survived for at least 90 days postoperatively were included in this retrospective study. The impact of surveillance (structured vs. no structured surveillance) respectively of recurrence patterns (recurrence in follow-up vs. symptomatic recurrence) on overall and disease-free survival was investigated. Results: A total of 157 patients (76%) participated in a structured surveillance program after pancreatic resection. During a mean follow-up of 28.5 months, 137 patients (67%) developed recurrence. Patients with structured surveillance showed significantly better outcomes for overall survival after surgery (OSaS: 29.2 months with structured surveillance vs. 16.4 months without, p < 0.001), overall survival after recurrence (OSaR: 10.8 months vs. 3.6 months, p < 0.001), and disease-free survival (DFS: 14.8 months vs. 11.4 months, p = 0.010). In a subgroup analysis of 112 patients with recurrence, survival benefits were observed for those whose recurrence was detected during follow-up compared to those with symptomatic recurrence (OSaS: 24.8 months in the follow-up group vs. 17.2 months in the symptomatic group, p < 0.001; OSaR: 12.6 months vs. 6.5 months, p < 0.001). Conclusion: This study provides evidence that structured surveillance after PDAC resection is beneficial for both overall and disease-free survival. However, randomized studies are needed to confirm the positive impact of structured surveillance programs on survival after pancreatic resection.
CRIS-Team Scopus Importer:2025-05-23
Keywords: follow-up; pancreatic cancer; pancreatic ductal adenocarcinoma; recurrence; surveillance

Implementation of Current ENETS Guidelines for Surgery of Small (2cm) Pancreatic Neuroendocrine Neoplasms in the German Surgical Community: An Analysis of the Prospective DGAV StuDoQ|Pancreas Registry - Mintziras, Ioannis; Keck, Tobias; Werner, Jens; Fichtner-Feigl, Stefan; Wittel, Uwe; Senninger, Norbert; Vowinkel, Thorsten; Koeninger, Joerg; Anthuber, Matthias; Geissler, Bernd; Bartsch, Detlef Klaus; Ghadimi, Michael; et al. (World Journal of Surgery, 2019)
BackgroundENETS guidelines recommend parenchyma-sparing procedures without formal lymphadenectomy, ideally with a minimally invasive laparoscopic approach for sporadic small pNENs (2cm). Non-functioning (NF) small pNENs can also be observed. The aim of the study was to evaluate how these recommendations are implemented in the German surgical community.MethodsData from the prospective StuDoQ|Pancreas registry of the German Society of General and Visceral Surgery were analyzed regarding patient's demographics, tumor characteristics, surgical procedures, histology and perioperative outcomes.ResultsEighty-four (29.2%) of 287 patients had sporadic pNENs 2cm. Forty-three (51.2%) patients were male, and the mean age at diagnosis was 58.815.6years. Twenty-five (29.8%) pNENs were located in the pancreatic head. The diagnosis pNEN was preoperatively established in 53 (65%) of 84 patients. Sixty-two (73.8%) patients had formal pancreatic resections, including partial pancreaticoduodenectomy or total pancreatectomy (21.4%). Only 22 (26.2%) patients underwent parenchyma-sparing resections and 23 (27.4%) patients had minimally invasive procedures. A lymphadenectomy was performed in 63 (75.4%) patients, and lymph node metastases were diagnosed in 6 (7.2%) patients. Eighty-two (97.7%) patients had an R0 resection. Sixty (72%) tumors were classified G1, 24 (28%) tumors G2. Twenty-seven (32.2%) of 84 patients had postoperative relevant Clavien-Dindo grade 3 complications. Thirty- and 90-day mortalities were 2.4% and 3.6%.ConclusionsENETS guidelines for surgery of small pNENs are yet not well accepted in the German surgical community, since the rate of formal resections with standard lymphadenectomy is high and the minimally invasive approach is underused. The attitude to operate small NF tumors seems to be rather aggressive.
CRIS-Team WoS Importer:2020-02-21

Inactivation of autophagy ameliorates glucocorticoid-induced and ovariectomy-induced bone loss - Lin, Neng-Yu; Chen, Chih-Wei; Kagwiria, Rosebeth; Liang, Ruifang; Beyer, Christian; Distler, Alfiya; Luther, Julia; Engelke, Klaus; Schett, Georg; Distler, Jörg (Annals of the Rheumatic Diseases, 2016)
Autophagy has recently been shown to regulate osteoclast activity and osteoclast differentiation. Here, we aim to investigate the impact of autophagy inhibition as a potential therapeutic approach for the treatment of osteoporosis in preclinical models.Systemic bone loss was induced in mice by glucocorticoids and by ovariectomy (OVX). Autophagy was targeted by conditional inactivation of autophagy-related gene 7 (Atg7) and by treatment with chloroquine (CQ). Bone density was evaluated by microCT. The role of autophagy on osteoclastogenesis was analysed by osteoclastogenesis and bone resorption assays. The quantification of receptor activator of nuclear factor ? B ligand and osteoprotegerin proteins in cocultures was performed using ELISA whereas that of osteoclast and osteoblast differentiation markers was by qPCR.Selective deletion of Atg7 in monocytes from Atg7(fl/fl)_x_LysM-Cre mice mitigated glucocorticoid-induced and OVX-induced osteoclast differentiation and bone loss compared with Atg7(fl/fl) littermates. Pharmacological inhibition of autophagy by treatment with CQ suppressed glucocorticoid-induced osteoclastogenesis and protected mice from bone loss. Similarly, inactivation of autophagy shielded mice from OVX-induced bone loss. Inhibition of autophagy led to decreased osteoclast differentiation with lower expression of osteoclast markers such as NFATc1, tartrate-resistant acid phosphatase, OSCAR and cathepsin K and attenuated bone resorption in vitro. In contrast, osteoblast differentiation was not affected by inhibition of autophagy.Pharmacological or genetic inactivation of autophagy ameliorated glucocorticoid-induced and OVX-induced bone loss by inhibiting osteoclastogenesis. These findings may have direct translational implications for the treatment of osteoporosis, since inhibitors of autophagy such as CQ are already in clinical use.
EVALuna2:10103

Incarcerated recurrent inguinal hernia containing an acute appendicitis (Amyand hernia): an extremely rare surgical situation - Velimezis, Georgios; Vassos, Nikolaos; Kapogiannatos, Georgios; Koronakisi, Dimitrios; Perrakis, Evangelos; Perrakis, Aristotelis (Archives of Medical Science, 2017)
EVALuna2:15317

Increased expression of guanylate binding protein-1 in lesional skin of patients with cutaneous lupus erythematosus - Naschberger, Elisabeth; Wenzel, Joerg; Kretz, Cosima C.; Herrmann, Martin; Stürzl, Michael; Kuhn, Annegret (Experimental Dermatology, 2011)
The large GTPase human guanylate binding protein-1 (GBP-1) is a key mediator of angiostatic effects of inflammation and is induced by interferon (IFN)-α and IFN-γ in endothelial cells (ECs). The aim of this study was to investigate whether GBP-1 is a marker of skin lesions in patients with cutaneous lupus erythematosus (CLE). Western blotting revealed that GBP-1 was in vitro induced by IFN-α and -γ in primary keratinocytes obtained from healthy controls. Moreover, we found that this protein was expressed by keratinocytes and ECs in primary and ultraviolet (UV)-induced skin lesions from patients with various subtypes of CLE, when compared to non-lesional skin. No GBP-1 expression was noted in skin biopsy specimens 24 or 72h after UV irradiation prior to lesion formation in patients with CLE or in healthy control specimens with or without UV irradiation. Initial findings suggest that GBP-1 is not expressed in other skin diseases with different inflammatory aetiology, such as atopic dermatitis. We conclude that GBP-1 expression is closely associated with skin lesions in patients with CLE, suggesting a contribution of GBP-1 in the pathogenesis of this disease. © 2011 John Wiley & Sons A/S.
Created from Fastlane, Scopus look-up
Keywords: Guanylate binding protein; Inflammation; Interferon; Lupus erythematosus; Skin; UV light

Independent Validation and Assay Standardization of Improved Metabolic Biomarker Signature to Differentiate Pancreatic Ductal Adenocarcinoma From Chronic Pancreatitis - Mahajan, Ujjwal M.; Oehrle, Bettina; Sirtl, Simon; Alnatsha, Ahmed; Goni, Elisabetta; Regel, Ivonne; Beyer, Georg; Vornhülz, Marlies; Vielhauer, Jakob; Chromik, Ansgar; Bahra, Markus; Klein, Fritz; et al. (Gastroenterology, 2022)
Background & Aims: Pancreatic ductal adenocarcinoma cancer (PDAC) is a highly lethal malignancy requiring efficient detection when the primary tumor is still resectable. We previously developed the MxPancreasScore comprising 9 analytes and serum carbohydrate antigen 19-9 (CA19-9), achieving an accuracy of 90.6%. The necessity for 5 different analytical platforms and multiple analytical runs, however, hindered clinical applicability. We therefore aimed to develop a simpler single-analytical run, single-platform diagnostic signature. Methods: We evaluated 941 patients (PDAC, 356; chronic pancreatitis [CP], 304; nonpancreatic disease, 281) in 3 multicenter independent tests, and identification (ID) and validation cohort 1 (VD1) and 2 (VD2) were evaluated. Targeted quantitative plasma metabolite analysis was performed on a liquid chromatography–tandem mass spectrometry platform. A machine learning–aided algorithm identified an improved (i-Metabolic) and minimalistic metabolic (m-Metabolic) signatures, and compared them for performance. Results: The i-Metabolic Signature, (12 analytes plus CA19-9) distinguished PDAC from CP with area under the curve (95% confidence interval) of 97.2% (97.1%-97.3%), 93.5% (93.4%-93.7%), and 92.2% (92.1%-92.3%) in the ID, VD1, and VD2 cohorts, respectively. In the VD2 cohort, the m-Metabolic signature (4 analytes plus CA19-9) discriminated PDAC from CP with a sensitivity of 77.3% and specificity of 89.6%, with an overall accuracy of 82.4%. For the subset of 45 patients with PDAC with resectable stages IA-IIB tumors, the sensitivity, specificity, and accuracy were 73.2%, 89.6%, and 82.7%, respectively; for those with detectable CA19-9 >2 U/mL, 81.6%, 88.7%, and 84.5%, respectively; and for those with CA19-9 <37 U/mL, 39.7%, 94.1%, and 76.3%, respectively. Conclusions: The single-platform, single-run, m-Metabolic signature of just 4 metabolites used in combination with serum CA19-9 levels is an innovative accurate diagnostic tool for PDAC at the time of clinical presentation, warranting further large-scale evaluation.
CRIS-Team Scopus Importer:2022-11-04
Keywords: CA19-9; Chronic Pancreatitis; Diagnostic Signature; Metabolic Signature; Pancreatic Cancer

Indications for resection and perioperative outcomes of surgery for pancreatic neuroendocrine neoplasms in Germany: an analysis of the prospective DGAV StuDoQ vertical bar Pancreas registry - Mintziras, Ioannis; Keck, Tobias; Werner, Jens; Fichtner-Feigl, Stefan; Wittel, Uwe; Senninger, Norbert; Vowinkel, Thorsten; Koeninger, Joerg; Anthuber, Matthias; Geissler, Bernd; Bartsch, Detlef Klaus; Ghadimi, Michael; et al. (Surgery Today, 2019)
Purpose Pancreatic neuroendocrine neoplasms (pNENs) are rare, and their surgical management is complex. This study evaluated the current practice of pNEN surgery across Germany, including its adherence with guidelines and its perioperative outcomes.
CRIS-Team WoS Importer:2020-02-14

Indications for the surgical management of pancreatic neoplasms - Brunner, Maximilian; Belyaev, Orlin; Boesch, Florian; Keck, Tobias; Witzigmann, Helmut; Grützmann, Robert; Uhl, Waldemar; Werner, Jens (Zeitschrift für Gastroenterologie, 2021)
Due to its rising incidence, pancreatic neoplasia, which mainly include adenocarcinomas, neuroendocrine and cystic neoplasia of the pancreas, is becoming increasingly relevant in everyday clinical practice.
CRIS-Team WoS Importer:2021-12-10

Indikationen zur chirurgischen und interventionellen Behandlung der akuten Pankreatitis - Radulova-Mauersberger, Olga; Belyaev, Orlin; Birgin, Emrullah; Bösch, Florian; Brunner, Maximilian; Müller-Debus, Charlotte Friederieke; Wellner, Ulrich Friedrich; Grützmann, Robert; Keck, Tobias; Werner, Jens; Uhl, Waldemar; Witzigmann, Helmut (Zentralblatt für Chirurgie, 2020)
BACKGROUND: 15 to 20% of patients with acute pancreatitis develop necrosis of the pancreatic parenchyma or extrapancreatic tissue. The disease is associated with a mortality rate of up to 20%. The mainstays of treatment consist of intensive medical care and surgical and interventional therapy. METHODS: A systematic literature search focused on indications for surgical and interventional therapy of necrotising pancreatitis. 85 articles were analysed for this review. By using the Delphi method, the results were presented to the quality committee for pancreas diseases of the German Society for General and Visceral Surgery and to expert pancreatologists in an interactive conference using plenary voting during the visceral medicine congress 2019 in Wiesbaden. For the finalised recommendations, an agreement of 84% of participants was achieved. RESULTS: Documented or clinical suspicion of infected, necrotising pancreatitis are indications for surgical and interventional therapy (recommendation grade: strong; evidence grade; low). Sterile necrosis is a less common indication for intervention due to late complications or persistent severe pancreatitis. Invasive interventions should be delayed when possible until four weeks after onset of pancreatitis. Optimal treatment strategy consists of a "step-up approach" (evidence grade: high; recommendation grade: strong). The first step is catheter drainage, followed, if necessary, by minimally invasive surgical or interventional necrosectomy. If minimally invasive techniques do not result in clinical improvement, open necrosectomy is necessary. 35 to 50% of patients are successfully treated with drainage alone. Indications for emergency intervention are bowel perforation, bowel ischemia and bleeding. Surgical decompression of abdominal compartment syndrome is indicated if the patient is refractory to medical treatment and percutaneous drainage. Abscesses and symptomatic pseudocysts are indications for interventional drainage. Early cholecystectomy during index admission is recommended for patients with mild biliary pancreatitis. Cholecystectomy should be delayed after severe, biliary pancreatitis. CONCLUSION: The recommendations for surgical an interventional therapy of necrotising pancreatitis address the basis of current indications in literature. They should serve in daily practice as a reference standard for decision making in multidisciplinary teams.
CRIS-Team Scopus Importer:2020-06-30

Induction of apoptosis in circulating angiogenic cells by microparticles. - Distler, Jörg; Akhmetshina, Alfiya; Dees, Clara; Juengel, Astrid; Stürzl, Michael; Gay, Steffen; Pisetsky, David S.; Schett, Georg; Distler, Oliver (Arthritis & Rheumatism-Arthritis Care & Research, 2011)
Systemic sclerosis (SSc) is an autoimmune disease marked by aberrant activation and apoptosis of endothelial cells (ECs) and decreased numbers of circulating angiogenic cells (CACs). The aim of this study was to analyze whether microparticles might link pathologic activation and apoptosis of ECs with reduced numbers of CACs. Apoptosis was quantified by staining for annexin V and measurement of caspase 3 activity. The uptake of microparticles by CACs was determined by fluorescence-activated cell sorting and by fluorescence microscopy. Tritiated arachidonic acid and phosphatidylinositol 3,5-bisphosphate were used to demonstrate the transfer of arachidonic acid and highlight the role of the acid sphingomyelinase in microparticle-induced apoptosis of endothelial progenitor cells. Microparticles derived from activated or apoptotic ECs, the expression of which is strongly increased in the blood of patients with SSc, induce apoptosis in CACs in a dose-dependent manner. Microparticles, which are rich in arachidonic acid, are phagocytosed by CACs. Inhibition of phagocytosis prevents the induction of apoptosis in CACs by microparticles. Microparticles can transport arachidonic acid from ECs to CACs, and purified arachidonic acid mimics the proapoptotic effects of microparticles. Arachidonic acid activates the acid sphingomyelinase, and inhibition of acid sphingomyelinase prevents microparticle-induced apoptosis of CACs. Thus, phagocytosis of microparticles might stimulate the activity of acid sphingomyelinase and activate the apoptotic machinery. The induction of apoptosis in CACs by microparticles derived from ECs provides a novel link between aberrant activation or apoptosis of ECs, decreased numbers of CACs, and impaired formation of new vessels in SSc. OBJECTIVE METHODS RESULTS CONCLUSION

Infection with human immunodeficiency virus-1 increases expression of vascular endothelial cell growth factor in T cells: implications for acquired immunodeficiency syndrome-associated vasculopathy. - Ascherl, Gudrun; Hohenadl, Christine; Schatz, Octavian; Shumay, Elena; Bogner, J.; Tschachler, Erwin; Monini, Paolo; Ensoli, Barbara; Stürzl, Michael; et al. (Blood, 1999)
Alterations in the vascular system and the onset of angioproliferative lesions such as Kaposi's sarcoma (KS) are common traits of human immunodeficiency virus-1 (HIV-1)-infected patients. To investigate possible factors involved in acquired immunodeficiency syndrome (AIDS)-associated vasculopathy and vascular malfunction, expression of vascular endothelial cell growth factor-A (VEGF-A) was analyzed in HUT 78 T lymphocytes upon infection with HIV-1. VEGF-A was found to be increased in supernatants from infected cells as compared with uninfected cells. In addition, VEGF-A mRNA expression and protein secretion were significantly increased in HUT 78 cells incubated with conditioned medium (CM) derived from HIV-1 chronically infected HUT 78 cells (HIV-TCM) as compared with CM from uninfected cells (TCM). Increase of VEGF-A production in T cells was promoted by inflammatory cytokines (IC) present in HIV-TCM, including tumor necrosis factor alpha (TNFalpha), interferon gamma (IFNgamma), interleukin-1beta (IL-1beta), and IL-6. These IC that have been shown to be increased in sera of HIV-1-infected patients and to be increased by HIV-1 infection or cell activation in these individuals as well as HIV-TCM also increased VEGF-A expression in primary T lymphocytes. Consistent with this, VEGF-A concentrations were found to be higher in sera of HIV-1-infected patients with (mean, 357.1 +/- 197.9 pg/mL) and without KS (mean, 256.7 +/- 137.5 pg/mL) as compared with uninfected individuals (mean, 188.6 +/- 91.7 pg/mL). These data suggest that increased secretion of VEGF-A by T lymphocytes of HIV-1-infected individuals may induce vascular leakage and stimulate proliferation of vascular endothelial cells, which are hallmarks of AIDS-associated vasculopathy and especially of KS development.

Inflammatory cytokines synergize with the HIV-1 Tat protein to promote angiogenesis and Kaposi's sarcoma via induction of basic fibroblast growth factor and the alpha v beta 3 integrin. - Barillari, Giovanni; Sgadari, Cecilia; Palladino, Clelia; Gendelman, R; Caputo, Antonella; Morris, C B; Nair, B. C.; Markham, P; Nel, A; Stürzl, Michael; Ensoli, Barbara (Journal of Immunology, 1999)
The Tat protein of HIV-1, a transactivator of viral gene expression, is released by acutely infected T cells and, in this form, exerts angiogenic activities. These have linked the protein to the pathogenesis of Kaposi's sarcoma (KS), a vascular tumor frequent and aggressive in HIV-1-infected individuals (AIDS-KS). In this study, we show that a combination of the same inflammatory cytokines increased in KS lesions, namely IL-1 beta, TNF-alpha, and IFN-gamma, synergizes with Tat to promote in nude mice the development of angioproliferative KS-like lesions that are not observed with each factor alone. Inflammatory cytokines induce the tissue expression of both basic fibroblast growth factor (bFGF) and vascular endothelial growth factor (VEGF), two angiogenic molecules highly produced in primary KS lesions. However, bFGF, but not VEGF, synergizes with Tat in vivo and induces endothelial cells to migrate, to adhere, and to grow in response to Tat in vitro. Tat angiogenic effects correlate with the expression of the alpha v beta 3 integrin that is induced by bFGF and binds the arginine-glycine-aspartic acid (RGD) region of Tat. In contrast, no correlation is observed with the expression of alpha v beta 5, which is promoted by VEGF and binds Tat basic region. Finally, KS lesion formation induced by bFGF and Tat in nude mice is blocked by antagonists of RGD-binding integrins. Because alpha v beta 3 is an RGD-binding integrin that is highly expressed in primary KS lesions, where it colocalizes with extracellular Tat on vessels and spindle cells, these results suggest that alpha v beta 3 competitors may represent a new strategy for the treatment of AIDS-KS.

Influence of body mass index on long-term outcome in patients with rectal cancer-a single centre experience - Kalb, Maximilian; Langheinrich, Melanie C.; Merkel, Susanne; Krautz, Christian; Brunner, Maximilian; Bénard, Alan; Weber, Klaus; Pilarsky, Christian; Grützmann, Robert; Weber, Georg (Cancers, 2019)
Background: Excess bodyweight is known to influence the risk of colorectal cancer; however, little evidence exists for the influence of the body mass index (BMI) on the long-term outcome of patients with rectal cancer. Methods: We assessed the impact of the BMI on the risk of local recurrence, distant metastasis and overall-survival in 612 patients between 2003 and 2010 after rectal cancer diagnosis and treatment at the University Hospital Erlangen. A Cox-regression model was used to estimate the hazard ratio and multivariate risk of mortality and distant-metastasis. Median follow up-time was 58 months. Results: Patients with obesity class II or higher (BMI ≥ 35 kg/m2, n = 25) and patients with underweight (BMI < 18.5 kg/m2, n = 5) had reduced overall survival (hazard ratio (HR) = 1.6; 95% confidence interval (CI) 0.9-2.7) as well as higher rates of distant metastases (hazard ratio HR = 1.7; 95% CI 0.9-3.3) as compared to patients with normal bodyweight (18.5 ≤ BMI < 25 kg/m2, n = 209), overweight (25 ≤ BMI <30 kg/m2, n = 257) or obesity class I (30 ≤ BMI >35 kg/m2, n = 102). There were no significant differences for local recurrence. Conclusions: Underweight and excess bodyweight are associated with lower overall survival and higher rates of distant metastasis in patients with rectal cancer.
CRIS-Team Scopus Importer:2019-06-21
Keywords: Body mass index; Distant metastasis; Overall survival; Rectal cancer

Influence of interrupted versus continuous suture technique on intestinal anastomotic leakage rate in patients with Crohn’s disease — a propensity score matched analysis - Mittelstädt, Anke; von Löffelholz, Tobias; Weber, Klaus; Denz, Axel; Krautz, Christian; Grützmann, Robert; Weber, Georg; Brunner, Maximilian (International Journal of Colorectal Disease, 2022)
Purpose: Intestinal anastomosis is a crucial step in most intestinal resections, as anastomotic leakage is often associated with severe consequences for affected patients. There are especially two different techniques for hand-sewn intestinal anastomosis: the interrupted suture technique (IST) and the continuous suture technique (CST). This study investigated whether one of these two suture techniques is associated with a lower rate of anastomotic leakage. Methods: A retrospective review of 332 patients with Crohn’s disease who received at least one hand-sewn colonic anastomosis at our institution from 2010 to 2020 was performed. Using propensity score matching 183 patients with IST were compared to 96 patients with CST in regard to the impact of the anastomotic technique on patient outcomes. Results: Overall anastomotic leakage rate was 5%. Leakage rate did not differ between the suture technique groups (IST: 6% vs. CST: 3%, p = 0.393). Multivariate analysis revealed the ASA score as only independent risk factor for anastomotic leakage (OR 5.3 (95% CI = 1.2–23.2), p = 0.026). Suture technique also showed no significant influence on morbidity and the re-surgery rate in multivariate analysis. Conclusion: Our data suggest that the chosen suture technique (interrupted vs. continuous) has no influence on postoperative outcome, especially on anastomotic leakage rate. This finding should be confirmed by a randomized controlled trial.
CRIS-Team Scopus Importer:2022-10-21
Keywords: Anastomotic leakage; Continuous suture technique; Crohn’s disease; Interrupted suture technique; Intestinal anastomosis

Inhibition of cGAS DNA Sensing by a Herpesvirus Virion Protein - Wu, Jian-Jun; Li, Wenwei; Shao, Yaming; Avey, Denis; Fu, Bishi; Gillen, Joseph; Hand, Travis; Ma, Siming; Liu, Xia; Miley, Wendell; Konrad, Andreas; Neipel, Frank; et al. (Cell Host & Microbe, 2015)
Invading viral DNA can be recognized by the host cytosolic DNA sensor, cyclic GMP-AMP (cGAMP) synthase (cGAS), resulting in production of the second messenger cGAMP, which directs the adaptor protein STING to stimulate production of type I interferons (IFNs). Although several DNA viruses are sensed by cGAS, viral strategies targeting cGAS are virtually unknown. We report here that Kaposi's sarcoma-associated herpesvirus (KSHV) ORF52, an abundant gammaherpesvirus-specific tegument protein, subverts cytosolic DNA sensing by directly inhibiting cGAS enzymatic activity through a mechanism involving both cGAS binding and DNA binding. Moreover, ORF52 homologs in other gammaherpesviruses also inhibit cGAS activity and similarly bind cGAS and DNA, suggesting conserved inhibitory mechanisms. Furthermore, KSHV infection evokes cGAS-dependent responses that can limit the infection, and an ORF52 null mutant exhibits increased cGAS signaling. Our findings reveal a mechanism through which gammaherpesviruses antagonize host cGAS DNA sensing.
EVALuna2:8258

Inhibition of Hedgehog Acyltransferase Alleviates the Profibrotic Effects of Transforming Growth Factor beta in Systemic Sclerosis - Liang, Ruifang; Kagwiria, Rosebeth; Dees, Clara; Zhang, Yun; Distler, Oliver; Schett, Georg; Distler, Jörg (2017)
EVALuna2:33436

Inhibition of integrin αvβ6 sparks T-cell antitumor response and enhances immune checkpoint blockade therapy in colorectal cancer - Busenhart, Philipp; Montalban-Arques, Ana; Katkeviciute, Egle; Morsy, Yasser; Van Passen, Chiara; Hering, Larissa; Atrott, Kirstin; Lang, Silvia; Garzon, Jesus Francisco Glaus; Naschberger, Elisabeth; Hartmann, Arndt; Rogler, Gerhard; et al. (Journal for ImmunoTherapy of Cancer, 2022)
Background Integrin αvβ6 is a heterodimeric cell surface protein whose cellular expression is determined by the availability of the integrin β6 subunit (ITGB6). It is expressed at very low levels in most organs during tissue homeostasis but shows highly upregulated expression during the process of tumorigenesis in many cancers of epithelial origin. Notably, enhanced expression of integrin αvβ6 is associated with aggressive disease and poor prognosis in numerous carcinoma entities. Integrin αvβ6 is one of the major physiological activators of transforming growth factor-β (TGF-β), which has been shown to inhibit the antitumor T-cell response and cause resistance to immunotherapy in mouse models of colorectal and mammary cancer. In this study, we investigated the effect of ITGB6 expression and antibody-mediated integrin αvβ6 inhibition on the tumor immune response in colorectal cancer. Methods Using orthotopic and heterotopic tumor cell injection, we assessed the effect of ITGB6 on tumor growth and tumor immune response in wild type mice, mice with defective TGF-β signaling, and mice treated with anti-integrin αvβ6 antibodies. To examine the effect of ITGB6 in human colorectal cancer, we analyzed RNAseq data from the colon adenocarcinoma dataset of The Cancer Genome Atlas (TCGA-COAD). Results We demonstrate that expression of ITGB6 is an immune evasion strategy in colorectal cancer, causing inhibition of the antitumor immune response and resistance to immune checkpoint blockade therapy by activating latent TGF-β. Antibody-mediated inhibition of integrin αvβ6 sparked a potent cytotoxic T-cell response and overcame resistance to programmed cell death protein 1 (PD-1) blockade therapy in ITGB6 expressing tumors, provoking a drastic increase in anti-PD-1 treatment efficacy. Further, we show that the majority of tumors in patients with colorectal cancer express sufficient ITGB6 to provoke inhibition of the cytotoxic T-cell response, indicating that most patients could benefit from integrin αvβ6 blockade therapy. Conclusions These findings propose inhibition of integrin αvβ6 as a promising new therapy for colorectal cancer, which blocks tumor-promoting TGF-β activation, prevents tumor exclusion of cytotoxic T-cells and enhances the efficacy of immune checkpoint blockade therapy.
CRIS-Team Scopus Importer:2022-02-25
Keywords: CD8-positive T-lymphocytes; cytotoxicity; drug evaluation; immunologic; immunotherapy; preclinical; tumor microenvironment

Inhibition of phosphodiesterase 4 (PDE4) reduces dermal fibrosis by interfering with the release of interleukin-6 from M2 macrophages - Maier, Christiane; Bergmann, Christina; Weinkam, Rita; Kittan, Nicolai; Schett, Georg; Distler, Jörg; Beyer, Christian; Ramming, Andreas (Annals of the Rheumatic Diseases, 2017)
To investigate the disease-modifying effects of phosphodiesterase 4 (PDE4) inhibition in preclinical models of systemic sclerosis (SSc).We studied the effects of PDE4 inhibition in a prevention and a treatment model of bleomycin-induced skin fibrosis, in the topoisomerase mouse model as well as in a model of sclerodermatous chronic graft-versus-host disease. To better understand the mode of action of PDE4 blockade in preclinical models of SSc, we investigated fibrosis-relevant mediators in fibroblasts and macrophages from healthy individuals and patients suffering from diffuse-cutaneous SSc on blockade of PDE4.Specific inhibition of PDE4 by rolipram and apremilast had potent antifibrotic effects in bleomycin-induced skin fibrosis models, in the topoisomerase I mouse model and in murine sclerodermatous chronic graft-versus-host disease. Fibroblasts were not the direct targets of the antifibrotic effects of PDE4 blockade. Reduced leucocyte infiltration in lesional skin on PDE4 blockade suggested an immune-mediated mechanism. Further analysis revealed that PDE4 inhibition decreased the differentiation of M2 macrophages and the release of several profibrotic cytokines, resulting in reduced fibroblast activation and collagen release. Within these profibrotic mediators, interleukin-6 appeared to play a central role.PDE4 inhibition reduces inflammatory cell activity and the release of profibrotic cytokines from M2 macrophages, leading to decreased fibroblast activation and collagen release. Importantly, apremilast is already approved for the treatment of psoriasis and psoriatic arthritis. Therefore, PDE4 inhibitors might be further developed as potential antifibrotic therapies for patients with SSc. Our findings suggest that particularly patients with inflammation-driven fibrosis might benefit from PDE4 blockade.
EVALuna2:13394

In-hospital mortality and failure to rescue following hepatobiliary surgery in Germany - a nationwide analysis - Krautz, Christian; Gall, Christine; Gefeller, Olaf; Nimptsch, Ulrike; Mansky, Thomas; Brunner, Maximilian; Grützmann, Robert; Kersting, Stephan; Weber, Georg (BMC Surgery, 2020)
BACKGROUND: Recent observational studies on volume-outcome associations in hepatobiliary surgery were not designed to account for the varying extent of hepatobiliary resections and the consequential risk of perioperative morbidity and mortality. Therefore, this study aimed to determine the risk-adjusted in-hospital mortality for minor and major hepatobiliary resections at the national level in Germany and to examine the effect of hospital volume on in-hospital mortality, and failure to rescue. METHODS: All inpatient cases of hepatobiliary surgery (n = 31,114) in Germany from 2009 to 2015 were studied using national hospital discharge data. After ranking hospitals according to increasing hospital volumes, five volume categories were established based on all hepatobiliary resections. The association between hospital volume and in-hospital mortality following minor and major hepatobiliary resections was evaluated by multivariable regression methods. RESULTS: Minor hepatobiliary resections were associated with an overall mortality rate of 3.9% and showed no significant volume-outcome associations. In contrast, overall mortality rate of major hepatobiliary resections was 10.3%. In this cohort, risk-adjusted in-hospital mortality following major resections varied widely across hospital volume categories, from 11.4% (95% CI 10.4-12.5) in very low volume hospitals to 7.4% (95% CI 6.6-8.2) in very high volume hospitals (risk-adjusted OR 0.59, 95% CI 0.41-0.54). Moreover, rates of failure to rescue decreased from 29.38% (95% CI 26.7-32.2) in very low volume hospitals to 21.38% (95% CI 19.2-23.8) in very high volume hospitals. CONCLUSIONS: In Germany, patients who are undergoing major hepatobiliary resections have improved outcomes, if they are admitted to higher volume hospitals. However, such associations are not evident following minor hepatobiliary resections. Following major hepatobiliary resections, 70-80% of the excess mortality in very low volume hospitals was estimated to be attributable to failure to rescue.
CRIS-Team Scopus Importer:2020-08-07

Initiating a Robotic Program for Abdominal Surgery - Experiences from a Centre in Germany - Brunner, Maximilian; Matzel, Klaus; Aladashvili, Archil; Krautz, Christian; Grützmann, Robert; Croner, Roland (Zentralblatt für Chirurgie, 2018)
PURPOSE: Robotic systems are becoming increasingly important in abdominal surgery. We describe the implementation of a robotic program at a German centre for abdominal surgery, with focus on feasibility, safety, patient selection, learning curves, financial aspects and the lessons learned. METHODS: This retrospective analysis covered data on patient demographics, intra- and postoperative parameters, oncological results and costs of all robotic-assisted abdominal operations performed at our institution between August 2012 to December 2016. It was also evaluated how possible factors for preoperative patient selection might influence intra- or postoperative outcome and learning parameters. RESULTS: 81 operations were performed - mostly colorectal resections (n = 35), ventral mesh rectopexy (n = 23) and liver resections (n = 18). The conversion rate was 7%. All oncological patients underwent R0 resection. Mean postoperative hospitalisation was 8.8 days; mean morbidity was 24%, with major complications (Clavien-Dindo > II) in 7%; mortality was 0%. BMI above 33.5 kg/m2 was associated with significantly higher morbidity (p = 0.024) and rate of major complications (p = 0.046), as well as a significantly longer hospitalisation (p = 0.009). Patients older than 65 years had significantly higher morbidity (p = 0.025). With increasing numbers of operations, time of surgery decreased (p = 0.001). The average cost of a robot-assisted operation, including hospital stay, was 15,221 €. The costs of robotic sigmoid resections or liver resections were higher (compared to the open approach: 106.8 and 62.8% higher, respectively, compared to the laparoscopic approach 93.5 and 66.5% higher, respectively). CONCLUSIONS: Robotic surgery is a safe approach. A crucial factor in the successful and safe performance of robotic assisted operations is proper patient selection, especially during the implementation period. The inevitable learning curve and the higher costs compared to open and laparocopic surgery must be respected and specialisation of the whole team is necessary.
EVALuna2:34496

Innate PD-L1 limits T cell-mediated adipose tissue inflammation and ameliorates diet-induced obesity - Schwartz, Christian; Schmidt, Viviane; Deinzer, Andrea; Hawerkamp, H. C.; Hams, E.; Bayerlein, Jasmin; Roeger, O.; Bailer, Moritz; Krautz, Christian; El Gendy, Amr; Elshafei, Moustafa; Heneghan, H. M.; et al. (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

Innate PD-L1 limits T cell mediated adipose tissue inflammation - Schwartz, Christian; Schmidt, Viviane; Deinzer, Andrea; Hawerkamp, Heike C.; Hams, Emily; Bayerlein, Jasmin; Roeger, Ole; Bailer, Moritz; Krautz, Christian; El Gendy, Amr; Elshafei, Moustafa; Hogan, Andrew E.; et al. (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
Obesity has become a major health problem in the industrialized world. Immune regulation plays an important role in adipose tissue homeostasis; however, the initial events that shift the balance from a noninflammatory homeostatic environment toward inflammation leading to obesity are poorly understood. Here, we report a role for the costimulatory molecule programmed death-ligand 1 (PD-L1) in the limitation of diet-induced obesity. Functional ablation of PD-L1 on dendritic cells (DCs) using conditional knockout mice increased weight gain and metabolic syndrome during diet-induced obesity, whereas PD-L1 expression on type 2 innate lymphoid cells (ILC2s), T cells, and macrophages was dispensable for obesity control. Using in vitro cocultures, DCs interacted with T cells and ILC2s via the PD-L1:PD-1 axis to inhibit T helper type 1 proliferation and promote type 2 polarization, respectively. A role for PD-L1 in adipose tissue regulation was also shown in humans, with a positive correlation between PD-L1 expression in visceral fat of people with obesity and elevated body weight. Thus, we define a mechanism of adipose tissue homeostasis controlled by the expression of PD-L1 by DCs, which may be a clinically relevant finding with regard to immune-related adverse events during immune checkpoint inhibitor therapy.<br
CRIS-Team WoS Importer:2022-03-11

In Reply - Raptis, Dimitrios; Schneider, Ignaz Hans Friedrich; Matzel, Klaus E.; Hohenberger, Werner; Ott, Oliver; Fietkau, Rainer (Deutsches Ärzteblatt international, 2015)
EVALuna2:15209

In silico analysis of the transportome in human pancreatic ductal adenocarcinoma - Zaccagnino, A.; Pilarsky, Christian; Tawfik, D.; Sebens, Susanne; Trauzold, A.; Novak, Ivana; Schwab, A.; Kalthoff, H. (European Biophysics Journal, 2016)
The altered expression and/or activity of ion channels and transporters (transportome) have been associated with malignant behavior of cancer cells and were proposed to be a hallmark of cancer. However, the impact of altered transportome in epithelial cancers, such as pancreatic ductal adenocarcinoma (PDAC), as well as its pathophysiological consequences, still remains unclear. Here, we report the in silico analysis of 840 transportome genes in PDAC patients' tissues. Our study was focused on the transportome changes and their correlation with functional and behavioral responses in PDAC tumor and stromal compartments. The dysregulated gene expression datasets were filtered using a cut-off of fold-change values <=-2 or >=2 (adjusted p value <=0.05). The dysregulated transportome genes were clearly associated with impaired physiological secretory mechanisms and/or pH regulation, control of cell volume, and cell polarity. Additionally, some down-regulated transportome genes were found to be closely linked to epithelial cell differentiation. Furthermore, the observed decrease in genes coding for calcium and chloride transport might be a mechanism for evasion of apoptosis. In conclusion, the current work provides a comprehensive overview of the altered transportome expression and its association with predicted PDAC malignancy with special focus on the epithelial compartment.
EVALuna2:15285

Interdisciplinary Surgical Approaches in Vaginal and Perineal Reconstruction of Advanced Rectal and Anal Female Cancer Patients - Horch, Raymund E.; Ludolph, Ingo; Weber, Klaus; Grützmann, Robert; Arkudas, Andreas; Cai, Aijia (Frontiers in Oncology, 2020)
Relapsing or far advanced rectal and anal cancers remain difficult to treat and require interdisciplinary approaches. Due to modern standard protocols all patients receive irradiation and neoadjuvant chemotherapy—and in case of a relapse a second irradiation—rendering the surgical site prone to surgical site infections and oftentimes long lasting sinus and septic complications after exenteration in the pelvis. Despite an improved overall survival rate in these patients the downside of radical tumor surgery in the pelvis is a major loss of quality of life, especially in women when parts of the vagina need to be resected. Derived from our experince with over 300 patients receiving pelvic and perineal reconstruciton with a transpelvic vertical rectus abdominis myocutaneous (tpVRAM) flap we studied the impact of this surgical technique on the outcomes of female patients with or without vaginal reconstruction following pelvic exenteration. We found out that the tpVRAM flap is reliably perfused and helps to reduce long term wound healing desasters in the irradiated perineal/vaginal/gluteal region.
CRIS-Team Scopus Importer:2020-06-02
Keywords: anal cancer; rectal cancer; transpelvic vertical rectus abdominis myocutaneous flap; vaginal reconstruction; VRAM

Interesting image. Tc-99m sestamibi SPECT/CT as a new tool for monitoring perfusion and viability of buried perforator based free flaps in breast reconstruction after breast cancer. - Dragu, Adrian; Linke, Rainer; Kuwert, Torsten; Unglaub, Frank; Kneser, Ulrich; Stürzl, Michael; Horch, Raymund E.; Bach, Alexander D. (Clinical Nuclear Medicine, 2010)

Interferon-alpha prevents apoptosis of endothelial cells after short-term exposure but induces replicative senescence after continuous stimulation. - Pammer, Johannes; Reinisch, Christine; Birner, Peter; Pogoda, Kristin; Stürzl, Michael; Tschachler, Erwin (Laboratory Investigation, 2006)
Although the antiangiogenic activity of type I interferons (IFN) is well known, the mechanism by which it occurs is unclear. In the present study, we have investigated effects of short-term and long-term IFN-alpha exposure on different types of endothelial cells (EC). Short-term IFN-alpha treatment resulted in a distinct reduction of apoptosis of serum and growth factor starved HUVEC and HDMEC. This was accompanied by a strong upregulation of the IFN inducible guanylate binding protein-1 (GBP-1) whereas no consistent regulation of several known antiapoptotic proteins was evident. Stable transfection of HUVEC with an expression vector for GBP-1 mimicked the protective effect of IFN-alpha, suggesting that GBP-1 may contribute to the inhibition of apoptosis. When IFN-alpha, together with serum and EC growth factors, was present continuously a decrease of population doublings by more than 40% was observed in both HDMEC and HCAEC. In addition, the cells displayed a senescent phenotype significantly earlier than control cells and showed an increased adherence for monocytes. Our findings suggest that the antiangiogenic effect of IFN-alpha is mediated by inducing EC senescence rather than EC apoptosis. Furthermore IFN-alpha released in chronic inflammatory conditions might contribute via its prosenescent activity to the pathogenesis of atherosclerosis.

Interferon Gamma Counteracts the Angiogenic Switch and Induces Vascular Permeability in Dextran Sulfate Sodium Colitis in Mice - Haep, Lisa; Britzen-Laurent, Nathalie; Weber, Thomas G.; Naschberger, Elisabeth; Schäfer, Amrei; Kremmer, Elisabeth; Försch, Sebastian; Scheuer, Werner; Wirtz, Stefan; Waldner, Maximilian; Stürzl, Michael; Vieth, Michael (Inflammatory Bowel Diseases, 2015)
Interferon (IFN)-? is a central pathogenesis factor in inflammatory bowel disease (IBD) with pleiotropic effects on many different cell types. However, as yet, the immune modulatory functions of IFN-? in IBD have been predominantly investigated. Based on previous studies showing that IFN-? acts antiangiogenic in colorectal carcinoma, we investigated the effects of IFN-? on the vascular system in IBD.Colon tissues of patients with IBD and dextran sulfate sodium-induced colitis in mice were subjected to immunohistochemistry, quantitative real-time polymerase chain reactions, and in situ hybridization to quantify cell activation, angiogenesis, and immune responses. Vascular structure and permeability in mice were analyzed by ultramicroscopy and in vivo confocal laser endomicroscopy.We showed a significantly increased blood vessel density in IBD and dextran sulfate sodium colitis. In mice, this was associated with a disorganized blood vessel structure and profound vascular leakage. As compared with genes associated with angiogenesis, genes associated with inflammatory cell activation including IFN-? were more strongly upregulated in colitis tissues. IFN-? exerted direct effects on endothelial cells in IBD tissues in vivo, as indicated by the expression of IFN-?-induced guanylate binding protein 1 (GBP-1). Neutralization of IFN-? in the acute dextran sulfate sodium colitis model demonstrated that this cytokine exerts endogenous angiostatic activity in IBD and contributes to increased vascular permeability.The dissection of the pleiotropic activities of IFN-? in IBD provides new insights to the pathological functions of this cytokine and may be of high relevance for the optimization of combination therapy approaches.
EVALuna2:1969

Interferon-gamma triggers an anti-tumorigenic chain reaction in the tumor vessels of colorectal carcinoma - Stürzl, Michael; Langer, Victoria; Regensburger, Daniela; Tenkerian, Clara; Klingler, Annika; Waldner, Maximilian; Becker, Christoph; Meniel, Valerie; Grützmann, Robert; Geppert, Carol-Immanuel; Britzen-Laurent, Nathalie; Naschberger, Elisabeth (CANCER RESEARCH, 2018)
CRIS-Team WoS Importer:2019-06-18

Interferon-α counteracts the angiogenic switch and reduces tumor cell proliferation in a spontaneous model of prostatic cancer - Persano, Luca; Moserle, Lidia; Esposito, Giovanni; Bronte, Vincenzo; Barbieri, Vito; Iafrate, Massimo; Gardiman, Marina P.; Larghero, Patrizia; Pfeffer, Ulrich; Naschberger, Elisabeth; Stürzl, Michael; Indraccolo, Stefano; et al. (Carcinogenesis, 2009)
Interferon (IFN)-α is a cytokine with marked therapeutic activity in transplantable tumor models, that is in part due to angiogenesis inhibition. Aim of this study was to investigate the effects of IFN-α during the early phases of tumor development in the transgenic adenocarcinoma of the mouse prostate (TRAMP) model. To provide sustained IFN-α production, TRAMP mice were injected intraperitoneally with lentiviral vectors. IFN-α administration resulted in rapid and protracted upregulation of IFN-α-regulated genes associated with antiangiogenic and antiproliferative functions in the prostate of TRAMP mice, including guanylate-binding protein 1 (GBP-1), IFI204 and CXCL10-11. These transcriptional changes were accompanied by effects on the tumor vasculature, including significant reduction of intraductal microvessel density and increased pericyte coverage, and marked reduction of tumor cell proliferation, without induction of tumor necrosis. Intriguingly, GBP-1 and myxovirus resistance A, two IFN-regulated proteins, were found expressed in ∼40% of human prostate cancer samples analyzed, suggesting expression of endogenous IFN-α. Overall, these findings demonstrate that IFN-α is able to counteract the angiogenic switch and impairs tumor cell proliferation in preinvasive lesions. Since the angiogenic switch also marks progression of human prostatic cancer, these results highlight the potential of angiogenesis inhibitors for the development of chemoprevention strategies in high-risk individuals. © The Author 2009. Published by Oxford University Press. All rights reserved.
Created from Fastlane, Scopus look-up

Interferon γ-Induced human guanylate binding protein 1 inhibits mammary tumor growth in mice - Lipnik, Karoline; Naschberger, Elisabeth; Britzen-Laurent, Nathalie; Kodajova, Petra; Petznek, Helga; Rungaldier, Stefanie; Astigiano, Simonetta; Ferrini, Silvano; Stürzl, Michael; Hohenadl, Christine (Molecular Medicine, 2010)
Interferon γ (IFN-γ) has recently been implicated in cancer immunosurveillance. Among the most abundant proteins induced by IFN-γ are guanylate binding proteins (GBPs), which belong to the superfamily of large GTPases and are widely expressed in various species. Here, we investigated whether the well-known human GBP-1 (hGBP-1), which has been shown to exert antiangio-genic activities and was described as a prognostic marker in colorectal carcinomas, may contribute to an IFN-γ-mediated tumor defense. To this end, an IFN-independent, inducible hGBP-1 expression system was established in murine mammary carcinoma (TS/A) cells, which were then transplanted into syngeneic immune-competent Balb/c mice. Animals carrying TS/A cells that had been given doxycycline for induction of hGBP-1 expression revealed a significantly reduced tumor growth compared with mock-treated mice. Immunohistochemical analysis of the respective tumors demonstrated a tightly regulated, high-level expression of hGBP-1. No signs of an enhanced immunosurveillance were observed by investigating the number of infiltrating B and T cells. However, hemoglobin levels as well as the number of proliferating tumor cells were shown to be significantly reduced in hGBP-1-expressing tumors. This finding corresponded to reduced amounts of vascular endothelial growth factor A (VEGF-A) released by hGBP-1-expressing TS/A cells in vitro and reduced VEGF-A protein levels in the corresponding mammary tumors in vivo. The results suggest that hGBP-1 may contribute to IFN-γ-mediated antitumorigenic activities by inhibiting paracrine effects of tumor cells on angiogenesis. Consequently, owing to these activities GBPs might be considered as potent members in an innate, IFN-γ-induced antitumoral defense system. © 2010 The Feinstein Institute for Medical Research.
Created from Fastlane, Scopus look-up

International Continence Society best practice statement for use of sacral neuromodulation. - Goldman, Howard B.; Lloyd, Jessica C.; Noblett, Karen L.; Carey, Marcus P.; Castano Botero, Juan Carlos; Gajewski, Jerzy B.; Lehur, Paul A.; Hassouna, Magdy M.; Matzel, Klaus; Paquette, Ian M.; De Wachter, Stefan; Ehlert, Michael J.; et al. (Neurourology and Urodynamics, 2018)
AIMS: Sacral neuromodulation (SNM) is an accepted therapy for a variety of conditions. However, despite over 20 years of experience, it remains a specialized procedure with a number of subtleties. Here we present the recommendations issued from the International Continence Society (ICS) SNM Consensus Panel. METHODS: Under the auspices of the ICS, eight urologists, three colorectal surgeons and two urogynecologists, covering a wide breadth of geographic and specialty interest representation, met in January 2017 to discuss best practices for neuromodulation. Suggestions for statements were submitted in advance and specific topics were assigned to committee members, who prepared and presented supporting data to the group, at which time each topic was discussed in depth. Best practice statements were formulated based on available data. This document was then circulated to multiple external reviewers after which final edits were made and approved by the group. RESULTS: The present recommendations, based on the most relevant data available in the literature, as well as expert opinion, address a variety of specific and at times problematic issues associated with SNM. These include the use of SNM for a variety of underlying conditions, need for pre-procedural testing, use of staged versus single-stage procedures, screening for success during the trial phase, ideal anesthesia, device implantation, post-procedural management, trouble-shooting loss of device function, and future directions for research. CONCLUSIONS: These guidelines undoubtedly constitute a reference document, which will help urologists, gynecologists, and colorectal surgeons optimize their use of SNM for refractory urinary urgency and frequency, UUI, NOR, and FI.
EVALuna2:34497

International validation of the consensus Immunoscore for the classification of colon cancer: a prognostic and accuracy study - Pages, Franck; Mlecnik, Bernhard; Marliot, Florence; Bindea, Gabriela; Ou, Fang-Shu; Bifulco, Carlo; Lugli, Alessandro; Zlobec, Inti; Rau, Tilman T.; Berger, Martin D.; Nagtegaal, Iris D.; Vink-Borger, Elisa; et al. (Lancet, 2018)
BACKGROUND: The estimation of risk of recurrence for patients with colon carcinoma must be improved. A robust immune score quantification is needed to introduce immune parameters into cancer classification. The aim of the study was to assess the prognostic value of total tumour-infiltrating T-cell counts and cytotoxic tumour-infiltrating T-cells counts with the consensus Immunoscore assay in patients with stage I-III colon cancer. METHODS: An international consortium of 14 centres in 13 countries, led by the Society for Immunotherapy of Cancer, assessed the Immunoscore assay in patients with TNM stage I-III colon cancer. Patients were randomly assigned to a training set, an internal validation set, or an external validation set. Paraffin sections of the colon tumour and invasive margin from each patient were processed by immunohistochemistry, and the densities of CD3+ and cytotoxic CD8+ T cells in the tumour and in the invasive margin were quantified by digital pathology. An Immunoscore for each patient was derived from the mean of four density percentiles. The primary endpoint was to evaluate the prognostic value of the Immunoscore for time to recurrence, defined as time from surgery to disease recurrence. Stratified multivariable Cox models were used to assess the associations between Immunoscore and outcomes, adjusting for potential confounders. Harrell's C-statistics was used to assess model performance. FINDINGS: Tissue samples from 3539 patients were processed, and samples from 2681 patients were included in the analyses after quality controls (700 patients in the training set, 636 patients in the internal validation set, and 1345 patients in the external validation set). The Immunoscore assay showed a high level of reproducibility between observers and centres (r=0·97 for colon tumour; r=0·97 for invasive margin; p<0·0001). In the training set, patients with a high Immunoscore had the lowest risk of recurrence at 5 years (14 [8%] patients with a high Immunoscore vs 65 (19%) patients with an intermediate Immunoscore vs 51 (32%) patients with a low Immunoscore; hazard ratio [HR] for high vs low Immunoscore 0·20, 95% CI 0·10-0·38; p<0·0001). The findings were confirmed in the two validation sets (n=1981). In the stratified Cox multivariable analysis, the Immunoscore association with time to recurrence was independent of patient age, sex, T stage, N stage, microsatellite instability, and existing prognostic factors (p<0·0001). Of 1434 patients with stage II cancer, the difference in risk of recurrence at 5 years was significant (HR for high vs low Immunoscore 0·33, 95% CI 0·21-0·52; p<0·0001), including in Cox multivariable analysis (p<0·0001). Immunoscore had the highest relative contribution to the risk of all clinical parameters, including the American Joint Committee on Cancer and Union for International Cancer Control TNM classification system. INTERPRETATION: The Immunoscore provides a reliable estimate of the risk of recurrence in patients with colon cancer. These results support the implementation of the consensus Immunoscore as a new component of a TNM-Immune classification of cancer. FUNDING: French National Institute of Health and Medical Research, the LabEx Immuno-oncology, the Transcan ERAnet Immunoscore European project, Association pour la Recherche contre le Cancer, CARPEM, AP-HP, Institut National du Cancer, Italian Association for Cancer Research, national grants and the Society for Immunotherapy of Cancer.
EVALuna2:34256

International validation of the low anterior resection syndrome score - Juul, Therese; Ahlberg, Madelene; Biondo, Sebastiano; Emmertsen, Katrine Jossing; Espin, Eloy; Jimenez, Luis Miguel; Matzel, Klaus; Palmer, Gabriella; Sauermann, Anna Catherin; Trenti, Loris; Zhang, Wei; Laurberg, Soren; et al. (Annals of Surgery, 2014)
The aims of this study were to investigate the convergent and discriminative validity and reliability of the low anterior resection syndrome (LARS) score in an international setting.The LARS score is a simple self-administered questionnaire measuring bowel dysfunction after rectal cancer surgery. The score is intended to be commonly used in international research and clinical practice in the future. Therefore, a thorough validation in an international setting is of utmost importance.The LARS score was translated using methods in keeping with current international recommendations. A total of 801 patients operated for rectal cancer in Sweden, Spain, Germany, and Denmark completed the LARS score questionnaire, including an anchor question assessing the impact of bowel function on quality of life. A subgroup of 218 patients completed the LARS score twice. Data were analyzed per country.The LARS score has demonstrated a high convergent validity in terms of a high correlation between LARS score and quality of life (P < 0.001). Sensitivity ranged from 67.7% to 88.3% and specificity from 58.1% to 86.3%. The LARS score was able to discriminate between groups of patients differing with regard to radiotherapy, surgery, and age (P < 0.05). The score also demonstrated high reliability at test-retest with narrow limits of agreement and no statistically significant difference between scores at the first and second test.The Swedish, Spanish, German, and Danish versions of the LARS score have proven to be valid and reliable tools for measuring LARS in European rectal cancer patients.
EVALuna2:15141

Interplay of GTPases and Cytoskeleton in Cellular Barrier Defects during Gut Inflammation - Lopez Posadas, Rocío; Stürzl, Michael; Atreya, Imke; Neurath, Markus; Britzen-Laurent, Nathalie (Frontiers in Immunology, 2017)
An essential role of the intestine is to build and maintain a barrier preventing the luminal gut microbiota from invading the host. This involves two coordinated physical and immunological barriers formed by single layers of intestinal epithelial and endothelial cells, which avoid the activation of local immune responses or the systemic dissemination of microbial agents, and preserve tissue homeostasis. Accordingly, alterations of epithelial and endothelial barrier functions have been associated with gut inflammation, for example during inflammatory bowel disease (IBD). The discriminative control of nutriment uptake and sealing toward potentially pathological microorganisms requires a profound regulation of para- and transcellular permeability. On the subcellular level, the cytoskeleton exerts key regulatory functions in the maintenance of cellular barriers. Increased epithelial/endothelial permeability occurs primarily as a result of a reorganization of cytoskeletal-junctional complexes. Pro-inflammatory mediators such as cytokines can induce cytoskeletal rearrangements, causing inflammation-dependent defects in gut barrier function. In this context, small GTPases of the Rho family and large GTPases from the Dynamin superfamily appear as major cellular switches regulating the interaction between intercellular junctions and actomyosin complexes, and in turn cytoskeleton plasticity. Strikingly, some of these proteins, such as RhoA or guanylate-binding protein-1 (GBP-1) have been associated with gut inflammation and IBD. In this review, we will summarize the role of small and large GTPases for cytoskeleton plasticity and epithelial/endothelial barrier in the context of gut inflammation.
EVALuna2:15286

Interstitial brachytherapy as a boost to patients with anal carcinoma and poor response to chemoradiation: Single-institution long-term results - Gryc, Thomas; Ott, Oliver; Putz, Florian; Knippen, Stefan; Raptis, Dimitrios; Fietkau, Rainer; Strnad, Vratislav (Brachytherapy, 2016)
To analyze the efficacy of a protocol-based brachytherapy (BT) boost after external beam radiation therapy (EBRT) with simultaneous chemotherapy in patients with anal carcinoma.About 190 patients have been analyzed. Around 143 patients were identified with a good clinical response at the end of EBRT. Another 47 patients received an additional BT boost to the residual tumor at 6 weeks after end of chemoradiation.The 5-year incidence of local recurrence was 24% in patients with BT boost and 19% in patients without BT boost (p = 0.238). The 5-year disease-free survival rate, overall survival rate, and colostomy-free survival rate were 64% and 75% and 76.1% in the BT group and 69% (p = 0.212), 72% (p = 0.924), and 82.7% (p = 0.488) in the non-BT group. We found no differences in late toxicity between the groups.For patients with anal cancer with not a good response to 50-59 Gy EBRT with simultaneous chemotherapy, the further dose escalation using the BT boost up to a mean of 67.5 Gy seems to improve the clinical outcome to the same level as observed in patients with a good response to ERBT, without an increase in late side effects.
EVALuna2:15265

Intracellular localization map of human herpesvirus 8 proteins. - Sander, Gaby; Konrad, Andreas; Thurau, Mathias; Wies, Effi; Leubert, Rene; Kremmer, Elisabeth; Dinkel, Holger; Schulz, Thomas; Neipel, Frank; Stürzl, Michael (Journal of Virology, 2008)
Human herpesvirus 8 (HHV-8) is the etiological agent of Kaposi's sarcoma. We present a localization map of 85 HHV-8-encoded proteins in mammalian cells. Viral open reading frames were cloned with a Myc tag in expression plasmids, confirmed by full-length sequencing, and expressed in HeLa cells. Protein localizations were analyzed by immunofluorescence microscopy. Fifty-one percent of all proteins were localized in the cytoplasm, 22% were in the nucleus, and 27% were found in both compartments. Surprisingly, we detected viral FLIP (v-FLIP) in the nucleus and in the cytoplasm, whereas cellular FLIPs are generally localized exclusively in the cytoplasm. This suggested that v-FLIP may exert additional or alternative functions compared to cellular FLIPs. In addition, it has been shown recently that the K10 protein can bind to at least 15 different HHV-8 proteins. We noticed that K10 and only five of its 15 putative binding factors were localized in the nucleus when the proteins were expressed in HeLa cells individually. Interestingly, in coexpression experiments K10 colocalized with 87% (13 of 15) of its putative binding partners. Colocalization was induced by translocation of either K10 alone or both proteins. These results indicate active intracellular translocation processes in virus-infected cells. Specifically in this framework, the localization map may provide a useful reference to further elucidate the function of HHV-8-encoded genes in human diseases.

Intracellular Quantification and Localization of Label-Free Iron Oxide Nanoparticles by Holotomographic Microscopy - Friedrich, Ralf P.; Schreiber, Eveline; Tietze, Rainer; Yang, Hai; Pilarsky, Christian; Alexiou, Christoph (Nanotechnology, Science and Applications, 2020)
Background: The limitations of optical microscopy to determine the cellular localization of label-free nanoparticles prevent a solid prediction of the cellular effect of particles intended for medical applications. To avoid the strong physicochemical changes associated with fluorescent labelling, which often result in differences in cellular uptake, efficiency and toxicity of particles, novel detection techniques are required.
CRIS-Team WoS Importer:2021-01-29

Intracellular trafficking of guanylate-binding proteins is regulated by heterodimerization in a hierarchical manner - Britzen-Laurent, Nathalie; Bauer, Michael; Berton, Valeria; Fischer, Nicole; Syguda, Adrian; Reipschlaeger, Simone; Naschberger, Elisabeth; Herrmann, Christian; Stürzl, Michael (PLoS ONE, 2010)
Guanylate-binding proteins (GBPs) belong to the dynamin family of large GTPases and represent the major IFN-c-induced proteins. Here we systematically investigated the mechanisms regulating the subcellular localization of GBPs. Three GBPs (GBP-1, GBP-2 and GBP-5) carry a C-terminal CaaX-prenylation signal, which is typical for small GTPases of the Ras family, and increases the membrane affinity of proteins. In this study, we demonstrated that GBP-1, GBP-2 and GBP-5 are prenylated in vivo and that prenylation is required for the membrane association of GBP-1, GBP-2 and GBP-5. Using coimmunoprecipitation, yeast-two-hybrid analysis and fluorescence complementation assays, we showed for the first time that GBPs are able to homodimerize in vivo and that the membrane association of GBPs is regulated by dimerization similarly to dynamin. Interestingly, GBPs could also heterodimerize. This resulted in hierarchical positioning effects on the intracellular localization of the proteins. Specifically, GBP-1 recruited GBP-5 and GBP-2 into its own cellular compartment and GBP-5 repositioned GBP-2. In addition, GBP-1, GBP-2 and GBP-5 were able to redirect non-prenylated GBPs to their compartment in a prenylation-dependent manner. Overall, these findings prove in vivo the ability of GBPs to dimerize, indicate that heterodimerization regulates sub-cellular localization of GBPs and underscore putative membrane-associated functions of this family of proteins. © 2010 Britzen-Laurent et al.
Created from Fastlane, Scopus look-up

Intraoperative robotic-assisted low anterior rectal resection performance assessment using procedure-specific binary metrics and a global rating scale - Gomez Ruiz, Marcos; Tou, Samson; Gallagher, Anthony G.; Cagigas Fernandez, Carmen; Cristobal Poch, Lidia; Matzel, Klaus (BJS Open, 2022)
In this prospective, multicentre study, we objectively assessed the performance of experienced and novice colorectal surgeons performing robotic-assisted low anterior rectal resection (for rectal cancer surgery) with two assessment methods: proficient-based progressive (PBP), and GEARS. Both assessment methods discriminated between group performances, but PBP binary metrics seem to be a more useful tool in this study. PBP binary metrics revealed that some experienced surgeons performed poorly.
CRIS-Team WoS Importer:2022-05-20

Inverse relation of Fas-ligand and tumor-infiltrating lymphocytes in angiosarcoma: indications of apoptotic tumor counterattack. - Zietz, Christian; Rumpler, Ulrich; Stürzl, Michael; Löhrs, Udo (American Journal of Pathology, 2001)
Fas and Fas-L regulate immune responses through the induction of cell death. Fas-L is commonly expressed in activated immune cells and in the endothelium. In the latter it contributes to the inhibition of transvascular cell migration by the induction of apoptosis in Fas-bearing lymphocytes. Here we investigated whether the Fas/Fas-L system may regulate lymphocyte invasion into angiosarcomas. Fas and Fas-L expression was quantitatively determined in different grade angiosarcomas (n = 40) and related to the number of extravasated tumor-infiltrating lymphocytes (TILs). Fas expression was detected in < 50% of the cases. In positive tumors both the number of Fas-positive cells and the staining intensity were highly variable and did not correlate with the number of TILs, the mean time of survival, and the histopathological tumor grade. By contrast, Fas-L expression was detected in >70% of the cases and the relative numbers of Fas-L-positive cells correlated inversely with the numbers of CD3- and CD8-positive TILs (P < or = 0.004). The survival times of patients with high Fas-L-expressing angiosarcomas were significantly reduced as compared to patients with low Fas-L-expressing tumors. Our results show that angiosarcomas with low Fas-L expression are characterized by numerous TILs, whereas sarcomas with high Fas-L expression show significantly reduced numbers of TILs. These results suggest that the Fas/Fas-L system may repress TIL invasion into angiosarcoma and by this may contribute to the evasion of the anti-tumor immune surveillance of angiosarcoma in the course of an apoptotic tumor counterattack mechanism.

Investigating Intestinal Barrier Breakdown in Living Organoids - Bardenbacher, Marco; Ruder, Barbara; Britzen-Laurent, Nathalie; Naschberger, Elisabeth; Becker, Christoph; Palmisano, Ralf; Stürzl, Michael; Tripal, Philipp (Journal of Visualized Experiments, 2020)
Organoids and three-dimensional (3D) cell cultures allow the investigation of complex biological mechanisms and regulations in vitro, which previously was not possible in classical cell culture monolayers. Moreover, monolayer cell cultures are good in vitro model systems but do not represent the complex cellular differentiation processes and functions that rely on 3D structure. This has so far only been possible in animal experiments, which are laborious, time consuming, and hard to assess by optical techniques. Here we describe an assay to quantitatively determine the barrier integrity over time in living small intestinal mouse organoids. To validate our model, we applied interferon gamma (IFN-gamma) as a positive control for barrier destruction and organoids derived from IFN-gamma receptor 2 knock out mice as a negative control. The assay allowed us to determine the impact of IFN-gamma on the intestinal barrier integrity and the IFN-gamma induced degradation of the tight junction proteins claudin-2, -7, and -15. This assay could also be used to investigate the impact of chemical compounds, proteins, toxins, bacteria, or patient-derived probes on the intestinal barrier integrity.
CRIS-Team WoS Importer:2020-04-17

In vivo imaging using fluorescent antibodies to tumor necrosis factor predicts therapeutic response in Crohn's disease - Atreya, Raja; Neumann, Helmut; Neufert, Clemens; Waldner, Maximilian; Billmeier, Ulrike; Zopf, Yurdagül; Willma, Marcus; App, Christine; Münster, Tino; Kessler, Hermann; Maas, Stefanie; Gebhardt, Bernd; et al. (Nature Medicine, 2014)
As antibodies to tumor necrosis factor (TNF) suppress immune responses in Crohn's disease by binding to membrane-bound TNF (mTNF), we created a fluorescent antibody for molecular mTNF imaging in this disease. Topical antibody administration in 25 patients with Crohn's disease led to detection of intestinal mTNF(+) immune cells during confocal laser endomicroscopy. Patients with high numbers of mTNF(+) cells showed significantly higher short-term response rates (92%) at week 12 upon subsequent anti-TNF therapy as compared to patients with low amounts of mTNF(+) cells (15%). This clinical response in the former patients was sustained over a follow-up period of 1 year and was associated with mucosal healing observed in follow-up endoscopy. These data indicate that molecular imaging with fluorescent antibodies has the potential to predict therapeutic responses to biological treatment and can be used for personalized medicine in Crohn's disease and autoimmune or inflammatory disorders.
EVALuna2:1838

IRAK-M Expression in Tumor Cells Supports Colorectal Cancer Progression through Reduction of Antimicrobial Defense and Stabilization of STAT3 - Kesselring, Rebecca; Glaesner, Joachim; Hiergeist, Andreas; Naschberger, Elisabeth; Neumann, Helmut; Brunner, Stefan M.; Wege, Anja K.; Seebauer, Caroline; Koehl, Gudrun; Merkl, Susanne; Croner, Roland S.; Hackl, Christina; et al. (Cancer Cell, 2016)
Colorectal cancer (CRC) is associated with loss of epithelial barrier integrity, which facilitates the interaction of the immunological microenvironment with the luminal microbiome, eliciting tumor-supportive inflammation. An important regulator of intestinal inflammatory responses is IRAK-M, a negative regulator of TLR signaling. Here we investigate the compartment-specific impact of IRAK-M on colorectal carcinogenesis using a mouse model. We demonstrate that IRAK-M is expressed in tumor cells due to combined TLR and Wnt activation. Tumor cell-intrinsic IRAK-M is responsible for regulation of microbial colonization of tumors and STAT3 protein stability in tumor cells, leading to tumor cell proliferation. IRAK-M expression in human CRCs is associated with poor prognosis. These results suggest that IRAK-M may be a potential therapeutic target for CRC treatment.
EVALuna2:2089

Isolation of Endothelial Cells from Human Tumors - Naschberger, Elisabeth; Schellerer, Vera; Rau, Tilman T.; Croner, Roland S.; Stürzl, Michael (Cancer Cell Culture, 2011)
Antiangiogenic drugs have been used successfully for the treatment of colorectal cancer (CRC) and several other tumor types. Until recently, viable tumor endothelial cells (TEC) and normal endothelial cells of uninvolved colon tissue (NEC) from the same patient have not been available to optimize treatment strategies in vitro. Here, we describe a protocol for the isolation of TEC and NEC. These cells were isolated at a very high purity via magnetic cell sorting of tissue samples obtained from surgical specimens of patients suffering from CRC. Isolated TEC and NEC expressed CD31, CD105, VE-cadherin, VCAM-1, ICAM-1, and E-selectin, formed capillaries in basal membrane extract, and were able to take up acetylated LDL. They were negative for podoplanin, CD45, CD68, and CK-20, indicating blood vessel endothelial lineage. Expression of vWF was more pronounced in NEC cultures, whereas vWF was absent or only slightly expressed in all TEC cultures in vitro. Lower intracellular concentrations of vWF were also detected in TEC as compared to NEC at the tissue level. The latter finding demonstrated that differential features of TEC and NEC in vivo arc stably perpetuated in culture. The isolated endothelial cell cultures may provide a useful in vitro model system to elucidate epigenetic effects on angiogenesis in cancer and to optimize antiangiogenic therapy.
Created from Fastlane, WoS look-up

Isolation of Enterococcus faecium and determination of its mechanism for promoting the growth and development of Drosophila - Li, Yujuan; Pan, Lei; Li, Pengcheng; Gao, Fuguo; Wang, Lei; Chen, Jian; Li, Zhichao; Gao, Yongheng; Gong, Yumei; Jin, Faguang (Scientific Reports, 2023)
Intestinal symbiotic microorganisms have a strong capacity to regulate the physiological functions of their host, and Drosophila serves as a useful model. Enterococcus faecium (E. faecium) is a member of the normal intestinal flora of animals. Lactic acid bacteria (LAB) such as E. faecium can promote the growth and development of Drosophila, but the mechanism of regulation of Drosophila is poorly understood. In this study, we found that E. faecium used a carbon source to produce probiotic acids. E. faecium is a symbiotic bacterium for Drosophila, and adult flies passed on parental flora to offspring. E. faecium promoted the growth and development of Drosophila, especially under poor nutritional conditions. E. faecium shortened the developmental process for Drosophila and accelerated the transformation from larva to pupa. Finally, E. faecium promoted the growth and development of Drosophila through TOR and insulin signalling pathways.
CRIS-Team Scopus Importer:2023-11-17

Isolation of Human Endothelial Cells from Normal Colon and Colorectal Carcinoma - An Improved Protocol - Naschberger, Elisabeth; Regensburger, Daniela; Tenkerian, Clara; Langheinrich, Melanie; Engel, Felix; Geppert, Carol-Immanuel; Hartmann, Arndt; Grützmann, Robert; Schellerer, Vera; Stürzl, Michael (Journal of Visualized Experiments, 2018)
Primary cells isolated from human carcinomas are valuable tools to identify pathogenic mechanisms contributing to disease development and progression. In particular, endothelial cells (EC) constituting the inner surface of vessels, directly participate in oxygen delivery, nutrient supply, and removal of waste products to and from tumors, and are thereby prominently involved in the constitution of the tumor microenvironment (TME). Tumor endothelial cells (TECs) can be used as cellular biosensors of the intratumoral microenvironment established by communication between tumor and stromal cells. TECs also serve as targets of therapy. Accordingly, in culture these cells allow studies on mechanisms of response or resistance to anti-angiogenic treatment. Recently, it was found that TECs isolated from human colorectal carcinoma (CRC) exhibit memory-like effects based on the specific TME they were derived from. Moreover, these TECs actively contribute to the establishment of a specific TME by the secretion of different factors. For example, TECs in a prognostically favorable Th1-TME secrete the anti-angiogenic tumor-suppressive factor secreted protein, acidic and rich in cysteine-like 1 (SPARCL1). SPARCL1 regulates vessel homeostasis and inhibits tumor cell proliferation and migration. Hence, cultures of pure, viable TECs isolated from human solid tumors are a valuable tool for functional studies on the role of the vascular system in tumorigenesis. Here, a new up-to-date protocol for the isolation of primary EC from the normal colon as well as CRC is described. The technique is based on mechanical and enzymatic tissue digestion, immunolabeling, and fluorescence activated cell sorting (FACS)-sorting of triple-positive cells (CD31, VE-cadherin, CD105). With this protocol, viable TEC or normal endothelial cell (NEC) cultures could be isolated from colon tissues with a success rate of 62.12% when subjected to FACS-sorting (41 pure EC cultures from 66 tissue samples). Accordingly, this protocol provides a robust approach to isolate human EC cultures from normal colon and CRC.
EVALuna2:34267

IT infrastructure components to support clinical care and translational research projects in a comprehensive cancer center - Prokosch, Hans-Ulrich; Ries, Markus; Beyer, Alexander; Schwenk, Martin; Seggewies, Christof; Köpcke, Felix; Mate, Sebastian; Martin, Marcus; Bärthlein, Barbara; Beckmann, Matthias; Stürzl, Michael; Croner, Roland; et al. (User Centred Networked Health Care, 2011)
This paper presents the concept of an integrated IT infrastructure framework established at the comprehensive cancer center at the University Hospital Erlangen. The framework is based on the single source concept where data from the electronic medical record are reused for clinical and translational research projects. The applicability of the approach is illustrated by two case studies from colon cancer and prostate cancer research projects. © 2011 European Federation for Medical Informatics. All rights reserved.
UnivIS-Import:2015-04-14:Pub.2011.tech.IMMD.infome.itinfr
Keywords: Cancer documentation; Center; Comprehensive cancer; IT infrastructure framework; Single source concept; Translational research

IVOPAK II Study: Morbidity Following Secondary Resection of Colorectal Liver Metastases - Schellerer, Vera; Merkel, Susanne; Grützmann, Robert; Kersting, Stephan; Wein, Axel (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-03-20

JAK1-dependent transphosphorylation of JAK2 limits the antifibrotic effects of selective JAK2 inhibitors on long-term treatment - Zhang, Yun; Liang, Ruifang; Chen, Chih-Wei; Mallano, Tatjana; Dees, Clara; Distler, Alfiya; Reich, Adam; Bergmann, Christina; Ramming, Andreas; Gelse, Kolja; Mielenz, Dirk; Distler, Oliver; et al. (Annals of the Rheumatic Diseases, 2017)
Janus kinase 2 (JAK2) has recently been described as a novel downstream mediator of the pro-fibrotic effects of transforming growth factor-?. Although JAK2 inhibitors are in clinical use for myelodysplastic syndromes, patients often rapidly develop resistance. Tumour cells can escape the therapeutic effects of selective JAK2 inhibitors by mutation-independent transactivation of JAK2 by JAK1. Here, we used selective JAK2 inhibition as a model to test the hypothesis that chronic treatment may provoke resistance by facilitating non-physiological signalling pathways in fibroblasts.The antifibrotic effects of long-term treatment with selective JAK2 inhibitors and reactivation of JAK2 signalling by JAK1-dependent transphosphorylation was analysed in cultured fibroblasts and experimental dermal and pulmonary fibrosis. Combined JAK1/JAK2 inhibition and co-treatment with an HSP90 inhibitor were evaluated as strategies to overcome resistance.The antifibrotic effects of selective JAK2 inhibitors on fibroblasts decreased with prolonged treatment as JAK2 signalling was reactivated by JAK1-dependent transphosphorylation of JAK2. This reactivation could be prevented by HSP90 inhibition, which destabilised JAK2 protein, or with combined JAK1/JAK2 inhibitors. Treatment with combined JAK1/JAK2 inhibitors or with JAK2 inhibitors in combination with HSP90 inhibitors was more effective than monotherapy with JAK2 inhibitors in bleomycin-induced pulmonary fibrosis and in adTBR-induced dermal fibrosis.Fibroblasts can develop resistance to chronic treatment with JAK2 inhibitors by induction of non-physiological JAK1-dependent transactivation of JAK2 and that inhibition of this compensatory signalling pathway, for example, by co-inhibition of JAK1 or HSP90 is important to maintain the antifibrotic effects of JAK2 inhibition with long-term treatment.
EVALuna2:13270

Jumonji Domain Containing Protein 3 (JMJD3) As a Novel Epigenetic Mechanism of Fibroblast Activation By Regulation of Fra-2 - Bergmann, Christina; Brandt, Adrian; Dees, Clara; Zhang, Yun; Lin, Neng-Yu; Chen, Chih-Wei; Mallano, Tatjana; Liang, Ruifang; Kam, Pui-See; Distler, Oliver; Schett, Georg; Distler, Jörg (2016)
EVALuna2:35056

Kaposi's sarcoma: a review of gene expression and ultrastructure of KS spindle cells in vivo. - Stürzl, Michael; Brandstetter, Heinz; Roth, W K (Aids Research and Human Retroviruses, 1992)
The ultrastructural features and the gene expression pattern of Kaposi's sarcoma (KS) spindle cells in vivo suggest that KS is a tumor of the mixed cell type. The expression pattern of cytokines and cytokine receptors in the tumor lesion, together with the results obtained from in vitro characterization of KS-derived cells, provide evidence that paracrine mechanisms of growth factor action are important for the maintenance of KS. The reports on virus infection of KS cells suggest an indirect role of virus infection in the induction of KS, most likely mediated by immunostimulation and subsequent production of cytokines.

Kaposi's sarcoma-associated herpesvirus gH/gL: glycoprotein export and interaction with cellular receptors. - Hahn, Alexander; Birkmann, Alexander; Wies, Effi; Dorer, Dominik; Mahr, Kerstin; Stürzl, Michael; Titgemeyer, Fritz; Neipel, Frank (Journal of Virology, 2009)
The attachment, entry, and fusion of Kaposi's sarcoma-associated herpesvirus (KSHV) with target cells are mediated by complex machinery containing, among others, viral glycoprotein H (gH) and its alleged chaperone, gL. We observed that KSHV gH, in contrast to its homologues in several other herpesviruses, is transported to the cytoplasm membrane independently from gL, but not vice versa. Mutational analysis revealed that the N terminus of gH is sufficient for gL interaction. However, the entire extracellular part of gH is required for efficient gL secretion. The soluble ectodomain of gH was sufficient to interact with the surfaces of potential target cells in a heparin-dependent manner, and binding was further enhanced by coexpression of gL. Surface plasmon resonance revealed a remarkably high affinity of gH for glycosaminoglycans. Heparan sulfate (HS) proteoglycans of the syndecan family act as cellular receptors for the gH/gL complex. They promoted KSHV infection, and expression of gH/gL on target cells inhibited subsequent KSHV infection. Whereas gH alone was able to bind to HS, we observed that only the gH/gL complex adhered to heparan sulfate-negative cells at lamellipodium-like structures.

Kaposi's sarcoma-associated herpesvirus serology in Europe and Uganda: multicentre study with multiple and novel assays. - Schatz, Octavian; Monini, Paolo; Bugarini, Roberto; Neipel, Frank; Schulz, Thomas F.; Andreoni, Massimo; Erb, Peter; Eggers, Maren; Haas, Jürgen; Buttò, Stefano; Lukwiya, Matthew; Bogner, Johannes R.; et al. (Journal of Medical Virology, 2001)
A multicentre study was undertaken to define novel assays with increased inter-assay concordance, sensitivity, specificity and predictive value for serological diagnosis of human herpesvirus type 8 (HHV-8) infection. A total of 562 sera from European and Ugandan human immunodeficiency virus (HIV)-infected or uninfected individuals with or without Kaposi's sarcoma (KS) and blood donors were examined under code by 18 different assays in seven European laboratories. Sera from KS patients and all non-KS sera found positive by at least 70%, 80%, or 90% of the assays were considered "true positive." The validity of the assays was then evaluated by univariate logistic regression analysis. Two immunofluorescence assays (IFA) for detection of antibodies against HHV-8 lytic (Rlyt) or latent (LLANA) antigens and two enzyme-linked-immunosorbent assays (ELISA) (M2, EK8.1) for detection of antibodies against HHV-8 structural proteins were found to be highly concordant, specific, and sensitive, with odds ratios that indicated a high predictive value. When used together, the two IFA (Rlyt-LLANA) showed the best combination of sensitivity (89.1%) and specificity (94.9%). The performance of these assays indicate that they may be used for the clinical management of individuals at risk of developing HHV-8 associated tumours such as allograft recipients.

Kaposi's sarcoma associated herpesvirus tegument protein ORF75 is essential for viral lytic replication and plays a critical role in the antagonization of ND10-instituted intrinsic immunity - Full, Florian; Jungnickl, Doris; Reuter, Nina; Bogner, Elke; Brulois, Kevin; Scholz, Brigitte; Stürzl, Michael; Myoung, Jinjong; Jung, Jae U.; Stamminger, Thomas; Enßer, Armin (PLoS Pathogens, 2014)
Nuclear domain 10 (ND10) components are restriction factors that inhibit herpesviral replication. Effector proteins of different herpesviruses can antagonize this restriction by a variety of strategies, including degradation or relocalization of ND10 proteins. We investigated the interplay of Kaposi's Sarcoma-Associated Herpesvirus (KSHV) infection and cellular defense by nuclear domain 10 (ND10) components. Knock-down experiments in primary human cells show that KSHV-infection is restricted by the ND10 components PML and Sp100, but not by ATRX. After KSHV infection, ATRX is efficiently depleted and Daxx is dispersed from ND10, indicating that these two ND10 components can be antagonized by KSHV. We then identified the ORF75 tegument protein of KSHV as the viral factor that induces the disappearance of ATRX and relocalization of Daxx. ORF75 belongs to a viral protein family (viral FGARATs) that has homologous proteins in all gamma-herpesviruses. Isolated expression of ORF75 in primary cells induces a relocalization of PML and dispersal of Sp100, indicating that this viral effector protein is able to influence multiple ND10 components. Moreover, by constructing a KSHV mutant harboring a stop codon at the beginning of ORF75, we could demonstrate that ORF75 is absolutely essential for viral replication and the initiation of viral immediate-early gene expression. Using recombinant viruses either carrying Flag- or YFP-tagged variants of ORF75, we could further corroborate the role of ORF75 in the antagonization of ND10-mediated intrinsic immunity, and show that it is independent of the PML antagonist vIRF3. Members of the viral FGARAT family target different ND10 components, suggesting that the ND10 targets of viral FGARAT proteins have diversified during evolution. We assume that overcoming ND10 intrinsic defense constitutes a critical event in the replication of all herpesviruses; on the other hand, restriction of herpesviral replication by ND10 components may also promote latency as the default outcome of infection.
EVALuna2:8222

Kaposi's sarcoma-derived cell line SLK is not of endothelial origin, but is a contaminant from a known renal carcinoma cell line. - Stürzl, Michael; Gaus, Dominika; Dirks, Wilhelm G.; Ganem, Don; Jochmann, Ramona (International Journal of Cancer, 2013)
Kaposi's sarcoma (KS) is an endothelial cell-derived tumor. Investigations of the molecular mechanisms of KS pathogenesis and the identification of drugs for treatment of KS depend critically on valid cell-culture models. Two major immortalized cell lines are available for KS research. Recently, the KS cell line KS Y-1 has been shown to be cross-contaminated with the T24 urinary bladder cancer cell line (ATCC HTB-4). Here, we show by short tandem repeat profiling that the second KS cell line, SLK, is indistinguishable from the clear-cell renal-cell carcinoma cell line Caki-1. Immunocytochemical detection of cytokeratin expression confirmed the epithelial-cell origin of SLK cells. Our findings indicate that SLK cells are not of endothelial origin and should not be used in future studies as a model for KS-derived endothelial tumor cells. We suggest that in the future, more attention needs to be paid to the authenticity of cells in lines derived from human tissues.

Ketos: Clinical decision support and machine learning as a service – A training and deployment platform based on Docker, OMOP-CDM, and FHIR Web Services - Gründner, Julian; Schwachhofer, Thorsten; Sippl, Phillip; Wolf, Nicolas; Erpenbeck, Marcel; Gulden, Christian; Kapsner, Lorenz A.; Zierk, Jakob; Mate, Sebastian; Stürzl, Michael; Croner, Roland; Prokosch, Hans-Ulrich; et al. (PLoS ONE, 2019)
Background and objective To take full advantage of decision support, machine learning, and patient-level prediction models, it is important that models are not only created, but also deployed in a clinical setting. The KETOS platform demonstrated in this work implements a tool for researchers allowing them to perform statistical analyses and deploy resulting models in a secure environment. Methods The proposed system uses Docker virtualization to provide researchers with reproducible data analysis and development environments, accessible via Jupyter Notebook, to perform statistical analysis and develop, train and deploy models based on standardized input data. The platform is built in a modular fashion and interfaces with web services using the Health Level 7 (HL7) Fast Healthcare Interoperability Resources (FHIR) standard to access patient data. In our prototypical implementation we use an OMOP common data model (OMOP-CDM) database. The architecture supports the entire research lifecycle from creating a data analysis environment, retrieving data, and training to final deployment in a hospital setting. Results We evaluated the platform by establishing and deploying an analysis and end user application for hemoglobin reference intervals within the University Hospital Erlangen. To demonstrate the potential of the system to deploy arbitrary models, we loaded a colorectal cancer dataset into an OMOP database and built machine learning models to predict patient outcomes and made them available via a web service. We demonstrated both the integration with FHIR as well as an example end user application. Finally, we integrated the platform with the open source DataSHIELD architecture to allow for distributed privacy preserving data analysis and training across networks of hospitals. Conclusion The KETOS platform takes a novel approach to data analysis, training and deploying decision support models in a hospital or healthcare setting. It does so in a secure and privacy-preserving manner, combining the flexibility of Docker virtualization with the advantages of standardized vocabularies, a widely applied database schema (OMOP-CDM), and a standardized way to exchange medical data (FHIR).
CRIS-Team Scopus Importer:2019-10-11

Lack of inhibitory effects of the anti-fibrotic drug imatinib on endothelial cell functions in vitro and in vivo. - Venalis, Paulius; Maurer, Britta; Akhmetshina, Alfiya; Busch, Nicole; Dees, Clara; Stürzl, Michael; Zwerina, Jochen; Juengel, Astrid; Gay, Steffen; Schett, Georg; Distler, Oliver; Distler, Jörg (Journal of Cellular and Molecular Medicine, 2009)
Systemic sclerosis (SSc) is a systemic autoimmune disease that is characterized by microangiopathy with progressive loss of capillaries and tissue fibrosis. Imatinib exerts potent anti-fibrotic effects and is currently evaluated in clinical trials. The aim of the present study was to exclude that the anti-fibrotic effects of imatinib are complicated by inhibitory effects on endothelial cell functions, which might augment vascular disease in SSc. Endothelial cells and mice were treated with pharmacologically relevant concentrations of imatinib. The expression of markers of vascular activation was assessed with real-time PCR. Proliferation was analysed with the cell counting experiments and the MTT assay. Apoptosis was quantified with caspase 3 assays, annexin V in vitro and with TUNEL staining in vivo. Migration was studied with scratch and transwell assays. Tube forming was investigated with the matrigel assay. Imatinib did not alter the expression of markers of vascular activation. Imatinib did not increase the percentage of annexin V positive cells or the activity of caspase 3. No reduction in proliferation or metabolic activity of endothelial cells was observed. Imatinib did not affect migration of endothelial cells and did not reduce the formation of capillary tubes. Consistent with the in vitro data, no difference in the number of apoptotic endothelial cells was observed in vivo in mice treated with imatinib. Imatinib does not inhibit activation, viability, proliferation, migration or tube forming of endothelial cells in vitro and in vivo. Thus, treatment with imatinib might not augment further endothelial cell damage in SSc.

Laparoscopic right hemicolectomy with CME: standardization using the "critical view" concept - Strey, Christoph Werner; Wullstein, Christoph; Adamina, Michel; Agha, Ayman; Aselmann, Heiko; Becker, Thomas; Grützmann, Robert; Kneist, Werner; Maak, Matthias; Mann, Benno; Moesta, Kurt Thomas; Runkel, Norbert; et al. (Surgical Endoscopy, 2018)
BACKGROUND: Complete mesocolic excision is gradually becoming an established oncologic surgical principle for right hemicolectomy. However, the procedure is technically demanding and carries the risk of serious complications, especially when performed laparoscopically. A standardized procedure that minimizes technical hazards and facilitates teaching is, therefore, highly desirable. METHODS: An expert group of surgeons and one anatomist met three times. The initial aim was to achieve consensus about the surgical anatomy before agreeing on a sequence for dissection in laparoscopic CME. This proposal was evaluated and discussed in an anatomy workshop using post-mortem body donors along with videos of process-informed procedures, leading to a definite consensus. RESULTS: In order to provide a clear picture of the surgical anatomy, the "open book" model was developed, consisting of symbolic pages representing the corresponding dissection planes (retroperitoneal, ileocolic, transverse mesocolic, and mesogastric), vascular relations, and radicality criteria. The description of the procedure is based on eight preparative milestones, which all serve as critical views of safety. The chosen sequence of the milestones was designed to maximize control during central vascular dissection. Failure to reach any of the critical views should alert the surgeon to a possible incorrect dissection and to consider converting to an open procedure. CONCLUSION: Combining the open-book anatomical model with a clearly structured dissection sequence, using critical views as safety checkpoints, may provide a safe and efficient platform for teaching laparoscopic right hemicolectomy with CME.
EVALuna2:210704

Laparoscopic Right Hemicolectomy with Complete Mesocolic Excision (CME) Laparoskopische Hemikolektomie rechts mit kompletter mesokolischer Exzision (CME) - Brunner, Maximilian; Wiesmüller, Felix; Weber, Klaus; Maak, Matthias; Kersting, Stephan; Grützmann, Robert; Krautz, Christian; Weber, Georg (Zentralblatt für Chirurgie, 2020)
CRIS-Team Scopus Importer:2020-03-17

Laryngeal morbidity after intubation with or without neuromuscular block in thyroid surgery using recurrent laryngeal nerve monitoring - Birkholz, Torsten; Irouschek, Andrea; Saalfrank-Schardt, Christina; Klein, Peter; Schmidt, Joachim (Auris Nasus Larynx, 2012)
The avoidance of neuromuscular blocking agents (NMBA) for endotracheal intubation is associated with a higher incidence of laryngeal discomfort and lesions, but could impair effectiveness of intra operative recurrent laryngeal nerve monitoring (IONM).In a retrospective quality assessment study over a period of 30 months, a collective that had been intubated without NMBA was compared with a group, which had received NMBA. Endolaryngeal EMG was accomplished with a MagStim(®)-EMG-electrode.Out of the 127 patients with 224 nerves at risk (NAR; NMBA 102 NAR, no NMBA 122 NAR), more than 90% received a total intravenous anaesthesia with propofol, and 88% had remifentanil. Laryngeal side effects and damage scores did not differ significantly.In this special setting of IONM and thyroid surgery, avoidance of NMBA for endotracheal intubation seems not to increase the incidence of laryngeal side effects and lesions. If endotracheal intubation without NMBA is required, the authors suggest a standardized approach using induction agents as propofol and remifentanil.
EVALuna2:15058

Left-sided Gallbladder in the Era of Laparoscopic Cholecystectomy: A Single-center Experience - Velimezis, Georgios; Vassos, Nikolaos; Kapogiannatos, Georgios; Koronakis, Dimitrios; Salpiggidis, Christos; Perrakis, Evangelos; Perrakis, Aristotelis (American Surgeon, 2015)
The malposition of gallbladder under the liver segment III, defined as left-sided gallbladder (LSG), is an unexpected situation for the laparoscopic surgeon. The purpose of this study is to present our experience in treating patients with cholecystitis and LSG discovered incidentally during laparoscopic surgical procedure. Between 1993 and 2009, 5569 patients underwent laparoscopic cholecystectomy in our surgical department. Their records were reviewed and seven patients revealed having LSG (0.12%). Analysis parameters included demographic data, diagnostic methods, mode of surgery, and postoperative outcome. Mean follow-up was 140 months. Of the seven patients, five were women. Mean patient age was 56.7 years. All patients were referred to our department with clinical symptoms of classic cholelithiasis and the diagnosis was established in all of them during surgery. Laparoscopic cholecystectomy was successful in five patients, while in two patients, a conversion to open procedure was needed. A postoperative complication, i.e., biliary leakage was registered in one patient, which was treated successfully. Laparoscopic cholecystectomy is safe even in LSG, but the surgeon must consider the possibility for more anatomical anomalies, adjust the technique of dissection, and must not hesitate, if in doubt, to strive for conversion to open procedure to avoid serious complications.
EVALuna2:15182

Lehrfilm Facharztweiterbildung: Hemithyreoidektomie mit Neuromonitoring des N. laryngeus recurrens - Brunner, Maximilian; Bleichroth, Hannah; Linke, Katja; Krautz, Christian; Grützmann, Robert; Kersting, Stephan; Weber, Georg (Zentralblatt für Chirurgie, 2019)
INTRODUCTION: The mean prevalence of thyroid nodules in adults is about 20% and increases with age. Most of the thyroid nodules are benign, and are rarely malignant. However, malignancy can often only be conclusively determined after resection. Therefore, it is essential that the surgical technique should be free of complications. Despite all published minimally invasive techniques, the open procedure via a Kocher incision is still standard and commonly used in a teaching setting. This standardised technique is presented step-by-step in the video. INDICATION: Sonographic and MIBI-scintigraphic possibly malignant solitary node in the right thyroid lobe. PROCEDURE: Hemithyreoidectomy with neuromonitoring of recurrent laryngeal nerve. CONCLUSION: Hemithyroidectomy is an adequate primary therapy for a solitary possibly malignant thyroid nodule. Intraoperative neuromonitoring to identify and protect the recurrent laryngeal nerve, visualisation and protection of the parathyroid glands without compromising blood circulation and careful hemostasis are the main pillars of low risk surgery of the thyroid.
CRIS-Team Scopus Importer:2019-12-24

Length of Variable Numbers of Tandem Repeats in the Carboxyl Ester Lipase (CEL) Gene May Confer Susceptibility to Alcoholic Liver Cirrhosis but Not Alcoholic Chronic Pancreatitis - Fjeld, Karianne; Beer, Sebastian; Johnstone, Marianne; Zimmer, Constantin; Moessner, Joachim; Ruffert, Claudia; Krehan, Mario; Zapf, Christian; Njolstad, Pal Rasmus; Johansson, Stefan; Bugert, Peter; Miyajima, Fabio; et al. (PLoS ONE, 2016)
Carboxyl-ester lipase (CEL) contributes to fatty acid ethyl ester metabolism, which is implicated in alcoholic pancreatitis. The CEL gene harbours a variable number of tandem repeats (VNTR) region in exon 11. Variation in this VNTR has been linked to monogenic pancreatic disease, while conflicting results were reported for chronic pancreatitis (CP). Here, we aimed to investigate a potential association of CEL VNTR lengths with alcoholic CP.Overall, 395 alcoholic CP patients, 218 patients with alcoholic liver cirrhosis (ALC) serving as controls with a comparable amount of alcohol consumed, and 327 healthy controls from Germany and the United Kingdom (UK) were analysed by determination of fragment lengths by capillary electrophoresis. Allele frequencies and genotypes of different VNTR categories were compared between the groups.Twelve repeats were overrepresented in UK ACP patients (P = 0.04) compared to controls, whereas twelve repeats were enriched in German ALC compared to alcoholic CP patients (P = 0.03). Frequencies of CEL VNTR lengths of 14 and 15 repeats differed between German ALC patients and healthy controls (P = 0.03 and 0.008, respectively). However, in the genotype and pooled analysis of VNTR lengths no statistical significant association was depicted. Additionally, the 16-16 genotype as well as 16 repeats were more frequent in UK ALC than in alcoholic CP patients (P = 0.034 and 0.02, respectively). In all other calculations, including pooled German and UK data, allele frequencies and genotype distributions did not differ significantly between patients and controls or between alcoholic CP and ALC.We did not obtain evidence that CEL VNTR lengths are associated with alcoholic CP. However, our results suggest that CEL VNTR lengths might associate with ALC, a finding that needs to be clarified in larger cohorts.
EVALuna2:15257

Leukocytosis and neutrophilia as independent prognostic immunological biomarkers for clinical outcome in the CAO/ARO/AIO-04 randomized phase 3 rectal cancer trial - Diefenhardt, Markus; Hofheinz, Ralf Dieter; Martin, Daniel; Beißbarth, Tim; Arnold, Dirk; Hartmann, Arndt; von der Grün, Jens; Grützmann, Robert; Liersch, Torsten; Ströbel, Philipp; Grabenbauer, Gerhard G.; Rieger, Michael; et al. (International Journal of Cancer, 2019)
Peripheral blood leukocytosis and neutrophilia reflect cancer inflammation and have been proposed as prognostic immunological biomarkers in various malignancies. However, previous studies were limited by their retrospective nature and small patient numbers. Baseline peripheral blood leukocytes, neutrophils, hemoglobin, platelets, lactate dehydrogenase and carcinoembryonic antigen (CEA) were correlated with clinicopathologic characteristics, and clinical outcome in 1236 patients with rectal cancer treated with 5-FU-based preoperative chemoradiotherapy (CRT) alone or with oxaliplatin followed by surgery and adjuvant chemotherapy within the CAO/ARO/AIO-04 randomized phase 3 trial. Multivariable analyses were performed using Cox regression models. After a median follow-up of 50 months, baseline leukocytosis remained an independent adverse prognostic factor for disease-free survival (DFS; HR 1.457; 95% CI 1.163–1.825; p = 0.001), distant metastasis (HR 1.696; 95% CI 1.266–2.273; p < 0.001) and overall survival (OS; HR 1.716; 95% CI 1.264–2.329; p = 0.001) in multivariable analysis. Similar significant findings were observed for neutrophilia and high CEA levels. Conversely, treatment-induced leukopenia correlated with favorable DFS (p = 0.037), distant metastasis (p = 0.028) and OS (p = 0.012). Intriguingly, addition of oxaliplatin to 5-FU CRT resulted in a significant DFS improvement only in patients with neutrophilia and leukocytosis (p = 0.028 and p = 0.002). Our findings have important clinical implications and provide high-level evidence on the adverse prognostic role of leukocytes and neutrophils, and the impact of chemotherapy in the context of these biomarkers. These data could help guide patient stratification and should be further validated within prospective studies.
CRIS-Team Scopus Importer:2019-05-07
Keywords: clinical radiotherapeutic studies; clinical trials; colorectal cancer; molecular markers of metastasis and progression; radiochemotherapy

Leveraging medical imaging for medical education - A cinematic rendering-featured lecture - Binder, Johannes; Krautz, Christian; Engel, Klaus; Grützmann, Robert; Fellner, Franz A.; Burger, Pascal H.M.; Scholz, Michael (Annals of Anatomy-Anatomischer Anzeiger, 2018)
BACKGROUND: The integration of medical imaging into anatomical education offers advantages in understanding and learning. However, spatial orientation with conventional (2D) imaging data is challenging, and the students' ability to imagine structures in three dimensions is individual. In addition, the quality of current volume rendering methods is limited. OBJECTIVE: We tested Cinematic Rendering (CR), a novel visualization technique that provides photorealistic volume rendering, in the setting of an interactive anatomy lecture with first-year undergraduate medical and dental students. Our goal was to estimate the acceptance and positive effects CR adds to the subjects. METHODS: A total of 120 students were surveyed with specifically designed self-assessment questionnaires on the use of CR as a tool in anatomical education. RESULTS: Of 120 participating students (87 medical and 33 dental) a large majority of 95.9% (Q3) experienced CR as helpful to understand anatomy better. Overall a large majority of the students experienced CR as helpful for learning and understanding, 85% saw an improvement in anatomical education through the integration of CR (Q3-6) and could also imagine using CR as a self-study tool on an electronic device. CONCLUSION: Our undergraduate medical and dental students experienced CR as a beneficial tool for anatomical education in the chosen setting (lecture) and see further opportunities for the sensible use of this technique. Future research on the topic should include other application possibilities as well.
EVALuna2:35343

Lipomatous Solitary Fibrous Tumors Harbor Rare NAB2-STAT6 Fusion Variants and Show Up-Regulation of the Gene PPARG, Encoding for a Regulator of Adipocyte Differentiation - Haller, Florian; Schlieben, Lea D.; Ferrazzi, Fulvia; Michal, Michael; Stöhr, Robert; Moskalev, Evgeny; Bieg, Matthias; Bovée, Judith V.M.G.; Ströbel, Philip; Ishaque, Naveed; Grützmann, Robert; Meidenbauer, Norbert; et al. (American Journal of Pathology, 2021)
Solitary fibrous tumors (SFTs) harbor activating NAB2-STAT6 gene fusions. Different variants of the NAB2-STAT6 gene fusion have been associated with distinct clinicopathologic features. Lipomatous SFTs are a morphologic variant of SFTs, characterized by a fat-forming tumor component. Our aim was to evaluate NAB2-STAT6 fusion variants and to further study the molecular genetic features in a cohort of lipomatous SFTs. A hybrid-capture–based next-generation sequencing panel was employed to detect NAB2-STAT6 gene fusions at the RNA level. In addition, the RNA expression levels of 507 genes were evaluated using this panel, and were compared with a control cohort of nonlipomatous SFTs. Notably, 5 of 11 (45%) of lipomatous SFTs in the current series harbored the uncommon NAB2 exon 4–STAT6 exon 4 gene fusion variant, which is observed in only 0.9% to 1.4% of nonlipomatous SFTs. Furthermore, lipomatous SFTs displayed significant differences in gene expression compared with their nonlipomatous counterparts, including up-regulation of the gene peroxisome proliferator activated receptor-γ (PPARG). Peroxisome proliferator activated receptor-γ is a nuclear receptor regulating adipocyte differentiation, providing a possible explanation for the fat-forming component in lipomatous SFTs. In summary, the current study provides a possible molecular genetic basis for the distinct morphologic features of lipomatous SFTs.
CRIS-Team Scopus Importer:2021-06-04

Liposomal doxorubicin in the treatment of AIDS-associated Kaposi's sarcoma: clinical, histological and cell biological evaluation. - Stürzl, Michael; Zietz, Christian; Eisenburg, B; Goebel, F D; Gillitzer, R; Hofschneider, Peter Hans; Bogner, J. R. (RES VIROLOGY, 1994)
AIDS-associated Kaposi's sarcoma (KS) in eight patients was treated with the systemic application of liposomal doxorubicin (20 mg/m2 per cycle). After six cycles of treatment a significant regression of KS was observed in all patients. Tumour volume was reduced from 556 +/- 635 mm3 before therapy to 42 +/- 134 mm3 after therapy as determined by ultrasonography of selected tumours. Histological examination revealed a reduction of tumour-like structures and the absence of KS spindle cells in involved areas after therapy. In vitro experiments with KS-derived cell cultures, which most likely represent the KS spindle cells, suggested that liposomal doxorubicin may cause regression of KS via two different mechanisms: (i) by highly specific inhibition of KS spindle cell proliferation and (ii) by induction of monocyte chemoattractant protein-1 expression in KS spindle cells, which may result in increased recruitment of phagocytic cells (monocytes/macrophages) into the lesions. A cooperative action of both mechanisms may explain the high efficacy of liposomal doxorubicin in the treatment of AIDS-KS.
Keywords: AIDS; Kaposi's sarcoma; Doxorubicin; Liposome Therapy; Spindle cells; Monocyte chemoattractant protein-1

Local therapy for cancer: Also an important pillar of precision medicine in oncology Lokale Tumortherapie: Auch eine wichtige Säule der Präzisionsmedizin in der Onkologie - Guckenberger, Matthias; Grützmann, Robert; Ricke, Jens; Schmidberger, H. (Onkologe, 2020)
CRIS-Team Scopus Importer:2020-09-04

Long-term efficacy of NASHA Dx injection therapy for treatment of fecal incontinence - Mellgren, A.; Matzel, Klaus; Pollack, J.; Hull, T.; Bernstein, M.; Graf, W. (Neurogastroenterology and Motility, 2014)
Injectable bulking treatment for fecal incontinence (FI) is intended to expand tissue in the anal canal and prevent fecal leakage. Use of injectable bulking agents is increasing because it can be performed in an outpatient setting and with low risk for morbidity. This study evaluated the long-term (36-month) clinical effectiveness and safety of injection of non-animal stabilized hyaluronic acid/dextranomer (NASHA Dx) on FI symptoms.In a prospective multicenter trial, 136 patients with FI received the NASHA Dx bulking agent. Treatment success defined as a reduction in number of FI episodes by 50% or more compared with baseline (Responder50 ). Change from baseline in Cleveland Clinic Florida Fecal Incontinence Score (CCFIS) and Fecal Incontinence Quality of Life Scale (FIQL), and adverse events were also evaluated.Successful decrease in symptoms was achieved in 52% of patients at 6 months and this was sustained at 12 months (57%) and 36 months (52%). Mean CCFIS decreased from 14 at baseline to 11 at 36 months (p < 0.001). Quality-of-life scores for all four domains improved significantly between baseline and 36 months of follow-up. Severe adverse events were rare and most adverse events were transient and pertained to minor bleeding and pain or discomfort.Submucosal injection of NASHA Dx provided a significant improvement of FI symptoms in a majority of patients and this effect was stable during the course of the follow-up and maintained for 3 years.
EVALuna2:15171

Long-term outcome of sacral neuromodulation for chronic refractory constipation - Maeda, Yasuko; Kamm, Michael A.; Vaizey, Carolynne J.; Matzel, Klaus; Johansson, Claes; Rosen, Harald; Baeten, Cornelius G.; Laurberg, Soren (Techniques in Coloproctology, 2017)
Sacral neuromodulation has been reported as a treatment for severe idiopathic constipation. This study aimed to evaluate the long-term effects of sacral neuromodulation by following patients who participated in a prospective, open-label, multicentre study up to 5 years.Patients were followed up at 1, 3, 6, 12, 24, 36, 48 and 60 months. Symptoms and quality of life were assessed using bowel diary, the Cleveland Clinic constipation score and the Short Form-36 quality-of-life scale.Sixty-two patients (7 male, median age 40 years) underwent test stimulation, and 45 proceeded to permanent implantation. Twenty-seven patients exited the study (7 withdrawn consent, 7 loss of efficacy, 6 site-specific reasons, 4 withdrew other reasons, 2 lost to follow-up, 1 prior to follow-up). Eighteen patients (29%) attended 60-month follow-up. In 10 patients who submitted bowel diary, their improvement of symptoms was sustained: the number of defecations per week (4.1 ± 3.7 vs 8.1 ± 3.4, mean ± standard deviation, p < 0.001, baseline vs 60 months) and sensation of incomplete emptying (0.8 ± 0.3 vs 0.2 ± 0.1, p = 0.002). In 14 patients (23%) with Cleveland Clinic constipation score, improvement was sustained at 60 months [17.9 ± 4.4 (baseline) to 10.4 ± 4.1, p < 0.001]. Some 103 device-related adverse events were reported in 27 (61%).Benefit from sacral neuromodulation in the long-term was observed in a small minority of patients with intractable constipation. The results should be interpreted with caution given the high dropout and complication rate during the follow-up period.
EVALuna2:15316

Long-term outcomes of sacral nerve stimulation for faecal incontinence - Altomare, D. F.; Giuratrabocchetta, S.; Knowles, C. H.; Munoz Duyos, A.; Robert-Yap, J.; Matzel, Klaus (British Journal of Surgery, 2015)
Sacral nerve stimulation (SNS) has proven short- to medium-term effectiveness for the treatment of faecal incontinence (FI); fewer long-term outcomes have been presented and usually in small series. Here, the long-term effectiveness of SNS was evaluated in a large European cohort of patients with a minimum of 5 years' follow-up.Prospectively registered data from patients with FI who had received SNS for at least 5 years from ten European centres were collated by survey. Daily stool diaries, and Cleveland Clinic and St Mark's incontinence scores were evaluated at baseline, after implantation and at the last follow-up. SNS was considered successful when at least 50 per cent symptom improvement was maintained at last follow-up.A total of 407 patients underwent temporary stimulation, of whom 272 (66·8 per cent) had an impulse generator implanted; 228 (56·0 per cent) were available for long-term follow-up at a median of 84 (i.q.r. 70-113) months. Significant reductions in the number of FI episodes per week (from median 7 to 0·25) and summative symptom scores (median Cleveland Clinic score from 16 to 7, St Mark's score from 19 to 6) were recorded after implantation (all P < 0·001) and maintained in long-term follow-up. In per-protocol analysis, long-term success was maintained in 71·3 per cent of patients and full continence was achieved in 50·0 per cent; respective values based on intention-to-treat analysis were 47·7 and 33·4 per cent. Predictive analyses determined no significant association between pretreatment variables and successful outcomes. Risk of long-term failure correlated with minor symptom score improvement during the temporary test phase.SNS remains an effective treatment for FI in the long term for approximately half of the patients starting therapy.
EVALuna2:15198

Long-term tumor-free survival in a metastatic pancreatic carcinoma patient with FOLFIRINOX/Mitomycin, high-dose, fever inducing Viscum album extracts and subsequent R0 resection: A case report - Werthmann, Paul Georg; Inter, Pia; Welsch, Thilo; Sturm, Anne-Kathrin; Grützmann, Robert; Debus, Markus; Sterner, Martin-Guenther; Kienle, Gunver Sophia (Medicine, 2018)
RATIONALE: Metastatic pancreatic cancer has a dismal prognosis. Many patients seek integrative care as an add-on to their conventional cancer treatment. Viscum album extracts (VAE)-widely used as an adjunct to cancer treatment-have cytotoxic, apoptogenic, and immune stimulatory properties. A statistically significant survival benefit has been demonstrated for VAE in advanced pancreatic cancer. PATIENT CONCERNS AND DIAGNOSIS: A 28-year old patient presented with painless jaundice and was subsequently diagnosed as pancreatic adenocarcinoma with liver metastases. INTERVENTIONS: He was treated with FOLFIRINOX/Mitomycin, hyperthermia and fever-inducing VAE. OUTCOMES: Subsequently, the liver metastases regressed. Surgical intervention involved successful R0-resection of the primary tumor, as well as an atypical liver resection. A relapse was again treated with FOLFIRINOX/Mitomycin and hyperthermia. As of publication of this report, 49 months after initial diagnosis, the patient exhibits good condition, and is unrestricted in quality of life (till publication). LESSONS: This case demonstrates the favorable outcome of a patient with metastatic pancreatic cancer following treatment with chemotherapy, integrative medicine, and surgical excision. As other positive outcomes in pancreatic cancer patients are related to inflammatory events, we presume the immunologic effects of VAE to have contributed to the favorable outcome here. Based on this case, and the other positive results of VAE use in pancreatic cancer, further investigations seem highly worthwhile.
EVALuna2:210703

Loss of IFN-gamma pathway gene expression in tumor cells as mechanism of immune escape of colorectal carcinoma - Britzen-Laurent, Nathalie; Straube, Julia; Waldner, Maximilian; Becker, Christoph; Croner, Roland; Pilarsky, Christian; Merkel, Susanne; Stürzl, Michael (CANCER RESEARCH, 2018)
CRIS-Team WoS Importer:2019-06-18

Low anterior resection syndrome and quality of life: an international multicenter study - Juul, Therese; Ahlberg, Madelene; Biondo, Sebastiano; Espin, Eloy; Jimenez, Luis Miguel; Matzel, Klaus; Palmer, Gabriella Jansson; Sauermann, Anna Catherin; Trenti, Loris; Zhang, Wei; Laurberg, Soren; Christensen, Peter (Diseases of the colon & rectum, 2014)
An increasing number of patients are surviving a diagnosis of rectal cancer. The majority of the patients are treated with the sphincter-sparing surgical procedure low anterior resection, and 50% to 90% of these patients experience bowel dysfunction, known as the low anterior resection syndrome. No previous studies have investigated the association between the low anterior resection syndrome and quality of life in an international setting with the use of a validated instrument for the classification of the low anterior resection syndrome.The aim of this study was to investigate the association between quality of life and the low anterior resection syndrome in European patients who have had rectal cancer.The study was designed as an international cross-sectional study involving 5 centers in 4 European countries.All patients had undergone low anterior resection for rectal cancer, had no stoma, had no dissemination or recurrence at the time of the study, and were at least 16 months past surgery.The patients received by mail the Low Anterior Resection Syndrome Score and the quality-of-life questionnaire EORTC QLQ-C30.Eight subscales were selected to be the focus of this study: global quality of life; physical, role, emotional, and social functioning; fatigue; constipation; and diarrhea.A total of 796 patients were included, which corresponds to a response rate of 75.0%. In comparison with patients without low anterior resection syndrome, patients with major low anterior resection syndrome fared substantially worse in all selected subscales (difference >= 10 points, p < 0.01), with the exception of constipation.The cross-sectional design prevents an evaluation of causality.The quality of life of patients who have had rectal cancer is closely associated with the severity of the low anterior resection syndrome. Therefore, it is important that clinicians and researchers focus on this syndrome to improve the prevention and the treatment of bowel dysfunction and the information given to patients.
EVALuna2:15166

Low-Dose CT Fluoroscopy-Guided Drainage of Deep Pelvic Fluid Collections after Colorectal Cancer Surgery: Technical Success, Clinical Outcome and Safety in 40 Patients - Stahl, Robert; Seidensticker, Max; De Figueiredo, Giovanna Negrao; Pedersen, Vera; Crispin, Alexander; Forbrig, Robert; Ozpeynirci, Yigit; Liebig, Thomas; D'Anastasi, Melvin; Hackner, Danilo; Trumm, Christoph G. (Diagnostics, 2023)
Purpose: To assess the technical (TS) and clinical success (CS) of CT fluoroscopy-guided drainage (CTD) in patients with symptomatic deep pelvic fluid collections following colorectal surgery. Methods: A retrospective analysis (years 2005 to 2020) comprised 43 drain placements in 40 patients undergoing low-dose (10–20 mA tube current) quick-check CTD using a percutaneous transgluteal (n = 39) or transperineal (n = 1) access. TS was defined as sufficient drainage of the fluid collection by ≥50% and the absence of complications according to the Cardiovascular and Interventional Radiological Society of Europe (CIRSE). CS comprised the marked reduction of elevated laboratory inflammation parameters by ≥50% under minimally invasive combination therapy (i.v. broad-spectrum antibiotics, drainage) within 30 days after intervention and no surgical revision related to the intervention required. Results: TS was gained in 93.0%. CS was obtained in 83.3% for C-reactive Protein and in 78.6% for Leukocytes. In five patients (12.5%), a reoperation due to an unfavorable clinical outcome was necessary. Total dose length product (DLP) tended to be lower in the second half of the observation period (median: years 2013 to 2020: 544.0 mGy*cm vs. years 2005 to 2012: 735.5 mGy*cm) and was significantly lower for the CT fluoroscopy part (median: years 2013 to 2020: 47.0 mGy*cm vs. years 2005 to 2012: 85.0 mGy*cm). Conclusions: Given a minor proportion of patients requiring surgical revision due to anastomotic leakage, the CTD of deep pelvic fluid collections is safe and provides an excellent technical and clinical outcome. The reduction of radiation exposition over time can be achieved by both the ongoing development of CT technology and the increased level of interventional radiology (IR) expertise.
CRIS-Team Scopus Importer:2023-03-10
Keywords: clinical outcome; colorectal surgery; CT-guided drainage; pelvic fluid collection; technical outcome

Low-Milliampere CT Fluoroscopy-Guided Percutaneous Drainage Placement after Pancreatic Surgery: Technical and Clinical Outcome in 133 Consecutive Patients during a 14-Year Period - Trumm, Christoph G.; Hackner, Danilo; Badmann, Katharina; Crispin, Alexander; Forbrig, Robert; Ozpeynirci, Yigit; Kuppinger, David; Pedersen, Vera; Liebig, Thomas; Stahl, Robert (Diagnostics, 2022)
(1) Purpose: To retrospectively assess the technical and clinical outcome of patients with symptomatic postoperative fluid collections after pancreatic surgery, treated with CT-guided drainage (CTD). (2) Methods: 133 eligible patients between 2004 and 2017 were included. We defined technical success as the sufficient drainage of the fluid collection(s) and the absence of peri-interventional complications (minor or major according to SIR criteria). Per definition, clinical success was characterized by normalization of specific blood parameters within 30 days after the intervention or a decrease by at least 50% without requiring additional surgical revision. C-reactive protein (CRP), Leukocytes, Interleukin-6, and Dose length product (DLP) for parts of the intervention were determined. (3) Results: 97.0% of 167 interventions were technically successful. Clinical success was achieved in 87.5% of CRP, in 78.4% of Leukocytes, and in 87.5% of Interleukin-6 assessments. The median of successful decrease was 6 days for CRP, 5 days for Leukocytes, and 2 days for Interleukin-6. No surgical revision was necessary in 93.2%. DLP was significantly lower in the second half of the observation period (total DLP: median 621.5 mGy*cm between 2011-2017 vs. median 944.5 mGy*cm between 2004-2010). (4) Conclusions: Technical success rate of CTD was very high and the clinical success rate was fair to good. Given an elderly and multimorbid patient cohort, CTD can have a temporizing effect in the postoperative period after pancreatic surgery. Reducing the radiation dose over time might reflect developments in CT technology and increased experience of interventional radiologists.
CRIS-Team WoS Importer:2022-09-30

Machine Learning-Supported Diagnosis of Small Blue Round Cell Sarcomas Using Targeted RNA Sequencing. - Schlieben, Lea D.; Carta, Maria Giulia; Moskalev, Evgeny; Stöhr, Robert; Metzler, Markus; Besendörfer, Manuel; Meidenbauer, Norbert; Semrau, Sabine; Janka, Rolf Matthias; Grützmann, Robert; Wiemann, Stefan; Hartmann, Arndt; et al. (Journal of Molecular Diagnostics, 2024)
Small blue round cell sarcomas (SBRCSs) are a heterogeneous group of tumors with overlapping morphologic features but markedly varying prognosis. They are characterized by distinct chromosomal alterations, particularly rearrangements leading to gene fusions, whose detection currently represents the most reliable diagnostic marker. Ewing sarcomas are the most common SBRCSs, defined by gene fusions involving EWSR1 and transcription factors of the ETS family, and the most frequent non-EWSR1-rearranged SBRCSs harbor a CIC rearrangement. Unfortunately, currently the identification of CIC::DUX4 translocation events, the most common CIC rearrangement, is challenging. Here, we present a machine-learning approach to support SBRCS diagnosis that relies on gene expression profiles measured via targeted sequencing. The analyses on a curated cohort of 69 soft-tissue tumors showed markedly distinct expression patterns for SBRCS subgroups. A random forest classifier trained on Ewing sarcoma and CIC-rearranged cases predicted probabilities of being CIC-rearranged >0.9 for CIC-rearranged-like sarcomas and <0.6 for other SBRCSs. Testing on a retrospective cohort of 1335 routine diagnostic cases identified 15 candidate CIC-rearranged tumors with a probability >0.75, all of which were supported by expert histopathologic reassessment. Furthermore, the multigene random forest classifier appeared advantageous over using high ETV4 expression alone, previously proposed as a surrogate to identify CIC rearrangement. Taken together, the expression-based classifier can offer valuable support for SBRCS pathologic diagnosis.
EVALuna2:565265

Malignant progression of invasive tumour cells seen in hypoxia present an accumulation of β-catenin in the nucleus at the tumour front - Demir, Resit; Dimmler, Arno; Naschberger, Elisabeth; Demir, Ilknur; Papadopoulos, Thomas; Melling, Nathaniel; Stürzl, Michael; Hohenberger, Werner (Experimental and Molecular Pathology, 2009)
Of all processes involved in tumour progression, local invasion and formation of metastases are the clinically most relevant but the scientifically least well understood at their molecular level. The loss of cell adhesion, then tumour cell migration with changes in the cytoskeleton, invasion and metastatic dissemination are the steps of the "metastatic cascade". The E-cadherin-catenin complex plays a key role in cell adhesion thus building the first step in malignant progression. In many epithelial cancers, E-cadherin is lost concomitantly with tumour progression. Thus β-catenin dissociates in the cytoplasm and accumulates in the nucleus as a transcription factor. Recent experimental progress has identified that tumour hypoxia not only induces tumour angiogenesis, but also modulates malignant progression to initiate tumour invasion and metastasis. It was hypothesised that hypoxia within tumours causes dysfunction of the E-cadherin-catenin complex with an accumulation of β-catenin in the nucleus and produces an invasive phenotype of tumour cells. For this purpose fertilized chicken eggs were incubated for ten days in normoxic conditions. Subsequently colon carcinoma cells (SW-480) were placed on the chorioallantoic membrane. During the following six days the eggs were incubated either in normoxic conditions or in stepwise decreasing hypoxic conditions. SW-480 colon carcinoma cells did not invade the epithelial layer in normoxic conditions. β-catenin was membrane bound or in the cytoplasm. The nuclei were regularly omitted. In contrast, an invasion through the epithelial layer into the mesoderm was already seen after three days when incubated in hypoxic conditions. β-catenin was membrane bound in non-invasive regions of the tumour nodule but there was an accumulation of β-catenin in the nucleus in the invasive tumour front. Hypoxia seems to be responsible for accumulation of β-catenin in the nucleus which is accompanied by a more invasive phenotype of tumour cells at the tumour front. © 2009 Elsevier Inc. All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: Beta-Catenin; Chorioallantoic membrane; Hypoxia; Malignant progression

Management of clinically relevant postpancreatectomy hemorrhage (PPH) over two decades - A comparative study of 1 450 consecutive patients undergoing pancreatic resection - Wolk, Steffen; Grützmann, Robert; Rahbari, Nuh N.; Hoffmann, Ralf T.; Plodeck, Verena; Weitz, Juergen; Welsch, Thilo; Distler, Marius (Pancreatology, 2017)
PPH is the main cause of mortality (up to 50%) after pancreatic resection. Due to differences in time of onset, localization and clinical impairment, there is no consistent management algorithm.Between 1994 and 2014 the occurrence of PPH in 115 out of 1 450 patients from a prospectively collected database was analyzed. The cohort was divided into two time periods: 1994-2009 and 2010-2014. The differences between the two groups were analyzed.The overall incidence of PPH was 7.9%. The main causes of hemorrhage were the pancreatic anastomosis (31.1%) and the splanchnic arteries (23.5%). In the first period, there were more anastomotic hemorrhages (40.0% vs. 20.4%, p = 0.02), while in the second period more hemorrhages from the splanchnic arteries occurred (12.3% vs. 37%, p = 0.002). Bleeding control was achieved by relaparotomy (45.7%), noninterventionally (22.8%), endoscopically (19.7%) and angiographically (13.4%). In the second period, the relevance of interventional angiography significantly increased (24.6% vs. 4.3%, p = 0.001), whereas endoscopy lost importance (7% vs. 30%, p = 0.001). The in-hospital case fatality rate after PPH was 27.4%, with higher case fatality rate following extraluminal hemorrhage (23.9% vs. 3.4%, p < 0.001).A shift in the management of PPH could be seen over the two periods. Interventional angiography has gained more importance in the treatment of severe extraluminal hemorrhage of the splanchnic arteries. Adequate treatment of PPH is crucial to improve the outcome.
EVALuna2:15302

Management of Complications of Pancreatic Anastomoses - Schmid, Axel; Uder, Michael; Grützmann, Robert; Weber, Georg (Zentralblatt für Chirurgie, 2017)
Background The pancreatic anastomosis may be the Achilles heel in pancreatic surgery. When a postoperative pancreatic fistula develops, be it mild or severe, in some cases life-threatening, POPF-associated complications can occur. Objectives Possibilities for the prophylaxis, diagnosis and therapy of POPF and POPF-associated complications in an interdisciplinary setting. Results Differentiated diagnostic and therapeutic management of POPF grade A - C is supported by recent studies to reduce morbidity and mortality. Depending on time and severity of POPF and POPF-associated complications, a conservative/interventional or surgical approach is indicated. Conclusion With the precise classification of POPF and POPF-associated complications, interdisciplinary diagnostic and therapeutic management can reduce morbidity and mortality after pancreatic surgery.
EVALuna2:15303

Management of Fecal Incontinence: Surgical Treatment Options - Bittorf, Birgit; Matzel, Klaus (Visceral Medicine, 2024)
Background: Fecal incontinence (FI) is a frequent, often underestimated, health issue in adults. Its treatment is primarily nonsurgical. Only if conservative options fail to result in adequate symptom reduction should surgery be considered. We present an overview of historical and current surgical treatment options. Summary: Well-known sphincter replacement techniques such as dynamic graciloplasty and the artificial bowel sphincter are no longer used because of their invasiveness and relevant comorbidity. Today, sphincteroplasty and sacral neuromodulation (SNM) are the most common procedures recommended in current guidelines. The therapeutic choice is based on diagnostic findings. Sphincteroplasty is an option only in patients with an anal sphincter lesion and has only moderate long-Term success. SNM has become the established first choice in multiple pathophysiological conditions resulting in FI, as it has proved highly successful with minimal invasiveness. Over time, the spectrum of indications has evolved and the technique is now successful in morphological sphincter defects as well. Key Messages: The spectrum of surgical options to treat FI is limited. Owing to its efficacy and low comorbidity, SNM is now considered the gold standard in multiple pathophysiological and morphological conditions, whereas sphincteroplasty remains an option in patients with FI from a defined sphincter lesion.
CRIS-Team Scopus Importer:2024-11-08
Keywords: Fecal incontinence; Sacral neuromodulation; Sphincteroplasty

Maternal HIV type 1 infection suppresses MMP-1 expression in endothelial cells of uninfected newborns: Non viral vertical transmission of HIV type 1-related effects - Naschberger, Elisabeth; Stürzl, Michael; et al. (Aids Research and Human Retroviruses, 2005)
HIV-1 infection is associated with vascular alterations. This is accompanied by an increased risk of cardiovascular diseases and Kaposi's sarcoma, an endothelial cell-derived tumor. We investigated the impact of maternal HIV-1 infection on phenotype and gene expression of endothelial cells in newborns. For this reason endothelial precursor cells and differentiated endothelial cells were isolated from cord blood as well as from umbilical veins and arteries of noninfected infants born to HIV-1-infected (H-group) and noninfected (N-group) mothers. No apparent differences in proliferation, capillary formation, and expression of endothelial cell markers were detected in these cells. Interestingly, the expression of matrix metalloproteinase was repressed significantly (χ2 analysis, p < 0.002) and consistently at the RNA, the protein, and the secretory levels in the H-group as compared to the N-group. Neither treatment with zidovudine (AZT), mutations in the matrix metalloproteinase-1 (MMP-1) promoter, nor epigenetic changes in the promoter methylation pattern were responsible for the repression of MMP-1 expression in H-group endothelial cells. The reduced MMP-1 expression may contribute to the impaired cardiac function that has been observed in children of HIV-1-infected women. Most interestingly, our findings indicate that HIV-1-related effects can be transferred from mother to child in the absence of HIV-1 transmission. © Mary Ann Liebert, Inc.
Created from Fastlane, Scopus look-up

Matricellular Protein SPARCL1 Regulates Blood Vessel Integrity and Antagonizes Inflammatory Bowel Disease - Regensburger, Daniela; Tenkerian, Clara; Pürzer, Victoria; Schmid, Benjamin; Wohlfahrt, Thomas; Stolzer, Iris; Lopez Posadas, Rocío; Günther, Claudia; Waldner, Maximilian; Becker, Christoph; Sticht, Heinrich; Petter, Katja; et al. (Inflammatory Bowel Diseases, 2021)
Background The understanding of vascular plasticity is key to defining the role of blood vessels in physiologic and pathogenic processes. In the present study, the impact of the vascular quiescence marker SPARCL1 on angiogenesis, capillary morphogenesis, and vessel integrity was evaluated. Methods Angiogenesis was studied using the metatarsal test, an ex vivo model of sprouting angiogenesis. In addition, acute and chronic dextran sodium sulfate colitis models with SPARCL1 knockout mice were applied. Results This approach indicated that SPARCL1 inhibits angiogenesis and supports vessel morphogenesis and integrity. Evidence was provided that SPARCL1-mediated stabilization of vessel integrity counteracts vessel permeability and inflammation in acute and chronic dextran sodium sulfate colitis models. Structure-function analyses of purified SPARCL1 identified the acidic domain of the protein necessary for its anti-angiogenic activity. Conclusions Our findings inaugurate SPARCL1 as a blood vessel–derived anti-angiogenic molecule required for vessel morphogenesis and integrity. SPARCL1 opens new perspectives as a vascular marker of susceptibility to colitis and as a therapeutic molecule to support blood vessel stability in this disease. <br
Keywords: angiogenesis; blood vessel; DSS colitis; endothelial cell; inflammatory bowel disease; permeability; SPARCL1

Matricellular protein SPARCL1 regulates tumor microenvironment-dependent endothelial cell heterogeneity in colorectal carcinoma - Naschberger, Elisabeth; Liebl, Andrea; Schellerer, Vera; Schütz, Manuela; Britzen-Laurent, Nathalie; Kölbel, Patrick; Schaal, Ute; Haep, Lisa; Regensburger, Daniela; Wittmann, Thomas; Klein-Hitpass, Ludger; Rau, Tilman; et al. (Journal of Clinical Investigation, 2016)
Different tumor microenvironments (TMEs) induce stromal cell plasticity that affects tumorigenesis. The impact of TME-dependent heterogeneity of tumor endothelial cells (TECs) on tumorigenesis is unclear. Here, we isolated pure TECs from human colorectal carcinomas (CRCs) that exhibited TMEs with either improved (Th1-TME CRCs) or worse clinical prognosis (control-TME CRCs). Transcriptome analyses identified markedly different gene clusters that reflected the tumorigenic and angiogenic activities of the respective TMEs. The gene encoding the matricellular protein SPARCL1 was most strongly upregulated in Th1-TME TECs. It was also highly expressed in ECs in healthy colon tissues and Th1-TME CRCs but low in control-TME CRCs. In vitro, SPARCL1 expression was induced in confluent, quiescent ECs and functionally contributed to EC quiescence by inhibiting proliferation, migration, and sprouting, whereas siRNA-mediated knockdown increased sprouting. In human CRC tissues and mouse models, vessels with SPARCL1 expression were larger and more densely covered by mural cells. SPARCL1 secretion from quiescent ECs inhibited mural cell migration, which likely led to stabilized mural cell coverage of mature vessels. Together, these findings demonstrate TME-dependent intertumoral TEC heterogeneity in CRC. They further indicate that TEC heterogeneity is regulated by SPARCL1, which promotes the cell quiescence and vessel homeostasis contributing to the favorable prognoses associated with Th1-TME CRCs.
EVALuna2:6838

Mbd2 enables tumourigenesis within the intestine while preventing tumour-promoting inflammation - May, Stephanie; Owen, Heather; Phesse, Toby J.; Greenow, Kirsty R.; Jones, Gareth-Rhys; Blackwood, Adam; Cook, Peter C.; Towers, Christopher; Gallimore, Awen M.; Williams, Geraint T.; Stürzl, Michael; Britzen-Laurent, Nathalie; et al. (Journal of Pathology, 2018)
Epigenetic regulation plays a key role in the link between inflammation and cancer. Here we examine Mbd2, which mediates epigenetic transcriptional silencing by binding to methylated DNA. In separate studies the Mbd2-/- mouse has been shown (1) to be resistant to intestinal tumourigenesis and (2) to have an enhanced inflammatory/immune response, observations that are inconsistent with the links between inflammation and cancer. To clarify its role in tumourigenesis and inflammation, we used constitutive and conditional models of Mbd2 deletion to explore its epithelial and non-epithelial roles in the intestine. Using a conditional model, we found that suppression of intestinal tumourigenesis is due primarily to the absence of Mbd2 within the epithelia. Next, we demonstrated, using the DSS colitis model, that non-epithelial roles of Mbd2 are key in preventing the transition from acute to tumour-promoting chronic inflammation. Combining models revealed that prior to inflammation the altered Mbd2-/- immune response plays a role in intestinal tumour suppression. However, following inflammation the intestine converts from tumour suppressive to tumour promoting. To summarise, in the intestine the normal function of Mbd2 is exploited by cancer cells to enable tumourigenesis, while in the immune system it plays a key role in preventing tumour-enabling inflammation. Which role is dominant depends on the inflammation status of the intestine. As environmental interactions within the intestine can alter DNA methylation patterns, we propose that Mbd2 plays a key role in determining whether these interactions are anti- or pro-tumourigenic and this makes it a useful new epigenetic model for inflammation-associated carcinogenesis. © 2018 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.
EVALuna2:210709

Mechanism of GTPase-activity-induced self-assembly of human guanylate binding protein 1. - Voepel, Tobias; Syguda, Adrian; Britzen-Laurent, Nathalie; Kunzelmann, Simone; Luedemann, Maik-Borris; Dovengerds, Christine; Stürzl, Michael; Herrmann, Christian (Journal of Molecular Biology, 2010)
Human guanylate binding protein 1 (hGBP1) belongs to the dynamin superfamily of large GTPases (LGs). In the course of GTP hydrolysis, the protein undergoes structural changes leading to self-assembly of the protein, which is a characteristic property of all family members. For self-assembly, the protein employs two distinct interaction sites, one of which is located within the LG domain of the protein located at the N-terminus, and the second is located in the C-terminal alpha-helical domain. Here, we identify intramolecular contacts between the LG domain and the helical part of hGBP1, which relay nucleotide-dependent structural changes from the N-terminus to the C-terminus and thereby mediate tetramer formation of the protein through a second contact site at the C-terminus. Furthermore, we demonstrate the impact of this intramolecular communication on the enzymatic activity of hGBP1 and on its cellular localization.

Mechanism of paclitaxel activity in Kaposi's sarcoma. - Sgadari, Cecilia; Toschi, Elena; Palladino, Clelia; Barillari, Giovanni; Carlei, Davide; Cereseto, Anna; Ciccolella, Cristiana; Yarchoan, Robert; Monini, Paolo; Stürzl, Michael; Ensoli, Barbara (Journal of Immunology, 2000)
Kaposi's sarcoma (KS) is an angioproliferative disease characterized by proliferation of spindle-shaped cells predominantly of endothelial cell origin, neoangiogenesis, inflammatory cell infiltration, and edema. At least in early stage, KS behaves as a reactive lesion sustained by the action of inflammatory cytokines and growth factors, has a polyclonal nature, and can regress. However, in time it can become monoclonal, especially in the nodular stage, evolving into a true sarcoma, likely in association with the increased expression of antiapoptotic oncogenes. We have recently demonstrated by immunohistochemical analysis that Bcl-2, a proto-oncogene known to prolong cellular viability and to antagonize apoptosis, is highly expressed in spindle cells and vessels of both AIDS-KS and classical KS lesions and that its expression increases with lesion stage. Paclitaxel, a microtubule-stabilizing drug known to inhibit Bcl-2 antiapoptotic activity and to be highly effective in the treatment of certain neoplasms, has recently been found to be active also in patients with advanced HIV-associated KS. In this report we investigated the mechanism(s) of paclitaxel activity in KS. By using a model of experimental KS induced by the inoculation of KS-derived spindle cells in nude mice and primary cultures of KS spindle cells, we found that paclitaxel promotes regression of KS lesions in vivo and that it blocks the growth, migration, and invasion of KS cells in vitro. Furthermore, paclitaxel treatment promoted apoptosis and down-regulated Bcl-2 protein expression in KS cells in vitro and in KS-like lesions in mice. Our results suggest that paclitaxel interferes with KS by down-regulating Bcl-2 antiapoptotic effect.

MED12 loss activates endogenous retroelements to sensitise immunotherapy in pancreatic cancer - Tang, Yingying; Tang, Shijie; Yang, Wenjuan; Zhang, Zhengyan; Wang, Teng; Wu, Yuyun; Xu, Junyi; Pilarsky, Christian; Mazzone, Massimiliano; Wang, Lei Wei; Sun, Yongwei; Tian, Ruijun; et al. (Gut, 2024)
Objective Pancreatic ductal adenocarcinoma (PDAC) stands as one of the most lethal cancers, marked by its lethality and limited treatment options, including the utilisation of checkpoint blockade (ICB) immunotherapy. Epigenetic dysregulation is a defining feature of tumourigenesis that is implicated in immune surveillance, but remains elusive in PDAC. Design To identify the factors that modulate immune surveillance, we employed in vivo epigenetic-focused CRISPR-Cas9 screen in mouse PDAC tumour models engrafted in either immunocompetent or immunodeficient mice. Results Here, we identified MED12 as a top hit, emerging as a potent negative modulator of immune tumour microenviroment (TME) in PDAC. Loss of Med12 significantly promoted infiltration and cytotoxicity of immune cells including CD8+ T cells, natural killer (NK) and NK1.1+ T cells in tumours, thereby heightening the sensitivity of ICB treatment in a mouse model of PDAC. Mechanistically, MED12 stabilised heterochromatin protein HP1A to repress H3K9me3-marked endogenous retroelements. The derepression of retrotransposons induced by MED12 loss triggered cytosolic nucleic acid sensing and subsequent activation of type I interferon pathways, ultimately leading to robust inflamed TME . Moreover, we uncovered a negative correlation between MED12 expression and immune resposne pathways, retrotransposon levels as well as the prognosis of patients with PDAC undergoing ICB therapy. Conclusion In summary, our findings underscore the pivotal role of MED12 in remodelling immnue TME through the epigenetic silencing of retrotransposons, offering a potential therapeutic target for enhancing tumour immunogenicity and overcoming immunotherapy resistance in PDAC.
CRIS-Team Scopus Importer:2024-09-27

Meeting Medical Need - Development of a High-Throughput Assay Using Pancreatic Cancer Patient Derived Organoids as a Tool for Personalized Medicine - Sankarasubramanian, Sushmitha; Niethard, Maya; Pilarsky, Christian; Regenbrecht, Christian; Wedeken, Lena (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-12-16

Melanocytes as an emerging key player in niche regulation of limbal stem cells - Schlötzer-Schrehardt, Ursula; Polisetti, Naresh; Zenkel, Matthias; Naschberger, Elisabeth; Heger, Lukas; Dudziak, Diana; Stürzl, Michael; Kruse, Friedrich (2018)
EVALuna2:34738

Metabolic biomarker signature to differentiate pancreatic ductal adenocarcinoma from chronic pancreatitis - Mayerle, Julia; Kalthoff, Holger; Reszka, Regina; Kamlage, Beate; Peter, Erik; Schniewind, Bodo; Maldonado, Sandra González; Pilarsky, Christian; Heidecke, Claus Dieter; Schatz, Philipp; Distler, Marius; Scheiber, Jonas A.; et al. (Gut, 2017)
Current non-invasive diagnostic tests can distinguish between pancreatic cancer (pancreatic ductal adenocarcinoma (PDAC)) and chronic pancreatitis (CP) in only about two thirds of patients. We have searched for blood-derived metabolite biomarkers for this diagnostic purpose.For a case-control study in three tertiary referral centres, 914 subjects were prospectively recruited with PDAC (n=271), CP (n=282), liver cirrhosis (n=100) or healthy as well as non-pancreatic disease controls (n=261) in three consecutive studies. Metabolomic profiles of plasma and serum samples were generated from 477 metabolites identified by gas chromatography-mass spectrometry and liquid chromatography-tandem mass spectrometry.A biomarker signature (nine metabolites and additionally CA19-9) was identified for the differential diagnosis between PDAC and CP. The biomarker signature distinguished PDAC from CP in the training set with an area under the curve (AUC) of 0.96 (95% CI 0.93-0.98). The biomarker signature cut-off of 0.384 at 85% fixed specificity showed a sensitivity of 94.9% (95% CI 87.0%-97.0%). In the test set, an AUC of 0.94 (95% CI 0.91-0.97) and, using the same cut-off, a sensitivity of 89.9% (95% CI 81.0%-95.5%) and a specificity of 91.3% (95% CI 82.8%-96.4%) were achieved, successfully validating the biomarker signature.In patients with CP with an increased risk for pancreatic cancer (cumulative incidence 1.95%), the performance of this biomarker signature results in a negative predictive value of 99.9% (95% CI 99.7%-99.9%) (training set) and 99.8% (95% CI 99.6%-99.9%) (test set). In one third of our patients, the clinical use of this biomarker signature would have improved diagnosis and treatment stratification in comparison to CA19-9.
EVALuna2:15284

Metabolic impairment of non-small cell lung cancers by mitochondrial HSPD1 targeting - Parma, Beatrice; Ramesh, Vignesh; Gollavilli, Paradesi Naidu; Siddiqui, Aarif; Pinna, Luisa; Schwab, Annemarie; Marschall, Sabine; Zhang, Shuman; Pilarsky, Christian; Napoli, Francesca; Volante, Marco; Urbanczyk, Sophia; et al. (Journal of Experimental & Clinical Cancer Research, 2021)
Background The identification of novel targets is of paramount importance to develop more effective drugs and improve the treatment of non-small cell lung cancer (NSCLC), the leading cause of cancer-related deaths worldwide. Since cells alter their metabolic rewiring during tumorigenesis and along cancer progression, targeting key metabolic players and metabolism-associated proteins represents a valuable approach with a high therapeutic potential. Metabolic fitness relies on the functionality of heat shock proteins (HSPs), molecular chaperones that facilitate the correct folding of metabolism enzymes and their assembly in macromolecular structures. Methods Gene fitness was determined by bioinformatics analysis from available datasets from genetic screenings. HSPD1 expression was evaluated by immunohistochemistry from formalin-fixed paraffin-embedded tissues from NSCLC patients. Real-time proliferation assays with and without cytotoxicity reagents, colony formation assays and cell cycle analyses were used to monitor growth and drug sensitivity of different NSCLC cells in vitro. In vivo growth was monitored with subcutaneous injections in immune-deficient mice. Cell metabolic activity was analyzed through extracellular metabolic flux analysis. Specific knockouts were introduced by CRISPR/Cas9. Results We show heat shock protein family D member 1 (HSPD1 or HSP60) as a survival gene ubiquitously expressed in NSCLC and associated with poor patients' prognosis. HSPD1 knockdown or its chemical disruption by the small molecule KHS101 induces a drastic breakdown of oxidative phosphorylation, and suppresses cell proliferation both in vitro and in vivo. By combining drug profiling with transcriptomics and through a whole-genome CRISPR/Cas9 screen, we demonstrate that HSPD1-targeted anti-cancer effects are dependent on oxidative phosphorylation and validated molecular determinants of KHS101 sensitivity, in particular, the creatine-transporter SLC6A8 and the subunit of the cytochrome c oxidase complex COX5B. Conclusions These results highlight mitochondrial metabolism as an attractive target and HSPD1 as a potential theranostic marker for developing therapies to combat NSCLC.
CRIS-Team WoS Importer:2021-08-20

Metastatic adenocarcinomas of the stomach or esophagogastric junction (UICC stage IV) are not always a palliative situation: a retrospective analysis - Schildberg, Claus W.; Weidinger, Thomas; Hohenberger, Werner; Wein, Axel; Langheinrich, Melanie; Neurath, Markus; Boxberger, Frank (World Journal of Surgery, 2014)
Gastric cancer is one of the most common cancers. Unfortunately, it is often diagnosed at the advanced stage International Union Against Cancer stage IV. This induced us to carry out an interdisciplinary analysis of this patient group with the Department of Internal Medicine 1. Our aim was to discuss cancers classified initially as unresectable in a meeting of the interdisciplinary tumor board after palliative chemotherapy, and to refer selected patients for surgery after establishing resectability. The outcome of the chemotherapy, operation method, complication rate, and long-term survival were analyzed.From 1999 to 2008, 76 patients with metastatic gastric cancer or carcinoma of the esophagogastric junction were discussed by the interdisciplinary tumor board of the University of Erlangen and classified initially as unresectable. The patients then received palliative chemotherapy according to the AIO regimen (weekly high-dose 5-fluorouracil/folinic acid [FU/FA] in a 24 h infusion), plus irinotecan. If the tumor was subsequently classified as resectable, the patient underwent either gastric resection or gastrectomy with DII-III dissection. Metastases were resected depending on their location (liver). Peritoneal carcinomatosis was treated additionally by HIPEC. Statistical analysis was with SPSSS version 20.Surgical and general complications and hospital mortality were acceptable. There were no cases of anastomotic leak, but one patient died of fulminant pneumonia. The R0 resection rate was 69 %, and four patients had long-term survival of more than 60 months. There were significant survival advantages.Metastatic gastric cancer or carcinoma of the esophagogastric junction can become resectable after downsizing the tumor with palliative chemotherapy. Long-term survival is achieved in some cases. Therefore, every patient with this type of cancer should be discussed by the interdisciplinary tumour board after palliative chemotherapy to provide him with a chance of cure after re-evaluation.
EVALuna2:1716

Microbiome Patterns in Matched Bile, Duodenal, Pancreatic Tumor Tissue, Drainage, and Stool Samples: Association with Preoperative Stenting and Postoperative Pancreatic Fistula Development - Langheinrich, Melanie; Wirtz, Stefan; Kneis, Barbara; Gittler, Matthias M.; Tyc, Olaf; Schierwagen, Robert; Brunner, Maximilian; Krautz, Christian; Pilarsky, Christian; Trebicka, Jonel; Agaimy, Abbas; Grützmann, Robert; et al. (Journal of Clinical Medicine, 2020)
Postoperative complications after pancreatic surgery are still a significant problem in clinical practice. The aim of this study was to characterize and compare the microbiomes of different body compartments (bile duct, duodenal mucosa, pancreatic tumor lesion, postoperative drainage fluid, and stool samples; preoperative and postoperative) in patients undergoing pancreatic surgery for suspected pancreatic cancer, and their association with relevant clinical factors (stent placement, pancreatic fistula, and gland texture). For this, solid (duodenal mucosa, pancreatic tumor tissue, stool) and liquid (bile, drainage fluid) biopsy samples of 10 patients were analyzed using 16s rRNA gene next-generation sequencing. Our analysis revealed: (i) a distinct microbiome in the different compartments, (ii) markedly higher abundance of Enterococcus in patients undergoing preoperative stent placement in the common bile duct, (iii) significant differences in the beta diversity between patients who developed a postoperative pancreatic fistula (POPF B/C), (iv) patients with POPF B/C were more likely to have bacteria belonging to the genus Enterococcus, and (v) differences in microbiome composition with regard to the pancreatic gland texture. The structure of the microbiome is distinctive in different compartments, and can be associated with the development of a postoperative pancreatic fistula.
CRIS-Team WoS Importer:2020-11-06

Microfluidics applications for high-throughput single cell sequencing - Zhou, Wen-Min; Yan, Yan-Yan; Guo, Qiao-Ru; Ji, Hong; Wang, Hui; Xu, Tian-Tian; Makabel, Bolat; Pilarsky, Christian; He, Gen; Yu, Xi-Yong; Zhang, Jian-Ye (Journal of Nanobiotechnology, 2021)
The inherent heterogeneity of individual cells in cell populations plays significant roles in disease development and progression, which is critical for disease diagnosis and treatment. Substantial evidences show that the majority of traditional gene profiling methods mask the difference of individual cells. Single cell sequencing can provide data to characterize the inherent heterogeneity of individual cells, and reveal complex and rare cell populations. Different microfluidic technologies have emerged for single cell researches and become the frontiers and hot topics over the past decade. In this review article, we introduce the processes of single cell sequencing, and review the principles of microfluidics for single cell analysis. Also, we discuss the common high-throughput single cell sequencing technologies along with their advantages and disadvantages. Lastly, microfluidics applications in single cell sequencing technology for the diagnosis of cancers and immune system diseases are briefly illustrated. [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2021-10-29
Keywords: Biomedical applications; Droplets; High-throughput; Microfluidic; Single cell RNA sequencing (scRNA-seq); Single cell separation

Microfluidic Technology for the Isolation and Analysis of Exosomes - Wu, Yusong; Wang, Yuqing; Lu, Yanjun; Luo, Xiaomei; Huang, Yinghong; Xie, Ting; Pilarsky, Christian; Dang, Yuanye; Zhang, Jianye (Micromachines, 2022)
Exosomes are lipid-bilayer enclosed vesicles with diameters of 30–150 nm, which play a pivotal role in cell communication by transporting their cargoes such as proteins, lipids, and genetic materials. In recent years, exosomes have been under intense investigation, as they show great promise in numerous areas, especially as bio-markers in liquid biopsies. However, due to the high heterogeneity and the nano size of exosomes, the separation of exosomes is not easy. This review will deliver an outline of the conventional methods and the microfluidic-based technologies for exosome separation. Particular attention is devoted to microfluidic devices, highlighting the efficiency of exosome isolation by these methods. Additionally, this review will introduce advances made in the integrated microfluidics technologies that enable the separation and analysis of exosomes.
CRIS-Team Scopus Importer:2022-11-11
Keywords: detection; exosomes; extra-cellular vesicle; isolation; microfluidics

MiR-122, the regulator of the immune privileged liver - Gefen, Maytal; Layani, Shanny; Klahr, Emma; Hindi, Mor; Rosenberg, Nofar; Abramovitch, Rinat; Nachmansson, Nathalie; Yehezkel, Adi; Peled, Amnon; Rachmilewitz, Jacob; Abraham, Michal; Berger, Michael; et al. (JOURNAL OF HEPATOLOGY, 2022)
CRIS-Team WoS Importer:2022-08-12

MiR-132 controls pancreatic beta cell proliferation and survival through Pten/Akt/Foxo3 signaling - Mziaut, Hassan; Henniger, Georg; Ganss, Katharina; Hempel, Sebastian; Wolk, Steffen; McChord, Johanna; Chowdhury, Kamal; Ravassard, Philippe; Knoch, Klaus Peter; Krautz, Christian; Weitz, Jürgen; Grützmann, Robert; et al. (Molecular Metabolism, 2020)
Objective: MicroRNAs (miRNAs) play an integral role in maintaining beta cell function and identity. Deciphering their targets and precise role, however, remains challenging. In this study, we aimed to identify miRNAs and their downstream targets involved in the regeneration of islet beta cells following partial pancreatectomy in mice. Methods: RNA from laser capture microdissected (LCM) islets of partially pancreatectomized and sham-operated mice were profiled with microarrays to identify putative miRNAs implicated in beta cell regeneration. Altered expression of the selected miRNAs, including miR-132, was verified by RT-PCR. Potential targets of miR-132 were selected through bioinformatic data mining. Predicted miR-132 targets were validated for their changed RNA, protein expression levels, and signaling upon miR-132 knockdown and/or overexpression in mouse MIN6 and human EndoC-βH1 insulinoma cells. The ability of miR-132 to foster beta cell proliferation in vivo was further assessed in pancreatectomized miR-132−/− and control mice. Results: Partial pancreatectomy significantly increased the number of BrdU+/insulin+ islet cells. Microarray profiling revealed that 14 miRNAs, including miR-132 and -141, were significantly upregulated in the LCM islets of the partially pancreatectomized mice compared to the LCM islets of the control mice. In the same comparison, miR-760 was the only downregulated miRNA. The changed expression of these miRNAs in the islets of the partially pancreatectomized mice was confirmed by RT-PCR only in the case of miR-132 and -141. Based on previous knowledge of its function, we focused our attention on miR-132. Downregulation of miR-132 reduced the proliferation of MIN6 cells while enhancing the levels of pro-apoptotic cleaved caspase-9. The opposite was observed in miR-132 overexpressing MIN6 cells. Microarray profiling, RT-PCR, and immunoblotting of the latter cells demonstrated their downregulated expression of Pten with concomitant increased levels of pro-proliferative factors phospho-Akt and phospho-Creb and inactivation of pro-apoptotic Foxo3a via its phosphorylation. Downregulation of Pten was further confirmed in the LCM islets of pancreatectomized mice compared to the sham-operated mice. Moreover, overexpression of miR-132 correlated with increased proliferation of EndoC-βH1 cells. The regeneration of beta cells following partial pancreatectomy was lower in the miR-132/212−/− mice than the control littermates. Conclusions: This study provides compelling evidence about the critical role of miR-132 for the regeneration of mouse islet beta cells through the downregulation of its target Pten. Hence, the miR-132/Pten/Akt/Foxo3 signaling pathway may represent a suitable target to enhance beta cell mass.
CRIS-Team Scopus Importer:2019-12-24
Keywords: Apoptosis; miR-132; Pancreatectomy; Pten/Akt/Foxo3a; β cell regeneration

MiRNA-21 Expression Decreases from Primary Tumors to Liver Metastases in Colorectal Carcinoma - Feiersinger, Fabian; Nolte, Elke; Wach, Sven; Rau, Tilman; Vassos, Nikolaos; Geppert, Carol-Immanuel; Konrad, Andreas; Merkel, Susanne; Taubert, Helge; Stürzl, Michael; Croner, Roland S. (PLoS ONE, 2016)
Metastasis is the major cause of death in colorectal cancer patients. Expression of certain miRNAs in the primary tumors has been shown to be associated with progression of colorectal cancer and the initiation of metastasis. In this study, we compared miRNA expression in primary colorectal cancer and corresponding liver metastases in order to get an idea of the oncogenic importance of the miRNAs in established metastases.We analyzed the expression of miRNA-21, miRNA-31 and miRNA-373 in corresponding formalin-fixed paraffin-embedded (FFPE) tissue samples of primary colorectal cancer, liver metastasis and healthy tissues of 29 patients by quantitative real-time PCR.All three miRNAs were significantly up-regulated in the primary tumor tissues as compared to healthy colon mucosa of the respective patients (p < 0.01). MiRNA-21 and miRNA-31 were also higher expressed in liver metastases as compared to healthy liver tissues (p < 0.01). No significant difference of expression of miRNA-31 and miRNA-373 was observed between primary tumors and metastases. Of note, miRNA-21 expression was significantly reduced in liver metastases as compared to the primary colorectal tumors (p < 0.01).In the context of previous studies demonstrating increased miRNA-21 expression in metastatic primary tumors, our findings raise the question whether miRNA-21 might be involved in the initiation but not in the perpetuation and growth of metastases.
EVALuna2:6831

Mitoxantrone and Mitoxantrone-Loaded Iron Oxide Nanoparticles Induce Cell Death in Human Pancreatic Ductal Adenocarcinoma Cell Spheroids - Dinter, Jonas; Friedrich, Ralf P.; Yang, Hai; Pilarsky, Christian; Mangge, Harald; Pöttler, Marina; Janko, Christina; Alexiou, Christoph; Lyer, Stefan (Materials, 2023)
Pancreatic ductal adenocarcinoma is a hard-to-treat, deadly malignancy. Traditional treatments, such as surgery, radiation and chemotherapy, unfortunately are still not able to significantly improve long-term survival. Three-dimensional (3D) cell cultures might be a platform to study new drug types in a highly reproducible, resource-saving model within a relevant pathophysiological cellular microenvironment. We used a 3D culture of human pancreatic ductal adenocarcinoma cell lines to investigate a potential new treatment approach using superparamagnetic iron oxide nanoparticles (SPIONs) as a drug delivery system for mitoxantrone (MTO), a chemotherapeutic agent. We established a PaCa DD183 cell line and generated PANC-1SMAD4 (−/−) cells by using the CRISPR-Cas9 system, differing in a prognostically relevant mutation in the TGF-β pathway. Afterwards, we formed spheroids using PaCa DD183, PANC-1 and PANC-1SMAD4 (−/−) cells, and analyzed the uptake and cytotoxic effect of free MTO and MTO-loaded SPIONs by microscopy and flow cytometry. MTO and SPION–MTO-induced cell death in all tumor spheroids in a dose-dependent manner. Interestingly, spheroids with a SMAD4 mutation showed an increased uptake of MTO and SPION–MTO, while at the same time being more resistant to the cytotoxic effects of the chemotherapeutic agents. MTO-loaded SPIONs, with their ability for magnetic drug targeting, could be a future approach for treating pancreatic ductal adenocarcinomas.
CRIS-Team Scopus Importer:2023-04-28
Keywords: 3D cell culture; magnetic drug targeting; nanomedicine; pancreatic ductal adenocarcinoma; superparamagnetic iron oxide nanoparticles

Modulation of the extrinsic cell death signaling pathway by viral Flip induces acute-death mediated liver failure - Bittel, Miriam; Kremer, Andreas; Stürzl, Michael; Wirtz, Stefan; Stolzer, Iris; Neurath, Markus; Ballon, Gianna; Günther, Claudia (Cell Death & Disease, 2019)
During viral infections viruses express molecules that interfere with the host-cell death machinery and thus inhibit cell death responses. For example the viral FLIP (vFLIP) encoded by Kaposi’s sarcoma-associated herpesvirus interacts and inhibits the central cell death effector, Caspase-8. In order to analyze the impact of anti-apoptotic viral proteins, like vFlip, on liver physiology in vivo, mice expressing vFlip constitutively in hepatocytes (vFlipAlbCre+) were generated. Transgenic expression of vFlip caused severe liver tissue injury accompanied by massive hepatocellular necrosis and inflammation that finally culminated in early postnatal death of mice. On a molecular level, hepatocellular death was mediated by RIPK1-MLKL necroptosis driven by an autocrine TNF production. The loss of hepatocytes was accompanied by impaired bile acid production and disruption of the bile duct structure with impact on the liver-gut axis. Notably, embryonic development and tissue homeostasis were unaffected by vFlip expression. In summary our data uncovered that transgenic expression of vFlip can cause severe liver injury in mice, culminating in multiple organ insufficiency and death. These results demonstrate that viral cell death regulatory molecules exhibit different facets of activities beyond the inhibition of cell death that may merit more sophisticated in vitro and in vivo analysis.
CRIS-Team Scopus Importer:2019-12-03

Molecular characterization of peripheral arterial disease in proximal extremity arteries - Croner, Roland S.; Balzer, Klaus; Schellerer, Vera; Mueller, Volker; Schlabrakowsi, Anne; Stürzl, Michael; Naschberger, Elisabeth; Lang, Werner (Journal of Surgical Research, 2012)
Purpose: Although risk factors for atherosclerosis in peripheral arterial disease (PAD) are well defined, the underlying mechanisms are poorly understood and no medication exists for causal therapy. Molecular pathways that could be targeted have not been identified so far. To address this issue, we compared the molecular profiles of healthy versus PAD proximal femoral arteries. Methods: Gene expression profiles from proximal femoral arteries of patients with PAD (Fontaine stage IIb-IV; n = 20) and femoral arteries from healthy controls (CO) (n = 3) were compared by microarray technology. We evaluated all samples by histopathology and performed microdissection on the CO tissue before molecular analysis. We analyzed genes regarding their cellular localization, molecular function, and risk factors such as hypercholesterolemia, smoking, and diabetes. We used a selected panel of genes for polymerase chain reaction validation of microarray results and compared the data with previously published studies. Results: Most genes overexpressed in PAD versus CO were located in the cytoplasm, membrane, and nucleus. Functionally, they had binding activity to nucleotides, cytoskeletal proteins, and transcription factors. They were mainly involved in immune regulation (e.g., interleukin-8, chemokine ligand 18, and allograft-inflammatory factor-1) (P < 0.01). Down-regulated genes in PAD versus CO were located in the extracellular region. They had transporter and G-protein receptor activity. They were associated with signaling, cell growth, and tissue formation (e.g., myosin VB, marker for differentiated aortic smooth muscle, myosin 11) (P < 0.01). Polymerase chain reaction successfully validated the expression of the differences among 10 selected genes (e.g., chemokine ligand 18, common leukocyte antigen, killer cell lectin-like receptor subfamily B, member 1, and interleukin-8). Conclusions: Genes enrolled in immune regulation and inflammatory response were identified as key players in PAD. Various membrane-bound molecules with binding activity are hereunder. Identification of such molecules may elucidate relevant players that act as candidates for therapeutic targets or prognostic markers in the future. © 2012 Elsevier Inc. All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: Artheriosclerosis; Microarray; Molecular marker; Peripheral arterial disease

Molecularly characterised xenograft tumour mouse models: valuable tools for evaluation of new therapeutic strategies for secondary liver cancers. - Mischek, Daniela; Steinborn, Ralf; Petznek, Helga; Bichler, Christoph; Zatloukal, Kurt; Stürzl, Michael; Guenzburg, Walter H.; Hohenadl, Christine (Journal of Biomedicine and Biotechnology, 2009)
To develop and evaluate new therapeutic strategies for the treatment of human cancers, well-characterised preclinical model systems are a prerequisite. To this aim, we have established xenotransplantation mouse models and corresponding cell cultures from surgically obtained secondary human liver tumours. Established xenograft tumours were patho- and immunohistologically characterised, and expression levels of cancer-relevant genes were quantified in paired original and xenograft tumours and the derivative cell cultures applying RT-PCR-based array technology. Most of the characteristic morphological and immunohistochemical features of the original tumours were shown to be maintained. No differences were found concerning expression of genes involved in cell cycle regulation and oncogenesis. Interestingly, cytokine and matrix metalloproteinase encoding genes appeared to be expressed differentially. Thus, the established models are closely reflecting pathohistological and molecular characteristics of the selected human tumours and may therefore provide useful tools for preclinical analyses of new antitumour strategies in vivo.

Molecular mechanisms of lymphatic metastasis in solid tumors of the gastrointestinal tract. - Langheinrich, Melanie; Schellerer, Vera; Perrakis, Aristotelis; Lohmüller, Clemens; Schildberg, Claus; Naschberger, Elisabeth; Stürzl, Michael; Hohenberger, Werner; Croner, Roland S. (International Journal of Clinical and Experimental Pathology, 2012)
Tumor cell dissemination from the primary tumor site to distant organs is one of the characteristic properties of malignant tumors and represents a crucial step in the progression of disease. Although the pattern of spread may vary in different types of carcinomas, dissemination via the lymphatic system represents a common event in metastasis. The extent of lymph node metastasis is one of the major determinants for the prognosis of patients with gastrointestinal carcinomas and guides the therapeutically management. During the last decades, significant attention has been given to the molecular mechanisms that control lymphatic metastasis. The process of lymphangiogenesis has come into the focus. Lymphangiogenesis, the formation of newly lymphatics, comprises a series of complex cellular events and is controlled by a balance between pro- and anti-lymphangiogenic signals. This article will briefly describe the lymphatic system and then provide an overview of the molecular players involved in tumor lymphangiogenesis.

Molecular signature for lymphatic metastasis in colorectal carcinomas. - Croner, Roland S.; Förtsch, Thomas; Brueckl, Wolfgang M.; Roedel, Franz; Roedel, Claus; Papadopoulos, Thomas; Brabletz, Thomas; Kirchner, Thomas; Sachs, Martin; Behrens, Jürgen; Klein-Hitpass, Ludger; Stürzl, Michael; et al. (Annals of Surgery, 2008)
Fifty differently expressed genes between stage UICC I, II versus III CRC were identified respecting the selection criteria by allowing for multiple testing. The data validation by the independent clinical study confirmed our results. In comparison to MC, the genes were over- or underexpressed. They belong to various functional groups such as cellular adhesion, transporters, signaling, metabolism, protein synthesis, gene control, and immune system. Forty tumor samples of stage UICC I, II CRC, 40 samples of stage III CRC, and 25 biopsies of healthy mucosa (MC) were shock frozen in liquid nitrogen and underwent cryotomy after manual dissection for tumor tissue or MC enrichment. Isolated RNA was hybridized to GeneChips (HG-U133A, Affymetrix). Preprocessing of the microarray results was done by the robust multichip average method, and differentially expressed genes were selected by the maximum Wilcoxon statistic over 22,215 probe sets. The results were validated at an independent clinical study. Our large patient cohort and the data validation on an independent study identified 50 differentially expressed genes between CRC of different histopathologic stages. These findings indicate that molecular staging of CRC may be possible, which could help to guide individual CRC treatment before surgery. TNM-staging of colorectal carcinomas (CRC) relies on the histopathologic workup of the surgically removed specimen. If valid preoperative staging methods existed, patients could be selected for adequate individual therapy before surgery. Microarray techniques provide a promising tool to identify stage-specific molecular signatures on primary tumor biopsies. RESULTS MATERIAL AND METHODS CONCLUSION PURPOSE

Molecular staging of lymph node-negative colon carcinomas by one-step nucleic acid amplification (OSNA) results in upstaging of a quarter of patients in a prospective, European, multicentre study - Croner, R. S.; Geppert, Carol-Immanuel; Bader, F. G.; Nitsche, U.; Spaeth, C.; Rosenberg, R.; Zettl, A.; Matias-Guiu, Xavier; Tarragona, J.; Gueller, U.; Stürzl, Michael; Zuber, M. (British Journal of Cancer, 2014)
Background:Current histopathological staging procedures in colon carcinomas depend on midline division of the lymph nodes with one section of haematoxylin & eosin (H&E) staining only. By this method, tumour deposits outside this transection line may be missed and could lead to understaging of a high-risk group of stage UICC II cases, which recurs in 20% of cases. A new diagnostic semiautomated system, one-step nucleic acid amplification (OSNA), detects cytokeratin (CK) 19 mRNA in lymph node metastases and enables the investigation of the whole lymph node. The objective of this study was to assess whether histopathological pN0 patients can be upstaged to stage UICC III by OSNA.Methods:Lymph nodes from patients who were classified as lymph node negative after standard histopathology (single (H&E) slice) were subjected to OSNA. A result revealing a CK19 mRNA copy number >250, which makes sure to detect mainly macrometastases and not isolated tumour cells (ITC) or micrometastases only, was regarded as positive for lymph node metastases based on previous threshold investigations.Results:In total, 1594 pN0 lymph nodes from 103 colon carcinomas (median number of lymph nodes per patient: 14, range: 1-46) were analysed with OSNA. Out of 103 pN0 patients, 26 had OSNA-positive lymph nodes, resulting in an upstaging rate of 25.2%. Among these were 6/37 (16.2%) stage UICC I and 20/66 (30.3%) stage UICC II patients. Overall, 38 lymph nodes were OSNA positive: 19 patients had one, 3 had two, 3 had three, and 1 patient had four OSNA-positive lymph nodes.Conclusions:OSNA resulted in an upstaging of over 25% of initially histopathologically lymph node-negative patients. OSNA is a standardised, observer-independent technique, allowing the analysis of the whole lymph node. Therefore, sampling bias due to missing investigation of certain lymph node tissue can be avoided, which may lead to a more accurate staging.
EVALuna2:6584

Moonlighting chromatin: when DNA escapes nuclear control - Singh, Jeeshan; Boettcher, Michael; Dölling, Maximilian; Heuer, Annika; Hohberger, Bettina; Leppkes, Moritz; Naschberger, Elisabeth; Schapher, Mirco; Schauer, Christine; Schoen, Janina; Stürzl, Michael; Vitkov, Ljubomir; et al. (Cell Death and Differentiation, 2023)
Extracellular chromatin, for example in the form of neutrophil extracellular traps (NETs), is an important element that propels the pathological progression of a plethora of diseases. DNA drives the interferon system, serves as autoantigen, and forms the extracellular scaffold for proteins of the innate immune system. An insufficient clearance of extruded chromatin after the release of DNA from the nucleus into the extracellular milieu can perform a secret task of moonlighting in immune-inflammatory and occlusive disorders. Here, we discuss (I) the cellular events involved in the extracellular release of chromatin and NET formation, (II) the devastating consequence of a dysregulated NET formation, and (III) the imbalance between NET formation and clearance. We include the role of NET formation in the occlusion of vessels and ducts, in lung disease, in autoimmune diseases, in chronic oral disorders, in cancer, in the formation of adhesions, and in traumatic spinal cord injury. To develop effective therapies, it is of utmost importance to target pathways that cause decondensation of chromatin during exaggerated NET formation and aggregation. Alternatively, therapies that support the clearance of extracellular chromatin are conceivable. [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2023-02-17

Morphologic HIV demonstration in formalin embedded material–techniques, problems, results - Zietz, Christian; Speiser, B; Hell, W; Stürzl, Michael; Wolf, H; Roth, W K (Verhandlungen der Deutschen Gesellschaft für Pathologie, 1991)
Formalin-fixed, paraffin-embedded material of archival specimens is suitable for a morphological HIV-detection: Infected cells with HIV in the proliferative phase can be demonstrated with reliable results on tissue sections by immunohistological technics using new antibodies. In situ nucleic acid hybridisation technics can also show HIV in the expression phase on paraffin-embedded material, but often fail in demonstrating latently HIV-infected cells. The DNA-Polymerase chain reaction can detect latent Provirus in morphologically defined areas of paraffin sections even in autopsy material, i.e. lymphnodes and even eyes of patients with HIV-Infection, but requires precaution and control with respect to contamination.

Multiple interferon regulatory factor and NF-κB sites cooperate in mediating cell-type-and maturation-specific activation of the human CD83 promoter in dendritic cells - Stein, Marcello F.; Lang, Stefan; Winkler, Thomas; Deinzer, Anja; Erber, Sebastian; Nettelbeck, Dirk M.; Naschberger, Elisabeth; Jochmann, Ramona; Stürzl, Michael; Slany, Robert; Werner, Thomas; Steinkasserer, Alexander; et al. (Molecular and Cellular Biology, 2013)
CD83 is one of the best-known surface markers for fully mature dendritic cells (mature DCs), and its cell-type-and maturationspecific regulation makes the CD83 promoter an interesting tool for the genetic modulation of DCs. To determine the mechanisms regulating this DC-and maturation-specific CD83 expression, chromatin immunoprecipitation (ChIP)-on-chip microarray, biocomputational, reporter, electrophoretic mobility shift assay (EMSA), and ChIP analyses were performed. These studies led to the identification of a ternary transcriptional activation complex composed of an upstream regulatory element, a minimal promoter, and an enhancer, which have not been reported in this arrangement for any other gene so far. Notably, these DNA regions contain a complex framework of interferon regulatory factor (IRF)-and NF-κB transcription factor-binding sites mediating their arrangement. Mutation of any of the IRF-binding sites resulted in a significant loss of promoter activity, whereas overexpression of NF-κB transcription factors clearly enhanced transcription. We identified IRF-1, IRF-2, IRF-5, p50, p65, and cRel to be involved in regulating maturation-specific CD83 expression in DCs. Therefore, the characterization of this promoter complex not only contributes to the knowledge of DC-specific gene regulation but also suggests the involvement of a transcriptional module with binding sites separated into distinct regions in transcriptional activation as well as cell-type-and maturation-specific transcriptional targeting of DCs. © 2013, American Society for Microbiology.

Muscle‐derived cytokines reduce growth, viability and migratory activity of pancreatic cancer cells - Schwappacher, Raphaela; Dieterich, Walburga; Reljic, Dejan; Pilarsky, Christian; Mukhopadhyay, Debabrata; Chang, David K.; Biankin, Andrew; Siebler, Jürgen; Herrmann, Hans J.; Neurath, Markus; Zopf, Yurdagül (Cancers, 2021)
The evidence that regular physical exercise reduces the risk of developing cancer is well described. However, the interaction between physical exercise and cancer is not fully clarified yet. Several myokines released by skeletal muscle appear to have a direct anti‐tumour function. There are few data on myokine secretion after exercise in patients with advanced tumours. Pancreatic cancer (PC) is a very aggressive and usually fatal cancer. To investigate the effects of exercise in PC, the blood of advanced‐stage PC patients was analysed after 12 weeks of resistance training using whole‐body electromyostimulation. After the 12‐week training period, the patient serum inhibited the proliferation and the motility of PC cells and enhanced PC cell apoptosis. The impact of exercise training was also investigated in an exercise‐mimicking in vitro model using electric pulse stimulation of human myotubes and revealed similar anti‐tumour effects on PC cells, clearly indicating direct cancer‐protective properties of activated skeletal muscle. Protein and gene expression analyses in plasma from exercise‐trained patients and in myotube cultures after in vitro exercise showed that interleukin 10 (IL10), C‐X‐C motif ligand 1 (CXCL1) and C‐C motif chemokine ligand 4 (CCL4) are myokines released from activated skeletal muscle. In accordance with the effects of serum from exercise‐trained patients, the supplementation with recombinant IL10, CXCL1 and CCL4 impaired growth and migration of PC cells. Treatment of PC cells with these myokines upregulated caspase 3/7 expression and the cleavage of poly(ADP‐ribose) polymerase, leading to enhanced PC cell death. The identification of myokines with anti‐tumour properties in advanced‐stage PC patients after exercise opens a new perspective in supportive therapy with sports and exercise for cancer patients.
CRIS-Team Scopus Importer:2021-08-13
Keywords: Apoptosis; Electric pulse stimulation; Exercise; Migration; Myokine; Pancreatic cancer; Physical activity; Proliferation; Whole‐body electromyostimulation

MYC ecDNA promotes intratumour heterogeneity and plasticity in PDAC - Fiorini, Elena; Malinova, Antonia; Schreyer, Daniel; Pasini, Davide; Bevere, Michele; Alessio, Giorgia; Rosa, Diego; D’Agosto, Sabrina; Azzolin, Luca; Milite, Salvatore; Andreani, Silvia; Lupo, Francesca; et al. (Nature, 2025)
Intratumour heterogeneity and phenotypic plasticity drive tumour progression and therapy resistance1,2. Oncogene dosage variation contributes to cell-state transitions and phenotypic heterogeneity3, thereby providing a substrate for somatic evolution. Nonetheless, the genetic mechanisms underlying phenotypic heterogeneity are still poorly understood. Here we show that extrachromosomal DNA (ecDNA) is a major source of high-level focal amplification in key oncogenes and a major contributor of MYC heterogeneity in pancreatic ductal adenocarcinoma (PDAC). We demonstrate that ecDNAs drive varying levels of MYC dosage, depending on their regulatory landscape, enabling cancer cells to rapidly and reversibly adapt to microenvironmental changes. In the absence of selective pressure, a high ecDNA copy number imposes a substantial fitness cost on PDAC cells. We also show that MYC dosage affects cell morphology and dependence of cancer cells on stromal niche factors. Our work provides a detailed analysis of ecDNAs in PDAC and describes a new genetic mechanism driving MYC heterogeneity in PDAC.
CRIS-Team Scopus Importer:2025-04-01

Myocutaneous transpelvic flaps do improve quality of life and help to reduce wound healing complications in patients receiving abdominoperineal resection in the real world - Horch, Raymund E.; Hohenberger, Werner; Weber, Klaus; Arkudas, Andreas; Beier, Justus (International Journal of Colorectal Disease, 2016)
EVALuna2:15233

NAR score as surrogate for disease-free survival in the CAO/ARO/AIO-04 phase 3 rectal cancer trial - Fokas, E.; Fietkau, Rainer; Hartmann, Arndt; Hohenberger, Werner; Grützmann, Robert; Ghadimi, M.; Liersch, T.; Stroebel, P.; Grabenbauer, G.; Wittekind, C.; Sauer, Rolf; Kaufmann, M.; et al. (2018)
EVALuna2:36513

NCR, an Inflammation and Nutrition Related Blood-Based Marker in Colon Cancer Patients: A New Promising Biomarker to Predict Outcome - Langheinrich, Melanie; Siebenhüner, Alexander Reinhard; Baecker, Justus; Miragall, Maximilian; Wiesmüller, Felix; Schellerer, Vera; Merkel, Susanne; Brunner, Maximilian; Krautz, Christian; Weber, Klaus; Grützmann, Robert; Kersting, Stephan (Diagnostics, 2023)
Background: Colorectal carcinoma (CRC) is a heterogeneous disease, and differences in outcomes have been reported among patients diagnosed with the same disease stage. Prognostic and predictive biomarkers provide information for patient risk stratification and guide treatment selection. Although numerous studies have analyzed the effects of systemic inflammatory factors on CRC outcomes, clinical significance remains to be elucidated. In particular, the treatment strategy of colon cancer patients is different from that of rectal cancer due to outcome and recurrence differences. The identification of patients with a poor prognosis who might benefit from intensive treatment approaches is clinically necessary. Methods: This study aimed to evaluate the value of different blood-based markers and assess the significance of our newly developed inflammatory-nutrition-related biomarker (NCR = BMI × albumin/CRP) in patients with colon cancer. A two-stage design was used with 212 patients with colon cancer (CC) in the discovery cohort (n = 159) and in an external validation cohort (n = 53). Results: A lower preoperative NCR level was significantly correlated with a worse prognosis, sidedness, undifferentiated histology, nodal involvement, and advanced UICC stage. We compared the NCR with other established prognostic indices and showed that the NCR is a more reliable indicator of a poor prognosis for patients with CC. Patients with low NCR levels experienced a significantly shorter Overall Survival (OS) than patients with high levels. Multivariate analysis confirmed preoperative NCR levels as an independent predictor for overall survival with a hazard ratio of 3.3 (95% confidence interval 1.628–6.709, p < 0.001). Finally, we confirmed the predictive value of the NCR in an independent validation cohort and confirmed NCR as an independent prognostic factor for OS. Conclusion: Taken together, we discovered a new prognostic index (NCR) based on BMI, albumin, and CRP levels as an independent prognostic predictor of OS in patients with colon cancer. In all UICC stages, our newly developed NCR marker is able to distinguish patients with better and worse prognoses. We, therefore, propose that NCR may serve as a supplement to the TNM staging system to optimize the risk stratification in CC patients towards personalized oncology. In particular, NCR can be used in clinical trials to stratify patients with UICC II and III tumors and help better select patients who might benefit from adjuvant treatment.
CRIS-Team Scopus Importer:2023-01-20
Keywords: biomarker; colon cancer; colorectal cancer; inflammation; nutrition; prognosis; sidedness; tumor marker

Netrank: network-based approach for biomarker discovery - Al-Fatlawi, Ali; Rusadze, Eka; Shmelkin, Alexander; Malekian, Negin; Ozen, Cigdem; Pilarsky, Christian; Schroeder, Michael (BMC Bioinformatics, 2023)
Background: Integrating multi-omics data is fast becoming a powerful approach for predicting disease progression and treatment outcomes. In light of that, we introduce a modified version of the NetRank algorithm, a network-based algorithm for biomarker discovery that incorporates the protein associations, co-expressions, and functions with its phenotypic association to differentiate different types of cancer. NetRank is introduced here as a robust feature selection method for biomarker selection in cancer prediction. We assess the robustness and suitability of the RNA gene expression data through scanning genomic data for 19 cancer types with more than 3000 patients from The Cancer Genome Atlas (TCGA). Results: The results of evaluating different cancer type profiles from the TCGA data demonstrate the strength of our approach to identifying interpretable biomarker signatures for cancer outcome prediction. NetRank’s biomarkers segregate most cancer types with an area under the curve (AUC) above 90% using compact signatures. Conclusion: In this paper we provide a fast and efficient implementation of NetRank, with a case study from The Cancer Genome Atlas, to assess the performance. We incorporated complete functionality for pre and post-processing for RNA-seq gene expression data with functions for building protein-protein interaction networks. The source code of NetRank is freely available (at github.com/Alfatlawi/Omics-NetRank) with an installable R library. We also deliver a comprehensive practical user manual with examples and data attached to this paper.
CRIS-Team Scopus Importer:2023-08-11
Keywords: Biomarker; Cancer; Gene expression; Protein networks; R package; RNA

Neuromodulation in an era of rising need and cost: a time for multifaceted consideration - Matzel, Klaus (Diseases of the colon & rectum, 2014)
EVALuna2:15178

Neutrophil extracellular traps and DNases orchestrate formation of peritoneal adhesions. - Elrod, Julia; Heuer, Annika; Knopf, Jasmin; Schoen, Janina; Schönfeld, Lavinia; Trochimiuk, Magdalena; Stiel, Carolin; Appl, Birgit; Raluy, Laia Pagerols; Saygi, Ceren; Zlatar, Leticija; Hosari, Sami; et al. (iScience, 2023)
Peritoneal adhesions are poorly understood but highly prevalent conditions that can cause intestinal obstruction and pelvic pain requiring surgery. While there is consensus that stress-induced inflammation triggers peritoneal adhesions, the molecular processes of their formation still remain elusive. We performed murine models and analyzed human samples to monitor the formation of adhesions and the treatment with DNases. Various molecular analyses were used to evaluate the adhesions. The experimental peritoneal adhesions of the murine models and biopsy material from humans are largely based on neutrophil extracellular traps (NETs). Treatment with DNASE1 (Dornase alfa) and the human DNASE1L3 analog (NTR-10), significantly reduced peritoneal adhesions in experimental models. We conclude that NETs serve as essential scaffold for the formation of adhesions; DNases interfere with this process. Herein, we show that therapeutic application of DNases can be employed to prevent the formation of murine peritoneal adhesions. If this can be translated into the human situation requires clinical studies.
EVALuna2:551953

Neutrophil extracellular traps drive epithelial‐mesenchymal transition of human colon cancer - Stehr, Antonia; Wang, Guangxia; Demmler, Richard; Stemmler, Marc; Straube, Julia; Tripal, Philipp; Schmid, Benjamin; Geppert, Carol-Immanuel; Hartmann, Arndt; Munoz, Luis Enrique; Schoen, Janina; Völkl, Simon; et al. (Journal of Pathology, 2021)
Neutrophil extracellular traps (NETs) are extracellular structures, composed of nuclear DNA and various proteins released from neutrophils. Evidence is growing that NETs exert manifold functions in infection, immunity, and cancer. Recently, NETs have been detected in colorectal cancer (CRC) tissues but their association with disease progression and putative functional impact on tumourigenesis remained elusive. Using high-resolution stimulated emission depletion (STED) microscopy we showed that citrullinated histone H3 (H3cit) is sufficient to specifically detect citrullinated NETs in colon cancer tissues. Among other evidence this was supported by the close association of H3cit with de-condensed extracellular DNA, the hallmark of NETs. Extracellular DNA was reliably differentiated from nuclear condensed DNA by staining with an anti-DNA-antibody providing a novel and valuable tool to detect NETs in FFPE tissues. Using these markers, the clinical association of NETs has been investigated in a cohort of 85 patients with colon cancer. NETs were frequently detected (n = 37/n = 85, 44%) in colon cancer tissue sections and preferentially localized either only in the tumour centre or both, in the tumour centre and the invasive front. Of note, citrullinated NETs were significantly associated with high histopathologic tumour grades and lymph node metastasis. In vitro, purified NETs induced filopodia formation and cell motility in CRC cell lines. This was associated with increased expression of mesenchymal marker mRNAs (vimentin [VIM], fibronectin [FN1]) and epithelial- mesenchymal transition (EMT) promoting transcription factors (ZEB1 and Slug [SNAI2]) as well as decreased expression of the epithelial markers E-cadherin (CDH1) and EpCAM (EPCAM). These findings indicated that NETs activate an EMT-like process in CRC cells and may contribute to the metastatic progression of CRC.
Keywords: epithelial–mesenchymal transition (EMT); colorectal neoplasms; stimulated emission depletion (STED) microscopy; neutrophils; migration; extracellular traps

Neutrophil-to-Lymphocyte Ratio and Prognostic Nutritional Index Are Predictors for Overall Survival after Primary Pancreatic Resection of Pancreatic Ductal Adenocarcinoma: A Single Centre Evaluation - Hackner, Danilo; Merkel, Susanne; Weiß, Andreas; Krautz, Christian; Weber, Georg; Grützmann, Robert; Brunner, Maximilian (Cancers, 2024)
Purpose: Prognostic inflammation-based parameters have been reported as useful tools in various oncologic diseases. Pancreatic ductal adenocarcinoma (PDAC) is characterized by a high mortality rate, making reliable prognostic markers highly desirable. However, there is still inconsistency in the literature regarding the efficacy of the different available scores. Methods: A total of 207 patients, who underwent primary resection of PDAC from January 2000 to December 2018 at the University Hospital of Erlangen, were included in this retrospective single-center study. Different biomarkers, including the preoperative neutrophil–lymphocyte ratio (NLR), the platelet–lymphocyte ratio (PLR), the c-reactive protein (CRP)–albumin ratio (CAR), the lymphocyte–CRP ratio (LCR), the prognostic nutritional index (PNI) and the modified Glasgow prognostic score (mGPS) were analyzed for their ability to predict overall survival (OS). Results: In our cohort, the median overall survival was 20.7 months. Among the investigated biomarkers, NLR and PNI were identified as independent prognostic markers (Hazard Ratio (HR) 1.6 (1.0–2.5), p = 0.048 and HR 0.6 (0.4–0.9), p = 0.018), whereas PLR, CAR, LCR and mGPS did not reach significance in the multivariate analysis. Subgroup analysis revealed that the prognostic value of NLR and PNI is particularly evident in locally advanced tumor stages (pT3/4 and pN+). Conclusions: The NLR and PNI could serve as valuable tools for estimating prognosis in patients with PDAC undergoing pancreatic resection in curative intention, especially in locally advanced tumor stages. However, conflicting results in the current literature highlight the need for further prospective studies to validate these findings.
CRIS-Team Scopus Importer:2024-09-06
Keywords: biomarkers; neutrophil-to-lymphocyte ratio; overall survival; pancreatic ductal adenocarcinoma; pancreatic resection; prognostic nutritional index

New Technologies and Applications in Sacral Neuromodulation: An Update - De Wachter, Stefan; Knowles, Charles H.; Elterman, Dean S.; Kennelly, Michael J.; Lehur, Paul A.; Matzel, Klaus; Engelberg, Stefan; Van Kerrebroeck, Philip E.V. (Advances in Therapy, 2020)
Recently rechargeable devices have been introduced for sacral neuromodulation (SNM) with conditional safety for full-body magnetic resonance imaging (MRI). Currently a recharge-free SNM device represents the standard implant; however, it is only approved for MRI head scans. As further new technologies with broader MRI capabilities are emerging, the advantages as well as disadvantages of both rechargeable versus recharge-free devices will be briefly discussed in this commentary from the perspective of patients, healthcare professionals, and providers.
CRIS-Team Scopus Importer:2020-02-14
Keywords: Fecal incontinence; Magnetic resonance imaging; Overactive bladder; Rechargeable battery; Sacral neuromodulation; Stimulator; Urology

N-glycosylation Regulates Intrinsic IFN-γ Resistance in Colorectal Cancer: Implications for Immunotherapy - Krug, Julia; Rodrian, Gabriele; Petter, Katja; Yang, Hai; Khoziainova, Svetlana; Guo, Wei; Benard, Alan; Merkel, Susanne; Gellert, Susan; Maschauer, Simone; Spermann, Monika; Waldner, Maximilian; et al. (Gastroenterology, 2023)
Background & AIMS: Advanced colorectal carcinoma (CRC) is characterized by a high frequency of primary immune evasion and refractoriness to immunotherapy. Given the importance of interferon (IFN)-γ in CRC immunosurveillance, we investigated whether and how acquired IFN-γ resistance in tumor cells would promote tumor growth, and whether IFN-γ sensitivity could be restored. Methods: Spontaneous and colitis-associated CRC development was induced in mice with a specific IFN-γ pathway inhibition in intestinal epithelial cells. The influence of IFN-γ pathway gene status and expression on survival was assessed in patients with CRC. The mechanisms underlying IFN-γ resistance were investigated in CRC cell lines. Results: The conditional knockout of the IFN-γ receptor in intestinal epithelial cells enhanced spontaneous and colitis-associated colon tumorigenesis in mice, and the loss of IFN-γ receptor α (IFNγRα) expression by tumor cells predicted poor prognosis in patients with CRC. IFNγRα expression was repressed in human CRC cells through changes in N-glycosylation, which decreased protein stability via proteasome-dependent degradation, inhibiting IFNγR-signaling. Downregulation of the bisecting N-acetylglucosaminyltransferase III (MGAT3) expression was associated with IFN-γ resistance in all IFN-γ–resistant cells, and highly correlated with low IFNγRα expression in CRC tissues. Both ectopic and pharmacological reconstitution of MGAT3 expression with all-trans retinoic acid increased bisecting N-glycosylation, as well as IFNγRα protein stability and signaling. Conclusions: Together, our results demonstrated that tumor-associated changes in N-glycosylation destabilize IFNγRα, causing IFN-γ resistance in CRC. IFN-γ sensitivity could be reestablished through the increase in MGAT3 expression, notably via all-trans retinoic acid treatment, providing new prospects for the treatment of immune-resistant CRC.
CRIS-Team Scopus Importer:2023-02-10
Keywords: Colon Cancer; IFNGR1; Immune Evasion

Nintedanib macrophage activation and ameliorates vascular and fibrotic manifestations in the Fra2 mouse model of systemic sclerosis - Huang, Jingang; Maier, Christiane; Zhang, Yun; Soare, Alina; Dees, Clara; Beyer, Christian; Harre, Ulrike; Chen, Chih-Wei; Distler, Oliver; Schett, Georg; Wollin, Lutz; Distler, Jörg (Annals of the Rheumatic Diseases, 2017)
Nintedanib is an inhibitor targeting platelet-derived growth factor receptor, fibroblast growth factor receptor and vascular endothelial growth factor receptor tyrosine kinases that has recently been approved for the treatment of idiopathic pulmonary fibrosis. The aim of this study was to analyse the effects of nintedanib in the fos-related antigen-2 (Fra2) mouse model of systemic sclerosis (SSc).The effects of nintedanib on pulmonary arterial hypertension with proliferation of pulmonary vascular smooth muscle cells (PVSMCs) and luminal occlusion, on microvascular disease with apoptosis of microvascular endothelial cells (MVECs) and on fibroblast activation with myofibroblast differentiation and accumulation of extracellular matrix were analysed. We also studied the effects of nintedanib on the levels of key mediators involved in the pathogenesis of SSc and on macrophage polarisation.Nintedanib inhibited proliferation of PVSMCs and prevented thickening of the vessel walls and luminal occlusion of pulmonary arteries. Treatment with nintedanib also inhibited apoptosis of MVECs and blunted the capillary rarefaction in Fra2-transgenic mice. These effects were associated with a normalisation of the serum levels of vascular endothelial growth factor in Fra2 mice on treatment with nintedanib. Nintedanib also effectively blocked myofibroblast differentiation and reduced pulmonary, dermal and myocardial fibrosis in Fra2-transgenic mice. The antifibrotic effects of nintedanib were associated with impaired M2 polarisation of monocytes and reduced numbers of M2 macrophages.Nintedanib targets core features of SSc in Fra2-transgenic mice and ameliorates histological features of pulmonary arterial hypertension, destructive microangiopathy and pulmonary and dermal fibrosis. These data might have direct implications for the ongoing phase III clinical trial with nintedanib in SSc-associated interstitial lung diseas
EVALuna2:13441

NLRP3 Inhibition Leads to Impaired Mucosal Fibroblast Function in Patients with Inflammatory Bowel Diseases - Weber, Simone; Sitte, Selina; Vögele, Anna-Lena; Sologub, Ludmilla; Wilfer, Angelika; Rath, Timo; Nägel, Andreas; Zundler, Sebastian; Franchi, Luigi; Opipari, Anthony W.; Sonnewald, Sophia; Reid, Stephen; et al. (Journal of Crohns & Colitis, 2023)
Background and Aims: Inflammatory bowel diseases (IBD) are characterized by mucosal inflammation and sequential fibrosis formation, but the exact role of the hyperactive NLRP3 inflammasome in these processes is unclear. Thus, we studied the expression and function of the NLRP3 inflammasome in the context of inflammation and fibrosis in IBD. Methods: We analysed intestinal NLRP3 expression in mucosal immune cells and fibroblasts from IBD patients and NLRP3-associated gene expression via single-cell RNA sequencing and microarray analyses. Furthermore, cytokine secretion of NLRP3 inhibitor treated blood and mucosal cells, as well as proliferation, collagen production, and cell death of NLRP3 inhibitor treated intestinal fibroblasts from IBD patients were studied. Results: We found increased NLRP3 expression in the inflamed mucosa of IBD patients and NLRP3 inhibition led to reduced IL-1β and IL-18 production in blood cells and diminished the bioactive form of mucosal IL-1β. Single cell analysis identified overlapping expression patterns of NLRP3 and IL-1β in classically activated intestinal macrophages and we also detected NLRP3 expression in CD163+ macrophages. In addition, NLRP3 expression was also found in intestinal fibroblasts from IBD patients. Inhibition of NLRP3 led to reduced proliferation of intestinal fibroblasts, which was associated with a marked decrease in production of collagen type I and type VI in IBD patients. Moreover, NLRP3 inhibition in intestinal fibroblasts induced autophagy, a cellular process involved in collagen degradation. Conclusions: In the presented study, we demonstrate that inhibiting NLRP3 might pave the way for novel therapeutic approaches in IBD, especially to prevent the severe complication of intestinal fibrosis formation.
CRIS-Team Scopus Importer:2023-11-17
Keywords: fibroblasts; fibrosis; IL-18; IL-1β; Inflammatory bowel diseases; mucosal immune system; NLRP3 inflammasome; small molecule inhibitor

No NETs no TIME: Crosstalk between neutrophil extracellular traps and the tumor immune microenvironment - Fang, Qi; Stehr, Antonia; Naschberger, Elisabeth; Knopf, Jasmin; Herrmann, Martin; Stürzl, Michael (Frontiers in Immunology, 2022)
The tumor immune microenvironment (TIME) controls tumorigenesis. Neutrophils are important components of TIME and control tumor progression and therapy resistance. Neutrophil extracellular traps (NETs) ejected by activated neutrophils are net-like structures composed of decondensed extracellular chromatin filaments decorated with a plethora of granules as well as cytoplasmic proteins. Many of these harbour post translational modifications. Cancer cells reportedly trigger NET formation, and conversely, NETs alter the TIME and promote tumor cell proliferation and migration. The specific interactions between NETs and TIME and the respective effects on tumor progression are still elusive. In certain tumors, a CD4(+) T helper (Th) 2 cell-associated TIME induces NETs and exerts immunosuppressive functions via programmed death 1 (PD-1)/PD-L1, both associated with poorer prognosis. In other cases, NETs induce the proliferation of Th1 cells, associated with an improved prognosis in cancer. In addition, NETs can drive macrophage polarization and often rely on macrophages to promote cancer cell invasion and metastasis. In turn, macrophages can swiftly clear NETs in an immunologically silent manner. The aim of this review is to summarize the knowledge about the mutual interaction between NETs and TIME and its impact on tumor growth and therapy.
CRIS-Team WoS Importer:2023-01-27
Keywords: adaptive immunity; innate immunity; macrophages; cancer; immunotherapy; tumor microenvironment; neutrophil extracellular traps; neutrophils

Noninvasive Bioluminescence Imaging of AKT Kinase Activity in Subcutaneous and Orthotopic NSCLC Xenografts: Correlation of AKT Activity with Tumor Growth Kinetics - Suchowski, Karina; Poechinger, Thomas; Rehemtulla, Alnawaz; Stürzl, Michael; Scheuer, Werner (Neoplasia, 2017)
Aberrant signaling through the AKT kinase mediates oncogenic phenotypes including cell proliferation, survival, and therapeutic resistance. Here, we utilize a bioluminescence reporter for AKT kinase activity (BAR) to noninvasively assess the therapeutic efficacy of the EGFR inhibitor erlotinib in KRAS-mutated lung cancer therapy. A549 non-small cell lung cancer cell line, engineered to express BAR, enabled the evaluation of compounds targeting the EGFR/PI3K/AKT pathway in vitro as well as in mouse models. We found that erlotinib treatment of resistant A549 subcutaneous and orthotopic xenografts resulted in significant AKT inhibition as determined by an 8- to 13-fold (P < .0001) increase in reporter activity 3 hours after erlotinib (100 mg/kg) administration compared to the control. This was confirmed by a 25% (P < .0001) decrease in pAKT ex vivo and a decrease in tumor growth. Treatment of the orthotopic xenograft with varying doses of erlotinib (25, 50, and 100 mg/kg) revealed a dose- and time-dependent increase in reporter activity (10-, 12-, and 23-fold). Correspondingly, a decrease in phospho-AKT levels (0%, 16%, and 28%, respectively) and a decrease in the AKT dependent proliferation marker PCNA (0%, 50%, and 50%) were observed. We applied ?-CT imaging for noninvasive longitudinal quantification of lung tumor load which revealed a corresponding decrease in tumor growth in a dose-dependent manner. These findings demonstrate the utility of BAR to noninvasively monitor AKT activity in preclinical studies in response to AKT modulating agents. These results also demonstrate that BAR can be applied to study drug dosing, drug combinations, and treatment efficacy in orthotopic mouse lung tumor models.
EVALuna2:15309

Noninvasive Sacral Neuromodulation in Children and Adolescents: A Case-Control Study of Patients With Chronic Refractory Constipation - Diez, Sonja; Kirchgatter, Annemarie; Adam, Dana; Füldner, Arne; Müller, Hanna; Matzel, Klaus; Besendörfer, Manuel (Neuromodulation, 2022)
Objectives: In adult patients with chronic refractory constipation, invasive sacral neuromodulation (SNM) has been applied successfully. There is a need for less invasive solutions while providing comparable therapeutic effects in children and adolescents. We present a prospective, interventional case-control study on the application of noninvasive SNM. Materials and Methods: Patients with chronic constipation refractory to conservative treatment were prospectively included in the study from 2018 to 2021 and randomized to either SNM (SNM group: single current stimulation for 24 h/d, frequency 15 Hz, pulse width 210 μs, intensity 1–10 mA) or conventional treatment (controls: full range of pharmacologic and nonpharmacologic options). Treatment was conducted for 12 weeks. Treatment effects were collected with specialized questionnaires and quality-of-life analysis (KINDLR). Outcome variables were defecation frequency, stool consistency, fecal incontinence (FI) episodes, and abdominal pain. Results: Analysis was conducted in 28 patients with SNM and 31 controls (median age 7.0, range 3–16 years). Overall responsiveness to treatment was 86% of the SNM group and 39% of the control group (p < 0.001). All outcome variables were positively influenced by SNM treatment. Defecation frequency improved in 46% of patients with SNM and in 19% of controls (p = 0.026), as did stool consistency in 57% of patients with SNM and in 26% of controls (p = 0.014). Fecal incontinence was significantly reduced in 76% of patients with SNM (n = 16/21 vs 42% of controls [n = 11/26], p = 0.042). Quality of life improved significantly during SNM treatment (71.32 [baseline] vs 85.00 [after 12 weeks], p < 0.001) and confirmed a positive influence of SNM treatment compared with the control group (85.00 [SNM after 12 weeks] vs 79.29 [controls after 12 weeks], p = 0.047). Conclusions: Outcome of noninvasive SNM treatment in patients with chronic refractory constipation is better than conventional treatment.
CRIS-Team Scopus Importer:2022-11-18
Keywords: Fecal incontinence; functional constipation; Hirschsprung disease; sacral nerve stimulation; sacral neuromodulation

Notch3 signalling promotes tumour growth in colorectal cancer - Serafin, Valentina; Persano, Luca; Moserle, Lidia; Esposito, Giovanni; Ghisi, Margherita; Curtarello, Matteo; Bonanno, Laura; Masiero, Massimo; Ribatti, Domenico; Stürzl, Michael; Naschberger, Elisabeth; Croner, Roland S.; et al. (Journal of Pathology, 2011)
Increased Notch1 activity has been observed in intestinal tumours, partially accomplished by β-catenin-mediated up-regulation of the Notch ligand Jagged-1. Whether further mechanisms of Notch activation exist and other Notch receptors might be involved is unclear. Microarray data indicated that Notch3 transcript levels are significantly up-regulated in primary and metastatic CRC samples compared to normal mucosa. Moreover, Notch3 protein was expressed at strong/moderate levels by 19.7% of 158 CRC samples analysed, and at weak levels by 51.2% of the samples. Intrigued by these findings, we sought to investigate whether Notch3 modulates oncogenic features of CRC cells. By exploiting xenografts of CRC cells with different tumourigenic properties in mice, we found that the aggressive phenotype was associated with altered expression of components of the Notch pathway, including Notch3, Delta-like 4 (DLL4), and Jagged-1 ligands. Stimulation with immobilized recombinant DLL4 or transduction with DLL4-expressing vectors dramatically increased Notch3 expression in CRC cells, associated with accelerated tumour growth. Forced expression of an active form of Notch3 mirrored the effects of DLL4 stimulation and increased tumour formation. Conversely, attenuation of Notch3 levels by shRNA resulted in perturbation of the cell cycle followed by reduction in cell proliferation, clonogenic capacity, and inhibition of tumour growth. Altogether, these findings indicate that Notch3 can modulate the tumourigenic properties of CRC cells and contributes to sustained Notch activity in DLL4-expressing tumours. Copyright © 2011 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.
Created from Fastlane, Scopus look-up
Keywords: angiogenesis; colorectal cancer; DLL4; Notch3

Novel criteria for intratumoral budding with prognostic relevance for colon cancer and its histological subtypes - Pour Farid, Pantea; Eckstein, Markus; Merkel, Susanne; Grützmann, Robert; Hartmann, Arndt; Bruns, Volker; Benz, Michaela; Schneider-Stock, Regine; Geppert, Carol-Immanuel (International Journal of Molecular Sciences, 2021)
Peritumoral budding and intratumoral budding (ITB) are important prognostic factors for colorectal cancer patients. Scientists worldwide have investigated the role of budding in tumor progression and its prognosis, but guidelines for reliably identifying tumor buds based on morphology are lacking. In this study, next-generation tissue microarray (ngTMA® ) construction was used for tumor bud evaluation, and highly detailed rule-out annotation was used for tumor definition in pancytokeratin-stained tissue sections. Initially, tissues of 245 colon cancer patients were evaluated with high interobserver reliability, and a concordance of 96% was achieved. It was shown that high ITB scores were associated with poor distant metastasis-free survival (p = 0.006 with a cut-off of ≥10 buds). This cut-off was defined as the best maximum value from one of two/three ngTMA® cores (0.6 mm diameter). ITB in 30 cases of mucinous, medullary, and signet ring cell carcinoma was analyzed for the subsequent determination of differences in tumor bud analyses between those subtypes. In conclusion, blinded randomized punched cores in the tumor center can be useful for ITB detection. It can be assumed that this method is suitable for its adoption in clinical routines.
CRIS-Team Scopus Importer:2021-12-17
Keywords: Histological subtypes; Immunohistochemistry; Medullary carcinoma; Metastasis; Mucinous carcinoma; Next-generation tissue microarray analysis; Prognostic biomarker; Signet ring cell carcinoma; Survival analysis; Tumor budding

Nuclear factor-κB motif and interferon-α-stimulated response element co-operate in the activation of guanylate-binding protein-1 expression by inflammatory cytokines in endothelial cells - Naschberger, Elisabeth; Stürzl, Michael; et al. (Biochemical Journal, 2004)
The large GTPase GBP-1 (guanylate-binding protein -1) is a major IFN-γ (interferon-γ)-induced protein with potent anti-angiogenic activity in endothelial cells. An ISRE (IFN-α-stimulated response element) is necessary and sufficient for the induction of GBP-1 expression by IFN-γ. Recently, we have shown that in vivo GBP-1 expression is strongly endothelial-cell-associated and is, in addition to IFN-γ, also activated by interleukin-1β and tumour necrosis factor-α, both in vitro and in vivo [Lubeseder-Martellato, Guenzi, Jörg, Töpolt, Naschberger, Kremmer, Zietz, Tschachler, Hutzler, Schwemmle et al. (2002) Am. J. Pathol. 161, 1749-1759; Guenzi, Töpolt, Cornali, Lubeseder-Martellato, Jörg, Matzen, Zietz, Kremmer, Nappi, Schwemmle et al. (2001) EMBO J. 20, 5568-5577]. In the present study, we identified a NF-κB (nuclear factor κB)-binding motif that, together with ISRE, is required for the induction of GBP-1 expression by interleukin-1β and tumour necrosis factor-α. Deactivation of the NF-κB motif reduced the additive effects of combinations of these cytokines with IFN-γ by more than 50%. Importantly, NF-κB p50 rather than p65 activated the GBP-1 promoter. The NF-κB motif and ISRE were detected in an almost identical spatial organization, as in the GBP-1 promoter, in the promoter regions of various inflammation-associated genes. Therefore both motifs may constitute a cooperative inflammatory cytokine response module that regulates GBP-1 expression. Our findings may open new perspectives for the use of NF-κB inhibitors to support angiogenesis in inflammatory diseases including ischaemia.
Created from Fastlane, Scopus look-up
Keywords: Guanylate-binding protein-1 (GBP-1); Human umbilical-vein endothelial cells (HUVEC); Inflammation; Interleukin-1; Nuclear factor κB (NF-κB); Tumour necrosis factor

Nucleotide-dependent farnesyl switch orchestrates polymerization and membrane binding of human guanylate-binding protein 1 - Shydlovskyi, Sergii; Zienert, Anke Y.; Ince, Semra; Dovengerds, Christine; Hohendahl, Annika; Dargazanli, Julia M.; Blum, Ailisa; Guenther, Saskia D.; Kladt, Nikolay; Stürzl, Michael; Schauss, Astrid C.; Kutsch, Miriam; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2017)
Dynamin-like proteins (DLPs) mediate various membrane fusion and fission processes within the cell, which often require the polymerization of DLPs. An IFN-inducible family of DLPs, the guanylate-binding proteins (GBPs), is involved in antimicrobial and antiviral responses within the cell. Human guanylate-binding protein 1 (hGBP1), the founding member of GBPs, is also engaged in the regulation of cell adhesion and migration. Here, we show how the GTPase cycle of farnesylated hGBP1 (hGBP1F) regulates its self-assembly and membrane interaction. Using vesicles of various sizes as a lipid bilayer model, we show GTP-dependent membrane binding of hGBP1F In addition, we demonstrate nucleotide-dependent tethering ability of hGBP1F Furthermore, we report nucleotide-dependent polymerization of hGBP1F, which competes with membrane binding of the protein. Our results show that hGBP1F acts as a nucleotide-controlled molecular switch by modulating the accessibility of its farnesyl moiety, which does not require any supportive proteins.
EVALuna2:15310

Obstructed defaecation syndrome: European consensus guidelines on the surgical management - Picciariello, Arcangelo; O'Connell, P. R.; Hahnloser, D.; Gallo, Gaetano; Munoz-Duyos, A.; Schwandner, O.; Sileri, P.; Milito, G.; Riss, S.; Boccasanta, P. A.; Naldini, G.; Arroyo, A.; et al. (British Journal of Surgery, 2021)
Lay Summary Clinical decision-making in the treatment of patients with obstructed defaecation remains controversial and no international guidelines have been provided so far. This study reports a consensus among European opinion leaders on the management of obstructed defaecation in different possible clinical scenarios.
CRIS-Team WoS Importer:2021-11-26

O-GlcNAc transferase inhibits KSHV propagation and modifies replication relevant viral proteins as detected by systematic O-GlcNAcylation analysis. - Jochmann, Ramona; Pfannstiel, Jens; Chudasama, Priya; Kühn, Elisabeth; Konrad, Andreas; Stürzl, Michael (Glycobiology, 2013)
O-GlcNAcylation is an inducible, highly dynamic and reversible post-translational modification, mediated by a unique enzyme named O-linked N-acetyl-d-glucosamine (O-GlcNAc) transferase (OGT). In response to nutrients, O-GlcNAc levels are differentially regulated on many cellular proteins involved in gene expression, translation, immune reactions, protein degradation, protein-protein interaction, apoptosis and signal transduction. In contrast to eukaryotic cells, little is known about the role of O-GlcNAcylation in the viral life cycle. Here, we show that the overexpression of the OGT reduces the replication efficiency of Kaposi's sarcoma-associated herpesvirus (KSHV) in a dose-dependent manner. In order to investigate the global impact of O-GlcNAcylation in the KSHV life cycle, we systematically analyzed the 85 annotated KSHV-encoded open reading frames for O-GlcNAc modification. For this purpose, an immunoprecipitation (IP) strategy with three different approaches was carried out and the O-GlcNAc signal of the identified proteins was properly controlled for specificity. Out of the 85 KSHV-encoded proteins, 18 proteins were found to be direct targets for O-GlcNAcylation. Selected proteins were further confirmed by mass spectrometry for O-GlcNAc modification. Correlation of the functional annotation and the O-GlcNAc status of KSHV proteins showed that the predominant targets were proteins involved in viral DNA synthesis and replication. These results indicate that O-GlcNAcylation plays a major role in the regulation of KSHV propagation.

Ökonomische Auswirkung der COVID-19-Pandemie in der Allgemein- und Viszeralchirurgie: Ein Vergleich von Leistungs- und Erlösdaten zweier Kliniken aus Krankenhäusern unterschiedlicher Versorgungsstufen - Binder, Johannes; Brunner, Maximilian; Maak, Matthias; Denz, Axel; Grützmann, Robert; Krautz, Christian; Weber, Georg (Chirurg, 2021)
Background: During the first wave of the coronavirus disease 2019 (COVID-19) pandemic, German hospitals were required to limit the capacity for elective surgery to prevent the healthcare system from general overload. In March 2020, the German government passed the COVID-19 Hospital Relief Act that guaranteed compensation payments for these limitations. In this study the regional impact of this intervention were analyzed. Material and methods: The performance data and revenue figures for the departments of general and visceral surgery of the University Hospital of Erlangen (UKER) and the District Hospital St. Anna Höchstadt/Aisch (KKH) during the period from 1 April to 30 June 2019 were compared with the respective period in 2020. Results: There was a significant decrease in bed occupancy rates and case numbers of inpatient treatment. The latter declined by 20.06% in the UKER and 60.76% in the KKH. Nononcological elective surgery was reduced by 33.04% in the UKER and 60.87% in the KKH. The number of emergency procedures remained unchanged in the UKER, while they decreased by 51.58% in the KKH. The revenues from diagnosis-related groups (DRG) decreased by 22.12% (UKER) and 54% (KKH), respectively. After taking compensation payments and savings from variable material costs into account, the UKER recorded a loss of −3.87%, while there was a positive revenue effect of 6.5% in the KKH. Discussion: The nonselective restriction of elective surgery had a significant impact on patient care and revenue figures at both locations. With respect to the increase of intensive care capacities, such untargeted measures do not appear to be efficient. In addition, the fixed rate of compensation payments led to an unbalanced distribution of the financial aid between the two departments.
CRIS-Team Scopus Importer:2021-07-02
Keywords: Coronavirus; DRG billing data; Hospital Relief Act; Surgery; Treatment quality

Old Age, nodular Melanoma, Tumor Thickness and Ulceration are Risk Factors for regional and systemic Metastases in Melanoma Patients after negative Sentinel Node Biopsy - Erdmann, M.; Dominik, S.; Göhl, Jonas; Grützmann, Robert; Schuler, Gerold; Schellerer, Vera (2017)
EVALuna2:15294

O-linked N-acetylglucosaminylation of Sp1 inhibits the human immunodeficiency virus type 1 promoter - Jochmann, Ramona; Thurau, Mathias; Jung, Susan; Hofmann, Christian; Naschberger, Elisabeth; Kremmer, Elisabeth; Harrer, Thomas; Miller, Matthew; Schaft, Niels; Stürzl, Michael (Journal of Virology, 2009)
Human immunodeficiency virus type 1 (HIV-1) gene expression and replication are regulated by the promoter/enhancer located in the U3 region of the proviral 5′ long terminal repeat (LTR). The binding of cellular transcription factors to specific regulatory sites in the 5′ LTR is a key event in the replication cycle of HIV-1. Since transcriptional activity is regulated by the posttranslational modification of transcription factors with the monosaccharide O-linked N-acetyl-D-glucosamine (O-GlcNAc), we evaluated whether increased O-GlcNAcylation affects HIV-1 transcription. In the present study we demonstrate that treatment of HIV-1-infected lymphocytes with the O-GlcNAcylation-enhancing agent glucosamine (GlcN) repressed viral transcription in a dose-dependent manner. Overexpression of O-GlcNAc transferase (OGT), the sole known enzyme catalyzing the addition of O-GlcNAc to proteins, specifically inhibited the activity of the HIV-1 LTR promoter in different T-cell lines and in primary CD4+ T lymphocytes. Inhibition of HIV-1 LTR activity in infected T cells was most efficient (>95%) when OGT was recombinantly overexpressed prior to infection. O-GlcNAcylation of the transcription factor Sp1 and the presence of Sp1-binding sites in the LTR were found to be crucial for this inhibitory effect. From this study, we conclude that O-GlcNAcylation of Sp1 inhibits the activity of the HIV-1 LTR promoter. Modulation of Sp1 O-GlcNAcylation may play a role in the regulation of HIV-1 latency and activation and links viral replication to the glucose metabolism of the host cell. Hence, the establishment of a metabolic treatment might supplement the repertoire of antiretroviral therapies against AIDS. Copyright © 2009, American Society for Microbiology. All Rights Reserved.
Created from Fastlane, Scopus look-up

Omega suture technique for minimally invasive rectal anastomosis – a video vignette - Brunner, Maximilian; Weber, Klaus; Denz, Axel; Langheinrich, Melanie; Kersting, Stephan; Weber, Georg; Grützmann, Robert; Krautz, Christian (Colorectal Disease, 2023)
CRIS-Team Scopus Importer:2023-05-19

Oncogenesis in HIV-infection. - Albini, Adriana; Aluigi, M; Benelli, Roberto; Biberfeld, Peter; Blasig, C; Calabro, M; Calvo, F; Chieco-Bianchi, L; Corbellino, M; Del Mistro, A; Ekman, M; Favero, A; et al. (International Journal of Oncology, 1996)
The presence of human Kaposi's sarcoma associated herpesvirus-like sequences (KSHV) was examined in different epidemiological variants of Kaposi's sarcoma (KS) and in KS-derived cell cultures by polymerase chain reaction (PCR). KSHV DNA was present in all tumor biopsies of AIDS-associated KS (59 biopsies), endemic KS (26 biopsies; 21 African endemic KS, 5 Greek endemic KS), sporadic/classical KS (28 biopsies) and post-transplant/iatrogenic KS (6 of 7 biopsies). On the contrary, these sequences were only detected rarely in non-involved skin of KS patients (3 positive specimens of 12), in the peripheral blood mononuclear cells of HIV-infected patients (3 positive specimens of 54) and in lymphoma-biopsies (3 positive specimens of 47). Cell cultures derived from KS skin lesions were positive for KSHV DNA only in the first two passages. However, two longer-term positive cultures from a biopsy of a patient affected with sporadic KS and a biopsy of a patient affected with epidemic KS was identified. A strong association of KSHV with KS tissue was observed in all the different epidemiological variants of KS. Long-term positive KS-derived cell cultures will be an important tool to study the herpesvirus-like agent and to investigate its functional role in the initiation and progression of KS.

Oncological colorectal surgery during the COVID-19pandemic—a national survey - Brunner, Maximilian; Krautz, Christian; Kersting, Stephan; Stinner, Benno; Benz, Stefan R.; Grützmann, Robert; Weber, Georg (International Journal of Colorectal Disease, 2020)
Purpose: The aim of this study was to clarify the surgical supply situation of oncological colorectal patients in Germany during limitations of the OR caseload due to the COVID-19 pandemic. Methods: Between 11th and 19th April 2020, all members of a consortium of German colorectal cancer centers were invited to participate in a web-based survey on the current status of surgical care situation of colorectal cancer patients in Germany. Results: A total of 112 colorectal surgeons of 101 German hospitals participated in the survey. Eighty-seven percent of the participating hospitals had to reduce their total surgical caseload and 34% their surgical volume for oncological colorectal patients during COVID-19 pandemic. Restrictions of the surgical caseload were independent of the size of the hospital and the number of cases of COVID-19 in the federal state of the hospital. Sixteen percent of colorectal surgeons consider surgical limitations to be not justified and 78% to be justified only if the care of oncological patients is ensured. Ninety-five percent of the colorectal surgeons interviewed stated that all oncological colorectal patients with an indication for surgery should be operated in time, despite the current reservations for COVID-19 patients. For the majority of the respondents (63% and 51%, respectively), an extended waiting time for surgery of up to 2 weeks was acceptable for non-metastatic and metastatic patients, respectively. Conclusion: In Germany, there is a temporarily relevant reduction of surgical volume in oncological colorectal patients. Most colorectal surgeons stated that oncological colorectal surgery should not be compromised despite the measures taken during the COVID-19 pandemic.
CRIS-Team Scopus Importer:2020-08-07
Keywords: Colorectal surgery; COVID-19 pandemic; Oncological surgery; SARS-CoV-2 infection; Surgical caseload

Oncological outcome after hyperthermic isolated limb perfusion for primarily unresectable versus locally recurrent soft tissue sarcoma of extremities - Vassos, N.; Brunner, Maximilian; Perrakis, A.; Göhl, Jonas; Grützmann, Robert; Hohenberger, Werner; Croner, R. S. (Surgical Oncology-Oxford, 2020)
Introduction: The management of locally advanced extremity soft tissue sarcomas, particularly in terms of a limb salvage strategy, represents a challenge, especially in recurrent tumors. In the context of a patient-tailored multimodal therapy, hyperthermic isolated limb perfusion (ILP) is a promising limb-saving treatment option. We report the outcome of patients with primarily irresectable and locally recurrent soft tissue sarcoma (STS) treated by ILP. Patients and methods: Data about patient demographics, clinical und histopathological characteristics, tumor response, morbidity and oncological outcome of all patients with STS, who underwent an ILP at our institution in a 10-year period, were retrospectively detected and analyzed. Results: The cohort comprised 30 patients. Two patients were treated with ILP for palliative tumor control, 13 patients because of a local recurrent soft tissue sarcoma (rSTS) and 15 patients because of primarily unresectable soft tissue sarcoma (puSTS). 25 of the 28 patients with curative intention received surgery after ILP (11 pts with rSTS and 14 pts with puSTS). Histopathologically we observed complete response in 6 patients (24%) and partial responses in 19 patients (76%) with a significant better remission in patients with puSTS (p = 0,043). Limb salvage rate was 75%. Mean follow-up was 69 months [range 13–142 months]. Seven (7/11; 64%) patients with rSTS and one (1/14; 7%) patient with puSTS developed local recurrence after ILP and surgery, whereas eight (8/13; 62%) rSTS patients and seven (7/15; 47%) puSTS patients developed distant metastasis. During follow-up, eight patients (28.5%) died of disease (5/13; 38%) rSTS and 3/15 (20%) puSTS. ILP in the group of previously irradiated sarcoma patients (n = 13) resulted in a limb salvage rate of 69% and was not associated in an increased risk for adverse events. Discussion: ILP for advanced extremity STS is a treatment option for both puSTS and rSTS resulting in good local control and should be considered in multimodal management. ILP is also a good option for patients after radiation history.
CRIS-Team Scopus Importer:2020-09-11
Keywords: Isolated limb perfusion; Recurrent; Soft tissue sarcoma

One Step Nucleic Acid Amplification (OSNA) - a new method for lymph node staging in colorectal carcinomas - Croner, Roland S.; Schellerer, Vera; Demund, Helene; Schildberg, Claus; Papadopulos, Thomas; Naschberger, Elisabeth; Stürzl, Michael; Matzel, Klaus E.; Hohenberger, Werner; Schlabrakowski, Anne (Journal of Translational Medicine, 2010)
Background: Accurate histopathological evaluation of resected lymph nodes (LN) is essential for the reliable staging of colorectal carcinomas (CRC). With conventional sectioning and staining techniques usually only parts of the LN are examined which might lead to incorrect tumor staging. A molecular method called OSNA (One Step Nucleic Acid Amplification) may be suitable to determine the metastatic status of the complete LN and therefore improve staging.Methods: OSNA is based on a short homogenisation step and subsequent automated amplification of cytokeratin 19 (CK19) mRNA directly from the sample lysate, with result available in 30-40 minutes. In this study 184 frozen LN from 184 patients with CRC were investigated by both OSNA and histology (Haematoxylin & Eosin staining and CK19 immunohistochemistry), with half of the LN used for each method. Samples with discordant results were further analysed by RT-PCR for CK19 and carcinoembryonic antigen (CEA).Results: The concordance rate between histology and OSNA was 95.7%. Three LN were histology+/OSNA- and 5 LN histology-/OSNA+. RT-PCR supported the OSNA result in 3 discordant cases, suggesting that metastases were exclusively located in either the tissue analysed by OSNA or the tissue used for histology. If these samples were excluded the concordance was 97.2%, the sensitivity 94.9%, and the specificity 97.9%. Three patients (3%) staged as UICC I or II by routine histopathology were upstaged as LN positive by OSNA. One of these patients developed distant metastases (DMS) during follow up.Conclusion: OSNA is a new and reliable method for molecular staging of lymphatic metastases in CRC and enables the examination of whole LN. It can be applied as a rapid diagnostic tool to estimate tumour involvement in LN during the staging of CRC. © 2010 Croner et al; licensee BioMed Central Ltd.
Created from Fastlane, Scopus look-up

Operationsindikationen bei neuroendokrinen Neoplasien des Pankreas - Bösch, Florian; Belyaev, Orlin; Brunner, Maximilian; Müller-Debus, Charlotte Friederieke; Grützmann, Robert; Keck, Tobias; Uhl, Waldemar; Witzigmann, Helmut; Werner, Jens (Zentralblatt für Chirurgie, 2020)
Neuroendocrine neoplasms of the pancreas (pNEN) have an increasing incidence and prevalence. Thus, this entity is of increasing clinical significance. Patients with pNEN become clinically apparent due to different and unspecific symptoms. Some tumours secrete hormones and peptides and become clinically symptomatic. In general, these tumours can metastasise early and even small tumours lead to distant metastases. Nonetheless, primary tumour size and grading are important prognostic factors. On the basis of a systematic literature research and the formulation of key issues according to the PICO system, therapeutic concepts were established. These concepts were evaluated with a Delphi process among the members of the pancreas research group and the indications for surgery group of the German Society of General and Visceral Surgery. Thus this article gives an overview of the surgical treatment modalities and indications for the treatment of pNEN. Surgery is still the gold standard in treatment and the only potential chance of cure. Surgery is indicated for sporadic as well as hereditary pNEN > 2 cm independent of the functional activity. A so called wait and see strategy might be indicated in smaller pNEN; however, there is little evidence for this approach. In this respect, pNEN of 1-2 cm represent a surgical indication. The treatment of hereditary pNEN is challenging and should be interdisciplinary. Even in the case of distant metastases, a curative approach might be feasible and multimodal treatment is indicated.
CRIS-Team Scopus Importer:2020-08-07
Keywords: neuroendocrine neoplasm; operative indication; pancreas; pancreatic surgery; tumour size

Operationsindikationen bei zystischen Tumoren des Pankreas - Brunner, Maximilian; Belyaev, Orlin; Bösch, Florian; Müller-Debus, Charlotte Friederieke; Radulova-Mauersberger, Olga; Wellner, Ulrich Friedrich; Keck, Tobias; Uhl, Waldemar; Werner, Jens; Witzigmann, Helmut; Grützmann, Robert (Zentralblatt für Chirurgie, 2020)
A steady improvement in modern imaging as well as increasing age in society have led to an increasing number of cystic pancreatic tumours being detected. Pancreatic cysts are a clinically challenging entity because they span a broad biological spectrum and their differentiation is often difficult, especially in small tumours. Therefore, they require a differentiated indication for indication of surgery. To determine recommendations for the surgical indication in cystic tumours of the pancreas, a quality committee for pancreatic diseases of the German Society for General and Visceral Surgery performed a systematic literature search and created this review. Based on the current evidence, signs of malignancy and high-risk criteria (icterus due to cystic pancreatic duct obstruction in the bile duct, enhancing mural nodules ≥ 5 mm or solid components in the cyst or pancreatic duct ≥ 10 mm), as well as symptoms, are a surgical indication, independently of the cyst entity (except pseudocysts). If the entity of the pancreatic cyst is detectable by diagnostic imaging, all main duct IPMN and IPMN of the mixed type, all MCN > 4 cm and all SPN should be resected. SCN and branch-duct IPMN without worrisome features do not constitute an indication for surgery. The indication of operation in branch-duct IPMN with relative risk criteria and MCN < 4 cm is the subject of current discussions and should be individualised. By defining indication recommendations, the present work aims to improve the indication quality in cystic pancreatic tumours. However, the surgical indication should always be individualised, taking into account age, comorbidities and the patient's wishes.
CRIS-Team Scopus Importer:2020-09-04

Orphan Nuclear Receptor Ror alpha Is a Key Regulator of Tgf beta- and WNT-Signaling in Fibrotic Diseases - Kagwiria, Rosebeth; Liang, Ruifang; Matei, Alexandru-Emil; Sihler, Niclas; Chen, Chih-Wei; Burris, Thomas; Distler, Oliver; Schett, Georg; Distler, Jörg (2018)
EVALuna2:34962

Outcome and complications of endoscopic balloon dilatations in various types of ileocaecal and colonic stenosis in patients with Crohn's disease - Hagel, Alexander; Hahn, Anna; Dauth, Wolfgang; Matzel, Klaus; Konturek, Peter C.; Neurath, Markus; Raithel, Martin (Surgical Endoscopy, 2014)
We examined the outcome and the complications of endoscopic balloon dilatation (EBD) of ileocaecal and colonic strictures due to Crohn's disease.We examined 237 dilatation procedures in 77 patients with symptomatic ileocaecal and colonic stenosis regarding outcome, individual perforation risk, the need for further interventions, and other complications within a 10 years observation period.In 50 of 77 patients (64.9%), endoscopic dilatation procedures were successful within a median follow-up period of 24 months (25th and 75th percentile 10-38.5 months). Thirty five patients (45.5%) were successfully dilated with only one endoscopic procedure, while the remaining patients required two or more EBDs. Albeit the EBD, 27 patients of the whole cohort (35.1%) underwent surgical repair of the stenosis in due course. Overall complication rate was 7.6%, with postdilatation bleeding in 1.7% and abdominal pain longer than 24 h in 4.2%. Perforation occurred in 4 of 77 patients (5.2%), resulting in a perforation rate of 1.7% per intervention, or, more importantly, for the individual patient in a long-term perforation rate of 5.2% per patient, respectively.Endoscopic balloon dilatation (EBD) is a safe and effective approach to ileocaecal and colonic stenosis in approximately 65% of Crohn's disease patients. Even in case of recurrence, further endoscopic treatments can be undertaken. The perforation rate depending on the number of interventions is low, but for the individual patient a cumulative per patient perforation risk of 5.2% in the long-term should be considered during patient information and decisions for or against surgical interventions.
EVALuna2:1834

Outcomes After Distal Pancreatectomy with Celiac Axis Resection for Pancreatic Cancer: A Pan-European Retrospective Cohort Study - Klompmaker, Sjors; Van Hilst, Jony; Gerritsen, Sarah L.; Adham, Mustapha; Quer, M. Teresa Albiol; Bassi, Claudio; Berrevoet, Frederik; Boggi, Ugo; Busch, Olivier R.; Cesaretti, Manuela; Dalla Valle, Raffaele; Darnis, Benjamin; et al. (Annals of Surgical Oncology, 2018)
BACKGROUND: Western multicenter studies on distal pancreatectomy with celiac axis resection (DP-CAR), also known as the Appleby procedure, for locally advanced pancreatic cancer are lacking. We aimed to study overall survival, morbidity, mortality and the impact of preoperative hepatic artery embolization (PHAE). METHODS: Retrospective cohort study within the European-African Hepato-Pancreato-Biliary-Association, on DP-CAR between 1-1-2000 and 6-1-2016. Primary endpoint was overall survival. Secondary endpoints were radicality (R0-resection), 90-day mortality, major morbidity, and pancreatic fistulae (grade B/C). RESULTS: We included 68 patients from 20 hospitals in 12 countries. Postoperatively, 53% of patients had R0-resection, 25% major morbidity, 21% an ISGPS grade B/C pancreatic fistula, and 16% mortality. In total, 82% received (neo-)adjuvant chemotherapy and median overall survival in 62 patients with pancreatic ductal adenocarcinoma patients was 18 months (CI 10-37). We observed no impact of PHAE on ischemic complications. CONCLUSIONS: DP-CAR combined with chemotherapy for locally advanced pancreatic cancer is associated with acceptable overall survival. The 90-day mortality is too high and should be reduced. Future studies should investigate to what extent increasing surgical volume or better patient selection can improve outcomes.
EVALuna2:202862

Outcomes research in pancreatic cancer surgery - Krautz, Christian; Grützmann, Robert (Onkologe, 2017)
Background. Numerous international studies have identified hospital volume as a significant independent variable of death following complex surgery. Based on these data many countries aimed to centralize complex procedures, such as pancreatic surgery by the introduction of minimum caseload requirements. Objective. To summarize the current body of outcomes research on pancreatic cancer surgery and to investigate international experiences with the centralization of surgical care in this field. Material and methods. A systematic literature search was performed to identify studies that examined volume-outcome relationships and the effects of minimum caseload requirements on care structures and outcomes of pancreatic cancer surgery. Results. Several national and international studies confirmed that patients undergoing pancreatic surgery have better outcomes when treated in facilities with high annual caseloads. In countries with a relevant centralization of care structures impressive improvements of surgical outcomes have been reported. In Germany, a large proportion of hospitals that perform pancreatic surgery still do not meet the minimum caseload requirements. As a result of insufficient centralization in the recent past, mortality rates on the national level in Germany have remained unchanged. Conclusion. In view of the impressive results of other countries, efficient concentration of care structures seems to be the key to improvement of surgical outcomes in pancreatic surgery.
EVALuna2:15304

Overview of Subtypes and Therapies of acute Mesenteric Ischemia EAMI, TAMI, VAMI, NOMI - How to detect and treat them - Eckhardt, Daniel; Schmid, Axel; Grützmann, Robert (Zentralblatt für Chirurgie, 2019)
CRIS-Team WoS Importer:2021-10-18

p21 Prevents the Exhaustion of CD4+ T Cells Within the Antitumor Immune Response Against Colorectal Cancer - Thoma, Oana-Maria; Naschberger, Elisabeth; Kubánková, Markéta; Larafa, Imen; Kramer, Viktoria; Menchicchi, Bianca; Merkel, Susanne; Britzen-Laurent, Nathalie; Jefremow, André; Grützmann, Robert; Koop, Kristina; Neufert, Clemens; et al. (Gastroenterology, 2024)
Background & Aims: T cells are crucial for the antitumor response against colorectal cancer (CRC). T-cell reactivity to CRC is nevertheless limited by T-cell exhaustion. However, molecular mechanisms regulating T-cell exhaustion are only poorly understood. Methods: We investigated the functional role of cyclin-dependent kinase 1a (Cdkn1a or p21) in cluster of differentiation (CD) 4+ T cells using murine CRC models. Furthermore, we evaluated the expression of p21 in patients with stage I to IV CRC. In vitro coculture models were used to understand the effector function of p21-deficient CD4+ T cells. Results: We observed that the activation of cell cycle regulator p21 is crucial for CD4+ T-cell cytotoxic function and that p21 deficiency in type 1 helper T cells (Th1) leads to increased tumor growth in murine CRC. Similarly, low p21 expression in CD4+ T cells infiltrated into tumors of CRC patients is associated with reduced cancer-related survival. In mouse models of CRC, p21-deficient Th1 cells show signs of exhaustion, where an accumulation of effector/effector memory T cells and CD27/CD28 loss are predominant. Immune reconstitution of tumor-bearing Rag1−/− mice using ex vivo-treated p21-deficient T cells with palbociclib, an inhibitor of cyclin-dependent kinase 4/6, restored cytotoxic function and prevented exhaustion of p21-deficient CD4+ T cells as a possible concept for future immunotherapy of human disease. Conclusions: Our data reveal the importance of p21 in controlling the cell cycle and preventing exhaustion of Th1 cells. Furthermore, we unveil the therapeutic potential of cyclin-dependent kinase inhibitors such as palbociclib to reduce T-cell exhaustion for future treatment of patients with colorectal cancer.
CRIS-Team Scopus Importer:2024-01-19
Keywords: CD4; Colorectal Cancer; p21; Palbociclib

Palliative therapy concepts for pancreatic carcinoma - Brunner, Michaela; Grützmann, Robert; Weber, Georg (Chirurg, 2018)
The majority of patients with ductal pancreatic adenocarcinoma are already in a locally advanced or metastatic stage at the time of diagnosis and require palliative therapy. Interventional and operative measures are available for the restoration of biliary outflow in bile duct obstruction and the continuity of the upper intestinal lumen in duodenal or gastric outlet obstruction. In the presence of tumor-related pain, pain therapy according to the World Health Organization (WHO) scheme or a truncus coeliacus blockade, in cachexia a nutritional therapy and in thromboembolic events an anticoagulant therapy are used. An individualized palliative chemotherapy regimen should be selected for each patient, taking into account the patient's general condition and the side effects profile of the chemotherapeutic agents. Radiochemotherapy and local ablative therapies should currently only be used within the framework of studies. A palliative resection is not recommended according to current knowledge.
EVALuna2:212624

Palliative Treatment of Colorectal Cancer with Secondary Metastasis Resection in Germany - Impact of the Multidisciplinary Treatment Approach on Prognosis and Cost: The Northern Bavaria IVOPAK I Project - Wein, Axel; Emmert, Martin; Merkel, Susanne; Harich, Hans-Detlev; Thiemann, Roland; Lamberti, Christof; Göttler, Bernhard; Fries, Stefan; Kiani, Alexander; Schlag, Rudolf; Grüner, Marcus; Steinbild, Simone; et al. (Oncology, 2015)
Purpose The aim of this study was to evaluate the quality of care and interdisciplinary cooperation in the palliative treatment of colorectal cancer (CRC), including the associated costs. Patients and Methods 103 patients were enrolled from 13 institutions to reflect the existing clinical treatment reality and costs of palliative CRC treatment. We present the clinical outcome of the patients and compare the results obtained in the 3 centers with double-figure recruitment numbers (centers A, B, and C). Results First-line treatment with 5-fluorouracil monotherapy was applied in exceptional cases. The regular treatment method comprised either an irinotecan- (30%) or an oxaliplatin-based regimen (32%). Biological agents were added to the treatment of 33 patients (32%). The median overall survival (OS) of the total patient collective was 25 months. The OS differed significantly in 2 out of the 3 centers, ranging between 27 and 11 months. Secondary metastasis resections were performed in 26% of the total patient collective. The center with the most favorable outcome results also had the lowest costs for palliative treatment and care, including the lowest drug costs. Conclusion A combined chemotherapy treatment was the rule. Concerning biological agents, a significant lack of their application in first-line treatment and the quality of interdisciplinary cooperation have to be addresse
Keywords: Interdisciplinary cooperation; Costs; Colorectal cancer; Palliative treatment results

Pancreas transplantation as rescue therapy in a patient with type 1 diabetes and concurrent subcutaneous insulin resistance - Füermann, Florian; Heller, Katharina M.; Pavel, Marianne Ellen; Herbst, Larissa; Grützmann, Robert; Schiffer, Mario (American Journal of Transplantation, 2024)
Patients with type 1 diabetes and concurrent subcutaneous insulin resistance present unique diagnostic and therapeutic challenges for clinicians. The standard therapeutic approach is the administration of intravenous insulin. Pancreatic transplantation should be considered at an appropriate time, particularly in the event of life-threatening ketoacidosis, hyperglycemia, hypoglycemia, catheter-associated thrombosis, and infections. We present the case of a 24-year-old woman with type 1 diabetes since early childhood and increasingly uncontrollable subcutaneous and intramuscular insulin resistance. Furthermore, we present the diagnostic pathway and therapeutic interventions performed, culminating in pancreatic transplantation as a curative approach. Immediate graft function resulted in optimal glycemic control.
CRIS-Team Scopus Importer:2024-11-01
Keywords: pancreas transplantation; subcutaneous insulin resistance; type 1 diabetes

Pancreatic cystic space-occupying lesions-Diagnostics, treatment and follow-up care Current recommendations taking the current German S3 guidelines on pancreatic cancer into account - Brunner, Maximilian; Haeberle, Lena; Esposito, Irene; Grützmann, Robert (Chirurg, 2022)
Due to their increased detection pancreatic cystic space-occupying lesions are becoming increasingly relevant in the clinical routine and represent a morphologically and biologically heterogeneous and thus clinically demanding as well as potentially (pre)malignant entity. As a result, recommendations for the diagnostics and treatment of pancreatic cystic tumors have now been incorporated into the current German S3 guidelines on pancreatic cancer. The diagnostics of pancreatic cystic space-occupying lesions are based on the following three elements: collection of relevant clinical information, performance of high-resolution imaging procedures and if diagnostic uncertainty persists, puncture diagnostics. Differentiated diagnostics are of essential importance as these represent the basis for an adequate treatment decision. Pancreatic cystic lesions with a relevant risk of malignant transformation, e.g., main duct intraductal papillary mucinous neoplasms (IPMN), followed by mucinous cystic neoplasms (MCN), solid pseudopapillary neoplasms (SPN) and generally pancreatic cystic lesions with risk factors independent of the entity, should be resected, whereas a differentiated and individualized approach is necessary, especially for branch-duct IPMNs. The serous cystic neoplasms (SCN) have no malignant potential and do not require any treatment if they are asymptomatic. Important principles in surgery of pancreatic cancer, such as adequate surgical resection taking oncological standards into account and standardized appropriate histopathological processing of the specimens as well as intraoperative frozen section analysis also play an important role in pancreatic cystic space-occupying lesions. An annual follow-up seems to be meaningful, especially for IPMNs.
CRIS-Team WoS Importer:2022-04-01

Paraduodenal pancreatitis as diagnostic challenge: clinical and morphological features of patients with pancreatic pathology involving the pancreatic groove. - Vitali, Francesco; Heinrich, Marc Christopher; Strobel, Deike; Zundler, Sebastian; Aghdassi, Ali A; Uder, Michael; Neurath, Markus; Grützmann, Robert; Wiesmüller, Marco; Frulloni, Luca; Wildner, Dane (Annals of Gastroenterology, 2024)
BACKGROUND: Paraduodenal pancreatitis (PP) is an inflammation involving the groove zone, delimited by the duodenum lumen, bile duct, and the head of the pancreas. This area may also be involved during acute pancreatitis (AP). The differential diagnosis is clinically relevant, since PP generally persists, whereas AP resolves. Hence, we compared a cohort of patients with PP and AP involving the groove area. METHODS: We retrospectively evaluated patients with pathology involving the groove area. The primary aim was to define the diagnostic features of PP compared to non-PP pancreatitis involving the groove area. PP was diagnosed by imaging, while AP was diagnosed according to the revised Atlanta classification and the clinical course, to exclude chronic pancreatitis. RESULTS: The study population consisted of 37 patients (32 men, age 56.9±9.1 years), 25 with a diagnosis of PP (23 men, mean age 54.9±8.5 years), and 12 (9 men, mean age 61.2±9.2 years) with AP involving the groove. All 25 patients with PP and 4 (33.3%) with AP reported a history of alcohol abuse, 23 patients (92%) with PP, and 3 (25%) with AP had a history of smoking. On imaging, PP patients presented a significantly thicker duodenal wall compared to the AP group (P=0.010). Chronic pancreatitis in the body/tail and exocrine insufficiency was prevalent in PP (P<0.001 and P=0.02). The medial displacement of the gastroduodenal artery was more frequent in the PP group (P=0.011). CONCLUSION: PP has a different clinical and imaging profile compared to AP involving the groove area.
EVALuna2:583244

Partial pancreatoduodenectomy versus duodenum-preserving pancreatic head resection in chronic pancreatitis: the multicentre, randomised, controlled, double-blind ChroPac trial - Diener, Markus K.; Huettner, Felix J.; Kieser, Meinhard; Knebel, Phillip; Doerr-Harim, Colette; Distler, Marius; Grützmann, Robert; Wittel, Uwe A.; Schirren, Rebekka; Hau, Hans-Michael; Kleespies, Axel; Heidecke, Claus-Dieter; et al. (Lancet, 2017)
There is substantial uncertainty regarding the optimal surgical treatment for chronic pancreatitis. Short-term outcomes have been found to be better after duodenum-preserving pancreatic head resection (DPPHR) than after partial pancreatoduodenectomy. Therefore, we designed the multicentre ChroPac trial to investigate the long-term outcomes of patients with chronic pancreatitis within 24 months after surgery.This randomised, controlled, double-blind, parallel-group, superiority trial was done in 18 hospitals across Europe. Patients with chronic pancreatitis who were planned for elective surgical treatment were randomly assigned to DPPHR or partial pancreatoduodenectomy with a central web-based randomisation tool. The primary endpoint was mean quality of life within 24 months after surgery, measured with the physical functioning scale of the European Organisation for Research and Treatment of Cancer QLQ-C30 questionnaire. Primary analysis included all patients who underwent one of the assigned procedures; safety analysis included all patients who underwent surgical intervention (categorised into groups as treated). Patients and outcome assessors were masked to group assignment. The trial was registered, ISRCTN38973832. Recruitment was completed on Sept 3, 2013.Between Sept 10, 2009, and Sept 3, 2013, 250 patients were randomly assigned to DPPHR (n=125) or partial pancreatoduodenectomy (n=125), of whom 226 patients (115 in the DPPHR group and 111 in the partial pancreatoduodenectomy group) were analysed. No difference in quality of life was seen between the groups within 24 months after surgery (75·3 [SD 16·4] for partial pancreatoduodenectomy vs 73·0 [16·4] for DPPHR; mean difference -2·3, 95% CI -6·6 to 2·0; p=0·284). The incidence and severity of serious adverse events did not differ between the groups. 70 (64%) of 109 patients in the DPPHR group and 61 (52%) of 117 patients in the partial pancreatoduodenectomy group had at least one serious adverse event, with the most common being reoperations (for reasons other than chronic pancreatitis), gastrointestinal problems, and other surgical morbidity.No differences in quality of life after surgery for chronic pancreatitis were seen between the interventions. Results from single-centre trials showing superiority for DPPHR were not confirmed in the multicentre setting.German Research Foundation (DFG).
EVALuna2:15300

Pathological function of neutrophil extracellular traps in human colon cancer - Stehr, Antonia; Wang, Guangxia; Demmler, Richard; Stemmler, Marc; Tripal, Philipp; Geppert, Carol-Immanuel; Merkel, Susanne; Herrmann, Martin; Stürzl, Michael (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-12-16

Pathophysiological role of guanylate-binding proteins in gastrointestinal diseases - Britzen-Laurent, Nathalie; Herrmann, Christian; Naschberger, Elisabeth; Croner, Roland S.; Stürzl, Michael (World Journal of Gastroenterology, 2016)
Guanylate-binding proteins (GBPs) are interferon-stimulated factors involved in the defense against cellular pathogens and inflammation. These proteins, particularly GBP-1, the most prominent member of the family, have been established as reliable markers of interferon-?-activated cells in various diseases, including colorectal carcinoma (CRC) and inflammatory bowel diseases (IBDs). In CRC, GBP-1 expression is associated with a Th1-dominated angiostatic micromilieu and is correlated with a better outcome. Inhibition of tumor growth by GBP-1 is the result of its strong anti-angiogenic activity as well as its direct anti-tumorigenic effect on tumor cells. In IBD, GBP-1 mediates the anti-proliferative effects of interferon-? on intestinal epithelial cells. In addition, it plays a protective role on the mucosa by preventing cell apoptosis, by inhibiting angiogenesis and by regulating the T-cell receptor signaling. These functions rely to a large extent on the ability of GBP-1 to interact with and remodel the actin cytoskeleton.
EVALuna2:15238

Patients with COVID-19: in the dark-NETs of neutrophils - Ackermann, Maximilian; Anders, Hans-Joachim; Bilyy, Rostyslav; Bowlin, Gary L.; Daniel, Christoph; De Lorenzo, Rebecca; Egeblad, Mikala; Henneck, Timo; Hidalgo, Andres; Hoffmann, Markus; Hohberger, Bettina; Kanthi, Yogendra; et al. (Cell Death and Differentiation, 2021)
SARS-CoV-2 infection poses a major threat to the lungs and multiple other organs, occasionally causing death. Until effective vaccines are developed to curb the pandemic, it is paramount to define the mechanisms and develop protective therapies to prevent organ dysfunction in patients with COVID-19. Individuals that develop severe manifestations have signs of dysregulated innate and adaptive immune responses. Emerging evidence implicates neutrophils and the disbalance between neutrophil extracellular trap (NET) formation and degradation plays a central role in the pathophysiology of inflammation, coagulopathy, organ damage, and immunothrombosis that characterize severe cases of COVID-19. Here, we discuss the evidence supporting a role for NETs in COVID-19 manifestations and present putative mechanisms, by which NETs promote tissue injury and immunothrombosis. We present therapeutic strategies, which have been successful in the treatment of immunο-inflammatory disorders and which target dysregulated NET formation or degradation, as potential approaches that may benefit patients with severe COVID-19.
CRIS-Team Scopus Importer:2021-06-04

PCR-synthesized single-stranded DNA: a useful tool for 'hyb' and 'HAP' standardization for construction of subtraction libraries. - Stürzl, Michael; Roth, Willy Kurt (Trends in Genetics, 1990)

Permacol collagen paste for cryptoglandular and Crohn's anal fistula - Brunner, Michaela; Schneider, Ignaz Hans Friedrich; Guenther, K.; Grützmann, Robert; Matzel, Klaus (Techniques in Coloproctology, 2019)
BackgroundPermacol collagen paste, an acellular crosslinked porcine dermal collagen matrix suspension, is a new treatment option for anal fistula. Data remain limited, however, and as yet only the results of one case of Crohn's fistula treated with Permacol paste has been reported. The aim of this study was to assess the use of Permacol collagen paste in patients with cryptoglandular and Crohn's perianal fistulae.MethodsA prospective study was conducted on patients with anal fistula, treated with Permacol paste. Patients were followed at 1week, 6 and 12months, and on demand thereafter. The main focus was on fistula healing and postoperative continence. The former was defined as the absence of signs of recurrence on clinical examination, proctoscopy and rigid rectoscopy. Fecal incontinence was assessed before surgery and at each follow-up.ResultsThirty patients (19 women, 11 men; mean age 46years), 12 (40%) of whom had Crohn's disease were included. The average number of previous fistula operations was 6. All patients had 6months of follow-up, and 24 patients (80%) had 12months of follow-up. The healing rate in all patients was 57% (17 of 30 patients) at 6months and 63% (15 of 24 patients) at 12months. One patient reported a worsening of fecal incontinence at 12 months; 2 patients had adverse events (perianal pain: n=1, fluid accumulation n=1) requiring fistula drainage. Patient characteristics, healing, incontinence, and adverse events did not differ significantly between patients with and without Crohn's disease.ConclusionsOur data indicate that Permacol paste is a safe and moderately effective treatment for cryptoglandular and Crohn's fistulae.
CRIS-Team WoS Importer:2019-04-12

Permeability analyses and three dimensional imaging of interferon gamma-induced barrier disintegration in intestinal organoids - Bardenbacher, Marco; Ruder, Barbara; Britzen-Laurent, Nathalie; Schmid, Benjamin; Waldner, Maximilian; Naschberger, Elisabeth; Scharl, Michael; Mueller, Werner; Günther, Claudia; Becker, Christoph; Stürzl, Michael; Tripal, Philipp (Stem Cell Research, 2019)
The aberrant regulation of the epithelial barrier integrity is involved in many diseases of the digestive tract, including inflammatory bowel diseases and colorectal cancer. Intestinal epithelial cell organoid cultures provide new perspectives for analyses of the intestinal barrier in vitro. However, established methods of barrier function analyses from two dimensional cultures have to be adjusted to the analysis of three dimensional organoid structures. Here we describe the methodology for analysis of epithelial barrier function and molecular regulation in intestinal organoids. Barrier responses to interferon-y of intestinal organoids with and without epithelial cellspecific deletion of the interferon-y-receptor 2 gene were used as a model system. The established method allowed monitoring of the kinetics of interferon-y-induced permeability changes in living organoids. Proteolytic degradation and altered localization of the tight junction proteins claudin-2, -7, and - 15 was detected using confocal spinning disc microscopy with 3D reconstruction. Hessian analysis was used for quantification of relocalization of claudins. In summary, we provide a novel methodologic approach for quantitative analyses of intestinal epithelial barrier functions in the 3D organoid model.
CRIS-Team WoS Importer:2019-03-12

Personality rather than clinical variables determines quality of life after major colorectal surgery - Siassi, Ramin Michael; Weiss, Maren; Hohenberger, Werner; Lösel, Friedrich; Matzel, Klaus (Diseases of the colon & rectum, 2009)
PURPOSE: Clinical factors, especially the presence of a stoma, have been presumed to be the major determinants of quality of life after colorectal surgery. We investigated the relative influence of other variables, e.g., patient's personality, sense of coherence, and coping strategies, to determine the validity of this long-held assumption. METHODS: We investigated 79 patients undergoing major colorectal surgery. Quality of Life was assessed with the Short Form-36 and Gastrointestinal Quality of Life Index questionnaires at three and 12 months postsurgery. Additionally, baseline psychologic data on personality and sense of coherence were assessed. The results were analyzed in both a bivariate manner and by multivariate hierarchical regression analysis. RESULTS: In the bivariate analysis, clinical parameters had a small and temporary effect on quality of life, if any. In the multivariate model the character of the underlying disease and the presence of a stoma did not affect quality of life significantly. In contrast, emotional lability, extraversion, and sense of coherence had a strong and lasting influence, accounting for 49 percent of variance (Delta R2) for emotional quality of life, 22 percent for physical and 32 percent for disease-specific Quality of Life. CONCLUSION: Personality exerts a strong and lasting effect on quality of life after colorectal surgery. This effect by far exceeds the influence of common clinical variables.

Pharmacological inhibition of porcupine induces regression of experimental skin fibrosis by targeting Wnt signalling - Chen, Chih-Wei; Beyer, Christian; Liu, Jun; Maier, Christiane; Li, Chun; Thuong Trinh-Minh,; Xu, Xiaohan; Cole, Stuart H.; Hsieh, Mindy H.; Ng, Nicholas; Althage, Alana; Meeusen, Shelly; et al. (Annals of the Rheumatic Diseases, 2017)
Wnt signalling has been implicated in activating a fibrogenic programme in fibroblasts in systemic sclerosis (SSc). Porcupine is an O-acyltransferase required for secretion of Wnt proteins in mammals. Here, we aimed to evaluate the antifibrotic effects of pharmacological inhibition of porcupine in preclinical models of SSc.The porcupine inhibitor GNF6231 was evaluated in the mouse models of bleomycin-induced skin fibrosis, in tight-skin-1 mice, in murine sclerodermatous chronic-graft-versus-host disease (cGvHD) and in fibrosis induced by a constitutively active transforming growth factor-?-receptor I.Treatment with pharmacologically relevant and well-tolerated doses of GNF6231 inhibited the activation of Wnt signalling in fibrotic murine skin. GNF6231 ameliorated skin fibrosis in all four models. Treatment with GNF6231 also reduced pulmonary fibrosis associated with murine cGvHD. Most importantly, GNF6231 prevented progression of fibrosis and showed evidence of reversal of established fibrosis.These data suggest that targeting the Wnt pathway through inhibition of porcupine provides a potential therapeutic approach to fibrosis in SSc. This is of particular interest, as a close analogue of GNF6231 has already demonstrated robust pathway inhibition in humans and could be available for clinical trials.
EVALuna2:13348

Plasma extracellular vesicle messenger RNA profiling identifies prognostic EV signature for non-invasive risk stratification for survival prediction of patients with pancreatic ductal adenocarcinoma - Han, Yi; Drobisch, Pascal; Krüger, Alexander; William, Doreen; Grützmann, Konrad; Böthig, Lukas; Polster, Heike; Seifert, Lena; Seifert, Adrian M.; Distler, Marius; Pecqueux, Mathieu; Riediger, Carina; et al. (Journal of Hematology & Oncology, 2023)
Background: The prognosis of pancreatic ductal adenocarcinoma (PDAC) is one of the most dismal of all cancers and the median survival of PDAC patients is only 6–8 months after diagnosis. While decades of research effort have been focused on early diagnosis and understanding of molecular mechanisms, few clinically useful markers have been universally applied. To improve the treatment and management of PDAC, it is equally relevant to identify prognostic factors for optimal therapeutic decision-making and patient survival. Compelling evidence have suggested the potential use of extracellular vesicles (EVs) as non-invasive biomarkers for PDAC. The aim of this study was thus to identify non-invasive plasma-based EV biomarkers for the prediction of PDAC patient survival after surgery. Methods: Plasma EVs were isolated from a total of 258 PDAC patients divided into three independent cohorts (discovery, training and validation). RNA sequencing was first employed to identify differentially-expressed EV mRNA candidates from the discovery cohort (n = 65) by DESeq2 tool. The candidates were tested in a training cohort (n = 91) by digital droplet polymerase chain reaction (ddPCR). Cox regression models and Kaplan–Meier analyses were used to build an EV signature which was subsequently validated on a multicenter cohort (n = 83) by ddPCR. Results: Transcriptomic profiling of plasma EVs revealed differentially-expressed mRNAs between long-term and short-term PDAC survivors, which led to 10 of the top-ranked candidate EV mRNAs being tested on an independent training cohort with ddPCR. The results of ddPCR enabled an establishment of a novel prognostic EV mRNA signature consisting of PPP1R12A, SCN7A and SGCD for risk stratification of PDAC patients. Based on the EV mRNA signature, PDAC patients with high risk displayed reduced overall survival (OS) rates compared to those with low risk in the training cohort (p = 0.014), which was successfully validated on another independent cohort (p = 0.024). Interestingly, the combination of our signature and tumour stage yielded a superior prognostic performance (p = 0.008) over the signature (p = 0.022) or tumour stage (p = 0.016) alone. It is noteworthy that the EV mRNA signature was demonstrated to be an independent unfavourable predictor for PDAC prognosis. Conclusion: This study provides a novel and non-invasive prognostic EV mRNA signature for risk stratification and survival prediction of PDAC patients.
CRIS-Team Scopus Importer:2023-02-17
Keywords: Extracellular vesicles; mRNA biomarkers; Pancreatic ductal adenocarcinoma; Plasma extracellular vesicle; Prognosis

Plasma Metabolic Profiling Identify Metabolic Subtypes of Pancreatic Ductal Adenocarcinoma - Mahajan, U. M.; Alnatsha, A.; Li, Q.; Oehrle, B.; Weiss, U.; Sendler, M.; Distler, M.; Uhl, W.; Fahlbusch, T.; Goni, E.; Beyer, G.; Chromik, A.; et al. (PANCREAS, 2021)
CRIS-Team WoS Importer:2021-10-29

Plasma Metabolome Profiling Identifies Metabolic Subtypes of Pancreatic Ductal Adenocarcinoma - Mahajan, Ujjwal Mukund; Alnatsha, Ahmed; Li, Qi; Oehrle, Bettina; Weiss, Frank-Ulrich; Sendler, Matthias; Distler, Marius; Uhl, Waldemar; Fahlbusch, Tim; Goni, Elisabetta; Beyer, Georg; Chromik, Ansgar; et al. (Cells, 2021)
Pancreatic ductal adenocarcinoma (PDAC) is one of the deadliest cancers. Developing biomarkers for early detection and chemotherapeutic response prediction is crucial to improve the dismal prognosis of PDAC patients. However, molecular cancer signatures based on transcriptome analysis do not reflect intratumoral heterogeneity. To explore a more accurate stratification of PDAC phenotypes in an easily accessible matrix, plasma metabolome analysis using MxP(R) Global Profiling and MxP(R) Lipidomics was performed in 361 PDAC patients. We identified three metabolic PDAC subtypes associated with distinct complex lipid patterns. Subtype 1 was associated with reduced ceramide levels and a strong enrichment of triacylglycerols. Subtype 2 demonstrated increased abundance of ceramides, sphingomyelin and other complex sphingolipids, whereas subtype 3 showed decreased levels of sphingolipid metabolites in plasma. Pathway enrichment analysis revealed that sphingolipid-related pathways differ most among subtypes. Weighted correlation network analysis (WGCNA) implied PDAC subtypes differed in their metabolic programs. Interestingly, a reduced expression among related pathway genes in tumor tissue was associated with the lowest survival rate. However, our metabolic PDAC subtypes did not show any correlation to the described molecular PDAC subtypes. Our findings pave the way for further studies investigating sphingolipids metabolisms in PDAC.
CRIS-Team WoS Importer:2021-08-06

Poly(ADP-ribose) polymerase-1 regulates fibroblast activation in systemic sclerosis - Zhang, Yun; Pötter, Sebastian; Chen, Chih-Wei; Liang, Ruifang; Gelse, Kolja; Ludolph, Ingo; Horch, Raymund E.; Distler, Oliver; Schett, Georg; Distler, Jörg; Dees, Clara (Annals of the Rheumatic Diseases, 2018)
OBJECTIVES: The enzyme poly(ADP-ribose) polymerase-1 (PARP-1) transfers negatively charged ADP-ribose units to target proteins. This modification can have pronounced regulatory effects on target proteins. Recent studies showed that PARP-1 can poly(ADP-ribosyl)ate (PARylate) Smad proteins. However, the role of PARP-1 in the pathogenesis of systemic sclerosis (SSc) has not been investigated. METHODS: The expression of PARP-1 was determined by quantitative PCR and immunohistochemistry. DNA methylation was analysed by methylated DNA immunoprecipitation assays. Transforming growth factor-β (TGFβ) signalling was assessed using reporter assays, chromatin immunoprecipitation assays and target gene analysis. The effect of PARP-1 inactivation was investigated in bleomycin-induced and topoisomerase-induced fibrosis as well as in tight-skin-1 (Tsk-1) mice. RESULTS: The expression of PARP-1 was decreased in patients with SSc, particularly in fibroblasts. The promoter of PARP-1 was hypermethylated in SSc fibroblasts and in TGFβ-stimulated normal fibroblasts. Inhibition of DNA methyltransferases (DNMTs) reduced the promoter methylation and reactivated the expression of PARP-1. Inactivation of PARP-1 promoted accumulation of phosphorylated Smad3, enhanced Smad-dependent transcription and upregulated the expression of TGFβ/Smad target genes. Inhibition of PARP-1 enhanced the effect of TGFβ on collagen release and myofibroblast differentiation in vitro and exacerbated experimental fibrosis in vivo. PARP-1 deficiency induced a more severe fibrotic response to bleomycin with increased dermal thickening, hydroxyproline content and myofibroblast counts. Inhibition of PARylation also exacerbated fibrosis in Tsk-1 mice and in mice with topoisomerase-induced fibrosis. CONCLUSION: PARP-1 negatively regulates canonical TGFβ signalling in experimental skin fibrosis. The downregulation of PARP-1 in SSc fibroblasts may thus directly contribute to hyperactive TGFβ signalling and to persistent fibroblast activation in SSc.
EVALuna2:34150

Precision Oncology in Surgery: Patient Selection for Operable Pancreatic Cancer - Dreyer, Stephan B; Pinese, Mark; Jamieson, Nigel B.; Scarlett, Christopher J; Colvin, Emily K; Pajic, Marina; Johns, Amber L.; Humphris, Jeremy; Wu, Jianmin; Cowley, Mark J.; Chou, Angela; Nagrial, Adnan M.; et al. (Annals of Surgery, 2018)
OBJECTIVE: We aimed to define preoperative clinical and molecular characteristics that would allow better patient selection for operative resection. BACKGROUND: Although we use molecular selection methods for systemic targeted therapies, these principles are not applied to surgical oncology. Improving patient selection is of vital importance for the operative treatment of pancreatic cancer (pancreatic ductal adenocarcinoma). Although surgery is the only chance of long-term survival, 80% still succumb to the disease and approximately 30% die within 1 year, often sooner than those that have unresected local disease. METHOD: In 3 independent pancreatic ductal adenocarcinoma cohorts (total participants = 1184) the relationship between aberrant expression of prometastatic proteins S100A2 and S100A4 and survival was assessed. A preoperative nomogram based on clinical variables available before surgery and expression of these proteins was constructed and compared to traditional measures, and a postoperative nomogram. RESULTS: High expression of either S100A2 or S100A4 was independent poor prognostic factors in a training cohort of 518 participants. These results were validated in 2 independent patient cohorts (Glasgow, n = 198; Germany, n = 468). Aberrant biomarker expression stratified the cohorts into 3 distinct prognostic groups. A preoperative nomogram incorporating S100A2 and S100A4 expression predicted survival and nomograms derived using postoperative clinicopathological variables. CONCLUSIONS: Of those patients with a poor preoperative nomogram score, approximately 50% of patients died within a year of resection. Nomograms have the potential to improve selection for surgery and neoadjuvant therapy, avoiding surgery in aggressive disease, and justifying more extensive resections in biologically favorable disease.
EVALuna2:212801

Pre-clinical Models of Metastasis in Pancreatic Cancer - Miquel Sedo, Maria; Zhang, Shuman; Pilarsky, Christian (Frontiers in Cell and Developmental Biology, 2021)
Pancreatic ductal adenocarcinoma (PDAC) is a hostile solid malignancy coupled with an extremely high mortality rate. Metastatic disease is already found in most patients at the time of diagnosis, resulting in a 5-year survival rate below 5%. Improved comprehension of the mechanisms leading to metastasis is pivotal for the development of new targeted therapies. A key field to be improved are modeling strategies applied in assessing cancer progression, since traditional platforms fail in recapitulating the complexity of PDAC. Consequently, there is a compelling demand for new preclinical models that mirror tumor progression incorporating the pressure of the immune system, tumor microenvironment, as well as molecular aspects of PDAC. We suggest the incorporation of 3D organoids derived from genetically engineered mouse models or patients as promising new tools capable to transform PDAC pre-clinical modeling and access new frontiers in personalized medicine.
CRIS-Team Scopus Importer:2021-11-19
Keywords: GEMMs; metastasis; metastasis models; organoids; pancreatic cancer; PDAC – pancreatic ductal adenocarcinoma

Predicting Clinical Outcomes in Colorectal Cancer Using Machine Learning - Gründner, Julian; Prokosch, Hans-Ulrich; Stürzl, Michael; Croner, Roland S.; Christoph, Jan; Toddenroth, Dennis (Studies in health technology and informatics, 2018)
Using gene markers and other patient features to predict clinical outcomes plays a vital role in enhancing clinical decision making and improving prognostic accuracy. This work uses a large set of colorectal cancer patient data to train predictive models using machine learning methods such as random forest, general linear model, and neural network for clinically relevant outcomes including disease free survival, survival, radio-chemotherapy response (RCT-R) and relapse. The most successful predictive models were created for dichotomous outcomes like relapse and RCT-R with accuracies of 0.71 and 0.70 on blinded test data respectively. The best prediction models regarding overall survival and disease-free survival had C-Index scores of 0.86 and 0.76 respectively. These models could be used in the future to aid a decision for or against chemotherapy and improve survival prognosis. We propose that future work should focus on creating reusable frameworks and infrastructure for training and delivering predictive models to physicians, so that they could be readily applied to other diseases in practice and be continuously developed integrating new data.
EVALuna2:209471

Predictive value of PD-L1 based on mRNA level in the treatment of stage IV melanoma with ipilimumab - Brueggemann, C.; Kirchberger, M. C.; Goldinger, S. M.; Weide, B.; Konrad, A.; Erdmann, M.; Schadendorf, D.; Croner, R. S.; Krahenbuhl, L.; Kaehler, K. C.; Hafner, C.; Leisgang, W.; et al. (Journal of Cancer Research and Clinical Oncology, 2017)
PD-L1 is established as a predictive marker for therapy of non-small cell lung cancer with pembrolizumab. Furthermore, PD-L1 positive melanoma has shown more favorable outcomes when treated with anti-PD1 antibodies and dacarbazine compared to PD-L1 negative melanoma. However, the role of PD-L1 expression with regard to response to checkpoint inhibition with anti-CTLA-4 is not clear, yet. In addition, the lack of standardization in the immunohistochemical assessment of PD-L1 makes the comparison of results difficult. In this study, we investigated the PD-L1 gene expression with a new fully automated technique via RT-PCR and correlated the findings with the response to the anti-CTLA-4 antibody ipilimumab.Within a retrospective multi-center trial, PD-L1 gene expression was evaluated in 78 melanoma patients in a total of 111 pre-treatment tumor samples from 6 skin cancer centers and analyzed with regard to response to ipilimumab. For meaningful statistical analysis, the cohort was enriched for responders with 30 responders and 48 non-responders. Gene expression was assessed by quantitative RT-PCR after extracting mRNA from formalin-fixed paraffin embedded tumor tissue and correlated with results from immunohistochemical (IHC) stainings.The evaluation of PD-L1 expression based on mRNA level is feasible. Correlation between PD-L1 expression as assessed by IHC and RT-PCR showed varying levels of concordance depending on the antibody employed. RT-PCR should be further investigated to measure PD-L1 expression, since it is a semi-quantitative method with observer-independent evaluation. With this approach, there was no statistical significant difference in the PD-L1 expression between responders and non-responders to the therapy with ipilimumab. The evaluation of PD-L1 expression based on mRNA level is feasible. Correlation between PD-L1 expression as assessed by IHC and RT-PCR showed varying levels of concordance depending on the antibody employed. RT-PCR should be further investigated to measure PD-L1 expression, since it is a semi-quantitative method with observer-independent evaluation. With this approach, there was no statistical significant difference in the PD-L1 expression between responders and non-responders to the therapy with ipilimumab.
EVALuna2:15289

Predictors and severity of intestinal ischaemia following on-pump cardiac surgery: a retrospective, propensity-matched analysis - Wiesmueller, Felix; Bryan, Darren S.; Krautz, Christian; Grützmann, Robert; Weyand, Michael; Strecker, Thomas (European Journal of Cardio-Thoracic Surgery, 2022)
OBJECTIVES: Risk factors associated with intestinal ischaemia after heart surgery have been previously explored; however, a paucity of data exists with regard to extent of intestinal ischaemia in patients requiring surgical intervention. The purpose of this study is to assess predictors of abdominal exploration and extent of ischaemia following cardiac surgery.
CRIS-Team WoS Importer:2022-03-11

Primary aortoduodenal fistula - Overlooked because of guidelines? - Wiesmüller, Felix; Neufert, Clemens; Croner, Roland; Lang, Werner; Grützmann, Robert; Siebler, Jürgen (Innovative Surgical Science, 2020)
Primary aortoduodenal fistula is an uncommon yet mostly lethal finding. We present a case of a 63 year-old male who exhibited significant upper gastrointestinal bleeding and hemorrhagic shock. Repeated endoscopies did not detect any source of bleeding. Emergency laparotomy disclosed an aortoduodenal fistula. Despite intense medical efforts for several months the patient did not fully recover and treatment was limited to palliative care. In light of the substantial mortality associated with this condition, computed tomography imaging should be performed in case of doubt to prevent delayed diagnosis.
CRIS-Team Scopus Importer:2020-11-20
Keywords: aortoduodenal fistula; aortoenteric fistula; gastrointestinal bleeding; PADF; primary aortoduodenal fistula

Processing and secretion of guanylate binding protein-1 depend on inflammatory caspase activity - Naschberger, Elisabeth; Geissdorfer, Walter; Bogdan, Christian; Tripal, Philipp; Kremmer, Elisabeth; Stürzl, Michael; Britzen-Laurent, Nathalie (Journal of Cellular and Molecular Medicine, 2017)
Human guanylate binding protein-1 (GBP-1) belongs to the family of large GTPases. The expression of GBP-1 is inducible by inflammatory cytokines, and the protein is involved in inflammatory processes and host defence against cellular pathogens. GBP-1 is the first GTPase which was described to be secreted by eukaryotic cells. Here, we report that precipitation of GBP-1 with GMP-agarose from cell culture supernatants co-purified a 47-kD fragment of GBP-1 (p47-GBP-1) in addition to the 67-kD full-length form. MALDI-TOF sequencing revealed that p47-GBP-1 corresponds to the C-terminal helical part of GBP-1 and lacks most of the globular GTPase domain. In silico analyses of protease target sites, together with cleavage experiments in vitro and in vivo, showed that p67-GBP-1 is cleaved by the inflammatory caspases 1 and 5, leading to the formation of p47-GBP-1. Furthermore, the secretion of p47-GBP-1 was found to occur via a non-classical secretion pathway and to be dependent on caspase-1 activity but independent of inflammasome activation. Finally, we showed that p47-GBP-1 represents the predominant form of secreted GBP-1, both in cell culture supernatants and, in vivo, in the cerebrospinal fluid of patients with bacterial meningitis, indicating that it may represent the biologically active form of extracellular GBP-1. These findings confirm the involvement of caspase-1 in non-classical secretion mechanisms and open novel perspectives for the extracellular function of secreted GBP-1.
EVALuna2:7752

Prognosis of patients with colonic carcinoma before, during and after implementation of complete mesocolic excision - Merkel, Susanne; Weber, K.; Matzel, Klaus; Agaimy, Abbas; Göhl, Jonas; Hohenberger, Werner (British Journal of Surgery, 2016)
The implementation of complete mesocolic excision (CME) for colonic cancer was accompanied by other important changes, including more patients with early diagnosis by screening and the introduction of adjuvant chemotherapy in patients with stage III disease. The contribution of CME remains unclear.In this observational study, data from patients with stage I-III colonic carcinoma were analysed by comparing five time intervals: 1978-1984 (pre-CME), 1985-1994 (CME development), 1995-2002 (CME implementation), 2003-2009 (CME) and 2010-2014 (CME), with a special focus on indicators of process and outcome quality.During the observed periods, the median age of patients increased (from 65 to 67 years), there were more right-sided carcinomas (from 17·0 to 32·4 per cent), more stage I disease (from 14·0 to 27·7 per cent) and fewer patients with regional lymph node metastases (from 42·7 to 32·0 per cent). The proportion of patients with pN0 disease and at least 12 examined regional lymph nodes increased (from 84·8 to 100 per cent) as did the R0 resection rate (from 97·0 to 100 per cent). Overall morbidity increased, whereas the in-hospital mortality rate was stable (range 1·8-3·7 per cent). Use of adjuvant chemotherapy in stage III colonic carcinoma increased from 0 to 79 per cent. The improvement in outcome quality was more evident in stage III than in stage I-II tumours. In stage III, the 5-year locoregional recurrence rate decreased from 14·8 to 4·1 per cent (P = 0·046) and the 5-year cancer-related survival rate increased from 61·7 to 80·9 per cent (P = 0·010).With CME, the quality indicators of process and outcome quality improved, especially in stage III colonic carcinoma. Adjuvant chemotherapy in stage III and multidisciplinary approaches in patients with metachronous distant metastases contributed to further outcome improvement.
EVALuna2:6780

Prognostic role of nutrition parameters on short- and long-term outcome in patients with primary resectable pancreatic ductal adenocarcinoma - Bareiß, Sophie; Merkel, Susanne; Krautz, Christian; Weber, Georg; Grützmann, Robert; Brunner, Maximilian (Clinical Nutrition ESPEN, 2024)
Purpose: Nutrition status of patients with pancreatic ductal adenocarcinoma (PDAC) has gained an increasing importance - especially in the preoperative setting. The aim of the present study was to evaluate different preoperative nutritional parameters including body composition parameters regarding their impact on short- and long-term outcome in patients with resectable PDAC. Methods: This retrospective single center study included 162 patients, who underwent primary resection of PDAC from January 2003 to December 2018 at the University Hospital of Erlangen. The influence of different preoperative nutrition parameters as well as different CT-based body composition parameters on short- (major morbidity, postoperative pancreatic fistula (POPF) and longer hospital stay) as well as on long-term outcome (overall and disease-free survival) were tested using multiple regression analysis. Results: Major morbidity and POPF occurred in 30% respectively 18%. Median length of hospital stay was 18 days. Median overall and disease free survival were 20.3 respectively 12.0 months. Multivariate analysis revealed among the different nutritional parameters following independent predictors: PMTH (psoas muscle thickness/height) for major morbidity (HR 2.1, p = 0.038), PMA (psoas muscle area) for a prolonged hospital stay >18 days (HR 7.3, p = 0.010) and NRS (nutritional risk score) for overall survival (HR 1.7, p = 0.043). Conclusion: In our cohort, nutritional parameters played a minor role in predicting short- and long-term outcome in patients with primary resectable PDAC, as there were only significant associations between selected psoas muscle parameters and short-term outcome parameters and the nutritional risk score (NRS) with the overall survival.
CRIS-Team Scopus Importer:2024-06-21
Keywords: Body composition; Nutrition; Outcome; Pancreatic ductal adenocarcinoma; Primary resection; Survival

Prognostic subdivision of pT2 rectal carcinomas - Merkel, Susanne; Weber, Klaus; Brunner, Maximilian; Baecker, Justus; Agaimy, Abbas; Göhl, Jonas; Hohenberger, Werner; Schellerer, Vera; Grützmann, Robert (International Journal of Colorectal Disease, 2019)
Purpose The aim of the present study is to explore the prognostic impact of a subdivision of pT2 by the depth of invasion into the muscularis propria in rectal carcinomas.
CRIS-Team WoS Importer:2019-04-18

Prognostic subdivision of ypT3 rectal tumours according to extension beyond the muscularis propria - Merkel, Susanne; Weber, K.; Schellerer, Vera; Göhl, Jonas; Fietkau, Rainer; Agaimy, Abbas; Hohenberger, Werner; Hermanek, Peter (British Journal of Surgery, 2014)
The subdivision of T3 in rectal carcinoma according to the depth of invasion into perirectal fat has been recommended in the TNM Supplement since 1993. This study assessed the prognostic impact of this pathological staging in tumours removed after neoadjuvant chemoradiotherapy (ypT3).Data from patients with ypT3 rectal carcinoma (less than 12 cm from the anal verge) treated with neoadjuvant chemoradiation and total mesorectal excision were analysed. Tumour category ypT3 was subdivided into ypT3a (5 mm or less) and ypT3b (more than 5 mm), based on histological measurements of maximal tumour invasion beyond the outer border of the muscularis propria.Important differences between ypT3a (81 patients) and ypT3b (43) were found in 5-year rates of locoregional recurrence (7 versus 18 per cent; P = 0·049), distant metastasis (20 versus 41 per cent; P = 0·002), disease-free survival (73 versus 47 per cent; P = 0·001), overall survival (79 versus 74 per cent; P = 0·036) and cancer-related survival (81 versus 74 per cent; P = 0·007). In Cox regression analyses, the ypT3 subclassification was identified as an independent prognostic factor for disease-free (ypT3b: hazard ratio (HR) 2·13, 95 per cent confidence interval 1·16 to 3·89; P = 0·014), observed (ypT3b: HR 2·02, 1·05 to 3·87; P = 0·035) and cancer-related (ypT3b: HR 2·46, 1·20 to 5·04; P = 0·014) survival. Extramural venous invasion was found to be an additional prognostic factor, but the pathological node category after chemoradiotherapy (ypN) did not influence survival.In ypT3 rectal carcinomas, the proposed subclassification is superior to ypN in predicting prognosis.
EVALuna2:6571

Prognostic value of β1 integrin expression in colorectal liver metastases. - Vassos, Nikolaos; Rau, Tilman; Merkel, Susanne; Feiersinger, Fabian; Geppert, Carol-Immanuel; Stürzl, Michael; Hohenberger, Werner; Croner, Roland S. (International Journal of Clinical and Experimental Pathology, 2014)
Integrins are cell surface adhesion molecules (CAM) that regulate via intercellular and cell-matrix signaling various cellular processes including wound healing, cell differentiation, division, growth, migration and metastatic dissemination. Although a correlation between carcinogenesis and changes in integrin expression, especially β1 integrin, has been reported, its role in colorectal liver metastases remains unclear. This study aimed to evaluate the expression of β1 integrin in colorectal liver metastases and to correlate the pattern of expression with clinicopathological features and to investigate the putative role of β1 integrin expression on survival of these patients. Formalin-fixed, paraffin-embedded (FFPE) tumor samples of 81 patients who were operated because of colorectal liver metastases without any neoadjuvant therapy were obtained and stained with hematoxylin and eosin (H & E). An immunohistochemical examination was performed using Dako, Peroxidase/DAB kit and a primary monoclonal β1 integrin (CD29, fibronectin receptor subunit beta; ab3167, Abcam plc). β1 integrin expression was evaluated according to the immunoreactive score of Remmele and Stegner and was related with clinicopathological features of prognostic significance and with disease-free and overall survival as well. Statistical analysis was performed using SPSS version 21.0. β1 integrin was overexpressed in tumor cells in 37 (48%) patients and in stromal cell in 27 (33%) patients. The β1 expression was not statistically correlated with clinicopathological features of the primary tumors but it was statistically correlated (p=0.03) with the histological grading of liver metastases. Kaplan-Meier survival analysis showed that there is a tendency but no statistically significant correlation in disease-free and overall survival. Considering that expression of β1 integrin in colorectal liver metastases remains controversial, specially its relation with survival of patients, we showed that the β1 expression represents a reliable prognostic factor regarding the grading of liver metastases of CRC and our findings imply that β1 integrin expression profiles may have further potential in identifying the stage of colorectal liver metastases and being a marker of prognosis in these patients. UNLABELLED METHODS RESULTS CONCLUSION

Proposal for a new M1 subclassification in colorectal carcinoma - Merkel, Susanne; Weber, K.; Croner, R.; Golcher, H.; Göhl, Jonas; Agaimy, Abbas; Semrau, S.; Wein, Axel; Hohenberger, Werner; Wittekind, C.; Siebler, Jürgen (2016)
EVALuna2:2176

Proposal of a Standardized Questionnaire to Structure Clinical Peer Reviews of Mortality and Failure of Rescue in Pancreatic Surgery - Brunner, Maximilian; Mücke, Franziska; Langheinrich, Melanie; Struller, Florian; Rueckert, Felix; Welsch, Thilo; Distler, Marius; Kersting, Stephan; Grützmann, Robert; Krautz, Christian; Weber, Georg (Journal of Clinical Medicine, 2021)
Background: Quality management tools such as clinical peer reviews facilitate root cause analysis and may, ultimately, help to reduce surgery-related morbidity and mortality. This study aimed to evaluate the reliability of a standardized questionnaire for clinical peer reviews in pancreatic surgery. Methods: All cases of in-hospital-mortality following pancreatic surgery at two high-volume centers (n = 86) were reviewed by two pancreatic surgeons. A standardized mortality review questionnaire was developed and applied to all cases. In a second step, 20 cases were randomly assigned to an online re-review that was completed by seven pancreatic surgeons. The overall consistency of the results between the peer review and online re-review was determined by Cohen's kappa (kappa). The inter-rater reliability of the online re-review was assessed by Fleiss' kappa (kappa). Results: The clinical peer review showed that 80% of the patient mortality was related to surgery. Post-operative pancreatic fistula (POPF) (36%) followed by post-pancreatectomy hemorrhage (PPH) (22%) were the most common surgical underlying (index) complications leading to in-hospital mortality. Most of the index complications yielded in abdominal sepsis (62%); 60% of the cases exhibited potential of improvement, especially through timely diagnosis and therapy (42%). There was a moderate to substantial strength of agreement between the peer review and the online re-review in regard to the category of death (surgical vs. non-surgical; kappa = 0.886), type of surgical index complication (kappa = 0.714) as well as surgical and non-surgical index complications (kappa = 0.492 and kappa = 0.793). Fleiss' kappa showed a moderate to substantial inter-rater agreement of the online re-review in terms of category of death (kappa = 0.724), category of common surgical index complications (kappa = 0.455) and surgical index complication (kappa = 0.424). Conclusion: The proposed questionnaire to structure clinical peer reviews is a reliable tool for root cause analyses of in-hospital mortality and may help to identify specific options to improve outcomes in pancreatic surgery. However, the reliability of the peer feedback decreases with an increasing specificity of the review questions.
CRIS-Team WoS Importer:2021-05-28

Proposal of a T3 Subclassification for Colon Carcinoma. - Merkel, Susanne; Brunner, Maximilian; Geppert, Carol-Immanuel; Grützmann, Robert; Weber, Klaus; Agaimy, Abbas (Cancers, 2022)
The TNM classification system is one of the most important factors determining prognosis for cancer patients. In colorectal cancer, the T category reflects the depth of tumor invasion. T3 is defined by a tumor that invades through the muscularis propria into pericolorectal tissues. The data of 1047 patients with complete mesocolic excision were analyzed. The depth of invasion beyond the outer border of the muscularis propria into the subserosa or into nonperitonealized pericolic tissue was measured and categorized in 655 pT3 patients: pT3a (≤1 mm), pT3b,c (>1-15 mm) and pT3d (>15 mm). The prognosis of these categories was compared. Five-year distant metastasis increased significantly from pT3a (5.7%) over pT3b,c (17.7%) to pT3d (37.2%; p = 0.001). There was no difference between pT2 (5.3%) and pT3a or between pT3d and pT4a (42.1%) or pT4b (33.7%). The 5-year disease-free survival decreased significantly from pT3a (77.4%) over pT3b,c (65.4%) to pT3d (50.1%; p = 0.015). No significant difference was found between pT2 (80.5%) and pT3a or between pT3d and pT4a (43.9%; p = 0.296) or pT4b (53.4%). The prognostic inhomogeneity in pT3 colon carcinoma has been demonstrated. A three-level subdivision of T3 for colon carcinoma in the TNM system into T3a (≤1 mm), T3b (>1-15 mm), and T3c (>15 mm) is recommended.
EVALuna2:514502

Protein tyrosine phosphatase nonreceptor type 2 controls colorectal cancer development - Katkeviciute, Egle; Hering, Larissa; Montalban-Arques, Ana; Busenhart, Philipp; Schwarzfischer, Marlene; Manzini, Roberto; Conde, Javier; Atrott, Kirstin; Lang, Silvia; Rogler, Gerhard; Naschberger, Elisabeth; Schellerer, Vera; et al. (Journal of Clinical Investigation, 2021)
Protein tyrosine phosphatase nonreceptor type 2 (PTPN2) recently emerged as a promising cancer immunotherapy target. We set out to investigate the functional role of PTPN2 in the pathogenesis of human colorectal carcinoma (CRC), as its role in immune-silent solid tumors is poorly understood. We demonstrate that in human CRC, increased PTPN2 expression and activity correlated with disease progression and decreased immune responses in tumor tissues. In particular, stage II and III tumors displayed enhanced PTPN2 protein expression in tumor-infiltrating T cells, and increased PTPN2 levels negatively correlated with expression of PD-1, CTLA4, STAT1, and granzyme A. In vivo, T cell- and DC-specific PTPN2 deletion reduced tumor burden in several CRC models by promoting CD44+ effector/memory T cells, as well as CD8+ T cell infiltration and cytotoxicity in the tumor. In direct relevance to CRC treatment, T cell-specific PTPN2 deletion potentiated anti-PD-1 efficacy and induced antitumor memory formation upon tumor rechallenge in vivo. Our data suggest a role for PTPN2 in suppressing antitumor immunity and promoting tumor development in patients with CRC. Our in vivo results identify PTPN2 as a key player in controlling the immunogenicity of CRC, with the strong potential to be exploited for cancer immunotherapy.
CRIS-Team Scopus Importer:2021-01-15

PU.1 controls fibroblast polarization and tissue fibrosis - Wohlfahrt, Thomas; Rauber, Simon; Uebe, Steffen; Luber, Markus; Soare, Alina; Ekici, Arif Bülent; Weber, Stefanie; Matei, Alexandru-Emil; Chen, Chih-Wei; Maier, Christiane; Karouzakis, Emmanuel; Kiener, Hans P.; et al. (Nature, 2019)
Fibroblasts are polymorphic cells with pleiotropic roles in organ morphogenesis, tissue homeostasis and immune responses. In fibrotic diseases, fibroblasts synthesize abundant amounts of extracellular matrix, which induces scarring and organ failure. By contrast, a hallmark feature of fibroblasts in arthritis is degradation of the extracellular matrix because of the release of metalloproteinases and degrading enzymes, and subsequent tissue destruction. The mechanisms that drive these functionally opposing pro-fibrotic and pro-inflammatory phenotypes of fibroblasts remain unknown. Here we identify the transcription factor PU.1 as an essential regulator of the pro-fibrotic gene expression program. The interplay between transcriptional and post-transcriptional mechanisms that normally control the expression of PU.1 expression is perturbed in various fibrotic diseases, resulting in the upregulation of PU.1, induction of fibrosis-associated gene sets and a phenotypic switch in extracellular matrix-producing pro-fibrotic fibroblasts. By contrast, pharmacological and genetic inactivation of PU.1 disrupts the fibrotic network and enables reprogramming of fibrotic fibroblasts into resting fibroblasts, leading to regression of fibrosis in several organs.
EVALuna2:35476

Pylorus-Preserving Pancreaticoduodenectomy (PPPD) with Segmental Portal Vein Resection - Brunner, Maximilian; Krautz, Christian; Maak, Matthias; Weber, Georg; Grützmann, Robert (Zentralblatt für Chirurgie, 2021)
CRIS-Team WoS Importer:2021-08-06

Qualität der Chirurgie als Prognosefaktor beim Rektumkarzinom nach neoadjuvanter Radiochemotherapie - Brunner, M.; Perrakis, Aristotelis; Merkel, Susanne; Weber, K.; Grützmann, Robert (Chirurgische Praxis, 2019)
The prognosis of patients with rectal carcinoma has improved significantly in recent years, in particular through the introduction of TME (total mesorectal excision) surgery and neoadjuvant therapy with radiation or chemoradiotherapy in locally advanced carcinomas. Even in the era of TME surgery and neoadjuvant chemoradiation high-quality surgical therapy plays an important role for the prognosis of patients with rectal cancer, especially for local tumor control. Prognostically relevant surgical quality indicators represent the quality of TME, the R0 resection, the negative circumferential resection margin (CRM) and the avoidance of intraoperative local tumor cell dissemination. These four factors mainly affect the local recurrence rate, but are also significant in terms of overall survival.
CRIS-Team Scopus Importer:2021-04-20
Keywords: Neoadjuvant therapy; Preoperative chemoradiation; Prognostic factors; Quality of surgery; Rectal carcinoma; TME

Qualitätsindikatoren für die Pankreaschirurgie - Wellner, U. F.; Grützmann, Robert; Keck, T.; Nuessler, N.; Witzigmann, H. E.; Buhr, H. -J. (Chirurg, 2018)
Quality indicators are by definition indirect measures of quality. The selection for the field of pancreatic surgery was based on the clinical relevance and controllability, scientific evidence and the practicability of data acquisition. In terms of outcome quality, hospital mortality, the composite endpoint MTL30 (mortality-transfer-length of stay), and major complications (Clavien-Dindo classification grades 3b and 4) were chosen as being essential. With respect to structural quality, the presence of interventional radiology with constant availability was considered essential. To evaluate target values two strategies were used: a systematic literature search and evaluation of the current numbers from the German Society for General and Visceral Surgery (DGAV) StuDoQ|Pancreas registry for the years 2014-2016. The results are presented in the following consensus statement.
EVALuna2:212863

Quality of life and patient’s expectations after closure of a temporary stoma - Siassi, Ramin Michael; Hohenberger, Werner; Lösel, Friedrich; Weiss, Maren (International Journal of Colorectal Disease, 2008)
Introduction Little is known about the changes in quality of life following reversal of a temporary loop ileostomy after rectal cancer surgery. We therefore conducted a prospective study assessing physical symptoms, quality of life, problems in everyday life, and patient’s expectations and complaints. Materials and methods We investigated 35 patients who received a temporary stoma after colorectal surgery between 15/11/2002 and 15/11/2003. The patients were followed up for 1 year. Quality of life was assessed using the Short-Form 36 (SF-36) and the Gastrointestinal Quality of Life Index (GLQI). In addition, we performed a semi-structured interview that assessed quality of life, function, patient’s expectations, and complaints. Results The interviews showed a significant improvement in body image and leisure activities while the questionnaires showed no change in qol. Conversely, there was a significant increase in gastrointestinal problems that persisted until 1 year after primary surgery. An increasing proportion of patients stated that they felt worse than they expected after stoma closure. That was accompanied by an increased number of complaints about the hospital and the medical staff. Conclusion Although from the surgeon’s point of view, stoma closure is only a minor procedure, it causes significant functional problems for the patients that lead to considerable dissatisfaction. Other than usually presupposed, there is no general improvement in quality of life and everyday life after stoma closure. Therefore, thorough preoperative counseling about the consequences of stoma reversal is mandatory.

Quality of life of GIST patients with and without current tyrosine kinase inhibitor treatment: Cross-sectional results of a German multicentre observational study (PROSa) - Eichler, Martin; Pink, Daniel; Menge, Franka; Jakob, Jens; Hentschel, Leopold; Richter, Stephan; Hohenberger, Peter; Kasper, Bernd; Andreou, Dimosthenis; Singer, Susanne; Grützmann, Robert; Dmytrow, Diana I.; et al. (European Journal of Cancer Care, 2021)
Objective: We investigated the health-related quality of life (HRQoL) of patients with gastrointestinal stromal tumours (GIST). Methods: In the multicentre PROSa study, the HRQoL of adult GIST patients was assessed between 2017 and 2019 using the European Organisation for Research and Treatment of Cancer HRQoL questionnaire (EORTC QLQ-C30). We performed group comparisons and multivariate linear regressions. Results: Among 130 patients from 13 centres, the mean global HRQoL was 63.3 out of 100 points. Higher sores indicate better HRQoL. The highest restrictions were in emotional, social, role functioning, insomnia, fatigue, and pain. In multivariate linear regression, we found no significant differences between patients receiving tyrosine kinase inhibitor (TKI) treatment and those without TKI treatment as well as between patients treated with curative or with palliative intent. Patients who received multiple lines of TKI treatment had the most restrictions, notably in physical (unstandardized regression coefficient [B] = −15.7), role (B = −25.7), social (B = −18.4), and cognitive functioning (B = −19.7); fatigue (B = 15.93); general health (B = −14.23); and EORTC-sum score (B = −13.82) compared to all other patients. Conclusion: The highest HRQoL restrictions were in GIST patients receiving multiple lines of TKI therapy. Underlying causes need further investigation.
CRIS-Team Scopus Importer:2021-08-13
Keywords: clinically important restrictions and symptoms; gastrointestinal stromal tumours; health-related quality of life; observational study; rare disease; tyrosine kinase inhibitors

Quantitative proteome profiling of lymph node-positive vs. -negative colorectal carcinomas pinpoints MX1 as a marker for lymph node metastasis - Croner, Roland S.; Stürzl, Michael; Rau, Tilman; Metodieva, Gergana; Geppert, Carol-Immanuel; Naschberger, Elisabeth; Lausen, Berthold; Metodiev, Metodi V. (International Journal of Cancer, 2014)
We used high-resolution mass spectrometry to measure the abundance of more than 9,000 proteins in 19 individually dissected colorectal tumors representing lymph node metastatic (n = 10) and nonmetastatic (n = 9) phenotypes. Statistical analysis identified MX1 and several other proteins as overexpressed in lymph node-positive tumors. MX1, IGF1-R and IRF2BP1 showed significantly different expression in immunohistochemical validation (Wilcoxon test p = 0.007 for IGF1-R, p = 0.04 for IRF2BP1 and p = 0.02 for MX1 at the invasion front) in the validation cohort. Knockout of MX1 by siRNA in cell cultures and wound healing assays provided additional evidence for the involvement of this protein in tumor invasion. The collection of identified and quantified proteins to our knowledge is the largest tumor proteome dataset available at the present. The identified proteins can give insights into the mechanisms of lymphatic metastasis in colorectal carcinoma and may act as prognostic markers and therapeutic targets after further prospective validation.
EVALuna2:6585

R0 resection following chemo (radio)therapy improves survival of primary inoperable pancreatic cancer patients. Interim results of the German randomized CONKO-007± trial - Fietkau, Rainer; Grützmann, Robert; Wittel, U. A.; Croner, R. S.; Jacobasch, L.; Neumann, U. P.; Reinacher-Schick, A.; Imhoff, D.; Boeck, S.; Keilholz, L.; Oettle, H.; Hohenberger, Werner; et al. (Strahlentherapie und Onkologie, 2020)
Purpose: Chemotherapy with or without radiotherapy is the standard in patients with initially nonmetastatic unresectable pancreatic cancer. Additional surgery is in discussion. The CONKO-007 multicenter randomized trial examines the value of radiotherapy. Our interim analysis showed a significant effect of surgery, which may be relevant to clinical practice. Methods: One hundred eighty patients received induction chemotherapy (gemcitabine or FOLFIRINOX). Patients without tumor progression were randomized to either chemotherapy alone or to concurrent chemoradiotherapy. At the end of therapy, a panel of five independent pancreatic surgeons judged the resectability of the tumor. Results: Following induction chemotherapy, 126/180 patients (70.0%) were randomized to further treatment. Following study treatment, 36/126 patients (28.5%) underwent surgery; (R0: 25/126 [19.8%]; R1/R2/Rx [n = 11/126; 6.1%]). Disease-free survival (DFS) and overall survival (OS) were significantly better for patients with R0 resected tumors (median DFS and OS: 16.6 months and 26.5 months, respectively) than for nonoperated patients (median DFS and OS: 11.9 months and 16.5 months, respectively; p = 0.003). In the 25 patients with R0 resected tumors before treatment, only 6/113 (5.3%) of the recommendations of the panel surgeons recommended R0 resectability, compared with 17/48 (35.4%) after treatment (p < 0.001). Conclusion: Tumor resectability of pancreatic cancer staged as unresectable at primary diagnosis should be reassessed after neoadjuvant treatment. The patient should undergo surgery if a resectability is reached, as this significantly improves their prognosis.
CRIS-Team Scopus Importer:2020-09-25
Keywords: Neoadjuvant chemoradiotherapy; Pancreatic adenocarcinoma; Prospective randomized multicenter trial; Surgery; Tumor resectability

Radical Resection in Entero-Pancreatic Neuroendocrine Tumors: Recurrence-Free Survival Rate and Definition of a Risk Score for Recurrence - Merola, Elettra; Pascher, A.; Rinke, A.; Bartsch, D. K.; Zerbi, A.; Nappo, G.; Carnaghi, C.; Ciola, M.; Mcnamara, M. G.; Zandee, W.; Bertani, E.; Marcucci, S.; et al. (Annals of Surgical Oncology, 2022)
Background Surgery with radical intent is the only potentially curative option for entero-pancreatic neuroendocrine tumors (EP-NETs) but many patients develop recurrence even after many years. The subset of patients at high risk of disease recurrence has not been clearly defined to date. Objective The aim of this retrospective study was to define, in a series of completely resected EP-NETs, the recurrence-free survival (RFS) rate and a risk score for disease recurrence. Patients and Methods This was a multicenter retrospective analysis of sporadic pancreatic NETs (PanNETs) or small intestine NETs (SiNETs) [G1/G2] that underwent R0/R1 surgery (years 2000-2016) with at least a 24-month follow-up. Survival analysis was performed using the Kaplan-Meier method and risk factor analysis was performed using the Cox regression model. Results Overall, 441 patients (224 PanNETs and 217 SiNETs) were included, with a median Ki67 of 2% in tumor tissue and 8.2% stage IV disease. Median RFS was 101 months (5-year rate 67.9%). The derived prognostic score defined by multivariable analysis included prognostic parameters, such as TNM stage, lymph node ratio, margin status, and grading. The score distinguished three risk categories with a significantly different RFS (p < 0.01). Conclusions Approximately 30% of patients with EP-NETs recurred within 5 years after radical surgery. Risk factors for recurrence were disease stage, lymph node ratio, margin status, and grading. The definition of risk categories may help in selecting patients who might benefit from adjuvant treatments and more intensive follow-up programs.
CRIS-Team WoS Importer:2022-06-03

Randomized Phase II Trial of Chemoradiotherapy Plus Induction or Consolidation Chemotherapy as Total Neoadjuvant Therapy for Locally Advanced Rectal Cancer: CAO/ARO/AIO-12 - Fokas, Emmanouil; Allgäuer, Michael; Polat, Bülent; Klautke, Gunther; Grabenbauer, Gerhard G.; Fietkau, Rainer; Kuhnt, Thomas; Staib, Ludger; Brunner, Thomas; Grosu, Anca-Ligia; Schmiegel, Wolff; Jacobasch, Lutz; et al. (Journal of Clinical Oncology, 2019)
PURPOSE: Total neoadjuvant therapy is a new paradigm for rectal cancer treatment. Optimal scheduling of preoperative chemoradiotherapy (CRT) and chemotherapy remains to be established. PATIENTS AND METHODS: We conducted a multicenter, randomized, phase II trial using a pick-the-winner design on the basis of the hypothesis of an increased pathologic complete response (pCR) of 25% after total neoadjuvant therapy compared with standard 15% after preoperative CRT. Patients with stage II or III rectal cancer were assigned to group A for induction chemotherapy using three cycles of fluorouracil, leucovorin, and oxaliplatin before fluorouracil/oxaliplatin CRT (50.4 Gy) or to group B for consolidation chemotherapy after CRT. Secondary end points included toxicity, compliance, and surgical morbidity. RESULTS: Of the 311 patients enrolled, 306 patients were evaluable (156 in group A and 150 in group B). CRT-related grade 3 or 4 toxicity was lower (37% v 27%) and compliance with CRT higher in group B (91%, 78%, and 76% v 97%, 87%, and 93% received full-dose radiotherapy, concomitant fluorouracil, and concomitant oxaliplatin in groups A and B, respectively); 92% versus 85% completed all induction/consolidation chemotherapy cycles, respectively. The longer interval between completion of CRT and surgery in group B (median 90 v 45 days in group A) did not increase surgical morbidity. A pCR in the intention-to-treat population was achieved in 17% in group A and in 25% in group B. Thus, only group B (P < .001), but not group A (P = .210), fulfilled the predefined statistical hypothesis. CONCLUSION: Up-front CRT followed by chemotherapy resulted in better compliance with CRT but worse compliance with chemotherapy compared with group A. Long-term follow-up will assess whether improved pCR in group B translates to better oncologic outcome.
CRIS-Team Scopus Importer:2019-12-10

Rapid qPCR-based quantitative immune cell phenotyping in mouse tissues - Huang, Jinghao; Demmler, Richard; Mohamed Abdou, Mariam; Thoma, Oana-Maria; Weigmann, Benno; Waldner, Maximilian; Stürzl, Michael; Naschberger, Elisabeth (Journal of Investigative Medicine, 2024)
The immune microenvironment plays an important role in the regulation of diseases. The characterization of the cellular composition of immune cell infiltrates in diseases and respective models is a major task in pathogenesis research and diagnostics. For the assessment of immune cell populations in tissues, fluorescence-activated cell sorting (FACS) or immunohistochemistry (IHC) are the two most common techniques presently applied, but they are cost intensive, laborious, and sometimes limited by the availability of suitable antibodies. Complementary rapid qPCR-based approaches exist for the human situation but are lacking for experimental mouse models. Accordingly, we developed a robust, rapid RT-qPCR-based approach to determine and quantify the abundance of prominent immune cell populations such as T cells, helper T (Th) cells, cytotoxic T cells, Th1 cells, B cells, and macrophages in mouse tissues. The results were independently validated by the gold standards IHC and FACS in corresponding tissues and showed high concordance.
CRIS-Team Scopus Importer:2023-12-22
Keywords: FACS; IHC; immune cell phenotyping; mouse tissue; RT-qPCR

Reactivation and persistence of human herpesvirus-8 infection in B cells and monocytes by Th-1 cytokines increased in Kaposi's sarcoma. - Monini, Paolo; Colombini, Sandra; Stürzl, Michael; Goletti, Delia; Cafaro, Aurelio; Sgadari, Cecilia; Buttò, Stefano; Franco, Marina; Leone, Patrizia; Fais, Stefano; Leone, Pasqualina; Melucci-Vigo, Gianna; et al. (Blood, 1999)
Patients with Kaposi's sarcoma (KS) have a human herpesvirus-8 (HHV-8) load higher than patients without KS and present a CD8(+) T-cell activation with production of Th1-type cytokines both in tissues and peripheral blood mononuclear cells (PBMC). Because in tissues of KS patients detection of inflammatory cytokines (IC) can precede detection of HHV-8 DNA and because signs of immunoactivation and/or dysregulation can precede KS development, we investigated the effect of IC on HHV-8 infection. To achieve this goal, PBMC and purified cell populations from 45 patients with KS and 45 patients at risk of KS were analyzed for HHV-8 DNA and/or gene expression and for cell survival, growth, and phenotype before or after culture with or without the IC increased in KS. The results indicate that PBMC that are polymerase chain reaction (PCR)-positive at day 0 generally loose the virus upon culture. However, the presence of IC maintains HHV-8 DNA load in cultured cells. In addition, IC increase viral load to detectable levels in PBMC from serologically positive patients that were PCR-negative before culture. gamma Interferon is sufficient for these effects, whereas tumor necrosis factor and interleukin-6 have little or no activity. The increase of HHV-8 DNA by IC is observed after short-term (7 days) or long-term (28 days) culture of the cells and occurs in one or both of the two circulating cell types that are infected in vivo: B cells and monocytes. In both cases it is associated with lytic gene expression, suggesting that virus reactivation is one of the most likely mechanisms for the effect of IC on virus load. However, IC have also effects on the cells target of HHV-8 infection, because they increase B-cell survival and induce the growth and differentiation of monocytes into KS-like spindle cells with markers of endothelial macrophages. Because cells with markers of endothelial macrophages are present in blood and lesions from KS patients and are infected by HHV-8, these data may explain the high HHV-8 load associated with KS development and suggest that infected monocytes may carry the virus to tissues, transmit the infection, or differentiate in loco in spindle cells with endothelial macrophage markers.

Reactivation and role of HHV-8 in Kaposi's sarcoma initiation. - Ensoli, Barbara; Stürzl, Michael; Monini, Paolo (Advances in Cancer Research, 2001)
Kaposi's sarcoma (KS) is an angioproliferative disease occurring in several clinical-epidemio-logic forms but all associated with infection by the human herpesvirus-8 (HHV-8). At least in early stages, KS is a reactive disease associated with a state of immune dysregulation characterized by CD8+ T-cell activation and production of Th1-type inflammatory cytokines (IC) that precedes lesion development. In fact, evidence indicates that IC can trigger lesion formation by inducing the activation of endothelial cells that leads to adhesion and tissue extravasation of lymphomonocytes, spindle cell formation, and angiogenesis, and HHV-8 reactivation that, in turn, leads to virus spread to all circulating cell types and virus dissemination into tissues. Due to virus escape mechanisms and deficient immune responses toward HHV-8, virus reactivation and spread are not controlled by the immune system but induce immune responses that may paradoxically exacerbate the reactive process. The virus is recruited into "activated" tissue sites where it finds an optimal environment for growth. In fact, viral load is very low in early lesions, whereas almost all spindle cells are infected in late-stage lesions. Although early KS is a reactive process of polyclonal nature that can regress, in time and in the presence of immunodeficiency, it can progress to a true sarcoma. This is likely due to the long-lasting expression of HHV-8 latency genes in spindle cells associated with the deregulated expression of oncogenes and oncosuppressor genes and, for AIDS-KS, with the effects of the HIV-1 Tat protein.

Recapitulating Drug Treatment in a Dish - Investigating the Impact of 2D Versus 3D In Vitro Cancer Models and Different Treatment Schemes on Drug Response - Sankarasubramanian, Sushmitha; Kroger, Anne-Claire; Pfohl, Ulrike; Loskutov, Jurgen; Linnebacher, Michael; Regenbrecht, Christian; Regenbrecht, Christian; Wedeken, Lena (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-12-16

Recurrence pattern and its risk factors in patients with resected pancreatic ductal adenocarcinoma – A retrospective analysis of 272 patients - Brunner, Maximilian; Flessa, Maarten; Jacobsen, Anne; Merkel, Susanne; Krautz, Christian; Weber, Georg; Grützmann, Robert (Pancreatology, 2024)
Background: The aim of this study was to investigate the patterns of recurrence and their associated risk factors in patients who underwent resection for pancreatic carcinoma. Methods: This retrospective study included 272 patients, who underwent Ro/R1-resection of PDAC from 2005 to 2020 at the University Hospital Erlangen. Risk factors for different recurrence patterns and the prognostic value of recurrence pattern on the overall survival after recurrence were evaluated. Results: 61 % of the patients experienced recurrence, mostly within the first 12 postoperative months (62 %) and in the form of metastases (87 %). The median overall survival from recurrence was 9.2 months. The preoperative absence of diabetes and the presence of lymph node metastasis were independent risk factors for recurrence and a preoperative CA19-9 exceeding 97 U/ml for early recurrence. Additionally, lymph node metastases were associated with a higher risk of metastatic recurrence. Early recurrence, but not the site of recurrence, was identified as an independent prognostic factor for worse overall survival from recurrence. Conclusion: The occurrence of recurrence and especially of early and metastatic recurrence are associated with a worse overall survival. Patients lacking preoperative diabetes, having high preoperative CA19-9 values and lymph node metastases are particularly at risk for (early) recurrence.
CRIS-Team Scopus Importer:2024-09-06
Keywords: Early recurrence; Locoregional recurrence; Overall survival; Pancreatic ductal adenocarcinoma; Recurrence; Resection; Surgery

Reduced cytotoxicity by mutation of lysine 590 of Pseudomonas exotoxin can be restored in an optimized, lysine-free immunotoxin. - Ammon, Anna-Maria; Mellenthin, Lisa; Emmerich, C.; Naschberger, Elisabeth; Stürzl, Michael; Mackensen, Andreas; Müller, Fabian (Immunotherapy Advances, 2022)
Immunotoxins, which are fusion proteins of an antibody fragment and a fragment of a bacterial or a plant toxin, induce apoptosis in target cells by inhibition of protein synthesis. ADP-ribosylating toxins often have few lysine residues in their catalytic domain. As they are the target for ubiquitination, the low number of lysines possibly prevents ubiquitin-dependent degradation of the toxin in the cytosol. To reduce this potential degradation, we aimed to generate a lysine-free (noK), Pseudomonas exotoxin (PE)-based immunotoxin. The new generation 24 kDa PE, which lacks all but the furin-cleavage site of domain II, was mutated at lysine 590 (K590) and at K606 in a CD22-targeting immunotoxin and activity was determined against various B cell malignancies in vitro and in vivo. On average, K590 mutated to arginine (R) reduced cytotoxicity by 1.3-fold and K606R enhanced cytotoxicity by 1.3-fold compared to wild type (wt). Mutating K590 to histidine or deleting K590 did not prevent this loss in cytotoxicity. Neither stability nor internalization rate of K590R could explain reduced cytotoxicity. These results highlight the relevance of lysine 590 for PE intoxication. In line with in vitro results, the K606R mutant was more than 1.8-fold more active than the other variants in vivo suggesting that this single mutation may be beneficial when targeting CD22-positive malignancies. Finally, reduced cytotoxicity by K590R was compensated for by K606R and the resulting lysine-free variant achieved wt-like activity in vitro and in vivo. Thus, PE24-noK may represent a promising candidate for down-stream applications that would interfere with lysines.
EVALuna2:505954

Regression of apoptosis-resistant colorectal tumors by induction of necroptosis in mice - He, Gui-Wei; Günther, Claudia; Thonn, Veronika; Yu, Yu-Qiang; Martini, Eva; Buchen, Barbara; Neurath, Markus; Stürzl, Michael; Becker, Christoph (Journal of Experimental Medicine, 2017)
Cancer cells often acquire capabilities to evade cell death induced by current chemotherapeutic treatment approaches. Caspase-8, a central initiator of death receptor-mediated apoptosis, for example, is frequently inactivated in human cancers via multiple mechanisms such as mutation. Here, we show an approach to overcome cell death resistance in caspase-8-deficient colorectal cancer (CRC) by induction of necroptosis. In both a hereditary and a xenograft mouse model of caspase-8-deficient CRC, second mitochondria-derived activator of caspase (SMAC) mimetic treatment induced massive cell death and led to regression of tumors. We further demonstrate that receptor-interacting protein kinase 3 (RIP3), which is highly expressed in mouse models of CRC and in a subset of human CRC cell lines, is the deciding factor of cancer cell susceptibility to SMAC mimetic-induced necroptosis. Thus, our data implicate that it may be worthwhile to selectively evaluate the efficacy of SMAC mimetic treatment in CRC patients with caspase-8 deficiency in clinical trials for the development of more effective personalized therapy.
EVALuna2:15307

Reply to D. Sargent et al - Glimelius, Bengt; Hohenberger, Werner; Matzel, Klaus; Sugihara, Kenichi; Quirke, Philip (Journal of Clinical Oncology, 2016)
EVALuna2:15248

Reprogramming Sacral Neuromodulation for Sub-Optimal Outcomes: Evidence and Recommendations for Clinical Practice - Dudding, Thomas C.; Lehur, Paul A.; Sorensen, Michael; Engelberg, Stefan; Bertapelle, Maria Paola; Chartier-Kastler, Emmanuel; Everaert, Karel; Van Kerrebroeck, Philip; Knowles, Charles H.; Lundby, Lilli; Matzel, Klaus; Munoz-Duyos, Arantxa; et al. (Neuromodulation, 2021)
Objectives: In some patients treated for urinary or fecal incontinence with sacral neuromodulation (SNM) persistence of symptoms, a reduction in efficacy or adverse effects of stimulation can occur. In such situations, further programming of the SNM device can help resolve problems. Infrequently hardware failure is detected. This article aims to provide practical guidance to solve sub-optimal outcomes (troubleshooting) occurring in the course of SNM therapy. Materials and Methods: A systematic literature review was performed. Collective clinical experience from an expert multidisciplinary group was used to form opinion where evidence was lacking. Results: Circumstances in which reprogramming is required are described. Actions to undertake include changes of electrode configuration, stimulation amplitude, pulse frequency, and pulse width. Guidance in case of loss of efficacy and adverse effects of stimulation, developed by a group of European experts, is presented. In addition, various hardware failure scenarios and their management are described. Conclusions: Reprogramming aims to further improve patient symptoms or ensure a comfortable delivery of the therapy. Initial changes of electrode configuration and adjustment of stimulation parameters can be performed at home to avoid unnecessary hospital visits. A logical and stepwise approach to reprogramming can improve the outcome of therapy and restore patient satisfaction.
CRIS-Team Scopus Importer:2021-07-30
Keywords: Fecal incontinence; reprogramming; sacral neuromodulation; troubleshooting; urinary incontinence

Resection of pancreatic cancer in Europe and USA: an international large-scale study highlighting large variations - Huang, Lei; Jansen, Lina; Balavarca, Yesilda; Molina-Montes, Esther; Babaei, Masoud; Van Der Geest, Lydia; Lemmens, Valery; Van Eycken, Liesbet; De Schutter, Harlinde; Johannesen, Tom B.; Fristrup, Claus W.; Mortensen, Michael B.; et al. (Gut, 2017)
Resection can potentially cure resectable pancreatic cancer (PaC) and significantly prolong survival in some patients. This large-scale international study aimed to investigate variations in resection for PaC in Europe and USA and determinants for its utilisation.Data from six European population-based cancer registries and the US Surveillance, Epidemiology, and End Results Program database during 2003-2016 were analysed. Age-standardised resection rates for overall and stage I-II PaCs were computed. Associations between resection and demographic and clinical parameters were assessed using multivariable logistic regression models.A total of 153 698 records were analysed. In population-based registries in 2012-2014, resection rates ranged from 13.2% (Estonia) to 21.2% (Slovenia) overall and from 34.8% (Norway) to 68.7% (Denmark) for stage I-II tumours, with great international variations. During 2003-2014, resection rates only increased in USA, the Netherlands and Denmark. Resection was significantly less frequently performed with more advanced tumour stage (ORs for stage III and IV versus stage I-II tumours: 0.05-0.18 and 0.01-0.06 across countries) and increasing age (ORs for patients 70-79 and >=80 versus those <60 years: 0.37-0.63 and 0.03-0.16 across countries). Patients with advanced-stage tumours (stage III-IV: 63.8%-81.2%) and at older ages (>=70 years: 52.6%-59.5%) receiving less frequently resection comprised the majority of diagnosed cases. Patient performance status, tumour location and size were also associated with resection application.Rates of PaC resection remain low in Europe and USA with great international variations. Further studies are warranted to explore reasons for these variations.
EVALuna2:15298

Resection of pancreatic cancer in Europe and USA: An international large-scale study highlighting large variations - Huang, Lei; Jansen, Lina; Balavarca, Yesilda; Molina-Montes, Esther; Babaei, Masoud; Van Der Geest, Lydia; Lemmens, Valery; Van Eycken, Liesbet; De Schutter, Harlinde; Johannesen, Tom B.; Fristrup, Claus W.; Mortensen, Michael B.; et al. (Gut, 2019)
Objective: Resection can potentially cure resectable pancreatic cancer (PaC) and significantly prolong survival in some patients. This large-scale international study aimed to investigate variations in resection for PaC in Europe and USA and determinants for its utilisation. Design: Data from six European population-based cancer registries and the US Surveillance, Epidemiology, and End Results Program database during 2003-2016 were analysed. Age-standardised resection rates for overall and stage I-II PaCs were computed. Associations between resection and demographic and clinical parameters were assessed using multivariable logistic regression models. Results: A total of 153 698 records were analysed. In population-based registries in 2012-2014, resection rates ranged from 13.2% (Estonia) to 21.2% (Slovenia) overall and from 34.8% (Norway) to 68.7% (Denmark) for stage I-II tumours, with great international variations. During 2003-2014, resection rates only increased in USA, the Netherlands and Denmark. Resection was significantly less frequently performed with more advanced tumour stage (ORs for stage III and IV versus stage I-II tumours: 0.05-0.18 and 0.01-0.06 across countries) and increasing age (ORs for patients 70-79 and ≥80 versus those <60 years: 0.37-0.63 and 0.03-0.16 across countries). Patients with advanced-stage tumours (stage III-IV: 63.8%-81.2%) and at older ages (≥70 years: 52.6%-59.5%) receiving less frequently resection comprised the majority of diagnosed cases. Patient performance status, tumour location and size were also associated with resection application. Conclusion: Rates of PaC resection remain low in Europe and USA with great international variations. Further studies are warranted to explore reasons for these variations.
CRIS-Team Scopus Importer:2019-05-03
Keywords: age; pancreatic cancer; population-based; surgical resection; TNM stage; variation

Results of Surgical and Conservative Treatment for Enterocutaneous Fistulas. Is there an Indication for Conservative Treatment? - Schildberg, C. W.; Raptis, Dimitrios; Langheinrich, M.; Hohenberger, Werner; Horbach, T. (Zentralblatt für Chirurgie, 2016)
The manifestation of enterocutaneous fistulas is varied. They can range from controlled secretion via the abdominal wall to septic disease. The disease is categorised into low-, moderate- and high-output fistulas. Often the only option is surgical treatment. Occasionally, there is spontaneous healing under conservative treatment. The aim of this study was to work out a possible subgroup of patients who benefit from conservative treatment. Material und Methods: Ninety-nine patients were treated for enterocutaneous fistulas from 1 January 1995 to 31 December 2005. Seventy patients underwent surgery, 29 patients were treated conservatively. All data was collected prospectively using an admission form and was analysed retrospectively. Conservative treatment consisted of fasting with parenteral nutrition, while fistulas in the surgical group were treated by suture repair or resection. Additive treatments such as vacuum dressings or TNF-? medication for patients with Crohn's disease were not performed.In our study we achieved a total cure rate of 69%, with an average hospital stay of 38 days. Surgical treatment led to significantly better results compared with conservative treatment (83 vs. 34%). Mortality in the surgical group was distinctly, but not significantly reduced at 7%, compared with 14% in the conservative group. The fistulas that healed after conservative treatment were low-output fistulas only.Enterocutaneous fistulas are diseases associated with long hospital stays and, therefore, expensive treatment. Low-output fistulas may heal spontaneously. The best results are achieved by surgical treatment. More recent treatments such as vacuum therapy and TNF-? medication for patients with Crohn's disease are promising approaches. In the future, many of these will have to be combined with surgical treatment.
EVALuna2:15208

Reverse transfected cell microarrays in infectious disease research - Konrad, Andreas; Jochmann, Ramona; Kühn, Elisabeth; Naschberger, Elisabeth; Chudasama, Priya; Stürzl, Michael (Methods in Molecular Biology, 2011)
Several human pathogenic viruses encode large genomes with often more than 100 genes. Viral pathogenicity is determined by carefully orchestrated co-operative activities of several different viral genes which trigger the phenotypic functions of the infected cells. Systematic analyses of these complex interactions require high-throughput transfection technology. Here we have provided a laboratory manual for the reverse transfected cell microarray (RTCM; alternative name: cell chip) as a high-throughput transfection procedure, which has been successfully applied for the systematic analyses of single and combination effects of genes encoded by the human herpesvirus-8 on the NF-kappaB signal transduction pathway. In order to quantitatively determine the effects of viral genes in transfected cells, protocols for the use of GFP as an indicator gene and for indirect immunofluorescence staining of cellular target proteins have been included. RTCM provides a useful methodological approach to investigate systematically combination effects of viral genes on cellular functions.
Created from Fastlane, Scopus look-up
Keywords: Cell chip; High-throughput; Human herpesvirus-8; KSHV; Microarray; Transfection

Risk factors for appendiceal neoplasm and malignancy among patients with acute appendicitis - Brunner, Maximilian; Lapins, Philipp; Langheinrich, Melanie; Baecker, Justus; Krautz, Christian; Kersting, Stephan; Grützmann, Robert; Maak, Matthias; Weber, Georg (International Journal of Colorectal Disease, 2019)
Purpose: Non-operative management of acute uncomplicated appendicitis has shown promising results but might carry the risk of delayed diagnosis of premalignant or malignant appendiceal tumors found by chance in 0.7–2.5% of appendiceal specimen after appendectomy. Purpose of this study was to analyze whether appendiceal tumors are associated with a complicated appendicitis and to determine risk factors for appendiceal neoplasm and malignancy in patients with acute appendicitis. Methods: We performed a retrospective analysis of 1033 adult patients, who underwent appendectomy for acute appendicitis from 2010 to 2016 at the University hospital Erlangen. Data included patients’ demographics; comorbidities; pre-, intra- and postoperative findings; and histopathological results. Complicated appendicitis was defined in the presence of perforation or abscess. Results: Appendiceal neoplasm respectively malignancy rate was 2.8% respectively 1.5%. Using univariate analysis, we identified seven risk factors at least for appendiceal neoplasm or malignancy: age, ASA, C-reactive protein, appendiceal diameter, perforation, intraoperative perithyphilitic abscess, and complicated appendicitis. Risk for appendiceal neoplasm or malignancy was 4.4% respectively 2.7% in complicated acute appendicitis compared to 2.0% respectively 1.0% in uncomplicated appendicitis (p = 0.043 respectively p = 0.060). In multivariate analysis, age ≥ 50 years and a diameter of the appendix in the sonography ≥ 13 mm were independent risk factors predicting the presence of appendiceal neoplasm and malignancy. Conclusion: Among patients with appendicitis, there are relevant risk factors predicting appendiceal tumors, especially age and appendiceal diameter in sonography. But the identified risk factors have a low sensitivity and specificity, so obtaining a confident preoperative diagnosis is challenging.
CRIS-Team Scopus Importer:2019-12-20
Keywords: Appendectomy; Appendiceal neoplasm; Complicated appendicitis; Malignancy; Risk factors

Risk Factors for Conversion from Laparoscopic to Open Appendectomy - Bancke Laverde, Bruno Leonardo; Maak, Matthias; Langheinrich, Melanie; Kersting, Stephan; Denz, Axel; Krautz, Christian; Weber, Georg; Grützmann, Robert; Brunner, Maximilian (Journal of Clinical Medicine, 2023)
(1) Background: Since its introduction in the 1990s, laparoscopic appendectomy has become established over the years and is today considered the standard therapy for acute appendicitis. In some cases, however, a conversion to the open approach is still necessary. The primary aim of this study was to identify risk factors for the need to convert from the laparoscopic to an open approach during appendectomy for acute appendicitis. (2) Methods: A retrospective analysis of 1220 adult patients who underwent laparoscopic appendectomy for acute appendicitis from 2010 to 2020 at the University Hospital Erlangen was performed. Data, including patient demographics and pre-, intra-, and postoperative findings, were collected and compared between patients with and without conversion. (3) Results: The conversion rate in our cohort was 5.5%. A higher preoperative WBC count and CRP (OR 1.9, p = 0.042, and OR 2.3, p = 0.019, respectively), as well as the presence of intraoperative perforation, necrosis or gangrene, perityphlitic abscess and peritonitis (OR 3.2, p = 0.001; OR 2.3, p = 0.023; OR 2.6, p = 0.006 and OR 2.0, p = 0.025, respectively) were identified as independent risk factors for conversion from the laparoscopic to the open approach. Conversion was again independently associated with higher morbidity (OR 2.2, p = 0.043). (4) Conclusion: The laparoscopic approach is feasible and safe in the majority of patients with acute appendicitis. Only increased inflammatory blood markers could be detected as the preoperative risk factors potentially influencing the choice of surgical approach but only with low specificity and sensitivity. For the decision to convert, intraoperative findings are additionally crucial. However, patients with conversion should receive special attention in the postoperative course, as these have an increased risk of developing complications.
CRIS-Team Scopus Importer:2023-07-28
Keywords: acute appendicitis; conversion; laparoscopic approach; morbidity

Risk Factors for Postoperative Major Morbidity, Anastomotic Leakage, Re-Surgery and Mortality in Patients with Colonic Perforation. - Brunner, Maximilian; Gärtner, Lara; Weiß, Andreas; Weber, Klaus; Denz, Axel; Krautz, Christian; Weber, Georg; Grützmann, Robert (Journal of Clinical Medicine, 2024)
Background/Objectives: This study aimed to determine the risk factors associated with postoperative major morbidity, anastomotic/suture leakage, re-surgery and mortality in patients undergoing emergency surgery for colonic perforation. Methods: A total of 204 adult patients treated surgically for colonic perforation from 2016 to 2021 at the University Hospital Erlangen were included in a retrospective analysis. Patient demographics and pre-, intra- and postoperative parameters were obtained and evaluated among various outcome groups (in-hospital major morbidity, anastomotic/suture leakage, re-surgery and 90-day mortality). Results: Postoperative in-hospital major morbidity, anastomotic/suture leakage, need of re-surgery and 90-day mortality occurred in 45%, 12%, 25% and 12% of the included patients, respectively. Independent risk factors for in-hospital major morbidity were identified and included the presence of any comorbidity, a significantly reduced preoperative general condition, the localization of perforation in the right hemicolon and the need for an intraoperative blood transfusion. The only independent risk factor for anastomotic/suture leakage was the presence of any comorbidity, whereas no independent risk factors for re-surgery were found. An age > 65 years, a significantly reduced preoperative general condition and the need for an intraoperative blood transfusion were independent risk factors for 90-day mortality. Conclusions: Our study identified risk factors impacting postoperative outcomes in patients undergoing emergency surgery for colonic perforation. These patients should receive enhanced postoperative care and may benefit from individualized and targeted therapeutic approaches.
EVALuna2:582568

Risk factors for postoperative morbidity, prolonged length of stay and hospital readmission after appendectomy for acute appendicitis - Laverde, Bruno Leonardo Bancke; Maak, Matthias; Langheinrich, Melanie; Kersting, Stephan; Denz, Axel; Krautz, Christian; Weber, Georg; Grützmann, Robert; Brunner, Maximilian (European Journal of Trauma and Emergency Surgery, 2023)
PurposeThe aim of the present study was to identify risk factors associated with postoperative morbidity and major morbidity, with a prolonged length of hospital stay and with the need of readmission in patients undergoing appendectomy due to acute appendicitis.MethodsWe performed a retrospective analysis of 1638 adult patients who underwent emergency appendectomy for preoperatively suspected acute appendicitis from 2010 to 2020 at the University Hospital Erlangen. Data including patient demographics, pre-, intra-, and postoperative findings were collected and compared between different outcome groups (morbidity, major morbidity, prolonged length of postoperative hospital stay (LOS) and readmission) from those patients with verified acute appendicitis (n = 1570).ResultsRate of negative appendectomies was 4%. In patients with verified acute appendicitis, morbidity, major morbidity and readmission occurred in 6%, 3% and 2%, respectively. Mean LOS was 3.9 days. Independent risk factors for morbidity were higher age, higher preoperative WBC-count and CRP, lower preoperative hemoglobin, longer time to surgery and longer duration of surgery. As independent risk factors for major morbidity could be identified higher age, higher preoperative CRP, lower preoperative hemoglobin and longer time to surgery. Eight parameters were independent risk factors for a prolonged LOS: higher age, higher preoperative WBC-count and CRP, lower preoperative hemoglobin, need for conversion, longer surgery duration, presence of intraoperative complicated appendicitis and of postoperative morbidity. Presence of malignancy and higher preoperative WBC-count were independent risk factors for readmission.ConclusionAmong patients undergoing appendectomy for acute appendicitis, there are relevant risk factors predicting postoperative complications, prolonged hospital stays and readmission. Patients with the presence of the identified risk factors should receive special attention in the postoperative course and may benefit from a more individualized therapy.
CRIS-Team WoS Importer:2023-03-03

Risk Factors for Postoperative Morbidity, Suture Insufficiency, Re-Surgery and Mortality in Patients with Gastroduodenal Perforation - Treuheit, Julia; Krautz, Christian; Weber, Georg; Grützmann, Robert; Brunner, Maximilian (Journal of Clinical Medicine, 2023)
(1) Background: The aim of the present study was to identify risk factors associated with postoperative morbidity, suture/anastomotic insufficiency, re-surgery, and mortality in patients undergoing surgery for gastroduodenal perforation. (2) Methods: A retrospective analysis of 273 adult patients who received surgical treatment for gastroduodenal perforation from January 2006 to June 2021 at the University Hospital Erlangen was performed. The patient demographics and preoperative, intraoperative, and postoperative parameters were collected and compared among the different outcome groups (in-hospital morbidity, suture/anastomotic insufficiency, re-surgery, and 90-day mortality). (3) Results: In-hospital morbidity, suture/anastomotic insufficiency, need for re-surgery, and 90-day mortality occurred in 71%, 10%, 26%, and 25% of patients, respectively. The independent risk factors for morbidity were a significantly reduced general condition, a lower preoperative hemoglobin level, and a higher preoperative creatinine level. The independent risk factors for suture/anastomotic insufficiency could be identified as an intake of preoperative steroids and a perforation localization in the proximal stomach or duodenum. The four parameters were independent risk factors for the need for re-surgery: a significantly reduced general condition, a perforation localization in the proximal stomach, a higher preoperative creatinine level, and a higher preoperative CRP level. An age over 66 years and a higher preoperative CRP level were independent risk factors for 90-day mortality. (4) Conclusions: Our study could identify relevant risk factors for the postoperative outcome of patients undergoing surgical treatment for gastroduodenal perforation. Patients exhibiting the identified risk factors should receive heightened attention in the postoperative period and may potentially benefit from personalized and tailored therapy.
CRIS-Team Scopus Importer:2023-10-20
Keywords: gastroduodenal perforation; morbidity; mortality; re-surgery; risk factors; surgery; suture insufficiency

Risk Factors for Regional and Systemic Metastases in Patients with Sentinel Lymph Node-negative Melanoma - Erdmann, Michael; Sigler, Dominic; Uslu, Ugur; Göhl, Jonas; Grützmann, Robert; Schuler, Gerold; Schellerer, Vera (Anticancer Research, 2018)
BACKGROUND: Sentinel lymph node status is a strong prognostic factor in melanoma. However, up to 21% of sentinel lymph node-negative patients develop locoregional and distant metastases during follow-up. AIM: To analyze risk factors for locoregional and distant metastasis in patients with sentinel lymph node-negative melanoma. PATIENTS AND METHODS: A total of 545 patients underwent sentinel lymph node biopsy (SNB) between 2005 and 2013 at our hospital. Data for 449 patients with a negative SNB were analyzed regarding risk factors and development of metastases. Follow-up was performed until 2016. RESULTS: A total of 72 SNB-negative patients developed metastases, including 25 (34.7%) distant and 47 (63.3%) locoregional metastases. Locoregional metastases occurred earlier compared to distant metastases (with a mean of 24.2 and 23.5 months for regional lymph node and cutaneous metastases, respectively, vs. 31.4 months for distant metastases). Patients with metastases despite negative SNB had a greater tumor thickness (p=0.001), a higher rate of nodular melanoma (p=0.001), ulceration (p<0.001), and were older (p=0.05) compared to SNB-negative patients without subsequent metastases. Out of SNB-negative patients, 16% developed metastases. CONCLUSION: Close clinical follow-up including sonography of the draining lymph node region is mandatory for melanoma patients regardless of SNB status.
EVALuna2:203619

Roboterassistierte Pankreassegmentresektion - Weber, Georg; Krautz, Christian; Grützmann, Robert; Brunner, Maximilian (Zentralblatt für Chirurgie, 2025)
Central pancreatectomy is an excellent alternative to left pancreatectomy for symptomatic benign or premalignant lesions of the pancreatic body or tail. A key advantage of this technique lies in the preservation of pancreatic parenchyma, resulting in a lower rate of postoperative diabetes mellitus. However, this procedure requires more complex reconstruction, which in turn is associated with an increased risk of morbidity.Insulinoma in the pancreatic body.Robot-assisted central pancreatectomy with pancreaticojejunostomy using a modified Blumgart technique.Central pancreatectomy is a generally rare and challenging pancreatic procedure, but clearly plays a significant role in modern pancreatic surgery due to its functional advantages. When appropriate and technically feasible, central pancreatectomy should be preferred to the alternative of left pancreatectomy and whenever possible, performed minimally invasively.
EVALuna2:582564

Roboterassistierte viszeralchirurgische Eingriffe in Deutschland: Eine Analyse zum aktuellen Stand sowie zu Trends der letzten 5 Jahre anhand von StuDoQ|Robotik-Registerdaten - Brunner, Maximilian; Elgendy, Amr; Denz, Axel; Weber, Georg; Grützmann, Robert; Krautz, Christian (Die Chirurgie, 2023)
Robot-assisted systems have been increasingly used in general surgery for several years. Accordingly, the number of systems installed in Germany has also rapidly increased. While around 100 robot-assisted systems were used in German hospitals in 2018, this figure had already risen to more than 200 by 2022. The aim of this article is to present the current state of development and trends in robotic surgery in Germany. For this purpose, data from the StuDoQ|Robotics register were analyzed. Furthermore, a descriptive analysis of concomitant diagnosis-related groups (DRG) data was carried out via the Federal Statistical Office (Destatis), for a better assessment of the representativeness of the StuDoQ|Robotics register data. In both data sets, the annual number of robot-assisted visceral surgery procedures in Germany steadily increased. Compared to the DRG data, only 3.7% up to a maximum of 36.7% of all robot-assisted procedures performed were documented in the StuDoQ|Robotics register, depending on the type of procedure. Colorectal resections were the most frequent robot-assisted procedures (StuDoQ: 32.5% and 36.7% vs. DRG data: 24.2% and 29.7%) and had, for example, low mortality rates (StuDoQ: 1% and 1% vs. DRG data: 2.3% and 1.3%). Due to the low coverage rates of robot-assisted esophageal, gastric, pancreatic and liver interventions, no valid statements could be derived from the StuDoQ data for these areas. With the current coverage rates, the informative value of the StuDoQ|Robotics register is considerably limited for some types of intervention. In the future, measures should therefore be explored that lead to a significant increase in the coverage rates.
CRIS-Team Scopus Importer:2023-08-11
Keywords: Hospital billing data; Robotic colorectal surgery; Robotic hepato-pancreato-biliary surgery; Robotic surgery of the upper gastrointestinal tract; StuDoQ register

Robotische Pankreatoduodenektomie: Variationen der Pankreasanastomose in modifizierter Blumgart-Technik - Seeger, Philipp; Distler, Marius; Thomaschewski, Michael; Zimmermann, Markus; Heumann, Asmus; Uzunoglu, Faik Güntac; Grützmann, Robert; Weber, Georg; Brunner, Maximilian; Kersting, Stephan; Hackert, Thilo; Keck, Tobias; et al. (Zentralblatt für Chirurgie, 2024)
Zusammenfassung Zielsetzung Die wichtigste Komplikation nach Pankreatoduodenektomie ist die klinisch relevante Pankreasfistel. Um die Rate an Komplikationen zu senken, ist eine routinierte und standardisierte Operationstechnik zur Anlage der Pankreatojejunostomie notwendig. Indikationen Die Pankreatoduodenektomie ist im multimodalen Setting der Goldstandard zur Behandlung des lokal begrenzten Pankreaskopfkarzinoms und weiterer Pathologien. Das robotische Verfahren bietet als innovatives minimalinvasives Verfahren Vorteile bez. Morbiditat und Ergonomie. Methode Nach der Resektionsphase folgt die Rekonstruktion beginnend mit der Pankreatojejunostomie. Die aktuell meistverbreitete robotische Technik ist die Anastomose nach Blumgart: Dabei wird eine au ss ere Naht transpankreatisch zwischen Jejunalwand und dem gesamten Pankreasparenchym in ventrodorsaler Ausrichtung angelegt, die Spannungs- und Scherkrafte verteilt. Die innere Naht wird durch eine Duct-to-Mucosa-Naht des Pankreasganges mit einer kleinen Jejujunostomie erreicht. In diesem Manuskript werden verschiedene Varianten dieser Rekonstruktion in robotischer Technik gezeigt. Schlussfolgerung Hinsichtlich der wissenschaftlichen Evidenz zeigt keine Anastomosenvariante einen Vorteil. Das Outcome ist abhangig von der Expertise des Operateurs, entsprechend sollte diejenige Anastomosentechnik angewendet werden, fur die am meisten Erfahrung verfugbar ist. Die in diesem Beitrag gezeigten Variationen sollen fur Anwender den Fokus auf wichtige Details legen sowie Tipps und Tricks zur Durchfuhrung geben.
EVALuna2:582588

Roflumilast inhibits tumor growth and migration in STK11/LKB1 deficient pancreatic cancer - Zhang, Shuman; Yun, Duo; Yang, Hao; Eckstein, Markus; Elbait, Gihan Daw; Zhou, Yaxing; Lu, Yanxi; Yang, Hai; Zhang, Jinping; Dörflein, Isabella; Britzen-Laurent, Nathalie; Pfeffer, Susanne; et al. (Cell Death Discovery, 2024)
Pancreatic cancer is a malignant tumor of the digestive system. It is highly aggressive, easily metastasizes, and extremely difficult to treat. This study aimed to analyze the genes that might regulate pancreatic cancer migration to provide an essential basis for the prognostic assessment of pancreatic cancer and individualized treatment. A CRISPR knockout library directed against 915 murine genes was transfected into TB 32047 cell line to screen which gene loss promoted cell migration. Next-generation sequencing and PinAPL.py- analysis was performed to identify candidate genes. We then assessed the effect of serine/threonine kinase 11 (STK11) knockout on pancreatic cancer by wound-healing assay, chick agnosia (CAM) assay, and orthotopic mouse pancreatic cancer model. We performed RNA sequence and Western blotting for mechanistic studies to identify and verify the pathways. After accelerated Transwell migration screening, STK11 was identified as one of the top candidate genes. Further experiments showed that targeted knockout of STK11 promoted the cell migration and increased liver metastasis in mice. Mechanistic analyses revealed that STK11 knockout influences blood vessel morphogenesis and is closely associated with the enhanced expression of phosphodiesterases (PDEs), especially PDE4D, PDE4B, and PDE10A. PDE4 inhibitor Roflumilast inhibited STK11-KO cell migration and tumor size, further demonstrating that PDEs are essential for STK11-deficient cell migration. Our findings support the adoption of therapeutic strategies, including Roflumilast, for patients with STK11-mutated pancreatic cancer in order to improve treatment efficacy and ultimately prolong survival.
CRIS-Team Scopus Importer:2024-04-12

Role of guanylate binding protein-1 in vascular defects associated with chronic inflammatory diseases - Hammon, Matthias; Herrmann, Martin; Bleiziffer, Oliver; Pryymachuk, Galyna; Andreoli, Laura; Munoz, Luis Enrique; Amann, Kerstin Ute; Mondini, Michele; Gariglio, Marisa; Airo, Paolo; Schellerer, Vera; Hatzopoulos, Antonis K.; et al. (Journal of Cellular and Molecular Medicine, 2011)
Rheumatic autoimmune disorders are characterized by a sustained pro-inflammatory microenvironment associated with impaired function of endothelial progenitor cells (EPC) and concomitant vascular defects. Guanylate binding protein-1 (GBP-1) is a marker and intracellular regulator of the inhibition of proliferation, migration and invasion of endothelial cells induced by several pro-inflammatory cytokines. In addition, GBP-1 is actively secreted by endothelial cells. In this study, significantly increased levels of GBP-1 were detected in the sera of patients with chronic inflammatory disorders. Accordingly we investigated the function of GBP-1 in EPC. Interestingly, stable expression of GBP-1 in T17b EPC induced premature differentiation of these cells, as indicated by a robust up-regulation of both Flk-1 and von Willebrand factor expression. In addition, GBP-1 inhibited the proliferation and migration of EPC in vitro. We confirmed that GBP-1 inhibited vessel-directed migration of EPC at the tissue level using the rat arterio-venous loop model as a novel quantitative in vivo migration assay. Overall, our findings indicate that GBP-1 contributes to vascular dysfunction in chronic inflammatory diseases by inhibiting EPC angiogenic activity via the induction of premature EPC differentiation. © 2011 The Authors Journal of Cellular and Molecular Medicine © 2011 Foundation for Cellular and Molecular Medicine/Blackwell Publishing Ltd.
Created from Fastlane, Scopus look-up
Keywords: Endothelial progenitor cells; Guanylate binding protein-1; Inflammation; Rheumatic autoimmune disorders; Rheumatoid arthritis; Systemic lupus erythematosus; Systemic sclerosis

Role of IFN-gamma-activation of distinct tumor and stromal cell populations in colorectal carcinoma pathogenesis - Britzen-Laurent, Nathalie; Guo, Wei; Langer, Victoria; Khoziainova, Svetlana; Weisenburger, Thomas; Winkler, Thomas; Straube, Julia; Waldner, Maximilian; Becker, Christoph; Naschberger, Elisabeth; Skottke, Lisa; Tripal, Philipp; et al. (CANCER RESEARCH, 2019)
CRIS-Team WoS Importer:2019-10-22

"Run-off" synthesis and application of defined single-stranded DNA hybridization probes. - Stürzl, Michael; Roth, Willy Kurt (Analytical Biochemistry, 1990)
A simple and efficient method for synthesizing radioactively labeled single-stranded DNA hybridization probes with Thermus aquaticus (Taq) DNA polymerase is described. This is done in a "run-off" polymerization with repeated cycles of denaturation, annealing, and extension. It leads to high yields of a single-stranded DNA of defined length (up to 5000 nt), which is labeled to a high specific activity (1.3 x 10(8) cpm/micrograms DNA). These hybridization probes are equally sensitive as nick-translated DNA probes, but strand specific. This was tested by slot blot hybridization with in vitro-transcribed target RNAs and by Northern blotting. The use of single-stranded DNA hybridization probes combines the benefits of DNA stability and single-strand RNA probes.

Sacral malformations: use of imaging to optimise sacral nerve stimulation - Povo, A.; Arantes, Mavilde; Matzel, Klaus; Barbosa, Joselina; Ferreira, M. A. (International Journal of Colorectal Disease, 2016)
The success of sacral nerve stimulation, a common treatment for pelvic floor disorders, depends on correct placement of the electrodes through the sacral foramina. When the bony anatomy and topography of the sacrum and sacral spinal nerves are intact, this is easily achieved; where sacral anomalies exist, it can be challenging. A better understanding of common sacral malformations can improve the success of sacral nerve stimulation (SNS) electrode placement.We reviewed 998 consecutive MRI scans performed to investigate low back pain in patients who had undergone CT and/or X-ray.Congenital sacral malformations were found in 24.1%, the most common being sacral meningeal cysts (16%) and spina bifida occulta (9.9%). Others were lumbosacral transitional vertebrae (2.5%), anterior occult meningocele (0.5%), partial sacral agenesis (0.2%) and vertebral dysplasia of S1 (0.2%).This radiologic review uncovered a high incidence of sacral malformations, and most were asymptomatic. All surgeons who perform SNS should have a basic understanding of sacral malformations, their incidence and effect on foraminal anatomy. Imaging will aid procedural planning.
EVALuna2:15263

Sacral nerve stimulation for faecal incontinence and constipation: a European consensus statement - Maeda, Yasuko; O'Connell, P. R.; Lehur, P. -A.; Matzel, Klaus; Laurberg, S. (Colorectal Disease, 2015)
In Europe during the last decade sacral nerve stimulation (SNS) or sacral neuromodulation (SNM) has been used to treat faecal incontinence (FI) and constipation. Despite this, there is little consensus on baseline investigations, patient selection and operative technique. A modified Delphi process was conducted to seek consensus on the current practice of SNS/SNM for FI and constipation.A systematic literature search of SNS for FI and constipation was conducted using PubMed. A set of questions derived from the search and expert opinion were answered on-line on two occasions by an international panel of specialists from Europe. A 1-day face-to-face meeting of the experts finalized the discussion.Three hundred and ninety-three articles were identified from the literature search, of which 147 fulfilled the inclusion criteria. Twenty-two specialists in FI and constipation from Europe participated. Agreement was achieved on 43 (86%) of 50 domains including the set-up of service, patient selection, baseline investigations, operative technique and programming of the device. The median of agreement was 95% (35-100%).Consensus was achieved on the majority of domains of SNS/SNM for FI and constipation. This should serve as a benchmark for safe and quality practice of SNS/SNM in Europe.
EVALuna2:15199

Sacral nerve stimulation for faecal incontinence in patients with sacral malformation - Brunner, Michaela; Cui, Z.; Matzel, Klaus (International Journal of Colorectal Disease, 2017)
Sacral nerve stimulation (SNS) is a common and effective treatment for faecal incontinence (FI), but accessibility of the sacral nerves is mandatory. In some cases, electrode placement fails for unknown reasons. A frequent cause could be sacral malformations, which have a high incidence (up to 24.1%) and can be unsuspected.We report two patients with FI consequent to congenital anorectal malformation and associated sacral malformation. Despite partial sacral agenesis, SNS was feasible in both. They benefitted greatly from SNS, with an improved ability to postpone the urge up to at least 15 min, reduced incontinence episodes (at least 50%), and significantly better quality of life.SNS may be feasible in patients with FI, even in the presence of sacral malformation. However, clinicians should be aware of the attendant technical difficulties. Preoperative imaging, preferably with MRI of the sacrum, is advisable. If the sacral spinal nerves are inaccessible technically, pudendal nerve stimulation could be considered, if anatomy permits.
EVALuna2:15239

Sacral neuromodulation for constipation and fecal incontinence in children and adolescents – study protocol of a prospective, randomized trial on the application of invasive vs. non-invasive technique - Besendörfer, Manuel; Kirchgatter, Annemarie; Carbon, Roman; Weiss, Christel; Müller, Hanna; Matzel, Klaus; Diez, Sonja (Trials, 2024)
Background: A therapeutic effect of sacral neuromodulation (SNM) on fecal incontinence (FI) and quality of life has been proven in adults. SNM is, however, rarely used in pediatric cases. The aim of the study is to investigate effects of SNM in pediatric constipation in a prospective parallel-group trial. Methods: A monocentric, randomized, unblinded, parallel-group trial is conducted. SNM is conducted in the invasive variant and in an innovative, external approach with adhesive electrodes (enteral neuromodulation, ENM). We include patients with constipation according to the ROME IV criteria and refractory to conventional options. Patients with functional constipation and Hirschsprung’s disease are able to participate. Participants are allocated in a 1:1 ratio to either SNM or ENM group. Clinical data and quality of life is evaluated in regular check-ups. Neuromodulation is applied continuously for 3 months (end point of the study) with follow-up-points at 6 and 12 months. Findings are analyzed statistically considering a 5% significance level (p ≤ 0.05). Outcome variables are defined as change in (1) episodes of abdominal pain, (2) episodes of FI, (3) defecation frequency, (4) stool consistency. Improvement of proprioception, influence on urinary incontinence, quality of life and safety of treatment are assessed as secondary outcome variables. We expect a relevant improvement in both study groups. Discussion: This is the first trial, evaluating effects of neuromodulation for constipation in children and adolescents and comparing effects of the invasive and non-invasive application (SNM vs. ENM). Trial registration: The study is registered with clinicaltrials.gov, Identifier NCT04713085 (date of registration 01/14/2021).
CRIS-Team Scopus Importer:2024-04-05
Keywords: Chronic refractory constipation; Enteral neuromodulation; Fecal incontinence; Functional constipation; Hirschsprung’s disease; Sacral nerve stimulation; Sacral neuromodulation

Sacral Neuromodulation for Fecal Incontinence and Constipation: Evidence, Programming and Long-term Management Sakralnervmodulation in der Therapie der Stuhlinkontinenz und Obstipation: Evidenz, Programmierung und Langzeitmanagement - Bittorf, Birgit; Matzel, Klaus (Zentralblatt für Chirurgie, 2023)
Background Over the last two decades, sacral neuromodulation (SNM) has established its role in the treatment of functional pelvic organ-/pelvic floor disorders. Even though the mode of action is not fully understood, SNM has become the preferred surgical treatment of fecal incontinence. Methods and Results A literature search was carried out on programming sacral neuromodulation and long-term outcomes in treating fecal incontinence and constipation. Sacral neuromodulation was found to be successful in the long term. Over the years, the spectrum of indications has expanded, and now includes patients presenting with anal sphincter lesions. The use of SNM for low anterior resection syndrome (LARS) is currently under clinical investigation. Findings of SNM for constipation are less convincing. In several randomised crossover studies, no success was demonstrated, even though it is possible that subgroups may benefit from the treatment. Currently the application cannot be recommended in general. The pulse generator programming sets the electrode configuration, amplitude, pulse frequency and pulse width. Usually pulse frequency and pulse width follow a default setting (14 Hz, 210 s), while electrode configuration and stimulation amplitude are adjusted individually to the patient need and perception of stimulation. Despite low infection rates and few electrode-/pulse generator dysfunctions, up to 65% of patients require surgical reintervention during long term follow-up - in 50% of cases because of battery depletion, which is an expected event. At least one reprogramming is necessary in about 75% of the patients during the course of the treatment, mostly because of changes in effectiveness, but rarely because of pain. Regular follow-up visits appear to be advisable. Conclusion Sacral neuromodulation can be considered to be a safe and effective long-term therapy of fecal incontinence. To optimise the therapeutic effect, a structured follow-up regime is advisable.
CRIS-Team Scopus Importer:2023-06-30
Keywords: fecal incontinence; long-term management; programming; sacral neuromodulation

Sacral neuromodulation for persistent faecal incontinence after laparoscopic ventral rectopexy for high-grade internal rectal prolapse - Mishra, A.; Prapasrivorakul, S.; Gosselink, M. P.; Gorissen, K. J.; Hompes, R.; Jones, O.; Cunningham, C.; Matzel, K. E.; Lindsey, I. (Colorectal Disease, 2016)
Internal rectal prolapse is recognized as an aetiological factor in faecal incontinence. Patients found to have a high-grade internal rectal prolapse on routine proctography are offered a laparoscopic ventral rectopexy after failed maximum medical therapy. Despite adequate anatomical repair, faecal incontinence persists in a number of patients. The aim of this study was to evaluate the outcome of sacral neuromodulation in this group of patients.Between August 2009 and January 2012, 52 patients who underwent a laparoscopic ventral rectopexy for faecal incontinence associated with high-grade internal rectal prolapse had persistent symptoms of faecal incontinence and were offered sacral neuromodulation. Symptoms were evaluated before and after the procedure using the Fecal Incontinence Severity Index (FISI) and the Gastrointestinal Quality of Life Index (GIQLI).Temporary test stimulation was successful in 47 (94%) of the patients who then underwent implantation of a permanent pulse generator. The median FISI score 1 year after sacral neuromodulation was lower than the median score before [34 (28-59) vs 19 (0-49); P < 0.01], indicating a significant improvement in faecal continence. Quality of life (GIQLI) was significantly better after starting sacral neuromodulation [78 (31-107) vs 96 (55-129); P < 0.01].Patients may benefit from sacral neuromodulation for persisting faecal incontinence after laparoscopic ventral rectopexy.
EVALuna2:15207

Sakrale Neuromodulation - Matzel, Klaus E.; Bittorf, B. (Coloproctology, 2020)
Over the last few years sacral neuromodulation has evolved to become the mainstay of surgical treatment of fecal incontinence. The electrode positioning is the crucial element of the operative intervention. With suboptimal electrode placement the probability of treatment success is reduced, the risk of negative side effects is increased and the energy consumption of the stimulation is increased resulting in reduced longevity of the battery and higher treatment costs. Preliminary findings indicate that the modified technique of electrode placement using intraoperative imaging and a curved stylet leads to better electrode positioning. The modified technique of electrode placement in sacral neuromodulation enables a more precise and effective treatment.
CRIS-Team Scopus Importer:2020-03-06
Keywords: Curved stylets; Electrode placement; Fecal incontinence; Sacral spinal nerve stimulation; Tined lead electrode

Screening for pancreatic cancer in individuals with genetic susceptibility - Grützmann, Robert; Brunner, Maximilian (Hepatobiliary Surgery and Nutrition, 2023)
CRIS-Team WoS Importer:2023-06-02
Keywords: Pancreatic cancer; screening; genetic susceptibility; guideline; BRCA

Scribble Deficiency Promotes Pancreatic Ductal Adenocarcinoma Development and Metastasis - Bermejo-Rodriguez, Camino; Araos Henríquez, Joaquín; Caligiuri, Giuseppina; Pinto Teles, Sara; Park, Youngkyu; Evans, Anthony; Barrera, Lawrence N.; Neesse, Albrecht; Grützmann, Robert; Aust, Daniela; Rümmele, Petra; Knösel, Thomas; et al. (Cancer Research, 2024)
Perturbation of cell polarity is a hallmark of pancreatic ductal adenocarcinoma (PDAC) progression. Scribble (SCRIB) is a well-characterized polarity regulator that has diverse roles in the pathogenesis of human neoplasms. To investigate the impact of SCRIB deficiency in PDAC development and progression, Scrib expression was genetically ablated in well-established mouse models of PDAC. Scrib loss in combination with KrasG12D did not influence development of pancreatic intraepithelial neoplasms in mice. However, Scrib deletion cooperated with KrasG12D and concomitant Trp53 heterozygous deletion to promote invasive PDAC and metastatic dissemination, leading to reduced overall survival. Immunohistochemical and transcriptome analyses revealed that Scrib-null tumors display a pronounced reduction of collagen content and an abundance of cancer-associated fibroblasts (CAF). Mechanistically, IL1α levels were reduced in Scrib-deficient tumors, and Scrib knockdown downregulated IL1α in mouse PDAC organoids (mPDO), which impaired CAF activation. Furthermore, Scrib loss increased YAP activation in mPDOs and established PDAC cell lines, enhancing cell survival. Clinically, SCRIB expression was decreased in human PDAC, and SCRIB mislocalization was associated with poorer patient outcome. These results indicate that SCRIB deficiency enhances cancer cell survival and remodels the tumor microenvironment to accelerate PDAC development and progression, establishing the tumor suppressor function of SCRIB in advanced pancreatic cancer. Significance: SCRIB loss promotes invasive pancreatic cancer development via both cell-autonomous and non-cell-autonomous processes and is associated with poorer outcomes, denoting SCRIB as a tumor suppressor and potential biomarker for the prediction of recurrence.
CRIS-Team Scopus Importer:2024-09-27

Sequential ATR and PARP inhibition overcomes acquired DNA damaging agent resistance in pancreatic ductal adenocarcinoma - Herbert, Katharine J.; Upstill-Goddard, Rosie; Dreyer, Stephan B.; Rebus, Selma; Pilarsky, Christian; Debabrata, Mukhopadhyay; Lord, Christopher J.; Biankin, Andrew V.; Froeling, Fieke E.M.; Chang, David K. (British Journal of Cancer, 2025)
Background: Pancreatic ductal adenocarcinoma (PDAC) remains the most lethal cancer. While DNA damaging agents such as platinum and PARP inhibitors have derived clinical benefits, acquired resistance invariably develops. Hence there is an urgent need for novel therapeutic strategies to overcome acquired resistance. Methods: Clinically relevant resistance in PDAC patient-derived cell lines was achieved by extended exposure to chemotherapy agents. Synergy scoring, clonogenicity, flow cytometry, immunofluorescence, and transcriptomic analysis were used to investigate the efficacy of ATR (ceralasertib) and PARP (olaparib) inhibitors in overcoming acquired resistance. Results: Acquired resistance was associated with transcriptomic shifts in cell cycle checkpoint regulation, metabolic control, DNA damage response (DDR), programmed cell death, and the replication stress response. Combination treatment with ceralasertib, and olaparib was synergistic in all models of acquired resistance. Sequential use of ceralasertib prior to olaparib was highly effective at low dose for DDR proficient models, whereas DDR deficient models responded better with olaparib treatment first. Conclusions: We provide in vitro evidence of a novel therapeutic strategy to overcome acquired resistance to PARP inhibitor and platinum in PDAC, using sequential exposure to ceralasertib and olaparib. A sequential regimen should be investigated clinically to circumvent dose limiting toxicity seen in concurrent combinations.
CRIS-Team Scopus Importer:2025-06-06

Serum concentrations of fibroblast growth factor 2 are increased in HIV type 1-infected patients and inversely related to survival probability. - Ascherl, Gudrun; Sgadari, Cecilia; Bugarini, Roberto; Bogner, Johannes; Schatz, Octavian; Ensoli, Barbara; Stürzl, Michael (Aids Research and Human Retroviruses, 2001)
HIV-1-infected patients develop a generalized vasculopathy that is clinically most evident as Kaposi's sarcoma (KS), a multifocally appearing endothelial cell-derived tumor. Fibroblast growth factor 2 (FGF-2) is a potent autocrine and paracrine mitogen of endothelial cells and has been implicated in the cell proliferation and angiogenesis observed in KS. Here we determined by ELISA the FGF-2 serum concentrations in different clinical groups of HIV-1-infected patients. AIDS-KS patients (n = 53) and HIV-1-infected patients without KS (n = 39) revealed significantly increased FGF-2 serum concentrations (median, 4.5 and 4.6 pg/ml, respectively), as compared with the healthy control group (n = 22; median, 2.2 pg/ml; p < 0.01). FGF-2 concentrations were highest in untreated HIV-1-infected patients (median, 8.6 pg/ml) and were significantly decreased in patients undergoing antiretroviral therapy (AZT-median, 4.5 pg/ml; HAART-median, 2.5 pg/ml; p < 0.01). In addition, FGF-2 serum concentrations above 5.2 pg/ml were associated with a statistically significant higher risk of death in HIV-1-infected patients. Multivariate analysis showed that this effect is independent of CD4 levels, localization of KS (cutaneous or visceral), AIDS-defining opportunistic diseases, and therapy. Circulating FGF-2 may contribute to AIDS-associated vasculopathy and may be a sensitive and easily accessible surrogate marker to determine the survival time of HIV-1-infected patients and the efficacy of antiretroviral therapy.

Setting a benchmark in surgical training robotic training under the European School of Coloproctology, ESCP - Gomez Ruiz, M.; Tou, S.; Matzel, Klaus (Colorectal Disease, 2019)
CRIS-Team WoS Importer:2019-04-16

Short- and long term effects of epidural analgesia on morbidity and mortality of esophageal cancer surgery - Heinrich, Stefan; Janitz, Katrin; Merkel, Susanne; Klein, Peter; Schmidt, Joachim (Langenbecks Archives of Surgery, 2015)
Perioperative regional anesthesia with consecutive reduction of intra- and postoperative systemic opioid requirements in order to improve oncological result after cancer surgery has only been addressed by a few reports. This hypothesis has never been proved in esophageal cancer with a long-term follow-up of more than 5 years. Therefore, we addressed the impact on short- and long-term outcomes of epidural analgesia for esophagus cancer surgery.All available records from patients who underwent esophageal cancer surgery from 1995 to 2005 were retrospectively analyzed. Short- and long-term outcome variables including opioid requirements, duration of ICU-stay, survival, and cancer recurrence were compared between patients with and patients without epidural analgesia for abdomino-right-thoracic esophagectomy.Overall, the analysis included 153 patients, 118 received epidural analgesia; in 35 patients, epidural analgesia was avoided. We found significantly increased postoperative median opioid consumption (10-day intravenous morphine equivalent 187 versus 104 mg) and duration of ICU hospitalization (10.1 vs. 5.9 days, p < 0.05) in the non-epidural group compared with the epidural group. However, there were no significant differences in cancer recurrence (23 % non-epidural group, 27 % epidural group), 1-year mortality (14 vs. 11 %), or 5-year survival (29 vs. 28 %) between the two patient groups.The results of our study underline the well-known clinical benefits of epidural analgesia for esophagus surgery. However, we found no evidence that the further oncological outcome is determined or significantly influenced by the presence or absence of epidural analgesia.
EVALuna2:15179

Short-term outcomes of laparoscopic ventral rectopexy for obstructed defecation in patients with overt pelvic structural abnormalities-a Chinese pilot study - Ye, G. Y.; Wang, Z.; Matzel, K. E.; Cui, Z. (International Journal of Colorectal Disease, 2017)
As laparoscopic ventral rectopexy (LVR) gained increasing popularity in the past decade, studies from non-western area remain rare. The aim of this pilot study is to evaluate the efficacy and safety of LVR for obstructed defecation (OD) in Chinese patients with overt pelvic structural abnormalities.A series of 19 consecutive patients is presented undergoing LVR for OD. All patients showed various forms of pelvic structural abnormalities which were verified by dynamic defecography exam. Data was prospectively recorded and the functional outcomes were evaluated using the Cleveland Clinic Constipation Score (CCCS) and Patients Assessment of Constipation Quality of Life Score (PAC-QoL).Pelvic structural abnormalities of the 19 patients included external rectal prolapse (ER) in 10.5% (2/19), high grade internal rectal prolapse (IR) in 57.8% (11/19), rectocele in 52.6% (10/19), enterocele in 15.7% (3/19), cystocele/vaginal prolapse in 15.7 (3/19), descending perineum (DP) in 63.5% (12/19). 89.4% patients (17/19) showed at least two co-existed abnormalities and 15.7% (3/19) showed multicompartmental abnormalities. The mean follow-up was 9 months (range 1-18). No mesh-related complication was observed. At last available follow-up (LAFU), improvement of OD symptom was observed in 15 (78.9%) patients, the mean scores of CCCS decreased from 17 to 10 (p < 0.05), all four subsets of PAC-QoL scores improved, and three of them (physical discomfort, worries and concerns, satisfaction) showed statistical significance (p < 0.05).Laparoscopic ventral rectopexy appears to be a safe and effective procedure for obstructed defecation in Chinese patients with overt pelvic structural abnormalities in short-term follow-up.
EVALuna2:15314

Should the Benefit of Adjuvant Chemotherapy in Colon Cancer Be Re-Evaluated? - Pahlman, Lars A.; Hohenberger, Werner; Matzel, Klaus; Sugihara, Kenichi; Quirke, Philip; Glimelius, Bengt (Journal of Clinical Oncology, 2016)
EVALuna2:15225

Silenced ZNF154 is associated with longer survival in resectable pancreatic cancer - Wiesmüller, Felix; Kopke, Josephin; Aust, Daniela; Roy, Janine; Dahl, Andreas; Pilarsky, Christian; Grützmann, Robert (International Journal of Molecular Sciences, 2019)
Pancreatic cancer has become the third leading cause of cancer-related death in the Western world despite advances in therapy of other cancerous lesions. Late diagnosis due to a lack of symptoms during early disease allows metastatic spread of the tumor. Most patients are considered incurable because of metastasized disease. On a cellular level, pancreatic cancer proves to be rather resistant to chemotherapy. Hence, early detection and new therapeutic targets might improve outcomes. The detection of DNA promoter hypermethylation has been described as a method to identify putative genes of interest in cancer entities. These genes might serve as either biomarkers or might lead to a better understanding of the molecular mechanisms involved. We checked tumor specimens from 80 patients who had undergone pancreatic resection for promoter hypermethylation of the zinc finger protein ZNF154. Then, we further characterized the effects of ZNF154 on cell viability and gene expression by in vitro experiments. We found a significant association between ZNF154 hypermethylation and better survival in patients with resectable pancreatic cancer. Moreover, we suspect that the cell growth suppressor SLFN5 might be linked to a silenced ZNF154 in pancreatic cancer.
CRIS-Team Scopus Importer:2019-11-12
Keywords: Biomarker; DNA methylation; Methylation-specific PCR; Pancreatic cancer; PDAC; SLFN5; ZNF154

Simultaneous gene silencing of KRAS and anti-apoptotic genes as a multitarget therapy - Werner, Kristin; Lademann, Franziska; Thepkaysone, May-Linn; Jahnke, Beatrix; Aust, Daniela; Kahlert, Christoph; Weitz, Juergen; Grützmann, Robert; Pilarsky, Christian; Pilarsky, Christian; Weber, Georg (Oncotarget, 2016)
Pancreatic cancer is one of the most lethal tumor types worldwide and an effective therapy is still elusive. Targeted therapy focused against a specific alteration is by definition unable to attack broad pathway signaling modification. Tumor heterogeneity will render targeted therapies ineffective based on the regrowth of cancer cell sub-clones. Therefore multimodal therapy strategies, targeting signaling pathways simultaneously should improve treatment.SiRNAs against KRAS and the apoptosis associated genes BCLXL, FLIP, MCL1L, SURVIVIN and XIAP were transfected into human and murine pancreatic cancer cell lines. Induction of apoptosis was measured by Caspase 3/7 activation, subG1 FACS analysis and PARP cleavage. The therapeutic approach was tested in a subcutaneous allograft model with a murine cancer cell line.By using siRNAs as a systematic approach to remodel signal transduction in pancreatic cancer the results showed increasing inhibition of proliferation and apoptosis induction in vitro and in vivo. Thus, siRNAs are suitable to model multimodal therapy against signaling pathways in pancreatic cancer. Improvements in in vivo delivery of siRNAs against a multitude of targets might therefore be a potential therapeutic approach.
EVALuna2:15258

SMYD2 targets RIPK1 and restricts TNF-induced apoptosis and necroptosis to support colon tumor growth - Yu, Yidong; Thonn, Veronika; Patankar, Jay; Thoma, Oana-Maria; Waldner, Maximilian; Zielinska, Marta; Bao, Lili; Gonzalez Acera, Miguel; Wallmueller, Stefan; Engel, Felix; Stürzl, Michael; Neurath, Markus; et al. (Cell Death & Disease, 2022)
SMYD2 is a histone methyltransferase, which methylates both histone H3K4 as well as a number of non-histone proteins. Dysregulation of SMYD2 has been associated with several diseases including cancer. In the present study, we investigated whether and how SMYD2 might contribute to colorectal cancer. Increased expression levels of SMYD2 were detected in human and murine colon tumor tissues compared to tumor-free tissues. SMYD2 deficiency in colonic tumor cells strongly decreased tumor growth in two independent experimental cancer models. On a molecular level, SMYD2 deficiency sensitized colonic tumor cells to TNF-induced apoptosis and necroptosis without affecting cell proliferation. Moreover, we found that SMYD2 targeted RIPK1 and inhibited the phosphorylation of RIPK1. Finally, in a translational approach, pharmacological inhibition of SMYD2 attenuated colonic tumor growth. Collectively, our data show that SMYD2 is crucial for colon tumor growth and inhibits TNF-induced apoptosis and necroptosis.
CRIS-Team WoS Importer:2022-01-21

Soluble intercellular adhesion molecule-1 is a prognostic marker in colorectal carcinoma - Schellerer, Vera; Langheinrich, Melanie C.; Zver, Veronika; Grützmann, Robert; Stürzl, Michael; Gefeller, Olaf; Naschberger, Elisabeth; Merkel, Susanne (International Journal of Colorectal Disease, 2019)
PurposeSerological tumor markers are routinely used to monitor tumor onset and progression. In colorectal carcinoma (CRC), the carcinoembryonic antigen (CEA) is roughly elevated in 50% of patients at initial diagnosis. Soluble ICAM-1 (sICAM-1) is elevated in different cancers. The aim of this study was to evaluate the prognostic relevance of sICAM-1 combined with CEA in patients with CRC.MethodsIn blood samples of 297 CRC patients, sICAM-1 was determined by ELISA and CEA by microparticle enzyme immunoassay the day before oncologic resection. Separation in patients with sICAM-1(high) and sICAM-1(low) was performed by minimum p value approach; separation in CEA normal and elevated was performed according to the established diagnostic cutoff. Clinical data were obtained from the prospective collected data from the Erlangen Registry for Colorectal Carcinomas.ResultsCancer-related 5-year survival rate of patients with sICAM-1(low) (<290ng/ml, n=208) was significantly increased (83.4%) as compared to that of patients with sICAM-1(high) (290ng/ml, n=89) (66.2%; p<0.001). Patients with normal CEA concentrations (n=199; 90.8%) showed a significantly (p<0.001) improved cancer-related 5-year survival rate compared to patients with elevated CEA concentrations (n=98; 52.1%). Moreover, high sICAM-1 was an independent risk factor (hazard ratio 1.6) in multivariate analysis. Of note, increased sICAM-1 levels, either within normal or within elevated CEA, allowed to identify high-risk subgroups, both for overall (p<0.001) and cancer-related survival (p<0.001).ConclusionApplication of a novel risk score combining CEA/sICAM-1 serum concentrations allows the identification of high-risk groups for poor survival in CRC patients.
CRIS-Team WoS Importer:2019-02-21

SPARCL1 is an angiocrine inhibitor of tumorigenesis in colorectal carcinoma - Tenkerian, Clara; Regensburger, Daniela; Langer, Victoria; Klingler, Anika; Borau, Anne; Sticht, Heinrich; Ramming, Andreas; Wohlfahrt, Thomas; Schmid, Benjamin; Meniel, Valerie; Grützmann, Robert; Britzen-Laurent, Nathalie; et al. (CANCER RESEARCH, 2019)
CRIS-Team WoS Importer:2019-10-15

Spatial Single Cell Profiling Using Imaging Mass Cytometry: Inflammatory Versus Penetrating Crohn's Disease - Lehmann, Malte; Weixler, Benjamin; Elezkurtaj, Sefer; Loddenkemper, Christopher; Atreya, Imke; Atreya, Raja; Bacher, Petra; Becker, Christoph; Bojarski, Christian; Britzen-Laurent, Nathalie; Bosch-Voskens, Caroline; Chang, Hyun Dong; et al. (Journal of Crohns & Colitis, 2024)
Background and Aims: Fistula formation is a major complication in Crohn's disease [CD] and the role of the immune cell compartment remains to be elucidated. Thus, we compared the immune cell compartment of CD fistula to inflammatory CD colitis using imaging mass cytometry [IMC] and immunofluorescence. Methods: A 36-marker panel including structural, functional, and lineage markers for use in IMC was established. This panel was applied to analyse paraffin-embedded CD fistula tract [n = 11], CD colitis [n = 10], and colon samples from non-inflamed controls [n = 12]. Computational methods for cell segmentation, dimensionality reduction, and cell type clustering were used to define cell populations for cell frequency, marker distribution, and spatial neighbourhood analysis. Multiplex immunofluorescence was used for higher resolution spatial analysis. Results: Analysis of cell frequencies in CD fistulas compared to CD colitis and control colonic samples revealed a significant increase in neutrophils, effector cytotoxic T cells, and inflammatory macrophages in CD fistula samples, whereas regulatory T cells were decreased. Neutrophils in CD fistula expressed significantly more matrix metalloproteinase 9 [MMP9], correlating with extracellular matrix remodelling. Neighbourhood analysis revealed a strong association between MMP9+ neutrophils and effector cytotoxic T cells in both CD fistulas and colitis. Conclusions: This study presents the first highly multiplexed single cell analysis of the immune cell compartment of CD fistulas and their spatial context. It links immune cell dynamics, particularly MMP9+ neutrophils, to extracellular matrix remodelling in CD fistulas, offering insights into the complex network of cellular interactions and potential therapeutic targets for CD complications.
CRIS-Team Scopus Importer:2024-09-13
Keywords: fistula; imaging mass cytometry; Penetrating Crohn's disease

Species-, organ- and cell-type-dependent expression of SPARCL1 in human and mouse tissues. - Klingler, Anika; Regensburger, Daniela; Tenkerian, Clara; Britzen-Laurent, Nathalie; Hartmann, Arndt; Stürzl, Michael; Naschberger, Elisabeth (PLoS ONE, 2020)
SPARCL1 is a matricellular protein with anti-adhesive, anti-proliferative and anti-tumorigenic functions and is frequently downregulated in tumors such as colorectal carcinoma or non-small cell lung cancer. Studies have identified SPARCL1 as an angiocrine tumor suppressor secreted by tumor vessel endothelial cells, thereby exerting inhibitory activity on angiogenesis and tumor growth, in colorectal carcinoma. It is unknown whether SPARCL1 may exert these homeostatic functions in all organs and in other species. Therefore, SPARCL1 expression was comparatively analysed between humans and mice in a systematic manner. Murine Sparcl1 (mSparcl1) is most strongly expressed in the lung; expressed at an intermediate level in most organs, including the large intestine; and absent in the liver. In human tissues, SPARCL1 (hSPARCL1) was detected in all organs, with the strongest expression in the stomach, large intestine and lung, mostly consistent with the murine expression pattern. A striking difference between human and murine tissues was the absence of mSparcl1 expression in murine livers, while human livers showed moderate expression. Furthermore, mSparcl1 was predominantly associated with mural cells, whereas hSPARCL1 was detected in both mural and endothelial cells. Human SPARCL1 expression was downregulated in different carcinomas, including lung and colon cancers. In conclusion, this study revealed species-, organ- and cell-type-dependent expression of SPARCL1, suggesting that its function may not be similar between humans and mice.

Stimulation of the soluble guanylate cyclase (sGC) inhibits fibrosis by blocking non-canonical TGF? signalling - Beyer, Christian; Zenzmaier, Christoph; Palumbo-Zerr, Katrin; Mancuso, Rossella; Distler, Alfiya; Dees, Clara; Zerr, Pawel; Huang, Jingang; Maier, Christiane; Pachowsky, Milena; Friebe, Andreas; Sandner, Peter; et al. (Annals of the Rheumatic Diseases, 2015)
We have previously described the antifibrotic role of the soluble guanylate cyclase (sGC). The mode of action, however, remained elusive. In the present study, we describe a novel link between sGC signalling and transforming growth factor ? (TGF?) signalling that mediates the antifibrotic effects of the sGC.Human fibroblasts and murine sGC knockout fibroblasts were treated with the sGC stimulator BAY 41-2272 or the stable cyclic guanosine monophosphate (cGMP) analogue 8-Bromo-cGMP and stimulated with TGF?. sGC knockout fibroblasts were isolated from sGCI(fl/fl) mice, and recombination was induced by Cre-adenovirus. In vivo, we studied the antifibrotic effects of BAY 41-2272 in mice overexpressing a constitutively active TGF-?1 receptor.sGC stimulation inhibited TGF?-dependent fibroblast activation and collagen release. sGC knockout fibroblasts confirmed that the sGC is essential for the antifibrotic effects of BAY 41-2272. Furthermore, 8-Bromo-cGMP reduced TGF?-dependent collagen release. While nuclear p-SMAD2 and 3 levels, SMAD reporter activity and transcription of classical TGF? target genes remained unchanged, sGC stimulation blocked the phosphorylation of ERK. In vivo, sGC stimulation inhibited TGF?-driven dermal fibrosis but did not change p-SMAD2 and 3 levels and TGF? target gene expression, confirming that non-canonical TGF? pathways mediate the antifibrotic sGC activity.We elucidated the antifibrotic mode of action of the sGC that increases cGMP levels, blocks non-canonical TGF? signalling and inhibits experimental fibrosis. Since sGC stimulators have shown excellent efficacy and tolerability in phase 3 clinical trials for pulmonary arterial hypertension, they may be further developed for the simultaneous treatment of fibrosis and vascular disease in systemic sclerosis.
EVALuna2:12978

Strangulation and necrosis of right hemicolon as an extremely rare complication of Spigelian hernia - Velimezis, Georgios; Vassos, Nikolaos; Kapogiannatos, Georgios; Koronakis, Dimitrios; Salpiggidis, Christos; Perrakis, Evangelos; Perrakis, Aristotelis (Archives of Medical Science, 2016)
EVALuna2:15264

Structural proteins of Kaposi's sarcoma-associated herpesvirus antagonize p53-mediated apoptosis - Chudasama, Priya; Konrad, A.; Jochmann, R.; Lausen, Berthold; Holz, Patrick; Naschberger, Elisabeth; Neipel, Frank; Britzen-Laurent, Nathalie; Stürzl, Michael (Oncogene, 2015)
The tumor suppressor p53 is a central regulatory molecule of apoptosis and is commonly mutated in tumors. Kaposi's sarcoma-associated herpesvirus (KSHV)-related malignancies express wild-type p53. Accordingly, KSHV encodes proteins that counteract the cell death-inducing effects of p53. Here, the effects of all KSHV genes on the p53 signaling pathway were systematically analyzed using the reversely transfected cell microarray technology. With this approach we detected eight KSHV-encoded genes with potent p53 inhibiting activity in addition to the previously described inhibitory effects of KSHV genes ORF50, K10 and K10.5. Interestingly, the three most potent newly identified inhibitors were KSHV structural proteins, namely ORF22 (glycoprotein H), ORF25 (major capsid protein) and ORF64 (tegument protein). Validation of these results with a classical transfection approach showed that these proteins inhibited p53 signaling in a dose-dependent manner and that this effect could be reversed by small interfering RNA-mediated knockdown of the respective viral gene. All three genes inhibited p53-mediated apoptosis in response to Nutlin-3 treatment in non-infected and KSHV-infected cells. Addressing putative mechanisms, we could show that these proteins could also inhibit the transactivation of the promoters of apoptotic mediators of p53 such as BAX and PIG3. Altogether, we demonstrate for the first time that structural proteins of KSHV can counteract p53-induced apoptosis. These proteins are expressed in the late lytic phase of the viral life cycle and are incorporated into the KSHV virion. Accordingly, these genes may inhibit cell death in the productive and in the early entrance phase of KSHV infection.
EVALuna2:8221

Study protocol for an International Prospective Observational Cohort Study for Optimal Bowel Resection Extent and Central Radicality for Colon Cancer (T-REX study) - Shiozawa, Manabu; Ueno, Hideki; Shiomi, Akio; Kim, Nan Kyu; Kim, Jin Cheon; Tsarkov, Petr; Grützmann, Robert; Dulskas, Audrius; Liang, Jin Tung; Samalavičius, Narimantas; West, Nick; Sugihara, Kenichi (Japanese Journal of Clinical Oncology, 2021)
This is a prospective observational cohort study aiming to include 4000 patients with stages I to III colon cancer treated at 35 specialist institutions in Japan, South Korea, Germany, Russia, Lithuania and Taiwan. The anatomical distribution of lymph nodes and feeding arteries are investigated using surgical specimens according to pre-specified categorizing methods using intraoperative anatomical markings. Primary analyses are performed to identify the general principles of metastatic lymph node distribution in terms of its relation to the location of the primary tumor and feeding arteries. Secondary analyses will be used to estimate prognostic outcomes according to bowel resection length and central radicality and will be used to evaluate the quality of resected surgical specimens. Through in-depth lymph node mapping, standardized criteria for the definite area of 'regional' lymph node resection in routine surgical procedures can be identified, which is expected to contribute to international standardization in colon cancer surgery (ClinicalTrials.gov NCT02938481).
CRIS-Team Scopus Importer:2021-01-15
Keywords: bowel resection margin; complete mesocolic excision; D3 dissection; lymph node mapping; lymphadenectomy

Successful Multidisciplinary Treatment with Secondary Metastatic Liver Resection after Downsizing by Palliative Second-Line Treatment of Colorectal Cancer: A Curative Option - Wein, Axel; Görtz, Rüdiger; Wolff, Kerstin; Ostermeier, Nicola; Busse, Daniel; Kremer, Andreas; Koch, Franz; Hagel, Alexander; Farnbacher, Michael; Kammerer, Ferdinand J.; Neurath, Markus; Grützmann, Robert; et al. (Case Reports in Oncology, 2016)
The prognostic outcome following progression after palliative first-line treatment for patients suffering from metastatic colorectal adenocarcinoma is generally poor. Long-term relapse-free survival with palliative second-line treatment may be achieved in only a limited number of individual cases.A 37-year-old patient presented with bilobar liver metastases of colon cancer confirmed by histology with wild-type K-RAS (exon 2). Due to progressive disease after eight cycles of first-line therapy with FOLFIRI plus cetuximab, second-line chemotherapy with modified FOLFOX4 (mFOLFOX4) plus bevacizumab was initiated. During four cycles of mFOLFOX4 plus bevacizumab (2 months), no higher-grade toxicity occurred. Liver MRI with contrast medium revealed downsizing of the segment II/III metastases, as well as regressive, small, faint, hardly definable lesions in segments VI and IVb. The interdisciplinary tumor board of the University of Erlangen thus decided to perform resection of the liver metastases. Segments II and III were resected, and the liver metastases in segments IVa and VI were excised (R0). Histopathology confirmed three of the R0-resected metastases to be completely necrotic, with residual scarring. As perioperative therapy, four additional cycles of mFOLFOX4 plus bevacizumab were administered postoperatively. No higher-grade toxicity was observed. Three years after the initial diagnosis, the patient is relapse free, professionally fully reintegrated, and has an excellent performance status.Patients suffering from metastatic colorectal cancer may benefit from multidisciplinary treatment with secondary metastatic liver resection after downsizing by palliative second-line treatment. In individual cases, patients may even have a curative treatment option, provided that close interdisciplinary collaboration exists.
EVALuna2:2220

Surface anatomical landmarks for the location of posterior sacral foramina in sacral nerve stimulation - Povo, A.; Arantes, M.; Matzel, K. E.; Barbosa, Joselina; Ferreira, M. A.; Pais, D.; Rodriguez-Baeza, A. (Techniques in Coloproctology, 2016)
Sacral nerve stimulation is a common treatment for various pelvic floor disorders. It consists of the percutaneous introduction of electrodes through the posterior sacral foramina for therapeutic stimulation of the target sacral spinal nerve. The aim of our study was to determine the surface anatomical landmarks of the sacrum to facilitate identification of the posterior sacral foramina.This study was conducted on 20 human cadavers. The cadavers were placed in a prone position, and all the soft tissues of the sacral region were removed to allow exposure of the osseous structures. Different measurements were taken in relation to the posterior sacral foramina, the posterior superior iliac spine (PSIS) and the median sacral crest (MSC). A median coefficient of variation (CV) was determined.The diameter of the second sacral foramen showed the greatest variability. The distances between each individual foramen and the MSC had an acceptable variability (CV < 20%). In contrast, the distance between foramina had a high variability. The distance between PSIS and the second posterior sacral foramen was also found to have an acceptable variability (CV < 20%). However, the angle formed by an horizontal line between PSIS and a line between PSIS and S2 foramina had high variability.We found that the distance between sacral foramina and MSC is relatively constant while the distance between foramina and the relations between foramina and PSIS is highly variable. Detailed knowledge of the anatomy may facilitate electrode placement and is complementary to the regular use of fluoroscopy.
EVALuna2:15262

Surgical anatomy of the rectum: a series of video tutorials – a video vignette - Wedel, Thilo; Gómez Ruiz, Marcos; Tou, Samson; Stelzner, Sigmar; Matzel, Klaus (Colorectal Disease, 2022)
CRIS-Team Scopus Importer:2022-12-23

Surgical and oncological outcome after extended lymph node dissection for carcinoma of the stomach and the esophagogastric junction: a retrospective analysis from an experienced single center - Raptis, Dimitrios; Maak, Matthias; Krautz, Christian; Merkel, Susanne; Brunner, Maximilian; Agaimy, Abbas; Hartmann, Arndt; Semrau, Sabine; Ott, Oliver; Fietkau, Rainer; Siebler, Jürgen; Grützmann, Robert; et al. (Archives of Medical Science, 2024)
Introduction: Gastric cancer remains the fourth leading cause of cancer-related death in Europe, while the proportion of adenocarcinomas of the esophagogastric junction has risen by more than one third over recent years. In 2018, 14,700 new cases of gastric cancer were estimated in Germany, while the 5-year relative survival rate is reported to be 33% for women and 30% for men; in the USA almost the same rate was reported, with 31% 5-year survival. Material and methods: Between 2001 and 2014, 590 patients with a diagnosis of gastric cancer underwent surgery in our institution, including 120 Siewert type II/III carcinomas of the esophagogastric junction. All patients underwent distal resection of the stomach, gastrectomy or total gastrectomy combined with transhiatal distal esophageal resection. All operations included D2-D3 lymph node dissection (LND). Data were recorded by the cancer registry of the department of surgery and analyzed retrospectively. Results: The patients were classified according to the TNM (UICC 2010) and Lauren classification. 29% of the patients underwent primary surgery and 31% received neoadjuvant therapy. The median number of harvested lymph nodes was 33 for patients diagnosed with gastric cancer, and 29 for esophagogastric adenocarcinomas, respectively. The anastomotic leak rate was 3%. In this study, the 5-year overall survival rate was 51% concerning gastric carcinomas, 44% for Siewert type II and 47% for Siewert III cancers of the esophagogastric junction. Conclusions: Increased survival with low complication rates were achieved after individualized and multimodal treatment concepts combined with consistently applied extended lymphadenectomy.
CRIS-Team Scopus Importer:2024-04-19
Keywords: D3 dissection; gastric cancer; Siewert II/III

Survival analysis in rectal carcinoma after neoadjuvant chemoradiation: various methods with different results - Merkel, Susanne; Weber, Klaus; Göhl, Jonas; Agaimy, Abbas; Fietkau, Rainer; Hohenberger, Werner; Grützmann, Robert; Hermanek, Peter (International Journal of Colorectal Disease, 2017)
Survival is an important indicator of outcome quality in rectal carcinoma. The 5-year survival rate is the typical outcome measurement. In patients with neoadjuvant chemoradiation followed by curative surgery, 7 years of follow-up is recommended. Different methods of survival analysis lead to different results. Here, we compared four different methods.The data of 439 patients with rectal carcinoma treated with neoadjuvant chemoradiation followed by curative total mesorectal excision (TME) surgery between 1995 and 2010 were analysed. After stratifying by stage, relative survival (RS), cancer-related survival (CRS), overall survival (OS) and disease-free survival (DFS) were compared. In particular, the 3-year disease-free survival rate was compared to the 5- and 7-year overall survival rates.In the total cohort, the 5-year survival rates ranged from 90% (RS), over 84% (CRS) and 83% (OS) to 72% (DFS). Depending on the stage of disease, the differences between the 5-year survival rates varied between 10 and 32 percentage points. The differences were lowest in UICC stage y0 and highest in UICC stage yIV. The 3-year DFS-rate was always lower (worse) than the 5-year OS rate and higher (better) than the 7-year OS rate, with the exception of stage yIV.Comparisons of survival are only meaningful if the same methods are applied. The 3-year rate of DFS was always worse than the rate of 5-year OS. Therefore, the 3-year rate of DFS appears to be a useful surrogate indicator in rectal carcinoma treatment studies.
EVALuna2:6896

Survival-associated factors and a prognostic nomogram in resected pancreatic cancer: A large international population-based cohort study - Huang, L.; Balavarca, Y.; Van Der Geest, L.; Lemmens, V.; Van Eycken, L.; De Schutter, H.; Johannesen, T. B.; Zadnik, V.; Primic-Zakelj, M.; Magi, M.; Grützmann, Robert; Besselink, M. G.; et al. (ANNALS OF ONCOLOGY, 2018)
CRIS-Team WoS Importer:2019-03-08

Survival outcome and prognostic factors after pancreatoduodenectomy for distal bile duct carcinoma: a retrospective multicenter study - Petrova, Ekaterina; Rueckert, Felix; Zach, Sebastian; Shen, Yinfeng; Weitz, Juergen; Grützmann, Robert; Wittel, Uwe A.; Makowiec, Frank; Hopt, Ulrich T.; Bronsert, Peter; Kuehn, Florian; Rau, Bettina M.; et al. (Langenbecks Archives of Surgery, 2017)
Pancreatoduodenectomy is the most common operative procedure performed for distal bile duct carcinoma. Data on outcome after surgery for this rare malignancy is scarce, especially from western countries. The purpose of this study is to explore the prognostic factors and outcome after pancreatoduodenectomy for distal bile duct carcinoma.Patients receiving pancreatoduodenectomy for distal bile duct carcinoma were identified from institutional databases of five German and one Russian academic centers for pancreatic surgery. Univariable and multivariable general linear model, Kaplan-Meier method, and Cox regression were used to identify prognostic factors for postoperative mortality and overall survival.N = 228 patients operated from 1994 to 2015 were included. Reoperation (OR 5.38, 95%CI 1.51-19.22, p = 0.010), grade B/C postpancreatectomy hemorrhage (OR 3.73, 95%CI 1.13-12.35, p = 0.031), grade B/C postoperative pancreatic fistula (OR 4.29, 95%CI 1.25-14.72, p = 0.038), and advanced age (OR 4.00, 95%CI 1.12-14.03, p = 0.033) were independent risk factors for in-hospital mortality in multivariable analysis. Median survival was 29 months, 5-year survival 27%. Positive resection margin (HR 2.07, 95%CI 1.29-3.33, p = 0.003), high tumor grade (HR 1.71, 95%CI 1.13-2.58, p = 0.010), lymph node (HR 1.68, 95%CI 1.13-2.51, p = 0.011), and distant metastases (HR 2.70, 95%CI 1.21-5.58, p = 0.014), as well as severe non-fatal postoperative complications (HR 1.64, 95%CI 1.04-2.58, p = 0.033) were independent negative prognostic factors for survival in multivariable analysis.Distant metastases and positive resection margin are the strongest negative prognostic factors for survival after pancreatoduodenectomy for distal bile duct carcinoma; thus, surgery with curative intent is only warranted in patients with local disease, where R0 resection is feasible.
EVALuna2:15301

Survival outcome following surgical versus non-surgical treatment of colorectal lung metastasis—a retrospective cohort study - Denz, Axel; Hahn, Veronika; Weber, Klaus; Weber, Georg; Grützmann, Robert; Krautz, Christian; Brunner, Maximilian (Langenbecks Archives of Surgery, 2024)
Purpose: The optimal management of colorectal lung metastases (CRLM) is still controversial. The aim of this study was to compare surgical and non-surgical treatment for CRLM regarding the prognostic outcome. Methods: This retrospective single-center cohort study included 418 patients, who were treated from January 2000 to December 2018 at a German University Hospital due to their colorectal carcinoma and had synchronous or metachronous lung metastases. Patients were stratified according the treatment of the CRLM into two groups: surgical resection of CRLM versus no surgical resection of CRLM. The survival from the time of diagnosis of lung metastasis was compared between the groups. Results: Two- and 5-year overall survival (OS) from the time of diagnosis of lung metastasis was 78.2% and 54.6%, respectively, in our cohort. Patients undergoing pulmonary metastasectomy showed a significantly better 2- and 5-year survival compared to patients with non-surgical treatment (2-year OS: 98.1% vs. 67.9%; 5-year OS: 81.2% vs. 28.8%; p < 0.001). Multivariate Cox regression revealed the surgical treatment (HR 4.51 (95% CI = 2.33–8.75, p < 0.001) and the absence of other metastases (HR 1.79 (95% CI = 1.05–3.04), p = 0.032) as independent prognostic factors in patients with CRLM. Conclusion: Our data suggest that patients with CRLM, who qualify for surgery, benefit from surgical treatment. Randomized controlled trials are needed to confirm our findings. Clinical trial registry number: The work has been retrospectively registrated at the German Clinical Trial Registry (DRKS00032938).
CRIS-Team Scopus Importer:2024-04-26
Keywords: Colorectal carcinoma; Lung metastases; Non-surgical treatment; Outcome; Overall survival; Surgical resection

Systems biology of the IMIDIA biobank from organ donors and pancreatectomised patients defines a novel transcriptomic signature of islets from individuals with type 2 diabetes - Solimena, Michele; Schulte, Anke M.; Marselli, Lorella; Ehehalt, Florian; Richter, Daniela; Kleeberg, Manuela; Mziaut, Hassan; Knoch, Klaus Peter; Parnis, Julia; Bugliani, Marco; Siddiq, Afshan; Jörns, Anne; et al. (Diabetologia, 2017)
Pancreatic islet beta cell failure causes type 2 diabetes in humans. To identify transcriptomic changes in type 2 diabetic islets, the Innovative Medicines Initiative for Diabetes: Improving beta-cell function and identification of diagnostic biomarkers for treatment monitoring in Diabetes (IMIDIA) consortium ( www.imidia.org ) established a comprehensive, unique multicentre biobank of human islets and pancreas tissues from organ donors and metabolically phenotyped pancreatectomised patients (PPP).Affymetrix microarrays were used to assess the islet transcriptome of islets isolated either by enzymatic digestion from 103 organ donors (OD), including 84 non-diabetic and 19 type 2 diabetic individuals, or by laser capture microdissection (LCM) from surgical specimens of 103 PPP, including 32 non-diabetic, 36 with type 2 diabetes, 15 with impaired glucose tolerance (IGT) and 20 with recent-onset diabetes (<1 year), conceivably secondary to the pancreatic disorder leading to surgery (type 3c diabetes). Bioinformatics tools were used to (1) compare the islet transcriptome of type 2 diabetic vs non-diabetic OD and PPP as well as vs IGT and type 3c diabetes within the PPP group; and (2) identify transcription factors driving gene co-expression modules correlated with insulin secretion ex vivo and glucose tolerance in vivo. Selected genes of interest were validated for their expression and function in beta cells.Comparative transcriptomic analysis identified 19 genes differentially expressed (false discovery rate <=0.05, fold change >=1.5) in type 2 diabetic vs non-diabetic islets from OD and PPP. Nine out of these 19 dysregulated genes were not previously reported to be dysregulated in type 2 diabetic islets. Signature genes included TMEM37, which inhibited Ca2+-influx and insulin secretion in beta cells, and ARG2 and PPP1R1A, which promoted insulin secretion. Systems biology approaches identified HNF1A, PDX1 and REST as drivers of gene co-expression modules correlated with impaired insulin secretion or glucose tolerance, and 14 out of 19 differentially expressed type 2 diabetic islet signature genes were enriched in these modules. None of these signature genes was significantly dysregulated in islets of PPP with impaired glucose tolerance or type 3c diabetes.These studies enabled the stringent definition of a novel transcriptomic signature of type 2 diabetic islets, regardless of islet source and isolation procedure. Lack of this signature in islets from PPP with IGT or type 3c diabetes indicates differences possibly due to peculiarities of these hyperglycaemic conditions and/or a role for duration and severity of hyperglycaemia. Alternatively, these transcriptomic changes capture, but may not precede, beta cell failure.
EVALuna2:15297

T17b murine embryonal endothelial progenitor cells can be induced towards both proliferation and differentiation in a fibrin matrix - Bleiziffer, Oliver; Horch, Raymund E.; Hammon, Matthias; Arkudas, Andreas; Naschberger, Elisabeth; Rath, Subha; Pryymachuk, Galyna; Beier, Justus; Hatzopoulos, Antonis K.; Stürzl, Michael; Kneser, Ulrich (Journal of Cellular and Molecular Medicine, 2009)
Endothelial progenitor cells (EPC) may enhance blood vessel formation in a variety of clinical settings such as ischaemia and tumour angiogenesis as well as in tissue-engineered matrices. In the present study, we cultured a murine endothelial progenitor cell line, T17b, in vitro in cell culture as well as in an FDA-approved fibrin matrix and investigated cell proliferation, differentiation and secretion patterns of the angiogenic growth factor VEGF under hypoxia and differentiation. We show that T17b EPC remain viable for at least 8 days in the fibrin matrix where they proliferate and form clusters including lumen-like structures. Proliferation in fibrin clots overlayed with basal medium (BM) was confirmed morphologically and immunohistochemically by positive Ki67 staining, indicating mitotic activity. Significant cell proliferation and Ki-67 expression were absent when cells were incubated with dibutyryl-cAMP and retinoic acid (RA). Incubation with dibutyryl-cAMP and RA stimulated the expression of the EPC differentiation markers von Willebrand Factor (vWF) and VEGF receptor 2 (VEGFR-2), indicating successful differentiation in the fibrin clot. EPC differentiation induced by dibutyryl-cAMP and RA was confirmed in 2-D chamber slide cultures by positive vWF immunostaining, which was absent in BM controls. EPC chamber slides also displayed positive vWF staining when exposed to hypoxia under BM conditions, indicating EPC activation and differentiation could also be induced by hypoxia. Taken together, T17b EPC secrete increased levels of VEGF when submitted to either hypoxia or differentiation and can be differentiated into mature endothelial cells not only in cell and matrigel cultures but also in a fibrin matrix that is FDA approved for clinical application. © 2009 Foundation for Cellular and Molecular Medicine/Blackwell Publishing Ltd.
Created from Fastlane, Scopus look-up
Keywords: Angiogenesis; Embryonal endothelial progenitor cells; Tissue engineering

Tailoring the Use of Central Pancreatectomy Through Prediction Models for Major Morbidity and Postoperative Diabetes: International Retrospective Multicenter Study - Van Bodegraven, Eduard Antonie; Lof, Sanne; Jones, Leia; Aussilhou, Béatrice; Yong, Gao; Jishu, Wei; Klotz, Rosa; Rocha-Castellanos, Dario Missael; Matsumato, Ippei; De Ponthaud, Charles; Tanaka, Kimitaka; Biesel, Esther; et al. (Annals of Surgery, 2024)
Objective: To develop a prediction model for major morbidity and endocrine dysfunction after central pancreatectomy (CP) which could help in tailoring the use of this procedure. Background: CP is a parenchyma-sparing alternative to distal pancreatectomy for symptomatic benign and premalignant tumors in the body and neck of the pancreas CP lowers the risk of new-onset diabetes and exocrine pancreatic insufficiency compared with distal pancreatectomy but it is thought to increase the risk of short-term complications, including postoperative pancreatic fistula (POPF). Methods: International multicenter retrospective cohort study including patients from 51 centers in 19 countries (2010-2021). The primary endpoint was major morbidity. Secondary endpoints included POPF grade B/C, endocrine dysfunction, and the use of pancreatic enzymes. Two risk models were designed for major morbidity and endocrine dysfunction utilizing multivariable logistic regression and internal and external validation. Results: A total of 838 patients after CP were included [301 (36%) minimally invasive] and major morbidity occurred in 248 (30%) patients, POPF B/C in 365 (44%), and 30-day mortality in 4 (1%). Endocrine dysfunction in 91 patients (11%) and use of pancreatic enzymes in 108 (12%). The risk model for major morbidity included male sex, age, Body Mass Index, and American Society of Anesthesiologists score ≥3. The model performed acceptably with an area under the curve of 0.72 (CI: 0.68-0.76). The risk model for endocrine dysfunction included higher Body Mass Index and male sex and performed well [area under the curve: 0.83 (CI: 0.77-0.89)]. Conclusions: The proposed risk models help in tailoring the use of CP in patients with symptomatic benign and premalignant lesions in the body and neck of the pancreas.
CRIS-Team Scopus Importer:2024-11-22
Keywords: central pancreatectomy; complications; patient selection; risk model

Targeting DNA Damage Response and Replication Stress in Pancreatic Cancer - Dreyer, Stephan B.; Upstill-Goddard, Rosie; Paulus-Hock, Viola; Paris, Clara; Lampraki, Eirini Maria; Dray, Eloise; Serrels, Bryan; Caligiuri, Giuseppina; Rebus, Selma; Plenker, Dennis; Galluzzo, Zachary; Brunton, Holly; et al. (Gastroenterology, 2021)
Background & Aims: Continuing recalcitrance to therapy cements pancreatic cancer (PC) as the most lethal malignancy, which is set to become the second leading cause of cancer death in our society. The study aim was to investigate the association between DNA damage response (DDR), replication stress, and novel therapeutic response in PC to develop a biomarker-driven therapeutic strategy targeting DDR and replication stress in PC. Methods: We interrogated the transcriptome, genome, proteome, and functional characteristics of 61 novel PC patient–derived cell lines to define novel therapeutic strategies targeting DDR and replication stress. Validation was done in patient-derived xenografts and human PC organoids. Results: Patient-derived cell lines faithfully recapitulate the epithelial component of pancreatic tumors, including previously described molecular subtypes. Biomarkers of DDR deficiency, including a novel signature of homologous recombination deficiency, cosegregates with response to platinum (P <.001) and PARP inhibitor therapy (P <.001) in vitro and in vivo. We generated a novel signature of replication stress that predicts response to ATR (P <.018) and WEE1 inhibitor (P <.029) treatment in both cell lines and human PC organoids. Replication stress was enriched in the squamous subtype of PC (P <.001) but was not associated with DDR deficiency. Conclusions: Replication stress and DDR deficiency are independent of each other, creating opportunities for therapy in DDR-proficient PC and after platinum therapy.
CRIS-Team Scopus Importer:2020-12-25
Keywords: DNA Damage Response; Pancreatic Cancer; Personalized Medicine; Replication Stress

Technical considerations for isolated limb perfusion: A consensus paper - Hayes, Andrew J.; Coker, David J.; Been, Lukas; Boecxstaens, Veerle WSM; Bonvalot, Sylvie; De Cian, Franco; de la Cruz-Merino, Luis; Duarte, Carlos; Eggermont, Alexander; Farricha, Victor; Fiore, Marco; Grünhagen, Dirk; et al. (Ejso, 2024)
Background: Isolated limb perfusion (ILP) is a well-established surgical procedure for the administration of high dose chemotherapy to a limb for the treatment of advanced extremity malignancy. Although the technique of ILP was first described over 60 years ago, ILP is utilised in relatively few specialist centres, co-located with tertiary or quaternary cancer centres. The combination of high dose cytotoxic chemotherapy and the cytokine tumour necrosis factor alpha (TNFα), mandates leakage monitoring to prevent potentially serious systemic toxicity. Since the procedure is performed at relatively few specialist centres, an ILP working group was formed with the aim of producing technical consensus guidelines for the procedure to streamline practice and to provide guidance for new centres commencing the technique. Methods: Between October 2021 and October 2023 a series of face to face online and hybrid meetings were held in which a modified Delphi process was used to develop a unified consensus document. After each meeting the document was modified and recirculated and then rediscussed at subsequent meeting until a greater than 90% consensus was achieved in all recommendations. Results: The completed consensus document comprised 23 topics in which greater than 90% consensus was achieved, with 83% of recommendations having 100% consensus across all members of the working group. The consensus recommendations covered all areas of the surgical procedure including pre-operative assessment, drug dosing and administration, perfusion parameters, hyperthermia, leakage monitoring and theatre logistics, practical surgical strategies and also post-operative care, response evaluation and staff training. Conclusion: We present the first joint expert-based consensus statement with respect to the technical aspects of ILP that can serve as a reference point for both existing and new centres in providing ILP.
CRIS-Team Scopus Importer:2024-04-05

Tetramerization of human guanylate-binding protein 1 is mediated by coiled-coil formation of the C-terminal α-helices - Syguda, Adrian; Bauer, Michael; Benscheid, Utz; Ostler, Nicole; Naschberger, Elisabeth; Ince, Semra; Stürzl, Michael; Herrmann, Christian (Febs Journal, 2012)
The human guanylate-binding protein 1 (hGBP1) is a large GTP-binding protein belonging to the dynamin family, a common feature of which is nucleotide-dependent assembly to homotypic oligomers. Assembly leads to stimulation of GTPase activity, which, in the case of dynamin, is responsible for scission of vesicles from membranes. By yeast two-hybrid and biochemical experiments we addressed intermolecular interactions between all subdomains of hGBP1 and identified the C-terminal subdomain, α12/13, as a new interaction site for self-assembly. α12/13 represents a stable subdomain of hGBP1, as shown by CD spectroscopy. In addition to contacts between GTPase domains leading to dimer formation, the interaction between two α12/13 subdomains, in the course of GTP hydrolysis, results in tetramer formation of the protein. With the help of CD spectroscopy we showed coiled-coil formation of two α12/13 subdomains and concentration-dependent measurements allow estimating a value for the dissociation constant of 7.3 μm. We suggest GTP hydrolysis-driven release of the α12/13 subdomain, making it available for coiled-coil formation. Furthermore, we can demonstrate the biological relevance of hGBP1 tetramer formation in living cells by chemical cross-link experiments. © 2012 FEBS.
Created from Fastlane, Scopus look-up
Keywords: aluminum fluoride; dynamin; protein dimer; protein-protein association; self-assembly

The clinical value of von Willebrand factor in colorectal carcinomas. - Schellerer, Vera; Müller-Bergh, Larissa; Merkel, Susanne; Zimmermann, Robert; Weiss, Dominik R.; Schlabrakowski, Anne; Naschberger, Elisabeth; Stürzl, Michael; Hohenberger, Werner; Croner, Roland S. (American Journal of Translational Research, 2011)
To identify the value of von Willebrand factor (vWF) as a clinical marker in colorectal carcinoma (CRC). Plasma levels of vWF were measured in 79 patients with UICC Stage I-IV CRC at time of operation and correlated with TNM categories, levels of the carcinoembryonic antigen (CEA), blood groups (BG) and 19 controls (CO). CO included cancer-free patients without bacterial or viral infections. For tissue analysis paraffin embedded tumour and mucosa sections of operation specimens were stained immunohistochemically for vWF and compared to vWF plasma levels as well as to TNM categories. VWF plasma levels in CRC patients were significantly dependent on blood groups (p=0.012) and elevated compared to the normal ranges as well as to controls (BG 0: p=0.668, BG A/AB/B: p=0.020). CRC-Patients over 60 years of age presented with significantly higher vWF levels than patients below 60 years (BG 0: p=0.005; BG A/AB/B: p=0.035). There was no correlation of vWF plasma levels and UICC stages in CRC. Patients with elevated vWF plasma levels also presented with elevated CEA levels, but significance was missing (p=0.080). VWF concentration within the tumour tissue was independent of concentration within normal mucosa, blood groups, histopathological characteristics and did not correlate with plasma vWF levels. VWF plasma levels are elevated in CRC patients, but not in a stage dependent manner. Besides the tumour at least blood groups and age mainly influence plasma vWF levels. In our opinion vWF as a routinely used clinical marker in CRC cannot be recommended. BACKGROUND METHODS RESULTS CONCLUSION

The contribution of systems biology and reverse genetics to the understanding of Kaposi's sarcoma-associated herpesvirus pathogenesis in endothelial cells. - Stürzl, Michael; Konrad, Andreas; Alkharsah, Khaled R.; Jochmann, Ramona; Thurau, Mathias; Marquardt, Gaby; Schulz, Thomas F. (Thrombosis and Haemostasis, 2009)
Kaposi's sarcoma-associated herpesvirus (KSHV)/human herpesvirus-8 is the causative agent of the endothelial cell-derived tumour Kaposi's sarcoma. Herpesviruses possess large complex genomes which provide many options to regulate cellular physiology during the viral life cycle and in the course of tumourigenicity. Novel techniques of systems biology and reverse genetics are increasingly applied to dissect the complex interaction of KSHV with endothelial cells. This review will outline novel results and pitfalls of these technologies in the elucidation of KSHV pathogenicity.

The cross-talk between the macro and micro-environment in precursor lesions of pancreatic cancer leads to new and promising circulating biomarkers - Mottini, Carla; Auciello, Francesca Romana; Manni, Isabella; Pilarsky, Christian; Caputo, Damiano; Caracciolo, Giulio; Rossetta, Alessandro; Di Gennaro, Elena; Budillon, Alfredo; Blandino, Giovanni; Roca, Maria Serena; Piaggio, Giulia (Journal of Experimental & Clinical Cancer Research, 2024)
Pancreatic cancer (PC) is a clinically challenging tumor to combat due to its advanced stage at diagnosis as well as its resistance to currently available therapies. The absence of early symptoms and known detectable biomarkers renders this disease incredibly difficult to detect/manage. Recent advances in the understanding of PC biology have highlighted the importance of cancer-immune cell interactions, not only in the tumor micro-environment but also in distant systemic sites, like the bone marrow, spleen and circulating immune cells, the so-called macro-environment. The response of the macro-environment is emerging as a determining factor in tumor development by contributing to the formation of an increasingly immunogenic micro-environment promoting tumor homeostasis and progression. We will summarize the key events associated with the feedback loop between the tumor immune micro-environment (TIME) and the tumor immune macroenvironment (TIMaE) in pancreatic precancerous lesions along with how it regulates disease development and progression. In addition, liquid biopsy biomarkers capable of diagnosing PC at an early stage of onset will also be discussed. A clearer understanding of the early crosstalk between micro-environment and macro-environment could contribute to identifying new molecular therapeutic targets and biomarkers, consequently improving early PC diagnosis and treatment.
CRIS-Team Scopus Importer:2024-07-26
Keywords: Circulating biomarkers; Immune landscape; Macro-environment; Micro-environment; Pancreatic cancer

The Differential Diagnosis and Inter - disciplinary Treatment of Anal Carcinoma - Raptis, Dimitrios; Schneider, Ignaz Hans Friedrich; Matzel, Klaus E.; Ott, Oliver; Fietkau, Rainer; Hohenberger, Werner (Deutsches Ärzteblatt international, 2015)
Anal carcinoma accounts for 2-4% of all cases of colorectal and anorectal carcinoma. Its peak incidence is from age 58 to age 64; women are affected somewhat more commonly than men. Its incidence has risen markedly in the past three decades.This article is based on a selective review of the literature, including the guidelines of the National Comprehensive Cancer Network and the European Society of Medical Oncology.Anal carcinoma is often an incidental finding. About 85% of newly diagnosed cases are associated with an HPV infection with strain 16, 18, or 33. Radiochemotherapy with 5-fluorouracil and mitomycin C is the treatment of choice. The 5-year survival rate is 80-90%. Primary surgery with curative intent is indicated only for well-differentiated carcinoma of the anal margin (T1, N0). 10-30% of patients now undergo radical resection. The utility of endosonography and positron emission tomography for staging is debated and needs further study.The treatment of patients with anal carcinoma requires a specialized multidisciplinary approach in accordance with the current evidence-based guidelines. The potential role of prophylactic vaccination against oncogenic types of HPV in the prevention of anal carcinoma merits further investigation.
EVALuna2:15196

The Ebola virus glycoprotein and HIV-1 Vpu employ different strategies to counteract the antiviral factor tetherin. - Kühl, Annika; Banning, Carina; Marzi, Andrea; Votteler, Jörg; Steffen, Imke; Bertram, Stephanie; Glowacka, Ilona; Konrad, Andreas; Stürzl, Michael; Guo, Ju-Tao; Schubert, Ulrich; Feldmann, Heinz; et al. (Journal of Infectious Diseases, 2011)
The antiviral protein tetherin/BST2/CD317/HM1.24 restricts cellular egress of human immunodeficiency virus (HIV) and of particles mimicking the Ebola virus (EBOV), a hemorrhagic fever virus. The HIV-1 viral protein U (Vpu) and the EBOV-glycoprotein (EBOV-GP) both inhibit tetherin. Here, we compared tetherin counteraction by EBOV-GP and Vpu. We found that EBOV-GP but not Vpu counteracted tetherin from different primate species, indicating that EBOV-GP and Vpu target tetherin differentially. Tetherin interacted with the GP2 subunit of EBOV-GP, which might encode the determinants for tetherin counteraction. Vpu reduced cell surface expression of tetherin while EBOV-GP did not, suggesting that both proteins employ different mechanisms to counteract tetherin. Finally, Marburg virus (MARV)-GP also inhibited tetherin and downregulated tetherin in a cell type-dependent fashion, indicating that tetherin antagonism depends on the cellular source of tetherin. Collectively, our results indicate that EBOV-GP counteracts tetherin by a novel mechanism and that tetherin inhibition is conserved between EBOV-GP and MARV-GP.

The Effect of GPRC5a on the Proliferation, Migration Ability, Chemotherapy Resistance, and Phosphorylation of GSK-3β in Pancreatic Cancer - Liu, Bin; Yang, Hai; Pilarsky, Christian; Weber, Georg (International Journal of Molecular Sciences, 2018)
Pancreatic cancer (PaCa) is the fourth leading cause of cancer-related death, and personalized targeted cancer therapy is becoming a promising treatment strategy for PaCa. The central approach of targeted therapy is to find a targetable key and an effective targeting method. In this study, the importance of GPRC5a (the G-protein-coupled receptor family C, member 5, group A) was identified using data mining methods based on published datasets. After analysis of the basic expression of GPRC5a in normal pancreas tissue and various PaCa cell lines, gene editing of GPRC5a in the human PaCa cell line MIA PaCa-2 and the mouse PaCa cell line TB32047 was performed using CRISPR/Cas9 (Clustered Regularly Interspaced Short Palindromic Repeats/CRISPR-associated proteins 9) to investigate the influence of GPRC5a on the proliferation and migration of PaCa cells as well as its effects on chemotherapy drug resistance. The results showed that GPRC5a was upregulated in PaCa tissues and various PaCa cell lines. Knockout of GPRC5a reduced the proliferation and migration ability of PaCa cell lines and suppressed the chemotherapy drug resistance of gemcitabine, oxaliplatin, and fluorouracil in PaCa cells. The phosphorylation of GSK-3β (Glycogen synthase kinase-3β) was found to be upregulated in the MIA PaCa-2 and TB32047 cells after GPRC5a knockout. In conclusion, GPRC5a was upregulated in PaCa leading to an enhanced drug resistance in PaCa cells. These results provide for the first time a theoretical basis for the development of an improved PaCa targeted therapy.
EVALuna2:210711

The effects of iloprost on colonic anastomotic healing in rats under obstructive ileus conditions - Galanopoulos, Georgios; Raptis, Dimitrios; Pramateftakis, Manousos-Georgios; Mantzoros, Ioannis; Kanellos, Ioannis; Lazarides, Charalambos (Journal of Surgical Research, 2014)
The aim of this study was to investigate the effects of iloprost, on colonic anastomotic healing in rats, under obstructive ileus conditions.Eighty male Albino rats were randomized into four groups of 20 animals each. They underwent colonic resection followed by an inverted anastomosis. The rats of group 1 (control) and group 2 (ileus) received 3 mL of saline 0.9% intraperitoneally and those of group 3 (iloprost), and group 4 (ileus + iloprost) iloprost (2 ?g/kg of body weight), immediately postoperatively and daily until the day of sacrifice. Each group was further divided into two equal subgroups, depending on the day of sacrifice. The animals of subgroup "a" were sacrificed on the fourth postoperative day, whereas those of "b" on the eighth day. Macroscopic and histologic assessment was performed, whereas anastomotic bursting pressures and the tissue concentrations in hydroxyproline and collagenase I were evaluated.Means of bursting pressure, neoangiogenesis, fibroblast activity, and hydroxyproline concentration were significantly increased in group 4 compared with group 2. In addition, on the fourth postoperative day, the inflammatory cell infiltration and the collagenase I concentration were significantly decreased in group 4 compared with group 2. Moreover, on the eighth postoperative day, collagen deposition was significantly increased in group 4 compared with group 2.Iloprost after intraperitoneal administration reverses the negative effect of obstructive ileus. It promotes not only the angiogenic activity but also collagen formation, resulting in increased bursting pressures on the fourth and eighth postoperative days.
EVALuna2:15193

The EMT-activator Zeb1 is a key factor for cell plasticity and promotes metastasis in pancreatic cancer - Krebs, Angela M.; Mitschke, Julia; Losada, Maria Lasierra; Schmalhofer, Otto; Boerries, Melanie; Busch, Hauke; Böttcher, Martin; Mougiakakos, Dimitrios; Reichardt, Wilfried; Bronsert, Peter; Brunton, Valerie G.; Pilarsky, Christian; et al. (Nature Cell Biology, 2017)
Metastasis is the major cause of cancer-associated death. Partial activation of the epithelial-to-mesenchymal transition program (partial EMT) was considered a major driver of tumour progression from initiation to metastasis. However, the role of EMT in promoting metastasis has recently been challenged, in particular concerning effects of the Snail and Twist EMT transcription factors (EMT-TFs) in pancreatic cancer. In contrast, we show here that in the same pancreatic cancer model, driven by Pdx1-cre-mediated activation of mutant Kras and p53 (KPC model), the EMT-TF Zeb1 is a key factor for the formation of precursor lesions, invasion and notably metastasis. Depletion of Zeb1 suppresses stemness, colonization capacity and in particular phenotypic/metabolic plasticity of tumour cells, probably causing the observed in vivo effects. Accordingly, we conclude that different EMT-TFs have complementary subfunctions in driving pancreatic tumour metastasis. Therapeutic strategies should consider these potential specificities of EMT-TFs to target these factors simultaneously.

The ephrin receptor tyrosine kinase A2 is a cellular receptor for Kaposi's sarcoma-associated herpesvirus - Hahn, Alexander; Kaufmann, Johanna K.; Wies, Effi; Naschberger, Elisabeth; Panteleev-Ivlev, Julia; Schmidt, Katharina; Holzer, Angela; Schmidt, Martin; Chen, Jin; Koenig, Simone; Enßer, Armin; Myoung, Jinjong; et al. (Nature Medicine, 2012)
Kaposi's sarcoma-associated herpesvirus (KSHV) is the causative agent of Kaposi's sarcoma, a highly vascularized tumor originating from lymphatic endothelial cells, and of at least two different B cell malignancies. A dimeric complex formed by the envelope glycoproteins H and L (gH-gL) is required for entry of herpesviruses into host cells. We show that the ephrin receptor tyrosine kinase A2 (EphA2) is a cellular receptor for KSHV gH-gL. EphA2 co-precipitated with both gH-gL and KSHV virions. Infection of human epithelial cells with a GFP-expressing recombinant KSHV strain, as measured by FACS analysis, was increased upon overexpression of EphA2. Antibodies against EphA2 and siRNAs directed against EphA2 inhibited infection of endothelial cells. Pretreatment of KSHV with soluble EphA2 resulted in inhibition of KSHV infection by up to 90%. This marked reduction of KSHV infection was seen with all the different epithelial and endothelial cells used in this study. Similarly, pretreating epithelial or endothelial cells with the soluble EphA2 ligand ephrinA4 impaired KSHV infection. Deletion of the gene encoding EphA2 essentially abolished KSHV infection of mouse endothelial cells. Binding of gH-gL to EphA2 triggered EphA2 phosphorylation and endocytosis, a major pathway of KSHV entry. Quantitative RT-PCR and in situ histochemistry revealed a close correlation between KSHV infection and EphA2 expression both in cultured cells derived from human Kaposi's sarcoma lesions or unaffected human lymphatic endothelium, and in situ in Kaposi's sarcoma specimens, respectively. Taken together, our results identify EphA2, a tyrosine kinase with known functions in neovascularization and oncogenesis, as an entry receptor for KSHV. © 2012 Nature America, Inc. All rights reserved.
Created from Fastlane, Scopus look-up

The gammaherpesviruses Kaposi's sarcoma-associated herpesvirus and murine gammaherpesvirus 68 modulate the Toll-like receptor-induced proinflammatory cytokine response - Bussey, Kendra A.; Reimer, Elisa; Todt, Helene; Denker, Brigitte; Gallo, Antonio; Konrad, Andreas; Ottinger, Matthias; Adler, Heiko; Stuerl, Michael; Brune, Wolfram; Brinkmann, Melanie M. (Journal of Virology, 2014)
The human pathogen Kaposi's sarcoma-associated herpesvirus (KSHV), the etiological agent of Kaposi's sarcoma, primary effusion lymphoma, and multicentric Castleman's disease, establishes lifelong latency upon infection. Murine gammaherpesvirus 68 (MHV68) is a well-established model for KSHV. Toll-like receptors (TLRs) play a crucial role for the innate immune response to pathogens. Although KSHV and MHV68 are detected by TLRs, studies suggest they modulate TLR4 and TLR9 signaling, respectively. In this study, we show that in bone marrow-derived macrophages (BMDMs), MHV68 did not induce a detectable proinflammatory cytokine response. Furthermore, MHV68 abrogated the response to TLR2, -4, -7, and -9 agonists in BMDMs. Similarly to observations with MHV68, infection with KSHV efficiently inhibited TLR2 signaling in THP-1 monocytes. Using a KSHV open reading frame (ORF) library, we found that K4.2, ORF21, ORF31, and the replication and transcription activator protein (RTA)/ORF50 inhibited TLR2-dependent nuclear factor kappa B (NF-?B) activation in HEK293 TLR2-yellow fluorescent protein (YFP)- and Flag-TLR2-transfected HEK293T cells. Of the identified ORFs, RTA/ORF50 strongly downregulated TLR2 and TLR4 signaling by reducing TLR2 and TLR4 protein expression. Confocal microscopy revealed that TLR2 and TLR4 were no longer localized to the plasma membrane in cells expressing RTA/ORF50. In this study, we have shown that the gammaherpesviruses MHV68 and KSHV efficiently downmodulate TLR signaling in macrophages and have identified a novel function of RTA/ORF50 in modulation of the innate immune response.The Toll-like receptors (TLRs) are an important class of pattern recognition receptors of the innate immune system. They induce a potent proinflammatory cytokine response upon detection of a variety of pathogens. In this study, we found that the gammaherpesviruses murine gammaherpesvirus 68 (MHV68) and Kaposi's sarcoma-associated herpesvirus (KSHV) efficiently inhibit the TLR-mediated innate immune response. We further identified the KSHV-encoded replication and transcription activator protein (RTA) as a novel modulator of TLR signaling. Our data suggest that the gammaherpesviruses MHV68 and KSHV prevent activation of the innate immune response by targeting TLR signaling.
EVALuna2:15172

The glycan CA19-9 promotes pancreatitis and pancreatic cancer in mice - Engle, Dannielle D.; Tiriac, Herve; Rivera, Keith D.; Pommier, Arnaud; Whalen, Sean; Oni, Tobiloba E.; Alagesan, Brinda; Lee, Eun Jung; Yao, Melissa A.; Lucito, Matthew S.; Spielman, Benjamin; Da Silva, Brandon; et al. (Science, 2019)
Glycosylation alterations are indicative of tissue inflammation and neoplasia, but whether these alterations contribute to disease pathogenesis is largely unknown. To study the role of glycan changes in pancreatic disease, we inducibly expressed human fucosyltransferase 3 and b1,3-galactosyltransferase 5 in mice, reconstituting the glycan sialyl-Lewisa, also known as carbohydrate antigen 19-9 (CA19-9). Notably, CA19-9 expression in mice resulted in rapid and severe pancreatitis with hyperactivation of epidermal growth factor receptor (EGFR) signaling. Mechanistically, CA19-9 modification of the matricellular protein fibulin-3 increased its interaction with EGFR, and blockade of fibulin-3, EGFR ligands, or CA19-9 prevented EGFR hyperactivation in organoids. CA19-9–mediated pancreatitis was reversible and could be suppressed with CA19-9 antibodies. CA19-9 also cooperated with the KrasG12D oncogene to produce aggressive pancreatic cancer. These findings implicate CA19-9 in the etiology of pancreatitis and pancreatic cancer and nominate CA19-9 as a therapeutic target.
CRIS-Team Scopus Importer:2019-07-09

The glycan CA19-9 promotes pancreatitis and pancreatic cancer in mice - Engle, Dannielle; Tiriac, Herve; Rivera, Keith; Pommier, Arnaud; Whalen, Sean; Oni, Tobiloba; Alagesan, Brinda; Lee, Eun; Yao, Melissa; Lucito, Matthew; Spielman, Benjamin; Yu, Kenneth; et al. (CANCER RESEARCH, 2019)
CRIS-Team WoS Importer:2020-05-02

The G Protein-Coupled Receptor RAI3 Is an Independent Prognostic Factor for Pancreatic Cancer Survival and Regulates Proliferation via STAT3 Phosphorylation - Jahny, Elisabeth; Yang, Hai; Liu, Bin; Jahnke, Beatrix; Lademann, Franziska; Knoesel, Thomas; Ruemmele, Petra; Grützmann, Robert; Aust, Daniela; Pilarsky, Christian; Denz, Axel (PLoS ONE, 2017)
Pancreatic Ductal Adenocarcinoma (PDAC) is one of the deadliest tumors worldwide. Understanding the function of gene expression alterations is a prerequisite for developing new strategies in diagnostic and therapy. GPRC5A (RAI3), coding for a seven transmembrane G protein-coupled receptor is known to be overexpressed in pancreatic cancer and might be an interesting candidate for therapeutic intervention. Expression levels of RAI3 were compared using a tissue microarray of 435 resected patients with pancreatic cancer as well as 209 samples from chronic pancreatitis (CP), intra-ductal papillary mucinous neoplasm (IPMN) and normal pancreatic tissue. To elucidate the function of RAI3 overexpression, siRNA based knock-down was used and transfected cells were analyzed using proliferation and migration assays. Pancreatic cancer patients showed a statistically significant overexpression of RAI3 in comparison to normal and chronic pancreatitis tissue. Especially the loss of apical RAI3 expression represents an independent prognostic parameter for overall survival of patients with pancreatic cancer. Suppression of GPRC5a results in decreased cell growth, proliferation and migration in pancreatic cancer cell lines via a STAT3 modulated pathway, independent from ERK activation.
EVALuna2:6846

The guanylate binding protein-1 GTPase controls the invasive and angiogenic capability of endothelial cells through inhibition of MMP-1 expression - Naschberger, Elisabeth; Stürzl, Michael; et al. (EMBO Journal, 2003)
Expression of the large GTPase guanylate binding protein-1 (GBP-1) is induced by inflammatory cytokines (ICs) in endothelial cells (ECs), and the helical domain of the molecule mediates the repression of EC proliferation by ICs. Here we show that the expression of GBP-1 and of the matrix metalloproteinase-1 (MMP-1) are inversely related in vitro and in vivo, and that GBP-1 selectively inhibits the expression of MMP-1 in ECs, but not the expression of other proteases. The GTPase activity of GBP-1 was necessary for this effect, which inhibited invasiveness and tube-forming capability of ECs in three-dimensional collagen-I matrices. A GTPase-deficient mutant (D184N-GBP-1) operated as a transdominant inhibitor of wild-type GBP-1 and rescued MMP-1 expression in the presence of ICs. Expression of D184N-GBP-1, as well as paracrine supplementation of MMP-1, restored the tube-forming capability of ECs in the presence of wild-type GBP-1. The latter finding indicated that the inhibition of capillary formation is specifically due to the repression of MMP-1 expression by GBP-1, and is not affected by the anti-proliferative activity of the helical domain of GBP-1. These findings substantiate the role of GBP-1 as a major regulator of the anti-angiogenic response of ECs to ICs.
Created from Fastlane, Scopus look-up
Keywords: Angiogenesis; Collagenase; Inflammation; Invasion; MMP

The health-related quality of life of sarcoma patients and survivors in germany—cross-sectional results of a nationwide observational study (Prosa) - Eichler, Martin; Hentschel, Leopold; Richter, Stephan; Hohenberger, Peter; Kasper, Bernd; Andreou, Dimosthenis; Pink, Daniel; Jakob, Jens; Singer, Susanne; Grützmann, Robert; Fung, Stephen; Wardelmann, Eva; et al. (Cancers, 2020)
Sarcomas are rare cancers with high heterogeneity in terms of type, location, and treatment. The health-related quality of life (HRQoL) of sarcoma patients has rarely been investigated and is the subject of this analysis. Adult sarcoma patients and survivors were assessed between September 2017 and February 2019 in 39 study centers in Germany using standardized, validated questionnaires (European Organization for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ-C30)). Associated factors were analyzed exploratively using multivariable linear regressions. Among 1113 patients, clinically important limitations and symptoms were most pronounced in emotional (63%, 95% CI 60–66%), physical (60%, 95% CI 57–62%), role functioning (51%, 95% CI 48–54%), and pain (56%, 95% CI 53–59%) and fatigue (51%, 95% CI 48–54%). HRQoL differed between tumor locations with lower extremities performing the worst and sarcoma types with bone sarcoma types being most affected. Additionally, female gender, higher age, lower socioeconomic status, recurrent disease, not being in retirement, comorbidities, and being in treatment were associated with lower HRQoL. Sarcoma patients are severely restricted in their HRQoL, especially in functioning scales. The heterogeneity of sarcomas with regard to type and location is reflected in HRQoL outcomes. During treatment and follow-up, close attention has to be paid to the reintegration of the patients into daily life as well as to their physical abilities and emotional distress.
CRIS-Team Scopus Importer:2020-12-11
Keywords: Clinically important restrictions and symptoms; Health-related quality of life; Observational study; Rare disease; Sarcoma

The helical domain of GBP-1 mediates the inhibition of endothelial cell proliferation by inflammatory cytokines. - Guenzi, Eric; Töpolt, Kristin; Cornali, Emmanuelle; Lubeseder‐Martellato, Clara; Jörg, Anita; Matzen, Kathrin; Zietz, Christian; Kremmer, Elisabeth; Nappi, Filomena; Schwemmle, Martin; Hohenadl, Christine; Barillari, Giovanni; et al. (EMBO Journal, 2001)
Inflammatory cytokines (IC) activate endothelial cell adhesiveness for monocytes and inhibit endothelial cell growth. Here we report the identification of the human guanylate binding protein-1 (GBP-1) as the key and specific mediator of the anti-proliferative effect of IC on endothelial cells. GBP-1 expression was induced by IC, downregulated by angiogenic growth factors, and inversely related to cell proliferation both in vitro in microvascular and macrovascular endothelial cells and in vivo in vessel endothelial cells of Kaposi's sarcoma. Experimental modulation of GBP-1 expression demonstrated that GBP-1 mediates selectively the anti-proliferative effect of IC, without affecting endothelial cell adhesiveness for monocytes. GBP-1 anti-proliferative activity did not affect ERK-1/2 activation, occurred in the absence of apoptosis, was found to be independent of the GTPase activity and isoprenylation of the molecule, but was specifically mediated by the C-terminal helical domain of the protein. These results define GBP-1 as an important tool for dissection of the complex activity of IC on endothelial cells, and detection and specific modulation of the IC-activated non-proliferating phenotype of endothelial cells in vascular diseases.

The Histone Demethylase Jumonji Domain-Containing Protein 3 (JMJD3) As Central Mediator of Fibroblast Activation - Bergmann, Christina; Brandt, Adrian; Dees, Clara; Zhang, Yun; Chen, Chih-Wei; Mallano, Tatjana; Wohlfahrt, Thomas; Liang, Ruifang; Kagwiria, Rosebeth; Bozec, Aline; Rieker, Ralf; Abraham, David; et al. (2017)
EVALuna2:33428

The histone demethylase Jumonji domain-containing protein 3 (JMJD3) regulates fibroblast activation in systemic sclerosis - Bergmann, Christina; Brandt, Adrian; Merlevede, Benita; Hallenberger, Ludwig; Dees, Clara; Wohlfahrt, Thomas; Pötter, Sebastian; Zhang, Yun; Chen, Chih-Wei; Mallano, Tatjana; Liang, Ruifang; Kagwiria, Rosebeth; et al. (Annals of the Rheumatic Diseases, 2017)
Systemic sclerosis (SSc) fibroblasts remain activated even in the absence of exogenous stimuli. Epigenetic alterations are thought to play a role for this endogenous activation. Trimethylation of histone H3 on lysine 27 (H3K27me3) is regulated by Jumonji domain-containing protein 3 (JMJD3) and ubiquitously transcribed tetratricopeptide repeat on chromosome X (UTX) in a therapeutically targetable manner. The aim of this study was to explore H3K27me3 demethylases as potential targets for the treatment of fibrosis.JMJD3 was inactivated by small interfering RNA-mediated knockdown and by pharmacological inhibition with GSKJ4. The effects of targeted inactivation of JMJD3 were analysed in cultured fibroblasts and in the murine models of bleomycin-induced and topoisomerase-I (topoI)-induced fibrosis. H3K27me3 at the FRA2 promoter was analysed by ChIP.The expression of JMJD3, but not of UTX, was increased in fibroblasts in SSc skin and in experimental fibrosis in a transforming growth factor beta (TGF?)-dependent manner. Inactivation of JMJD3 reversed the activated fibroblast phenotype in SSc fibroblasts and prevented the activation of healthy dermal fibroblasts by TGF?. Pharmacological inhibition of JMJD3 ameliorated bleomycin-induced and topoI-induced fibrosis in well-tolerated doses. JMJD3 regulated fibroblast activation in a FRA2-dependent manner: Inactivation of JMJD3 reduced the expression of FRA2 by inducing accumulation of H3K27me3 at the FRA2 promoter. Moreover, the antifibrotic effects of JMJD3 inhibition were reduced on knockdown of FRA2.We present first evidence for a deregulation of JMJD3 in SSc. JMJD3 modulates fibroblast activation by regulating the levels of H3K27me3 at the promoter of FRA2. Targeted inhibition of JMJD3 limits the aberrant activation of SSc fibroblasts and exerts antifibrotic effects in two murine models.
EVALuna2:13457

The impact of body mass index on prognosis in patients with colon carcinoma - Fuchs, Julian; Schellerer, Vera S.; Brunner, Maximilian; Geppert, Carol-Immanuel; Grützmann, Robert; Weber, Klaus; Merkel, Susanne (International Journal of Colorectal Disease, 2022)
Background: The impact of body mass index (BMI) on prognosis in patients with curatively resected stage I–III colon carcinoma was analyzed. Methods: The prospectively collected data of 694 patients who underwent complete mesocolic excision between 2003 and 2014 were analyzed. BMI was classified into four categories: underweight (BMI < 18.5 kg/m2; n = 13), normal weight (BMI 18.5 to 24.9 kg/m2; n = 221), overweight (BMI 25.0 to 29.9 kg/m2; n = 309), and obese (BMI ≥ 30.0 kg/m2; n = 151). Univariate and multivariate analyses for comparison of prognosis were performed. Results: The 5-year rate of locoregional recurrence in all 694 patients was 2.1%, and no differences were found with respect to BMI (p = 0.759). For distant metastasis, the 5-year rate for all patients was 13.4%, and BMI did not have a significant impact (p = 0.593). The 5-year rate of disease-free survival for all 694 patients was 72.4%. The differences with respect to BMI were not found to be significant in univariate analysis (p = 0.222). In multivariate Cox regression analysis, disease-free survival was significantly better in obese patients (HR 0.7; p = 0.034). Regarding overall survival, the 5-year rate for all patients was 78.1%. In univariate analyses, no significant differences were found for BMI (p = 0.094). In the Cox regression analysis, overweight and obese patients had significantly better survival (overweight: HR 0.7; p = 0.027; obese: HR 0.6; p = 0.019). Conclusion: The better survival of overweight and obese patients in multivariate analyses must be interpreted with caution. It is influenced by several factors and seems to correspond to the phenomenon of the obesity paradox.
CRIS-Team Scopus Importer:2022-04-22
Keywords: Body mass index; Colon carcinoma; Obesity paradox; Overall survival; Prognosis

The impact of surgical experience and frequency of practice on perioperative outcomes in pancreatic surgery - Krautz, Christian; Haase, Elisabeth; Elshafei, Moustafa; Saeger, Hans Detlev; Distler, Marius; Grützmann, Robert; Weber, Georg (BMC Surgery, 2019)
Objective: We aimed to determine the impact of surgical experience and frequency of practice on perioperative morbidity and mortality in pancreatic surgery. Methods: 1281 patients that underwent pancreatic resections from 1993 to 2013 were retrospectively analyzed using logistic regression models. All cases were stratified according to the surgeon's level of experience, which was based on the number of previously performed pancreatic resections and the extent of received supervision (novice: N < 20/intensive; intermediate: N = 21-90/decreasing; and experienced surgeon: N > 90/none). Additional stratification was based on the frequency of practice (sporadic: 3 resections > 6 weeks, frequent: 3 resections ≤6 weeks). Results: The novice and experienced categories were related to a decreased risk of postoperative pancreatic fistulas (odds ratio [OR] 0.46, 95% confidence interval [CI] 0.26-0.82 and 0.54, 95% CI 0.36-0.82) and in-hospital mortality (OR 0.45, 95% CI 0.17-1.16 and 0.42, 95% CI 0.21-0.83) compared to the intermediate category. Frequent practice was associated with a significantly lower risk of delayed gastric emptying (OR 0.56, 95% CI 0.38-0.83), postpancreatectomy hemorrhage (OR 0.64, 95% CI 0.42-0.98) and in-hospital mortality (OR 0.45, 95% CI 0.24-0.87). Conclusions: Our results emphasize the importance of supervision within a pancreatic surgery training program. In addition, our data underline the need of a sufficient patient caseload to ensure frequent practice.
CRIS-Team Scopus Importer:2019-08-27
Keywords: Frequency of practice; In-hospital mortality; Pancreatic surgery; Perioperative outcomes; Surgical experience; Volume-outcome relationship

The impact of surgical quality on prognosis in patients undergoing rectal carcinoma surgery after preoperative chemoradiation - Kiehlmann, Marcus; Weber, Klaus; Göhl, Jonas; Fietkau, Rainer; Agaimy, Abbas; Hohenberger, Werner; Merkel, Susanne (International Journal of Colorectal Disease, 2016)
The aim of the study was to analyse the impact of surgical quality on the prognosis of rectal carcinoma patients who underwent preoperative long-term chemoradiation and TME surgery.In a total of 314 patients, four quality indicators, including plane of surgery, pathological circumferential resection margin (pCRM), intraoperative local tumour cell dissemination and anastomotic leakage, were analysed with respect to locoregional recurrence, distant metastasis and overall survival.In 260 (82.8 %) of the patients, all four quality indicators were fulfilled. In 30 (9.6 %) of the patients, at least one quality indicator was not fulfilled; in 24 (7.6 %) of the patients, the data were not complete. Locoregional recurrence was significantly increased in patients who underwent surgery in the muscularis propria plane, who had a pCRM <= 1 mm or who experienced local tumour cell dissemination. In patients who had at least one quality indicator that was not fulfilled (suboptimal surgical quality), the 5-year rate of locoregional recurrence in those patients was 23.1 % compared to 4.8 % in patients who underwent optimal surgery (P = 0.001). In multivariate analysis, suboptimal surgery (hazard ratio (HR) 3.9; P = 0.020), abdominoperineal excision (HR 4.7; P = 0.003) and poor regression of primary tumours (HR 8.5; P < 0.001) were identified as independent prognostic factors for locoregional recurrence. In contrast to type of surgical treatment, ypT, ypN and regression grade, the quality of surgery did not significantly influence distant metastasis or overall survival.Even after preoperative chemoradiation, the surgical quality still has a strong impact on local control in patients with rectal carcinoma.
EVALuna2:6711

The importance of pancreatic inflammation in endosonographic diagnostics of solid pancreatic masses - Vitali, Francesco; Strobel, Deike; Frulloni, Luca; Heinrich, Marc Christopher; Pfeifer, Lukas; Görtz, Rüdiger; Hundorfean, Gheorghe; Wachter, David Lukas; Wachter, David; Grützmann, Robert; Bernatik, Thomas; Neurath, Markus; et al. (Medical Ultrasonography, 2018)
AIMS: Endosonography (EUS) is one of the main diagnostic tools for the differential diagnosis of pancreatic masses. The aim of our study was to describe the value of this technique in the work-up of solid pancreatic lesions, considering the influence of the morphological evidence of pancreatic inflammation in the diagnostic process. MATERIAL AND METHODS: Retrospective analysis of prospectively collected data in our tertiary University center. From March 2007 to October 2015, 218 patients underwent EUS for a suspected solid pancreatic neoplasm (based on previous cross-sectional imaging results, idiopatic acute pancreatitis, weight loss, pancreatic hyperenzymemia, painless jaundice or elevated Ca 19-9 values). RESULTS: Malignant lesions were diagnosed in 98 (45%) patients. Sensitivity of EUS for malignancy was 91% and specificity 89.2%. Signs of pancreatic inflammation in the surrounding pancreatic parenchyma around the focal lesion were present in 97 patients (44.4%)(more often in men, smokers and drinkers, and the most common etiology was focal chronic pancreatitis) and in these patients the sensitivity and sensibility dropped to 44% and 87.1%, respectively. In patients without signs of pancreatic inflammation, the pancreatic focal lesions were adenocarcinoma, neuroendocrine tumor, ventral/dorsal split, non-pancreatic pathology, pancreatic lipomatosis and autoimmune pancreatitis. CONCLUSION: Pancreatic inflammation (either focal or involving the whole gland) lowers the diagnostic sensibility of EUS in the work- up of pancreatic masses suspected for cancer, requiring further invasive diagnostic methods. Focal autoimmune pancreatitis and paraduodenal pancreatitis are still confused with pancreatic cancer, even in the absence of pancreatic inflammation.
EVALuna2:35194

The Influence of Body Mass Index on Long-Term Prognosis in Patients with Colon Carcinomas - Merkel, Susanne; Fuchs, Julian; Schellerer, Vera; Brunner, Maximilian; Geppert, Carol-Immanuel; Grützmann, Robert; Weber, Klaus (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-03-20

The influence of expectations on recovery, quality of life, and treatment satisfaction in surgical patients - Weiss, Maren; Siassi, Ramin Michael; Hohenberger, Werner; Lösel, Friedrich (Psychology of Expectations, 2010)

The influence of postoperative complications on long-term prognosis in patients with colorectal carcinoma - Beck, Clemens; Weber, Klaus; Brunner, Maximilian; Agaimy, Abbas; Semrau, Sabine; Grützmann, Robert; Schellerer, Vera; Merkel, Susanne (International Journal of Colorectal Disease, 2020)
Background: The impact of postoperative complications (POCs) on the long-term prognosis of patients with colorectal carcinoma was analysed with respect to their severity according to the Clavien-Dindo classification (CDC). Methods: The prospectively collected data of 2158 patients who underwent curative resection of a colorectal carcinoma (1168 rectal carcinomas, 990 colon carcinomas) without distant metastases from 1995 to 2014 were analysed. The POCs were documented in a standardized form and graded with the CDC. Patients who died postoperatively (CDC grade V, 1.7%) were excluded. Results: In total, 467 patients (21.6%) had POCs: CDC I, 141 (6.5%); CDC II, 162 (7.5%); CDC III, 112 (5.2%); and CDC IV, 52 (2.4%). More POCs and higher CDC grades were found in men, ASA III-IV patients, rectal carcinoma patients, and patients who underwent abdominoperineal excisions or multivisceral resections. The 5-year locoregional recurrence rate was 5.3% in patients without POCs and 6.6% in patients with POCs. It was highest in CDC III patients (12.9%), which was confirmed in multivariate analysis (HR 2.2; p = 0.005). The 5-year distant metastasis rate was 15.9% in CDC 0 patients and 19.5% in CDC I–IV patients. In multivariate analysis, distant metastasis was highest in CDC III patients (HR 1.7; p = 0.020). The 5-year overall survival rate was 83.5% in patients without POCs and 73.5% in patients with POCs. It was worst in CDC IV patients (63.1%), which was confirmed by multivariate analysis (HR 1.9; p = 0.001). Conclusion: Patients with POCs after colorectal surgery have a poor long-term prognosis. As the CDC grade increases, survival deteriorates.
CRIS-Team Scopus Importer:2020-04-14
Keywords: Clavien-Dindo classification; Colorectal carcinoma; Postoperative complications; Prognosis

The Influence of Postoperative Complications on Long-Term Prognosis in Patients with Colorectal Carcinomas - Beck, Clemens; Schellerer, Vera; Weber, Klaus; Brunner, Maximilian; Agaimy, Abbas; Semrau, Sabine; Grützmann, Robert; Merkel, Susanne (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-03-20

The influence of tumour site on prognosis in metastatic colorectal carcinomas with primary tumour resection - Merkel, Susanne; Schellerer, Vera; Wein, Axel; Semrau, Sabine; Geppert, Carol-Immanuel; Göhl, Jonas; Hohenberger, Werner; Weber, Klaus; Grützmann, Robert (International Journal of Colorectal Disease, 2018)
PURPOSE: The aim of our study was to compare the characteristics and prognosis between right- and left-sided metastatic colorectal carcinomas. METHODS: Data from 937 patients with stage IV colorectal carcinomas (synchronous distant metastasis) who had a resection of the primary tumour between 1985 and 2014 were analysed. Carcinomas in the caecum to transverse colon were defined as right-sided (n = 250; 26.7%). They were compared to tumours located from the splenic flexure to the rectum categorised as left-sided (n = 687; 73.3%). RESULTS: In right-sided carcinomas, we observed significantly more female patients (50.8 vs 36.2%; p < 0.001), more unfavourable histological types (24.0 vs 8.6%; p < 0.001), more M1c carcinomas (metastases to the peritoneum ± others; 32.0 vs 14.4%; p < 0.001) and more emergencies (11.6 vs 7.1%; p = 0.029), while multimodal treatment was utilised in fewer patients (51.6 vs 63.8%; p = 0.001) and curative resections were less frequently (24.1 vs 35.4%; p = 0.002). Prognosis was significantly worse in patients with right-sided carcinomas (2-year-survival 27.2 vs 44.6%, p < 0.01). This difference was more pronounced after R2 resection (15.3 vs 29.7%; p < 0.001), than after macroscopic curative resection (2-year-survival 63.9 vs 71.9%; p = 0.106). In multivariate Cox regression analysis, tumour site was found to be an independent prognostic factor for overall survival (HR 1.2; 95% CI 1.0-1.5; p = 0.012). During the three 10-year periods, the prognosis improved equally in patients with right- and left-sided carcinomas, while the differences in survival remained identical. CONCLUSIONS: In a surgical patient cohort undergoing primary tumour resection, significant differences in prognosis were observed between patients with metastatic right- and left-sided colorectal carcinomas.
EVALuna2:35146

The Intratumoral and Intestinal Microbiome in Pancreatic Cancer - Langheinrich, Melanie; Wirtz, Stefan; Grützmann, Robert; Kersting, Stephan; Weber, Georg (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-03-20

The large GTPase AtGBPL3 links nuclear envelope formation and morphogenesis to transcriptional repression - Reimann, Theresa; Müdsam, Christina; Schachtler, Christina; Ince, Semra; Sticht, Heinrich; Herrmann, Christian; Stürzl, Michael; Kost, Benedikt (Nature Plants, 2023)
Guanylate binding proteins (GBPs) are prominent regulators of immunity not known to be required for nuclear envelope formation and morphogenesis. Here we identify the Arabidopsis GBP orthologue AtGBPL3 as a lamina component with essential functions in mitotic nuclear envelope reformation, nuclear morphogenesis and transcriptional repression during interphase. AtGBPL3 is preferentially expressed in mitotically active root tips, accumulates at the nuclear envelope and interacts with centromeric chromatin as well as with lamina components transcriptionally repressing pericentromeric chromatin. Reduced expression of AtGBPL3 or associated lamina components similarly altered nuclear morphology and caused overlapping transcriptional deregulation. Investigating the dynamics of AtGBPL3-GFP and other nuclear markers during mitosis (1) revealed that AtGBPL3 accumulation on the surface of daughter nuclei precedes nuclear envelope reformation and (2) uncovered defects in this process in roots of AtGBPL3 mutants, which cause programmed cell death and impair growth. AtGBPL3 functions established by these observations are unique among dynamin-family large GTPases.
CRIS-Team WoS Importer:2023-05-26

The management of retrorectal tumors – a single-center analysis of 21 cases and overview of the literature - Fechner, Katja; Bittorf, B.; Langheinrich, M.; Weber, K.; Brunner, Maximilian; Grützmann, Robert; Matzel, Klaus (Langenbecks Archives of Surgery, 2024)
Aim: Retrorectal tumors are rare and heterogeneous. They are often asymptomatic or present with nonspecific symptoms, making management challenging. This study examines the diagnosis and treatment of retrorectal tumors. Methods: Between 2002 and 2022, 21 patients with retrorectal tumors were treated in our department. We analyzed patient characteristics, diagnosis and treatment modalities retrospectively. Additionally, a literature review (2002–2023, “retrorectal tumors” and “presacral tumors”, 20 or more cases included) was performed. Results: Of the 21 patients (median age 54 years, 62% female), 17 patients (81%) suffered from benign lesions and 4 (19%) from malignant lesions. Symptoms were mostly nonspecific, with pain being the most common (11/21 (52%)). Diagnosis was incidental in eight cases. Magnetic resonance imaging was performed in 20 (95%) and biopsy was obtained in 10 (48%). Twenty patients underwent surgery, mostly via a posterior approach (14/20 (70%)). At a mean follow-up of 42 months (median 10 months, range 1–166 months), the local recurrence rate was 19%. There was no mortality. Our Pubmed search identified 39 publications. Conclusion: Our data confirms the significant heterogeneity of retrorectal tumors, which poses a challenge to management, especially considering the often nonspecific symptoms. Regarding diagnosis and treatment, our data highlights the importance of MRI and surgical resection. In particular a malignancy rate of almost 20% warrants a surgical resection in case of the findings of a retrorectal tumour. A local recurrence rate of 19% supports the need for follow up.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Presacral mass; Retrorectal tumors; Tailgut cyst; Treatment

The Molecular Mechanism of Polymer Formation of Farnesylated Human Guanylate-binding Protein 1 - Sistemich, Linda; Kutsch, Miriam; Hämisch, Benjamin; Zhang, Ping; Shydlovskyi, Sergii; Britzen-Laurent, Nathalie; Stürzl, Michael; Huber, Klaus; Herrmann, Christian (Journal of Molecular Biology, 2020)
The human guanylate-binding protein 1 (hGBP1) belongs to the dynamin superfamily proteins and represents a key player in the innate immune response. Farnesylation at the C-terminus is required for hGBP1’s activity against microbial pathogens, as well as for its antiproliferative and antitumor activity. The farnesylated hGBP1 (hGBP1fn) retains many characteristics of the extensively studied nonfarnesylated protein and gains additional abilities like binding to lipid membranes and formation of hGBP1fn polymers. These polymers are believed to serve as a protein depot, making the enzyme immediately available to fight the invasion of intracellular pathogens. Here we study the molecular mechanism of hGBP1 polymer formation as it is a crucial state of this enzyme, allowing for a rapid response demanded by the biological function. We employ Förster resonance energy transfer in order to trace intra and intermolecular distance changes of protein domains. Light scattering techniques yield deep insights into the changes in size and shape. The GTP hydrolysis driven cycling between a closed, farnesyl moiety hidden state and an opened, farnesyl moiety exposed state represents the first phase, preparing the molecule for polymerization. Within the second phase of polymer growth, opened hGBP1 molecules can be incorporated in the growing polymer where the opened structure is stabilized, similar to a surfactant molecule in a micelle, pointing the farnesyl moieties into the hydrophobic center and positioning the head groups at the periphery of the polymer. We contribute the molecular mechanism of polymer formation, paving the ground for a detailed understanding of hGBP1 function.
CRIS-Team Scopus Importer:2020-03-17
Keywords: dimer; GBPs; lag phase; large GTPase; polymerization

The Nuclear Receptor ROR-Alpha As a Key Checkpoint of Tissue Repair - Kagwiria, Rosebeth; Liang, Ruifang; Chen, Chih-Wei; Burris, Thomas; Schett, Georg; Distler, Jörg (2017)
EVALuna2:33434

The outcome of patients with inflammatory bowel disease-associated colorectal cancer is not worse than that of patients with sporadic colorectal cancer-a matched-pair analysis of survival - Vitali, Francesco; Wein, Axel; Rath, Timo; Eckstein, Markus; Neufert, Clemens; Siebler, Jürgen; Atreya, Raja; Hartmann, Arndt; Hohenberger, Werner; Weber, Klaus; Neurath, Markus; Grützmann, Robert; et al. (International Journal of Colorectal Disease, 2021)
Purpose Patients with inflammatory bowel disease (IBD) have an increased risk for colorectal cancer (CRC). In IBD patients, cancer is often diagnosed in advanced stages and conflicting data on survival compared to sporadic CRC have been reported. The aim of this study was to directly compare clinical characteristics and prognosis of patients with IBD-CRC and sporadic CRC. Methods The clinical and pathological data of 63 patients with IBD-CRC and 3710 patients with sporadic CRC treated at the University Hospital of Erlangen between 1995 and 2015 were compared. Forty-seven M0 patients with IBD were matched with sporadic CRC patients after curative resection (R0) according to tumor localization, stage, sex, and year of treatment. Overall and disease-free survival were compared. Results Sixty-three patients presented IBD-CRC. Fifty were affected with ulcerative colitis (UC) and 13 with Crohn's disease (CD). CRC was diagnosed within 1.45 years since last endoscopic surveillance. Twelve patients (19%) had a diagnosis of primary sclerosing cholangitis. In matched analysis, IBD patients were diagnosed with CRC at younger age compared to sporadic CRC and were more likely to have right-sided CRC (40% versus 23.3%) and rare histological subtypes (19% versus 9.2%). No differences in 5-year overall (78.7 versus 80.9 months) and 5-year disease-free survival (74.5 versus 70.2 months) were noted. Conclusion IBD-CRC patients were younger and more frequently had right-sided carcinomas compared to sporadic CRC. CRC in IBD patients did not show survival difference compared to matched-pair sporadic CRC patients without distant metastases after curative resection. Surveillance might be important for early detection of CRC in IBD patients.
CRIS-Team WoS Importer:2021-12-17

The prognostic value of the number of harvested negative lymph nodes in patients treated by esophagectomy with or without neoadjuvant chemoradiation - Brunner, Maximilian; Merkel, Susanne; Krautz, Christian; Kersting, Stephan; Grützmann, Robert; Weber, Georg (Anticancer Research, 2020)
Background/Aim: The prognostic value of the number of harvested negative lymph nodes (NLNs) in patients with node-negative esophageal carcinoma treated by esophagectomy with or without neoadjuvant chemoradiation is unclear. Patients and Methods: A total of 136 patients who underwent oncological esophagectomy with two-field lymphadenectomy from 1995 to 2014 were analyzed regarding the prognostic impact of NLNs. 86 patients received primary surgery (group 1) and 50 patients had preoperative chemoradiation followed by surgery (group 2). Results: The 5-year overall survival (OS) was 61.1%. Median lymph node harvest was significantly higher in group 1 (39 vs. 34 in group 2, p=0.007). In group 1, patients with a higher number of negative lymph nodes (>40) had a better OS [57.6% vs. 78.9%, HR=0.5 (0.3-0.9), p=0.026], whereas there was no significant difference in group 2 using the same cutoff (47.6% vs. 66.7%, p=0.476). Conclusion: The number of NLNs is an independent prognostic factor for patients with esophageal carcinoma treated by primary esophagectomy, but not in patients after neoadjuvant chemoradiation.
CRIS-Team Scopus Importer:2020-05-15
Keywords: Esophageal carcinoma; Lymphadenectomy; Neoadjuvant chemoradiation; Oncological esophagectomy; Prognosis; Survival

The rate of cholangiocarcinoma in Caroli Disease A German multicenter study - Fard-Aghaie, Mohammad H.; Makridis, Georgios; Reese, Tim; Feyerabend, Bernd; Wagner, Kim C.; Schnitzbauer, Andreas; Bechstein, Wolf O.; Oldhafer, Felix; Kleine, Moritz; Klempnauer, Jürgen; Rolinger, Jens; Nadalin, Silvio; et al. (Hpb, 2021)
Background: Caroli Disease (CD) and Caroli Syndrome (CS) are rare disorders presenting with dilation of the intrahepatic bile ducts. CD/CS are associated with cholangiocarcinoma (CCA). However, the true incidence of CCA is still unclear, although it may serve as an indication for surgery. In this paper, we analyzed (I) the incidence of CCA in German centers, (II) reviewed our single center population together with its clinical presentation and (III) performed a thorough literature review. Methods: 17 large HPB-centers across Germany were contacted and their patients after surgical treatment due to CD/CS with histopathology were included. Medline search for all studies published in English or German literature was performed. Patients who underwent surgery at our department between 2012 and 2020 due to CD or CS were analyzed. Results: In the multicenter study, 79 patients suffered from CD and 119 patients from CS, with a total number of 198 patients. In 14 patients, CCA was found (Overall: 7,1%; CD: 6,3%, CS 7,6%). Between 2012 and 2020, 1661 liver resections were performed at our department. 14 patients underwent surgery due to CD or CS. Histological examination showed synchronous cholangiocarcinoma in one patient. The literature review revealed a CCA-rate of 7,3% in large series, whereas in case reports a rate of 6,8% was found. Conclusion: There is risk of malignant transformation and patients with CD might also benefit from resection due to improvement of symptoms. Therefore, resection is strongly advised. As certain patients with CS require transplantation, treatment should not be guided by the relatively low rate of CCA but by the concomitant diseases that come along with hepatic failure.
CRIS-Team Scopus Importer:2021-07-30
Keywords: Caroli disease; Caroli Syndrome; Intrahepatic bile duct dilation; Liver surgery

The Role of Exosomes in Pancreatic Cancer - Lan, Bin; Zeng, Siyuan; Grützmann, Robert; Pilarsky, Christian (International Journal of Molecular Sciences, 2019)
Pancreatic cancer remains one of the deadliest cancers in the world, as a consequence of late diagnosis, early metastasis and limited response to chemotherapy, under which conditions the potential mechanism of pancreatic cancer progression requires further study. Exosomes are membrane vesicles which are important in the progression, metastasis and chemoresistance in pancreatic cancer. Additionally, they have been verified to be potential as biomarkers, targets and drug carriers for pancreatic cancer treatment. Thus, studying the role of exosomes in pancreatic cancer is significant. This paper focuses on the role of exosomes in the proliferation, metastasis and chemoresistance, as well as their potential applications for pancreatic cancer.
CRIS-Team Scopus Importer:2019-09-17
Keywords: biomarker; chemoresistance; exosomes; pancreatic cancer

The role of intraoperative swab during appendectomy in patients with uncomplicated and complicated appendicitis - Bancke Laverde, Bruno Leonardo; Maak, Matthias; Langheinrich, Melanie; Kersting, Stephan; Denz, Axel; Krautz, Christian; Weber, Georg; Grützmann, Robert; Brunner, Maximilian (International Journal of Colorectal Disease, 2023)
Introduction: Bacteria play an important role not only in pathogenesis of appendicitis but also in the postoperative course of patients. However, the usefulness of an intraoperative swab during appendectomy is controversial. The primary aim of this study was to investigate the impact of intraoperative swab during appendectomy on the postoperative outcome in patients with uncomplicated and complicated appendicitis. Methods: A retrospective analysis was conducted on a consecutive series of 1570 adult patients who underwent appendectomy for acute appendicitis at the University Hospital Erlangen between 2010 and 2020. Data regarding the intraoperative swab were collected and analyzed for the entire cohort as well as for patients with uncomplicated and complicated appendicitis. Results: An intraoperative swab was taken in 29% of the cohort. The bacterial isolation rate in the obtained intraoperative swabs was 51%, with a significantly higher rate observed in patients with complicated appendicitis compared to those with uncomplicated appendicitis (79% vs. 35%, p < 0.001). The presence of a positive swab was significantly associated with worse postoperative outcomes, including higher morbidity, increased need for re-surgery, and longer hospital stay, when compared to patients without a swab or with a negative swab. A positive swab was an independent risk factor for postoperative morbidity (OR 9.9 (95% CI 1.2–81.9), p = 0.034) and the need for adjustment of postoperative antibiotic therapy (OR 8.8 (95% CI 1.1–72.5), p = 0.043). However, a positive swab resulted in postoperative antibiotic therapy adjustment in only 8% of the patients with bacterial isolation in the swab. Conclusion: The analysis of swab samples obtained during appendectomy for acute appendicitis can help identify patients at a higher risk of a worse postoperative outcome. However, the frequency of antibiotic regime changes based on the swab analysis is low.
CRIS-Team Scopus Importer:2023-12-01
Keywords: Appendectomy; Bacterial isolation; Complicated appendicitis; Intraoperative swab; Uncomplicated appendicitis

The role of miR-200b/c in balancing EMT and proliferation revealed by an activity reporter - Gollavilli, Paradesi Naidu; Parma, Beatrice; Siddiqui, Aarif; Yang, Hai; Ramesh, Vignesh; Napoli, Francesca; Schwab, Annemarie; Natesan, Ramakrishnan; Mielenz, Dirk; Asangani, Irfan Ahmed; Brabletz, Thomas; Pilarsky, Christian; et al. (Oncogene, 2021)
Since their discovery, microRNAs (miRNAs) have been widely studied in almost every aspect of biology and medicine, leading to the identification of important gene regulation circuits and cellular mechanisms. However, investigations are generally focused on the analysis of their downstream targets and biological functions in overexpression and knockdown approaches, while miRNAs endogenous levels and activity remain poorly understood. Here, we used the cellular plasticity-regulating process of epithelial-to-mesenchymal transition (EMT) as a model to show the efficacy of a fluorescent sensor to separate cells with distinct EMT signatures, based on miR-200b/c activity. The system was further combined with a CRISPR-Cas9 screening platform to unbiasedly identify miR-200b/c upstream regulating genes. The sensor allows to infer miRNAs fundamental biological properties, as profiling of sorted cells indicated miR-200b/c as a molecular switch between EMT differentiation and proliferation, and suggested a role for metabolic enzymes in miR-200/EMT regulation. Analysis of miRNAs endogenous levels and activity for in vitro and in vivo applications could lead to a better understanding of their biological role in physiology and disease.
CRIS-Team Scopus Importer:2021-03-19

The role of plastic reconstructive surgery in surgical therapy of soft tissue sarcomas - Götzl, Rebekka; Sterzinger, Sebastian; Arkudas, Andreas; Boos, Anja; Semrau, Sabine; Vassos, Nikolaos; Grützmann, Robert; Agaimy, Abbas; Hohenberger, Werner; Horch, Raymund E.; Beier, Justus (Cancers, 2020)
Background: Soft tissue sarcoma (STS) treatment is an interdisciplinary challenge. Along with radio(chemo)therapy, surgery plays the central role in STS treatment. Little is known about the impact of reconstructive surgery on STS, particularly whether reconstructive surgery enhances STS resection success with the usage of flaps. Here, we analyzed the 10-year experience at a university hospital’s Comprehensive Cancer Center, focusing on the role of reconstructive surgery. Methods: We performed a retrospective analysis of STS-patients over 10 years. We investigated patient demographics, diagnosis, surgical management, tissue/function reconstruction, complication rates, resection status, local recurrence and survival. Results: Analysis of 290 patients showed an association between clear surgical margin (R0) resections and higher-grade sarcoma in patients with free flaps. Major complications were lower with primary wound closure than with flaps. Comparison of reconstruction techniques showed no significant differences in complication rates. Wound healing was impaired in STS recurrence. The local recurrence risk was over two times higher with primary wound closure than with flaps. Conclusion: Defect reconstructions in STS are reliable and safe. Plastic surgeons should have a permanent place in interdisciplinary surgical STS treatment, with the full armamentarium of reconstruction methods.
CRIS-Team Scopus Importer:2020-12-04
Keywords: Plastic surgery; Reconstruction; Reconstructive surgery; Soft tissue sarcoma; STS

The sarcoma ring trial: a case-based analysis of inter-center agreement across 21 German-speaking sarcoma centers - Roohani, Siyer; Handtke, Jolina; Hummedah, Kamal; Albertsmeier, Markus; Andreou, Dimosthenis; Apostolidis, Leonidas; Augustin, Marinela; Bauer, Sebastian; Billner, Moritz; Bösch, Florian; Deinzer, Christoph K.W.; Deventer, Niklas; et al. (Journal of Cancer Research and Clinical Oncology, 2025)
Purpose: The management of soft tissue sarcoma (STS) at reference centers with specialized multidisciplinary tumor boards (MTB) improves patient survival. The German Cancer Society (DKG) certifies sarcoma centers in German-speaking countries, promoting high standards of care. This study investigated the variability in treatment recommendations for localized STS across different German-speaking tertiary sarcoma centers. Methods: In this cross-sectional case-based survey study, 5 anonymized patient cases with imaging data of localized STS were presented to MTBs of 21 German-speaking tertiary referral hospitals. Centers provided recommendations on treatment sequence and modalities, along with the consensus level within their MTB. Agreement percentages were calculated, and consensus levels were rated on a scale of 1 to 10. Results: Five patient cases were discussed resulting in 105 recommendations. Agreement percentages for case 1 to 5 were 14.3%, 61.9%, 33.3%, 52.4% and 9.3%, with a median agreement percentage of 33.3%. Grouping pre- and postoperative therapies as "perioperative" and including recommendations with and without regional hyperthermia raised the median agreement to 47.6%. The mean consensus level within each center across all 5 cases was 9.5. Conclusion: This first case-based analysis of inter-center agreement for STS management in German-speaking countries reveals low inter-center agreement but high intra-center consensus. Our study includes nearly all tertiary sarcoma centers in German-speaking countries, affirming its strong external validity. These findings suggest potential and clinically very relevant differences in treatment standards among sarcoma centers. Enhanced case-based exchanges and collaborative efforts are needed to reduce discrepancies and standardize the management of STS patients.
CRIS-Team Scopus Importer:2025-01-31
Keywords: German Cancer Society; Guidelines; Inter-center agreement; Reference center; Ring trial; Soft tissue sarcoma

The Songdo consensus: Development of minimum reporting standards for studies of intervention in idiopathic anal fistula using a modified nominal group technique - Joshi, Shivani; Hanna, Luke; Cho, Dong Ho; Garg, Pankaj; Glyn, Tamara; Gurland, Brooke; Hwang, Do Yeon; Kim, Kiduk; Kotze, Paulo Gustavo; Lee, Jong Kyun; Lightner, Amy L.; Matzel, Klaus; et al. (Colorectal Disease, 2025)
Aim: Cryptoglandular anal fistulas carry a substantial burden to quality of life. Surgery is the only effective curative treatment but requires balancing fistula healing against pain, wounds and continence impairment. Sphincter-preserving procedures do exist but demonstrate variable rates of success. A lack of consistency and precision in outcome reporting and methodological quality hinders effective evidence-based decision-making. We aimed to establish a series of minimum reporting standards for interventional studies in idiopathic anal fistula, to eradicate low-quality studies, thus providing a consistent baseline of useful evidence. Methods: An international group of 16 experts participated in a modified nominal group technique consensus. The nominal question was: ‘What should be the minimum set of reporting standards for studies of intervention in idiopathic anal fistula?’ The process was conducted between May and June 2023, culminating in a hybrid in-person/virtual meeting that took place at the Songdo International Proctology Symposium in June 2023. Results: Initial idea generation resulted in 37 statements within the first round. Themes included variable reporting of follow-up and incontinence. Participants indicated their agreement via a 9-point Likert scale. Any statement achieving >70% consensus was retained. Subsequent group discussion condensed the list to 11 statements for further voting and a final minimum set of 12 reporting standards was created. Conclusion: To date, this is the first study dedicated to developing minimum reporting standards for interventional studies in idiopathic anal fistula using a modified nominal group technique. These standards will instruct researchers in producing meticulous, high-quality studies that are accurate, transparent and reproducible.
CRIS-Team Scopus Importer:2025-01-31
Keywords: anal fistula; cryptoglandular anal fistula; idiopathic anal fistula; minimum reporting standards; nominal group technique

The Tat protein of human immunodeficiency virus type-1 promotes vascular cell growth and locomotion by engaging the alpha5beta1 and alphavbeta3 integrins and by mobilizing sequestered basic fibroblast growth factor. - Barillari, Giovanni; Sgadari, Cecilia; Fiorelli, V; Samaniego, F; Colombini, S; Manzari, Vittorio; Modesti, A; Nair, B. C.; Cafaro, Aurelio; Stürzl, Michael; Ensoli, Barbara (Blood, 1999)
The Tat protein of human immunodeficiency virus type-1 (HIV-1) has been shown to be released during acute infection of T cells by HIV-1 and to promote angiogenesis and Kaposi's sarcoma (KS) development in infected individuals. In this study, we investigated the molecular mechanisms responsible for the angiogenic effects of Tat. The results shown herein indicate that two different Tat domains cooperate to induce these effects by different pathways. The arginine-glycine-aspartic acid (RGD) sequence present at the carboxyterminal of Tat mediates vascular cell migration and invasion by binding to the alpha5beta1 and alphavbeta3 integrins. This interaction also provides endothelial cells with the adhesion signal they require to grow in response to mitogens. At the same time, the Tat basic sequence retrieves into a soluble form extracellular basic fibroblast growth factor (bFGF) bound to heparan sulfate proteoglycans by competing for heparin-binding sites. This soluble bFGF mediates Tat-induced vascular cell growth. These effects resemble those of extracellular matrix proteins, suggesting that Tat enhances angiogenesis and promotes KS progression by a molecular mimicry of these molecules.

The transcription factor GLI2 as a downstream mediator of transforming growth factor-?-induced fibroblast activation in SSc - Liang, Ruifang; Sumova, Barbora; Cordazzo, Cinzia; Mallano, Tatjana; Zhang, Yun; Wohlfahrt, Thomas; Dees, Clara; Krasowska, Dorota; Michalska-Jakubus, Malgorzata; Distler, Oliver; Schett, Georg; Senolt, Ladislav; et al. (Annals of the Rheumatic Diseases, 2016)
Hedgehog signalling plays a critical role during the pathogenesis of fibrosis in systemic sclerosis (SSc). Besides canonical hedgehog signalling with smoothened (SMO)-dependent activation of GLI transcription factors, GLI can be activated independently of classical hedgehog ligands and receptors (so-called non-canonical pathways). Here, we aimed to evaluate the role of non-canonical hedgehog signalling in SSc and to test the efficacy of direct GLI inhibitors that target simultaneously canonical and non-canonical hedgehog pathways.The GLI inhibitor GANT-61 was used to inhibit canonical as well as non-canonical hedgehog signalling, while the SMO inhibitor vismodegib was used to selectively target canonical hedgehog signalling. Furthermore, GLI2 was selectively depleted in fibroblasts using the Cre-LoxP system. The effects of pharmacological or genetic of GLI2 on transforming growth factor-? (TGF-?) signalling were analysed in cultured fibroblasts, in bleomycin-induced pulmonary fibrosis and in mice with overexpression of a constitutively active TGF-? receptor I.TGF-? upregulated GLI2 in a Smad3-dependent manner and induced nuclear accumulation and DNA binding of GLI2. Fibroblast-specific knockout of GLI2 protected mice from TBR(act)-induced fibrosis. Combined targeting of canonical and non-canonical hedgehog signalling with direct GLI inhibitors exerted more potent antifibrotic effects than selective targeting of canonical hedgehog signalling with SMO inhibitors in experimental dermal and pulmonary fibrosis.Our data demonstrate that hedgehog pathways and TGF-? signalling both converge to GLI2 and that GLI2 integrates those signalling to promote tissue fibrosis. These findings may have translational implications as non-selective inhibitors of GLI2 are in clinical use and selective molecules are currently in development.
EVALuna2:13344

The use of single-stapling techniques reduces anastomotic complications in minimal-invasive rectal surgery - Brunner, Maximilian; Zu'bi, Alaa; Weber, Klaus; Denz, Axel; Langheinrich, Melanie; Kersting, Stephan; Grützmann, Robert; Krautz, Christian; Weber, Georg (International Journal of Colorectal Disease, 2022)
Background Leakage of rectal anastomoses is one of the most important and feared complications in colorectal surgery. Apart from patient-specific risk factors, technical aspects may influence the occurrence of anastomotic complications. This study investigated whether using single-stapling techniques (SST) instead of the double-stapling technique (DST) for minimal-invasive rectal anastomosis is associated with a lower rate of anastomotic complications. Methods A retrospective review of 272 patients who received a minimally invasive stapled rectal anastomosis (3-16 cm from the anal verge) at our institution from 2015 to 2020 was performed. In 131 patients, rectal anastomosis was created by SST (SST group), while 141 patients received a rectal anastomosis with crossing stapler lines (DST group). The impact of the anastomotic technique on patient outcomes was determined by uni- and multivariate analyses. Results Overall anastomotic leakage rate was 6%. Patients with SST anastomoses had a lower leakage rate than patients with DST anastomoses (3% vs. 9% in the DST group, p = 0.045). The rate of anastomotic stenosis was lower in the SST group than in the DST group (1% vs. 6%, p = 0.037). Overall morbidity and mortality did not differ between the two groups. Multivariate analysis showed that single-stapling techniques significantly reduce the risk of anastomotic leakage (OR 3.5 [1.0-11.5], p = 0.043). Conclusion The use of SST for rectal anastomosis may help to reduce anastomotic complications. This finding should be confirmed by a randomized controlled trial.
CRIS-Team WoS Importer:2022-07-01

The viral interferon-regulatory factor-3 is required for the survival of KSHV-infected primary effusion lymphoma cells. - Wies, Effi; Mori, Yasuko; Hahn, Alexander; Kremmer, Elisabeth; Stürzl, Michael; Fleckenstein, Bernhard; Neipel, Frank (Blood, 2008)
Human herpesvirus-8 (HHV-8), also known as Kaposi sarcoma-associated herpesvirus (KSHV), is etiologically linked to primary effusion lymphoma (PEL). At least 10 KSHV-encoded proteins with potential roles in KSHV-associated neoplasia have been identified. However, with few exceptions, these putative oncogenes were analyzed in heterologous systems only using overexpression of single genes. Thus, the pathogenetic relevance of most of these putative oncogenes remains essentially unclear. We used RNA interference (RNAi) to knock down the expression of several KSHV genes in cultured PEL cells carrying the KSHV genome. The viral interferon-regulatory factor-3 (vIRF-3) was found to be required for proliferation and survival of cultured PEL cells. Knock-down of vIRF-3 expression by various RNAi approaches unequivocally resulted in reduced proliferation and increased activity of caspase-3 and/or caspase-7. Thus, vIRF-3 can be seen as a bona fide oncogene of KSHV-associated lymphoma. Surprisingly, although the related Epstein-Barr virus (EBV) is usually sufficient to immortalize human B lymphocytes, silencing of vIRF-3 reduced the viability of both EBV(-) and EBV(+) PEL cells. This suggests that KSHV is the driving force in the pathogenesis of PEL.

Time to Surgery Does Not Affect Overall or Disease-Free Survival of Patients with Primary Resectable PDAC - Jacobsen, Anne; Hobbs, Mirianna; Merkel, Susanne; Mittelstädt, Anke; Czubayko, Franziska; Krautz, Christian; Grützmann, Robert; Brunner, Maximilian; Weber, Georg (Journal of Clinical Medicine, 2022)
(1) Background: Delay in therapy for pancreatic ductal adenocarcinoma (PDAC) may contribute to a worse outcome. The aim of this study was to investigate the prognostic value of time from diagnosis to surgery in patients undergoing upfront surgery for primarily resectable pancreatic carcinoma. (2) Methods: This retrospective single-center study included 214 patients who underwent primary resection of PDAC from January 2000 to December 2018 at University Hospital Erlangen. Using a minimum p-value approach, patients were stratified according to time to surgery (TtS) into two groups: TtS <= 23 days and TtS > 23 days. Postoperative outcome and long-term survival were compared. (3) Results: Median TtS was 25 days. The best cut-off for TtS was determined as 23 days. There were no differences regarding postoperative outcome or overall survival (OS) and disease-free survival (DFS) (OS: 23.8 vs. 20.4 months, p = 0.210, respectively, and DFS: 15.8 vs. 13.6 months, p = 0.187). Multivariate analysis revealed age, lymph node metastasis, tumor differentiation and resection status as significant independent prognostic predictors for OS and DFS. (4) Conclusions: A delay of surgery > 23 days after first diagnosis does not affect overall or disease-free survival of patients with primary resectable PDAC. However, the psychological impact of a delay to patients waiting for surgery should not be underestimated.
CRIS-Team WoS Importer:2022-08-26

Total Pancreatectomy and Islet Autotransplantation in a Child with Recurrent Pancreatitis - Grützmann, Robert; Ludwig, B.; Weitz, J.; Ludwig, S. (Zentralblatt für Chirurgie, 2016)
Hereditary pancreatitis in children is rare. The indications for surgery in these children are complications and severe pain that cannot be managed by conservative treatment. Surgical treatment options are duodenum preserving resections as well as drainage procedures. Recurrences are common following theses surgical procedures, because usually the whole pancreas is affected. The majority of the children with symptomatic hereditary pancreatitis are free of pain after total pancreatectomy. When total pancreatectomy is combined with islet autotransplantation, pancreoprivic diabetes can be attenuated or even prevented. The principle of spleen-preserving total pancreatectomy combined with subsequent islet autotransplantation is shown in a case of a 10-year-old child with chronic recurrent pancreatitis in this video.Symptomatic chronic hereditary pancreatitis in children.Spleen-preserving total pancreatectomy, reconstruction with hepatico-jejunostomy and duodeno-jejunostomy, islet autotransplantation via portal vein.If the surgeon has appropriate experience, spleen-preserving total pancreatectomy is a safe procedure. In combination with islet autotransplantation, it may attenuate or prevent diabetes mellitus associated with total pancreatectomy. In highly selected pediatric patients, this surgical procedure has a major benefit compared to a purely symptomatic therapy.
EVALuna2:15256

Transcriptional activation of endogenous retroviral sequences in human epidermal keratinocytes by UVB irradiation. - Hohenadl, Christine; Germaier, Herbert; Walchner, Monika; Hagenhofer, Manuela; Herrmann, Martin; Stürzl, Michael; Kind, Peter; Hehlmann, Ruediger; Erfle, Volker; Leib-Mösch, Christine (Journal of Investigative Dermatology, 1999)
Ultraviolet radiation is a pathogenic factor in various diseases, e. g., autoimmune disorders such as lupus erythematosus. On the other hand, endogenous retroviruses are discussed as etiologic agents in lupus erythematosus. Therefore, we investigated the influence of ultraviolet irradiation on expression of human endogenous retroviral sequences and human endogenous retroviral sequence promoter-driven transcription of cellular genes using human epidermal keratinocytes as a model system. First, conserved sequences of endogenous retroviral pol genes were amplified from cellular mRNA by reverse transcriptase polymerase chain reaction with degenerate oligonucleotide primers. Polymerase chain reaction products were hybridized in a reverse dot blot hybridization assay to a representative number of distinct cloned human endogenous retroviral pol fragments. Using this method, we could show that irradiation with 30 mJ per cm2 ultraviolet B activates transcription of various endogenous retroviral pol sequences in primary epidermal keratinocytes as well as in a spontaneously immortalized keratinocyte cell line (HaCaT). Interestingly, some of these sequences were found to be closely related to pol sequences of human endogenous retroviral sequences which have been shown to be expressed in autoimmune patients. Analysis of human endogenous retroviral pol expression in vivo using skin biopsies of lupus erythematosus patients revealed similar activation patterns. In a second approach, ultraviolet B- induced chimeric transcripts were isolated which are initiated by human endogenous retroviral promoters and proceed into cellular sequences using a newly established modified differential display polymerase chain reaction technique. The activation of human endogenous retroviral sequence transcription by ultraviolet B may contribute to the pathogenesis of lupus erythematosus, where inappropriate antigenic presentation of ultraviolet B-induced viral and cellular proteins could stimulate autoantibody production.
Keywords: autoantigens; differential display polymerase chain reaction; lupus erythematosus; reverse dot blot hybridization

Transcription pattern of human herpesvirus 8 open reading frame K3 in primary effusion lymphoma and Kaposi's sarcoma. - Rimessi, Paola; Bonaccorsi, Angela; Stürzl, Michael; Fabris, Marina; Brocca-Cofano, Egidio; Caputo, Antonella; Melucci-Vigo, Gianna; Falchi, Mario; Cafaro, Aurelio; Cassai, Enzo; Ensoli, Barbara; Monini, Paolo (Journal of Virology, 2001)
Human herpesvirus 8 (HHV-8) is found in immunoblastic B cells of patients with multicentric Castleman's disease (MCD) and, predominantly in a latent form, in primary effusion lymphoma (PEL) cells and Kaposi's sarcoma (KS) spindle cells. Recent studies have shown that upon reactivation, HHV-8 expresses factors that downregulate major histocompatibility class I proteins and coactivation molecules and that may enable productively infected cells to escape cytotoxic T lymphocytes and natural killer cell responses. One of these viral factors is encoded by open reading frame (ORF) K3. Here we show that in PEL cells, ORF K3 is expressed through viral transcripts that are induced very early upon virus reactivation, including bicistronic RNA molecules containing coding sequences from viral ORFs K3 and 70. Specifically, we found that a bicistronic transcript was expressed in the absence of de novo protein synthesis, thereby identifying a novel HHV-8 immediate-early gene product. Several features of the RNA molecules encoding the K3 product, including multiple transcriptional start sites, multiple donor splicing sites, and potential alternative ATG usage, suggest that there exists a finely tuned modulation of ORF K3 expression. By contrast, ORF K3 transcripts are not detected in the majority of cells present in KS lesions that are latently infected by the virus, suggesting that there are other, as-yet-unknown mechanisms of immune evasion for infected KS spindle cells. Nevertheless, because HHV-8 viremia precedes the development of KS lesions and is associated with the recrudescence of MCD symptoms, the prompt expression of ORF K3 in productively infected circulating cells may be important for virus pathogenesis. Thus, molecules targeting host or viral factors that activate ORF K3 expression or inactivate the biological functions of the K3 product should be exploited for the prevention or treatment of HHV-8-associated diseases in at-risk individuals.

Transverse Incision for Pancreatoduodenectomy Reduces Wound Complications: A Single-Center Analysis of 399 Patients - Junker, Stefanie; Jacobsen, Anne; Merkel, Susanne; Denz, Axel; Krautz, Christian; Weber, Georg; Grützmann, Robert; Brunner, Maximilian (Journal of Clinical Medicine, 2023)
Background: Even if the minimally invasive approach is advancing in pancreatic surgery, the open approach is still the standard for a pancreatoduodenectomy. There are two types of incisions used: the midline incision (MI) and transverse incision (TI). The aim of this study was to compare these two incision types, especially regarding wound complications. Methods: A retrospective review of 399 patients who underwent a pancreatoduodenectomy at the University Hospital Erlangen between 2012 and 2021 was performed. A total of 169 patients with MIs were compared with 230 patients with TIs, with a focus on postoperative fascial dehiscence, postoperative superficial surgical site infection (SSSI) and the occurrence of incisional hernias during follow-up. Results: Postoperative fascial dehiscence, postoperative SSSI and incisional hernias occurred in 3%, 8% and 5% of patients, respectively. Postoperative SSSI and incisional hernias were significantly less frequent in the TI group (SSI: 5% vs. 12%, p = 0.024; incisional hernia: 2% vs. 8%, p = 0.041). A multivariate analysis confirmed the TI type as an independent protective factor for the occurrence of SSSI and incisional hernias (HR 0.45 (95% CI = 0.20–0.99), p = 0.046 and HR 0.18 (95% CI = 0.04–0.92), p = 0.039, respectively). Conclusion: Our data suggest that the transverse incision for pancreatoduodenectomy is associated with reduced wound complications. This finding should be confirmed by a randomized controlled trial.
CRIS-Team Scopus Importer:2023-05-12
Keywords: fascial dehiscence; incisional hernia; midline incision; pancreatoduodenectomy; surgical site infection; transverse incision

Treatment and Prognosis of the Oldest Old with Colorectal Cancer - Denz, Axel; Kohl, Valerie; Weber, Klaus; Langheinrich, Melanie; Schellerer, Vera; Merkel, Susanne; Grützmann, Robert (Zentralblatt für Chirurgie, 2018)
INTRODUCTION: The demographic trend will lead to an increase of elderly persons in Germany in the future. The population is becoming smaller and older because of the deficiency in childbirths. This results in demographic ageing of the population in Germany. Studies addressing patients ≥ 85 years, the oldest old, are becoming more and more important. MATERIALS AND METHODS: The prospectively collected data of 141 patients ≥ 85 years with colorectal carcinoma treated between 1995 and 2014 were analysed retrospectively. Treatment, complications and prognosis were compared with a historical group of patients ≥ 85 years treated previously between 1978 and 1994 (n = 57) and with a less old group of patients 75 - 84 years old treated between 1995 and 2014 (n = 726). RESULTS: The cohort consisted of 64 men and 77 women. 88 patients had colon carcinoma, 53 patients rectal carcinoma. 127 patients were treated with tumour resection; 112 were classified as R0. Compared with the historical cohort (1978 - 1994), the number of patients increased, and more patients were given tumour resection (74 vs. 90%, p = 0.003) and fewer patients had synchronous distant metastases (28 vs. 14%, p = 0.015). The 5-year locoregional recurrence rate after curative resection decreased from 11.5 to 1.4% (p = 0.027). Comparison with the younger age group (75 - 84 years) revealed more women (55 vs. 42.3%, p = 0.007), more emergencies (22 vs. 9.8%, p < 0.001) and less frequent neoadjuvant treatment (11 vs. 3%, p = 0.003). Morbidity (41 vs. 31.2%, p = 0.032) and mortality (16 vs. 5%, p < 0.001) were higher in the oldest old. After curative resection and exclusion of postoperative deaths, overall survival (2-year rate 66.4%, 5-year rate 32.9%) was found to be worse than for the less old group, whereas cancer-related survival (2-year rate 93.1%, 5-year rate 86.7%) was similar. CONCLUSION: The number of oldest old patients ≥ 85 years with colorectal carcinoma will further increase. These patients have a higher risk of postoperative complications. After recovering from the surgery cancer-related survival is not worse than for less old patients.
EVALuna2:210714

Treatment of locoregional recurrent colon cancer - Handtrack, Claudia; Weber, Klaus; Merkel, Susanne; Grützmann, Robert; Denz, Axel (Coloproctology, 2022)
The local recurrence rate of colon cancer could be markedly reduced after complete mesocolic excision (CME) criteria were implemented in oncological surgery. Risk factors for local recurrence include incomplete resection as well as the site of the primary tumor and locally or lymph node advanced tumors (pT4/pN2). Further risk factors are emergency operations and postoperative complications, particularly anastomotic leakage. The outcome of local recurrent colon cancer is decisively influenced by the resectability. In cases of a curative R0 resection, possibly including neoadjuvant therapy or multivisceral resections, a 5-year survival rate of over 50% can be achieved.
CRIS-Team WoS Importer:2022-05-27
Keywords: Colorectal cancer; Local recurrence; R0 resection; Staging; Prognosis

Tumor-associated fibroblasts isolated from colorectal cancer tissues exhibit increased ICAM-1 expression and affinity for monocytes - Schellerer, Vera; Langheinrich, Melanie; Hohenberger, Werner; Croner, Roland S.; Merkel, Susanne; Rau, Tilman; Stürzl, Michael; Naschberger, Elisabeth (Oncology Reports, 2014)
Progression of colorectal cancer (CRC) is strongly associated with inflammation and other desmoplastic reactions in the tumor cell-surrounding tissue. We successfully isolated fibroblasts from the desmoplastic stroma of human CRC specimens and uninvolved colon tissue of patients treated surgically for CRC and investigated potential functional capacities. All of the isolated fibroblasts were vimentin-positive and CK-20/CD45-negative confirming the fibroblast phenotype. Differential expression patterns were detected between tumor-associated fibroblasts (TAFs) and normal tissue-associated fibroblasts (NAFs) regarding intercellular adhesion molecule-1 (ICAM-1) expression. In 11 of 12 TAF cultures, basal ICAM-1 expression was increased as compared to corresponding NAF cultures (p=0.001). After stimulation of the cultures with interleukin-1?, 8 of the 12 TAF cultures presented higher ICAM-1 levels when compared with the level in the corresponding NAF cultures (p=0.001). Moreover, the adhesive capacity of these cultures for U937 was increased in 8 out of 10 unstimulated and in 10 out of 10 stimulated cultures when TAFs and NAFs were compared. In corresponding tumor tissue sections from the same patients, the amount of ICAM-1-positive fibroblasts was significantly higher than that in the corresponding normal colon mucosa, indicating a tumor-specific effect that was maintained in the isolated cultures. These results indicate that fibroblasts from CRC tissue exhibit an increased affinity for monocytic cells. This increased intercellular interaction may contribute to elongated residence times of monocytes in CRC tissue. Therefore, these isolated fibroblasts are a useful tool for further functional investigation of desmoplastic tissue reactions in CRC.
EVALuna2:6524

Tumor Infiltration with CD20+CD73+ B Cells Correlates with Better Outcome in Colorectal Cancer - Hansen, Frederik; Wu, Zhiyuan; David, Paul; Mittelstädt, Anke; Jacobsen, Anne; Podolska, Malgorzata; Ubieta Hernández, Kenia; Brunner, Maximilian; Kouhestani, Dina; Swierzy, Izabela; Roßdeutsch, Lotta; Klösch, Bettina; et al. (International Journal of Molecular Sciences, 2022)
Immunotherapy has become increasingly important in the treatment of colorectal cancer (CRC). Currently, CD73, also known as ecto-5′-nucleotidase (NT5E), has gained considerable interest as a potential therapeutic target. CD73 is one of the key enzymes catalyzing the conversion of extracellular ATP into adenosine, which in turn exerts potent immune suppressive effects. However, the role of CD73 expression on various cell types within the CRC tumor microenvironment remains unresolved. The expression of CD73 on various cell types has been described recently, but the role of CD73 on B-cells in CRC remains unclear. Therefore, we analyzed CD73 on B-cells, especially on tumor-infiltrating B-cells, in paired tumor and adjacent normal tissue samples from 62 eligible CRC patients. The highest expression of CD73 on tumor-infiltrating B-cells was identified on classswitched memory B-cells, followed by naive B-cells, whereas no CD73 expression was observed on plasmablasts. Clinicopathological correlation analysis revealed that higher CD73+ B-cells infiltration in the CRC tumors was associated with better overall survival. Moreover, metastasized patients showed a significantly decreased number of tumor-infiltrating CD73+ B-cells. Finally, neoadjuvant therapy correlated with reduced CD73+ B-cell numbers and CD73 expression on B-cells in the CRC tumors. As promising new immune therapies are being developed, the role of CD73+ B-cells and their subsets in the development of colorectal cancer should be further explored to find new therapeutic options.
CRIS-Team Scopus Importer:2022-05-20
Keywords: B-cells; CD20; CD73; colorectal cancer; neoadjuvant treatment

Tumor microenvironment-dependent epigenetic imprinting in the vasculature predicts colon cancer outcome - Naschberger, Elisabeth; Fuchs, Maximilian; Dickel, Nicholas; Kunz, Meik; Popp, Bernt; Anchang, Charles Gwellem; Demmler, Richard; Lyu, Yanmin; Uebe, Steffen; Ekici, Arif Bülent; Geppert, Carol-Immanuel; Hartmann, Arndt; et al. (Cancer Communications, 2023)
CRIS-Team Scopus Importer:2023-10-27

Two Years of tranSMART in a University Hospital for Translational Research and Education - Christoph, Jan; Knell, Christian; Naschberger, Elisabeth; Stürzl, Michael; Maier, Christian; Prokosch, Hans-Ulrich; Sedlmayr, Martin (Studies in health technology and informatics, 2017)
For translational research, software platforms such as tranSMART with an integrated view of both clinical and omics data have gained more and more attention in the last years.We wanted to examine the success and failures of tranSMART in the fields of translational research and education by looking at the examples of six use cases at our hospital. We wanted to point out suitable scenarios and user groups as well as still existing challenges and limitations.We sum up the experience we made with our use cases with a focus on lessons learned.tranSMART was successfully established by a bottom-up approach at our university hospital and has been running for more than two years now. It has been used in four translational research projects as well as in education in the context of lectures and bachelor/master theses.tranSMART can be a very useful tool for translational research and education. But it should be used with both care and statistical knowledge to avoid wrong conclusions. Some technical constraints, especially for data modeling, still limit many applications. Version control and data provenance are remaining challenges.
EVALuna2:187

Two years of tranSMART in a university hospital for translational research and education - Christoph, Jan; Knell, Christian; Naschberger, Elisabeth; Stürzl, Michael; Maier, Christian; Prokosch, Hans-Ulrich; Sedlmayr, Martin (Health informatics meets eHealth: Digital insight information-driven health & care; proceedings of the 11th eHealth2017 Conference, 2017)
UnivIS-Import:2018-09-11:Pub.2017.tech.IMMD.infome.twoyea
Keywords: Biomedical research; Medical education; Research personnel; Translational medical research

Überblick über Subtypen und Therapien der akuten Mesenterialischämie - Eckhardt, Daniel; Schmid, Axel; Grützmann, Robert (Zentralblatt für Chirurgie, 2019)
CRIS-Team Scopus Importer:2019-06-28

Unique features of different members of the human guanylate-binding protein family - Tripal, Philipp; Bauer, Michael; Naschberger, Elisabeth; Mörtinger, Thomas; Hohenadl, Christine; Cornali, Emmanuelle; Thurau, Mathias; Stürzl, Michael (Journal of Interferon and Cytokine Research, 2007)
Guanylate-binding proteins (GBPs) are the most abundant cellular proteins expressed in response to interferon-γ (IFN-γ), with seven highly homologous members in humans, termed HuGBP-1 to HuGBP-7. To date, differential features that may indicate differential functions of these proteins have not been described. Here, we investigated the expression and subcellular localization of the different HuGBPs in endothelial cells (EC). IFN-γ, tumor necrosis factor-α (TNF-α), and interleukin-1β (IL-1β) induced the expression of HuGBP-1, HuGBP-2, and HuGBP-3 at similar high levels. In contrast, expression of HuGBP-4 and HuGBP-5 was robustly induced only by IFN-γ and not by TNF-α and IL-1β. Expression of HuGBP-6 and HuGBP-7 was not detected in EC under the various conditions examined. Investigating subcellular localization of the EC-expressed HuGBPs, HuGBP-1, HuGBP-3, and HuGBP-5 were exclusively detected in the cytoplasm, whereas HuGBP-2 and HuGBP-4 displayed a nucleocytoplasmic distribution. Treatment of the cells with IFN-γ and aluminum fluoride caused rapid enrichment of HuGBP-1 and HuGBP-2 in the Golgi apparatus, as demonstrated by time-lapse microscopy and fluorescence analyses of GFP-tagged HuGBPs. HuGBP-3 and HuGBP-4 were never detected in the Golgi apparatus, whereas HuGBP-5 was constitutively enriched in this cytosolic compartment, irrespective of stimulation. These results assign a characteristic pattern of expression and subcellular localization to each of the HuGBPs, indicating for the first time that these proteins may have different cellular functions. © Mary Ann Liebert, Inc.
Created from Fastlane, Scopus look-up

Unusual Manifestation of Live Staphylococcus saprophyticus, Corynebacterium urinapleomorphum, and Helicobacter pylori in the Gallbladder with Cholecystitis - Backert, Steffen; Tegtmeyer, Nicole; Oyarzabal, Omar A.; Osman, Dana; Rohde, Manfred; Grützmann, Robert; Vieth, Michael (International Journal of Molecular Sciences, 2018)
Culture-independent studies have identified DNA of bacterial pathogens in the gallbladder under pathological conditions, yet reports on the isolation of corresponding live bacteria are rare. Thus, it is unclear which pathogens, or pathogen communities, can colonize the gallbladder and cause disease. Using light microscopy, scanning electron microscopy, culture techniques, phylogenetic analysis, urease assays and Western blotting, we investigated the presence of live bacterial communities in the gallbladder of a cholecystitis patient after cholecystectomy. 16S rRNA gene sequencing of isolated bacterial colonies revealed the presence of pathogens most closely resembling Corynebacterium urinapleomorphum nov. sp., Staphylococcus saprophyticus and Helicobacter pylori. The latter colonies were confirmed as H. pylori by immunohistochemistry and biochemical methods. H. pylori cultured from the gallbladder exhibited both the same DNA fingerprinting and Western cagA gene sequence with ABC-type EPIYA (Glu-Pro-Ile-Tyr-Ala) phosphorylation motifs as isolates recovered from the gastric mucus of the same patient, suggesting that gastric H. pylori can also colonize other organs in the human body. Taken together, here we report, for the first time, the identification and characterization of a community consisting of live S. saprophyticus; C. urinapleomorphum, and H. pylori in the gallbladder of a patient with acute cholecystitis. Their potential infection routes and roles in pathogenesis are discussed.
EVALuna2:210710

Update on neuromodulation for fecal incontinence - Matzel, Klaus (Annals of Laparoscopic and Endoscopic Surgery, 2022)
Sacral neuromodulation (SNM) is an established surgical therapy for fecal incontinence (PI). The spectrum of indications has evolved over the last two decades. The role of SNM is the surgical treatment algorithm for FI is now central. Currently, the indications include a wide variety of pathophysiological and pathomorphological causes of FI, but also reach beyond FI to include complex conditions such as low anterior resection syndrome (LARS) and patients with concomitant evacuation disorders. The technique's minimal invasiveness, low risk and low comorbidity contributed to its success and increased acceptance, as did the option of a therapeutic test and a robust patient selection-patients are selected for chronic stimulation by a pragmatic approach, based on the clinical outcome of a highly predictive value of trial stimulation if positive-its sustained clinical efficacy, and reproducible outcomes. TO further improve the outcome of SNM, both for the test stimulation and the chronic stimulation, crucial elements of the therapy such as electrode placement, programming, and reprogramming have been revisited and standardized. This article addresses the scope of indications, highlights the reevaluation and standardization of the implant technique and updates on recent guidance for programming and troubleshooting. The standardization should lead to fewer side effects, more programming options, less battery consumption with increased battery longevity, and improved clinical outcome.
CRIS-Team WoS Importer:2022-06-10

Upregulation of CD20 positive B-cells and B-cell aggregates in the tumor infiltration zone is associated with better survival of patients with pancreatic ductal adenocarcinoma - Brunner, Maximilian; Maier, Katharina; Rümmele, Petra; Jacobsen, Anne; Merkel, Susanne; Benard, Alan; Krautz, Christian; Kersting, Stephan; Grützmann, Robert; Weber, Georg (International Journal of Molecular Sciences, 2020)
Patients with pancreatic ductal adenocarcinoma (PDAC) normally have a poor long-term prognosis. However, some rare cases of long-term survivors have been reported. The tumor microenvironment, consisting of cellular and stromal components, possibly plays an important role and might influence prognosis. In this context, the role of tumor-infiltrating B-cells and its impact on the survival in patients with PDAC remains controversial. We therefore aimed to assess the prognostic value of CD20-positive B-cells and CD20-positive B-cell aggregates as well as CD138, IgM, Pax5, and Ki67 on the survival of patients with PDAC using immunohistochemistry of FFPE pancreatectomy tissue sections from patients that underwent primary surgery for pT3-and R0-pancreatic adenocarcinoma between 1995 and 2016. Patients with PDAC were matched and grouped in 16 long-term-survivors (LTS, median overall survival (OS): 96 months [range: 61–177 months]) and 16 short-term-survivors (STS, median OS: 16 months [range: 7–32 months]). CD20-positive B-cells and B-cell aggregates in the tumor infiltration zone were significantly upregulated in the LTS-group compared to the STS-group (p = 0.0499 respectively p = 0.0432). Regarding the entire patient cohort (n = 32) CD20 positive B-cell aggregates in the tumor infiltration zone were an independent prognostic marker for overall survival in multivariate analysis (HR 9.2, CI 1.6–51.4, p = 0.012). These results underline the importance of tumor-associated B-cells for prognosis of patients with PDAC. The detailed role of B cells in the pathomechanism of PDAC should be further investigated for predicting outcome, identifying appropriate treatment regimens, and developing novel therapeutic options.
CRIS-Team Scopus Importer:2020-03-17
Keywords: B-cell aggregates; B-cells; CD20; Pancreatic ductal adenocarcinoma; Survival

Usability and Suitability of the Omics-Integrating Analysis Platform tranSMART for Translational Research and Education - Christoph, Jan; Knell, Christian; Boßerhoff, Anja Katrin; Naschberger, Elisabeth; Stürzl, Michael; Rübner, Matthias; Seuß, Hannes; Ruh, Manuel; Prokosch, Hans-Ulrich; Sedlmayr, Brita (Applied Clinical Informatics, 2017)
Platforms like tranSMART assist researchers in analyzing clinical and corresponding omics data. Usability is an important, yet often overlooked, factor affecting the adoption and meaningful use. Analyses on the specific needs of translational researchers and considerations about the application of such platforms for education are rare. The aim of this study was to test whether tranSMART can be used in education and how well medical students and professional researchers can handle it; to identify which kind of translational researchers-in terms of skills, experienced limitations, and available data-can take advantage of tranSMART; and to evaluate the usability and to generate recommendations for improvements. An online-based test has been done by medical students (N = 109) and researchers (N = 26). The test comprised 13 tasks in the context of four typical research scenarios based on experimental and clinical data. A web questionnaire was provided to identify both the needs and the conditions of research as well as to evaluate the system's usability based on the "System Usability Scale" (SUS). Students and researchers were able to handle tranSMART well and coped with most scenarios: cohort identification, data exploration, hypothesis generation, and hypothesis validation were answered with a rate of correctness between 82 and 100%. Of the total, 72.2% of the teaching researchers considered tranSMART suitable for their lessons and 84.6% of the researchers considered the platform useful for their daily work; 65.4% of the researchers named the nonavailability of a platform like tranSMART as a restriction on their research. The usability was rated "acceptable" with a SUS of 70.8. tranSMART is potentially suitable for education purposes and fits most of the needs of translational researchers. Improvements are needed on the presentation of analysis results and on the guidance of users through the analysis, especially to ensure the compliance of the analysis with the requirements of statistical testing.
EVALuna2:195

Validation of the reliability of computational O-GlcNAc prediction - Jochmann, Ramona; Holz, Patrick; Sticht, Heinrich; Stürzl, Michael (Biochimica Et Biophysica Acta-Proteins and Proteomics, 2014)
O-GlcNAcylation is an inducible, highly dynamic and reversible posttranslational modification, which regulates numerous cellular processes such as gene expression, translation, immune reactions, protein degradation, protein-protein interaction, apoptosis, and signal transduction. In contrast to N-linked glycosylation, O-GlcNAcylation does not display a strict amino acid consensus sequence, although serine or threonine residues flanked by proline and valine are preferred sites of O-GlcNAcylation. Based on this information, computational prediction tools of O-GlcNAc sites have been developed. Here, we retrospectively assessed the performance of two available O-GlcNAc prediction programs YinOYang 1.2 server and OGlcNAcScan by comparing their predictions for recently discovered experimentally validated O-GlcNAc sites. Both prediction programs efficiently identified O-GlcNAc sites situated in an environment resembling the consensus sequence P-P-V-[ST]-T-A. However, both prediction programs revealed numerous false negative O-GlcNAc predictions when the site of modification was located in an amino acid sequence differing from the known consensus sequence. By searching for a common sequence motif, we found that O-GlcNAcylation of nucleocytoplasmic proteins preferably occurs at serine and threonine residues flanked downstream by proline and valine and upstream by one to two alanines followed by a stretch of serine and threonine residues. However, O-GlcNAcylation of proteins located in the mitochondria or in the secretory lumen occurs at different sites and does not follow a distinct consensus sequence. Thus, our study indicates the limitations of the presently available computational prediction methods for O-GlcNAc sites and suggests that experimental validation is mandatory. Continuously update and further development of available databases will be the key to improve the performance of O-GlcNAc site prediction.
EVALuna2:15154

Vascular occlusion by neutrophil extracellular traps in COVID-19 - Leppkes, Moritz; Knopf, Jasmin; Naschberger, Elisabeth; Lindemann, Aylin; Singh, Jeeshan; Herrmann, Irmgard; Stürzl, Michael; Staats, Léonie; Mahajan, Aparna; Kremer, Anita; Amann, Kerstin Ute; Evert, Katja; et al. (EBioMedicine, 2020)
Background: Coronavirus induced disease 2019 (COVID-19) can be complicated by severe organ damage leading to dysfunction of the lungs and other organs. The processes that trigger organ damage in COVID-19 are incompletely understood. Methods: Samples were donated from hospitalized patients. Sera, plasma, and autopsy-derived tissue sections were examined employing flow cytometry, enzyme-linked immunosorbent assays, and immunohistochemistry. Patient findings: Here, we show that severe COVID-19 is characterized by a highly pronounced formation of neutrophil extracellular traps (NETs) inside the micro-vessels. Intravascular aggregation of NETs leads to rapid occlusion of the affected vessels, disturbed microcirculation, and organ damage. In severe COVID-19, neutrophil granulocytes are strongly activated and adopt a so-called low-density phenotype, prone to spontaneously form NETs. In accordance, markers indicating NET turnover are consistently increased in COVID-19 and linked to disease severity. Histopathology of the lungs and other organs from COVID-19 patients showed congestions of numerous micro-vessels by aggregated NETs associated with endothelial damage. Interpretation: These data suggest that organ dysfunction in severe COVID-19 is associated with excessive NET formation and vascular damage. Funding: Deutsche Forschungsgemeinschaft (DFG), EU, Volkswagen-Stiftung
CRIS-Team Scopus Importer:2020-08-14
Keywords: Aggregated neutrophil extracellular traps; Coagulopathy; Endothelialitis; Immunothrombosis; SARS-CoV-2

VEGFR2 Signaling Prevents Colorectal Cancer Cell Senescence to Promote Tumorigenesis in Mice With Colitis - Försch, Sebastian; Sperka, Tobias; Lindner, Christina; Taut, Astrid; Rudolph, Karl L.; Breier, Georg; Boxberger, Frank; Rau, Tilman; Hartmann, Arndt; Stürzl, Michael; Wittkopf, Nadine; Haep, Lisa; et al. (Gastroenterology, 2015)
Senescence prevents cellular transformation. We investigated whether vascular endothelial growth factor (VEGF) signaling via its receptor, VEGFR2, regulates senescence and proliferation of tumor cells in mice with colitis-associated cancer (CAC).CAC was induced in VEGFR2(?IEC) mice, which do not express VEGFR2 in the intestinal epithelium, and VEGFR2(fl/fl) mice (controls) by administration of azoxymethane followed by dextran sodium sulfate. Tumor development and inflammation were determined by endoscopy. Colorectal tissues were collected for immunoblot, immunohistochemical, and quantitative polymerase chain reaction analyses. Findings from mouse tissues were confirmed in human HCT116 colorectal cancer cells. We analyzed colorectal tumor samples from patients before and after treatment with bevacizumab.After colitis induction, VEGFR2(?IEC) mice developed significantly fewer tumors than control mice. A greater number of intestinal tumor cells from VEGFR2(?IEC) mice were in senescence than tumor cells from control mice. We found VEGFR2 to activate phosphatidylinositol-4,5-bisphosphate-3-kinase and AKT, resulting in inactivation of p21 in HCT116 cells. Inhibitors of VEGFR2 and AKT induced senescence in HCT116 cells. Tumor cell senescence promoted an anti-tumor immune response by CD8(+) T cells in mice. Patients whose tumor samples showed an increase in the proportion of senescent cells after treatment with bevacizumab had longer progression-free survival than patients in which the proportion of senescent tumor cells did not change before and after treatment.Inhibition of VEGFR2 signaling leads to senescence of human and mouse colorectal cancer cells. VEGFR2 interacts with phosphatidylinositol-4,5-bisphosphate-3-kinase and AKT to inactivate p21. Colorectal tumor senescence and p21 level correlate with patient survival during treatment with bevacizumab.
EVALuna2:1356

Ventral rectopexy with biological mesh for recurrent disorders of the posterior pelvic organ compartment - Brunner, Michaela; Roth, H.; Günther, K.; Grützmann, Robert; Matzel, Klaus E. (International Journal of Colorectal Disease, 2019)
PURPOSE: Recurrent prolapse of the posterior pelvic organ compartment presents a management challenge, with the best surgical procedure remaining unclear. We present functional outcome and patient satisfaction after laparoscopic and robotic ventral mesh rectopexy (VMR) with biological mesh in patients with recurrence. METHODS: We analyzed data from 30 patients with recurrent posterior pelvic organ prolapse who underwent VMR with biological mesh from August 2012 to January 2018. Data included patient demographics and intra- and postoperative findings; functional outcome as assessed by Cleveland Clinic Constipation Score (CCCS), Obstructed Defecation Score Longo (ODS), and Cleveland Clinic Incontinence Score (CCIS); and patient satisfaction. RESULTS: CCCS, CCIS, and ODS were significantly improved at 6-12 months postoperatively and at last follow-up. Patient satisfaction (visual analog scale [VAS] 6.7 [0 to 10]), subjective symptoms (+ 3.4 [scale - 5 to + 5]), and quality of life improvement (+ 3.0 [scale from - 5 to + 5]) were high at last follow-up. The rates of morbidity and major complications were 13% and 3%, respectively. There were no mesh-related complications or deaths. Difference in type of previous surgery (abdominal or transanal/perineal) had no significant effect on results. CONCLUSIONS: VMR with biological mesh is a safe and effective option for patients with recurrent posterior pelvic organ prolapse. It reduces functional symptoms, has a low complication rate, and promotes patient satisfaction.
CRIS-Team Scopus Importer:2019-10-01
Keywords: Biological mesh; Functional outcome; Laparoscopic ventral rectopexy; Recurrent posterior compartment prolapse; Recurrent rectal prolapse

Ventral rectopexy with biological mesh: short-term functional results - Brunner, Michaela; Roth, H.; Guenther, K.; Grützmann, Robert; Matzel, K. E. (International Journal of Colorectal Disease, 2018)
PURPOSE: Ventral mesh rectopexy (VMR) is an established, minimally invasive, nerve-sparing procedure for the treatment of various symptomatic morphological changes in the posterior pelvic compartment. We present the short-term functional outcome and patient satisfaction after laparoscopic and robotic VMR with biological mesh. METHODS: We analyzed data from 123 patients who underwent laparoscopic ventral mesh rectopexy (LVMR) or robotic ventral mesh rectopexy (RVMR) from August 2012 to January 2017. Included in these data were patient demographics, intra- and postoperative findings, Cleveland Clinic Constipation Score (CCCS), Obstructed Defecation Score Longo (ODS), Cleveland Clinic Incontinence Score (CCIS), and patient satisfaction as measured by visual analog scale (0-10). RESULTS: Improvements in CCCS, CCIS, and ODS were statistically significant at 6 and 12 months (p < 0.001). Patient satisfaction was excellent at 6 and 12 months (8.2/10 and 8.3/10, respectively). The overall complication rate was 14%, with a major complication rate of 2%. No mesh-related complications were observed. The need for surgical re-intervention because of relapse, symptom persistence or recurrence, or new symptoms was 3%. Outcome appears to be similar between LVMR and RVMR. CONCLUSIONS: Both LVMR and RVMR with biological mesh are safe and effective in reducing symptoms, as measured by CCCS, CCIS, and ODS, and patient satisfaction is high.
EVALuna2:212626

Viral FLIP blocks Caspase-8 driven apoptosis in the gut in vivo - Ruder, Barbara; Günther, Claudia; Stürzl, Michael; Neurath, Markus; Cesarman, Ethel; Ballon, Gianna; Becker, Christoph (PLoS ONE, 2020)
A strict cell death control in the intestinal epithelium is indispensable to maintain barrier integrity and homeostasis. In order to achieve a balance between cell proliferation and cell death, a tight regulation of Caspase-8, which is a key player in controlling apoptosis, is required. Caspase-8 activity is regulated by cellular FLIP proteins. These proteins are expressed in different isoforms (cFLIPlong and cFLIPshort) which determine cell death and survival. Interestingly, several viruses encode FLIP proteins, homologous to cFLIPshort, which are described to regulate Caspase-8 and the host cell death machinery. In the current study a mouse model was generated to show the impact of viral FLIP (vFLIP) from Kaposi's Sarcoma-associated Herpesvirus (KSHV)/ Human Herpesvirus-8 (HHV-8) on cell death regulation in the gut. Our results demonstrate that expression of vFlip in intestinal epithelial cells suppressed cFlip expression, but protected mice from lethality, tissue damage and excessive apoptotic cell death induced by genetic cFlip deletion. Finally, our model shows that vFlip expression decreases cFlip mediated Caspase-8 activation in intestinal epithelial cells. In conclusion, our data suggests that viral FLIP neutralizes and compensates for cellular FLIP, efficiently counteracting host cell death induction and facilitating further propagation in the host organism.
CRIS-Team Scopus Importer:2020-02-11

Viral inhibitor of apoptosis vFLIP/K13 protects endothelial cells against superoxide-induced cell death - Thurau, Mathias; Marquardt, Gaby; Britzen-Laurent, Nathalie; Weinlaender, Kristina; Naschberger, Elisabeth; Jochmann, Ramona; Alkharsah, Khaled R.; Schulz, Thomas F.; Thome, Margot; Neipel, Frank; Stürzl, Michael (Journal of Virology, 2009)
Human herpesvirus 8 (HHV-8) is the etiological agent of Kaposi's sarcoma (KS). HHV-8 encodes an antiapoptotic viral Fas-associated death domain-like interleukin-1β-converting enzyme-inhibitory protein (vFLIP/K13). The antiapoptotic activity of vFLIP/K13 has been attributed to an inhibition of caspase 8 activation and more recently to its capability to induce the expression of antiapoptotic proteins via activation of NF-κB. Our study provides the first proteome-wide analysis of the effect of vFLIP/K13 on cellular-protein expression. Using comparative proteome analysis, we identified manganese superoxide dismutase (MnSOD), a mitochondrial antioxidant and an important antiapoptotic enzyme, as the protein most strongly upregulated by vFLIP/K13 in endothelial cells. MnSOD expression was also upregulated in endothelial cells upon infection with HHV-8. Microarray analysis confirmed that MnSOD is also upregulated at the RNA level, though the differential expression at the RNA level was much lower (5.6-fold) than at the protein level (25.1-fold). The induction of MnSOD expression was dependent on vFLIP/K13-mediated activation of NF-κB, occurred in a cell-intrinsic manner, and was correlated with decreased intracellular superoxide accumulation and increased resistance of endothelial cells to superoxide-induced death. The upregulation of MnSOD expression by vFLIP/K13 may support the survival of HHV-8-infected cells in the inflammatory microenvironment in KS. Copyright © 2009, American Society for Microbiology. All Rights Reserved.
Created from Fastlane, Scopus look-up

Von der Deutschen Gesellschaft für Allgemein- und Viszeralchirurgie konsentierte Operationsindikationen beim duktalen Pankreasadenokarzinom - Belyaev, Orlin; Bösch, Florian; Brunner, Maximilian; Müller-Debus, Charlotte Friederieke; Radulova-Mauersberger, Olga; Wellner, Ulrich Friedrich; Grützmann, Robert; Keck, Tobias; Werner, Jens; Witzigmann, Helmut; Uhl, Waldemar (Zentralblatt für Chirurgie, 2020)
Background Surgery for pancreatic cancer in Germany is increasing due to the climbing incidence of this cancer in the population. This review presents a summary of modern evidence-based indications for surgery in patients with pancreatic ductal adenocarcinoma (PDAC). Methods The German Society for General and Visceral Surgery (DGAV) authorised a task force to define evidence based indications for surgery in patients with PDAC. A systematic literature search in Medline and Cochrane Library databases (1989-2019) was performed. Recommendations were summarised on the basis of the most relevant and recent guidelines and clinical studies and then voted by members of the Working Group on Hepato-Biliary and Pancreatic Diseases (CALGP) in a Delphi procedure. Results Indications for surgery in patients with PDAC should be set by experienced pancreatic surgeons within a tumour board. Decisions should consider the guidelines as well as the individual patient characteristics. Large vessel infiltration, metastatic disease and severe comorbidities are the most common contraindications for surgery. Borderline-resectable, primary resectable oligometastatic and secondary resectable PDAC should be preferably managed at high-volume centres as a part of clinical studies. Centralisation of pancreatic surgery reduces mortality and improves survival. Palliative bypass surgery as well as staging laparoscopy are still indicated in a large proportion of patients with PDAC. Conclusion Irrespective of the recent development of multimodal therapeutic concepts, surgical resection remains the sole chance of long-term cure for patients with PDAC. Due to the significant proportion of patients in advanced stages of the disease, palliative surgery still plays an important role in the complex management of this cancer.
CRIS-Team Scopus Importer:2020-07-24
Keywords: German Society for General and Visceral Surgery; guideline; indications for surgery; pancreatic ductal adenocarcinoma; surgery

Waiting ("Watch and Wait") for complete clinical remission after neoadjuvant radiochemotherapy of rectal carcinomas: influence of salvage-therapy on local tumor control - Hohenberger, Werner (Strahlentherapie und Onkologie, 2014)
EVALuna2:15176

What is Changing in Indications and Treatment of Focal Nodular Hyperplasia of the Liver. Is There Any Place for Surgery? - Perrakis, Aristotelis; Vassos, Nikolaos; Grützmann, Robert; Croner, Roland S. (Annals of Hepatology, 2017)
Focal nodular hyperplasia (FNH) is a common benign liver tumor, which occurs in the vast majority of the cases in young women. FNH represents a polyclonal lesion characterized by local vascular abnormalities and is a truly benign lesion without any potential for malignant transformation. A retrospective single institution analysis of 227 FNH patients, treated from 1990 to 2016 and a review of studies reporting surgical therapy of overall 293 patients with FNH was performed. Indications for resection with a focus on diagnostic workup, patient selection, surgical mode and operative mortality and morbidity have been analysed. Ninety three patients underwent elective hepatectomy and 134 patients observation alone, where median follow-up was 107 months. Postoperative complications were recorded in 14 patients, 92% of patients reported an improvement with respect to their symptoms. Overall among 293 patients underwent surgery in the series, included to this review, there was a morbidity of 13%, where median follow-up was 53 months. Systematic follow-up remains the gold standard in asymptomatic patients with FNH. However elective surgery should be considered in symptomatic patients, in those with marked enlargement and in case of uncertainty of diagnosis. Surgery for FNH is a safe procedure with low morbidity and very good long term results as far as quality of life after surgery is concerned and surely an integral part of the modern management of FNH.
EVALuna2:15281

Zystische Pankreastumoren - Brunner, Maximilian; Grützmann, Robert (Die Chirurgie, 2024)
Pancreatic cystic lesions represent a challenging heterogeneous entity with a potential risk of malignant transformation. The diagnostics include in particular medical history taking with collection of relevant clinical information and high-resolution imaging, preferably using magnetic resonance imaging (MRI) with MR cholangiopancreatography (MRCP) and/or endoscopic ultrasonography. A differentiation between different cystic entities and identification of risk factors are crucial for making appropriate treatment decisions. Only a small proportion of pancreatic cystic neoplasms require surgery. Pancreatic cystic lesions with a relevant risk of malignancy, such as main duct intraductal papillary mucinous neoplasms (IPMN), mucinous cystic neoplasms (MCN), solid pseudopapillary neoplasms (SPN) and general cystic pancreatic lesions with risk factors regardless of the entity, should be resected, whereas an individualized approach is required for branch duct IPMN and serous cystic neoplasms (SCN) and dysontogenetic cysts require no treatment. Parenchyma-sparing and minimally invasive resection techniques should be preferred whenever possible for resecting pancreatic cystic tumors. Approximately 10% of patients develop recurrences over time.
CRIS-Team Scopus Importer:2024-09-06
Keywords: Diagnostics; Intraductal papillary mucinous neoplasm; Pancreatic cystic neoplasm; Pancreatic cysts; Pancreatic surgery; Treatment

β6-integrin serves as a novel serum tumor marker for colorectal carcinoma - Bengs, Susan; Becker, Eugenia; Busenhart, Philipp; Spalinger, Marianne R.; Raselli, Tina; Kasper, Stephanie; Lang, Silvia; Atrott, Kirstin; Mamie, Celine; Vavricka, Stephan R.; von Boehmer, Lotta; Knuth, Alexander; et al. (International Journal of Cancer, 2019)
Colorectal cancer (CRC) is one of the leading causes of cancer-related deaths worldwide and the need for novel biomarkers and therapeutic strategies to improve diagnosis and surveillance is obvious. This study aims to identify β6-integrin (ITGB6) as a novel serum tumor marker for diagnosis, prognosis, and surveillance of CRC. ITGB6 serum levels were validated in retro- and prospective CRC patient cohorts. ITGB6 serum levels were analyzed by ELISA. Using an initial cohort of 60 CRC patients, we found that ITGB6 is present in the serum of CRC, but not in non-CRC control patients. A cut-off of ≥2 ng/mL ITGB6 reveals 100% specificity for the presence of metastatic CRC. In an enlarged study cohort of 269 CRC patients, ITGB6 predicted the onset of metastatic disease and was associated with poor prognosis. Those data were confirmed in an independent, prospective cohort consisting of 40 CRC patients. To investigate whether ITGB6 can also be used for tumor surveillance, serum ITGB6-levels were assessed in 26 CRC patients, pre- and post-surgery, as well as during follow-up visits. After complete tumor resection, ITGB6 serum levels declined completely. During follow-up, a new rise in ITGB6 serum levels indicated tumor recurrence or the onset of new metastasis as confirmed by CT scan. ITGB6 was more accurate for prognosis of advanced CRC and for tumor surveillance as the established marker carcinoembryonic antigen (CEA). Our findings identify ITGB6 as a novel serum marker for diagnosis, prognosis, and surveillance of advanced CRC. This might essentially contribute to an optimized patient care.
CRIS-Team Scopus Importer:2019-06-18
Keywords: colorectal cancer; ITGB6; metastasis; serum tumor marker; surveillance; therapy response

β8 Integrin Mediates Pancreatic Cancer Cell Radiochemoresistance - Jin, Sha; Lee, Wei Chun; Aust, Daniela; Pilarsky, Christian; Cordes, Nils (Molecular Cancer Research, 2019)
Pancreatic ductal adenocarcinoma (PDAC) stroma, composed of extracellular matrix (ECM) proteins, promotes therapy resistance and poor survival rate. Integrin-mediated cell/ECM interactions are well known to control cancer cell survival, proliferation, and therapy resistance. Here, we identified β8 integrin in a high-throughput knockdown screen in three-dimensional (3D), ECM-based cell cultures for novel focal adhesion protein targets as a critical determinant of PDAC cell radiochemoresistance. Intriguingly, β8 integrin localizes with the golgi apparatus perinuclearly in PDAC cells and resection specimen from PDAC patients. Upon radiogenic genotoxic injury, β8 integrin shows a microtubule-dependent perinuclear-to-cytoplasmic shift as well as strong changes in its proteomic interactome regarding the cell functions transport, catalysis, and binding. Parts of this interactome link β8 integrin to autophagy, which is diminished in the absence of β8 integrin. Collectively, our data reveal β8 integrin to critically coregulate PDAC cell radiochemoresistance, intracellular vesicle trafficking, and autophagy upon irradiation. IMPLICATIONS: This study identified β8 integrin as an essential determinant of PDAC cell radiochemosensitivity and as a novel potential cancer target.
CRIS-Team Scopus Importer:2019-10-11